Acute Hyperglycemia Induced by Hyperglycemic Clamp Affects Plasma Amyloid-β in Type 2 Diabetes. - Rolandsson, Olov; Tornevi, Andreas; Steneberg, Pär; Edlund, Helena; Olsson, Tommy; Andreasson, Ulf; Zetterberg, Henrik; Blennow, Kaj (J Alzheimers Dis, 2024)
BACKGROUND: Individuals with type 2 diabetes (T2D) have an increased risk of cognitive symptoms and Alzheimer's disease (AD). Mis-metabolism with aggregation of amyloid-β peptides (Aβ) play a key role in AD pathophysiology. Therefore, human studies on Aβ metabolism and T2D are warranted. OBJECTIVE: The objective of this study was to examine whether acute hyperglycemia affects plasma Aβ1-40 and Aβ1-42 concentrations in individuals with T2D and matched controls. METHODS: Ten participants with T2D and 11 controls (median age, 69 years; range, 66-72 years) underwent hyperglycemic clamp and placebo clamp (saline infusion) in a randomized order, each lasting 4 hours. Aβ1-40, Aβ1-42, and insulin-degrading enzyme (IDE) plasma concentrations were measured in blood samples taken at 0 and 4 hours of each clamp. Linear mixed-effect regression models were used to evaluate the 4-hour changes in Aβ1-40 and Aβ1-42 concentrations, adjusting for body mass index, estimated glomerular filtration rate, and 4-hour change in insulin concentration. RESULTS: At baseline, Aβ1-40 and Aβ1-42 concentrations did not differ between the two groups. During the hyperglycemic clamp, Aβ decreased in the control group, compared to the placebo clamp (Aβ1-40: p = 0.034, Aβ1-42: p = 0.020), IDE increased (p = 0.016) during the hyperglycemic clamp, whereas no significant changes in either Aβ or IDE was noted in the T2D group. CONCLUSIONS: Clamp-induced hyperglycemia was associated with increased IDE levels and enhanced Aβ40 and Aβ42 clearance in controls, but not in individuals with T2D. We hypothesize that insulin-degrading enzyme was inhibited during hyperglycemic conditions in people with T2D.
Keywords: Aged; Amyloid beta-Peptides; Blood Glucose; Diabetes Mellitus, Type 2; Female; Glucose Clamp Technique; Humans; Hyperglycemia; Insulysin; Male; Peptide Fragments

Addressing the Discrepancies Between Animal Models and Human Alzheimer's Disease Pathology: Implications for Translational Research. - Polis, Baruh; Samson, Abraham O (J Alzheimers Dis, 2024)
Animal models, particularly transgenic mice, are extensively used in Alzheimer's disease (AD) research to emulate key disease hallmarks, such as amyloid plaques and neurofibrillary tangles formation. Although these models have contributed to our understanding of AD pathogenesis and can be helpful in testing potential therapeutic interventions, their reliability is dubious. While preclinical studies have shown promise, clinical trials often yield disappointing results, highlighting a notable gap and disparity between animal models and human AD pathology. Existing models frequently overlook early-stage human pathologies and other key AD characteristics, thereby limiting their application in identifying optimal therapeutic interventions. Enhancing model reliability necessitates rigorous study design, comprehensive behavioral evaluations, and biomarker utilization. Overall, a nuanced understanding of each model's neuropathology, its fidelity to human AD, and its limitations is essential for accurate interpretation and successful translation of findings. This article analyzes the discrepancies between animal models and human AD pathology that complicate the translation of findings from preclinical studies to clinical applications. We also delve into AD pathogenesis and attributes to propose a new perspective on this pathology and deliberate over the primary limitations of key experimental models. Additionally, we discuss several fundamental problems that may explain the translational failures and suggest some possible directions for more effective preclinical studies.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Disease Models, Animal; Humans; Mice; Mice, Transgenic; Neurofibrillary Tangles; Reproducibility of Results; Translational Research, Biomedical

Apoptosis, Autophagy, and Mitophagy Genes in the CA3 Area in an Ischemic Model of Alzheimer's Disease with 2-Year Survival. - Pluta, Ryszard; Bogucka-Kocka, Anna; Bogucki, Jacek; Kocki, Janusz; Czuczwar, Stanisław J (J Alzheimers Dis, 2024)
BACKGROUND: Currently, no evidence exists on the expression of apoptosis (CASP3), autophagy (BECN1), and mitophagy (BNIP3) genes in the CA3 area after ischemia with long-term survival. OBJECTIVE: The goal of the paper was to study changes in above genes expression in CA3 area after ischemia in the period of 6-24 months. METHODS: In this study, using quantitative RT-PCR, we present the expression of genes associated with neuronal death in a rat ischemic model of Alzheimer's disease. RESULTS: First time, we demonstrated overexpression of the CASP3 gene in CA3 area after ischemia with survival ranging from 0.5 to 2 years. Overexpression of the CASP3 gene was accompanied by a decrease in the activity level of the BECN1 and BNIP3 genes over a period of 0.5 year. Then, during 1-2 years, BNIP3 gene expression increased significantly and coincided with an increase in CASP3 gene expression. However, BECN1 gene expression was variable, increased significantly at 1 and 2 years and was below control values 1.5 years post-ischemia. CONCLUSIONS: Our observations suggest that ischemia with long-term survival induces neuronal death in CA3 through activation of caspase 3 in cooperation with the pro-apoptotic gene BNIP3. This study also suggests that the BNIP3 gene regulates caspase-independent pyramidal neuronal death post-ischemia. Thus, caspase-dependent and -independent death of neuronal cells occur post-ischemia in the CA3 area. Our data suggest new role of the BNIP3 gene in the regulation of post-ischemic neuronal death in CA3. This suggests the involvement of the BNIP3 together with the CASP3 in the CA3 in neuronal death post-ischemia.
Keywords: Alzheimer Disease; Animals; Apoptosis; Apoptosis Regulatory Proteins; Autophagy; Beclin-1; Brain Ischemia; CA3 Region, Hippocampal; Caspase 3; Disease Models, Animal; Male; Membrane Proteins; Mitochondrial Proteins; Mitophagy; Rats; Rats, Wistar

The Association Between Distinct Delusional Ideations and Depressive Symptoms in Alzheimer's Disease: A Re-Analysis of CATIE-AD. - Nagata, Tomoyuki; Nakajima, Shinichiro; Kito, Shinsuke; Shinagawa, Shunichiro (J Alzheimers Dis, 2024)
BACKGROUND: Delusional ideations, one of neuropsychiatric symptoms (NPSs), are frequently shown in the long-term progression of Alzheimer's disease (AD), and comorbid with other NPSs including depression or agitation. Despite various types of delusional ideations, the comorbidity between each delusional ideation and depressive symptoms has not been discussed. OBJECTIVE: The present cross-sectional study is aimed at testing the hypothetical mechanism of comorbid pattern in AD. METHODS: Among 421 patients with AD, we analyzed the dataset of the Clinical Antipsychotic Trials of Intervention Effectiveness-Alzheimer's Disease to compare age, sex, racial type, Mini-Mental State Examination (MMSE) scores, and Neuropsychiatric Inventory (NPI) depression score of between the presence and absence of each delusional ideation (delusion of persecution, theft, jealousy, abandonment, phantom boarder, Capgras syndrome, misidentification of place, or television sign). Next, with the stratification based on MMSE score of < or > = 15 points, we further explored association between delusional ideation and depressive symptom that was found significances in the primary analysis. RESULTS: Among eight subtypes of delusional ideations, depression score was higher in those with persecution delusion or Capgras syndrome. Moreover, the Capgras syndrome was associated with presence of depression in severer global cognitive impairment status. CONCLUSIONS: As comorbid NPSs of delusional ideation in AD, depressive severity is associated with specific delusional subtype: persecution delusion and Capgras syndrome. Capgras syndrome may be attributable to severe cognitive impairment in addition to depressive symptom. The consideration of pathogenetic differences in the distinct delusional ideations may be helpful for clinicians to select the treatment strategy.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cross-Sectional Studies; Delusions; Depression; Female; Humans; Male; Mental Status and Dementia Tests

Association of Statin Use with Dementia Risk Among Older Adults in Japan: A Nested Case-Control Study Using the LIFE Study. - Ge, Sanyu; Kitamura, Tetsuhisa; Zha, Ling; Komatsu, Masayo; Komukai, Sho; Murata, Fumiko; Maeda, Megumi; Gon, Yasufumi; Kimura, Yasuyoshi; Kiyohara, Kosuke; Sobue, Tomotaka; Fukuda, Haruhisa (J Alzheimers Dis, 2024)
BACKGROUND: Previous studies have shown a possible association between statin use and a decreased risk of dementia, but the association has not been sufficiently established, especially in the super-aging society of Japan. OBJECTIVE: This study aimed to determine the association between statin use and the risk of dementia among Japanese participants aged> =65 years old. METHODS: Data from the Longevity Improvement and Fair Evidence (LIFE) Study were utilized, including medical and long-term care (LTC) claim data from 17 municipalities between April 2014 and December 2020. A nested case-control study was conducted with one case matched to five controls based on age, sex, municipality, and year of cohort entry. We used a conditional logistic regression model to calculate the odds ratios (ORs) and 95% confidence intervals (95% CIs). RESULTS: This study included 57,302 cases and 283,525 controls, with 59.7% of the participants being woman. After adjusting for potential confounders, statin use was associated with a lower risk of dementia (OR, 0.70; 95% CI: 0.68-0.73) and Alzheimer's disease (OR: 0.66; 95% CI: 0.63-0.69). Compared with non-users, the ORs of dementia were as follows: 1.42 (1.34-1.50) for 1-30 total standardized daily dose (TSDD), 0.91 (0.85-0.98) for 31-90 TSDD, 0.63 (0.58-0.69) for 91-180 TSDD, and 0.33 (0.31-0.36) for >180 TSDD in dose-analysis. CONCLUSIONS: Statin use is associated with a reduced risk of dementia and Alzheimer's disease among older Japanese adults. A low cumulative statin dose is associated with an increased risk of dementia, whereas a high cumulative statin dose is a protective factor against dementia.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Dementia; Female; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Japan; Male; Risk Factors

Association of Vitamin D Levels with Risk of Cognitive Impairment and Dementia: A Systematic Review and Meta-Analysis of Prospective Studies. - Zhang, Xiao-Xue; Wang, He-Ran; Hu, Ya-Zhuo; Sun, Hong-Mei; Feng, Yu-Xin; Jia, Jian-Jun (J Alzheimers Dis, 2024)
BACKGROUND: Emerging evidence suggests the potential relationship between vitamin D deficiency and risk of cognitive impairment or dementia. To what extent the excess risk of dementia conferred by vitamin D deficiency is less clear. OBJECTIVE: We summarized the current evidence from several aspects and further quantified these associations. METHODS: We collected relevant prospective cohort studies by searching PubMed, Embase and Cochrane up to July 2023. The pooled relative risks (RR) were evaluated by random-effects models. Dose-response analyses were conducted by the method of two-stage generalized least squares regression. RESULTS: Of 9,267 identified literatures, 23 were eligible for inclusion in the meta-analyses, among which 9 and 4 literatures were included in the dose-response analyses for the risk of dementia and Alzheimer's disease (AD). Vitamin D deficiency exhibited a 1.42 times risk for dementia (95% confidence interval (CI) = 1.21-1.65) and a 1.57-fold excess risk for AD (95% CI = 1.15-2.14). And vitamin D deficiency was associated with 34% elevated risk with cognitive impairment (95% CI = 1.19-1.52). Additionally, vitamin D was non-linearly related to the risk of dementia (pnonlinearity = 0.0000) and AD (pnonlinearity = 0.0042). The approximate 77.5-100 nmol/L 25-hydroxyvitamin D [25(OH)D] was optimal for reducing dementia risk. And the AD risk seemed to be decreased when the 25(OH)D level >40.1 nmol/L. CONCLUSIONS: Vitamin D deficiency was a risk factor for dementia, AD, and cognitive impairment. The nonlinear relationships may further provide the optimum dose of 25(OH)D for dementia prevention.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Dementia; Humans; Prospective Studies; Risk Factors; Vitamin D; Vitamin D Deficiency

A Brief History of the Progress in Our Understanding of Genetics and Lifestyle, Especially Diet, in the Risk of Alzheimer's Disease. - Grant, William B (J Alzheimers Dis, 2024)
The two major determining factors for Alzheimer's disease (AD) are genetics and lifestyle. Alleles of the apolipoprotein E (APOE) gene play important roles in the development of late-onset AD, with APOEɛ4 increasing risk, APOEɛ3 being neutral, and APOEɛ2 reducing risk. Several modifiable lifestyle factors have been studied in terms of how they can modify the risk of AD. Among these factors are dietary pattern, nutritional supplements such as omega-3 fatty acids, and B vitamins, physical exercise, and obesity, and vitamin D. The Western diet increases risk of AD, while dietary patterns such as the Mediterranean and vegetarian/vegan diets reduce risk. Foods associated with reduced risk include coffee, fruits and vegetables, whole grains and legumes, and fish, while meat and ultraprocessed foods are associated with increased risk, especially when they lead to obesity. In multi-country ecological studies, the amount of meat in the national diet has the highest correlation with risk of AD. The history of research regarding dietary patterns on risk of AD is emphasized in this review. The risk of AD can be modified starting at least by mid-life. People with greater genetic risk for AD would benefit more by choosing lifestyle factors to reduce and/or delay incidence of AD.
Keywords: Alzheimer Disease; Apolipoproteins E; Diet; Genetic Predisposition to Disease; Humans; Life Style; Risk Factors

Cerebrovascular miRNAs Track Early Development of Alzheimer's Disease and Target Molecular Markers of Angiogenesis and Blood Flow Regulation. - Chum, Phoebe P; Bishara, Mary A; Solis, Summer R; Behringer, Erik J (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is associated with impaired cerebral circulation which underscores diminished delivery of blood oxygen and nutrients to and throughout the brain. In the 3xTg-AD mouse model, we have recently found that > 10 cerebrovascular miRNAs pertaining to vascular permeability, angiogenesis, and inflammation (e.g., let-7d, miR-99a, miR-132, miR-133a, miR-151-5p, and miR-181a) track early development of AD. Further, endothelial-specific miRNAs (miR-126-3p, miR-23a/b, miR-27a) alter with onset of overall AD pathology relative to stability of smooth muscle/pericyte-specific miRNAs (miR-143, miR-145). OBJECTIVE: We tested the hypothesis that cerebrovascular miRNAs indicating AD pathology share mRNA targets that regulate key endothelial cell functions such as angiogenesis, vascular permeability, and blood flow regulation. METHODS: As detected by NanoString nCounter miRNA Expression panel for 3xTg-AD mice, 61 cerebrovascular miRNAs and respective mRNA targets were examined using Ingenuity Pathway Analysis for canonical Cardiovascular (Cardio) and Nervous System (Neuro) Signaling. RESULTS: The number of targets regulated per miRNA were 21±2 and 33±3 for the Cardio and Neuro pathways respectively, whereby 14±2 targets overlap among pathways. Endothelial miRNAs primarily target members of the PDE, PDGF, SMAD, and VEGF families. Individual candidates regulated by≥4 miRNAs that best mark AD pathology presence in 3xTg-AD mice include CFL2, GRIN2B, PDGFB, SLC6A1, SMAD3, SYT3, and TNFRSF11B. CONCLUSION: miRNAs selective for regulation of endothelial function and respective downstream mRNA targets support a molecular basis for dysregulated cerebral blood flow regulation coupled with enhanced cell growth, proliferation, and inflammation.
Keywords: Alzheimer Disease; Angiogenesis; Animals; Biomarkers; Brain; Cerebrovascular Circulation; Disease Models, Animal; Endothelial Cells; Humans; Mice; Mice, Transgenic; MicroRNAs; Neovascularization, Pathologic

Creating an Unprotected Class: Addressing Legal Risks in the Era of Biologically-Defined Alzheimer's Disease. - Vaishnav, Neil; Gonzalez, Rosa; Karunungan, Krystal; Tyler, Ana; Zheng, William; Arias, Jalayne J (J Alzheimers Dis, 2024)
BACKGROUND: Documentation of preclinical biomarker tests for Alzheimer's disease (AD) in the medical record may expose patients to employment and insurance discrimination risks. There is a gap in research describing clinicians' approaches to documenting biomarker results. OBJECTIVE: To evaluate discrimination risks faced by patients undergoing biomarker testing for AD through a qualitative analysis of clinician documentation practices. METHODS: Semi-structured interviews using hypothetical patient scenarios. The qualitative analysis focused on interviewees' responses related to documentation and disclosure of results. RESULTS: We collected and analyzed 17 interviews with dementia experts; and identified three approaches to documenting biomarkers as: an association with active AD, noninformative, and an increased susceptibility for AD. Those who associated biomarkers with active disease were more likely to favor disclosure to employers and insurers, which could increase discrimination risks. CONCLUSIONS: This study demonstrates the variety of documentation and disclosure practices likely to emerge for preclinical AD biomarker tests and highlights a need for guidelines in this area.
Keywords: Alzheimer Disease; Biomarkers; Disclosure; Humans

Current Status and Challenges in Dementia Care in the Philippines: A Scoping Review. - Anlacan, Veeda Michelle M; Lanuza, Pamela Danielle T; Sanchez, Anna Anjelica R; Jamora, Roland Dominic G (J Alzheimers Dis, 2024)
BACKGROUND: Dementia prevalence is increasing in low- and middle-income countries such as the Philippines. OBJECTIVE: This study aimed to give an overview of dementia care in the Philippines and to identify gaps in terms of local epidemiology, research, financial coverage, diagnostics, pharmacotherapy, manpower, and caregiver support. METHODS: This scoping review was conducted using the Preferred Reporting Items for Systematic reviews and Meta-analysis guidelines extension for scoping reviews. Six international and two local databases, and government and non-government websites were searched. Data published in the English or Filipino language on dementia epidemiology, research, diagnostics, management, manpower, and training were extracted from the earliest indexed record until June 2022. RESULTS: The prevalence of dementia in the Philippines is high and research output on all aspects of dementia is low. Cost is a major barrier as health care coverage is limited, with reliance mainly on out-of-pocket payments, leading to challenges in the proper diagnosis and treatment of dementia. There is a low specialist-to-population ratio, with shortages beyond manpower and training. CONCLUSIONS: Gaps in dementia care include limited published local data, high healthcare costs, inadequate health financing, and limited manpower.
Keywords: Dementia; Health Care Costs; Health Services; Humans; Philippines; Prevalence

Dementia Ideal Care: Ecosystem Map of Best Practices and Care Pathways Enhanced by Technology and Community. - Dombrowski, Wen; Mims, Adrienne; Kremer, Ian; Cano Desandes, Pedro; Rodrigo-Herrero, Silvia; Epps, Fayron; Snow, Teepa; Gutierrez, Myrna; Nasta, Anil; Epperly, Mikele Bunce; Manaloto, Katrina; Hansen, Jennie Chin (J Alzheimers Dis, 2024)
BACKGROUND: Globally, much work has been done by nonprofit, private, and academic groups to develop best practices for the care of people living with dementia (PLWD), including Alzheimer's disease. However, these best practices reside in disparate repositories and tend to focus on one phase of the patient journey or one relevant group. OBJECTIVE: To fill this gap, we developed a Dementia Ideal Care Map that everyone in the dementia ecosystem can use as an actionable tool for awareness, policy development, funding, research, training, service delivery, and technology design. The intended audience includes (and not limited to) policymakers, academia, industry, technology developers, health system leaders, clinicians, social service providers, patient advocates, PLWD, their families, and communities at large. METHODS: A search was conducted for published dementia care best practices and quality measures, which were then summarized in a visual diagram. The draft diagram was analyzed to identify barriers to ideal care. Then, additional processes, services, technologies, and quality measures to overcome those challenges were brainstormed. Feedback was then obtained from experts. RESULTS: The Dementia Ideal Care Map summarizes the ecosystem of over 200 best practices, nearly 100 technology enablers, other infrastructure, and enhanced care pathways in one comprehensive diagram. It includes psychosocial interventions, care partner support, community-based organizations; awareness, risk reduction; initial detection, diagnosis, ongoing medical care; governments, payers, health systems, businesses, data, research, and training. CONCLUSIONS: Dementia Ideal Care Map is a practical tool for planning and coordinating dementia care. This visualized ecosystem approach can be applied to other conditions.
Keywords: Delivery of Health Care; Dementia; Humans; Practice Guidelines as Topic

Effect of Metformin on Plasma and Cerebrospinal Fluid Biomarkers in Non-Diabetic Older Adults with Mild Cognitive Impairment Related to Alzheimer's Disease. - Weinberg, Marc S; He, Yingnan; Kivisäkk, Pia; Arnold, Steven E; Das, Sudeshna (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is a complicated condition involving multiple metabolic and immunologic pathophysiological processes that can occur with the hallmark pathologies of amyloid-β, tau, and neurodegeneration. Metformin, an anti-diabetes drug, targets several of these disease processes in in vitro and animal studies. However, the effects of metformin on human cerebrospinal fluid (CSF) and plasma proteins as potential biomarkers of treatment remain unexplored. OBJECTIVE: Using proteomics data from a metformin clinical trial, identify the impact of metformin on plasma and CSF proteins. METHODS: We analyzed plasma and CSF proteomics data collected previously (ClinicalTrials.gov identifier: NCT01965756, conducted between 2013 and 2015), and conduced bioinformatics analyses to compare the plasma and CSF protein levels after 8 weeks of metformin or placebo use to their baseline levels in 20 non-diabetic patients with mild cognitive impairment (MCI) and positive AD biomarkers participants. RESULTS: 50 proteins were significantly (unadjusted p < 0.05) altered in plasma and 26 in CSF after 8 weeks of metformin use, with 7 proteins in common (AZU1, CASP-3, CCL11, CCL20, IL32, PRTN3, and REG1A). The correlation between changes in plasma and CSF levels of these 7 proteins after metformin use relative to baseline levels was high (r = 0.98). The proteins also demonstrated temporal stability. CONCLUSIONS: Our pilot study is the first to investigate the effect of metformin on plasma and CSF proteins in non-diabetic patients with MCI and positive AD biomarkers and identifies several candidate plasma biomarkers for future clinical trials after confirmatory studies.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Cognitive Dysfunction; Double-Blind Method; Female; Humans; Hypoglycemic Agents; Male; Metformin; Middle Aged; Proteomics

Elevated Risk of Dementia Diagnosis in Older Adults with Low Frequencies and Durations of Social Conversation. - Shimada, Hiroyuki; Doi, Takehiko; Tsutsumimoto, Kota; Makino, Keitaro; Harada, Kenji; Tomida, Kouki; Arai, Hidenori (J Alzheimers Dis, 2024)
BACKGROUND: Social networks and social participation have protective effects on cognitive function maintenance and Alzheimer's disease and general dementia development. OBJECTIVE: We aimed to investigate the association between conversations and dementia incidence in older adults. METHODS: This longitudinal prospective cohort study used population data from the National Center for Geriatric and Gerontology-Study of Geriatric Syndromes (NCGG-SGS) from September 2015 to February 2017. The database included 4,167 individuals in Japan aged ≥60 years who were generally healthy and without major cognitive impairment. Participants were classified into two groups according to six daily conversation measures at baseline. The conversation index was calculated as a composite score for these measures. Participants were tracked monthly over 60 months for new-onset dementia. RESULTS: Data from 2,531 participants were analyzed (72.7±6.7 years; range: 60-96 years). Dementia incidence per 1,000 person-years was 15.7 (95% confidence interval, 13.6-18.1). The Youden index determined the cut-off point for dementia incidence, with a conversation index of 16/17 points. The low conversation group included more participants with new-onset dementia. Cox proportional hazards regression crude models showed remarkable relationships between dementia onset and specific conversation measurements, including conversation index. According to the Cox regression adjusted model, the cut-off point of the conversation index showed only a remarkable relationship with dementia onset. CONCLUSIONS: Dementia risk was extensively associated with low daily conversation statuses. The assessment of conversational factors may be useful as a risk indicator for the development of Alzheimer's disease and general dementia.
Keywords: Aged; Alzheimer Disease; Cognitive Dysfunction; Dementia; Geriatrics; Humans; Prospective Studies

Enhancing Rab7 Activity by Inhibiting TBC1D5 Expression Improves Mitophagy in Alzheimer's Disease Models. - Liang, Xiao; Wang, Yangyang; Li, Siyu; Fan, Jianing; Zhou, Fanlin; Li, Xiaoju; Li, Shijie; Li, Yu (J Alzheimers Dis, 2024)
BACKGROUND: Mitochondrial dysfunction exists in Alzheimer's disease (AD) brain, and damaged mitochondria need to be removed by mitophagy. Small GTPase Rab7 regulates the fusion of mitochondria and lysosome, while TBC1D5 inhibits Rab7 activation. However, it is not clear whether the regulation of Rab7 activity by TBC1D5 can improve mitophagy and inhibit AD progression. OBJECTIVE: To investigate the role of TBC1D5 in mitophagy and its regulatory mechanism for Rab7, and whether activation of mitophagy can inhibit the progression of AD. METHODS: Mitophagy was determined by western blot and immunofluorescence. The morphology and quantity of mitochondria were tracked by TEM. pCMV-Mito-AT1.03 was employed to detect the cellular ATP. Amyloid-β secreted by AD cells was detected by ELISA. Co-immunoprecipitation was used to investigate the binding partner of the target protein. Golgi-cox staining was applied to observe neuronal morphology of mice. The Morris water maze test and Y-maze were performed to assess spatial learning and memory, and the open field test was measured to evaluate motor function and anxiety-like phenotype of experimental animals. RESULTS: Mitochondrial morphology was impaired in AD models, and TBC1D5 was highly expressed. Knocking down TBC1D5 increased the expression of active Rab7, promoted the fusion of lysosome and autophagosome, thus improving mitophagy, and improved the morphology of hippocampal neurons and the impaired behavior in AD mice. CONCLUSIONS: Knocking down TBC1D5 increased Rab7 activity and promoted the fusion of autophagosome and lysosome. Our study provided insights into the mechanisms that bring new possibilities for AD therapy targeting mitophagy.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Disease Models, Animal; GTPase-Activating Proteins; Humans; Male; Mice; Mice, Transgenic; Mitochondria; Mitophagy; Neurons; rab GTP-Binding Proteins; rab7 GTP-Binding Proteins

Equilibrium of Dietary Patterns Between Alzheimer's Disease Patients and Healthy People: A Comprehensive Analysis Using Multiple Factor Analysis and Classification Modeling. - Ahmed, Tahera; Zhang, Ping; Kumar, Kuldeep (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is a particular type of dementia that currently lacks a definitive treatment and cure. It is possible to reduce the risk of developing AD and mitigate its severity through modifications to one's lifestyle, regular diet, and alcohol-drinking habits. OBJECTIVE: The objective of this study is to examine the daily dietary patterns of individuals with AD compared to healthy controls, with a focus on nutritional balance and its impact on AD. METHODS: This study incorporated multiple-factor analysis (MFA) to evaluate dietary patterns and employed Random Forest (RF) classifier and Sparse Logistic Regression (SLR) for Variable Importance analysis to identify food items significantly associated with AD. RESULTS: MFA revealed trends in the data and a strong correlation (Lg = 0.92, RV = 0.65) between the daily consumption of processed food and meat items in AD patients. In contrast, no significant relationship was found for any daily consumed food categories within the healthy control (HC) group. Food items such as meat pie, hamburger, ham, sausages, beef, capsicum, and cabbage were identified as important variables associated with AD in RF and SLR analyses. CONCLUSIONS: The findings from MFA indicated that the diversity or equilibrium of daily diet might play a potential role in AD development. RF and SLR classifications exhibit among the processed foods, especially deli meats and food made with meat items, are associated with AD.
Keywords: Alzheimer Disease; Diet; Factor Analysis, Statistical; Humans; Vegetables

The Etiology of Rapidly Progressive Dementia: A 3-Year Retrospective Study in a Tertiary Hospital in China. - Shi, Qin; Liu, Wei-Shi; Liu, Fang; Zeng, Yi-Xuan; Chen, Shu-Fen; Chen, Ke-Liang; Yu, Jin-Tai; Huang, Yu-Yuan (J Alzheimers Dis, 2024)
BACKGROUND: Rapidly progressive dementia (RPD), characterized by a rapid cognitive decline leading to dementia, comprises a diverse range of disorders. Despite advancements in diagnosis and treatment, research on RPD primarily focuses on Western populations. OBJECTIVE: This study aims to explore the etiology and demographics of RPD in Chinese patients. METHODS: We retrospectively analyzed 323 RPD inpatients at Huashan Hospital from May 2019 to March 2023. Data on sociodemographic factors, epidemiology, clinical presentation, and etiology were collected and analyzed. RESULTS: The median onset age of RPD patients was 60.7 years. Two-thirds received a diagnosis within 6 months of symptom onset. Memory impairment was the most common initial symptom, followed by behavioral changes. Neurodegenerative diseases accounted for 47.4% of cases, with central nervous system inflammatory diseases at 30.96%. Autoimmune encephalitis was the leading cause (16.7%), followed by Alzheimer's disease (16.1%), neurosyphilis (11.8%), and Creutzfeldt-Jakob disease (9.0%). Alzheimer's disease, Creutzfeldt-Jakob disease, and frontotemporal dementia were the primary neurodegenerative causes, while autoimmune encephalitis, neurosyphilis, and vascular cognitive impairment were the main non-neurodegenerative causes. CONCLUSIONS: The etiology of RPD in Chinese patients is complex, with neurodegenerative and non-neurodegenerative diseases equally prevalent. Recognizing treatable conditions like autoimmune encephalitis and neurosyphilis requires careful consideration and differentiation.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; China; Cognitive Dysfunction; Creutzfeldt-Jakob Syndrome; Dementia; Disease Progression; Encephalitis; Female; Frontotemporal Dementia; Humans; Male; Middle Aged; Neurodegenerative Diseases; Neurosyphilis; Retrospective Studies; Tertiary Care Centers

Functional Connectivity Favors Aberrant Visual Network c-Fos Expression Accompanied by Cortical Synapse Loss in a Mouse Model of Alzheimer's Disease. - L'Esperance, Oliver J; McGhee, Joshua; Davidson, Garett; Niraula, Suraj; Smith, Adam S; Sosunov, Alexandre A; Yan, Shirley ShiDu; Subramanian, Jaichandar (J Alzheimers Dis, 2024)
BACKGROUND: While Alzheimer's disease (AD) has been extensively studied with a focus on cognitive networks, visual network dysfunction has received less attention despite compelling evidence of its significance in AD patients and mouse models. We recently reported c-Fos and synaptic dysregulation in the primary visual cortex of a pre-amyloid plaque AD-model. OBJECTIVE: We test whether c-Fos expression and presynaptic density/dynamics differ in cortical and subcortical visual areas in an AD-model. We also examine whether aberrant c-Fos expression is inherited through functional connectivity and shaped by light experience. METHODS: c-Fos+ cell density, functional connectivity, and their experience-dependent modulation were assessed for visual and whole-brain networks in both sexes of 4-6-month-old J20 (AD-model) and wildtype (WT) mice. Cortical and subcortical differences in presynaptic vulnerability in the AD-model were compared using ex vivo and in vivo imaging. RESULTS: Visual cortical, but not subcortical, networks show aberrant c-Fos expression and impaired experience-dependent modulation. The average functional connectivity of a brain region in WT mice significantly predicts aberrant c-Fos expression, which correlates with impaired experience-dependent modulation in the AD-model. We observed a subtle yet selective weakening of excitatory visual cortical synapses. The size distribution of cortical boutons in the AD-model is downscaled relative to those in WT mice, suggesting a synaptic scaling-like adaptation of bouton size. CONCLUSIONS: Visual network structural and functional disruptions are biased toward cortical regions in pre-plaque J20 mice, and the cellular and synaptic dysregulation in the AD-model represents a maladaptive modification of the baseline physiology seen in WT conditions.
Keywords: Alzheimer Disease; Animals; Disease Models, Animal; Female; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Proto-Oncogene Proteins c-fos; Synapses; Visual Cortex

High-Fat Diets in Animal Models of Alzheimer's Disease: How Can Eating Too Much Fat Increase Alzheimer's Disease Risk? - Valentin-Escalera, Josue; Leclerc, Manon; Calon, Frederic (J Alzheimers Dis, 2024)
High dietary intake of saturated fatty acids is a suspected risk factor for neurodegenerative diseases, including Alzheimer's disease (AD). To decipher the causal link behind these associations, high-fat diets (HFD) have been repeatedly investigated in animal models. Preclinical studies allow full control over dietary composition, avoiding ethical concerns in clinical trials. The goal of the present article is to provide a narrative review of reports on HFD in animal models of AD. Eligibility criteria included mouse models of AD fed a HFD defined as > 35% of fat/weight and western diets containing > 1% cholesterol or > 15% sugar. MEDLINE and Embase databases were searched from 1946 to August 2022, and 32 preclinical studies were included in the review. HFD-induced obesity and metabolic disturbances such as insulin resistance and glucose intolerance have been replicated in most studies, but with methodological variability. Most studies have found an aggravating effect of HFD on brain Aβ pathology, whereas tau pathology has been much less studied, and results are more equivocal. While most reports show HFD-induced impairment on cognitive behavior, confounding factors may blur their interpretation. In summary, despite conflicting results, exposing rodents to diets highly enriched in saturated fat induces not only metabolic defects, but also cognitive impairment often accompanied by aggravated neuropathological markers, most notably Aβ burden. Although there are important variations between methods, particularly the lack of diet characterization, these studies collectively suggest that excessive intake of saturated fat should be avoided in order to lower the incidence of AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Diet, High-Fat; Disease Models, Animal; Fatty Acids; Mice; Mice, Transgenic

Long-Term Safety of Gantenerumab in Participants with Alzheimer's Disease: A Phase III, Double-Blind, and Open-Label Extension Study (Marguerite RoAD). - Neve, Anuja; Das, Bibha; Wojtowicz, Jakub; Huang, Zhiyue; Bullain, Szofia; Watkin, Michelle; Lott, Dominik; Bittner, Tobias; Delmar, Paul; Klein, Gregory; Hofmann, Carsten; Kerchner, Geoffrey A; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Gantenerumab is an anti-amyloid-β immunoglobulin G1 monoclonal antibody for subcutaneous (SC) administration. The efficacy and safety of low-dose (105 mg or 225 mg) gantenerumab were investigated in Marguerite RoAD (MR; NCT02051608), a Phase III, double-blind (DB), placebo-controlled study in participants with mild Alzheimer's disease (AD) dementia. Following a preplanned futility analysis of the SCarlet RoAD study (NCT01224106), MR was converted into an open-label extension (OLE). OBJECTIVE: The DB study aimed to assess the efficacy of gantenerumab compared with placebo from baseline to Week 104 in participants with mild AD dementia. Following conversion to an OLE, this objective became exploratory, as the OLE assessed the long-term safety and tolerability of SC gantenerumab at doses of up to 1,200 mg every 4 weeks (Q4W) in OLE participants. METHODS: Eligible DB study participants were offered the opportunity to receive gantenerumab up-titrated to 1,200 mg Q4W. Safety and tolerability were assessed using magnetic resonance imaging (MRI), physical and neurologic examinations, and adverse event monitoring. RESULTS: Overall, 225 participants were rolled over from the DB part of MR and received ≥1 gantenerumab dose in the OLE. The median treatment duration was 123 weeks. Fifty-nine (26.2%) and 41 (18.2%) participants had amyloid-related imaging abnormality (ARIA)-edema and ARIA-hemorrhage MRI findings, respectively. ARIA findings were manageable with MRI monitoring and dose intervention; most were asymptomatic. There were no unexpected safety findings. CONCLUSIONS: SC gantenerumab at doses of up to 1,200 mg Q4W were well tolerated in participants with mild AD dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Antibodies, Monoclonal, Humanized; Double-Blind Method; Female; Humans; Male; Middle Aged; Treatment Outcome

A Metabolomics Analysis of a Novel Phenotype of Older Adults at Higher Risk of Dementia. - Sultana, Munira; Camicioli, Richard; Dixon, Roger A; Whitehead, Shawn; Pieruccini-Faria, Frederico; Petrotchenko, Evgeniy; Speechley, Mark; Borchers, Christoph H; Montero-Odasso, Manuel (J Alzheimers Dis, 2024)
BACKGROUND: Older adults presenting with dual-decline in cognition and walking speed face a 6-fold higher risk for dementia compared with those showing no decline. We hypothesized that the metabolomics profile of dual-decliners would be unique even before they show signs of decline in cognition and gait speed. OBJECTIVE: The objective of this study was to determine if plasma metabolomics signatures can discriminate dual-decliners from no decliners, purely cognitive decliners, and purely motor decliners prior to decline. METHODS: A retrospective cross-sectional study using baseline plasma for untargeted metabolomics analyses to investigate early signals of later dual-decline status in study participants (n = 76) with convenient sampling. Dual-decline was operationalized as decline in gait speed (>10 cm/s) and cognition (>2 points decline in Montreal Cognitive Assessment score) on at least two consecutive 6-monthly assessments. The participants' decliner status was evaluated 3 years after the blood sample was collected. Pair-wise comparison of detected compounds was completed using principal components and hierarchical clustering analyses. RESULTS: Analyses did not detect any cluster separation in untargeted metabolomes across baseline groups. However, follow-up analyses of specific molecules detected 4 compounds (17-Hydroxy-12-(hydroxymethyl)-10-oxo-8 oxapentacyclomethyl hexopyranoside, Fleroxacin, Oleic acid, and 5xi-11,12-Dihydroxyabieta-8(14),9(11),12-trien-20-oic acid) were at significantly higher concentration among the dual-decliners compared to non-decliners. The pure cognitive decliner group had significantly lower concentration of six compounds (1,3-nonanediol acetate, 4-(2-carboxyethyl)-2-methoxyphenyl beta-D-glucopyranosiduronic acid, oleic acid, 2E-3-[4-(sulfo-oxy)phenyl] acrylic acid, palmitelaidic acid, and myristoleic acid) compared to the non-decliner group. CONCLUSIONS: The unique metabolomics profile of dual-decliners warrants follow-up metabolomics analysis. Results may point to modifiable pathways.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Cross-Sectional Studies; Dementia; Female; Humans; Male; Metabolomics; Phenotype; Retrospective Studies

Neural Computation-Based Methods for the Early Diagnosis and Prognosis of Alzheimer's Disease Not Using Neuroimaging Biomarkers: A Systematic Review. - Cabrera-León, Ylermi; Báez, Patricio García; Fernández-López, Pablo; Suárez-Araujo, Carmen Paz (J Alzheimers Dis, 2024)
BACKGROUND: The growing number of older adults in recent decades has led to more prevalent geriatric diseases, such as strokes and dementia. Therefore, Alzheimer's disease (AD), as the most common type of dementia, has become more frequent too. BACKGROUND: Objective: The goals of this work are to present state-of-the-art studies focused on the automatic diagnosis and prognosis of AD and its early stages, mainly mild cognitive impairment, and predicting how the research on this topic may change in the future. METHODS: Articles found in the existing literature needed to fulfill several selection criteria. Among others, their classification methods were based on artificial neural networks (ANNs), including deep learning, and data not from brain signals or neuroimaging techniques were used. Considering our selection criteria, 42 articles published in the last decade were finally selected. RESULTS: The most medically significant results are shown. Similar quantities of articles based on shallow and deep ANNs were found. Recurrent neural networks and transformers were common with speech or in longitudinal studies. Convolutional neural networks (CNNs) were popular with gait or combined with others in modular approaches. Above one third of the cross-sectional studies utilized multimodal data. Non-public datasets were frequently used in cross-sectional studies, whereas the opposite in longitudinal ones. The most popular databases were indicated, which will be helpful for future researchers in this field. CONCLUSIONS: The introduction of CNNs in the last decade and their superb results with neuroimaging data did not negatively affect the usage of other modalities. In fact, new ones emerged.
Keywords: Alzheimer Disease; Biomarkers; Cognitive Dysfunction; Deep Learning; Early Diagnosis; Humans; Neural Networks, Computer; Neuroimaging; Prognosis

O-GlcNAcylation and Its Roles in Neurodegenerative Diseases. - Du, Pengyang; Zhang, Xiaomin; Lian, Xia; Holscher, Christian; Xue, Guofang (J Alzheimers Dis, 2024)
As a non-classical post-translational modification, O-linked β-N-acetylglucosamine (O-GlcNAc) modification (O-GlcNAcylation) is widely found in human organ systems, particularly in our brains, and is indispensable for healthy cell biology. With the increasing age of the global population, the incidence of neurodegenerative diseases is increasing, too. The common characteristic of these disorders is the aggregation of abnormal proteins in the brain. Current research has found that O-GlcNAcylation dysregulation is involved in misfolding or aggregation of these abnormal proteins to mediate disease progression, but the specific mechanism has not been defined. This paper reviews recent studies on O-GlcNAcylation's roles in several neurodegenerative disorders such as Alzheimer's disease, Parkinson's disease, amyotrophic lateral sclerosis, Huntington's disease, Machado-Joseph's disease, and giant axonal neuropathy, and shows that O-GlcNAcylation, as glucose metabolism sensor, mediating synaptic function, participating in oxidative stress response and signaling pathway conduction, directly or indirectly regulates characteristic pathological protein toxicity and affects disease progression. The existing results suggest that targeting O-GlcNAcylation will provide new ideas for clinical diagnosis, prevention, and treatment of neurodegenerative diseases.
Keywords: Acetylglucosamine; Alzheimer Disease; Disease Progression; Humans; N-Acetylglucosaminyltransferases; Neurodegenerative Diseases; Protein Processing, Post-Translational; Proteins

Optimizing the Implementation of a Lifestyle Dementia Prevention Intervention for Older Patients in an Academic Healthcare System. - Mace, Ryan A; Lyons, Christopher; Cohen, Joshua E; Ritchie, Christine; Bartels, Stephen; Okereke, Olivia I; Hoeppner, Bettina B; Brewer, Judson A; Vranceanu, Ana-Maria (J Alzheimers Dis, 2024)
BACKGROUND: Interventions that promote healthy lifestyles are critical for the prevention of Alzheimer's disease and Alzheimer's disease related dementias (AD/ADRD). However, knowledge of the best practices for implementing AD/ADRD prevention in healthcare settings remains limited. OBJECTIVE: We aimed to qualitatively identify barriers and facilitators to implementing a clinical trial of a novel lifestyle intervention (My Healthy Brain) in our medical center for older patients with subjective cognitive decline who are at-risk for AD/ADRD. METHODS: We conducted focus groups with 26 healthcare professionals (e.g., physicians, psychology, nursing) from 5 clinics that treat older patients (e.g., memory care, psychiatry). Our qualitative analysis integrated two implementation frameworks to systematically capture barriers and facilitators to AD/ADRD prevention (Consolidated Framework for Implementation Science Research) that impact implementation outcomes of acceptability, appropriateness, and feasibility (Proctor's framework). RESULTS: We found widespread support for an RCT of My Healthy Brain and AD/ADRD prevention. Participants identified barriers related to patients (stigma, technological skills), providers (dismissiveness of "worried well," doubting capacity for behavior change), clinics (limited time and resources), and the larger healthcare system (underemphasis on prevention). Implementation strategies guided by Expert Recommendations for Implementing Change (ERIC) included: developing tailored materials, training staff, obtaining buy-in from leadership, addressing stigmatized language and practices, identifying "champions," and integrating with workflows and resources. CONCLUSIONS: The results will inform our recruitment, enrollment, and retention procedures to implement the first randomized clinical trial of My Healthy Brain. Our study provides a blueprint for addressing multi-level barriers to the implementation of AD/ADRD prevention for older patients in medical settings.
Keywords: Academic Medical Centers; Aged; Alzheimer Disease; Cognitive Dysfunction; Dementia; Female; Focus Groups; Health Personnel; Humans; Life Style; Male

Palliative Care in Nursing Home Residents with Young-Onset Dementia: Professional and Family Caregiver Perspectives. - Maters, Jasper; van der Steen, Jenny T; de Vugt, Marjolein E; Bakker, Christian; Koopmans, Raymond T C M (J Alzheimers Dis, 2024)
BACKGROUND: The evidence underpinning palliative care in dementia is mostly based on research in older populations. Little is known about the palliative care needs of people with young-onset dementia (YOD). OBJECTIVE: To describe palliative care practices including advance care planning (ACP) in people with YOD residing in Dutch nursing homes. METHODS: The study presents baseline questionnaire data from an observational cohort study. Physicians, family caregivers, and nursing staff completed questionnaires about 185 residents with YOD. The questionnaires included items on sociodemographics, quality of life measured with the quality of life in late-stage dementia (QUALID) scale, dementia-related somatic health problems, symptoms, pain medication, psychotropic drugs, and ACP. RESULTS: The mean age was 63.9 (SD 5.8) years. Half (50.3%) of them were female. Alzheimer's disease dementia (42.2%) was the most prevalent subtype. The mean QUALID score was 24.0 (SD 7.9) as assessed by family caregivers, and 25.3 (SD 8.6) as assessed by the nursing staff. Swallowing problems were the most prevalent dementia-related health problem (11.4%). Agitation was often reported by physicians (42.0%) and nursing staff (40.5%). Psychotropics were prescribed frequently (72.3%). A minority had written advance directives (5.4%) or documentation on treatment preferences by the former general practitioner (27.2%). Global care goals most often focused on comfort (73.9%). Proportions of do-not-treat orders were higher than do-treat orders for all interventions except for hospitalization and antibiotics. CONCLUSIONS: ACP must be initiated earlier, before nursing home admission. A palliative approach seems appropriate even though residents are relatively young and experience few dementia-related health problems.
Keywords: Aged; Alzheimer Disease; Caregivers; Dementia; Female; Humans; Male; Nursing Homes; Palliative Care; Quality of Life

Potential Impact of Slowing Disease Progression in Early Symptomatic Alzheimer's Disease on Patient Quality of Life, Caregiver Time, and Total Societal Costs: Estimates Based on Findings from GERAS-US Study. - Chandler, Julie M; Ye, Wenyu; Mi, Xiaojuan; Doty, Erin G; Johnston, Joseph A (J Alzheimers Dis, 2024)
BACKGROUND: Impact of Alzheimer's disease (AD) progression on patient health-related quality of life (HRQoL), caregiver time, and societal costs is not well characterized in early AD. OBJECTIVE: To assess the association of change in cognition with HRQoL, caregiver time, and societal costs over 36 months, and estimate the impact of slowing disease progression on these outcomes. METHODS: This post-hoc analysis included patients with amyloid-positive mild cognitive impairment (MCI) and mild AD dementia (MILD AD) from the 36-month GERAS-US study. Disease progression was assessed using the Mini-Mental State Examination score. Change in outcomes associated with slowing AD progression was estimated using coefficients from generalized linear models. RESULTS: At baseline, 300 patients had MCI and 317 had MILD AD. Observed natural progression over 36 months was associated with: 5.1 point decline in the Bath Assessment of Subjective Quality of Life in Dementia (BASQID) score (for HRQoL), increase in 1,050 hours of total caregiver time, and $8,504 total societal costs for MCI; 6.6 point decline in the BASQID score, increase in 1,929 hours of total caregiver time, and $12,795 total societal costs for MILD AD per person. Slowing AD progression by 30% could result in per person savings in HRQoL decline, total caregiver time, and total societal costs: for MCI: 1.5 points, 315 hours, and $2,638; for MILD AD: 2.0 points, 579 hours, and $3,974. CONCLUSIONS: Slowing AD progression over 36 months could slow decline in HRQoL and save caregiver time and societal cost in patients with MCI and MILD AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Caregivers; Cognitive Dysfunction; Cost of Illness; Disease Progression; Female; Humans; Male; Mental Status and Dementia Tests; Quality of Life; United States

Pre-existing dementia is associated with 2-3 folds risk for in-hospital mortality and complications after intracerebral hemorrhage stroke. - Zuo, Lijun; Hu, Yang; Dong, YanHong; Seet, Raymond Cs; Li, Zixiao; Wang, Yongjun; Zhao, Xingquan (J Alzheimers Dis, 2024)
BACKGROUND: Pre-existing dementia was related to poor functional outcome after intracerebral hemorrhage (ICH), and its commonly underlying pathologies were considered as cerebral amyloid angiopathy. But the impact of pre-existing dementia on in-hospital mortality in Chinese ICH patients has not been well characterized. OBJECTIVE: To investigate the association between pre-existing dementia and in-hospital mortality after ICH. METHODS: Data were extracted from the China Stroke Center Alliance database. Information about the existence of prior to stroke dementia was obtained from next of kin informants and registered in clinical charts. Patients' characteristics, in-hospital mortality, home discharge and complications were compared between ICH patients with and without pre-existing dementia. RESULTS: Out of the 72,318 ICH patients, we identified 328 patients with pre-existing dementia. Patients with pre-existing dementia were more likely to experience greater stroke severity as measured by the National Institute of Health Stroke Scale and Glasgow Coma Scale. In the adjusted models, the presence of pre-existing dementia was associated with an increased risk of in-hospital mortality (OR 2.31, 95% CI 1.12-4.77), more frequent in-hospital complications of pulmonary embolism (OR 5.41, 95% CI 1.16-25.14), pneumonia (OR 1.58, 95% CI 1.08-2.33), urinary tract infection (OR 2.37, 95% CI 1.21-4.64), gastrointestinal bleeding (OR 2.39, 95% CI 1.27-4.49) and lower home discharge (OR 0.59, 95% CI 0.38∼0.93). CONCLUSIONS: ICH patients with pre-existing dementia are more likely to suffer from greater stroke severity, poorer outcomes and lower home discharge. Future studies should evaluate the value of intensive risk factor control among individuals with pre-existing dementia for stroke prevention.
Keywords: Aged; Aged, 80 and over; Cerebral Hemorrhage; China; Dementia; Female; Hemorrhagic Stroke; Hospital Mortality; Humans; Male; Middle Aged; Risk Factors; Stroke

Psychosis in Neurodegenerative Dementias: A Systematic Comparative Review. - Cressot, Coralie; Vrillon, Agathe; Lilamand, Matthieu; Francisque, Hélène; Méauzoone, Aurélie; Hourregue, Claire; Dumurgier, Julien; Marlinge, Emeline; Paquet, Claire; Cognat, Emmanuel (J Alzheimers Dis, 2024)
BACKGROUND: Psychosis, characterized by delusions and/or hallucinations, is frequently observed during the progression of Alzheimer's disease (AD) and other neurodegenerative dementias (ND) (i.e., dementia with Lewy bodies (DLB), and frontotemporal dementia (FTD)) and cause diagnostic and management difficulties. OBJECTIVE: This review aims at presenting a concise and up-to-date overview of psychotic symptoms that occur in patients with ND with a comparative approach. METHODS: A systematic review was conducted following the PRISMA guidelines. 98 original studies investigating psychosis phenotypes in neurodegenerative dementias were identified (40 cohort studies, 57 case reports). RESULTS: Psychosis is a frequently observed phenomenon during the course of ND, with reported prevalence ranging from 22.5% to 54.1% in AD, 55.9% to 73.9% in DLB, and 18% to 42% in FTD. Throughout all stages of these diseases, noticeable patterns emerge depending on their underlying causes. Misidentification delusions (16.6-78.3%) and visual hallucinations (50-69.6%) are frequently observed in DLB, while paranoid ideas and somatic preoccupations seem to be particularly common in AD and FTD, (respectively 9.1-60.3% and 3.10-41.5%). Limited data were found regarding psychosis in the early stages of these disorders. CONCLUSIONS: Literature data suggest that different ND are associated with noticeable variations in psychotic phenotypes, reflecting disease-specific tendencies. Further studies focusing on the early stages of these disorders are necessary to enhance our understanding of early psychotic manifestations associated with ND and help in differential diagnosis issues.
Keywords: Alzheimer Disease; Delusions; Dementia; Frontotemporal Dementia; Humans; Lewy Body Disease; Neurodegenerative Diseases; Psychotic Disorders

Quantitative Metabolomic Analysis of the Rat Hippocampus: Effects of Age and of the Development of Alzheimer's Disease-Like Pathology. - Snytnikova, Olga; Telegina, Darya; Savina, Ekaterina; Tsentalovich, Yuri; Kolosova, Nataliya (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is the most common type of dementia in the elderly. Incomplete knowledge about the pathogenesis of this disease determines the absence of medications for the treatment of AD today. Animal models can provide the necessary knowledge to understand the mechanisms of biochemical processes occurring in the body in health and disease. OBJECTIVE: To identify the most promising metabolomic predictors and biomarkers reflecting metabolic disorders in the development of AD signs. METHODS: High resolution 1H NMR spectroscopy was used for quantitative metabolomic profiling of the hippocampus of OXYS rats, an animal model of sporadic AD, which demonstrates key characteristics of this disease. Animals were examined during several key periods: 20 days group corresponds to the "preclinical" period preceding the development of AD signs, during their manifestation (3 months), and active progression (18 months). Wistar rats of the same age were used as control. RESULTS: Ranges of variation and mean concentrations were established for 59 brain metabolites. The main metabolic patterns during aging, which are involved in energy metabolism pathways and metabolic shifts of neurotransmitters, have been established. Of particular note is the significant increase of scyllo-inositol and decrease of hypotaurine in the hippocampus of OXYS rats as compared to Wistars for all studied age groups. CONCLUSIONS: We suggest that the accumulation of scyllo-inositol and the reduction of hypotaurine in the brain, even at an early age, can be considered as predictors and potential biomarkers of the development of AD signs in OXYS rats and, probably, in humans.
Keywords: Aging; Alzheimer Disease; Animals; Disease Models, Animal; Hippocampus; Inositol; Magnetic Resonance Spectroscopy; Male; Metabolomics; Proton Magnetic Resonance Spectroscopy; Rats; Rats, Wistar

Recent Advances in Drug Delivery Systems Targeting Insulin Signalling for the Treatment of Alzheimer's Disease. - Sachdeva, Punya; Narayanan, Kannan Badri; Sinha, Jitendra Kumar; Gupta, Saurabh; Ghosh, Shampa; Singh, Krishna Kumar; Bhaskar, Rakesh; Almutary, Abdulmajeed G; Zothantluanga, James H; Kotta, Kranthi Kumar; Nelson, Vinod Kumar; Paiva-Santos, Ana Cláudia; et al. (J Alzheimers Dis, 2024)
Alzheimer's disease (AD) is a complex neurodegenerative disorder characterized by the accumulation of neurofibrillary tangles and amyloid-β plaques. Recent research has unveiled the pivotal role of insulin signaling dysfunction in the pathogenesis of AD. Insulin, once thought to be unrelated to brain function, has emerged as a crucial factor in neuronal survival, synaptic plasticity, and cognitive processes. Insulin and the downstream insulin signaling molecules are found mainly in the hippocampus and cortex. Some molecules responsible for dysfunction in insulin signaling are GSK-3β, Akt, PI3K, and IRS. Irregularities in insulin signaling or insulin resistance may arise from changes in the phosphorylation levels of key molecules, which can be influenced by both stimulation and inactivity. This, in turn, is believed to be a crucial factor contributing to the development of AD, which is characterized by oxidative stress, neuroinflammation, and other pathological hallmarks. Furthermore, this route is known to be indirectly influenced by Nrf2, NF-κB, and the caspases. This mini-review delves into the intricate relationship between insulin signaling and AD, exploring how disruptions in this pathway contribute to disease progression. Moreover, we examine recent advances in drug delivery systems designed to target insulin signaling for AD treatment. From oral insulin delivery to innovative nanoparticle approaches and intranasal administration, these strategies hold promise in mitigating the impact of insulin resistance on AD. This review consolidates current knowledge to shed light on the potential of these interventions as targeted therapeutic options for AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Drug Delivery Systems; Glycogen Synthase Kinase 3 beta; Humans; Insulin; Insulin Resistance

Safety Profile of Pimavanserin Therapy in Elderly Patients with Neurodegenerative Disease-Related Neuropsychiatric Symptoms: A Phase 3B Study. - Alva, Gus; Cubała, Wiesław J; Berrio, Ana; Coate, Bruce; Abler, Victor; Pathak, Sanjeev (J Alzheimers Dis, 2024)
BACKGROUND: Pimavanserin, a 5-HT2A receptor inverse agonist/antagonist, is the only medication approved by the FDA for the treatment of hallucinations and delusions associated with Parkinson's disease psychosis (PDP). Further expanding knowledge of the safety profile of pimavanserin in PDP and neurodegenerative diseases (NDD) such as Alzheimer's disease is of great interest for informing its use in patients with PDP (with or without dementia), given this population is highly sensitive to adverse effects following antipsychotic use. OBJECTIVE: This trial evaluated the effects of pimavanserin compared to placebo in frail older adults and elderly patients with neuropsychiatric symptoms related to NDD, such as hallucinations and delusions, to better understand the safety of pimavanserin in this population. METHODS: This was a phase 3b, 8-week treatment (study duration of up to 16 weeks), multicenter, randomized, double-blind, placebo-controlled, two-arm parallel-group trial (NCT03575052). The primary endpoint was safety and tolerability, measured by treatment-emergent adverse events (TEAEs). Secondary safety endpoints were change from baseline in motor and cognitive function; exploratory endpoints included suicidality, sleep quality, and neuropsychiatric symptoms. RESULTS: Incidences of TEAEs were similar between treatment groups; 29.8% reported ≥1 TEAE (pimavanserin: 30.4%; placebo: 29.3%), and 1.8% reported serious TEAEs (pimavanserin: 2.0%; placebo: 1.5%). Pimavanserin did not impact motor- or cognitive-related function. CONCLUSIONS: Pimavanserin was well tolerated and not associated with motor or cognitive impairment. Together, these findings highlight the manageable and generally favorable safety profile of pimavanserin in patients with NDD, contributing to our knowledge on the safety of pimavanserin as it generalizes to patients with PDP.
Keywords: Aged; Antipsychotic Agents; Drug Inverse Agonism; Hallucinations; Humans; Neurodegenerative Diseases; Piperidines; Psychotic Disorders; Urea

Senescence Targeting Methods Impact Alzheimer's Disease Features in 3xTg Mice. - Ng, Pei Y; Zhang, Cheng; Li, Hu; Baker, Darren J (J Alzheimers Dis, 2024)
BACKGROUND: Cellular senescence has been associated with neurodegenerative disease and clearance of senescent cells using genetic or pharmaceutical strategies (senolytics) has demonstrated beneficial effects in mouse models investigating individual disease etiologies of Alzheimer's disease (AD). However, it has remained unclear if senescent cell clearance in a mouse model exhibiting both plaque and tau pathologies modifies the disease state (3xTg). OBJECTIVE: To investigate the effects of senescent cell clearance in the 3xTg mouse model. METHODS: 3xTg mice were treated with senolytics (ABT263 (navitoclax; NAVI), a combination of dasatinib and quercetin (D+Q)), or subjected to transgene-mediated removal of p16-expressing cells (via INK-ATTAC). RESULTS: Senolytic treatments consistently reduced microgliosis and ameliorated both amyloid and tau pathology in 3xTg mice. Using RNA sequencing, we found evidence that synaptic dysfunction and neuroinflammation were attenuated with treatment. These beneficial effects were not observed with short-term senolytic treatment in mice with more advanced disease. CONCLUSIONS: Overall, our results further corroborate the beneficial effects senescent cell clearance could have on AD and highlight the importance of early intervention for the treatment of this debilitating disease.
Keywords: Alzheimer Disease; Animals; Cellular Senescence; Disease Models, Animal; Mice; Mice, Transgenic; Neurodegenerative Diseases; Senotherapeutics; tau Proteins

Socioeconomic Status and Dementia Risk Among Intensive Care Unit Survivors: Using National Health Insurance Cohort in Korea. - Park, Yu Shin; Joo, Hye Jin; Jang, Yun Seo; Jeon, Hajae; Park, Eun-Cheol; Shin, Jaeyong (J Alzheimers Dis, 2024)
BACKGROUND: In aging populations, more elderly patients are going to the intensive care unit (ICU) and surviving. However, the specific factors influencing the occurrence of post-intensive care syndrome in the elderly remain uncertain. OBJECTIVE: To investigate the association between socioeconomic status (SES) and risk of developing dementia within two years following critical care. METHODS: This study included participants from the Korean National Health Insurance Service Cohort Database who had not been diagnosed with dementia and had been hospitalized in the ICU from 2003 to 2019. Dementia was determined using specific diagnostic codes (G30, G31) and prescription of certain medications (rivastigmine, galantamine, memantine, or donepezil). SES was categorized into low (medical aid beneficiaries) and non-low (National Health Insurance) groups. Through a 1:3 propensity score matching based on sex, age, Charlson comorbidity index, and primary diagnosis, the study included 16,780 patients. We used Cox proportional hazard models to estimate adjusted hazard ratios (HR) of dementia. RESULTS: Patients with low SES were higher risk of developing dementia within 2 years after receiving critical care than those who were in non-low SES (HR: 1.23, 95% CI: 1.04-1.46). Specifically, patients with low SES and those in the high-income group exhibited the highest incidence rates of developing dementia within two years after receiving critical care, with rates of 3.61 (95% CI: 3.13-4.17) for low SES and 2.58 (95% CI: 2.20-3.03) for high income, respectively. CONCLUSIONS: After discharge from critical care, compared to the non-low SES group, the low SES group was associated with an increased risk of developing dementia.
Keywords: Aged; Dementia; Humans; Intensive Care Units; National Health Programs; Republic of Korea; Retrospective Studies; Social Class; Survivors

There are dementia patients in Gaza too. - Irfan, Bilal; Abu Shammala, Abdallah; Alshaer, Nour; Nasser, Elias; Wajahath, Muaaz; Hamawy, Adam; Tahir, Mohammed; Khawaja, Haseeb; Khan, Osaama; Fikry, Karim; Kaleem, Arshad; Nasser, Mosab; et al. (J Alzheimers Dis, 2024)
This editorial highlights the devastating impact of the ongoing Israeli military assault in Gaza on dementia patients, whose fragile care systems have collapsed, leaving them vulnerable and without essential medical support. Through harrowing stories of displacement, medication shortages, and tragic deaths, the piece underscores the profound moral failure in protecting Gaza's most vulnerable, calling for urgent global action to address the humanitarian crisis and ensure dignity and healthcare for all affected individuals.
Keywords: Dementia; Humans; Middle East

Transcriptomic Profiling Reveals Neuroinflammation in the Corpus Callosum of a Transgenic Mouse Model of Alzheimer's Disease. - Takase, Hajime; Hamanaka, Gen; Hoshino, Tomonori; Ohtomo, Ryo; Guo, Shuzhen; Mandeville, Emiri T; Lo, Eng H; Arai, Ken (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is a widespread neurodegenerative disorder characterized by progressive cognitive decline, affecting a significant portion of the aging population. While the cerebral cortex and hippocampus have been the primary focus of AD research, accumulating evidence suggests that white matter lesions in the brain, particularly in the corpus callosum, play an important role in the pathogenesis of the disease. OBJECTIVE: This study aims to investigate the gene expression changes in the corpus callosum of 5xFAD transgenic mice, a widely used AD mouse model. METHODS: We conducted behavioral tests for spatial learning and memory in 5xFAD transgenic mice and performed RNA sequencing analyses on the corpus callosum to examine transcriptomic changes. RESULTS: Our results show cognitive decline and demyelination in the corpus callosum of 5xFAD transgenic mice. Transcriptomic analysis reveals a predominance of upregulated genes in AD mice, particularly those associated with immune cells, including microglia. Conversely, downregulation of genes related to chaperone function and clock genes such as Per1, Per2, and Cry1 is also observed. CONCLUSIONS: This study suggests that activation of neuroinflammation, disruption of chaperone function, and circadian dysfunction are involved in the pathogenesis of white matter lesions in AD. The findings provide insights into potential therapeutic targets and highlight the importance of addressing white matter pathology and circadian dysfunction in AD treatment strategies.
Keywords: Alzheimer Disease; Animals; Corpus Callosum; Disease Models, Animal; Gene Expression Profiling; Mice; Mice, Transgenic; Neuroinflammatory Diseases

Vaccines and Dementia: Part I. Non-Specific Immune Boosting with BCG: History, Ligands, and Receptors. - Greenblatt, Charles L; Lathe, Richard (J Alzheimers Dis, 2024)
Vaccines such as Bacille Calmette-Guérin (BCG) can apparently defer dementia onset with an efficacy better than all drugs known to date, as initially reported by Gofrit et al. (PLoS One14, e0224433), now confirmed by other studies. Understanding how and why is of immense importance because it could represent a sea-change in how we manage patients with mild cognitive impairment through to dementia. Given that infection and/or inflammation are likely to contribute to the development of dementias such as Alzheimer's disease (Part II of this work), we provide a historical and molecular background to how vaccines, adjuvants, and their component molecules can elicit broad-spectrum protective effects against diverse agents. We review early studies in which poxvirus, herpes virus, and tuberculosis (TB) infections afford cross-protection against unrelated pathogens, a concept known as 'trained immunity'. We then focus on the attenuated TB vaccine, BCG, that was introduced to protect against the causative agent of TB, Mycobacterium tuberculosis. We trace the development of BCG in the 1920 s through to the discovery, by Freund and McDermott in the 1940 s, that extracts of mycobacteria can themselves exert potent immunostimulating (adjuvant) activity; Freund's complete adjuvant based on mycobacteria remains the most potent immunopotentiator reported to date. We then discuss whether the beneficial effects of BCG require long-term persistence of live bacteria, before focusing on the specific mycobacterial molecules, notably muramyl dipeptides, that mediate immunopotentiation, as well as the receptors involved. Part II addresses evidence that immunopotentiation by BCG and other vaccines can protect against dementia development.
Keywords: Adjuvants, Immunologic; BCG Vaccine; Dementia; Humans; Ligands; Mycobacterium tuberculosis; Tuberculosis; Tuberculosis Vaccines

Voluntary wheel running decreases amyloidogenic pathway and rescues cognition and mitochondrial energy metabolism in middle-aged female 3xTg-AD mouse model of Alzheimer's disease. - Dos Santos, Jonathas Rodrigo; Catalão, Carlos Henrique Rocha; Vulczak, Anderson; Azzolini, Ana Elisa Caleiro Seixas; Alberici, Luciane Carla (J Alzheimers Dis, 2024)
BACKGROUND: Evidence supports the neuroprotective effects of physical activity, either in experimental animal models or humans. However, the biological mechanisms by which physical exercise modulates dementia and Alzheimer's disease (AD) progression are still unclear. OBJECTIVE: This study investigated whether long-term (6 months) of voluntary wheel running induces neuroprotective effects in the pathogenesis of AD in middle-aged (8 months) female mice, focusing on energy metabolism. METHODS: A genetic mice model of AD (3xTg-AD) that performed wheel running presented changes in body metabolism and muscle oxidative profile, as well as restored discriminative and non-associative retention memories, evaluated by novel object recognition and open field tasks, respectively. RESULTS: In the hippocampus, these mice exhibited reduced levels of amyloidogenic AβPPβ fragment, phospho-Tau protein and phospho-Akt (activated form), without changes in phospho-AMPK (activated form). In addition, hippocampal mitochondria presented a restored respiratory function, characterized by lower coupling degree and weak contribution from complex I found in 3xTg-AD mice. CONCLUSIONS: The results demonstrated that voluntary exercise improves cognitive parameters and biochemical hallmarks of AD, modulates Akt activation and enhances mitochondrial energy metabolism in hippocampus of middle-aged 3xTg-AD female mice, thereby reinforcing the neuroprotective role of physical exercise and the involvement of mitochondria in the etiology of the AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cognition; Disease Models, Animal; Energy Metabolism; Female; Hippocampus; Mice; Mice, Transgenic; Mitochondria; Physical Conditioning, Animal; tau Proteins

Advanced Alzheimer's Disease Patients Show Safe, Significant, and Persistent Benefit in 6-Month Bryostatin Trial. - Alkon, Daniel L; Sun, Miao-Kun; Tuchman, Alan J; Thompson, Richard E (J Alzheimers Dis, 2023)
BACKGROUND: In pre-clinical studies, Bryostatin, MW (molecular weight) 904, has demonstrated synaptogenic, anti-apoptotic, anti-amyloid, and anti-tau tangle efficacies. OBJECTIVE: To identify AD patients who show significant cognitive benefit versus placebo when treated in a trial with chronic Bryostatin dosing. METHODS: In this 6-month 122 AD patient Bryostatin trial, there were two cohorts: the Moderate Cohort (MMSE, Mini-Mental Status Exam: 15-18) and the Moderately Severe Cohort (MMSE 10-14) as pre-specified secondary endpoints. Patient randomization was stratified by baseline SIB to insure balance in baseline cognitive ability between treatment arms. RESULTS: With no safety events noted by the data safety and monitoring board, the Moderately Severe (MMSE 10-14) Bryostatin-treated patients were significantly improved above the placebo patients for Weeks #13 through Week #42. After two cycles of 7 x i.v. Bryostatin doses over a 26-week period, the 10-14 Cohort Severe Impairment Battery (SIB), measured every 2 weeks, showed significant benefit using a Mixed Model Repeated Measures model (MMRM, 2-tailed, p < 0.05) for Weeks #13 through #42, even 16 weeks after dosing completion by Week #26. Placebo 10-14 patients showed no benefit, declining to negative 12.8 points by Week #42. Trend analyses confirmed the MMRM data for this Cohort, with a significant downward slope (equivalent to Cognitive Decline) for the placebo group, p < 0.001, 2-tailed, but no significant decline for the Bryostatin-treated group (p = 0.409, NS), treatment versus placebo p < 0.007. The Moderate Cohort patients showed no significant benefit. CONCLUSIONS: The Bryostatin-treated MMSE 10-14 patients showed no significant cognitive decline throughout the 10-month trial, versus placebo patients' decline of -12.8 SIB points.
Keywords: Alzheimer Disease; Bryostatins; Cognition Disorders; Double-Blind Method; Humans; Treatment Outcome

Age-Related Association Between APOE ɛ4 and Cognitive Progression in de novo Parkinson's Disease. - Liu, Jia-Yao; Ma, Ling-Zhi; Wang, Jun; Cui, Xin-Jing; Sheng, Ze-Hu; Fu, Yan; Li, Meng; Ou, Ya-Nan; Yu, Jin-Tai; Tan, Lan; Lian, Yan (J Alzheimers Dis, 2023)
BACKGROUND: APOE ɛ4 genotype was correlated with exacerbation of pathology and higher risk of dementia in Parkinson's disease (PD). Meanwhile, the differential influence of APOE ɛ4 on cognition in young and old individuals interpreted as antagonistic pleiotropy. OBJECTIVE: To examine whether the effect of APOE ɛ4 on cognitive progression in de novo PD is age dependent. METHODS: In this study, 613 de novo PD patients were recruited from Parkinson's Progression Markers Initiative (PPMI). To examine the age-dependent relationship between APOE ɛ4 and cognitive changes, we added 3-way interaction of APOE ɛ4*baseline age*time to the linear mixed-effect (LME) models and evaluated the specific roles of APOE ɛ4 in the middle age group and elderly group separately. Cox regression was utilized to examine the progression of cognition in age-stratified PD participants. RESULTS: Age significantly modified relationship between APOE ɛ4 and cognitive changes in most cognitive domains (pinteraction <0.05). In the elderly group, APOE ɛ4 carriers showed steeper decline in global cognition (p = 0.001) as well as in most cognitive domains, and they had a greater risk of cognitive progression (adjusted HR 1.625, 95% CI 1.143-2.310, p = 0.007), compared with non-carriers. However, in the middle age group, no significant relationships between APOE ɛ4 and cognitive decline can be detected. CONCLUSION: Our results indicated that the APOE ɛ4 allele has an age-dependent effect on cognitive decline in PD patients. The underlying mechanisms need to be investigated in the future.
Keywords: Aged; Apolipoprotein E4; Cognition; Cognitive Dysfunction; Disease Progression; Genotype; Heterozygote; Humans; Parkinson Disease

Association of Influenza Vaccination and Dementia Risk: A Meta-Analysis of Cohort Studies. - Sun, Huimin; Liu, Min; Liu, Jue (J Alzheimers Dis, 2023)
BACKGROUND: Dementia is a critical global public health problem. Previous cohort studies have found that influenza vaccination can decrease the risk of dementia. OBJECTIVE: This meta-analysis aimed to systematically examine the relationship between influenza vaccination and dementia risk. METHODS: We searched PubMed, Embase, Web of Science, ScienceDirect, medRxiv, and bioRxiv for studies investigating dementia risk based on influenza vaccination status, up to September 14, 2022. Relative risks (RRs) and 95% confidence intervals (95% CIs) were pooled in the meta-analysis. Subgroup analyses and sensitivity analyses were conducted as well. RESULTS: Of the 4,087 articles initially reviewed, 6 cohort studies were included in the final meta-analysis, and all eligible studies were at low risk of bias. There were 2,087,195 participants without dementia at baseline (mean age: 61.8-75.5 years, 57.05% males), and 149,804 (7.18%) cases of dementia occurred during 4.00-13.00 years of follow-up. Pooled analysis of adjusted RRs found that influenza vaccination could reduce dementia risk by 31% (RR = 0.69, 95% CI: 0.57-0.83). Subgroup analyses showed that in the study with a mean age of 75-80 years or 75%-100% males, the association was generally weakened compared with studies with a mean age of 60-75 years or 25%-50% males. The results were stable in the sensitivity analyses, and no publication bias was observed. CONCLUSION: Influenza vaccination in older adults was markedly associated with a decreased risk of dementia. More mechanistic studies and epidemiological studies are needed to clarify the association between influenza vaccination and decreased dementia risk.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Dementia; Humans; Influenza, Human; Vaccination

Best Medicine for Dementia: The Life-Long Defense of the Brain. - Andersson, Marcus J; Stone, Jonathan (J Alzheimers Dis, 2023)
This review deals with an unwelcome reality about several forms of dementia, including Alzheimer's disease- that these dementias are caused, in part or whole, by the aging of the vasculature. Since the vasculature ages in us all, dementia is our fate, sealed by the realit!ies of the circulation; it is not a disease with a cure pending. Empirically, cognitive impairment before our 7th decade is uncommon and considered early, while a diagnosis in our 11th decade is late but common in that cohort (>40%). Projections from earlier ages suggest that the prevalence of dementia in people surviving into their 12th decade exceeds 80%. We address the question why so few of many interventions known to delay dementia are recognized as therapy; and we try to resolve this few-and-many paradox, identifying opportunities for better treatment, especially pre-diagnosis. The idea of dementia as a fate is resisted, we argue, because it negates the hope of a cure. But the price of that hope is lost opportunity. An approach more in line with the evidence, and more likely to limit suffering, is to understand the damage that accumulates with age in the cerebral vasculature and therefore in the brain, and which eventually gives rise to cognitive symptoms in late life, too often leading to dementia. We argue that hope should be redirected to delaying that damage and with it the onset of cognitive loss; and, for each individual, it should be redirected to a life-long defense of their brain.
Keywords: Aging; Alzheimer Disease; Brain; Cognitive Dysfunction; Dementia; Humans

Characterizing Limbic-Predominant Age-Related TDP-43 Encephalopathy Without Alzheimer's Disease and Lewy Body Dementia in the Oldest Old: A Case Series. - Leiby, Anne-Marie C; Scambray, Kiana A; Nguyen, Hannah L; Basith, Farheen; Fakhraee, Shahrzad; Melikyan, Zarui A; Bukhari, Syed A; Montine, Thomas J; Corrada, Maria M; Kawas, Claudia H; Sajjadi, S Ahmad (J Alzheimers Dis, 2023)
BACKGROUND: Limbic-predominant age-related TDP-43 encephalopathy neuropathologic change (LATE-NC) is a clinicopathological construct proposed to facilitate studying TDP-43 pathology in older individuals. OBJECTIVE: Our aim was to describe clinical and cognitive characteristics of LATE-NC without Alzheimer's disease neuropathologic change (ADNC) and Lewy body (LB) and to compare this with ADNC and primary age related tauopathy (PART). METHODS: In 364 autopsies of the oldest old of The 90+ Study, we identified those with LATE-NC without ADNC and LB. Control groups were participants with ADNC and PART. RESULTS: Of 31% of participants who had LATE-NC, only 5 (1.4%) had LATE-NC without ADNC and LB, all of whom had tau. These participants had a gradual and progressive cognitive decline. Four (80%) had dementia at death, a rate that was higher than ADNC (50%) and PART (21.7%). Mean duration of cognitive impairment was twice as long in LATE-NC without ADNC and LB (6.2 years) compared to ADNC (2.9 years) and PART (3 years). LATE-NC without ADNC and LB group had a higher prevalence of syncope, depression, and extrapyramidal signs than the ADNC and PART groups. CONCLUSIONS: Despite the high prevalence of LATE-NC, LATE-NC without ADNC and LB was rare in this large oldest-old cohort, highlighting the very high prevalence of multiple pathologic changes in the oldest old. Slowly progressive cognitive decline, ubiquitous memory impairment, history of syncope and depression, and extrapyramidal signs were prominent features among our LATE-NC without ADNC and LB group.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; DNA-Binding Proteins; Humans; Lewy Body Disease; Syncope; Tauopathies; TDP-43 Proteinopathies

Characterizing Performance Gaps of a Code-Based Dementia Algorithm in a Population-Based Cohort of Cognitive Aging. - Vassilaki, Maria; Fu, Sunyang; Christenson, Luke R; Garg, Muskan; Petersen, Ronald C; St Sauver, Jennifer; Sohn, Sunghwan (J Alzheimers Dis, 2023)
BACKGROUND: Multiple algorithms with variable performance have been developed to identify dementia using combinations of billing codes and medication data that are widely available from electronic health records (EHR). If the characteristics of misclassified patients are clearly identified, modifying existing algorithms to improve performance may be possible. OBJECTIVE: To examine the performance of a code-based algorithm to identify dementia cases in the population-based Mayo Clinic Study of Aging (MCSA) where dementia diagnosis (i.e., reference standard) is actively assessed through routine follow-up and describe the characteristics of persons incorrectly categorized. METHODS: There were 5,316 participants (age at baseline (mean (SD)): 73.3 (9.68) years; 50.7% male) without dementia at baseline and available EHR data. ICD-9/10 codes and prescription medications for dementia were extracted between baseline and one year after an MCSA dementia diagnosis or last follow-up. Fisher's exact or Kruskal-Wallis tests were used to compare characteristics between groups. RESULTS: Algorithm sensitivity and specificity were 0.70 (95% CI: 0.67, 0.74) and 0.95 (95% CI: 0.95, 0.96). False positives (i.e., participants falsely diagnosed with dementia by the algorithm) were older, with higher Charlson comorbidity index, more likely to have mild cognitive impairment (MCI), and longer follow-up (versus true negatives). False negatives (versus true positives) were older, more likely to have MCI, or have more functional limitations. CONCLUSIONS: We observed a moderate-high performance of the code-based diagnosis method against the population-based MCSA reference standard dementia diagnosis. Older participants and those with MCI at baseline were more likely to be misclassified.
Keywords: Alzheimer Disease; Cognitive Aging; Cognitive Dysfunction; Dementia; Disease Progression; Female; Humans; Male

Chiral Amino Acid Profiling in Serum Reveals Potential Biomarkers for Alzheimer's Disease. - Liu, Mingxia; Li, Mo; He, Jing; He, Yi; Yang, Jian; Sun, Zuoli (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) is a complex neurodegenerative disease, and increasing evidence has linked dysregulation of amino acids to AD pathogenesis. However, the existing studies often ignore the chirality of amino acids, and some results are inconsistent and controversial. The changes of amino acid profiles in AD from the perspective of enantiomers remain elusive. OBJECTIVE: The purpose of this study is to investigate whether the levels of amino acids, especially D-amino acids, are deregulated in the peripheral serum of AD patients, with the ultimate goal of discovering novel biomarkers for AD. METHODS: The chiral amino acid profiles were determined by HPLC-MS/MS with a pre-column derivatization method. Experimental data obtained from 37 AD patients and 34 healthy controls (HC) were statistically analyzed. RESULTS: Among the 35 amino acids detected, D-proline, D/total-proline ratio, D-aspartate, and D/total-aspartate ratio were decreased, while D-phenylalanine was elevated in AD compared to HC. Significant age-dependent increases in D-proline, D/total-proline ratio, and D-phenylalanine were observed in HC, but not in AD. Receiver operator characteristic analyses of the combination of D-proline, D-aspartate, D-phenylalanine, and age for discriminating AD from HC provided satisfactory area under the curve (0.87), specificity (97.0%), and sensitivity (83.8%). Furthermore, the D-aspartate level was significantly decreased with the progression of AD, as assessed by the Clinical Dementia Rating Scale and Mini-Mental State Examination. CONCLUSION: The panels of D-proline, D-phenylalanine, and D-aspartate in peripheral serum may serve as novel biomarker candidates for AD. The latter parameter is further associated with the severity of AD.
Keywords: Alzheimer Disease; Amino Acids; Aspartic Acid; Biomarkers; D-Aspartic Acid; Humans; Neurodegenerative Diseases; Phenylalanine; Proline; Tandem Mass Spectrometry

Circulating Omega-3 and Omega-6 Fatty Acids, Cognitive Decline, and Dementia in Older Adults. - de Oliveira Otto, Marcia C; Wu, Jason H Y; Thacker, Evan L; Lai, Heidi Tsz Mung; Lemaitre, Rozenn N; Padhye, Nikhil; Song, Xiaoling; King, Irena B; Lopez, Oscar; Siscovick, David S; Mozaffarian, Dariush (J Alzheimers Dis, 2023)
BACKGROUND: Comprising nearly 35% of brain lipids, polyunsaturated fatty acids (PUFA) are essential for optimal brain function. However, the role of PUFA on cognitive health outcomes later in life is largely unknown. OBJECTIVE: We investigated prospective associations of plasma phospholipid omega-3 (ALA [18 : 3], EPA [20 : 5], DPA [22 : 5], DHA [22 : 6]) and omega-6 (LA [18 : 2], AA [20 : 4]) PUFA with cognitive decline, risk of cognitive impairment and dementia among adults aged≥65 years in the Cardiovascular Health Study. METHODS: Circulating fatty acid concentrations were measured serially at baseline (1992/1993), 6 years, and 13 years later. Cognitive decline and impairment were assessed using the 100-point Modified Mini-Mental State Examination (3MSE) up to 7 times. Clinical dementia was identified using adjudicated neuropsychological tests, and ICD-9 codes. RESULTS: Among 3,564 older adults free of stroke and dementia at baseline, cognitive function declined annually by approximately -0.5 3MSE points; 507 participants developed cognitive impairment and 499 dementia over up to 23 years of follow-up. In multivariable models, higher circulating arachidonic acid (AA) concentrations were associated with slower cognitive decline and lower dementia risk, with associations growing stronger with greater length of follow-up (hazard ratio [HR,95% CI] of dementia per interquintile range, 0.74 [0.56-0.97] at 5 years, and 0.53 [0.37-0.77] at 15 years). Circulating docosapentaenoic (DPA) concentrations were associated with slower cognitive decline and lower risk of cognitive impairment (extreme-quintile HR, 0.72 [95% CI: 0.55, 0.95]). Findings were generally null or inconsistent for other omega-3 or omega-6 PUFA. CONCLUSION: Circulating AA and DPA, but not other PUFA, are associated with slower rate of cognitive decline and lower risk of dementia or cognitive impairment later in life.
Keywords: Aged; Arachidonic Acid; Cognitive Dysfunction; Dementia; Fatty Acids; Fatty Acids, Omega-3; Fatty Acids, Omega-6; Fatty Acids, Unsaturated; Humans

The Complexity of Nutritional Problems in Persons with Dementia: Expanding a Theoretical Model. - van Buuren, Cornelia Pieternella; van der Steen, Jenny Theodora; Olthof-Nefkens, Maria; Bakker, Christian; Koopmans, Raymond Theodorus Catherina Maria; Perry, Marieke; Kalf, Johanna Gezina (J Alzheimers Dis, 2023)
BACKGROUND: Persons with dementia are at risk of developing nutritional problems. Theoretical models on nutritional problems have been developed, but have not been evaluated with healthcare professionals. OBJECTIVE: This study aimed to explore the comprehensiveness and applicability of a theoretical model of nutritional problems in persons with dementia for daily nursing home practice. METHODS: A qualitative design employing a combined deductive and inductive approach was used. Healthcare professionals were eligible to participate if they 1) had expert knowledge of and experience with nutritional problems related to dementia, and 2) worked in a nursing home affiliated with an academic network covering the east and south of the Netherlands. Three focus group interviews with 20 healthcare professionals from seven professions were held. We conducted thematic analysis and we compared themes with existing theoretical models from the literature. RESULTS: We identified six themes, four of which corresponded with the existing models (observing and analysing nutritional problems; consequences of nutritional problems; functioning of the person with dementia; environmental factors). Interprofessional collaboration and ethical factors were identified as new themes. The analyses indicated interactions within each theme, between themes, and a bidirectional connection between themes. CONCLUSIONS: This study demonstrated the relevance of interprofessional collaboration and ethical considerations in nutritional problems related to dementia. It uncovered complex bidirectional relations within and between factors regarding nutritional problems. All aspects should be taken into account to minimize the consequences of nutritional problems for persons with dementia.
Keywords: Attitude of Health Personnel; Dementia; Focus Groups; Health Personnel; Humans; Nursing Homes

Costs of Dementia in Low- And Middle-Income Countries: A Systematic Review. - Kenne Malaha, Angeladine; Thébaut, Clémence; Achille, Dayna; Preux, Pierre-Marie; Guerchet, Maëlenn (J Alzheimers Dis, 2023)
BACKGROUND: The proportion of people living with dementia in low- and middle-income countries (LMICs) is expected to reach 71% by 2050. Appraising the economic burden of the disease may contribute to strategic policy planning. OBJECTIVE: To review studies conducted on the costs of dementia in LMICs, describe their methodology and summarize available costs estimates. METHODS: Systematic review, including a search of health, economics, and social science bibliographic databases. No date or language restrictions were applied. All studies with a direct measure of the costs of dementia care were included. RESULTS: Of the 6,843 publications reviewed, 17 studies from 11 LMICs were included. Costs of dementia tended to increase with the severity of the disease. Medical costs were greater in the mild stage, while social and informal care costs were highest in the moderate and severe stages. Annual cost estimates per patient ranged from PPP$131.0 to PPP$31,188.8 for medical costs; from PPP$16.1 to PPP$10,581.7 for social care services and from PPP$140.0 to PPP$25,798 for informal care. Overall, dementia care can cost from PPP$479.0 to PPP$66,143.6 per year for a single patient. CONCLUSION: Few studies have been conducted on the costs of dementia in LMICs, and none so far in Africa. There seems to be a need to provide accurate data on the burden of disease in these countries to guide public health policies in the coming decades.
Keywords: Cost of Illness; Dementia; Developing Countries; Health Care Costs; Health Expenditures; Humans

Is Dementia Associated with COVID-19 Mortality? A Multicenter Retrospective Cohort Study Conducted in 50 Hospitals in Germany. - Kostev, Karel; Gessler, Nele; Wohlmuth, Peter; Arnold, Dirk; Bein, Berthold; Bohlken, Jens; Herrlinger, Klaus; Jacob, Louis; Koyanagi, Ai; Nowak, Lorenz; Smith, Lee; Wesseler, Claas; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Dementia has been identified as a major predictor of mortality associated with COVID-19. OBJECTIVE: The objective of this study was to investigate the association between dementia and mortality in COVID-19 inpatients in Germany across a longer interval during the pandemic. METHODS: This retrospective study was based on anonymized data from 50 hospitals in Germany and included patients with a confirmed COVID-19 diagnosis hospitalized between March 11, 2020 and July, 20, 2022. The main outcome of the study was the association of mortality during inpatient stays with dementia diagnosis, which was studied using multivariable logistic regression adjusted for age, sex, and comorbidities as well as univariate logistic regression for matched pairs. RESULTS: Of 28,311 patients diagnosed with COVID-19, 11.3% had a diagnosis of dementia. Prior to matching, 26.5% of dementia patients and 11.5% of non-dementia patients died; the difference decreased to 26.5% of dementia versus 21.7% of non-dementia patients within the matched pairs (n = 3,317). This corresponded to an increase in the risk of death associated with dementia (OR = 1.33; 95% CI: 1.16-1.46) in the univariate regression conducted for matched pairs. CONCLUSION: Although dementia was associated with COVID-19 mortality, the association was weaker than in previously published studies. Further studies are needed to better understand whether and how pre-existing neuropsychiatric conditions such as dementia may impact the course and outcome of COVID-19.
Keywords: COVID-19; COVID-19 Testing; Dementia; Germany; Hospitalization; Hospitals; Humans; Mortality; Retrospective Studies

Diet's Role in Modifying Risk of Alzheimer's Disease: History and Present Understanding. - Grant, William B; Blake, Steven M (J Alzheimers Dis, 2023)
Diet is an important nonpharmacological risk-modifying factor for Alzheimer's disease (AD). The approaches used here to assess diet's role in the risk of AD include multi-country ecological studies, prospective and cross-sectional observational studies, and laboratory studies. Ecological studies have identified fat, meat, and obesity from high-energy diets as important risk factors for AD and reported that AD rates peak about 15-20 years after national dietary changes. Observational studies have compared the Western dietary pattern with those of the Dietary Approaches to Stop Hypertension (DASH), Mediterranean (MedDi), and Mediterranean-DASH Intervention for Neurodegenerative Delay (MIND) diets. Those studies identified AD risk factors including higher consumption of saturated and total fats, meat, and ultraprocessed foods and a lower risk of AD with higher consumption of fruits, legumes, nuts, omega-3 fatty acids, vegetables, and whole grains. Diet-induced factors associated with a significant risk of AD include inflammation, insulin resistance, oxidative stress, elevated homocysteine, dietary advanced glycation end products, and trimethylamine N-oxide. The molecular mechanisms by which dietary bioactive components and specific foods affect risk of AD are discussed. Given most countries' entrenched food supply systems, the upward trends of AD rates would be hard to reverse. However, for people willing and able, a low-animal product diet with plenty of anti-inflammatory, low-glycemic load foods may be helpful.
Keywords: Alzheimer Disease; Cross-Sectional Studies; Diet; Humans; Prospective Studies; Risk Factors

Early Life Stress Enhances Cognitive Decline and Alters Synapse Function and Interneuron Numbers in Young Male APP/PS1 Mice. - Brosens, Niek; Samouil, Dimitris; Stolker, Sabine; Katsika, Efthymia Vasilina; Weggen, Sascha; Lucassen, Paul J; Krugers, Harm J (J Alzheimers Dis, 2023)
BACKGROUND: Exposure to stress early in life increases the susceptibility to Alzheimer's disease (AD) pathology in aged AD mouse models. So far, the underlying mechanisms have remained elusive. OBJECTIVE: To investigate 1) effects of early life stress (ELS) on early functional signs that precede the advanced neuropathological changes, and 2) correlate synaptosomal protein content with cognition to identify neural correlates of AD. METHODS: APPswe/PS1dE9 mice and littermates were subjected to ELS by housing dams and pups with limited bedding and nesting material from postnatal days 2-9. At 3 months of age, an age where no cognitive loss or amyloid-β (Aβ) pathology is typically reported in this model, we assessed hippocampal Aβ pathology, synaptic strength and synapse composition and interneuron populations. Moreover, cognitive flexibility was assessed and correlated with synaptosomal protein content. RESULTS: While ELS did not affect Aβ pathology, it increased synaptic strength and decreased the number of calretinin+ interneurons in the hippocampal dentate gyrus. Both genotype and condition further affected the level of postsynaptic glutamatergic protein content. Finally, APP/PS1 mice were significantly impaired in cognitive flexibility at 3 months of age, and ELS exacerbated this impairment, but only at relatively high learning criteria. CONCLUSIONS: ELS reduced cognitive flexibility in young APP/PS1 mice and altered markers for synapse and network function. These findings at an early disease stage provide novel insights in AD etiology and in how ELS could increase AD susceptibility.
Keywords: Adverse Childhood Experiences; Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cognitive Dysfunction; Disease Models, Animal; Interneurons; Male; Mice; Mice, Transgenic; Plaque, Amyloid; Presenilin-1; Synapses

The Effect of Exercise on Falls in People Living with Dementia: A Systematic Review. - Jehu, Deborah A; Davis, Jennifer C; Gill, Jessica; Oke, Olabamibo; Liu-Ambrose, Teresa (J Alzheimers Dis, 2023)
BACKGROUND: People living with dementia (PWD) are at a heightened risk for falls. However, the effects of exercise on falls in PWD are unclear. OBJECTIVE: To conduct a systematic review of randomized controlled trials (RCTs) examining the efficacy of exercise to reduce falls, recurrent falls, and injurious falls relative to usual care among PWD. METHODS: We included peer-reviewed RCTs evaluating any exercise mode on falls and related injuries among medically diagnosed PWD aged ≥55years (international prospective register of systematic reviews (PROSPERO) ID:CRD42021254637). We excluded studies that did not solely involve PWD and were not the primary publication examining falls. We searched the Cochrane Dementia and Cognitive Improvement Group's Specialized Register and grey literature on 08/19/2020 and 04/11/2022; topical categories included dementia, exercise, RCTs, and falls. We evaluated the risk of bias (ROB) using the Cochrane ROB Tool-2 and study quality using the Consolidated Standards of Reporting Trials. RESULTS: Twelve studies were included (n = 1,827; age = 81.3±7.0 years; female = 59.3%; Mini-Mental State Examination = 20.1±4.3 points; intervention duration = 27.8±18.5 weeks; adherence = 75.5±16.2%; attrition = 21.0±12.4%). Exercise reduced falls in two studies [Incidence Rate Ratio (IRR) range = 0.16 to 0.66; fall rate range: intervention = 1.35-3.76 falls/year, control = 3.07-12.21 falls/year]; all other studies (n = 10) reported null findings. Exercise did not reduce recurrent falls (n = 0/2) or injurious falls (n = 0/5). The RoB assessment ranged from some concerns (n = 9) to high RoB (n = 3); no studies were powered for falls. The quality of reporting was good (78.8±11.4%). CONCLUSION: There was insufficient evidence to suggest that exercise reduces falls, recurrent falls, or injurious falls among PWD. Well-designed studies powered for falls are needed.
Keywords: Dementia; Exercise; Female; Humans; Independent Living

Effects of Striatal Amyloidosis on the Dopaminergic System and Behavior: A Comparative Study in Male and Female 5XFAD Mice. - Lansdell, Theresa A; Xu, Hui; Galligan, James J; Dorrance, Anne M (J Alzheimers Dis, 2023)
BACKGROUND: Nearly two-thirds of patients diagnosed with Alzheimer's disease (AD) are female. In addition, female patients with AD have more significant cognitive impairment than males at the same disease stage. This disparity suggests there are sex differences in AD progression. While females appear to be more affected by AD, most published behavioral studies utilize male mice. In humans, there is an association between antecedent attention-deficit/hyperactivity disorder and increased risk of dementia. Functional connectivity studies indicate that dysfunctional cortico-striatal networks contribute to hyperactivity in attention deficit hyperactivity disorder. Higher plaque density in the striatum accurately predicts the presence of clinical AD pathology. In addition, there is a link between AD-related memory dysfunction and dysfunctional dopamine signaling. OBJECTIVE: With the need to consider sex as a biological variable, we investigated the influence of sex on striatal plaque burden, dopaminergic signaling, and behavior in prodromal 5XFAD mice. METHODS: Six-month-old male and female 5XFAD and C57BL/6J mice were evaluated for striatal amyloid plaque burden, locomotive behavior, and changes in dopaminergic machinery in the striatum. RESULTS: 5XFAD female mice had a higher striatal amyloid plaque burden than male 5XFAD mice. 5XFAD females, but not males, were hyperactive. Hyperactivity in female 5XFAD mice was associated with increased striatal plaque burden and changes in dopamine signaling in the dorsal striatum. CONCLUSION: Our results indicate that the progression of amyloidosis involves the striatum in females to a greater extent than in males. These studies have significant implications for using male-only cohorts in the study of AD progression.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloidosis; Animals; Disease Models, Animal; Dopamine; Female; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Plaque, Amyloid

The Efficacy and Safety of Physiotherapy in People with Dementia: A Systematic Review. - Saúde, Alexandra; Bouça-Machado, Raquel; Leitão, Mariana; Benedetti, Andrea; Ferreira, Joaquim J (J Alzheimers Dis, 2023)
BACKGROUND: Physiotherapy has become increasingly relevant as a new therapeutic intervention for dementia. However, it is unclear which interventions are the most suitable. OBJECTIVE: This study sought to summarize and critically appraise the evidence on physiotherapy interventions in dementia. METHODS: A systematic review conducted using CENTRAL, MEDLINE, and PEDro databases, from their inception to July 2022, identified all experimental studies of dementia that included physiotherapy interventions. RESULTS: Of 194 articles included, the most frequently used interventions were aerobic training (n = 82, 42%), strength training (n = 79, 41%), balance training (n = 48, 25%), and stretching (n = 22, 11%). These were associated with a positive effect on several motor and cognitive outcomes. A total number of 1,119 adverse events were reported. CONCLUSION: Physiotherapy has several motor and cognitive benefits in dementia. Future research should focus on establishing a physiotherapy prescription protocol for people with mild cognitive impairment and for each stage of dementia.
Keywords: Cognitive Dysfunction; Dementia; Humans; Physical Therapy Modalities; Resistance Training

Emotional Dysregulation in Mild Behavioral Impairment Is Associated with Reduced Cortical Thickness in the Right Supramarginal Gyrus. - Imai, Ayu; Matsuoka, Teruyuki; Narumoto, Jin (J Alzheimers Dis, 2023)
BACKGROUND: Mild behavioral impairment (MBI) has attracted attention as a possible precursor symptom of dementia, but its neural basis has not been fully investigated. OBJECTIVE: We aimed to investigate the relationship between MBI and surface area, cortical thickness, and volume in the temporal and parietal lobes, which are strongly associated with dementia and emotional disorders. METHODS: This retrospective study evaluated 123 participants: 90 with mild cognitive impairment (MCI), 13 with subjective cognitive decline (SCD), and 20 cognitively healthy (CH). Using analysis of covariance (ANCOVA) with sex, age, and MMSE score as covariates, cortical thickness, surface area, and volume in 10 regions were compared between groups with and without MBI. Groups with MBI emotional dysregulation were also compared with groups without MBI. RESULTS: ANCOVA revealed significantly smaller cortical thickness in the MBI group's right parahippocampal (p = 0.01) and supramarginal gyri (p = 0.002). After multiple comparison correction, only the right supramarginal gyrus was significantly smaller (p = 0.02). When considering only MBI emotional dysregulation, the right parahippocampal and supramarginal gyrus' cortical thicknesses were significantly smaller in this MBI group (p = 0.03, 0.01). However, multiple comparison correction identified no significant differences (p = 0.14, 0.11). CONCLUSION: Overall MBI and the emotional dysregulation domains were associated with reduced cortical thickness in the right parahippocampal and supramarginal gyri. Since neurodegeneration in the medial temporal and parietal lobe precedes early Alzheimer's disease (AD), MBI, particularly emotion dysregulation, may predict early AD below the diagnostic threshold.
Keywords: Alzheimer Disease; Attention; Cognitive Dysfunction; Dementia; Humans; Neuropsychological Tests; Parietal Lobe; Retrospective Studies

Exposure to World Trade Center Dust Exacerbates Cognitive Impairment and Evokes a Central and Peripheral Pro-Inflammatory Transcriptional Profile in an Animal Model of Alzheimer's Disease. - Iban-Arias, Ruth; Trageser, Kyle J; Yang, Eun-Jeong; Griggs, Elizabeth; Radu, Aurelian; Naughton, Sean; Al Rahim, Md; Tatsunori, Oguchi; Raval, Urdhva; Palmieri, Joshua; Huang, Zerlina; Chen, Lung-Chi; et al. (J Alzheimers Dis, 2023)
BACKGROUND: The terrorist attacks on September 11, 2001, on the World Trade Center (WTC) led to intense fires and a massive dense cloud of toxic gases and suspended pulverized debris. In the subsequent years, following the attack and cleanup efforts, a cluster of chronic health conditions emerged among First Responders (FR) who were at Ground Zero for prolonged periods and were repeatedly exposed to high levels of WTC particulate matter (WTCPM). Among those are neurological complications which may increase the risk for the development of Alzheimer's disease (AD) later in life. OBJECTIVE: We hypothesize that WTCPM dust exposure affects the immune cross-talking between the periphery and central nervous systems that may induce brain permeability ultimately promoting AD-type phenotype. METHODS: 5XFAD and wild-type mice were intranasally administered with WTCPM dust collected at Ground Zero within 72 h after the attacks. Y-maze assay and novel object recognition behavioral tests were performed for working memory deficits and learning and recognition memory, respectively. Transcriptomic analysis in the blood and hippocampus was performed and confirmed by RT qPCR. RESULTS: Mice exposed to WTCPM dust exhibited a significant impairment in spatial and recognition short and long-term memory. Furthermore, the transcriptomic analysis in the hippocampal formation and blood revealed significant changes in genes related to immune-inflammatory responses, and blood-brain barrier disruption. CONCLUSION: These studies suggest a putative peripheral-brain immune inflammatory cross-talking that may potentiate cognitive decline, identifying for the first time key steps which may be therapeutically targetable in future studies in WTC FR.
Keywords: Alzheimer Disease; Animals; Cognitive Dysfunction; Dust; Mice; Models, Animal; September 11 Terrorist Attacks

Impact of Computerized Cognitive Training on Default Mode Network Connectivity in Subjects at Risk for Alzheimer's Disease: A 78-week Randomized Controlled Trial. - Petrella, Jeffrey R; Michael, Andrew M; Qian, Min; Nwosu, Adaora; Sneed, Joel; Goldberg, Terry E; Devanand, Davangere P; Doraiswamy, P Murali (J Alzheimers Dis, 2023)
BACKGROUND: Mild cognitive impairment (MCI) represents a high risk group for Alzheimer's disease (AD). Computerized Cognitive Games Training (CCT) is an investigational strategy to improve targeted functions in MCI through the modulation of cognitive networks. OBJECTIVE: The goal of this study was to examine the effect of CCT versus a non-targeted active brain exercise on functional cognitive networks. METHODS: 107 patients with MCI were randomized to CCT or web-based crossword puzzles. Resting-state functional MRI (fMRI) was obtained at baseline and 18 months to evaluate differences in fMRI measured within- and between-network functional connectivity (FC) of the default mode network (DMN) and other large-scale brain networks: the executive control, salience, and sensorimotor networks. RESULTS: There were no differences between crosswords and games in the primary outcome, within-network DMN FC across all subjects. However, secondary analyses suggest differential effects on between-network connectivity involving the DMN and SLN, and within-network connectivity of the DMN in subjects with late MCI. Paradoxically, in both cases, there was a decrease in FC for games and an increase for the crosswords control (p < 0.05), accompanied by lesser cognitive decline in the crosswords group. CONCLUSION: Results do not support a differential impact on within-network DMN FC between games and crossword puzzle interventions. However, crossword puzzles might result in cognitively beneficial remodeling between the DMN and other networks in more severely impaired MCI subjects, parallel to the observed clinical benefits.
Keywords: Alzheimer Disease; Brain; Cognitive Dysfunction; Cognitive Training; Default Mode Network; Humans; Magnetic Resonance Imaging; Nerve Net

Impact of Hearing Aids on Progression of Cognitive Decline, Depression, and Quality of Life Among People with Cognitive Impairment and Dementia. - Atef, Roaa Zayed; Michalowsky, Bernhard; Raedke, Anika; Platen, Moritz; Mohr, Wiebke; Mühlichen, Franka; Thyrian, Jochen René; Hoffmann, Wolfgang (J Alzheimers Dis, 2023)
BACKGROUND: Hearing loss is common in people with dementia (PwD) and a modifiable risk factor for cognitive decline. Recent studies revealed that hearing loss could cause social isolation and depression, which is associated with health-related quality of life (HRQoL). However, there is a lack of knowledge about the impact of the utilization of hearing aids on these outcomes. OBJECTIVE: To assess whether hearing aids use might be positively associated with the progression of cognitive function, depression, and HRQoL among PwD. METHODS: We analyzed two-year follow-up data from 258 PwD (≥70 years, living at home). Cognitive decline was measured with Mini-Mental Status Examination (MMSE), depression using Geriatric Depression Scale (GDS), and HRQoL with Quality of Life in Alzheimer's Disease Scale (QoL-AD). The impact of hearing aid utilization on the progression of outcomes was assessed using multivariate regression models. RESULTS: 123 patients had hearing loss (47.7%), from which n = 54 (43.9%) used hearing aids. Patients with hearing loss were older and had a lower HRQoL than those without hearing loss. Use of hearing aids in patients with hearing loss was associated with a lower increase in depressive symptoms (b = -0.74, CI95 -1.48 --0.01, p = 0.047) over time as compared to those not using hearing aids. There was no effect on PwD's cognition, and the association with higher HRQoL was significant after one, but not consistently over two years. CONCLUSION: Early detection and intervention of presbycusis using hearing aids might improve mental health and HRQoL in dementia.
Keywords: Aged; Cognitive Dysfunction; Deafness; Dementia; Depression; Hearing Aids; Humans; Presbycusis; Quality of Life

Impact of the MIND Diet on Cognition in Individuals with Dementia. - Healy, Elizabeth (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) plagues 6.5 million Americans 65+, yet treatments are lacking. The Mediterranean-DASH Intervention for Neurodegenerative Delay (MIND) diet has been developed to address the expansive impact of dementias on the general public. This systematic review evaluated the impact of the MIND diet on cognition in those with pathologies across the dementia spectrum. OBJECTIVE: To evaluate the application of the MIND diet for prevention and/or treatment of dementia. METHODS: PubMed was used to conduct a search using the MIND diet and terms related to cognition. Articles were excluded if they were published prior to 2018, studied a population without dementia or significant risk factors, or did not include those 65 + . The overall quality of each source was analyzed based on the cognitive test(s) used, the selection of subjects, and the sample size. RESULTS: The search generated 33 papers, which yielded 11 articles after screening. Of these studies, one was conducted on those with mild cognitive impairment, one with AD, two with general dementia, and seven with at-risk individuals. All the studies found a positive correlation between adherence and some form of cognitive functioning, but results were mixed for specific cognitive domains. CONCLUSIONS: These findings suggest that the MIND diet may be a useful long-term treatment option for those with various dementia pathologies. However, more research is needed on subjects with onset dementias. Additionally, there is a need for more research into the mechanisms behind the common comorbidities.
Keywords: Alzheimer Disease; Cognition; Cognition Disorders; Cognitive Dysfunction; Diet, Mediterranean; Humans

Ketogenic Diet as a Promising Non-Drug Intervention for Alzheimer's Disease: Mechanisms and Clinical Implications. - Xu, Yunlong; Zheng, Fuxiang; Zhong, Qi; Zhu, Yingjie (J Alzheimers Dis, 2023)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder that is mainly characterized by cognitive deficits. Although many studies have been devoted to developing disease-modifying therapies, there has been no effective therapy until now. However, dietary interventions may be a potential strategy to treat AD. The ketogenic diet (KD) is a high-fat and low-carbohydrate diet with adequate protein. KD increases the levels of ketone bodies, providing an alternative energy source when there is not sufficient energy supply because of impaired glucose metabolism. Accumulating preclinical and clinical studies have shown that a KD is beneficial to AD. The potential underlying mechanisms include improved mitochondrial function, optimization of gut microbiota composition, and reduced neuroinflammation and oxidative stress. The review provides an update on clinical and preclinical research on the effects of KD or medium-chain triglyceride supplementation on symptoms and pathophysiology in AD. We also detail the potential mechanisms of KD, involving amyloid and tau proteins, neuroinflammation, gut microbiota, oxidative stress, and brain metabolism. We aimed to determine the function of the KD in AD and outline important aspects of the mechanism, providing a reference for the implementation of the KD as a potential therapeutic strategy for AD.
Keywords: Alzheimer Disease; Brain; Diet, Ketogenic; Humans; Ketone Bodies; Neuroinflammatory Diseases

Linking Air Pollution Exposure to Blood-Based Metabolic Features in a Community-Based Aging Cohort with and without Dementia. - Kalia, Vrinda; Kulick, Erin R; Vardarajan, Badri; Gu, Yian; Manly, Jennifer J; Elkind, Mitchell S V; Kaufman, Joel D; Jones, Dean P; Baccarelli, Andrea A; Mayeux, Richard; Kioumourtzoglou, Marianthi-Anna; Miller, Gary W (J Alzheimers Dis, 2023)
BACKGROUND: Long-term exposure to air pollution has been associated with changes in levels of metabolites measured in the peripheral blood. However, most research has been conducted in ethnically homogenous, young or middle-aged populations. OBJECTIVE: To study the relationship between the plasma metabolome and long-term exposure to three air pollutants: particulate matter (PM) less than 2.5μm in aerodynamic diameter (PM2.5), PM less than 10μm in aerodynamic diameter (PM10), and nitrogen dioxide (NO2) in an ethnically diverse, older population. METHODS: Plasma metabolomic profiles of 107 participants of the Washington Heights and Inwood Community Aging Project in New York City, collected from 1995-2015, including non-Hispanic white, Caribbean Hispanic, and non-Hispanic Black older adults were used. We estimated the association between each metabolic feature and predicted annual mean exposure to the air pollutants using three approaches: 1) A metabolome wide association study framework; 2) Feature selection using elastic net regression; and 3) A multivariate approach using partial-least squares discriminant analysis. RESULTS: 79 features associated with exposure to PM2.5 but none associated with PM10 or NO2. PM2.5 exposure was associated with altered amino acid metabolism, energy production, and oxidative stress response, pathways also associated with Alzheimer's disease. Three metabolites were associated with PM2.5 exposure through all three approaches: cysteinylglycine disulfide, a diglyceride, and a dicarboxylic acid. The relationship between several features and PM2.5 exposure was modified by diet and metabolic diseases. CONCLUSIONS: These relationships uncover the mechanisms through which PM2.5 exposure can lead to altered metabolic outcomes in an older population.
Keywords: Aged; Aging; Air Pollutants; Air Pollution; Dementia; Environmental Exposure; Humans; Nitrogen Dioxide; Particulate Matter

Lithium Provides Broad Therapeutic Benefits in an Alzheimer's Disease Mouse Model. - Wiseman, Alyssa L; Briggs, Clark A; Peritt, Ariel; Kapecki, Nicolas; Peterson, Daniel A; Shim, Seong S; Stutzmann, Grace E (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) is a chronic neurodegenerative disorder with a progressive loss of cognitive function. Currently, no effective treatment regimen is available. Lithium, a mood stabilizer for bipolar disorder, exerts broad neuroprotective and neurotrophic actions and improves cognitive function. OBJECTIVE: The study investigated if lithium stabilizes Ca2+ signaling abnormalities in hippocampal neurons and subsequently normalize downstream effects on AD neuropathology and synaptic plasticity in young AD mice. METHODS: Four-month-old 3xTg-AD mice were treated with a LiCl diet chow for 30 days. At the end of the lithium treatment, a combination of two-photon Ca2+ imaging, electrophysiology, and immunohistochemistry assays were used to assess the effects of the LiCl treatment on inositol trisphosphate receptor (IP3R)-dependent endoplasmic reticulum (ER) Ca2+ and voltage-gated Ca2+ channel (VGCC)-mediated Ca2+ signaling in CA1 neurons, neuronal nitric oxide synthase (nNOS) and hyperphosphorylated tau (p-tau) levels and synaptic plasticity in the hippocampus and overlying cortex from 3xTg-ADmice. RESULTS: Thirty-day LiCl treatment reduced aberrant IP3R-dependent ER Ca2+ and VGCC-mediated Ca2+ signaling in CA1 pyramidal neurons from 3xTg-AD mice and restored neuronal nitric oxide synthase (nNOS) and hyperphosphorylated tau (p-tau) levels to control levels in the hippocampal subfields and overlying cortex. The LiCl treatment enhanced post-tetanic potentiation (PTP), a form of short-term plasticity in the hippocampus. CONCLUSION: The study found that lithium exerts therapeutic effects across several AD-associated early neuronal signaling abnormalities including aberrant Ca2+ signaling, nNOS, and p-tau formation and enhances short-term synaptic plasticity. Lithium could serve as an effective treatment or co-therapeutic for AD.
Keywords: Alzheimer Disease; Animals; Calcium; Disease Models, Animal; Hippocampus; Lithium; Mice; Mice, Transgenic; Nitric Oxide Synthase Type I; tau Proteins

Malignant Brain Aging: The Formidable Link Between Dysregulated Signaling Through Mechanistic Target of Rapamycin Pathways and Alzheimer's Disease (Type 3 Diabetes). - de la Monte, Suzanne M (J Alzheimers Dis, 2023)
Malignant brain aging corresponds to accelerated age-related declines in brain functions eventually derailing the self-sustaining forces that govern independent vitality. Malignant brain aging establishes the path toward dementing neurodegeneration, including Alzheimer's disease (AD). The full spectrum of AD includes progressive dysfunction of neurons, oligodendrocytes, astrocytes, microglia, and the microvascular systems, and is mechanistically driven by insulin and insulin-like growth factor (IGF) deficiencies and resistances with accompanying deficits in energy balance, increased cellular stress, inflammation, and impaired perfusion, mimicking the core features of diabetes mellitus. The underlying pathophysiological derangements result in mitochondrial dysfunction, abnormal protein aggregation, increased oxidative and endoplasmic reticulum stress, aberrant autophagy, and abnormal post-translational modification of proteins, all of which are signature features of both AD and dysregulated insulin/IGF-1-mechanistic target of rapamycin (mTOR) signaling. This article connects the dots from benign to malignant aging to neurodegeneration by reviewing the salient pathologies associated with initially adaptive and later dysfunctional mTOR signaling in the brain. Effective therapeutic and preventive measures must be two-pronged and designed to 1) address complex and shifting impairments in mTOR signaling through the re-purpose of effective anti-diabetes therapeutics that target the brain, and 2) minimize the impact of extrinsic mediators of benign to malignant aging transitions, e.g., inflammatory states, obesity, systemic insulin resistance diseases, and repeated bouts of general anesthesia, by minimizing exposures or implementing neuroprotective measures.
Keywords: Alzheimer Disease; Brain; Diabetes Mellitus; Humans; Insulin; Sirolimus; TOR Serine-Threonine Kinases

Mild Cognitive Impairment is Associated with Poorer Everyday Decision Making. - Fenton, Laura; Han, S Duke; DiGuiseppi, Carolyn G; Fowler, Nicole R; Hill, Linda; Johnson, Rachel L; Peterson, Ryan A; Knoepke, Christopher E; Matlock, Daniel D; Moran, Ryan; Karlawish, Jason; Betz, Marian E (J Alzheimers Dis, 2023)
BACKGROUND: Older adults are faced with many unique and highly consequential decisions such as those related to finances, healthcare, and everyday functioning (e.g., driving cessation). Given the significant impact of these decisions on independence, wellbeing, and safety, an understanding of how cognitive impairment may impact decision making in older age is important. OBJECTIVE: To examine the impact of mild cognitive impairment (MCI) on responses to a modified version of the Short Portable Assessment of Capacity for Everyday Decision making (SPACED). METHODS: Participants were community-dwelling, actively driving older adults (N = 301; M age = 77.1 years, SD = 5.1; 69.4% with a college degree or higher; 51.2% female; 95.3% White) enrolled in the Advancing Understanding of Transportation Options (AUTO) study. A generalized linear model adjusted for age, education, sex, randomization group, cognitive assessment method, and study site was used to examine the relationship between MCI status and decision making. RESULTS: MCI status was associated with poorer decision making; participants with MCI missed an average of 2.17 times more points on the SPACED than those without MCI (adjusted mean ratio: 2.17, 95% CI: 1.02, 4.61, p = 0.044). CONCLUSION: This finding supports the idea that older adults with MCI exhibit poorer decision-making abilities than cognitively normal older adults. It also suggests that older adults with MCI may exhibit poorer decision making across a wide range of decision contexts.
Keywords: Aged; Cognitive Dysfunction; Decision Making; Delivery of Health Care; Educational Status; Female; Humans; Independent Living; Male

Mindfulness Prevents Depression and Psychopathology in Elderly People with Mild to Moderate Alzheimer's Disease: A Randomized Clinical Trial. - Quintana-Hernández, Domingo J; Rojas-Hernández, Jaime; Santana-Del Pino, Angelo; Céspedes Suárez, Carmen; Pellejero Silva, Mónica; Miró-Barrachina, María Teresa; Ibáñez Fernández, Ignacio; Estupiñán López, José Antonio; Borkel, Lucas F (J Alzheimers Dis, 2023)
BACKGROUND: This longitudinal study addressed whether mindfulness practice prevents psychological and behavioral symptoms, especially mood disorders, in Alzheimer's disease (AD). OBJECTIVE: To assess the incidence of depression in the course of AD and to determine which non-pharmacological treatment (NPT) is most effective in preventing psychopathological symptoms. METHODS: We conducted a longitudinal, non-inferiority and equivalence randomized clinical trial, repeated-measures design, with a control group and three experimental treatments: mindfulness, cognitive stimulation, and relaxation. Each experimental group performed three weekly sessions for two years. The pharmacological treatment of all participants was donepezil (10 mg). Participants were patients with probable AD without diagnosed depression from the public neurology services of the Canary Health Service, Spain. Psychological evaluation was performed using the Geriatric Depression Scale (GDS), Hamilton Depression Rating Scale (HDRS), and Neuropsychiatric Inventory (NPI-Q). The statistical analysis included only patients who attended at least 75% of the sessions. A nonparametric, repeated-measures analysis was performed with Kruskal-Wallis H test and between-group differences with Mann-Whitney U test with Bonferroni correction (p < 0.008). Effect size was calculated with partial eta-squared. RESULTS: The results showed significant differences with large effect sizes (η2p>0.14) between mindfulness and the rest of the experimental groups as well as the control in the GDS, HDRS, and NPI-Q scales. CONCLUSION: Compared to the other experimental groups, only mindfulness prevented the onset of depression and other psychopathologies in early-stage AD. Based on its effectiveness in maintaining cognitive functions and preventing psychopathology, we recommend mindfulness as the first-choice NPT for mild to moderate AD.
Keywords: Aged; Alzheimer Disease; Depression; Donepezil; Humans; Longitudinal Studies; Mindfulness

miRNAs and Stem Cells as Promising Diagnostic and Therapeutic Targets for Alzheimer's Disease. - Elzayat, Emad M; Shahien, Sherif A; El-Sherif, Ahmed A; Hosney, Mohamed (J Alzheimers Dis, 2023)
Alzheimer's disease (AD) is a cumulative progressive neurodegenerative disease characterized mainly by impairment in cognitive functions accompanied by memory loss, disturbance in behavior and personality, and difficulties in learning. Although the main causes of AD pathogenesis are not fully understood yet, amyloid-β peptides and tau proteins are supposed to be responsible for AD onset and pathogenesis. Various demographic, genetic, and environmental risk factors are involved in AD onset and pathogenesis such as age, gender, several genes, lipids, malnutrition, and poor diet. Significant changes were observed in microRNA (miRNA) levels between normal and AD cases giving hope for a diagnostic procedure for AD through a simple blood test. As yet, only two classes of AD therapeutic drugs are approved by FDA. They are classified as acetylcholinesterase inhibitors and N-methyl-D-aspartate antagonists (NMDA). Unfortunately, they can only treat the symptoms but cannot cure AD or stop its progression. New therapeutic approaches were developed for AD treatment including acitretin due to its ability to cross blood-brain barrier in the brain of rats and mice and induce the expression of ADAM 10 gene, the α-secretase of human amyloid-β protein precursor, stimulating the non-amyloidogenic pathway for amyloid-β protein precursor processing resulting in amyloid-β reduction. Also stem cells may have a crucial role in AD treatment as they can improve cognitive functions and memory in AD rats through regeneration of damaged neurons. This review spotlights on promising diagnostic techniques such as miRNAs and therapeutic approaches such as acitretin and/or stem cells keeping in consideration AD pathogenesis, stages, symptoms, and risk factors.
Keywords: Acitretin; Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Disease Susceptibility; Humans; MicroRNAs; Stem Cell Transplantation; Stem Cells

Mitochondria Profoundly Influence Apolipoprotein E Biology. - Gabrielli, Alexander P; Weidling, Ian; Ranjan, Amol; Wang, Xiaowan; Novikova, Lesya; Chowdhury, Subir Roy; Menta, Blaise; Berkowicz, Alexandra; Wilkins, Heather M; Peterson, Kenneth R; Swerdlow, Russell H (J Alzheimers Dis, 2023)
BACKGROUND: Mitochondria can trigger Alzheimer's disease (AD)-associated molecular phenomena, but how mitochondria impact apolipoprotein E (APOE; apoE) is not well known. OBJECTIVE: Consider whether and how mitochondrial biology influences APOE and apoE biology. METHODS: We measured APOE expression in human SH-SY5Y neuronal cells with different forms of mitochondrial dysfunction including total, chronic mitochondrial DNA (mtDNA) depletion (ρ0 cells); acute, partial mtDNA depletion; and toxin-induced mitochondrial dysfunction. We further assessed intracellular and secreted apoE protein levels in the ρ0 cells and interrogated the impact of transcription factors and stress signaling pathways known to influence APOE expression. RESULTS: SH-SY5Y ρ0 cells exhibited a 65-fold increase in APOE mRNA, an 8-fold increase in secreted apoE protein, and increased intracellular apoE protein. Other models of primary mitochondrial dysfunction including partial mtDNA-depletion, toxin-induced respiratory chain inhibition, and chemical-induced manipulations of the mitochondrial membrane potential similarly increased SH-SY5Y cell APOE mRNA. We explored potential mediators and found in the ρ0 cells knock-down of the C/EBPα and NFE2L2 (Nrf2) transcription factors reduced APOE mRNA. The activity of two mitogen-activated protein kinases, JNK and ERK, also strongly influenced ρ0 cell APOE mRNA levels. CONCLUSION: Primary mitochondrial dysfunction either directly or indirectly activates APOE expression in a neuronal cell model by altering transcription factors and stress signaling pathways. These studies demonstrate mitochondrial biology can influence the biology of the APOE gene and apoE protein, which are implicated in AD.
Keywords: Alzheimer Disease; Apolipoproteins E; Biology; Cell Line, Tumor; DNA, Mitochondrial; Humans; Mitochondria; Neuroblastoma; RNA, Messenger; Transcription Factors

Mortality Risks and Causes of Death by Dementia Types in a Japanese Cohort with Dementia: NCGG-STORIES. - Ono, Rei; Sakurai, Takashi; Sugimoto, Taiki; Uchida, Kazuaki; Nakagawa, Takeshi; Noguchi, Taiji; Komatsu, Ayane; Arai, Hidenori; Saito, Tami (J Alzheimers Dis, 2023)
BACKGROUND: Prognosis-related information regarding dementia needs to be updated, as changes in medical and long-term care environments for patients with dementia in recent decades may be improving the prognosis of the disease. OBJECTIVE: We aimed to investigate the mortality, cause of death, and prognostic factors by types of dementia in a Japanese clinic-based cohort. METHODS: The National Center for Geriatrics and Gerontology-Life Stories of People with Dementia consists of clinical records and prognostic data of patients who visited the Memory Clinic in Japan. Patients who attended the clinic between July 2010 and September 2018, or their close relatives, were asked about death information via a postal survey. A cohort of 3,229 patients (mean age, 76.9; female, 1,953) was classified into six groups: normal cognition (NC), mild cognitive impairment (MCI), Alzheimer's disease (AD), vascular dementia, dementia with Lewy bodies (DLB), and frontotemporal lobar degeneration. A Cox proportional hazards model was employed to compare the mortality of each type of dementia, MCI, and NC. RESULTS: Patients with all types of dementia and MCI had higher mortality rates than those with NC (hazard risks: 2.61-5.20). The most common cause of death was pneumonia, followed by cancer. In the MCI, AD, and DLB groups, older age, male sex, and low cognitive function were common prognostic factors but not presence of apolipoprotein E ɛ4 allele. CONCLUSION: Our findings suggest important differences in the mortality risk and cause of death among patients with dementia, which will be useful in advanced care planning and policymaking.
Keywords: Aged; Alzheimer Disease; Cause of Death; Cognitive Dysfunction; Dementia; East Asian People; Female; Humans; Lewy Body Disease; Male

Neural Stem Cells in the Treatment of Alzheimer's Disease: Current Status, Challenges, and Future Prospects. - Chen, Xiaokun; Jiang, Shenzhong; Wang, Renzhi; Bao, Xinjie; Li, Yongning (J Alzheimers Dis, 2023)
Alzheimer's disease (AD), a progressive dementia, is one of the world's most dangerous and debilitating diseases. Clinical trial results of amyloid-β (Aβ) and tau regulators based on the pretext of straightforward amyloid and tau immunotherapy were disappointing. There are currently no effective strategies for slowing the progression of AD. Further understanding of the mechanisms underlying AD and the development of novel therapeutic options are critical. Neurogenesis is impaired in AD, which contributes to memory deficits. Transplanted neural stem cells (NSCs) can regenerate degraded cholinergic neurons, and new neurons derived from NSCs can form synaptic connections with neighboring neurons. In theory, employing NSCs to replace and restore damaged cholinergic neurons and brain connections may offer new treatment options for AD. However there remain barriers to surmount before NSC-based therapy can be used clinically. The objective of this article is to describe recent advances in the treatment of AD models and clinical trials involving NSCs. In addition, we discuss the challenges and prospects associated with cell transplant therapy for AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Cholinergic Neurons; Disease Models, Animal; Humans; Neural Stem Cells

Non-Pharmacological Interventions for Feeding and Eating Disorders in Persons with Dementia: Systematic Review and Evidence Summary. - Chen, Hong-Li; Li, Cheng; Wang, Jing; Fei, Yang; Min, Min; Zhao, Yue; Shan, En-Fang; Yin, Yue-Heng; Liu, Chong-Yuan; Li, Xian-Wen (J Alzheimers Dis, 2023)
BACKGROUND: Feeding and eating disorders related to cognitive and psycho-behavioral symptoms are strongly associated with health status in persons with dementia (PWD). Non-pharmacological interventions have been the priority selection to address this significant issue. However, the direct targets of non-pharmacological interventions are unclear and there is no consistent evidence of recommendations on the intervention of different dementia stages and the settings of intervention practice. OBJECTIVE: To provide caregivers with a set of self-help non-pharmacological interventions for feeding and eating disorders in PWD. METHODS: Based on the process of evidence summary, a systematic literature search was performed on dementia websites and seven databases. Two researchers screened the studies independently and appraise the quality. The evidence was graded by Joanna Briggs Institute Grades of Recommendation. RESULTS: Twenty-eight articles were included. Twenty-three non-pharmacological intervention recommendations were categorized into six themes containing oral nutritional supplementation, assistance with eating and drinking, person-centered mealtime care, environmental modification, education or training, and multi-component intervention. These interventions corresponded to three direct targets including improving engagement, making up for loss ability, and increasing food intake directly. They were applied to different stages of dementia and most interventions were targeted at PWD in long-term care institutions. CONCLUSION: This article summarized the direct targets and the specific implementation of recommendations at different stages of dementia to provide caregivers with self-help non-pharmacological interventions. The practice of recommendations was more applicable to institutionalized PWD. When applied to PWD at home, caregivers need to identify the specific feeding and eating conditions at different stages and adopted the interventions in conjunction with the wishes of the PWD and professional advice.
Keywords: Caregivers; Dementia; Feeding and Eating Disorders; Health Status; Humans; Nutritional Status

Observed Improvement in Cognition During a Personalized Lifestyle Intervention in People with Cognitive Decline. - Sandison, Heather; Callan, Nini G L; Rao, Rammohan V; Phipps, John; Bradley, Ryan (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) is a chronic condition marked by progressive objective cognitive impairment (OCI). No monotherapy has substantially altered disease progression, suggesting the disease is multifactorial and may require a multimodal therapeutic approach. OBJECTIVE: We sought to determine if cognitive function in a sample with OCI would change in response to a multimodal, individualized care plan based on potential contributors to cognitive decline (e.g., nutritional status, infection, etc.). METHODS: Participants (n = 34) were recruited from the San Diego, CA area. The multimodal intervention included lifestyle changes (i.e., movement, diet, and stress management), nutraceutical support, and medications. It was delivered pragmatically over four clinical visits, and outcome measures were gathered at four study visits, occurring at baseline, one, three, and six months (primary endpoint). Study participants received weekly phone calls for nutrition support throughout study participation. Outcome measures included the Cambridge Brain Sciences (CBS) battery, and the Montreal Cognitive Assessment (MoCA). RESULTS: At 6 months, mean MoCA scores improved from 19.6±3.1 to 21.7±6.2 (p = 0.013). Significant improvement was observed in mean scores of the CBS memory domain [25.2 (SD 23.3) to 35.8 (SD 26.9); p < 0.01] and CBS overall composite cognition score [24.5 (SD 16.1) to 29.7 (SD 20.5); p = 0.02]. All CBS domains improved. CONCLUSION: Multiple measures of cognitive function improved after six months of intervention. Our results support the feasibility and impact of a multimodal, individualized treatment approach to OCI, warranting further research.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; California; Cognition; Cognitive Dysfunction; Diet, Healthy; Dietary Supplements; Disease Progression; Exercise; Feasibility Studies; Female; Healthy Lifestyle; Humans; Infections; Male; Memory; Middle Aged; Nutritional Status; Pragmatic Clinical Trials as Topic; Reproducibility of Results; Stress, Psychological; Time Factors; Treatment Outcome; Verbal Behavior

Pathogenesis, Animal Models, and Drug Discovery of Alzheimer's Disease. - Xia, Zhao-Di; Ma, Ruo-Xin; Wen, Jin-Feng; Zhai, Yu-Fei; Wang, Yu-Qi; Wang, Feng-Yun; Liu, Dan; Zhao, Xiao-Long; Sun, Bao; Jia, Pu; Zheng, Xiao-Hui (J Alzheimers Dis, 2023)
Alzheimer's disease (AD), the most common cause of dementia, is a chronic neurodegenerative disease induced by multiple factors. The high incidence and the aging of the global population make it a growing global health concern with huge implications for individuals and society. The clinical manifestations are progressive cognitive dysfunction and lack of behavioral ability, which not only seriously affect the health and quality of life of the elderly, but also bring a heavy burden to the family and society. Unfortunately, almost all the drugs targeting the classical pathogenesis have not achieved satisfactory clinical effects in the past two decades. Therefore, the present review provides more novel ideas on the complex pathophysiological mechanisms of AD, including classical pathogenesis and a variety of possible pathogenesis that have been proposed in recent years. It will be helpful to find out the key target and the effect pathway of potential drugs and mechanisms for the prevention and treatment of AD. In addition, the common animal models in AD research are outlined and we examine their prospect for the future. Finally, Phase I, II, III, and IV randomized clinical trials or on the market of drugs for AD treatment were searched in online databases (Drug Bank Online 5.0, the U.S. National Library of Medicine, and Alzforum). Therefore, this review may also provide useful information in the research and development of new AD-based drugs.
Keywords: Alzheimer Disease; Animals; Drug Discovery; Models, Animal; Neurodegenerative Diseases; Quality of Life

Pathogenomic Signature and Aberrant Neurogenic Events in Experimental Cerebral Ischemic Stroke: A Neurotranscriptomic-Based Implication for Dementia. - Roshan, Syed Aasish; Elangovan, Gayathri; Gunaseelan, Dharani; Jayachandran, Swaminathan K; Kandasamy, Mahesh; Anusuyadevi, Muthuswamy (J Alzheimers Dis, 2023)
BACKGROUND: Cerebral ischemic stroke is caused due to neurovascular damage or thrombosis, leading to neuronal dysfunction, neuroinflammation, neurodegeneration, and regenerative failure responsible for neurological deficits and dementia. The valid therapeutic targets against cerebral stroke remain obscure. Thus, insight into neuropathomechanisms resulting from the aberrant expression of genes appears to be crucial. OBJECTIVE: In this study, we have elucidated how neurogenesis-related genes are altered in experimental stroke brains from the available transcriptome profiles in correlation with transcriptome profiles of human postmortem stroke brain tissues. METHODS: The transcriptome datasets available on the middle cerebral artery occlusion (MCAo) rat brains were obtained from the Gene Expression Omnibus, National Center for Biotechnology Information. Of the available datasets, 97 samples were subjected to the meta-analysis using the network analyst tool followed by Cytoscape-based enrichment mapping analysis. The key differentially expressed genes (DEGs) were validated and compared with transcriptome profiling of human stroke brains. RESULTS: Results revealed 939 genes are differently expressed in the brains of the MCAo rat model of stroke, in which 30 genes are key markers of neural stem cells, and regulators of neurogenic processes. Its convergence with DEGs from human stroke brains has revealed common targets. CONCLUSION: This study has established a panel of highly important DEGs to signify the potential therapeutic targets for neuroregenerative strategy against pathogenic events associated with cerebral stroke. The outcome of the findings can be translated to mitigate neuroregeneration failure seen in various neurological and metabolic disease manifestations with neurocognitive impairments.
Keywords: Animals; Brain; Dementia; Humans; Infarction, Middle Cerebral Artery; Ischemic Stroke; Neurogenesis; Rats; Stroke

PM2.5 and Dementia in a Low Exposure Setting: The Influence of Odor Identification Ability and APOE. - Andersson, John; Sundström, Anna; Nordin, Maria; Segersson, David; Forsberg, Bertil; Adolfsson, Rolf; Oudin, Anna (J Alzheimers Dis, 2023)
BACKGROUND: Growing evidence show that long term exposure to air pollution increases the risk of dementia. OBJECTIVE: The aim of this study was to investigate associations between PM2.5 exposure and dementia in a low exposure area, and to investigate the role of olfaction and the APOE ɛ4 allele in these associations. METHODS: Data were drawn from the Betula project, a longitudinal study on aging, memory, and dementia in Sweden. Odor identification ability was assessed using the Scandinavian Odor Identification Test (SOIT). Annual mean PM2.5 concentrations were obtained from a dispersion-model and matched at the participants' residential address. Proportional hazard regression was used to calculate hazard ratios. RESULTS: Of 1,846 participants, 348 developed dementia during the 21-year follow-up period. The average annual mean PM2.5 exposure at baseline was 6.77μg/m3, which is 1.77μg/m3 above the WHO definition of clean air. In a fully adjusted model (adjusted for age, sex, APOE, SOIT, cardiovascular diseases and risk factors, and education) each 1μg/m3 difference in annual mean PM2.5-concentration was associated with a hazard ratio of 1.23 for dementia (95% CI: 1.01-1.50). Analyses stratified by APOE status (ɛ4 carriers versus non-carriers), and odor identification ability (high versus low), showed associations only for ɛ4 carriers, and for low performance on odor identification ability. CONCLUSION: PM2.5 was associated with an increased risk of dementia in this low pollution setting. The associations between PM2.5 and dementia seemed stronger in APOE carriers and those with below average odor identification ability.
Keywords: Air Pollutants; Air Pollution; Apolipoproteins E; Cohort Studies; Dementia; Environmental Exposure; Humans; Longitudinal Studies; Odorants; Particulate Matter

Poor Oral Health as a Risk Factor for Dementia in a Swedish Population: A Cohort Study with 40 Years of Follow-Up. - He, Fei; Luo, Huizi; Yin, Li; Roosaar, Ann; Axéll, Tony; Zhao, Hongwei; Ye, Weimin (J Alzheimers Dis, 2023)
BACKGROUND: Whether poor oral health is associated with dementia risk remains unclear. OBJECTIVE: We conducted a cohort study of 14,439 participants who were followed up for up to 40 years in Uppsala County, central Sweden, aiming to explore the association between poor oral health, namely the number of tooth loss, dental plaque status, and oral mucosal lesions, and the risk of dementia. METHODS: We used Cox proportional hazards regression model to derive cause-specific hazard ratios (HR) and corresponding 95% confidence intervals (CI), while adjusting for baseline potential confounders as well as a time-varying covariate, Charlson's Comorbidity Index score. RESULTS: Dementia risk was substantially higher among those with a higher number of tooth loss; compared to the group with tooth loss 0-10, the HRs were 1.21 (95% CI: 1.02, 1.42), 1.17 (95% CI: 0.97, 1.40), and 1.30 (95% CI: 1.09, 1.54) respectively for groups with increasing number of tooth loss. There was some evidence of dose-risk association in this study, with a HR of 1.10 (1.04, 1.18) comparing adjacent groups (ptrend = 0.001). In a stratified analysis by attained age, tooth loss was more pronouncedly associated with the risk of dementia onset before age 80 (those with 21-32 versus 0-10 lost teeth, HR = 1.82, (95% CI: 1.32, 2.51); HR = 1.22 (95% CI: 1.10, 1.35) comparing adjacent groups, ptrend < 0.001). CONCLUSION: In summary, there are some indications that poor oral health, as indicated by more tooth loss, is positively associated with an increased risk of dementia, especially for dementia onset before age 80.
Keywords: Aged, 80 and over; Cohort Studies; Dementia; Follow-Up Studies; Humans; Oral Health; Risk Factors; Sweden; Tooth Loss

Psychopharmacological Medication Use in Frontotemporal Dementia at the Time of Diagnosis: Comparison with Alzheimer's Disease. - Katisko, Kasper; Krüger, Johanna; Soppela, Helmi; Hartikainen, Päivi; Haapasalo, Annakaisa; Remes, Anne M; Solje, Eino (J Alzheimers Dis, 2023)
BACKGROUND: Due to the significant presence of neuropsychiatric symptoms in patients with frontotemporal dementia (FTD) spectrum disorders, psychiatric misdiagnoses, diagnostic delay, and use of psychiatric treatments are common prior to the FTD diagnosis. Furthermore, treatment of diagnosed FTD patients mainly relies on off-label psychopharmacological approaches. Currently, limited real-world data are available regarding the actual use of psychopharmacological medications in FTD. OBJECTIVE: To evaluate psychopharmacological medication use at the time of FTD diagnosis. METHODS: Psychopharmacological medication use was evaluated in a Finnish FTD cohort containing 222 FTD patients, including the major clinical disease phenotypes (behavioral, language, and motor variants) and genetic patients carrying the C9orf72 repeat expansion. A cohort of 214 Alzheimer's disease (AD) patients was used as a neurodegenerative disease reference group. RESULTS: Active use of psychopharmacological medications at the time of diagnosis was significantly more common in FTD compared to AD, especially in the case of antidepressants (26.1% versus 15.0%, OR = 2.01, p = 0.008), antipsychotics (23.9% versus 9.3%, OR = 3.15, p < 0.001), and mood-stabilizers (6.3% versus 1.9%, OR = 2.93, p = 0.085; not statistically significant), whereas the use of cholinesterase inhibitors or memantine was nearly nonexistent in FTD patients. Female gender and behavioral variant of FTD phenotype alongside with depressive and psychotic symptoms were the most prominent factors associating with the use of these medications among the FTD spectrum patients. CONCLUSION: Use of off-label psychopharmacological medication and polypharmacy is substantially common at the time of FTD diagnosis. This likely reflects the challenges in using symptom-driven treatment approaches, especially prior to the eventual diagnosis.
Keywords: Alzheimer Disease; Delayed Diagnosis; Female; Frontotemporal Dementia; Humans; Memantine; Neurodegenerative Diseases

The Role of Interferon-α in Neurodegenerative Diseases: A Systematic Review. - Hui, Brendan Su Mee; Zhi, Lee Rui; Retinasamy, Thaarvena; Arulsamy, Alina; Law, Christine Shing Wei; Shaikh, Mohd Farooq; Yeong, Keng Yoon (J Alzheimers Dis, 2023)
BACKGROUND: Neurodegenerative diseases (NDs) impose significant financial and healthcare burden on populations all over the world. The prevalence and incidence of NDs have been observed to increase dramatically with age. Hence, the number of reported cases is projected to increase in the future, as life spans continues to rise. Despite this, there is limited effective treatment against most NDs. Interferons (IFNs), a family of cytokines, have been suggested as a promising therapeutic target for NDs, particularly IFN-α, which governs various pathological pathways in different NDs. OBJECTIVE: This systematic review aimed to critically appraise the currently available literature on the pathological role of IFN-α in neurodegeneration/NDs. METHODS: Three databases, Scopus, PubMed, and Ovid Medline, were utilized for the literature search. RESULTS: A total of 77 journal articles were selected for critical evaluation, based on the inclusion and exclusion criteria. The studies selected and elucidated in this current systematic review have showed that IFN-α may play a deleterious role in neurodegenerative diseases through its strong association with the inflammatory processes resulting in mainly neurocognitive impairments. IFN-α may be displaying its neurotoxic function via various mechanisms such as abnormal calcium mineralization, activation of STAT1-dependent mechanisms, and increased quinolinic acid production. CONCLUSION: The exact role IFN-α in these neurodegenerative diseases have yet to be determine due to a lack in more recent evidence, thereby creating a variability in the role of IFN-α. Future investigations should thus be conducted, so that the role played by IFN-α in neurodegenerative diseases could be delineated.
Keywords: Cytokines; Databases, Factual; Humans; Interferon-alpha; Neurodegenerative Diseases

Safety, Feasibility, and Potential Clinical Efficacy of 40 Hz Invisible Spectral Flicker versus Placebo in Patients with Mild-to-Moderate Alzheimer's Disease: A Randomized, Placebo-Controlled, Double-Blinded, Pilot Study. - Agger, Mikkel Pejstrup; Danielsen, Else Rubæk; Carstensen, Marcus Schultz; Nguyen, N Mai; Horning, Maibritt; Henney, Mark Alexander; Jensen, Christopher Boe Ravn; Baandrup, Anders Ohlhues; Kjær, Troels Wesenberg; Madsen, Kristoffer Hougaard; Miskowiak, Kamilla; Petersen, Paul Michael; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Recent studies suggested induction of 40 Hz neural activity as a potential treatment for Alzheimer's disease (AD). However, prolonged exposure to flickering light raises adherence and safety concerns, encouraging investigation of tolerable light stimulation protocols. OBJECTIVE: To investigate the safety, feasibility, and exploratory measures of efficacy. METHODS: This two-stage randomized placebo-controlled double-blinded clinical trial, recruited first cognitive healthy participants (n = 3/2 active/placebo), and subsequently patients with mild-to-moderate AD (n = 5/6, active/placebo). Participants were randomized 1:1 to receive either active intervention with 40 Hz Invisible Spectral Flicker (ISF) or placebo intervention with color and intensity matched non-flickering white light. RESULTS: Few and mild adverse events were observed. Adherence was above 86.1% of intended treatment days, with participants remaining in front of the device for >51.3 min (60 max) and directed gaze >34.9 min. Secondary outcomes of cognition indicate a tendency towards improvement in the active group compared to placebo (mean: -2.6/1.5, SD: 6.58/6.53, active/placebo) at week 6. Changes in hippocampal and ventricular volume also showed no tendency of improvement in the active group at week 6 compared to placebo. At week 12, a potential delayed effect of the intervention was seen on the volume of the hippocampus in the active group compared to placebo (mean: 0.34/-2.03, SD: 3.26/1.18, active/placebo), and the ventricular volume active group (mean: -0.36/2.50, SD: 1.89/2.05, active/placebo), compared to placebo. CONCLUSION: Treatment with 40 Hz ISF offers no significant safety or adherence concerns. Potential impact on secondary outcomes must be tested in larger scale clinical trials.
Keywords: Alzheimer Disease; Cognition; Double-Blind Method; Feasibility Studies; Humans; Pilot Projects; Treatment Outcome

5-Hydroxymethylcytosine Signatures in Circulating Cell-Free DNA as Diagnostic Biomarkers for Late-Onset Alzheimer's Disease. - Chen, Lei; Shen, Qianqian; Xu, Shunliang; Yu, Hongzhuan; Pei, Shengjie; Zhang, Yangting; He, Xin; Wang, QiuZhen; Li, Duo (J Alzheimers Dis, 2022)
BACKGROUND: 5-Hydroxymethylcytosine (5hmC) is an epigenetic DNA modification that is highly abundant in central nervous system. It has been reported that DNA 5hmC dysregulation play a critical role in Alzheimer's disease (AD) pathology. Changes in 5hmC signatures can be detected in circulating cell-free DNA (cfDNA), which has shown potential as a non-invasive liquid biopsy material. OBJECTIVE: However, the genome-wide profiling of 5hmC in cfDNA and its potential for the diagnosis of AD has not been reported to date. METHODS: We carried out a case-control study and used a genome-wide chemical capture followed by high-throughput sequencing to detect the genome-wide profiles of 5hmC in human cfDNA and identified differentially hydroxymethylated regions (DhMRs) in late-onset AD patients and the control. RESULTS: We discovered significant differences of 5hmC enrichment in gene bodies which were linked to multiple AD pathogenesis-associated signaling pathways in AD patients compared with cognitively normal controls, indicating they can be well distinguished from normal controls by DhMRs in cfDNA. Specially, we identified 7 distinct genes (RABEP1, CPNE4, DNAJC15, REEP3, ROR1, CAMK1D, and RBFOX1) with predicting diagnostic potential based on their significant correlations with MMSE and MoCA scores of subjects. CONCLUSION: The present results suggest that 5hmC markers derived from plasma cfDNA can served as an effective, minimally invasive biomarkers for clinical auxiliary diagnosis of late-onset AD.
Keywords: 5-Methylcytosine; Aged; Alzheimer Disease; Biomarkers; Case-Control Studies; Cell-Free Nucleic Acids; DNA Methylation; DNA, Neoplasm; Epigenesis, Genetic; Female; High-Throughput Nucleotide Sequencing; Humans; Male; Middle Aged

Alteration of Gut Microbiota in Alzheimer's Disease and Their Relation to the Cognitive Impairment. - Khedr, Eman M; Omeran, Nehad; Karam-Allah Ramadan, Haidi; Ahmed, Gellan K; Abdelwarith, Ahmed M (J Alzheimers Dis, 2022)
BACKGROUND: Dysbiosis of gut microbiota has been reported to be enrolled in the pathogenesis of Alzheimer's disease (AD). However, there is a lack of relevant studies on this topic in Egyptian patients with AD. OBJECTIVE: To investigate different species of gut microbiota in Egyptian patients with AD and correlate microbiota bacterial abundance with clinical data. METHODS: The study included 25 patients with AD and 25 healthy volunteers as age and sex-matched controls. Clinical data was taken for each patient, including medical history and examination; Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) were assessed for each participant. Bacterial DNA was extracted from stool, and abundance quantified via qPCR using 16S rRNA group-specific primers. RESULTS: Akkermansia, Enterobacteria, Bacteroidetes, Bacillus cereus, Prevotella, and Clostridium cluster IV were more abundant in the AD group than in the control group, although there was significantly less abundance of Bifidobacterium spp., Firmicutes, and Actinobacteria in patients with AD than in controls, whereas no such significance was found for lactic acid bacteria between both groups. Lactic acid bacteria and Prevotella abundance was negatively correlated with cognitive impairment (p = 0.03 with MMSE, and p = 0.03 with MoCA). Prevotella abundance was positively correlated with age of onset and duration of illness and negatively correlated with smoking and coronary heart disease (p = 0.007, p = 0.03, p = 0.035, and p = 0.047, respectively). CONCLUSION: The current work highlighted a significant relationship between AD and gut microbiota dysbiosis. A higher abundance of Prevotella species and lactic acid bacteria was correlated with cognition.
Keywords: Alzheimer Disease; Bacteria; Cognitive Dysfunction; Dysbiosis; Gastrointestinal Microbiome; Humans; RNA, Ribosomal, 16S

Analysis and Identification Genetic Effect of SARS-CoV-2 Infections to Alzheimer's Disease Patients by Integrated Bioinformatics. - Wang, Fang; Xu, Jia; Xu, Shu-Jun; Guo, Jie-Jie; Wang, Feiming; Wang, Qin-Wen (J Alzheimers Dis, 2022)
BACKGROUND: COVID-19 pandemic is a global crisis which results in millions of deaths and causes long-term neurological sequelae, such as Alzheimer's disease (AD). OBJECTIVE: We aimed to explore the interaction between COVID-19 and AD by integrating bioinformatics to find the biomarkers which lead to AD occurrence and development with COVID-19 and provide early intervention. METHODS: The differential expressed genes (DEGs) were found by GSE147507 and GSE132903, respectively. The common genes between COVID-19 and AD were identified. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and protein-protein interactions (PPI) network analysis were carried out. Hub genes were found by cytoscape. A multivariate logistic regression model was constructed. NetworkAnalyst was used for the analysis of TF-gene interactions, TF-miRNA coregulatory network, and Protein-chemical Interactions. RESULTS: Forty common DEGs for AD and COVID-19 were found. GO and KEGG analysis indicated that the DEGs were enriched in the calcium signal pathway and other pathways. A PPI network was constructed, and 5 hub genes were identified (ITPR1, ITPR3, ITPKB, RAPGEF3, MFGE8). Four hub genes (ITPR1, ITPR3, ITPKB, RAPGEF3) which were considered as important factors in the development of AD that were affected by COVID-19 were shown by nomogram. Utilizing NetworkAnalyst, the interaction network of 4 hub genes and TF, miRNA, common AD risk genes, and known compounds is displayed, respectively. CONCLUSION: COVID-19 patients are at high risk of developing AD. Vaccination is required. Four hub genes can be considered as biomarkers for prediction and treatment of AD development caused by COVID-19. Compounds with neuroprotective effects can be used as adjuvant therapy for COVID-19 patients.
Keywords: Alzheimer Disease; Computational Biology; COVID-19; Databases, Genetic; Gene Expression Profiling; Humans; Protein Interaction Maps; SARS-CoV-2

Antihypertensive Medication Class and the Risk of Dementia and Cognitive Decline in Older Adults: A Secondary Analysis of the Prospective HELIAD Cohort. - Liampas, Ioannis; Hatzimanolis, Alex; Siokas, Vasileios; Yannakoulia, Mary; Kosmidis, Mary H; Sakka, Paraskevi; Hadjigeorgiou, Georgios M; Scarmeas, Nikolaos; Dardiotis, Efthimios (J Alzheimers Dis, 2022)
BACKGROUND: It is unclear whether the main antihypertensive medication classes (diuretics, calcium channel blockers, beta-blockers, angiotensin converting enzyme inhibitors, and angiotensin receptor blockers (ARBs)) are associated with different risks of cognitive decline. Published evidence is conflicting and stems mainly from observational studies. OBJECTIVE: To investigate the differential effects of antihypertensives on the risks of developing dementia and cognitive decline, with a specific focus on the vascular component of the mechanisms underlying these interactions. METHODS: Older adults with a history of hypertension and without dementia were drawn from the population-based HELIAD cohort. Age-, gender-, education-, and antihypertensive medication- (five dichotomous exposures) adjusted Cox proportional-hazards models and generalized estimating equations were performed to appraise the associations of baseline antihypertensive therapy with dementia incidence and cognitive decline (quantified using a comprehensive neuropsychological battery). Analyses were subsequently adjusted for clinical vascular risk (dyslipidemia, diabetes mellitus, smoking, cardiovascular, and cerebrovascular history) and genetic susceptibility to stroke (using polygenic risk scores generated according to the MEGASTROKE consortium GWAS findings). RESULTS: A total of 776 predominantly female participants (73.61±4.94 years) with hypertension and a mean follow-up of 3.02±0.82 years were analyzed. Baseline treatment was not associated with the risk of incident dementia. ARB users experienced a slower yearly global cognitive [2.5% of a SD, 95% CI = (0.1, 4.9)] and language [4.4% of a SD, 95% CI = (1.4, 7.4)] decline compared to non-users. The fully adjusted model reproduced similar associations for both global cognitive [β= 0.027, 95% CI =  (-0.003, 0.057)], and language decline [β= 0.063, 95% CI = (0.023, 0.104)]. CONCLUSION: ARBs may be superior to other antihypertensive agents in the preservation of cognition, an association probably mediated by vascular-independent mechanisms.
Keywords: Aged; Angiotensin Receptor Antagonists; Angiotensin-Converting Enzyme Inhibitors; Antihypertensive Agents; Calcium Channel Blockers; Cognitive Dysfunction; Dementia; Diuretics; Female; Humans; Hypertension; Male; Prospective Studies

Anti-Inflammatory Gene Therapy Improves Spatial Memory Performance in a Mouse Model of Alzheimer's Disease. - Yoo, Tai June (J Alzheimers Dis, 2022)
The immune system plays a critical role in neurodegenerative processes involved in Alzheimer's disease (AD). In this study, a gene-based immunotherapeutic method examined the effects of anti-inflammatory cellular immune response elements (CIREs) in the amyloid-β protein precursor (AβPP) mouse model. Bi-monthly intramuscular administration, beginning at either 4 or 6 months, and examined at 7.5 through 16 months, with plasmids encoding Interleukin (IL)-10, IL-4, TGF-β polynucleotides, or a combination thereof, into AβPP mice improved spatial memory performance. This work demonstrates an efficient gene therapy strategy to downregulate neuroinflammation, and possibly prevent or delay cognitive decline in AD.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Anti-Inflammatory Agents; Cognition; Disease Models, Animal; Female; Genetic Therapy; Immunity, Cellular; Immunotherapy; Injections, Intramuscular; Interleukin-10; Interleukin-4; Male; Mice; Mice, Transgenic; Spatial Memory

Behavioral and Psychological Symptoms of Dementia in Different Dementia Disorders: A Large-Scale Study of 10,000 Individuals. - Schwertner, Emilia; Pereira, Joana B; Xu, Hong; Secnik, Juraj; Winblad, Bengt; Eriksdotter, Maria; Nägga, Katarina; Religa, Dorota (J Alzheimers Dis, 2022)
BACKGROUND: The majority of individuals with dementia will suffer from behavioral and psychological symptoms of dementia (BPSD). These symptoms contribute to functional impairment and caregiver burden. OBJECTIVE: To characterize BPSD in Alzheimer's disease (AD), vascular dementia (VaD), mixed (Mixed) dementia, Parkinson's disease dementia (PDD), dementia with Lewy bodies (DLB), frontotemporal dementia (FTD), and unspecified dementia in individuals residing in long-term care facilities. METHODS: We included 10,405 individuals with dementia living in long-term care facilities from the Swedish registry for cognitive/dementia disorders (SveDem) and the Swedish BPSD registry. BPSD was assessed with the Neuropsychiatric Inventory - Nursing Home Version (NPI-NH). Multivariate logistic regression models were used to evaluate the associations between dementia diagnoses and different BPSDs. RESULTS: The most common symptoms were aberrant motor behavior, agitation, and irritability. Compared to AD, we found a lower risk of delusions (in FTD, unspecified dementia), hallucinations (FTD), agitation (VaD, PDD, unspecified dementia), elation/euphoria (DLB), anxiety (Mixed, VaD, unspecified dementia), disinhibition (in PDD), irritability (in DLB, FTD, unspecified dementia), aberrant motor behavior (Mixed, VaD, unspecified dementia), and sleep and night-time behavior changes (unspecified dementia). Higher risk of delusions (DLB), hallucinations (DLB, PDD), apathy (VaD, FTD), disinhibition (FTD), and appetite and eating abnormalities (FTD) were also found in comparison to AD. CONCLUSION: Although individuals in our sample were diagnosed with different dementia disorders, they all exhibited aberrant motor behavior, agitation, and irritability. This suggests common underlying psychosocial or biological mechanisms. We recommend prioritizing these symptoms while planning interventions in long-term care facilities.
Keywords: Alzheimer Disease; Behavioral Symptoms; Dementia, Vascular; Frontotemporal Dementia; Hallucinations; Humans; Parkinson Disease

"Captive by the Uncertainty"-Experiences with Anticipatory Guidance for People Living with Dementia and Their Caregivers at a Specialty Dementia Clinic. - Shafir, Adi; Ritchie, Christine S; Garrett, Sarah B; Bernstein Sideman, Alissa; Naasan, Georges; Merrilees, Jennifer; Widera, Eric; Flint, Lynn; Harrison, Krista L (J Alzheimers Dis, 2022)
BACKGROUND: After a diagnosis of Alzheimer's disease and related disorders, people living with dementia (PWD) and caregivers wonder what disease trajectory to expect and how to plan for functional and cognitive decline. This qualitative study aimed to identify patient and caregiver experiences receiving anticipatory guidance about dementia from a specialty dementia clinic. OBJECTIVE: To examine PWD and caregiver perspectives on receiving anticipatory guidance from a specialty dementia clinic. METHODS: We conducted semi-structured interviews with PWD, and active and bereaved family caregivers, recruited from a specialty dementia clinic. Interviews were recorded, transcribed, and systematically summarized. Thematic analysis identified anticipatory guidance received from clinical or non-clinical sources and areas where respondents wanted additional guidance. RESULTS: Of 40 participants, 9 were PWD, 16 were active caregivers, and 15 were bereaved caregivers. PWD had a mean age of 75 and were primarily male (n = 6/9); caregivers had a mean age of 67 and were primarily female (n = 21/31). Participants felt they received incomplete or "hesitant" guidance on prognosis and expected disease course via their clinicians and filled the gap with information they found via the internet, books, and support groups. They appreciated guidance on behavioral, safety, and communication issues from clinicians, but found more timely and advance guidance from other non-clinical sources. Guidance on legal and financial planning was primarily identified through non-clinical sources. CONCLUSION: PWD and caregivers want more information about expected disease course, prognosis, and help planning after diagnosis. Clinicians have an opportunity to improve anticipatory guidance communication and subsequent care provision.
Keywords: Aged; Alzheimer Disease; Caregivers; Dementia; Female; Humans; Male; Qualitative Research; Uncertainty

Caregiver Tele-Assistance for Reduction of Emotional Distress During the COVID-19 Pandemic. Psychological Support to Caregivers of People with Dementia: The Italian Experience. - Rotondo, Emanuela; Galimberti, Daniela; Mercurio, Matteo; Giardinieri, Giulia; Forti, Sara; Vimercati, Roberto; Borracci, Vittoria; Fumagalli, Giorgio G; Pietroboni, Anna M; Carandini, Tiziana; Nobili, Alessandro; Scarpini, Elio; et al. (J Alzheimers Dis, 2022)
BACKGROUND: COVID-19 pandemic worsened vulnerability of patients with dementia (PWD). This new reality associated with government restriction and isolation worsened stress burden and psychological frailties in PWD caregivers. OBJECTIVE: To give tele-psychological support to caregivers and evaluate the effect of this intervention by quantifying stress burden and quality of life during the first COVID-19 lockdown. METHODS: 50 caregivers were divided into two groups: "Caregiver-focused group" (Cg) and "Patient-focused group" (Pg). Both groups received telephone contact every 2 weeks over a 28-week period, but the content of the call was different: in Cg, caregivers answered questions about the state of the PWD but also explored their own emotional state, stress burden, and quality of life. In Pg instead, telephone contacts were focused only on the PWD, and no evaluation regarding the caregiver mood or state of stress was made. Psychometric scales were administered to evaluate COVID-19 impact, stress burden, and quality of life. RESULTS: Considering the time of intervention, from baseline (W0) to W28, Zarit Burden Interview and Quality of Life-caregiver questionnaires remained unchanged in Cg as compared with baseline (p > 0.05), whereas they worsened significantly in Pg (p < 0.01), showing increased stress over time and decreased quality of life in this group. Moreover, Impact on Event Scale values improved over the weeks in Cg (p = 0.015), while they remained unchanged in Pg (p = 0.483). CONCLUSION: Caregivers who received telephone support about their mood and stress burden did not worsen their psychological state during the time of intervention, as did instead those who did not get such support.
Keywords: Aged; Aged, 80 and over; Caregiver Burden; Caregivers; COVID-19; Dementia; Female; Humans; Italy; Male; Middle Aged; Psychological Distress; Psychosocial Support Systems; Quality of Life; Surveys and Questionnaires; Telephone

Chronic Renin-Angiotensin System Activation Induced Neuroinflammation: Common Mechanisms Underlying Hypertension and Dementia? - Tran, Shirley; Kuruppu, Sanjaya; Rajapakse, Niwanthi W (J Alzheimers Dis, 2022)
Hypertension is a major risk factor for the pathogenesis of vascular dementia and Alzheimer's disease. Chronic activation of the renin-angiotensin system (RAS) contributes substantially to neuroinflammation. We propose that neuroinflammation arising from chronic RAS activation can initiate and potentiate the onset of hypertension and related dementia. Neuroinflammation induced by chronic activation of the RAS plays a key role in the pathogenesis of dementia. Increased levels of pro-inflammatory cytokines tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and transforming growth factor (TGF)-β have been reported in brain tissue of vascular dementia patients and animal models of vascular dementia induced by either angiotensin II infusion or transverse aortic coarctation. It is proposed that neuronal cell death and synaptic dysfunction induced by neuroinflammation lead to cognitive impairment in dementia. The neuroprotective RAS pathway, regulated by angiotensin-converting enzyme 2 (ACE2) which converts angiotensin II into angiotensin-(1-7), can attenuate hypertension and dementia. Furthermore, the use of anti-hypertensive medications in preventing dementia or cognitive decline in hypertensive patients and animal models of dementia have mostly been beneficial. Current evidence suggests a strong link between RAS induced neuroinflammation and the onset of hypertension and dementia, which warrants further investigation. Strategies to counteract an overactive RAS and enhance the neuroprotective arm of the RAS may help prevent or improve cognitive impairment associated with hypertension.
Keywords: Angiotensin I; Angiotensin II; Animals; Antihypertensive Agents; Brain; Cytokines; Dementia, Vascular; Humans; Hypertension; Inflammation; Peptide Fragments; Renin-Angiotensin System

Cognitive Decline Risk Stratification in People with Late-Onset Epilepsy of Unknown Etiology: An Electroencephalographic Connectivity and Graph Theory Pilot Study. - Costa, Cinzia; Vecchio, Fabrizio; Romoli, Michele; Miraglia, Francesca; Nardi Cesarini, Elena; Alù, Francesca; Calabresi, Paolo; Rossini, Paolo Maria (J Alzheimers Dis, 2022)
BACKGROUND: Although people with late onset epilepsy of unknown etiology (LOEU) are at higher risk of cognitive decline compared to the general population, we still lack affordable tools to predict and stratify their risk of dementia. OBJECTIVE: This pilot-study investigates the potential application of electroencephalography (EEG) network small-world (SW) properties in predicting cognitive decline among patients with LOEU. METHODS: People diagnosed with LOEU and normal cognitive examination at the time of epilepsy diagnosis were included. Cerebrospinal fluid biomarkers, brain imaging, and neuropsychological assessment were performed at the time of epilepsy diagnosis. Baseline EEG was analyzed for SW properties. Patients were followed-up over time with neuropsychological testing to define the trajectory of cognitive decline. RESULTS: Over 5.1 years of follow-up, among 24 patients diagnosed with LOEU, 62.5% were female, mean age was 65.3 years, thirteen developed mild cognitive impairment (MCI), and four developed dementia. Patients with LOEU developing MCI had lower values of SW coefficients in the delta (p = 0.03) band and higher SW values in the alpha frequency bands (p = 0.02) compared to patients having normal cognition at last follow-up. The two separate ANOVAs, for low and alpha bands, confirmed an interaction between SW and cognitive decline at follow-up. A similar gradient was confirmed for patients developing dementia compared to those with normal cognitive function as well as to those developing MCI. CONCLUSION: Baseline EEG analysis through SW is worth investigating as an affordable, widely available tool to stratify LOEU patients for their risk of cognitive decline.
Keywords: Aged; Cognitive Dysfunction; Dementia; Electroencephalography; Epilepsy; Female; Humans; Male; Neuropsychological Tests; Pilot Projects; Risk Assessment

A Comparison of Behavioral and Psychological Symptoms of Dementia (BPSD) and BPSD Sub-Syndromes in Early-Onset and Late-Onset Alzheimer's Disease. - Altomari, Natalia; Bruno, Francesco; Laganà, Valentina; Smirne, Nicoletta; Colao, Rosanna; Curcio, Sabrina; Di Lorenzo, Raffaele; Frangipane, Francesca; Maletta, Raffaele; Puccio, Gianfranco; Bruni, Amalia Cecilia (J Alzheimers Dis, 2022)
BACKGROUND: Behavioral and psychological symptoms of dementia (BPSD) have a large impact on the quality of life of patients with Alzheimer's disease (AD). Few studies have compared BPSD between early-onset (EOAD) and late-onset (LOAD) patients, finding conflicting results. OBJECTIVE: The aims of this study were to: 1) characterize the presence, overall prevalence, and time of occurrence of BPSD in EOAD versus LOAD; 2) estimate the prevalence over time and severity of each BPSD in EOAD versus LOAD in three stages: pre-T0 (before the onset of the disease), T0 (from onset to 5 years), and T1 (from 5 years onwards); 3) track the manifestation of BPSD sub-syndromes (i.e., hyperactivity, psychosis, affective, and apathy) in EOAD versus LOAD at T0 and T1. METHODS: The sample includes 1,538 LOAD and 387 EOAD diagnosed from 1996 to 2018. Comprehensive assessment batteries, including the Neuropsychiatric Inventory (NPI), were administered at the first medical assessment and at different follow-up period. RESULTS: The overall prevalence for the most of BPSD was significantly higher in EOAD compared to LOAD whereas most BPSD appeared significantly later in EOAD patients. Between the two groups, from pre-T0 to T1 we recorded a different pattern of BPSD prevalence over time as well as for BPSD sub-syndromes at T0 and T1. Results on severity of BPSD did not show significant differences. CONCLUSION: EOAD and LOAD represent two different forms of a single entity not only from a neuropathological, cognitive, and functional level but also from a psychiatric point of view.
Keywords: Affective Symptoms; Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Apathy; Behavioral Symptoms; Dementia; Female; Humans; Italy; Male; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Psychomotor Agitation; Psychotic Disorders; Severity of Illness Index

Comparison of Steady-State Pharmacokinetics of Donepezil Transdermal Delivery System with Oral Donepezil. - Tariot, Pierre N; Braeckman, Rene; Oh, Charles (J Alzheimers Dis, 2022)
BACKGROUND: Donepezil is approved for treatment of dementia of the Alzheimer type and is currently available only in tablet forms in the United States. OBJECTIVE: To compare steady-state pharmacokinetics of once-weekly 10-mg/d and 5-mg/d Corplex™ donepezil transdermal delivery systems (TDS) with once-daily 10-mg oral donepezil. METHODS: Open-label, randomized, crossover study (NCT04617782) enrolled healthy participants aged 18-55 years. All participants received 5-mg/d donepezil TDS during the 5-week Period 1, followed by 10-mg/d TDS or 10-mg/d oral donepezil in the 5-week Period 2; treatments were switched in Period 3. Bioequivalence was assessed at steady state on Week 5. RESULTS: All 60 enrolled participants received 5-mg/d TDS, 55 received 10-mg/d TDS, and 56 received oral donepezil. Adjusted geometric mean ratio (% [90% CI]) for maximum plasma concentration and area under the plasma concentration versus time curve (0-168 h) were 88.7 (81.7-96.2) and 108.6 (100.5-117.4) for 10-mg/d and 86.1 (79.8-92.9) and 105.3 (97.6-113.6) for dose-normalized 5-mg/d TDS and were generally within the 80% -125% range for establishing bioequivalence with oral donepezil. Skin adhesion was similar for both TDSs (>80% of patches remaining ≥75% adhered throughout the wear period). Overall incidence of adverse events (AEs) was similar across treatments. Compared with 10-mg/d TDS, oral donepezil was associated with higher incidence of gastrointestinal and nervous system AEs (14.5% versus 53.6% and 14.5% versus 30.4%, respectively). CONCLUSION: Donepezil TDSs are bioequivalent to oral donepezil at steady state and have a safety profile that supports their use in treating dementia of the Alzheimer type.
Keywords: Adolescent; Adult; Alzheimer Disease; Cross-Over Studies; Donepezil; Humans; Middle Aged; Young Adult

A Comparison of Well-Being of Carers of People with Dementia and Their Ability to Manage Before and During the COVID-19 Pandemic: Findings from the IDEAL Study. - Gamble, Laura D; Parker, Sophie; Quinn, Catherine; Bennett, Holly Q; Martyr, Anthony; Sabatini, Serena; Pentecost, Claire; Collins, Rachel; Dawson, Eleanor; Hunt, Anna; Allan, Louise; Burns, Alistair; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Social restriction measures imposed to curb the spread of COVID-19 in the United Kingdom impacted on carers of people with dementia, limiting access to support services and increasing perceived burden of caring. Few studies have compared data collected both during and before the pandemic to examine the effect of these changes. OBJECTIVE: To explore whether the COVID-19 pandemic affected the well-being of carers of people with dementia living in the community, and their ability to cope with their caring responsibilities. METHODS: Analysis was conducted on two groups of carers who were enrolled in the IDEAL programme; the 'pre-pandemic group' (n = 312), assessed at two time points prior to the pandemic, and the 'pandemic group', assessed prior to and several months into the pandemic (n = 156). For the pre-pandemic group, carers were matched 2:1 to carers in the pandemic group on certain characteristics. Differences in change over time between the two groups on self-reported well-being, quality of life, coping, perceived competence, and role captivity, were investigated using mixed effect modelling. RESULTS: Compared to the pre-pandemic group, those in the pandemic group appeared to cope better and had more stable self-rated competency and role captivity. They did not differ in terms of well-being or quality of life. CONCLUSIONS: Despite reports of negative impacts on carers early in the pandemic, the findings suggest the pandemic had little negative longer-term impact on carers of people with dementia, and in fact they appeared to have a more positive attitude towards coping several months into the pandemic.
Keywords: Adaptation, Psychological; Caregivers; COVID-19; Dementia; Humans; Pandemics; Quality of Life

COVID-19 and Neurodegenerative Diseases: Prion-Like Spread and Long-Term Consequences. - Baazaoui, Narjes; Iqbal, Khalid (J Alzheimers Dis, 2022)
COVID-19 emerged as a global pandemic starting from Wuhan in China and spread at a lightning speed to the rest of the world. One of the potential long-term outcomes that we speculate is the development of neurodegenerative diseases as a long-term consequence of SARS-CoV-2 especially in people that have developed severe neurological symptoms. Severe inflammatory reactions and aging are two very strong common links between neurodegenerative diseases and COVID-19. Thus, patients that have very high viral load may be at high risk of developing long-term adverse neurological consequences such as dementia. We hypothesize that people with neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease, and aged people are at higher risk of getting the COVID-19 than normal adults. The basis of this hypothesis is the fact that SARS-CoV-2 uses as a receptor angiotensin-converting enzyme 2 to enter the host cell and that this interaction is calcium-dependent. This could then suggest a direct relationship between neurodegenerative diseases, ACE-2 expression, and the susceptibility to COVID-19. The analysis of the available literature showed that COVID-19 virus is neurotropic and was found in the brains of patients infected with this virus. Furthermore, that the risk of having the infection increases with dementia and that infected people with severe symptoms could develop dementia as a long-term consequence. Dementia could be developed following the acceleration of the spread of prion-like proteins. In the present review we discuss current reports concerning the prevalence of COVID-19 in dementia patients, the individuals that are at high risk of suffering from dementia and the potential acceleration of prion-like proteins spread following SARS-CoV-2 infection.
Keywords: Aged; COVID-19; Dementia; Humans; Neurodegenerative Diseases; Prions; SARS-CoV-2

Dementia Research on Facebook and Twitter: Current Practice and Challenges. - Hrincu, Viorica; An, Zijian; Joseph, Kenneth; Jiang, Yu Fei; Robillard, Julie M (J Alzheimers Dis, 2022)
BACKGROUND: Social media is a powerful tool for engaging diverse audiences in dementia research. However, there is little data summarizing current content exchange in this context. OBJECTIVE: To inform ethical dementia research engagement on social media, we characterized current practices by analyzing public social media posts. METHODS: We retrieved Facebook (2-year period, N = 7,896) and Twitter (1-year period, N = 9,323) posts containing dementia research-related keywords using manual and machine learning-based search strategies. We performed qualitative and quantitative content and sentiment analyses on random samples (10%) of the posts. RESULTS: Top Facebook users were advocacy (45%) and health organizations (25%). On Twitter, academics/researchers were the largest user group. Prevention was the most frequently coded theme (Facebook 30%; Twitter 26%), followed by treatment (Facebook 15%; Twitter 18%). Diagnostics had the highest Facebook engagement. Sharing knowledge was the primary form of content exchange (Facebook 63%; Twitter 80%). Most shared journal articles were peer-reviewed and open access. Emotional tone was overall more positive on Facebook. Justice was a prominent ethics topic regarding inequalities related to identity and intersecting modes of marginalization in dementia research. CONCLUSION: The findings indicate the importance of social media as an engagement tool of current topics in health research and reveal areas of potential for increased engagement. These data can inform consensus-based best practices for ethical social media application in dementia research.
Keywords: Dementia; Humans; Social Media

Diabetic Retinopathy Predicts Risk of Alzheimer's Disease: A Danish Registry-Based Nationwide Cohort Study. - Pedersen, Frederik Nørregaard; Stokholm, Lonny; Pouwer, Frans; Hass Rubin, Katrine; Peto, Tunde; Frydkjær-Olsen, Ulrik; Thykjær, Anne Suhr; Andersen, Nis; Andresen, Jens; Bek, Toke; La Cour, Morten; Heegaard, Steffen; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Retinal neurodegeneration is evident in early diabetic retinopathy (DR) which may be associated with other neurodegenerative diseases like Alzheimer's disease (AD). OBJECTIVE: To investigate diabetes and DR as a risk marker of present and incident AD. METHODS: A register-based cohort study was performed. We included 134,327 persons with diabetes above 60 years of age, who had attended DR screening, and 651,936 age- and gender-matched persons without diabetes. RESULTS: At baseline, the prevalence of AD was 0.7% and 1.3% among patients with and without diabetes, respectively. In a multivariable regression model, patients with diabetes were less likely to have AD at baseline (adjusted OR 0.63, 95% CI 0.59-0.68). During follow-up, incident AD was registered for 1473 (0.35%) and 6,899 (0.34%) persons with and without diabetes, respectively. Compared to persons without diabetes, persons with diabetes and no DR had a lower risk to develop AD (adjusted HR 0.87, 95% CI 0.81-0.93), while persons with diabetes and DR had higher risk of AD (adjusted HR 1.24, 95% CI 1.08-1.43). When persons with diabetes and no DR were used as references, a higher risk of incident AD was observed in persons with DR (adjusted HR 1.34, 95% CI 1.18-1.53). CONCLUSION: Individuals with diabetes without DR were less likely to develop AD compared to persons without diabetes. However, individuals with DR had a 34% higher risk of incident AD, which raise the question whether screening for cognitive impairment should be done among individuals with DR.
Keywords: Alzheimer Disease; Cohort Studies; Denmark; Diabetes Mellitus; Diabetic Retinopathy; Humans; Registries; Risk Factors

Digital Technologies to Prevent Social Isolation and Loneliness in Dementia: A Systematic Review. - Rai, Harleen Kaur; Kernaghan, David; Schoonmade, Linda; Egan, Kieren J; Pot, Anne Margriet (J Alzheimers Dis, 2022)
BACKGROUND: Dementia poses significant and sustained challenges to global society. Diagnosis can lead to increased feelings of loneliness and social isolation. People with dementia living alone are particularly at risk. Considering the growing number of technologies proposed to aid people with dementia address social isolation and loneliness, we reviewed the existing literature. OBJECTIVE: To collate and summarize current evidence for digital technologies to prevent social isolation and loneliness for people with dementia. METHODS: Following the PRISMA guidelines, we systematically searched five databases to identify studies of digital technologies designed to support or prevent social isolation or loneliness for people with dementia. Pre-specified outcomes included social isolation, loneliness, and quality of life. We used deductive thematic analysis to synthesize the major themes emerging from the studies. RESULTS: Ten studies met our inclusion criteria where all studies reported improvements in quality of life and seven reported benefits regarding social inclusion or a reduction in loneliness. Technologies were varied across purpose, delivery format, theoretical models, and levels of personalization. Two studies clearly described the involvement of people with dementia in the study design and five technologies were available outside the research context. CONCLUSION: There is limited- but increasing- evidence that technologies hold potential to improve quality of life and reduce isolation/loneliness for people with dementia. Results presented are largely based in small-scale research studies. Involvement of people with dementia was limited and few research concepts are reaching implementation. Closer collaboration with people with dementia to provide affordable, inclusive, and person-centered solutions is urgently required.
Keywords: Dementia; Digital Technology; Humans; Loneliness; Quality of Life; Social Isolation

Dimethyl Fumarate is a Potential Therapeutic Option for Alzheimer's Disease. - Sun, Xiaodi; Suo, Xinjun; Xia, Xianyou; Yu, Chunshui; Dou, Yan (J Alzheimers Dis, 2022)
BACKGROUND: Dimethyl fumarate (DMF) has been approved for clinical treatment of multiple sclerosis based on its antioxidant and anti-inflammatory effects by activating the Nrf2 pathway. Since both oxidative stress and inflammation are involved in Alzheimer's disease (AD), DMF is a potential therapeutic option for AD. OBJECTIVE: This study aims to test the therapeutic effects of DMF on AD model mice and to reveal its underlying molecular mechanisms. METHODS: Cell viability assay and in vitro immunofluorescence imaging were used to evaluate the antioxidant effect of DMF on embryonic mouse hippocampal neurons. Behavioral test and brain magnetic resonance imaging were used to assess the therapeutic effects of DMF on spatial learning and memory as well as hippocampal volume in AD model mice with and without Nrf2 knockdown. Western blotting was used to analyze the expression of antioxidant enzymes and molecules associated with AD-related pathological pathways. RESULTS: DMF inhibits reactive oxygen species overproduction and protects neurons without Nrf2 knockdown from death. DMF reduces amyloid-β induced memory impairment and hippocampal atrophy in AD model mice rather than in Nrf2 knockdown AD mice. DMF delays the progression of AD by activating the Nrf2 pathway to enhance the expression of downstream antioxidant enzymes and inhibits lipid peroxidation, apoptosis, inflammation, mitochondrial dysfunction and amyloid-β deposition. CONCLUSION: These results indicate that DMF is a potential therapeutic option for AD through its antioxidant, anti-inflammatory, anti-apoptotic, and other anti-AD effects by activating the Nrf2 pathway.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Antioxidants; Cell Survival; Dimethyl Fumarate; Disease Models, Animal; Hippocampus; Inflammation; Male; Memory Disorders; Mice; Mice, Inbred C57BL; Neurons; NF-E2-Related Factor 2; NF-kappa B; Oxidative Stress; Protective Agents; Reactive Oxygen Species

Effect of Probiotic Bifidobacterium breve in Improving Cognitive Function and Preventing Brain Atrophy in Older Patients with Suspected Mild Cognitive Impairment: Results of a 24-Week Randomized, Double-Blind, Placebo-Controlled Trial. - Asaoka, Daisuke; Xiao, Jinzhong; Takeda, Tsutomu; Yanagisawa, Naotake; Yamazaki, Takahiro; Matsubara, Yoichiro; Sugiyama, Hideki; Endo, Noemi; Higa, Motoyuki; Kasanuki, Koji; Ichimiya, Yosuke; Koido, Shigeo; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Probiotics have been reported to ameliorate cognitive impairment. OBJECTIVE: We investigated the effect of the probiotic strain Bifidobacterium breve MCC1274 (A1) in enhancing cognition and preventing brain atrophy of older patients with mild cognitive impairment (MCI). METHODS: In this RCT, 130 patients aged from 65 to 88 years old with suspected MCI received once daily either probiotic (B. breve MCC1274, 2×1010 CFU) or placebo for 24 weeks. Cognitive functions were assessed by ADAS-Jcog and MMSE tests. Participants underwent MRI to determine brain atrophy changes using Voxel-based Specific Regional Analysis System for Alzheimer's disease (VSRAD). Fecal samples were collected for the analysis of gut microbiota composition. RESULTS: Analysis was performed on 115 participants as the full analysis set (probiotic 55, placebo 60). ADAS-Jcog subscale "orientation" was significantly improved compared to placebo at 24 weeks. MMSE subscales "orientation in time" and "writing" were significantly improved compared to placebo in the lower baseline MMSE (< 25) subgroup at 24 weeks. VSRAD scores worsened in the placebo group; probiotic supplementation tended to suppress the progression, in particular among those subjects with progressed brain atrophy (VOI Z-score ≥1.0). There were no marked changes in the overall composition of the gut microbiota by the probiotic supplementation. CONCLUSION: Improvement of cognitive function was observed on some subscales scores only likely due to the lower sensitiveness of these tests for MCI subjects. Probiotics consumption for 24 weeks suppressed brain atrophy progression, suggesting that B. breve MCC1274 helps prevent cognitive impairment of MCI subjects.
Keywords: Aged; Aged, 80 and over; Atrophy; Bifidobacterium breve; Brain; Cognition; Cognitive Dysfunction; Double-Blind Method; Humans; Probiotics

The Efficacy and Safety of Alzheimer's Disease Therapies: An Updated Umbrella Review. - Fan, Fangcheng; Liu, Hua; Shi, Xiaojie; Ai, Yangwen; Liu, Qingshan; Cheng, Yong (J Alzheimers Dis, 2022)
BACKGROUND: Evidence summaries for efficacy and safety of frequently employed treatments of Alzheimer's disease (AD) are sparse. OBJECTIVE: We aimed to perform an updated umbrella review to identify an efficacious and safe treatment for AD patients. METHODS: We conducted a search for meta-analyses and systematic reviews on the Embase, PubMed, The Cochrane Library, and Web of Science to address this knowledge gap. We examined the cognitive functions, behavioral symptoms, global clinical assessment, and Activities of Daily Living as efficacy endpoints, and the incidence of adverse events as safety profiles. RESULTS: Sixteen eligible papers including 149 studies were included in the umbrella review. The results showed that AChE inhibitors (donepezil, galantamine, rivastigmine, Huperzine A), Ginkgo biloba, and cerebrolysin appear to be beneficial for cognitive, global performances, and activities of daily living in patients with AD. Furthermore, anti-Aβ agents are unlikely to have an important effect on slowing cognitive or functional impairment in mild to moderate AD. CONCLUSION: Our study demonstrated that AChE inhibitors, Ginkgo biloba, and cerebrolysin are the optimum cognitive and activities of daily living medication for patients with AD.
Keywords: Activities of Daily Living; Alzheimer Disease; Amino Acids; Cholinesterase Inhibitors; Cognition; Donepezil; Galantamine; Ginkgo biloba; Humans; Nootropic Agents; Patient Safety; Plant Extracts; Rivastigmine

Environmental Enrichment Effects on the Brain-Derived Neurotrophic Factor Expression in Healthy Condition, Alzheimer's Disease, and Other Neurodegenerative Disorders. - Cutuli, Debora; Landolfo, Eugenia; Petrosini, Laura; Gelfo, Francesca (J Alzheimers Dis, 2022)
Brain-derived neurotrophic factor (BDNF), a protein belonging to the neurotrophin family, is known to be heavily involved in synaptic plasticity processes that support brain development, post-lesion regeneration, and cognitive performances, such as learning and memory. Evidence indicates that BDNF expression can be epigenetically regulated by environmental stimuli and thus can mediate the experience-dependent brain plasticity. Environmental enrichment (EE), an experimental paradigm based on the exposure to complex stimulations, constitutes an efficient means to investigate the effects of high-level experience on behavior, cognitive processes, and neurobiological correlates, as the BDNF expression. In fact, BDNF exerts a key role in mediating and promoting EE-induced plastic changes and functional improvements in healthy and pathological conditions. This review is specifically aimed at providing an updated framework of the available evidence on the EE effects on brain and serum BDNF levels, by taking into account both changes in protein expression and regulation of gene expression. A further purpose of the present review is analyzing the potential of BDNF regulation in coping with neurodegenerative processes characterizing Alzheimer's disease (AD), given BDNF expression alterations are described in AD patients. Moreover, attention is also paid to EE effects on BDNF expression in other neurodegenerative disease. To investigate such a topic, evidence provided by experimental studies is considered. A deeper understanding of environmental ability in modulating BDNF expression in the brain may be fundamental in designing more tuned and effective applications of complex environmental stimulations as managing approaches to AD.
Keywords: Alzheimer Disease; Animals; Brain; Brain-Derived Neurotrophic Factor; Cognition; Disease Models, Animal; Environment; Humans; Neurodegenerative Diseases; Neuronal Plasticity

Functional Neurophysiological Biomarkers of Early-Stage Alzheimer's Disease: A Perspective of Network Hyperexcitability in Disease Progression. - Tok, Sean; Ahnaou, Abdallah; Drinkenburg, Wilhelmus (J Alzheimers Dis, 2022)
Network hyperexcitability (NH) has recently been suggested as a potential neurophysiological indicator of Alzheimer's disease (AD), as new, more accurate biomarkers of AD are sought. NH has generated interest as a potential indicator of certain stages in the disease trajectory and even as a disease mechanism by which network dysfunction could be modulated. NH has been demonstrated in several animal models of AD pathology and multiple lines of evidence point to the existence of NH in patients with AD, strongly supporting the physiological and clinical relevance of this readout. Several hypotheses have been put forward to explain the prevalence of NH in animal models through neurophysiological, biochemical, and imaging techniques. However, some of these hypotheses have been built on animal models with limitations and caveats that may have derived NH through other mechanisms or mechanisms without translational validity to sporadic AD patients, potentially leading to an erroneous conclusion of the underlying cause of NH occurring in patients with AD. In this review, we discuss the substantiation for NH in animal models of AD pathology and in human patients, as well as some of the hypotheses considering recently developed animal models that challenge existing hypotheses and mechanisms of NH. In addition, we provide a preclinical perspective on how the development of animal models incorporating AD-specific NH could provide physiologically relevant translational experimental data that may potentially aid the discovery and development of novel therapies for AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Biomarkers; Disease Progression; Humans; Nervous System Physiological Phenomena; Neurophysiology; tau Proteins

Impact of COVID-19 on 'Living Well' with Mild-to-Moderate Dementia in the Community: Findings from the IDEAL Cohort. - Clare, Linda; Martyr, Anthony; Gamble, Laura D; Pentecost, Claire; Collins, Rachel; Dawson, Eleanor; Hunt, Anna; Parker, Sophie; Allan, Louise; Burns, Alistair; Hillman, Alexandra; Litherland, Rachael; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Negative impacts of the COVID-19 pandemic on people with dementia have been widely-documented, but most studies have relied on carer reports and few have compared responses to information collected before the pandemic. OBJECTIVE: We aimed to explore the impact of the pandemic on community-dwelling individuals with mild-to-moderate dementia and compare responses with pre-pandemic data. METHODS: During the second wave of the pandemic, we conducted structured telephone interviews with 173 people with dementia and 242 carers acting as informants, all of whom had previously participated in the IDEAL cohort. Where possible, we benchmarked responses against pre-pandemic data. RESULTS: Significant perceived negative impacts were identified in cognitive and functional skills and ability to engage in self-care and manage everyday activities, along with increased levels of loneliness and discontinuity in sense of self and a decline in perceived capability to 'live well'. Compared to pre-pandemic data, there were lower levels of pain, depression, and anxiety, higher levels of optimism, and better satisfaction with family support. There was little impact on physical health, mood, social connections and relationships, or perceptions of neighborhood characteristics. CONCLUSION: Efforts to mitigate negative impacts of pandemic-related restrictions and restore quality of life could focus on reablement to address the effects on participation in everyday activities, creating opportunities for social contact to reduce loneliness, and personalized planning to reconnect people with their pre-COVID selves. Such efforts may build on the resilience demonstrated by people with dementia and carers in coping with the pandemic.
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Caregivers; COVID-19; Dementia; Female; Humans; Male; Middle Aged; Neighborhood Characteristics; Quality of Life; SARS-CoV-2

Informal Caregivers' Attitude Toward Dementia: The Impact of Dementia Knowledge, Confidence in Dementia Care, and the Behavioral and Psychological Symptoms of the Person with Dementia. A Cross-Sectional Study. - Teichmann, Birgit; Gkioka, Mara; Kruse, Andreas; Tsolaki, Magda (J Alzheimers Dis, 2022)
BACKGROUND: Dementia is rapidly increasing worldwide due to demographic aging. More than two-thirds of patients are cared by family members. The quality of care depends on the caregivers' attitude toward dementia influencing patient care decisions. OBJECTIVE: The aim of this study is to examine the factors that influence the caregivers' attitude and whether there is an association between participation in a psycho-educational program and attitude. METHODS: We performed a cross-sectional study using a structured closed-ended questionnaire to retrieve socio-demographic information from caregivers and the persons with dementia (N = 86). The study included validated scales such as the Dementia Attitude Scale, the Dementia Knowledge Assessment Tool 2, the Positive Aspects of Caregiving, the Zarit Burden Interview, the Confidence in Dementia Scale, and Spielberger's State-Trait Anxiety Inventory, as well as a neuropsychological battery to assess the condition of people with dementia. RESULTS: Our final model explains 55.6% of the total variance and shows a significant correlation of five factors with attitude toward dementia: confidence, behavioral and psychological symptoms of dementia, anxiety as a trait, positive aspects of caregiving, and dementia knowledge. The caregivers who participated in a psycho-educational program showed a significantly more positive attitude toward dementia, better dementia knowledge, higher confidence in dementia care, and lower anxiety as a state. CONCLUSION: The strong correlation of attitude and knowledge, as well as confidence in dementia care, supports the tripartite model of attitude, which hypothesizes the interrelation of affect, cognition, and behavior.
Keywords: Attitude; Caregivers; Cross-Sectional Studies; Dementia; Humans; Surveys and Questionnaires

Interaction Between Diet and Microbiota in the Pathophysiology of Alzheimer's Disease: Focus on Polyphenols and Dietary Fibers. - Ticinesi, Andrea; Mancabelli, Leonardo; Carnevali, Luca; Nouvenne, Antonio; Meschi, Tiziana; Del Rio, Daniele; Ventura, Marco; Sgoifo, Andrea; Angelino, Donato (J Alzheimers Dis, 2022)
Animal studies increasingly indicate that the gut microbiota composition and function can be involved in the pathophysiology and progression of Alzheimer's disease (AD) at multiple levels. However, few studies have investigated this putative gut-brain axis in human beings, and none of them considered diet as a determinant of intestinal microbiota composition. Epidemiological studies highlight that a high intake of fruit and vegetables, such as that typical of the Mediterranean diet, can modulate AD progression. Thus, nutritional interventions are being increasingly studied as a possible non-pharmacological strategy to slow down the progression of AD. In particular, polyphenols and fibers represent the nutritional compounds with the higher potential of counterbalancing the pathophysiological mechanisms of dementia due to their antioxidant, anti-inflammatory, and anti-apoptotic properties. These actions are mediated by the gut microbiota, that can transform polyphenols and fibers into biologically active compounds including, among others, phenyl-γ-valerolactones, urolithins, butyrate, and other short-chain fatty acids. In this review, the complex mechanisms linking nutrition, gut microbiota composition, and pathophysiology of cognitive decline in AD are discussed, with a particular focus on the role of polyphenols and fibers. The gaps between pre-clinical and clinical studies are particularly emphasized, as well as the urgent need for studies comprehensively evaluating the link between nutrition, microbiome, and clinical aspects of AD.
Keywords: Alzheimer Disease; Animals; Diet; Diet, Mediterranean; Dietary Fiber; Humans; Microbiota; Polyphenols

Probiotic Bifidobacterium breve Prevents Memory Impairment Through the Reduction of Both Amyloid-β Production and Microglia Activation in APP Knock-In Mouse. - Abdelhamid, Mona; Zhou, Chunyu; Ohno, Kazuya; Kuhara, Tetsuya; Taslima, Ferdous; Abdullah, Mohammad; Jung, Cha-Gyun; Michikawa, Makoto (J Alzheimers Dis, 2022)
BACKGROUND: Probiotic supplementation reestablishes microbiome diversity and improves brain function in Alzheimer's disease (AD); their molecular mechanisms, however, have not yet been fully illustrated. OBJECTIVE: We investigated the effects of orally supplemented Bifidobacterium breve MCC1274 on cognitive function and AD-like pathologies in AppNL-G-F mice. METHODS: Three-month-old AppNL-G-F mice were orally supplemented with B. breve MCC1274 for four months. The short-term memory function was evaluated using a novel object recognition test. Amyloid plaques, amyloid-β (Aβ) levels, Aβ fibril, amyloid-β protein precursor and its processing enzymes, its metabolic products, glial activity, and cell proliferation in the subgranular zone of the dentate gyrus were evaluated by immunohistochemistry, Aβ ELISA, western blotting, and immunofluorescence staining. The mRNA expression levels of pro- and anti-inflammatory cytokines were determined by qRT-PCR analysis. RESULTS: We found that the oral B. breve MCC1 274 supplementation prevented memory impairment in AppNL-G-F mice and decreased hippocampal Aβ levels through the enhancement of the a-disintegrin and metalloproteinase 10 (ADAM10) level. Moreover, administration of the probiotic activated the ERK/HIF-1α signaling pathway responsible for increasing the ADAM10 level and also attenuated microglial activation, which in turn led to reduction in the mRNA expression levels of pro-inflammatory cytokines in the brain. In addition, B. breve MCC1274 supplementation increased the level of synaptic proteins in the hippocampus. CONCLUSION: Our findings support the possibility that oral B. breve MCC1274 supplementation might be used as a potential preventive therapy for AD progression.
Keywords: Amyloid beta-Peptides; Animals; Bifidobacterium breve; Brain; Disease Models, Animal; Hippocampus; Memory Disorders; Mice; Mice, Transgenic; Microglia; Probiotics

Psychosis as a Treatment Target in Dementia: A Roadmap for Designing Interventions. - Agüera-Ortiz, Luis; Babulal, Ganesh M; Bruneau, Marie-Andrée; Creese, Byron; D'Antonio, Fabrizia; Fischer, Corinne E; Gatchel, Jennifer R; Ismail, Zahinoor; Kumar, Sanjeev; McGeown, William J; Mortby, Moyra E; Nuñez, Nicolas A; et al. (J Alzheimers Dis, 2022)
Psychotic phenomena are among the most severe and disruptive symptoms of dementias and appear in 30% to 50% of patients. They are associated with a worse evolution and great suffering to patients and caregivers. Their current treatments obtain limited results and are not free of adverse effects, which are sometimes serious. It is therefore crucial to develop new treatments that can improve this situation. We review available data that could enlighten the future design of clinical trials with psychosis in dementia as main target. Along with an explanation of its prevalence in the common diseases that cause dementia, we present proposals aimed at improving the definition of symptoms and what should be included and excluded in clinical trials. A review of the available information regarding the neurobiological basis of symptoms, in terms of pathology, neuroimaging, and genomics, is provided as a guide towards new therapeutic targets. The correct evaluation of symptoms is transcendental in any therapeutic trial and these aspects are extensively addressed. Finally, a critical overview of existing pharmacological and non-pharmacological treatments is made, revealing the unmet needs, in terms of efficacy and safety. Our work emphasizes the need for better definition and measurement of psychotic symptoms in dementias in order to highlight their differences with symptoms that appear in non-dementing diseases such as schizophrenia. Advances in neurobiology should illuminate the development of new, more effective and safer molecules for which this review can serve as a roadmap in the design of future clinical trials.
Keywords: Caregivers; Dementia; Hallucinations; Humans; Psychotic Disorders; Schizophrenia

Safety, Tolerability, Pharmacokinetics, and Pharmacodynamics of the Positive Modulator of HGF/MET, Fosgonimeton, in Healthy Volunteers and Subjects with Alzheimer's Disease: Randomized, Placebo-Controlled, Double-Blind, Phase I Clinical Trial. - Hua, Xue; Church, Kevin; Walker, William; L'Hostis, Philippe; Viardot, Geoffrey; Danjou, Philippe; Hendrix, Suzanne; Moebius, Hans J (J Alzheimers Dis, 2022)
BACKGROUND: Fosgonimeton (ATH-1017) is being developed as a first-in-class regenerative therapy for people with Alzheimer's disease (AD) and dementia; potentially improving dementia symptoms and altering disease progression by reversing synaptic disconnection and neuronal loss. OBJECTIVE: This randomized, double-blind, placebo-controlled phase I trial (NCT03298672) evaluated the safety, tolerability, pharmacokinetics, and pharmacodynamics of fosgonimeton. METHODS: Fosgonimeton was administered once daily via subcutaneous injection to 88 subjects. The single ascending dose study enrolled healthy young male subjects (n = 48; age, 33.4±6.3 years; dose, 2, 6, 20, 40, 60, or 90 mg); the multiple ascending dose study enrolled healthy elderly subjects (n = 29; age, 63.8±4.0 years; dose, 20, 40, 60, or 80 mg; 9-day duration); and the fixed-dose study enrolled AD subjects (n = 11; age, 69.2±7.1 years; dose, 40 mg; 9-day duration). Quantitative electroencephalogram (qEEG) and event-related potential (ERP) P300 measured neurophysiological signals following fosgonimeton treatment, supporting brain penetration and target engagement. RESULTS: Fosgonimeton and placebo were shown to be safe and well-tolerated across all doses. Pharmacokinetic results for fosgonimeton were dose-proportional, with no sex effect or accumulation over 9 days. The main effect of fosgonimeton on qEEG was acute and sustained gamma power induction. In AD subjects, there was a significant effect toward ERP P300 latency normalization compared with placebo (p = 0.027; n = 7 at 40 mg fosgonimeton versus n = 4 placebo). CONCLUSION: These results support the continued development of fosgonimeton as a novel therapeutic for people with AD and dementia. The fast-onset normalization of ERP P300 latency in AD subjects suggests enhancement of synaptic function and potential procognitive effects.
Keywords: Aged; Alzheimer Disease; Area Under Curve; Dose-Response Relationship, Drug; Double-Blind Method; Healthy Volunteers; Hepatocyte Growth Factor; Humans; Male

Sex Differences in Behavior and Molecular Pathology in the 5XFAD Model. - Sil, Annesha; Erfani, Arina; Lamb, Nicola; Copland, Rachel; Riedel, Gernot; Platt, Bettina (J Alzheimers Dis, 2022)
BACKGROUND: The prevalence of Alzheimer's disease (AD) is greater in women compared to men, but the reasons for this remain unknown. This sex difference has been widely neglected in experimental studies using transgenic mouse models of AD. OBJECTIVE: Here, we studied behavior and molecular pathology of 5-month-old 5XFAD mice, which express mutated human amyloid precursor protein and presenilin-1 on a C57BL/6J background, versus their wild-type littermate controls, to compare both sex- and genotype-dependent differences. METHODS: A novel behavioral paradigm was utilized (OF-NO-SI), comprising activity measures (Open Field, OF) arena, followed by Novel Object exploration (NO) and Social Interaction (SI) of a sex-matched conspecific. Each segment consisted of two repeated trials to assess between-trial habituation. Subsequently, brain pathology (amyloid load, stress response and inflammation markers, synaptic integrity, trophic support) was assessed using qPCR and western blotting. RESULTS: Female 5XFAD mice had higher levels of human APP and amyloid-β and heightened inflammation versus males. These markers correlated with hyperactivity observed in both sexes, yet only female 5XFAD mice presented with subtle deficits in object and social exploration. Male animals had higher expression of stress markers and neurotrophic factors irrespective of genotype, this correlated with cognitive performance. CONCLUSION: The impact of sex on AD-relevant phenotypes is in line with human data and emphasizes the necessity of appropriate study design and reporting. Differential molecular profiles observed in male versus female mice offer insights into possible protective mechanisms, and hence treatment strategies.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Disease Models, Animal; Female; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Pathology, Molecular; Presenilin-1; Sex Characteristics

A Tale of Two Diseases: Exploring Mechanisms Linking Diabetes Mellitus with Alzheimer's Disease. - Lynn, Jessica; Park, Mingi; Ogunwale, Christiana; Acquaah-Mensah, George K (J Alzheimers Dis, 2022)
Dementias, including the type associated with Alzheimer's disease (AD), are on the rise worldwide. Similarly, type 2 diabetes mellitus (T2DM) is one of the most prevalent chronic diseases globally. Although mechanisms and treatments are well-established for T2DM, there remains much to be discovered. Recent research efforts have further investigated factors involved in the etiology of AD. Previously perceived to be unrelated diseases, commonalities between T2DM and AD have more recently been observed. As a result, AD has been labeled as "type 3 diabetes". In this review, we detail the shared processes that contribute to these two diseases. Insulin resistance, the main component of the pathogenesis of T2DM, is also present in AD, causing impaired brain glucose metabolism, neurodegeneration, and cognitive impairment. Dysregulation of insulin receptors and components of the insulin signaling pathway, including protein kinase B, glycogen synthase kinase 3β, and mammalian target of rapamycin are reported in both diseases. T2DM and AD also show evidence of inflammation, oxidative stress, mitochondrial dysfunction, advanced glycation end products, and amyloid deposition. The impact that changes in neurovascular structure and genetics have on the development of these conditions is also being examined. With the discovery of factors contributing to AD, innovative treatment approaches are being explored. Investigators are evaluating the efficacy of various T2DM medications for possible use in AD, including but not limited to glucagon-like peptide-1 receptor agonists and peroxisome proliferator-activated receptor-gamma agonists. Furthermore, there are 136 active trials involving 121 therapeutic agents targeting novel AD biomarkers. With these efforts, we are one step closer to alleviating the ravaging impact of AD on our communities.
Keywords: Alzheimer Disease; Animals; Biomarkers; Brain Chemistry; Cognitive Dysfunction; Diabetes Mellitus, Type 2; Glucose; Glycation End Products, Advanced; Humans; Inflammation; Insulin Resistance; Oxidative Stress; Randomized Controlled Trials as Topic

α-Lipoic Acid Has the Potential to Normalize Copper Metabolism, Which Is Dysregulated in Alzheimer's Disease. - Metsla, Kristel; Kirss, Sigrid; Laks, Katrina; Sildnik, Gertrud; Palgi, Mari; Palumaa, Teele; Tõugu, Vello; Palumaa, Peep (J Alzheimers Dis, 2022)
BACKGROUND: Alzheimer's disease (AD) is an age-dependent progressive neurodegenerative disorder and the most common cause of dementia. The treatment and prevention of AD present immense yet unmet needs. One of the hallmarks of AD is the formation of extracellular amyloid plaques in the brain, composed of amyloid-β (Aβ) peptides. Besides major amyloid-targeting approach there is the necessity to focus also on alternative therapeutic strategies. One factor contributing to the development of AD is dysregulated copper metabolism, reflected in the intracellular copper deficit and excess of extracellular copper. OBJECTIVE: In the current study, we follow the widely accepted hypothesis that the normalization of copper metabolism leads to the prevention or slowing of the disease and search for new copper-regulating ligands. METHODS: We used cell culture, ICP MS, and Drosophila melanogaster models of AD. RESULTS: We demonstrate that the natural intracellular copper chelator, α-lipoic acid (LA) translocates copper from extracellular to intracellular space in an SH-SY5Y-based neuronal cell model and is thus suitable to alleviate the intracellular copper deficit characteristic of AD neurons. Furthermore, we show that supplementation with LA protects the Drosophila melanogaster models of AD from developing AD phenotype by improving locomotor activity of fruit fly with overexpression of human Aβ with Iowa mutation in the fly brain. In addition, LA slightly weakens copper-induced smooth eye phenotype when amyloid-β protein precursor (AβPP) and beta-site AβPP cleaving enzyme 1 (BACE1) are overexpressed in eye photoreceptor cells. CONCLUSION: Collectively, these results provide evidence that LA has the potential to normalize copper metabolism in AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Aspartic Acid Endopeptidases; Brain; Cell Line; Copper; Disease Models, Animal; Drosophila melanogaster; Humans; Neurons; Thioctic Acid

ANMerge: A Comprehensive and Accessible Alzheimer's Disease Patient-Level Dataset. - Birkenbihl, Colin; Westwood, Sarah; Shi, Liu; Nevado-Holgado, Alejo; Westman, Eric; Lovestone, Simon; Hofmann-Apitius, Martin (J Alzheimers Dis, 2021)
BACKGROUND: Accessible datasets are of fundamental importance to the advancement of Alzheimer's disease (AD) research. The AddNeuroMed consortium conducted a longitudinal observational cohort study with the aim to discover AD biomarkers. During this study, a broad selection of data modalities was measured including clinical assessments, magnetic resonance imaging, genotyping, transcriptomic profiling, and blood plasma proteomics. Some of the collected data were shared with third-party researchers. However, this data was incomplete, erroneous, and lacking in interoperability. OBJECTIVE: To provide the research community with an accessible, multimodal, patient-level AD cohort dataset. METHODS: We systematically addressed several limitations of the originally shared resources and provided additional unreleased data to enhance the dataset. RESULTS: In this work, we publish and describe ANMerge, a new version of the AddNeuroMed dataset. ANMerge includes multimodal data from 1,702 study participants and is accessible to the research community via a centralized portal. CONCLUSION: ANMerge is an information rich patient-level data resource that can serve as a discovery and validation cohort for data-driven AD research, such as, for example, machine learning and artificial intelligence approaches.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Datasets as Topic; Female; Gene Expression Profiling; Genotype; Humans; Magnetic Resonance Imaging; Male; Proteomics

Anti-Aβ Antibody Aducanumab Regulates the Proteome of Senile Plaques and Closely Surrounding Tissue in a Transgenic Mouse Model of Alzheimer's Disease. - Bastrup, Joakim; Hansen, Kathrine H; Poulsen, Thomas B G; Kastaniegaard, Kenneth; Asuni, Ayodeji A; Christensen, Søren; Belling, Dorthe; Helboe, Lone; Stensballe, Allan; Volbracht, Christiane (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease (AD) is characterized by accumulation of amyloid-β (Aβ) species and deposition of senile plaques (SPs). Clinical trials with the anti-Aβ antibody aducanumab have been completed recently. OBJECTIVE: To characterize the proteomic profile of SPs and surrounding tissue in a mouse model of AD in 10-month-old tgAPPPS1-21 mice after chronic treatment with aducanumab for four months with weekly dosing (10 mg/kg). METHODS: After observing significant reduction of SP numbers in hippocampi of aducanumab-treated mice, we applied a localized proteomic analysis by combining laser microdissection and liquid chromatography-tandem mass spectrometry (LC-MS/MS) of the remaining SPs in hippocampi. We microdissected three subregions, containing SPs, SP penumbra level 1, and an additional penumbra level 2 to follow the proteomic profile as gradient. RESULTS: In the aducanumab-treated mice, we identified 17 significantly regulated proteins that were associated with 1) mitochondria and metabolism (ACAT2, ATP5J, ETFA, EXOG, HK1, NDUFA4, NDUFS7, PLCB1, PPP2R4), 2) cytoskeleton and axons (ADD1, CAPZB, DPYSL3, MAG), 3) stress response (HIST1H1C/HIST1H1D, HSPA12A), and 4) AβPP trafficking/processing (CD81, GDI2). These pathways and some of the identified proteins are implicated in AD pathogenesis. Proteins associated with mitochondria and metabolism were mainly upregulated while proteins associated with AβPP trafficking/processing and stress response pathways were mainly downregulated, suggesting that aducanumab could lead to a beneficial proteomic profile around SPs in tgAPPPS1-21 mice. CONCLUSION: We identified novel proteomic patterns of SPs and surrounding tissue indicating that chronic treatment with aducanumab could inhibit Aβ toxicity and increase phagocytosis and cell viability.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Antibodies, Monoclonal, Humanized; Brain; Chromatography, Liquid; Cytoskeletal Proteins; Disease Models, Animal; Humans; Mice; Mice, Transgenic; Mitochondrial Proteins; Plaque, Amyloid; Presenilin-1; Protein Transport; Proteome; Proteomics; Stress, Physiological; Tandem Mass Spectrometry

APOE4 Copy Number-Dependent Proteomic Changes in the Cerebrospinal Fluid. - Berger, Miles; Cooter, Mary; Roesler, Alexander S; Chung, Stacey; Park, John; Modliszewski, Jennifer L; VanDusen, Keith W; Thompson, J Will; Moseley, Arthur; Devinney, Michael J; Smani, Shayan; Hall, Ashley; et al. (J Alzheimers Dis, 2021)
BACKGROUND: APOE4 has been hypothesized to increase Alzheimer's disease risk by increasing neuroinflammation, though the specific neuroinflammatory pathways involved are unclear. OBJECTIVE: Characterize cerebrospinal fluid (CSF) proteomic changes related to APOE4 copy number. METHODS: We analyzed targeted proteomic data from ADNI CSF samples using a linear regression model adjusting for age, sex, and APOE4 copy number, and additional linear models also adjusting for AD clinical status or for CSF Aβ, tau, or p-tau levels. False discovery rate was used to correct for multiple comparisons correction. RESULTS: Increasing APOE4 copy number was associated with a significant decrease in a CRP peptide level across all five models (q < 0.05 for each), and with significant increases in ALDOA, CH3L1 (YKL-40), and FABPH peptide levels (q < 0.05 for each) except when controlling for AD clinical status or neurodegeneration biomarkers (i.e., CSF tau or p-tau). In all models except the one controlling for CSF Aβ levels, though not statistically significant, there was a consistent inverse direction of association between APOE4 copy number and the levels of all 24 peptides from all 8 different complement proteins measured. The odds of this happening by chance for 24 unrelated peptides would be less than 1 in 16 million. CONCLUSION: Increasing APOE4 copy number was associated with decreased CSF CRP levels across all models, and increased CSF ALDOA, CH3L1, and FABH levels when controlling for CSF Aβ levels. Increased APOE4 copy number may also be associated with decreased CSF complement pathway protein levels, a hypothesis for investigation in future studies.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Biomarkers; Chitinase-3-Like Protein 1; DNA Copy Number Variations; Female; Fructose-Bisphosphate Aldolase; Humans; Male; Proteomics; Receptors, Immunologic

Assessing the Progression of Alzheimer's Disease in Real-World Settings in Three European Countries. - Lladó, Albert; Froelich, Lutz; Khandker, Rezaul K; Roset, Montserrat; Black, Christopher M; Lara, Nuria; Chekani, Farid; Ambegaonkar, Baishali M (J Alzheimers Dis, 2021)
BACKGROUND: There exists considerable variation in disease progression rates among patients with Alzheimer's disease (AD). OBJECTIVE: The primary objective of this observational study is to assess the progression of AD by characterizing cognitive, functional, and behavioral changes during the follow-up period between 6 and 24 months. METHODS: A longitudinal prospective study with community-dwelling patients with an established clinical diagnosis of AD of mild to moderate severity was conducted in Germany, Spain and the UK. A sample of 616 patients from 69 sites was included. RESULTS: Patients had a mean of 1.9 years (SD = 1.9) since AD diagnosis at study inclusion. Cognitive symptoms were reported to have first occurred a mean of 1.1 years (SD = 1.7) prior to AD diagnosis and 1.4 (SD = 1.8) years prior to AD treatment. Patients initially diagnosed with mild and moderate AD spent a median (95%CI) of 3.7 (2.8; 4.4) and 11.1 (6.1, 'not reached') years until progression to moderate and severe AD, respectively, according to the Mini-Mental State Examination (MMSE) scores. A mixed model developed for cognitive, functional, and neuropsychiatric scores, obtained from study patients at baseline and during follow-up period, showed progressive deterioration of AD patients over time. CONCLUSION: The study showed a deterioration of cognitive, functional, and neuropsychiatric functions during the follow-up period. Cognitive deterioration was slightly faster in patients with moderate AD compared to mild AD. The duration of moderate AD can be overestimated due to the use of retrospective data, lack of availability of MMSE scores in clinical charts and exclusion of patients at time of institutionalization.
Keywords: Alzheimer Disease; Cholinesterase Inhibitors; Cognition Disorders; Disease Progression; Europe; Germany; Humans; Institutionalization; Neuropsychological Tests; Spain

Automatic Subtyping of Individuals with Primary Progressive Aphasia. - Themistocleous, Charalambos; Ficek, Bronte; Webster, Kimberly; den Ouden, Dirk-Bart; Hillis, Argye E; Tsapkini, Kyrana (J Alzheimers Dis, 2021)
BACKGROUND: The classification of patients with primary progressive aphasia (PPA) into variants is time-consuming, costly, and requires combined expertise by clinical neurologists, neuropsychologists, speech pathologists, and radiologists. OBJECTIVE: The aim of the present study is to determine whether acoustic and linguistic variables provide accurate classification of PPA patients into one of three variants: nonfluent PPA, semantic PPA, and logopenic PPA. METHODS: In this paper, we present a machine learning model based on deep neural networks (DNN) for the subtyping of patients with PPA into three main variants, using combined acoustic and linguistic information elicited automatically via acoustic and linguistic analysis. The performance of the DNN was compared to the classification accuracy of Random Forests, Support Vector Machines, and Decision Trees, as well as to expert clinicians' classifications. RESULTS: The DNN model outperformed the other machine learning models as well as expert clinicians' classifications with 80% classification accuracy. Importantly, 90% of patients with nfvPPA and 95% of patients with lvPPA was identified correctly, providing reliable subtyping of these patients into their corresponding PPA variants. CONCLUSION: We show that the combined speech and language markers from connected speech productions can inform variant subtyping in patients with PPA. The end-to-end automated machine learning approach we present can enable clinicians and researchers to provide an easy, quick, and inexpensive classification of patients with PPA.
Keywords: Acoustics; Aged; Aphasia, Primary Progressive; Decision Trees; Female; Humans; Linguistics; Machine Learning; Male; Models, Theoretical; Neural Networks, Computer; Primary Progressive Nonfluent Aphasia; Reproducibility of Results; Support Vector Machine

The Behavioral and Psychological Symptoms of Dementia in Down Syndrome Scale (BPSD-DS II): Optimization and Further Validation. - Dekker, Alain D; Ulgiati, Aurora M; Groen, Henk; Boxelaar, Vincent A; Sacco, Silvia; Falquero, Ségolène; Carfi, Angelo; di Paola, Antonella; Benejam, Bessy; Valldeneu, Silvia; Fopma, Roelie; Oosterik, Marjo; et al. (J Alzheimers Dis, 2021)
BACKGROUND: People with Down syndrome (DS) are at high risk to develop Alzheimer's disease dementia (AD). Behavioral and psychological symptoms of dementia (BPSD) are common and may also serve as early signals for dementia. However, comprehensive evaluation scales for BPSD, adapted to DS, are lacking. Therefore, we previously developed the BPSD-DS scale to identify behavioral changes between the last six months and pre-existing life-long characteristic behavior. OBJECTIVE: To optimize and further study the scale (discriminative ability and reliability) in a large representative DS study population. METHODS: Optimization was based on item irrelevance and clinical experiences obtained in the initial study. Using the shortened and refined BPSD-DS II, informant interviews were conducted to evaluate 524 individuals with DS grouped according to dementia status: no dementia (DS, N = 292), questionable dementia (DS + Q, N = 119), and clinically diagnosed dementia (DS + AD, N = 113). RESULTS: Comparing item change scores between groups revealed prominent changes in frequency and severity for anxious, sleep-related, irritable, restless/stereotypic, apathetic, depressive, and eating/drinking behavior. For most items, the proportion of individuals displaying an increased frequency was highest in DS + AD, intermediate in DS + Q, and lowest in DS. For various items within sections about anxious, sleep-related, irritable, apathetic, and depressive behaviors, the proportion of individuals showing an increased frequency was already substantial in DS + Q, suggesting that these changes may serve as early signals of AD in DS. Reliability data were promising. CONCLUSION: The optimized scale yields largely similar results as obtained with the initial version. Systematically evaluating BPSD in DS may increase understanding of changes among caregivers and (timely) adaptation of care/treatment.
Keywords: Adult; Aged; Anxiety; Dementia; Down Syndrome; Female; Humans; Irritable Mood; Male; Middle Aged; Reproducibility of Results; Symptom Assessment

Broader Insights into Understanding Tumor Necrosis Factor and Neurodegenerative Disease Pathogenesis Infer New Therapeutic Approaches. - Clark, I A; Vissel, B (J Alzheimers Dis, 2021)
Proinflammatory cytokines such as tumor necrosis factor (TNF), with its now appreciated key roles in neurophysiology as well as neuropathophysiology, are sufficiently well-documented to be useful tools for enquiry into the natural history of neurodegenerative diseases. We review the broader literature on TNF to rationalize why abruptly-acquired neurodegenerative states do not exhibit the remorseless clinical progression seen in those states with gradual onsets. We propose that the three typically non-worsening neurodegenerative syndromes, post-stroke, post-traumatic brain injury (TBI), and post cardiac arrest, usually become and remain static because of excess cerebral TNF induced by the initial dramatic peak keeping microglia chronically activated through an autocrine loop of microglial activation through excess cerebral TNF. The existence of this autocrine loop rationalizes post-damage repair with perispinal etanercept and proposes a treatment for cerebral aspects of COVID-19 chronicity. Another insufficiently considered aspect of cerebral proinflammatory cytokines is the fitness of the endogenous cerebral anti-TNF system provided by norepinephrine (NE), generated and distributed throughout the brain from the locus coeruleus (LC). We propose that an intact LC, and therefore an intact NE-mediated endogenous anti-cerebral TNF system, plus the DAMP (damage or danger-associated molecular pattern) input having diminished, is what allows post-stroke, post-TBI, and post cardiac arrest patients a strong long-term survival advantage over Alzheimer's disease and Parkinson's disease sufferers. In contrast, Alzheimer's disease and Parkinson's disease patients remorselessly worsen, being handicapped by sustained, accumulating, DAMP and PAMP (pathogen-associated molecular patterns) input, as well as loss of the LC-origin, NE-mediated, endogenous anti-cerebral TNF system. Adrenergic receptor agonists may counter this.
Keywords: Alzheimer Disease; Anti-Inflammatory Agents, Non-Steroidal; Brain; Brain Injuries; COVID-19; Disease Progression; Etanercept; Heart Arrest; Humans; Locus Coeruleus; Neurodegenerative Diseases; Norepinephrine; Parkinson Disease; Risk Factors; SARS-CoV-2; Stroke; Survivors; Tumor Necrosis Factor-alpha

Cannabidiol Ameliorates Cognitive Function via Regulation of IL-33 and TREM2 Upregulation in a Murine Model of Alzheimer's Disease. - Khodadadi, Hesam; Salles, Évila Lopes; Jarrahi, Abbas; Costigliola, Vincenzo; Khan, M B; Yu, Jack C; Morgan, John C; Hess, David C; Vaibhav, Kumar; Dhandapani, Krishnan M; Baban, Babak (J Alzheimers Dis, 2021)
There is a dire need for due innovative therapeutic modalities to improve outcomes of AD patients. In this study, we tested whether cannabidiol (CBD) improves outcomes in a translational model of familial AD and to investigate if CBD regulates interleukin (IL)-33 and triggering receptor expressed on myeloid cells 2 (TREM2), which are associated with improved cognitive function. CBD was administered to 5xFAD mice, which recapitulate early onset, familial AD. Behavioral tests and immunoassays were used to evaluate cognitive and motor outcomes. Our findings suggest that CBD treatment enhanced IL-33 and TREM2 expression, ameliorated the symptoms of AD, and retarded cognitive decline.
Keywords: Alzheimer Disease; Animals; Cannabidiol; Cognition; Disease Models, Animal; Humans; Interleukin-33; Male; Membrane Glycoproteins; Mice; Mice, Transgenic; Receptors, Immunologic; Up-Regulation

COVID-19: Association Between Increase of Behavioral and Psychological Symptoms of Dementia During Lockdown and Caregivers' Poor Mental Health. - Pongan, Elodie; Dorey, Jean-Michel; Borg, Céline; Getenet, Jean Claude; Bachelet, Romain; Lourioux, Charles; Laurent, Bernard; Rey, Romain; Rouch, Isabelle (J Alzheimers Dis, 2021)
BACKGROUND: From March 2020, the support and care systems for caregivers and people with dementia (PWD) were suspended or dramatically changed due to the lockdown during the world pandemic of COVID-19. Thus, these changes in living conditions have had deleterious consequences on the behavior of PWD and subsequently on their caregivers' mental health, the two being linked. OBJECTIVE: Our study aimed to examine changes in behavior among PWD and to look for associations between the evolution of behavioral and psychological symptoms of dementia (BPSD) and caregivers' mental health in the context of COVID-19. METHODS: The study was conducted among caregivers of PWD living at home in France. Caregivers were interviewed via an anonymous cross-sectional online survey during the first lockdown between April 15 and June 15, 2020. RESULTS: Three hundred and eighty-nine caregivers accompanying a relative living at home participated in the study; 43.3%of the PWD presented a worsening of BPSD during the lockdown. With multivariate logistic regressions, a significant association was observed between "more BPSD" and burden, anxiety and depression, between "BPSD equivalent" and anxiety and depression, and between "emerging BPSD" and only depression. CONCLUSION: The lockdown seems to have an impact on behavioral disorders in PWD and these disorders are associated with poorer mental health of caregivers. Our findings suggest attention should be given to caregivers of PWD who have BPSD before lockdown and the need for continued consultations and professional help in case of new lockdowns.
Keywords: Aged; Aged, 80 and over; Caregivers; Communicable Disease Control; COVID-19; Cross-Sectional Studies; Dementia; Female; France; Humans; Male; Mental Disorders; Mental Health; Middle Aged; Surveys and Questionnaires

Current and Future Prevalence Estimates of Mild Cognitive Impairment, Dementia, and Its Subtypes in a Population-Based Sample of People 70 Years and Older in Norway: The HUNT Study. - GjØra, Linda; Strand, Bjørn Heine; Bergh, Sverre; Borza, Tom; Brækhus, Anne; Engedal, Knut; Johannessen, Aud; Kvello-Alme, Marte; Krokstad, Steinar; Livingston, Gill; Matthews, Fiona E; Myrstad, Christian; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Having accurate, up-to-date information on the epidemiology of mild cognitive impairment (MCI) and dementia is imperative. OBJECTIVE: To determine the prevalence of MCI and dementia in Norway using data from a large population-based study. METHODS: All people 70 + years of age, n = 19,403, in the fourth wave of the Trøndelag Health Study (HUNT4) were invited to participate in the study HUNT4 70 + . Trained health personnel assessed participants using cognitive tests at a field station, at homes, or at their nursing home. Interviewers also completed a structured carer questionnaire in regard to participants suspected of having dementia. Clinical experts made diagnoses according to DSM-5 criteria. We calculated prevalence weighing the data to ensure population representativeness. RESULTS: A total of 9,930 (51.2%) of the possible 19,403 people participated, and 9,663 of these had sufficient information for analysis. Standardized prevalence of dementia and MCI was 14.6% (95% confidence interval (CI) 13.9-15.4) and 35.3% (95% CI 34.3-36.4), respectively. Dementia was more prevalent in women and MCI more prevalent in men. The most prevalent dementia subtype was Alzheimer's disease (57%). By adding data collected from a study of persons < 70 years in the same region, we estimate that there are 101,118 persons with dementia in Norway in 2020, and this is projected to increase to 236,789 and 380,134 in 2050 and 2100, respectively. CONCLUSION: We found a higher prevalence of dementia and MCI than most previous studies. The present prevalence and future projections are vital for preparing for future challenges to the healthcare system and the entire society.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Dementia; Female; Forecasting; Humans; Male; Mental Status and Dementia Tests; Neuropsychological Tests; Norway; Prevalence; Sex Factors; Surveys and Questionnaires

Dementia-Friendly "Design": Impact on COVID-19 Death Rates in Long-Term Care Facilities Around the World. - Olson, Nancy L; Albensi, Benedict C (J Alzheimers Dis, 2021)
Persons with dementia (PWD) make up a large portion of the long-term care (LTC) population the world over. Before a global pandemic swept the world, governments and healthcare providers struggled with how to best care for this unique population. One of the greatest challenges is a PWD's tendency to "walk with purpose" and exhibit unsafe wayfinding and elopement, which places them at risk of falls and injury. Past solutions included increased use of restraints and pharmacological interventions, but these have fallen out of favor over the years and are not optimal. These challenges put enormous strain on staff and caregivers, who are often poorly trained in dementia care, underpaid, overworked, and overstressed. PWD are impacted by these stresses, and unmet needs in LTC places an even greater stress on them and increases their risks of morbidity and mortality. The physical design of their environments contributes to the problem. Old, institutionalized buildings have poor lighting, poor ventilation, long dead-end hallways, poor visual cues, lack of home-like décor, shared bedrooms and bathrooms, and are often dense and overcrowded. These design elements contribute to the four 'A's' of dementia: apathy, anxiety, agitation, and aggression, and they also contributed to the rapid spread of COVID-19 in these facilities the world over. In this review, we present current "dementia friendly" design models in the home, community, and LTC, and argue how they could have saved lives during the pandemic and reduced the stresses on both the dementia resident and the caregiver/staff.
Keywords: COVID-19; Dementia; Environment Design; Health Services Needs and Demand; Humans; Long-Term Care; Pandemics; Quality of Life

Effects of COVID-19 Home Confinement on Mental Health in Individuals with Increased Risk of Alzheimer's Disease. - Soldevila-Domenech, Natalia; Forcano, Laura; Boronat, Anna; Lorenzo, Thais; Piera, Iris; Puig-Pijoan, Albert; Mateus, Julian; González de Echevarri Gómez, José María; Knezevic, Iva; Soteras, Anna; Fauria, Karine; Pizarro, Nieves; et al. (J Alzheimers Dis, 2021)
We explored the impact of the Spanish COVID-19 strict home confinement on mental health and cognition in non-infected subjects (N = 16, 60-80 years) diagnosed with subjective cognitive decline and APOEɛ3/ɛ4 carriers. Mental health was monitored for 2 months on a daily, weekly, or monthly basis, and compared to pre-confinement values. Emotional distress, anxiety, and depression scores increased to pathological threshold values during and after confinement. Those with lower mood during confinement experienced a decline in their mood after confinement. Cognition did not change. These preliminary results suggest that mental health consequences of corona measures in preclinical stages of Alzheimer's disease should be further evaluated.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Anxiety Disorders; Apolipoprotein E3; Apolipoprotein E4; Cognition Disorders; Cognitive Dysfunction; COVID-19; Depressive Disorder; Female; Humans; Male; Mental Health; Middle Aged; Psychological Distress; Quarantine; Risk; Spain

Elevated Norepinephrine Metabolism Gauges Alzheimer's Disease-Related Pathology and Memory Decline. - Riphagen, Joost M; van Egroo, Maxime; Jacobs, Heidi I L (J Alzheimers Dis, 2021)
The noradrenergic (NE) locus coeruleus (LC) is vulnerable to hyperphosphorylated tau, and dysregulated NE-metabolism is linked to greater tau and disease progression. We investigated whether elevated NE-metabolism alone predicts memory decline or whether concomitant presence of tau and amyloid-β is required. Among 114 memory clinic participants, time trends (max. six years) showed dose-response declines in learning across groups with elevated NE-metabolite 3-methoxy-4-hydroxyphenylethyleneglycol (MHPG) with no, one, or two Alzheimer's disease biomarkers; and no decline in the low MHPG group. Elevated MHPG is required and sufficient to detect learning declines, supporting a pathophysiologic model including the LC-NE system contributing to initial Alzheimer's disease-related processes.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Cohort Studies; Disease Progression; Female; Humans; Learning; Locus Coeruleus; Male; Memory Disorders; Methoxyhydroxyphenylglycol; Middle Aged; Neuropsychological Tests; Norepinephrine; Predictive Value of Tests; tau Proteins

Is Engagement in Intellectual and Social Leisure Activities Protective Against Dementia Risk? Evidence from the English Longitudinal Study of Ageing. - Almeida-Meza, Pamela; Steptoe, Andrew; Cadar, Dorina (J Alzheimers Dis, 2021)
BACKGROUND: Studies have suggested that mentally stimulating activities and socially engaged lifestyles may reduce dementia risk; however, it is unclear which activities are more beneficial. OBJECTIVE: We investigated intellectual and social leisure activities in relation to dementia incidence and explored the modifying role of sex and marital status in these associations. METHODS: The sample was comprised of 8,030 participants aged 50+ from the English Longitudinal Study of Ageing, who joined at wave 1 (2002-2003), or waves 3 (2006-2007), or 4 (2008-2009). The end of the study period was wave 8 (2016-2017). Subdistribution hazard models investigated the role of leisure activities grouped into intellectual and social domains in relation to dementia while accounting for the risk of death. Subsequent analyses were conducted with individual leisure activities. RESULTS: During the study period of up to 15 years, 412 participants developed dementia, and 2,192 died. We found that increased engagement in the intellectual activities' domain was associated with a decreased dementia incidence (SHR 0.85, 95% CI 0.76-0.96, p = 0.007), independent of the risk of death in married individuals, but not in those who were single, divorced, or widowed. Individual analyses for each leisure activity showed independent associations for reading newspapers in females (SHR 0.65, 95% CI 0.49-0.84, p = 0.001), mobile phone usage in males (SHR 0.61, 95% CI 0.45-0.84, p = 0.002), and having hobbies for married individuals (SHR 0.70, 95% CI 0.51-0.95, p = 0.02). CONCLUSION: We found that intellectual leisure activities contribute to lower dementia risk in a representative population of English adults, suggesting intervention opportunities.
Keywords: Aged; Aged, 80 and over; Aging; Dementia; Female; Humans; Incidence; Leisure Activities; Life Style; Longitudinal Studies; Male; Marital Status; Middle Aged; Proportional Hazards Models; Sex Factors; Social Behavior; Surveys and Questionnaires; Survival Analysis; United Kingdom

Is the Frontal Lobe the Primary Target of SARS-CoV-2? - Toniolo, Sofia; Di Lorenzo, Francesco; Scarioni, Marta; Frederiksen, Kristian Steen; Nobili, Flavio (J Alzheimers Dis, 2021)
Acute delirium and other neuropsychiatric symptoms have frequently been reported in COVID-19 patients and are variably referred to as acute encephalopathy, COVID-19 encephalopathy, SARS-CoV-2 encephalitis, or steroid-responsive encephalitis. COVID-19 specific biomarkers of cognitive impairment are currently lacking, but there is some evidence that SARS-CoV-2 could preferentially and directly target the frontal lobes, as suggested by behavioral and dysexecutive symptoms, fronto-temporal hypoperfusion on MRI, EEG slowing in frontal regions, and frontal hypometabolism on 18F-FDG-PET imaging. We suggest that an inflammatory parainfectious process targeting preferentially the frontal lobes (and/or frontal networks) could be the underlying cause of these shared clinical, neurophysiological, and imaging findings in COVID-19 patients. We explore the biological mechanisms and the clinical biomarkers that might underlie such disruption of frontal circuits and highlight the need of standardized diagnostic procedures to be applied when investigating patients with these clinical findings. We also suggest the use of a unique label, to increase comparability across studies.
Keywords: Acute Febrile Encephalopathy; Biomarkers; COVID-19; Delirium; Electroencephalography; Frontal Lobe; Humans; Magnetic Resonance Imaging; Nerve Net; SARS-CoV-2; Virulence

Gut Microbiome Features of Chinese Patients Newly Diagnosed with Alzheimer's Disease or Mild Cognitive Impairment. - Guo, Mingyan; Peng, Jun; Huang, Xiaoyan; Xiao, Lingjun; Huang, Fenyan; Zuo, Zhiyi (J Alzheimers Dis, 2021)
BACKGROUND: Patients with Alzheimer's disease (AD) have gut microbiome alterations compared with healthy controls. However, previous studies often assess AD patients who have been on medications or other interventions for the disease. Also, simultaneous determination of gut microbiome in patients with mild cognitive impairment (MCI) or AD in a study is rare. OBJECTIVE: To determine whether there was a gut microbiome alteration in patients newly diagnosed with AD or MCI and whether the degree of gut microbiome alteration was more severe in patients with AD than patients with MCI. METHODS: Fecal samples of 18 patients with AD, 20 patients with MCI, and 18 age-matched healthy controls were collected in the morning for 16S ribosomal RNA sequencing. No patient had medications or interventions for AD or MCI before the samples were collected. RESULTS: Although there was no difference in the microbial α-diversity among the three groups, patients with AD or MCI had increased β-diversity compared with healthy controls. Patients with AD had decreased Bacteroides, Lachnospira, and Ruminiclostridium_9 and increased Prevotella at the genus level compared with healthy controls. The changing direction of these genera in patients with MCI was the same as patients with AD. However, Lachnospira was the only genus whose abundance in patients with MCI was statistically significantly lower than healthy controls. Bacteroides, Lachnospira, and Ruminiclostridium_9 were positively associated with better cognitive functions whereas Prevotella was on the contrary when subjects of all three groups were considered. The negative correlation of Prevotella with cognitive functions remained among patients with MCI. CONCLUSION: Patients newly diagnosed with AD or MCI have gut dysbiosis that includes the decrease of potentially protective microbiome, such as Bacteroides, and the increase of microbiome that can promote inflammation, such as Prevotella. Our results support a novel idea that the degree of gut dysbiosis is worsened with the disease stage from MCI to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Asians; Biodiversity; China; Cognition; Cognitive Dysfunction; Disease Progression; Feces; Female; Gastrointestinal Microbiome; Humans; Male; Middle Aged; RNA, Ribosomal, 16S

How Do Persons with Young and Late Onset Dementia Die? - Roβmeier, Carola; Hartmann, Julia; Riedl, Lina; Dorn, Bianca; Fischer, Julia; Hartmann, Florentine; Egert-Schwender, Silvia; Kehl, Victoria; Schneider-Schelte, Helga; Jox, Ralf J; Dinkel, Andreas; Diehl-Schmid, Janine (J Alzheimers Dis, 2021)
BACKGROUND: End of life symptoms and symptom management as well as the quality of dying (QoD) of persons with advanced dementia (PWAD) have not yet been systematically studied in Germany. OBJECTIVE: 1) To investigate symptoms, treatment and care at the end of life, advance care planning, and circumstances of death of recently deceased PWAD; 2) To determine whether there are differences between young and late onset dementia (YOD and LOD). METHODS: The study was performed in the context of the project EPYLOGE (IssuEs in Palliative care for persons in advanced and terminal stages of Young-onset and Late-Onset dementia in Germany). Closest relatives of recently deceased patients with advanced YOD (N = 46) and LOD (N = 54) living at home or in long term care were interviewed. RESULTS: Circumstances of death, symptoms, and treatment appeared to be similar between YOD and LOD, except that persons with LOD had significantly more somatic comorbidities and were admitted to hospital in the last three months of life more often than persons with LOD. At end of life, 60% of PWAD appeared to be "at peace". Difficulty swallowing, gurgling, shortness of breath, and discomfort were observed most frequently. Large interindividual differences in suffering and QoD were present. Determinants of QoD were not identified. CONCLUSION: Our findings suggest that low QoD was caused by inadequate recognition and/or insufficient treatment of burdensome physical and emotional symptoms. PWADs' needs should be assessed regularly, and strategies focusing on treatment and implementing support for both the patient and caregiver must be established.
Keywords: Advance Care Planning; Age of Onset; Aged; Aged, 80 and over; Caregivers; Dementia; Female; Humans; Long-Term Care; Male; Palliative Care; Quality of Life

The Impact of a Global Pandemic on People Living with Dementia and Their Care Partners: Analysis of 417 Lived Experience Reports. - Tam, Mallorie T; Dosso, Jill A; Robillard, Julie M (J Alzheimers Dis, 2021)
BACKGROUND: The COVID-19 pandemic is impacting the physical and emotional health of older adults living with dementia and their care partners. OBJECTIVE: Using a patient-centered approach, we explored the experiences and needs of people living with dementia and their care partners during the COVID-19 pandemic as part of an ongoing evaluation of dementia support services in British Columbia, Canada. METHODS: A survey instrument was developed around the priorities identified in the context of the COVID-19 and Dementia Task Force convened by the Alzheimer Society of Canada. RESULTS: A total of 417 surveys were analyzed. Overall, respondents were able to access information that was helpful for maintaining their own health and managing a period of social distancing. Care partners reported a number of serious concerns, including the inability to visit the person that they care for in long-term or palliative care. Participants also reported that the pandemic increased their levels of stress overall and that they felt lonelier and more isolated than they did before the pandemic. The use of technology was reported as a way to connect socially with their loved ones, with the majority of participants connecting with others at least twice per week. CONCLUSION: Looking at the complex effects of a global pandemic through the experiences of people living with dementia and their care partners is vital to inform healthcare priorities to restore their quality of life and health and better prepare for the future.
Keywords: Adaptation, Psychological; Aged; Alzheimer Disease; British Columbia; Caregivers; COVID-19; Disabled Persons; Female; Humans; Loneliness; Male; Needs Assessment; Psychosocial Support Systems; Social Isolation; Social Support; Stress, Psychological; Surveys and Questionnaires

Impact of Social Isolation on People with Dementia and Their Family Caregivers. - Azevedo, Lílian Viana Dos Santos; Calandri, Ismael Luis; Slachevsky, Andrea; Graviotto, Héctor Gastón; Vieira, Maria Carolina Santos; Andrade, Caíssa Bezerra de; Rossetti, Adriana Peredo; Generoso, Alana Barroso; Carmona, Karoline Carvalho; Pinto, Ludmilla Aparecida Cardoso; Sorbara, Marcos; Pinto, Alejandra; et al. (J Alzheimers Dis, 2021)
BACKGROUND: People with dementia and their family caregivers may face a great burden through social isolation due to the COVID-19 pandemic, which can be manifested as various behavioral and clinical symptoms. OBJECTIVE: To investigate the impacts of social isolation due to the COVID-19 pandemic on individuals with dementia and their family caregivers. METHODS: Two semi-structured questionnaires were applied via telephone to family caregivers of people diagnosed with dementia in three cities in Argentina, Brazil, and Chile, in order to assess clinical and behavioral changes in people with dementia and in their caregivers. RESULTS: In general, 321 interviews were conducted. A significant decline in memory function has been reported among 53.0%of people with dementia. In addition, 31.2%of individuals with dementia felt sadder and 37.4%had increased anxiety symptoms. These symptoms of anxiety were greater in individuals with mild to moderate dementia, while symptoms of agitation were greater in individuals with severe dementia. Moreover, compulsive-obsessive behavior, hallucinations, increased forgetfulness, altered appetite, and increased difficulty in activities of daily living were reported more frequently among individuals with moderate to severe dementia. Caregivers reported feeling more tired and overwhelmed during this period and these symptoms were also influenced by the severity of dementia. CONCLUSION: Social isolation during the COVID-19 pandemic triggered a series of negative behavioral repercussions, both for people with dementia and for their family caregivers in these three South American countries.
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Argentina; Brazil; Caregivers; Chile; COVID-19; Dementia; Female; Humans; Male; Middle Aged; Pandemics; Physical Distancing; Social Isolation; Surveys and Questionnaires

Implementing Delirium Prevention in the Era of COVID-19. - Radhakrishnan, Nila S; Mufti, Mariam; Ortiz, Daniel; Maye, Suzanne T; Melara, Jennifer; Lim, Duke; Rosenberg, Eric I; Price, Catherine C (J Alzheimers Dis, 2021)
Patients admitted with COVID-19 can develop delirium due to predisposing factors, isolation, and the illness itself. Standard delirium prevention methods focus on interaction and stimulation. It can be challenging to deliver these methods of care in COVID settings where it is necessary to increase patient isolation. This paper presents a typical clinical vignette of representative patients in a tertiary care hospital and how a medical team modified an evidence-based delirium prevention model to deliver high-quality care to COVID-19 patients. The implemented model focuses on four areas of delirium-prevention: Mobility, Sleep, Cognitive Stimulation, and Nutrition. Future studies will be needed to track quantitative outcome measures.
Keywords: Aged; Alzheimer Disease; COVID-19; Delirium; Humans; Male

Improving the Diagnosis of the Frontal Variant of Alzheimer's Disease with the DAPHNE Scale. - Lehingue, Elsa; Gueniat, Julien; Jourdaa, Sandra; Hardouin, Jean BenoÎt; Pallardy, Amandine; Courtemanche, Hélène; Rocher, Laetitia; Etcharry-Bouyx, Frédérique; Auriacombe, Sophie; Mollion, Hélène; Formaglio, Maıté; Rouaud, Olivier; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The frontal variant of Alzheimer's disease (fAD) is poorly understood and poorly defined. The diagnosis remains challenging. The main differential diagnosis is the behavioral variant of frontotemporal degeneration (bvFTD). For fAD, there is some dissociation between the clinical frontal presentation and imaging and neuropathological studies, which do not always find a specific involvement of the frontal lobes. DAPHNE is a behavioral scale, which demonstrated excellent performance to distinguish between bvFTD and AD. OBJECTIVE: The aim of the present study was to assess the reliability of this new tool to improve the clinical diagnosis of fAD. METHODS: Twenty fAD patients and their caregivers were prospectively included and were compared with 36 bvFTD and 22 AD patients. RESULTS: The three main behavioral disorders in the fAD patients were apathy, loss of empathy, and disinhibition. Three disorders were discriminant because they were less frequent and less severe in the fAD patients than in the bvFTD patients, namely hyperorality, neglect, and perseverations. This specific pattern of behavioral disorders was corroborated by SPECT or 18FDG PET-CT scan that showed that patients with fAD could have a medial frontal hypoperfusion, whereas in bvFTD patients the orbitofrontal cortex was the main involved region, with more diffuse hypoperfusion. CONCLUSION: We demonstrated that DAPHNE had good sensitivity and good specificity to discriminate between the three groups and in particular between fAD and bvFTD patients. DAPHNE is a quick tool that could help clinicians in memory clinics not only to differentiate bvFTD from typical AD but also from fAD.
Keywords: Aged; Alzheimer Disease; Cohort Studies; Diagnosis, Differential; Female; Frontal Lobe; Frontotemporal Dementia; Humans; Male; Middle Aged; Neuropsychological Tests

Incremental Healthcare Utilization and Cost Burden of Comorbid Insomnia in Alzheimer's Disease Patients. - Qureshi, Zaina P; Thiel, Ellen; Nelson, James; Khandker, Rezaul (J Alzheimers Dis, 2021)
BACKGROUND: Insomnia is associated with worsened clinical outcomes among Alzheimer's disease dementia (AD) patients, increased caregiver burden, and healthcare utilization. OBJECTIVE: This study aimed to characterize the incremental healthcare burden of insomnia in AD using real-world data. METHODS: A retrospective observational study was conducted on AD patients selected from the IBM® MarketScan Commercial and Medicare Supplemental Databases. AD patients with claims-based evidence of insomnia were direct matched to a non-insomnia cohort based on demographic factors. Healthcare utilization and associated costs were assessed for a 12-month follow-up period. RESULTS: A total of 3,500 insomnia AD patients and 9,884 non-insomnia AD patients were analyzed. The insomnia cohort had a higher comorbidity burden at baseline (mean score on Charlson Comorbidity Index 2.5 versus 2.2, p < 0.001) and higher proportions of patients with baseline diagnoses for other conditions including depression: 40%, insomnia cohort versus 25%, non-insomnia (p < 0.001). AD patients with insomnia were more likely to have a claim for inpatient hospitalizations (39.8%versus 32.3%), emergency room services (56.4%versus 48.0%), and skilled-nursing services (42.6%versus 31.9%) (all p < 0.05). Mean total annual healthcare costs during the 12-month follow-up period were significantly higher among AD patients with insomnia as compared to those without. (Mean costs: $37,356 versus $27,990, p < 0.001). CONCLUSION: AD patients with comorbid insomnia are more likely to use higher-cost healthcare services such as inpatient hospitalization, and skilled nursing, and have higher total healthcare costs. This real-world analysis provides evidence that AD disease management should consider proper treatment of comorbid insomnia due to the incremental burden and cost implications.
Keywords: Aged, 80 and over; Alzheimer Disease; Comorbidity; Databases, Factual; Female; Health Care Costs; Humans; Male; Medicare; Patient Acceptance of Health Care; Retrospective Studies; Sleep Initiation and Maintenance Disorders; United States

Mild Behavioral Impairment and Subjective Cognitive Decline Predict Cognitive and Functional Decline. - Ismail, Zahinoor; McGirr, Alexander; Gill, Sascha; Hu, Sophie; Forkert, Nils D; Smith, Eric E (J Alzheimers Dis, 2021)
BACKGROUND: Mild behavioral impairment (MBI) and subjective cognitive decline (SCD) are dementia risk states, and potentially represent neurobehavioral and neurocognitive manifestations, respectively, of early stage neurodegeneration. Both MBI and SCD predict incident cognitive decline and dementia, are associated with known dementia biomarkers, and are both represented in the NIA-AA research framework for AD in Stage 2 (preclinical disease). OBJECTIVE: To assess the associations of MBI and SCD, alone and in combination, with incident cognitive and functional decline in a population of older adults. We tested the hypothesis that MBI and SCD confer additive risk for decline. METHODS: Cognitively normal participants were followed up annually at Alzheimer's Disease Centers. Logistic regression assessed the relationship between baseline classification (MBI-SCD-, MBI-SCD+, MBI+SCD-, or MBI+SCD+) and 3-year outcome. RESULTS: Of 2,769 participants (mean age=76), 1,536 were MBI-SCD-, 254 MBI-SCD+, 743 MBI+SCD-, and 236 MBI+SCD+. At 3 years, 349 (12.6%) declined to CDR >0, including 23.1% of the MBI+group, 23.5% of the SCD+group, and 30.9% of the intersection group of both MBI+and SCD+participants. Compared to SCD-MBI-, we observed an ordinal progression in risk (ORs [95% CI]): 3.61 [2.42-5.38] for MBI-SCD+ (16.5% progression), 4.76 [3.57-6.34] for MBI+SCD- (20.7%), and 8.15 [5.71-11.64] for MBI+SCD+(30.9%). CONCLUSION: MBI and SCD together were associated with the greatest risk of decline. These complementary dementia risk syndromes can be used as simple and scalable methods to identify high-risk patients for workup or for clinical trial enrichment.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Disease Progression; Executive Function; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Odds Ratio; Risk Assessment

MIND Diet, Common Brain Pathologies, and Cognition in Community-Dwelling Older Adults. - Dhana, Klodian; James, Bryan D; Agarwal, Puja; Aggarwal, Neelum T; Cherian, Laurel J; Leurgans, Sue E; Barnes, Lisa L; Bennett, David A; Schneider, Julie A (J Alzheimers Dis, 2021)
BACKGROUND: MIND diet, a hybrid of the Mediterranean diet and the Dietary Approaches to Stop Hypertension diet, is associated with a slower cognitive decline and lower risk of Alzheimer's disease (AD) dementia in older adults. OBJECTIVE: We aim to examine whether the association of the MIND diet with cognition is independent of common brain pathologies. METHODS: Utilizing data from the Rush Memory and Aging Project (MAP), a longitudinal clinical-pathologic study, we studied 569 decedents with valid dietary data, cognitive testing proximate to death, and complete autopsy data at the time of these analyses. A series of regression analyses were used to examine associations of the MIND diet, dementia-related brain pathologies, and global cognition proximate to death adjusting for age, sex, education, APOEɛ4, late-life cognitive activities, and total energy intake. RESULTS: A higher MIND diet score was associated with better global cognitive functioning proximate to death (β= 0.119, SE = 0.040, p = 0.003), and neither the strength nor the significance of association changed substantially when AD pathology and other brain pathologies were included in the model. The β-estimate after controlling for global AD pathology was 0.111 (SE = 0.037, p = 0.003). The MIND diet-cognition relationship remained significant when we restricted our analysis to individuals without mild cognitive impairment at the baseline (β= 0.121, SE = 0.042, p = 0.005) or in people diagnosed with postmortem diagnosis of AD based on NIA-Reagan consensus recommendations (β= 0.114, SE = 0.050, p = 0.023). CONCLUSION: MIND diet is associated with better cognitive functioning independently of common brain pathology, suggesting that the MIND diet may contribute to cognitive resilience in the elderly.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid; Autopsy; Brain; Chicago; Cognition; Diet, Mediterranean; Female; Humans; Independent Living; Longitudinal Studies; Male; Neuropsychological Tests; Surveys and Questionnaires

Mortality After Ischemic Stroke in Patients with Alzheimer's Disease Dementia and Other Dementia Disorders. - Zupanic, Eva; von Euler, Mia; Winblad, Bengt; Xu, Hong; Secnik, Juraj; Kramberger, Milica Gregoric; Religa, Dorota; Norrving, Bo; Garcia-Ptacek, Sara (J Alzheimers Dis, 2021)
BACKGROUND: Stroke and dementia are interrelated diseases and risk for both increases with age. Even though stroke incidence and age-standardized death rates have decreased due to prevention of stroke risk factors, increased utilization of reperfusion therapies, and other changes in healthcare, the absolute numbers are increasing due to population growth and aging. OBJECTIVE: To analyze predictors of death after stroke in patients with dementia and investigate possible time and treatment trends. METHODS: A national longitudinal cohort study 2007-2017 using Swedish national registries. We compared 12,629 ischemic stroke events in patients with dementia with matched 57,954 stroke events in non-dementia controls in different aspects of patient care and mortality. Relationship between dementia status and dementia type (Alzheimer's disease and mixed dementia, vascular dementia, other dementias) and death was analyzed using Cox regressions. RESULTS: Differences in receiving intravenous thrombolysis between patients with and without dementia disappeared after the year 2015 (administered to 11.1% dementia versus 12.3% non-dementia patients, p = 0.117). One year after stroke, nearly 50% dementia and 30% non-dementia patients had died. After adjustment for demographics, mobility, nursing home placement, and comorbidity index, dementia was an independent predictor of death compared with non-dementia patients (HR 1.26 [1.23-1.29]). CONCLUSION: Dementia before ischemic stroke is an independent predictor of death. Over time, early and delayed mortality in patients with dementia remained increased, regardless of dementia type. Patients with≤80 years with prior Alzheimer's disease or mixed dementia had higher mortality rates after stroke compared to patients with prior vascular dementia.
Keywords: Aged; Aged, 80 and over; Comorbidity; Dementia; Female; Fibrinolytic Agents; Humans; Incidence; Ischemic Stroke; Male; Registries; Survival Rate; Sweden; Thrombolytic Therapy

Neuropsychiatric Symptoms in Patients with Dementia Associated with Increased Psychological Distress in Caregivers During the COVID-19 Pandemic. - Borelli, Wyllians Vendramini; Augustin, Marina Coutinho; de Oliveira, Paola Bell Felix; Reggiani, Lorenzo Casagrande; Bandeira-de-Mello, Renato Gorga; Schumacher-Schuh, Artur Francisco; Chaves, Marcia Lorena Fagundes; Castilhos, Raphael Machado (J Alzheimers Dis, 2021)
BACKGROUND: The social isolation imposed by COVID-19 pandemic can have a major impact on the mental health of dementia patients and their caregivers. OBJECTIVE: We aim to evaluate the neurological decline of patients with dementia and the caregivers' burden during the pandemic. METHODS: We performed a cross-sectional study. Caregivers of dementia patients following in the outpatient clinic were included. A structured telephone interview composed of the Neuropsychiatric Inventory Questionnaire (NPI-Q), Zarit Burden Interview (ZBI), Beck Depression (BDI) and Anxiety (BAI) Inventories to address cognitive, behavioral, and functional changes associated with social distancing during the Sars-Cov-2 outbreak. Patients were divided in two groups according to caregivers' report: with perceived Altered Cognition (AC) and Stable Cognition (SC). RESULTS: A total of 58 patients (median age: 57 years [21-87], 58.6%females) and caregivers (median age: 76.5 years [55-89], 79.3%females) were included. Cognitive decline was shown by most patients (53.4%), as well as behavioral symptoms (48.3%), especially apathy/depression (24.1%), and functional decline (34.5%). The AC group (n = 31) presented increased behavioral (67.7%versus 25.9%, p = 0.002) and functional (61.3%versus 3.7%, p < 0.001) changes when compared to the SC group. In the AC group, ZBI, BDI, NPI-Q caregiver distress, and NPI-Q patient's severity of symptoms scores were worse than the SC group (p < 0.005 for all). CONCLUSION: Patients' neuropsychiatric worsening and caregiver burden were frequent during the pandemic. Worsening of cognition was associated with increased caregivers' psychological distress.
Keywords: Adult; Aged; Aged, 80 and over; Brazil; Caregivers; COVID-19; Cross-Sectional Studies; Dementia; Female; Humans; Male; Mental Disorders; Middle Aged; Outpatient Clinics, Hospital; Pandemics; Psychological Distress; Social Isolation; Young Adult

New Frontiers in the Prevention, Diagnosis, and Treatment of Alzheimer's Disease. - Guzmán-Martínez, Leonardo; Calfío, Camila; Farías, Gonzalo A; Vilches, Cristian; Prieto, Raul; Maccioni, Ricardo B (J Alzheimers Dis, 2021)
One of the major puzzles in medical research and public health systems worldwide is Alzheimer's disease (AD), reaching nowadays a prevalence near 50 million people. This is a multifactorial brain disorder characterized by progressive cognitive impairment, apathy, and mood and neuropsychiatric disorders. The main risk of AD is aging; a normal biological process associated with a continuum dynamic involving a gradual loss of people's physical capacities, but with a sound experienced view of life. Studies suggest that AD is a break from normal aging with changes in the powerful functional capacities of neurons as well as in the mechanisms of neuronal protection. In this context, an important path has been opened toward AD prevention considering that there are elements of nutrition, daily exercise, avoidance of toxic substances and drugs, an active social life, meditation, and control of stress, to achieve healthy aging. Here, we analyze the involvement of such factors and how to control environmental risk factors for a better quality of life. Prevention as well as innovative screening programs for early detection of the disease using reliable biomarkers are becoming critical to control the disease. In addition, the failure of traditional pharmacological treatments and search for new drugs has stimulated the emergence of nutraceutical compounds in the context of a "multitarget" therapy, as well as mindfulness approaches shown to be effective in the aging, and applied to the control of AD. An integrated approach involving all these preventive factors combined with novel pharmacological approaches should pave the way for the future control of the disease.
Keywords: Acupuncture Therapy; Aging; Alzheimer Disease; Biomarkers; Dietary Supplements; Early Diagnosis; Humans; Medicine, Chinese Traditional; Meditation; Quality of Life; Treatment Outcome

Pharmacological Strategies to Improve Dendritic Spines in Alzheimer's Disease. - Ettcheto, Miren; Busquets, Oriol; Cano, Amanda; Sánchez-López, Elena; Manzine, Patricia R; Espinosa-Jimenez, Triana; Verdaguer, Ester; Sureda, Francesc X; Olloquequi, Jordi; Castro-Torres, Ruben D; Auladell, Carme; Folch, Jaume; et al. (J Alzheimers Dis, 2021)
To deeply understand late onset Alzheimer's disease (LOAD), it may be necessary to change the concept that it is a disease exclusively driven by aging processes. The onset of LOAD could be associated with a previous peripheral stress at the level of the gut (changes in the gut microbiota), obesity (metabolic stress), and infections, among other systemic/environmental stressors. The onset of LOAD, then, may result from the generation of mild peripheral inflammatory processes involving cytokine production associated with peripheral stressors that in a second step enter the brain and spread out the process causing a neuroinflammatory brain disease. This hypothesis could explain the potential efficacy of Sodium Oligomannate (GV-971), a mixture of acidic linear oligosaccharides that have shown to remodel gut microbiota and slowdown LOAD. However, regardless of the origin of the disease, the end goal of LOAD-related preventative or disease modifying therapies is to preserve dendritic spines and synaptic plasticity that underlay and support healthy cognition. Here we discuss how systemic/environmental stressors impact pathways associated with the regulation of spine morphogenesis and synaptic maintenance, including insulin receptor and the brain derived neurotrophic factor signaling. Spine structure remodeling is a plausible mechanism to maintain synapses and provide cognitive resilience in LOAD patients. Importantly, we also propose a combination of drugs targeting such stressors that may be able to modify the course of LOAD by acting on preventing dendritic spines and synapsis loss.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Dendritic Spines; Diet, Healthy; Exercise; Gastrointestinal Microbiome; Humans; Mannose; Oligosaccharides; Synapses

Primary Prevention of Dementia: An Ethical Review. - Horstkötter, Dorothee; Deckers, Kay; Köhler, Sebastian (J Alzheimers Dis, 2021)
Dementia poses important medical and societal challenges, and of all health risks people face in life, dementia is one of the most feared. Recent research indicates that up to about 40% of all cases of dementia might be preventable. A series of environmental, social, and medical risk-factors have been identified that should be targeted from midlife onwards when people are still cognitively healthy. At first glance, this seems not merely advisable, but even imperative. However, these new developments trigger a series of new ethical questions and concerns which have hardly been addressed to date. Pro-active ethical reflection, however, is crucial to ensure that the interests and well-being of those affected, ultimately all of us, are adequately respected. This is the goal of the current contribution. Against the background of a concrete case in primary dementia prevention, it provides a systematic overview of the current ethical literature and sketches an ethical research agenda. First, possible benefits of increased well-being must be balanced with the burdens of being engaged in particularly long-term interventions for which it is unclear whether they will ever pay out on a personal level. Second, while knowledge about one's options to maintain brain health might empower people, it might also undermine autonomy, put high social pressure on people, medicalize healthy adults, and stigmatize those who still develop dementia. Third, while synergistic effects might occur, the ideals of dementia prevention might also conflict with other health and non-health related values people hold in life.
Keywords: Dementia; Ethical Review; Humans; Life Style; Primary Prevention

Promoting Successful Cognitive Aging: A Ten-Year Update. - Krivanek, Taylor J; Gale, Seth A; McFeeley, Brittany M; Nicastri, Casey M; Daffner, Kirk R (J Alzheimers Dis, 2021)
A decade has passed since we published a comprehensive review in this journal addressing the topic of promoting successful cognitive aging, making this a good time to take stock of the field. Because there have been limited large-scale, randomized controlled trials, especially following individuals from middle age to late life, some experts have questioned whether recommendations can be legitimately offered about reducing the risk of cognitive decline and dementia. Despite uncertainties, clinicians often need to at least make provisional recommendations to patients based on the highest quality data available. Converging lines of evidence from epidemiological/cohort studies, animal/basic science studies, human proof-of-concept studies, and human intervention studies can provide guidance, highlighting strategies for enhancing cognitive reserve and preventing loss of cognitive capacity. Many of the suggestions made in 2010 have been supported by additional research. Importantly, there is a growing consensus among major health organizations about recommendations to mitigate cognitive decline and promote healthy cognitive aging. Regular physical activity and treatment of cardiovascular risk factors have been supported by all of these organizations. Most organizations have also embraced cognitively stimulating activities, a heart-healthy diet, smoking cessation, and countering metabolic syndrome. Other behaviors like regular social engagement, limiting alcohol use, stress management, getting adequate sleep, avoiding anticholinergic medications, addressing sensory deficits, and protecting the brain against physical and toxic damage also have been endorsed, although less consistently. In this update, we review the evidence for each of these recommendations and offer practical advice about behavior-change techniques to help patients adopt brain-healthy behaviors.
Keywords: Cognition; Cognitive Aging; Diet, Healthy; Exercise; Healthy Aging; Healthy Lifestyle; Humans

Quality of Life in Advanced Dementia with Late Onset, Young Onset, and Very Young Onset. - Hartmann, Julia; Roßmeier, Carola; Riedl, Lina; Dorn, Bianca; Fischer, Julia; Slawik, Till; Fleischhaker, Mareike; Hartmann, Florentine; Egert-Schwender, Silvia; Kehl, Victoria; Haller, Bernhard; Schneider-Schelte, Helga; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Advanced stages of dementia are characterized by severe cognitive and physical impairment. It has not yet been investigated whether persons with young onset dementia (YOD) and late onset dementia (LOD) differ in advanced disease stages. OBJECTIVES: To compare quality of life (QoL) between persons with advanced YOD and LOD; to explore the determinants of QoL; to investigate whether YOD and LOD differ with regard to symptoms and care. METHODS: The study was performed in the context of EPYLOGE (IssuEs in Palliative care for persons in advanced and terminal stages of YOD and LOD in Germany). Persons with advanced dementia (PWAD) were assessed and caregivers were interviewed. QoL was measured with the proxy rating Quality of Life in Late Stage Dementia (QUALID) scale. RESULTS: 93 persons with YOD and 98 with LOD were included. No significant differences in QoL were detected. Determinants of QoL were similar in YOD and LOD. Behavioral and psychological symptoms of dementia (BPSD), suffering and other distressing symptoms were associated with a lower QoL. In YOD but not in LOD antipsychotic treatment was associated with low QoL. The group of persons who were younger than 65 years at the time of the study visit experienced significantly more distressing symptoms than older PWAD. CONCLUSION: Overall, persons with advanced YOD do not appear to be disadvantaged compared to old and oldest PWAD. Special attention, however, must be paid to the group of the very young persons who seem to be particularly vulnerable.
Keywords: Adult; Age of Onset; Aged; Aged, 80 and over; Antipsychotic Agents; Behavioral Symptoms; Caregivers; Dementia; Disease Progression; Female; Germany; Home Care Services; Humans; Individuality; Male; Middle Aged; Pain; Palliative Care; Psychotropic Drugs; Quality of Life

Race/Ethnic Disparities in Mild Cognitive Impairment and Dementia: The Northern Manhattan Study. - Wright, Clinton B; DeRosa, Janet T; Moon, Michelle P; Strobino, Kevin; DeCarli, Charles; Cheung, Ying Kuen; Assuras, Stephanie; Levin, Bonnie; Stern, Yaakov; Sun, Xiaoyan; Rundek, Tatjana; Elkind, Mitchell S V; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Variability in dementia rates across racial and ethnic groups has been estimated at 60%. Studies suggest disparities in Caribbean Hispanic and Black populations, but community-based data are limited. OBJECTIVE: Estimate the prevalence of mild cognitive impairment (MCI) and dementia in the racially and ethnically diverse community-based Northern Manhattan Study cohort and examine sociodemographic, vascular risk factor, and brain imaging correlates. METHODS: Cases of MCI and dementia were adjudicated by a team of neuropsychologists and neurologists and prevalence was estimated across race/ethnic groups. Ordinal proportional odds models were used to estimate race/ethnic differences in the prevalence of MCI or dementia adjusting for sociodemographic variables (model 1), model 1 plus potentially modifiable vascular risk factors (model 2), and model 1 plus structural imaging markers of brain integrity (model 3). RESULTS: There were 989 participants with cognitive outcome determinations (mean age 69±9 years; 68% Hispanic, 16% Black, 14% White; 62% women; mean (±SD) follow-up five (±0.6) years). Hispanic and Black participants had greater likelihood of MCI (20%) and dementia (5%) than White participants accounting for age and education differences. Hispanic participants had greater odds of MCI or dementia than both White and Black participants adjusting for sociodemographic variables, vascular risk factors, and brain imaging factors. White matter hyperintensity burden was significantly associated with greater odds of MCI or dementia (OR = 1.3, 1.1 to 1.6), but there was no significant interaction by race/ethnicity. CONCLUSION: In this diverse community-based cohort, cross-sectional data revealed significant race/ethnic disparities in the prevalence of MCI and dementia. Longer follow-up and incidence data are needed to further clarify these relationships.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Cohort Studies; Cross-Sectional Studies; Dementia; Ethnicity; Female; Humans; Male; Middle Aged; New York City; Prevalence

Reliability of Telephone and Videoconference Methods of Cognitive Assessment in Older Adults with and without Dementia. - Hunter, Matthew B; Jenkins, Natalie; Dolan, Clare; Pullen, Hannah; Ritchie, Craig; Muniz-Terrera, Graciela (J Alzheimers Dis, 2021)
BACKGROUND: Telephone and videoconference administration of cognitive tests introduce additional sources of variance compared to in-person testing. Reviews of test-retest reliability have included mixed neurocognitive and psychiatric populations with limited consideration of methodological and statistical contributions. OBJECTIVE: We reviewed reliability estimates from comparison studies of older adults with and without dementia, considering test-retest analyses and study methods. METHODS: Medline, Embase, PsycINFO, and Web of Science were systematically searched from 1 January 2000 to 9 June 2020 for original articles comparing telephone or videoconference administered cognitive instruments to in-person administration in older adults with and without dementia or mild cognitive impairment. RESULTS: Of 4,125 articles, 23 were included: 11 telephone (N = 2 dementia cohorts) and 12 videoconference (N = 4 dementia cohorts). Telephone administered subtest scores trended in the same direction as in-person with comparable means. Person-level data were scarce. Data on dementia was only available for MMSE, with resulting subtle modality bias. MMSE, SMMSE, Letter Fluency, and HVLT-R in healthy to mild-moderate Alzheimer's disease were particularly reliable for videoconference administration. Other tests show promise but require more observations and comprehensive analyses. Most studies used high-speed stable videoconferencing hardware resulting in a lack of ecological validity for home administration. CONCLUSION: Remote administration is often consistent with in-person administration but variable and limited at the person/test level. Improved statistical design and inclusion of dementia related cohorts in telephone studies is recommended. Reliability evidence is stronger for videoconferencing but with limited applicability to home administration and severe dementia. Improved reporting of administrative procedures is recommended.
Keywords: Aged; Aged, 80 and over; Cognition; Cognitive Dysfunction; Dementia; Geriatric Assessment; Humans; Neuropsychological Tests; Remote Consultation; Reproducibility of Results; Telephone; Videoconferencing

The Right Temporal Variant of Frontotemporal Dementia Is Not Genetically Sporadic: A Case Series. - Ulugut Erkoyun, Hulya; van der Lee, Sven J; Nijmeijer, Bas; van Spaendonk, Rosalina; Nelissen, Anne; Scarioni, Marta; Dijkstra, Anke; Samancı, Bedia; Gürvit, Hakan; Yıldırım, Zerrin; Tepgeç, Fatih; Bilgic, Basar; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Right temporal variant frontotemporal dementia (rtvFTD) has been generally considered as a right sided variant of semantic variant primary progressive aphasia (svPPA), which is a genetically sporadic disorder. Recently, we have shown that rtvFTD has a unique clinical syndrome compared to svPPA and behavioral variant frontotemporal dementia. OBJECTIVE: We challenge the assumption that rtvFTD is a sporadic, non-familial variant of FTD by identifying potential autosomal dominant inheritance and related genes in rtvFTD. METHODS: We collected all subjects with a diagnosis of FTD or primary progressive aphasia who had undergone genetic screening (n = 284) and subsequently who had a genetic variant (n = 48) with a diagnosis of rtvFTD (n = 6) in 2 specialized memory clinics. RESULTS: Genetic variants in FTD related genes were found in 33% of genetically screened rtvFTD cases; including MAPT (n = 4), GRN (n = 1), and TARDBP (n = 1) genes, whereas only one svPPA case had a genetic variant in our combined cohorts. Additionally, 4 out of 6 rtvFTD subjects had a strong family history for dementia. CONCLUSION: Our results demonstrate that rtvFTD, unlike svPPA, is not a pure sporadic, but a heterogeneous potential genetic variant of FTD, and screening for genetic causes for FTD should be performed in patients with rtvFTD.
Keywords: Aphasia, Primary Progressive; DNA-Binding Proteins; Female; Frontotemporal Dementia; Functional Laterality; Genetic Testing; Genetic Variation; Gyrus Cinguli; Humans; Male; Middle Aged; Progranulins; tau Proteins

Social Robot Interventions for People with Dementia: A Systematic Review on Effects and Quality of Reporting. - Hirt, Julian; Ballhausen, Nicola; Hering, Alexandra; Kliegel, Matthias; Beer, Thomas; Meyer, Gabriele (J Alzheimers Dis, 2021)
BACKGROUND: Using non-pharmacological interventions is a current approach in dementia care to manage responsive behaviors, to maintain functional capacity, and to reduce emotional stress. Novel technologies such as social robot interventions might be useful to engage people with dementia in activities and interactions as well as to improve their cognitive, emotional, and physical status. OBJECTIVE: Assessing the effects and the quality of reporting of social robot interventions for people with dementia. METHODS: In our systematic review, we included quasi-experimental and experimental studies published in English, French, or German, irrespective of publication year. Searching CINAHL, Cochrane Library, MEDLINE, PsycINFO, and Web of Science Core Collection was supplemented by citation tracking and free web searching. To assess the methodological quality of included studies, we used tools provided by the Joanna Briggs Institute. To assess the reporting of the interventions, we applied CReDECI 2 and TIDieR. RESULTS: We identified sixteen studies published between 2012 and 2018, including two to 415 participants with mostly non-defined type of dementia. Eight studies had an experimental design. The predominant robot types were pet robots (i.e., PARO). Most studies addressed behavioral, emotion-related, and functional outcomes with beneficial, non-beneficial, and mixed results. Predominantly, cognitive outcomes were not improved. Overall, studies were of moderate methodological quality. CONCLUSION: Heterogeneous populations, intervention characteristics, and measured outcomes make it difficult to generalize the results with regard to clinical practice. The impact of social robot interventions on behavioral, emotion-related, and functional outcomes should therefore be assessed considering the severity of dementia and intervention characteristics.
Keywords: Dementia; Humans; Research; Robotics; Social Behavior

White Matter Connectivity in Incident Mild Cognitive Impairment: A Diffusion Spectrum Imaging Study of World Trade Center Responders at Midlife. - Huang, Chuan; Kritikos, Minos; Clouston, Sean A P; Deri, Yael; Serrano-Sosa, Mario; Bangiyev, Lev; Santiago-Michels, Stephanie; Gandy, Sam; Sano, Mary; Bromet, Evelyn J; Luft, Benjamin J (J Alzheimers Dis, 2021)
BACKGROUND: Individuals who participated in response efforts at the World Trade Center (WTC) following 9/11/2001 are experiencing elevated incidence of mild cognitive impairment (MCI) at midlife. OBJECTIVE: We hypothesized that white matter connectivity measured using diffusion spectrum imaging (DSI) would be restructured in WTC responders with MCI versus cognitively unimpaired responders. METHODS: Twenty responders (mean age 56; 10 MCI/10 unimpaired) recruited from an epidemiological study were characterized using NIA-AA criteria alongside controls matched on demographics (age/sex/occupation/race/education). Axial DSI was acquired on a 3T Siemen's Biograph mMR scanner (12-channel head coil) using a multi-band diffusion sequence. Connectometry examined whole-brain tract-level differences in white matter integrity. Fractional anisotropy (FA), mean diffusivity (MD), and quantified anisotropy were extracted for region of interest (ROI) analyses using the Desikan-Killiany atlas. RESULTS: Connectometry identified both increased and decreased connectivity within regions of the brains of responders with MCI identified in the corticothalamic pathway and cortico-striatal pathway that survived adjustment for multiple comparisons. MCI was also associated with higher FA values in five ROIs including in the rostral anterior cingulate; lower MD values in four ROIs including the left rostral anterior cingulate; and higher MD values in the right inferior circular insula. Analyses by cognitive domain revealed nominal associations in domains of response speed, verbal learning, verbal retention, and visuospatial learning. CONCLUSIONS: WTC responders with MCI at midlife showed early signs of neurodegeneration characterized by both increased and decreased white matter diffusivity in regions commonly affected by early-onset Alzheimer's disease.
Keywords: Brain; Cognitive Dysfunction; Diffusion Tensor Imaging; Emergency Responders; Female; Humans; Incidence; Male; Middle Aged; September 11 Terrorist Attacks; White Matter

Circulating Vitamin D Levels and Alzheimer's Disease: A Mendelian Randomization Study in the IGAP and UK Biobank. - Wang, Longcai; Qiao, Yanchun; Zhang, Haihua; Zhang, Yan; Hua, Jiao; Jin, Shuilin; Liu, Guiyou (J Alzheimers Dis, 2020)
Observational studies strongly supported the association of low levels of circulating 25-hydroxyvitamin D (25OHD) and cognitive impairment or dementia in aging populations. However, randomized controlled trials have not shown clear evidence that vitamin D supplementation could improve cognitive outcomes. In fact, some studies reported the association between vitamin D and cognitive impairment based on individuals aged 60 years and over. However, it is still unclear that whether vitamin D levels are causally associated with Alzheimer's disease (AD) risk in individuals aged 60 years and over. Here, we performed a Mendelian randomization (MR) study to investigate the causal association between vitamin D levels and AD using a large-scale vitamin D genome-wide association study (GWAS) dataset and two large-scale AD GWAS datasets from the IGAP and UK Biobank with individuals aged 60 years and over. Our results showed that genetically increased 25OHD levels were significantly associated with reduced AD risk in individuals aged 60 years and over. Hence, our findings in combination with previous literature indicate that maintaining adequate vitamin D status in older people especially aged 60 years and over, may contribute to slow down cognitive decline and forestall AD. Long-term randomized controlled trials are required to test whether vitamin D supplementation may prevent AD in older people especially those aged 60 years and may be recommended as preventive agents.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biological Specimen Banks; Cognition Disorders; Databases, Factual; Female; Genome-Wide Association Study; Humans; Hydroxycholecalciferols; Male; Mendelian Randomization Analysis; Middle Aged; Nutritional Status; United Kingdom; Vitamin D; Vitamin D Deficiency

Comparative Cognitive Effects of Choreographed Exercise and Multimodal Physical Therapy in Older Adults with Amnestic Mild Cognitive Impairment: Randomized Clinical Trial. - Bisbe, Marta; Fuente-Vidal, Andrea; López, Elisabet; Moreno, Marta; Naya, Marian; de Benetti, Claudio; Milà, Raimon; Bruna, Olga; Boada, Merce; Alegret, Montserrat (J Alzheimers Dis, 2020)
BACKGROUND: Recent research on mild cognitive impairment (MCI) has primarily focused on searching for measures to prevent or delay the progression of MCI to dementia. Physical exercise has shown to be effective in the prevention of age-related cognitive decline in elderly adults with MCI. However, the most effective type and dose of exercise for the improvement of cognition are yet to be determined. OBJECTIVE: To compare the cognitive effects of choreographed exercise (Choreography group) with a multimodal physical therapy program (Physical Therapy group) in elderly adults with amnestic MCI, a population with an increased risk of developing dementia. METHODS: We conducted a randomized clinical trial with two parallel groups under allocation concealment and assessor blinding. Participants were allocated into Choreography or Physical Therapy group and performed exercises twice per week in 60-minute sessions during 12 weeks. RESULTS: Thirty-six participants with amnestic MCI, ages 65 to 85, were assessed at baseline and after 12 weeks of intervention, by comprehensive validated neuropsychological and physical assessments. A Repeated measures General Lineal Model showed statistically significant differences in cognitive and physical outcomes. Both groups significantly improved in visual delayed recall. The Choreography group exhibited significantly more benefits on verbal recognition memory than the Physical Therapy group. CONCLUSION: Greater cognitive benefits were achieved in the choreographic intervention than in the multimodal physical therapy, mainly in those functions more related to the risk of conversion to dementia. Additional studies are needed to confirm whether the observed effects are related to delayed onset of Alzheimer's disease in elderly adults with amnestic MCI.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Combined Modality Therapy; Dance Therapy; Exercise Therapy; Female; Humans; Linear Models; Male; Neuropsychological Tests; Physical Therapy Modalities; Single-Blind Method

Dementia Care in the Time of COVID-19 Pandemic. - Tousi, Babak (J Alzheimers Dis, 2020)
Patients with dementia are particularly vulnerable during the COVID-19 pandemic. The initial response to COVID-19 promoted behavioral changes in both society and healthcare, while a long-term solution is sought by prioritizing societal values. In addition, there has been disruption to clinical care and clinical research. This pandemic might have significantly changed the care for our patients with dementia toward increased acceptance of telemedicine by the patients and providers, and its utilization in both clinical care and research.
Keywords: Betacoronavirus; Coronavirus Infections; Dementia; Health Services Accessibility; Humans; Pandemics; Pneumonia, Viral; Telemedicine

Dementia Care in Times of COVID-19: Experience at Fundació ACE in Barcelona, Spain. - Benaque, Alba; Gurruchaga, Miren Jone; Abdelnour, Carla; Hernandez, Isabel; Cañabate, Pilar; Alegret, Montserrat; Rodríguez, Isabel; Rosende-Roca, Maitee; Tartari, Juan Pablo; Esteban, Ester; López, Rogelio; Gil, Silvia; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Fundació ACE is a non-profit organization providing care based on a holistic model to persons with cognitive disorders and their families for 25 years in Barcelona, Spain. Delivering care to this vulnerable population amidst the COVID-19 pandemic has represented a major challenge to our institution. OBJECTIVE: To share our experience in adapting our model of care to the new situation to ensure continuity of care. METHODS: We detail the sequence of events and the actions taken within Fundació ACE to swiftly adapt our face-to-face model of care to one based on telemedicine consultations. We characterize individuals under follow-up by the Memory Unit from 2017 to 2019 and compare the number of weekly visits in 2020 performed before and after the lockdown was imposed. RESULTS: The total number of individuals being actively followed by Fundació ACE Memory Unit grew from 6,928 in 2017 to 8,147 in 2019. Among those newly diagnosed in 2019, most patients had mild cognitive impairment or mild dementia (42% and 25%, respectively). Weekly visits dropped by 60% following the suspension of face-to-face activity. However, by April 24 we were able to perform 78% of the visits we averaged in the weeks before confinement began. DISCUSSION: We have shown that Fundació ACE model of care has been able to successfully adapt to a health and social critical situation as COVID-19 pandemic. Overall, we were able to guarantee the continuity of care while preserving the safety of patients, families, and professionals. We also seized the opportunity to improve our model of care.
Keywords: Aged; Aged, 80 and over; Betacoronavirus; Coronavirus Infections; COVID-19; Dementia; Female; Follow-Up Studies; Holistic Health; Humans; Male; Pandemics; Patient-Centered Care; Pneumonia, Viral; SARS-CoV-2; Spain; Telemedicine

Dementia in the COVID-19 Period. - Korczyn, Amos D (J Alzheimers Dis, 2020)
Keywords: Betacoronavirus; Coronavirus; Coronavirus Infections; COVID-19; Dementia; Humans; Nervous System Diseases; Pandemics; Pneumonia, Viral; SARS-CoV-2; Telemedicine

Environmental Nanoparticles, SARS-CoV-2 Brain Involvement, and Potential Acceleration of Alzheimer's and Parkinson's Diseases in Young Urbanites Exposed to Air Pollution. - Calderón-Garcidueñas, Lilian; Torres-Jardón, Ricardo; Franco-Lira, Maricela; Kulesza, Randy; González-Maciel, Angelica; Reynoso-Robles, Rafael; Brito-Aguilar, Rafael; García-Arreola, Berenice; Revueltas-Ficachi, Paula; Barrera-Velázquez, Juana Adriana; García-Alonso, Griselda; García-Rojas, Edgar; et al. (J Alzheimers Dis, 2020)
Alzheimer's and Parkinson's diseases (AD, PD) have a pediatric and young adult onset in Metropolitan Mexico City (MMC). The SARS-CoV-2 neurotropic RNA virus is triggering neurological complications and deep concern regarding acceleration of neuroinflammatory and neurodegenerative processes already in progress. This review, based on our MMC experience, will discuss two major issues: 1) why residents chronically exposed to air pollution are likely to be more susceptible to SARS-CoV-2 systemic and brain effects and 2) why young people with AD and PD already in progress will accelerate neurodegenerative processes. Secondary mental consequences of social distancing and isolation, fear, financial insecurity, violence, poor health support, and lack of understanding of the complex crisis are expected in MMC residents infected or free of SARS-CoV-2. MMC residents with pre-SARS-CoV-2 accumulation of misfolded proteins diagnostic of AD and PD and metal-rich, magnetic nanoparticles damaging key neural organelles are an ideal host for neurotropic SARS-CoV-2 RNA virus invading the body through the same portals damaged by nanoparticles: nasal olfactory epithelium, the gastrointestinal tract, and the alveolar-capillary portal. We urgently need MMC multicenter retrospective-prospective neurological and psychiatric population follow-up and intervention strategies in place in case of acceleration of neurodegenerative processes, increased risk of suicide, and mental disease worsening. Identification of vulnerable populations and continuous effort to lower air pollution ought to be critical steps.
Keywords: Adult; Air Pollution; Alzheimer Disease; Brain Diseases; Coronavirus Infections; COVID-19; Disease Progression; Environmental Pollutants; Humans; Middle Aged; Nanoparticles; Pandemics; Parkinson Disease; Pneumonia, Viral; Suicide; Urban Population

Potential Novel Role of COVID-19 in Alzheimer's Disease and Preventative Mitigation Strategies. - Naughton, Sean X; Raval, Urdhva; Pasinetti, Giulio M (J Alzheimers Dis, 2020)
There are a number of potential implications for the field of Alzheimer's disease (AD) stemming from the global spread of SARS-CoV-2. Neuroinflammation is known to be a prominent feature of neurodegeneration and plays a major role in AD pathology. Immune response and excessive inflammation in COVID-19 may also accelerate the progression of brain inflammatory neurodegeneration, and elderly individuals are more susceptible to severe outcomes after SARS-CoV-2 infection. Individuals with type 2 diabetes (T2D) are at an increased risk for AD as well as severe outcomes after SARS-CoV-2 infection. Genetic and socioeconomic factors influencing the rates of T2D, AD, and COVID-19 severity may create an exceptionally high-risk profile for certain demographics such as African Americans and Hispanic Americans. Type I interferon response plays an important role in both host response to viral infection, as well as AD pathology and may be a sensible therapeutic target in both AD and COVID-19.
Keywords: Aged; Alzheimer Disease; Betacoronavirus; Coronavirus Infections; COVID-19; Diabetes Mellitus, Type 2; Humans; Interferon Type I; Pandemics; Pneumonia, Viral; SARS-CoV-2; Synapses

Resilience of Alzheimer's Disease to COVID-19. - Li, Jingwen; Long, Xi; Huang, Heqing; Tang, Jine; Zhu, Chunli; Hu, Shaoping; Wu, Jing; Li, Jinghong; Lin, Zhicheng; Xiong, Nian (J Alzheimers Dis, 2020)
BACKGROUND: Facing the novel coronavirus disease 2019 (COVID-19), most vulnerable individuals are seniors, especially those with comorbidities. More attention needs to been paid to the COVID-19 patients with Alzheimer's disease (AD), which is the top age-related neurodegenerative disease. OBJECTIVE: Since it is unclear whether AD patients are prone to COVID-19 infection and progression to severe stages, we report for the first time a retrospective analysis of the clinical characteristics of AD patients with COVID-19 pneumonia. METHODS: We conducted a retrospective cohort study of the clinical data of 19 AD patients with COVID-19 pneumonia, compared with 23 non-AD COVID-19 patients admitted at the same time to our hospital. Demographic, clinical, laboratory, radiological, and treatment data were collected and analyzed. RESULTS: Between AD patients and non-AD patients with COVID-19 pneumonia, the pneumonia severity was not significantly different. AD patients had a higher clustering onset than non-AD patients. The median duration from symptom onset to hospitalization were shorter in AD patients than non-AD patients, indicating the former were sent to the hospital by their family or from nursing home earlier than the later. The median duration from hospitalization to discharge seemed shorter in AD patients than non-AD patients. Dementia patients seemed less likely to report fatigue. It is noticed that more AD patients might have pericardial effusion than the non-AD patients. CONCLUSION: AD patients with COVID-19 were in milder conditions with a better prognosis than non-AD patients. AD patients who had adequate access to healthcare showed resilience to COVID-19 with shorter hospital stays.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cluster Analysis; Cohort Studies; Coronavirus Infections; COVID-19; Disease Progression; Fatigue; Female; Humans; Length of Stay; Male; Middle Aged; Pandemics; Patient Discharge; Pleural Effusion; Pneumonia; Pneumonia, Viral; Prognosis; Resilience, Psychological

Telemedicine for Delivery of Care in Frontotemporal Lobar Degeneration During COVID-19 Pandemic: Results from Southern Italy. - Capozzo, Rosa; Zoccolella, Stefano; Frisullo, Maria Elisa; Barone, Roberta; Dell'Abate, Maria Teresa; Barulli, Maria Rosaria; Musio, Marco; Accogli, Miriam; Logroscino, Giancarlo (J Alzheimers Dis, 2020)
BACKGROUND: The COVID-19 pandemic is changing clinical practice in neurology, after the governments decided the introduction of social distancing and interruption of medical non-emergency services in many countries. Teleneurology is an effective tool for the remote evaluation of patients but its adoption for frontotemporal lobar dementia (FTD) is in a preliminary stage. OBJECTIVE: We evaluated multidisciplinary assessment of patients with FTD using telehealth during the COVID-19 pandemic. METHODS: All patients received a diagnosis of FTD during 2018-2019 according to international criteria. A structured questionnaire and Clinical Dementia Rating Scale (CDR)-FTD were used by the neurologist with patients and/or caregivers. Index symptoms of COVID-19 infection were searched. RESULTS: Twenty-eight clinical interviews were completed with caregivers and four with both patients/caregivers. Most patients and caregivers were satisfied with the neurological interview and expressed their willingness to continue to be included in remote evaluation programs (90%). Fifty percent of patients experienced significant worsening of clinical picture and quality of life since the start of social distancing. The CDR-FTD scale revealed a significant worsening of behavior (p = 0.01) and language functions (p = 0.009), compared to the last in-person evaluation at the center. One patient presented index symptoms of COVID-19 infection and was confirmed to be positive for COVID-19 with pharyngeal swab. CONCLUSION: The study was conducted in Italy, one of the countries hit particularly hard by the COVID-19 pandemic, with interruption of all non-emergency medical services. Our study indicates that telemedicine is a valid tool to triage patients with FTD to increase practice outreach and efficiency.
Keywords: Aged; Aged, 80 and over; Behavior; Coronavirus Infections; COVID-19; Delivery of Health Care; Disease Progression; Female; Frontotemporal Lobar Degeneration; Humans; Italy; Language; Male; Mental Status and Dementia Tests; Middle Aged; Pandemics; Pneumonia, Viral; Quality of Life; Quarantine; Surveys and Questionnaires; Telemedicine; Triage

Age-Related Changes in the Spatial Frequency Threshold of Male and Female 3xTg-AD Mice Using OptoMotry. - King, Jillian L; Wong, Aimée A; Brown, Richard E (J Alzheimers Dis, 2018)
Visual impairments and retinal abnormalities occur in patients with Alzheimer's disease (AD) and in mouse models of AD. It is important to know the visual ability of mouse models of AD to ensure that age-related cognitive deficits are not confounded by visual impairments. Using OptoMotry, the spatial frequency thresholds of male and female 3xTg-AD mice did not differ from their B6129SF2 wildtype controls between 1-18 months of age, but females had higher spatial frequency thresholds than males. However, the differences were quite small, and the visual ability of all mice was comparable to that of C57BL/6 mice.
Keywords: Aging; Alzheimer Disease; Animals; Disease Models, Animal; Female; Humans; Male; Maze Learning; Mice; Mice, Inbred C57BL; Mice, Transgenic; Sex Characteristics; tau Proteins; Vision, Ocular

Alterations in Acrolein Metabolism Contribute to Alzheimer's Disease. - Tsou, Han-Hsing; Hsu, Wen-Chin; Fuh, Jong-Ling; Chen, Shih-Pin; Liu, Tsung-Yun; Wang, Hsiang-Tsui (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a detrimental neurodegenerative disease, and early diagnosis appears to be the key to successful treatment. Acrolein, a byproduct of lipid peroxidation, has been shown to contribute to the pathological process of AD. This study recruited 118 elderly subjects consisting of 58 non-demented control subjects and 62 AD patients. We analyzed the acrolein-related metabolites in the plasma, cerebrospinal fluid (CSF), and urine of all subjects. We found that the levels of acrolein-conjugated protein (Acr-PC) in the plasma (p = 0.00012) and CSF (p = 0.00161) of AD patients were significantly higher than those of control subjects, whereas the levels of a urinary acrolein metabolite, 3-hydroxypropyl mercapturic acid (3-HPMA), were markedly decreased (p = 0.00882) in AD patients. These data suggest that deregulated acrolein metabolism may be correlated with neuronal damage in AD patients, which might provide further insights into the disease progression and early diagnosis of AD.
Keywords: Acetylcysteine; Acrolein; Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Case-Control Studies; Creatinine; Disease Progression; Early Diagnosis; Female; Humans; Male; Middle Aged

Alzheimer-Like Pattern of Hypometabolism Emerges with Elevated Amyloid-β Burden in Down Syndrome. - Lao, Patrick J; Handen, Ben L; Betthauser, Tobey J; Mihaila, Iulia; Hartley, Sigan L; Cohen, Annie D; Tudorascu, Dana L; Bulova, Peter D; Lopresti, Brian J; Tumuluru, Rameshwari V; Murali, Dhanabalan; Mathis, Chester A; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The Down syndrome (DS) population is genetically predisposed to amyloid-β protein precursor overproduction and Alzheimer's disease (AD). OBJECTIVE: The temporal ordering and spatial association between amyloid-β, glucose metabolism, and gray matter (GM) volume in the DS population can provide insight into those associations in the more common sporadic AD. METHODS: Twenty-four adults (13 male, 11 female; 39±7 years) with DS underwent [11C]PiB, [18F]FDG, and volumetric MRI scans. Voxel-wise associations between PiB SUVR, FDG SUVR, and GM volume were investigated, with and without individual adjustments for variables of interest. RESULTS: Positive associations of PiB and age were widespread throughout the neocortex and striatum. Negative associations of FDG and age (frontal, parietal, and temporal cortex) and of GM volume and age (frontal and insular cortex) were observed. PiB and FDG were negatively associated in parietal cortex, after adjustment for GM volume. CONCLUSIONS: In adults with DS, early amyloid-β accumulation in the striatum is divergent from sporadic AD; however, despite the early striatal amyloid-β, glucose hypometabolism was confined to the typical AD-associated regions, which occurs similarly in autosomal dominant AD. Importantly, the glucose hypometabolism was not explained solely by increased partial volume effect due to GM volume reductions.
Keywords: Adult; Alzheimer Disease; Amyloid beta-Peptides; Down Syndrome; Female; Fluorodeoxyglucose F18; Gray Matter; Humans; Linear Models; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Positron-Emission Tomography; Radiopharmaceuticals; United States

Alzheimer's Disease Progression: Factors Influencing Cognitive Decline. - Ferrari, Camilla; Lombardi, Gemma; Polito, Cristina; Lucidi, Giulia; Bagnoli, Silvia; Piaceri, Irene; Nacmias, Benedetta; Berti, Valentina; Rizzuto, Debora; Fratiglioni, Laura; Sorbi, Sandro (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) patients present high variability in the rate of cognitive decline. Despite the wide knowledge on factors influencing dementia risk, little is known on what accounts for AD progression. Previous studies on this topic have mainly analyzed each factor separately without taking into account the interaction between genetic and non-genetic factors. OBJECTIVE: The aim of the present study is to evaluate the role of demographic, clinical, therapeutic, and genetic factors and their interaction on cognitive decline among newly diagnosed AD patients. METHODS: We retrospectively selected 160 AD patients diagnosed at the Neurology Unit of Careggi University Hospital of Florence. We evaluated the occurrence of rapid cognitive changes defined as the worsening of more than four points at the Mini-Mental State Examination after 2-year follow up period. RESULTS: Among the 160 AD patients, 50% presented rapid disease progression. Extrapyramidal signs at disease onset were predictors of worse outcome (OR 2.2), especially among Apolipoprotein E (APOE) ɛ4 allele carriers, while the presence of family history for dementia decreased the risk of rapid progression by about 50%. Higher educated ɛ4-carriers showed a slower AD progression. We identified the chronic use of aspirin as potential secondary preventative strategy for the non ɛ4-carriers. CONCLUSION: At dementia onset, some clinical and demographic data can be predictors of future progression. The outcomes of the present study support the already hypothesized interaction between genetic and non-genetic factors during disease course and suggest genetic-based approaches.
Keywords: Aged; Aged, 80 and over; Alleles; Alzheimer Disease; Apolipoprotein E4; Aspirin; Cognitive Dysfunction; Disease Progression; Female; Heterozygote; Humans; Italy; Male; Middle Aged; Neuropsychological Tests; Retrospective Studies; Secondary Prevention

Alzheimer's Disease: Recent Concepts on the Relation of Mitochondrial Disturbances, Excitotoxicity, Neuroinflammation, and Kynurenines. - Zádori, Dénes; Veres, Gábor; Szalárdy, Levente; Klivenyi, Peter; Vecsei, Laszlo (J Alzheimers Dis, 2018)
The pathomechanism of Alzheimer's disease (AD) certainly involves mitochondrial disturbances, glutamate excitotoxicity, and neuroinflammation. The three main aspects of mitochondrial dysfunction in AD, i.e., the defects in dynamics, altered bioenergetics, and the deficient transport, act synergistically. In addition, glutamatergic neurotransmission is affected in several ways. The balance between synaptic and extrasynaptic glutamatergic transmission is shifted toward the extrasynaptic site contributing to glutamate excitotoxicity, a phenomenon augmented by increased glutamate release and decreased glutamate uptake. Neuroinflammation in AD is predominantly linked to central players of the innate immune system, with central nervous system (CNS)-resident microglia, astroglia, and perivascular macrophages having been implicated at the cellular level. Several abnormalities have been described regarding the activation of certain steps of the kynurenine (KYN) pathway of tryptophan metabolism in AD. First of all, the activation of indolamine 2,3-dioxygenase, the first and rate-limiting step of the pathway, is well-demonstrated. 3-Hydroxy-L-KYN and its metabolite, 3-hydroxy-anthranilic acid have pro-oxidant, antioxidant, and potent immunomodulatory features, giving relevance to their alterations in AD. Another metabolite, quinolinic acid, has been demonstrated to be neurotoxic, promoting glutamate excitotoxicity, reactive oxygen species production, lipid peroxidation, and microglial neuroinflammation, and its abundant presence in AD pathologies has been demonstrated. Finally, the neuroprotective metabolite, kynurenic acid, has been associated with antagonistic effects at glutamate receptors, free radical scavenging, and immunomodulation, giving rise to potential therapeutic implications. This review presents the multiple connections of KYN pathway-related alterations to three main domains of AD pathomechanism, such as mitochondrial dysfunction, excitotoxicity, and neuroinflammation, implicating possible therapeutic options.
Keywords: Alzheimer Disease; Animals; Central Nervous System; Disease Models, Animal; Energy Metabolism; Glutamic Acid; Humans; Immunity, Innate; Inflammation; Kynurenine; Mitochondria; Quinolinic Acid; Reactive Oxygen Species; Receptors, Glutamate; Signal Transduction

An Aspartyl Cathepsin Targeted PET Agent: Application in an Alzheimer's Disease Mouse Model. - Snir, Jonatan A; Suchy, Mojmir; Bindseil, Geron A; Kovacs, Michael; Chronik, Blaine A; Hudson, Robert H E; Pasternak, Stephen H; Bartha, Robert (J Alzheimers Dis, 2018)
BACKGROUND: Early detection of Alzheimer's disease (AD) pathology is a serious challenge for both diagnosis and clinical trials. The aspartyl protease, Cathepsin D (CatD), is overexpressed in AD and could be a biomarker of disease. We have previously designed a unique contrast agent (CA) for dual-optical and magnetic resonance imaging of the activity of the CatD class of enzymes. OBJECTIVE: To compare the uptake and retention of a novel, more sensitive, and clinically-translatable 68Ga PET tracer targeting CatD activity in 5XFAD mice and non-Tg littermates. METHODS: The targeted CA consisted of an HIV-1 Tat cell penetrating peptide (CPP) conjugated to a specialized cleavage sequence targeting aspartyl cathepsins and a DOTA conjugate chelating 68Ga. PET images were acquired using a Siemens Inveon preclinical microPET in female Tg AD mice and non-Tg age matched female littermates (n = 5-8) following intravenous CA administration at 2, 6, and 9 months of age. Additionally, 18F fluorodeoxyglucose (FDG) PET imaging was performed at 10 months to measure glucose uptake. RESULTS: The Tg mice showed significantly higher relative uptake rate of the targeting CA in the forebrain relative to hindbrain at all ages compared to controls, consistent with histology. In contrast, no differences were seen in CA uptake in other organs. Additionally, the Tg mice did not show any differences in relative uptake of FDG at 10 months of age in the forebrain relative to the hindbrain compared to age matched non-Tg controls. CONCLUSIONS: Elevated aspartryl cathepsin activity was detected in vivo in the 5XFAD mouse model of AD using a novel targeted PET contrast agent.
Keywords: Alzheimer Disease; Animals; Brain; Cathepsin D; Contrast Media; Disease Models, Animal; Female; Fluorodeoxyglucose F18; Glucose; Mice; Mice, Transgenic; Positron-Emission Tomography

Assessment of the Genetic Architecture of Alzheimer's Disease Risk in Rate of Memory Decline. - Del-Aguila, Jorge L; Fernández, Maria Victoria; Schindler, Suzanne; Ibanez, Laura; Deming, Yuetiva; Ma, Shengmei; Saef, Ben; Black, Kathleen; Budde, John; Norton, Joanne; Chasse, Rachel; Harari, Oscar; et al. (J Alzheimers Dis, 2018)
Many genetic studies for Alzheimer's disease (AD) have been focused on the identification of common genetic variants associated with AD risk and not on other aspects of the disease, such as age at onset or rate of dementia progression. There are multiple approaches to untangling the genetic architecture of these phenotypes. We hypothesized that the genetic architecture of rate of progression is different than the risk for developing AD dementia. To test this hypothesis, we used longitudinal clinical data from ADNI and the Knight-ADRC at Washington University, and we calculated PRS (polygenic risk score) based on the IGAP study to compare the genetic architecture of AD risk and dementia progression. Dementia progression was measured by the change of Clinical Dementia Rating Sum of Boxes (CDR)-SB per year. Out of the 21 loci for AD risk, no association with the rate of dementia progression was found. The PRS rate was significantly associated with the rate of dementia progression (β= 0.146, p = 0.03). In the case of rare variants, TREM2 (β= 0.309, p = 0.02) was also associated with the rate of dementia progression. TREM2 variant carriers showed a 23% faster rate of dementia compared with non-variant carriers. In conclusion, our results indicate that the recently identified common and rare variants for AD susceptibility have a limited impact on the rate of dementia progression in AD patients.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Dementia; Disease Progression; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Heterozygote; Humans; Longitudinal Studies; Male; Membrane Glycoproteins; Memory Disorders; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Immunologic; Risk Assessment

Association of the New Variant Tyr424Asp at TBK1 Gene with Amyotrophic Lateral Sclerosis and Cognitive Decline. - Piaceri, Irene; Bessi, Valentina; Matà, Sabrina; Polito, Cristina; Tedde, Andrea; Berti, Valentina; Bagnoli, Silvia; Braccia, Arianna; Del Mastio, Monica; Pignone, Alberto Moggi; Pupi, Alberto; Sorbi, Sandro; et al. (J Alzheimers Dis, 2018)
A new risk gene associated with amyotrophic lateral sclerosis (ALS) has recently been identified: the Tank-binding kinase 1 (TBK1) gene. Up to now, 90 TBK1 variants have been described in ALS patients with or without frontotemporal dementia (FTD), thus making TBK1 the third or fourth most frequent genetic cause of ALS and FTD. A point mutation analysis in a cohort of 69 Italian ALS patients was performed in order to analyze the frequency of TBK1 mutations and the correlation with clinical phenotypes. The analysis identified the novel variant p.Tyr424Asp in a patient with a rapid progression of the disease. Our data supports the implication of TBK1 in ALS pathogenesis in Italy.
Keywords: Aged; Amyotrophic Lateral Sclerosis; Aspartic Acid; C9orf72 Protein; Cognitive Dysfunction; DNA Mutational Analysis; Female; Fluorodeoxyglucose F18; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Italy; Male; Mental Status and Dementia Tests; Middle Aged; Mutation; Neuropsychological Tests; Positron-Emission Tomography; Protein-Serine-Threonine Kinases; Tyrosine

Associations of Dietary Protein and Fiber Intake with Brain and Blood Amyloid-β. - Fernando, W M A D Binosha; Rainey-Smith, Stephanie R; Gardener, Samantha L; Villemagne, Victor L; Burnham, Samantha C; Macaulay, S Lance; Brown, Belinda M; Gupta, Veer Bala; Sohrabi, Hamid R; Weinborn, Michael; Taddei, Kevin; Laws, Simon M; et al. (J Alzheimers Dis, 2018)
Accumulating evidence suggests a diet high in protein and fiber may confer some protection against Alzheimer's disease (AD). However, no human studies to-date have assessed the relationship between protein and fiber intake, and plasma and brain amyloid-β (Aβ). Consequently, this cross-sectional study, investigated the association of self-reported dietary intakes of protein and fiber, with plasma and brain Aβ burden (n = 541, and n = 162 respectively), in a well-characterized cohort of cognitively normal older adults, drawn from the larger Australian Imaging, Biomarkers and Lifestyle (AIBL) study of aging. We observed 12.59 and 8.43 higher odds of 'high' brain Aβ burden (PiB PET SUVR≥1.5) if protein intake fell in the lowest and middle tertile, respectively, compared to the highest tertile (p = 0.008; p = 0.013). Thus, in this cohort, the more protein consumed, the less likelihood of 'high' Aβ burden in the brain. No other significant associations were observed. The results of this study highlight the potentially protective impact of high dietary protein intake on brain Aβ burden in older adults, before objective memory decline is apparent. While longitudinal validation is required, these findings may assist in the development of dietary approaches aimed at preventing or delaying AD onset.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Australia; Biomarkers; Brain; Cognition; Cohort Studies; Cross-Sectional Studies; Dietary Fiber; Dietary Proteins; Female; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography

Cardiorespiratory Fitness and White Matter Neuronal Fiber Integrity in Mild Cognitive Impairment. - Ding, Kan; Tarumi, Takashi; Zhu, David C; Tseng, Benjamin Y; Thomas, Binu P; Turner, Marcel; Repshas, Justin; Kerwin, Diana R; Womack, Kyle B; Lu, Hanzhang; Cullum, C Munro; Zhang, Rong (J Alzheimers Dis, 2018)
BACKGROUND: Mounting evidence showed the self-reported levels of physical activity are positively associated with white matter (WM) integrity and cognitive performance in normal adults and patients with mild cognitive impairment (MCI). However, the objective measure of cardiorespiratory fitness (CRF) was not used in these studies. OBJECTIVE: To determine the associations of CRF measured by maximal oxygen uptake (VO2max) with WM fiber integrity and neurocognitive performance in older adults with MCI. METHODS: Eighty-one participants (age = 65±7 years, 43 women), including 26 cognitively normal older adults and 55 amnestic MCI patients, underwent VO2max test to measure CRF, diffusion tensor imaging (DTI) to assess WM fiber integrity, and neurocognitive assessment focused on memory and executive function. DTI data were analyzed by the tract-based spatial statistics and region-of-interest approach. RESULTS: Cognitively normal older adults and MCI patients were not different in global WM fiber integrity and VO2max. VO2max was associated positively with DTI metrics of fractional anisotropy in ∼54% WM fiber tracts, and negatively with mean and radial diffusivities in ∼46% and ∼56% of the WM fiber tracts. The associations of VO2max with DTI metrics remained statistically significant after adjustment of age, sex, body mass index, WM lesion burden, and MCI status. The DTI metrics obtained from the area that correlated to VO2max were associated with executive function performance in MCI patients. CONCLUSIONS: Higher levels of CRF are associated with better WM fiber integrity, which in turn is correlated with better executive function performance in MCI patients.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Anisotropy; Cardiorespiratory Fitness; Case-Control Studies; Cognition; Cognitive Dysfunction; Diffusion Tensor Imaging; Executive Function; Female; Humans; Linear Models; Male; Memory; Middle Aged; Nerve Fibers, Myelinated; Neuropsychological Tests; Texas; White Matter

Cerebrospinal Fluid C-C Motif Chemokine Ligand 2 Correlates with Brain Atrophy and Cognitive Impairment in Alzheimer's Disease. - Kimura, Akio; Yoshikura, Nobuaki; Hayashi, Yuichi; Inuzuka, Takashi (J Alzheimers Dis, 2018)
BACKGROUND: Chronic neuroinflammation has been implicated in Alzheimer's disease (AD) pathology. OBJECTIVE: To investigate the association between cytokine and anti-amyloid-β (Aβ) autoantibody levels and the degree of brain atrophy and cognitive impairment in AD patients. METHODS: Cerebrospinal fluid (CSF) levels of C-C motif chemokine ligand 2 (CCL2), C-X-C motif chemokine ligand 8, C-X-C motif chemokine ligand 10, interleukin 6, and anti-Aβ autoantibody were evaluated in 69 AD patients. Serum levels of CCL2 and anti-Aβ autoantibody were also examined. The degree of brain atrophy was assessed using the voxel-based specific regional analysis system for AD, which targets the volumes of interest (VOI) in medial temporal structures. Cognitive function was evaluated by neuropsychological testing, including the Mini-Mental State Examination (MMSE) and Frontal Assessment Battery (FAB). RESULTS: CSF CCL2 levels correlated significantly with the severity (p = 0.023) and the extent (p = 0.022) of VOI atrophy, and with the extent of gray matter atrophy (p = 0.039) in AD patients. CSF anti-Aβ autoantibody levels were inversely correlated with the severity of VOI atrophy (p = 0.020), the extent of VOI atrophy (p = 0.015), and the ratio of VOI/GM atrophy (r = -0.358, p = 0.004). CSF CCL2 levels were also inversely correlated with MMSE (p = 0.0497) and FAB scores (p = 0.016). CONCLUSIONS: CSF CCL2 levels are associated with the degree of medial temporal lobe and gray matter atrophy, and cognitive decline in AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Atrophy; Biomarkers; Chemokine CCL2; Cognitive Dysfunction; Disease Progression; Female; Gray Matter; Humans; Linear Models; Magnetic Resonance Imaging; Male; Neuropsychological Tests; tau Proteins; Temporal Lobe

A Clinically-Translatable Machine Learning Algorithm for the Prediction of Alzheimer's Disease Conversion in Individuals with Mild and Premild Cognitive Impairment. - Grassi, Massimiliano; Perna, Giampaolo; Caldirola, Daniela; Schruers, Koen; Duara, Ranjan; Loewenstein, David A (J Alzheimers Dis, 2018)
BACKGROUND: Available therapies for Alzheimer's disease (AD) can only alleviate and delay the advance of symptoms, with the greatest impact eventually achieved when provided at an early stage. Thus, early identification of which subjects at high risk, e.g., with MCI, will later develop AD is of key importance. Currently available machine learning algorithms achieve only limited predictive accuracy or they are based on expensive and hard-to-collect information. OBJECTIVE: The current study aims to develop an algorithm for a 3-year prediction of conversion to AD in MCI and PreMCI subjects based only on non-invasively and effectively collectable predictors. METHODS: A dataset of 123 MCI/PreMCI subjects was used to train different machine learning techniques. Baseline information regarding sociodemographic characteristics, clinical and neuropsychological test scores, cardiovascular risk indexes, and a visual rating scale for brain atrophy was used to extract 36 predictors. Leave-pair-out-cross-validation was employed as validation strategy and a recursive feature elimination procedure was applied to identify a relevant subset of predictors. RESULTS: 16 predictors were selected from all domains excluding sociodemographic information. The best model resulted a support vector machine with radial-basis function kernel (whole sample: AUC = 0.962, best balanced accuracy = 0.913; MCI sub-group alone: AUC = 0.914, best balanced accuracy = 0.874). CONCLUSIONS: Our algorithm shows very high cross-validated performances that outperform the vast majority of the currently available algorithms, and all those which use only non-invasive and effectively assessable predictors. Further testing and optimization in independent samples will warrant its application in both clinical practice and clinical trials.
Keywords: Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Area Under Curve; Atrophy; Brain; Cognitive Dysfunction; Disease Progression; Female; Humans; Logistic Models; Machine Learning; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Predictive Value of Tests; Prognosis; Regression Analysis; Sensitivity and Specificity; Support Vector Machine

Clinic-Based Validation of Cerebrospinal Fluid Biomarkers with Florbetapir PET for Diagnosis of Dementia. - Álvarez, Ignacio; Aguilar, Miquel; González, Jose Manuel; Ysamat, Montse; Lorenzo-Bosquet, Carles; Alonso, Alvaro; Tartari, Juan Pablo; Romero, Silvia; Diez-Fairen, Monica; Carcel, Maria; Pujalte, Francisco; Pastor, Pau (J Alzheimers Dis, 2018)
BACKGROUND: Cerebrospinal fluid (CSF) biomarker studies have shown variable accuracy for diagnosis of Alzheimer's disease (AD); therefore, internal validation is recommended. OBJECTIVE: To investigate the correlation between CSF biomarkers and cerebral 18-Florbetapir positron emission tomography (Amyloid-PET) and calculate their sensitivity and specificity to obtain the optimal clinical cut-off points to diagnose the etiology of cognitive impairment. METHODS: We performed Amyloid-PET scans and CSF biomarker levels analyses in 68 subjects (50 with mild cognitive impairment, 11 with AD dementia, and 7 with non-AD dementia). Visual examination of Amyloid-PET scans was performed. CSF analyses were performed using standard sandwich ELISA. RESULTS: Amyloid-PET was positive in 36 subjects, negative in 26, and inconclusive in 6. Optimal clinical cut-off points for CSF markers were the following: amyloid-β 1-42 (Aβ42) = 629 pg/ml, total tau (t-tau) = 532 pg/ml, phosphorylated tau (p-tau) = 88 pg/ml, and t-tau/Aβ42 ratio = 0.58. T-tau/Aβ42 ratio showed the best sensitivity and specificity (92 and 84%, respectively). T-tau and p-tau CSF levels (r2 = 0.867) followed by the t-tau and t-tau/Aβ42 CSF ratio (r2 = 0.666) showed the strongest inter-marker correlation. Interestingly, subjects with inconclusive Amyloid-PET showed intermediate values for all CSF markers between negative and positive Amyloid-PET groups. CONCLUSIONS: CSF t-tau/Aβ42 ratio appears to be the most accurate AD CSF marker. The presence of intermediate values for CSF markers among the subjects with inconclusive Amyloid-PET suggests the presence of other dementias associated with AD pathology or intermediate phenotypes.
Keywords: Aged; Amyloid beta-Peptides; Analysis of Variance; Aniline Compounds; Apolipoproteins E; Biomarkers; Cognition Disorders; Dementia; Ethylene Glycols; Female; Humans; Male; Middle Aged; Peptide Fragments; Positron-Emission Tomography; tau Proteins

Cognitive Decline in Preclinical Alzheimer's Disease: Amyloid-Beta versus Tauopathy. - Huber, Colin M; Yee, Connor; May, Taylor; Dhanala, Apoorva; Mitchell, Cassie S (J Alzheimers Dis, 2018)
We perform a large-scale meta-analysis of 51 peer-reviewed 3xTg-AD mouse publications to compare Alzheimer's disease (AD) quantitative clinical outcome measures, including amyloid-β (Aβ), total tau, and phosphorylated tau (pTau), with cognitive performance in Morris water maze (MWM) and Novel Object Recognition (NOR). "High" levels of Aβ (Aβ40, Aβ42) showed significant but weak trends with cognitive decline (MWM: slope = 0.336, R2 = 0.149, n = 259, p < 0.001; NOR: slope = 0.156, R2 = 0.064, n = 116, p < 0.05); only soluble Aβ or directly measured Aβ meaningfully contribute. Tau expression in 3xTg-AD mice was within 10-20% of wild type and not associated with cognitive decline. In contrast, increased pTau is directly and significantly correlated with cognitive decline in MWM (slope = 0.408, R2 = 0.275, n = 371, p < < 0.01) and NOR (slope = 0.319, R2 = 0.176, n = 113, p < 0.05). While a variety of pTau epitopes (AT8, AT270, AT180, PHF-1) were examined, AT8 correlated most strongly with cognition (slope = 0.586, R2 = 0.521, n = 185, p < < 0.001). Multiple linear regression confirmed pTau is a stronger predictor of MWM performance than Aβ. Despite pTau's lower physical concentration than Aβ, pTau levels more directly and quantitatively correlate with 3xTg-AD cognitive decline. pTau's contribution to neurofibrillary tangles well after Aβ levels plateau makes pTau a viable treatment target even in late-stage clinical AD. Principal component analysis, which included hyperphosphorylation induced by kinases (pGSK3β, GSK3β, CDK5), identified phosphorylated ser9 GSK3β as the primary contributor to MWM variance. In summary, meta-analysis of cognitive decline in preclinical AD finds tauopathy more impactful than Aβ. Nonetheless, complex AD interactions dictate successful therapeutics harness synergy between Aβ and pTau, possibly through the GSK3 pathway.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Cognitive Dysfunction; Disease Models, Animal; Maze Learning; Mice; Reaction Time; Recognition (Psychology); tau Proteins

Combined Socio-Behavioral Evaluation Improves the Differential Diagnosis Between the Behavioral Variant of Frontotemporal Dementia and Alzheimer's Disease: In Search of Neuropsychological Markers. - Dodich, Alessandra; Cerami, Chiara; Cappa, Stefano F; Marcone, Alessandra; Golzi, Valeria; Zamboni, Michele; Giusti, Maria Cristina; Iannaccone, Sandro (J Alzheimers Dis, 2018)
BACKGROUND: Current diagnostic criteria for behavioral variant of frontotemporal dementia (bvFTD) and typical Alzheimer's disease (AD) include a differential pattern of neuropsychological impairments (episodic memory deficit in typical AD and dysexecutive syndrome in bvFTD). There is, however, large evidence of a frequent overlap in neuropsychological features, making the differential diagnosis extremely difficult. OBJECTIVES: In this retrospective study, we evaluated the diagnostic value of different cognitive and neurobehavioral markers in bvFTD and AD patient groups. METHODS: We included 95 dementia patients with a clinical and biomarker evidence of bvFTD (n = 48) or typical AD (n = 47) pathology. A clinical 2-year follow-up confirmed clinical classification. Performances at basic cognitive tasks (memory, executive functions, visuo-spatial, language) as well as social cognition skills and neurobehavioral profiles have been recorded. A stepwise logistic regression model compared the neuropsychological profiles between groups and assessed the accuracy of cognitive and neurobehavioral markers in discriminating bvFTD from AD. RESULTS: Statistical comparison between patient groups proved social cognition and episodic memory impairments as main cognitive signatures of bvFTD and AD neuropsychological profiles, respectively. Only half of bvFTD patients showed attentive/executive deficits, questioning their role as cognitive marker of bvFTD. Notably, the large majority of bvFTD sample (i.e., 70%) poorly performed at delayed recall tasks. Logistic regression analysis identified social cognition performances, Frontal Behavioral Inventory and Mini-Mental State Examination scores as the best combination in distinguishing bvFTD from AD. CONCLUSION: Social cognition tasks and socio-behavioral questionnaires are recommended in clinical settings to improve the accuracy of early diagnosis of bvFTD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Cognition; Diagnosis, Differential; Female; Frontotemporal Dementia; Humans; Logistic Models; Male; Memory, Episodic; Mental Recall; Middle Aged; Neuropsychological Tests; Retrospective Studies; Social Skills

Deep Brain Stimulation of Frontal Lobe Networks to Treat Alzheimer's Disease. - Scharre, Douglas W; Weichart, Emily; Nielson, Dylan; Zhang, Jun; Agrawal, Punit; Sederberg, Per B; Knopp, Michael V; Rezai, Ali R (J Alzheimers Dis, 2018)
The study objective was to evaluate the safety and efficacy of deep brain stimulation (DBS) at the ventral capsule/ventral striatum (VC/VS) region to specifically modulate frontal lobe behavioral and cognitive networks as a novel treatment approach for Alzheimer's disease (AD) patients. This is a non-randomized phase I prospective open label interventional trial of three subjects with matched comparison groups. AD participants given DBS for at least 18 months at the VC/VS target were compared on the Clinical Dementia Rating-Sum of Boxes (CDR-SB), our primary outcome clinical measure, to matched groups without DBS from the AD Neuroimaging Initiative (ADNI) cohort. Serial 2-Deoxy-2-[18F]fluoro-D-glucose (FDG) positron emission tomography (PET) images of AD participants were also compared longitudinally over time. Three AD DBS participants were matched to subjects from the ADNI cohort. All participants tolerated DBS well without significant adverse events. All three AD DBS participants had less performance decline and two of them meaningfully less decline over time on our primary outcome measure, CDR-SB, relative to matched comparison groups from the ADNI using score trajectory slopes. Minimal changes or increased metabolism on FDG-PET were seen in frontal cortical regions after chronic DBS at the VC/VS target. The first use of DBS in AD at a frontal lobe behavior regulation target (VC/VS) was well-tolerated and revealed less performance decline in CDR-SB. Frontal network modulation to improve executive and behavioral deficits should be furthered studied in AD.
Keywords: Aged; Alzheimer Disease; Deep Brain Stimulation; Female; Frontal Lobe; Humans; Male; Middle Aged; Ohio; Pilot Projects; Positron-Emission Tomography; Prospective Studies

Delirium Severity Post-Surgery and its Relationship with Long-Term Cognitive Decline in a Cohort of Patients without Dementia. - Vasunilashorn, Sarinnapha M; Fong, Tamara G; Albuquerque, Asha; Marcantonio, Edward R; Schmitt, Eva M; Tommet, Douglas; Gou, Yun; Travison, Thomas G; Jones, Richard N; Inouye, Sharon K (J Alzheimers Dis, 2018)
BACKGROUND: Delirium has been associated with more rapid cognitive decline. However, it is unknown whether increased delirium severity is associated with a higher rate of long-term cognitive decline. OBJECTIVE: To evaluate delirium severity and the presence and rate of cognitive decline over 36 months following surgery. METHODS: We examined patients from the Successful Aging after Elective Surgery Study, who were age ≥70 years undergoing major elective surgery (N = 560). Delirium severity was determined by the peak Confusion Assessment Method-Severity (CAM-S) score for each patient's hospitalization and grouped based on the sample distribution: scores of 0-2, 3-7, and 8-19. A neuropsychological composite, General Cognitive Performance (GCP), and proxy-reported Informant Questionnaire for Cognitive Decline (IQCODE) were used to examine cognitive outcomes following surgery at 0, 1, and 2 months, and then every 6 months for up to 3 years. RESULTS: No significant cognitive decline was observed for patients with peak CAM-S scores 0-2 (-0.17 GCP units/year, 95% confidence interval [CI] -0.35, 0.01). GCP scores decreased significantly in the group with peak CAM-S scores 3-7 (-0.30 GCP units/year, 95% CI -0.51, -0.09), and decreased almost three times faster in the highest delirium severity group (peak CAM-S scores 8-19; -0.82 GCP units/year, 95% CI -1.28, -0.37). A similar association was found for delirium severity and the proportion of patients who developed IQCODE impairment over time. CONCLUSION: Patients with the highest delirium severity experienced the greatest rate of cognitive decline, which exceeds the rate previously observed for patients with dementia, on serial neuropsychological testing administered over 3 years, with a dose-response relationship between delirium severity and long-term cognitive decline.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Cohort Studies; Delirium; Elective Surgical Procedures; Female; Humans; Male; Neuropsychological Tests; Postoperative Complications; Severity of Illness Index

Detection of Dementia Cases in Two Swedish Health Registers: A Validation Study. - Rizzuto, Debora; Feldman, Adina L; Karlsson, Ida K; Dahl Aslan, Anna K; Gatz, Margaret; Pedersen, Nancy L (J Alzheimers Dis, 2018)
BACKGROUND: Population-based health registers are potential assets in epidemiological research; however, the quality of case ascertainment is crucial. OBJECTIVE: To compare the case ascertainment of dementia, from the National Patient Register (NPR) and the Cause of Death Register (CDR) with dementia diagnoses from six Swedish population based studies. METHODS: Sensitivity, specificity, and positive predictive value (PPV) of dementia identification in NPR and CDR were estimated by individual record linkage with six Swedish population based studies (n = 19,035). Time to detection in NPR was estimated using data on dementia incidence from longitudinal studies with more than two decades of follow-up. RESULTS: Barely half of the dementia cases were ever detected by NPR or CDR. Using data from longitudinal studies we estimated that a record with a dementia diagnosis appears in the NPR on average 5.5 years after first diagnosis. Although the ability of the registers to detect dementia cases was moderate, the ability to detect non-dementia cases was almost perfect (99%). When registers indicate that there is a dementia diagnosis, there are very few instances in which the clinicians determined the person was not demented. Indeed, PPVs were close to 90%. However, misclassification between dementia subtype diagnoses is quite common, especially in NPR. CONCLUSIONS: Although the overall sensitivity is low, the specificity and the positive predictive value are very high. This suggests that hospital and death registers can be used to identify dementia cases in the community, but at the cost of missing a large proportion of the cases.
Keywords: Aged; Aged, 80 and over; Cause of Death; Dementia; Female; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Registries; Sensitivity and Specificity; Sweden; Twin Studies as Topic

The Diagnostic and Prognostic Value of a Dual-Tasking Paradigm in a Memory Clinic. - Nielsen, Malene Schjnning; Simonsen, Anja Hviid; Siersma, Volkert; Hasselbalch, Steen Gregers; Hoegh, Peter (J Alzheimers Dis, 2018)
BACKGROUND: Daily living requires the ability to perform dual-tasking. As cognitive skills decrease in dementia, performing a cognitive and motor task simultaneously become increasingly challenging and subtle gait abnormalities may even be present in pre-dementia stages. Therefore, a dual-tasking paradigm, such as the Timed Up and Go-Dual Task (TUG-DT), may be useful in the diagnostic assessment of mild cognitive impairment (MCI). OBJECTIVE: To investigate the diagnostic and prognostic ability of a dual-tasking paradigm in patients with MCI or mild Alzheimer's disease (AD) and to evaluate the association between the dual-tasking paradigm and cerebrospinal fluid (CSF) AD biomarkers. METHODS: The study is a prospective cohort study conducted in a clinical setting in two memory clinics. Eighty-six patients were included (28 MCI, 17 AD, 41 healthy controls (HC)). The ability to perform dual-tasking was evaluated by the TUG-DT. Patients underwent a standardized diagnostic assessment and were evaluated to determine progression yearly. RESULTS: ROC curve analysis illustrated a high discriminative ability of the dual-tasking paradigm in separating MCI patients from HC (AUC: 0.78, AUC: 0.82) and a moderate discriminative ability in separating MCI from AD (AUC: 0.73, AUC: 0.55). Performance discriminated clearly between all groups (p < 0.01). Logistic regression analyses revealed a low prognostic value of the dual-tasking paradigm for progression and rate of cognitive decline. A moderately strong correlation between the dual-tasking paradigm and CSF AD biomarkers was observed. CONCLUSION: In our study, we found that patients with MCI and mild AD have increasing difficulties in dual-tasking compared to healthy elderly. Hence, the dual-tasking paradigm may be a potential complement in the diagnostic assessment in a typical clinical setting.
Keywords: Aged; Alzheimer Disease; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Disease Progression; Female; Humans; Logistic Models; Male; Memory; Middle Aged; Neuropsychological Tests; Prognosis; Prospective Studies; ROC Curve

Differences in Synaptic Dysfunction Between rTg4510 and APP/PS1 Mouse Models of Alzheimer's Disease. - Gelman, Simon; Palma, Jonathan; Tombaugh, Geoffrey; Ghavami, Afshin (J Alzheimers Dis, 2018)
Genetically modified mice have provided insights into the progression and pathology of Alzheimer's disease (AD). Here, we have examined two mouse models of AD: the rTg4510 mouse, which overexpresses mutant human Tau gene, and the APP/PS1 mouse, which overexpresses mutant human genes for amyloid precursor protein and presenilin 1. Both models exhibit deficits in hippocampal function, but comparative analyses of these deficits are sparse. We used extracellular field potential recordings in hippocampal slices to study basal synaptic transmission (BST), paired-pulse facilitation (PPF), and long-term potentiation (LTP) at the Schaffer collateral-CA1 pyramidal cell synapses in both models. We found that 6-7, but not 2-3-month-old rTg4510 mice exhibited reduced pre-synaptic activation (fiber volley (FV) amplitude, ∼50%) and field excitatory post-synaptic potential (fEPSP) slope (∼40%) compared to wild-type controls. In contrast to previous reports, BST, when controlled for FV amplitude, was not altered in rTg4510. APP/PS1 mice (2-3 mo and 8-10 mo) had unchanged FV amplitude compared to wild-type controls, while fEPSP slope was reduced by ∼34% in older mice, indicating a deficit in BST. PPF was unchanged in 8-10-month-old APP/PS1 mice, but was reduced in 6-7-month-old rTg4510 mice. LTP was reduced only in older rTg4510 and APP/PS1 mice. Our data suggest that BST deficits appear earlier in APP/PS1 than in rTg4510, which exhibited no BST deficits at the ages tested. However, FV and synaptic plasticity deficits developed earlier in rTg4510. These findings highlight fundamental differences in the progression of synaptic pathology in two genetically distinct models of AD.
Keywords: Age Factors; Alzheimer Disease; Amyloid beta-Protein Precursor; Analysis of Variance; Animals; Biophysics; Disease Models, Animal; Electric Stimulation; Excitatory Postsynaptic Potentials; Hippocampus; Humans; Mice; Mice, Transgenic; Mutation; Presenilin-1; Synapses; Synaptic Transmission; tau Proteins

Does Fatty Acid Composition in Subcutaneous Adipose Tissue Differ between Patients with Alzheimer's Disease and Cohabiting Proxies? - Faxen-Irving, Gerd; Falahati, Farshad; Basun, Hans; Eriksdotter, Maria; Vedin, Inger; Wahlund, Lars-Olof; Schultzberg, Marianne; Hjorth, Erik; Palmblad, Jan; Cederholm, Tommy; Freund-Levi, Yvonne (J Alzheimers Dis, 2018)
Low tissue levels of the major marine ω3 fatty acids (FAs) DHA and EPA are found in Alzheimer's disease (AD). We investigated if healthy proxies to AD patients have higher levels of these ω3 FAs. We observed lower levels of EPA and DHA in subcutaneous adipose tissue biopsies from 64 AD patients compared with 16 cognitively healthy proxies. No significant difference was observed when pairwise comparisons were made between a subset of 16 AD patients and their co-habiting proxies. Larger studies are needed to replicate these findings and to determine if they could depend on FA intake or differences in metabolism.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Dietary Supplements; Fatty Acids, Omega-3; Female; Humans; Male; Regression Analysis; Subcutaneous Fat

Does the Genetic Feature of the Chinese Tree Shrew (Tupaia belangeri chinensis) Support Its Potential as a Viable Model for Alzheimer's Disease Research? - Fan, Yu; Luo, Rongcan; Su, Ling-Yan; Xiang, Qun; Yu, Dandan; Xu, Ling; Chen, Jia-Qi; Bi, Rui; Wu, Dong-Dong; Zheng, Ping; Yao, Yong-Gang (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a neurodegenerative disease with increasing incidence across the world and no cure at the present time. An ideal animal model would facilitate the understanding of the pathogenesis of AD and discovery of potential therapeutic targets. The Chinese tree shrew (Tupaia belangeri chinensis) has a closer genetic affinity to primates relative to rodents, and can attain ages of 8 years or older, which represents another advantage for the study of neurodegenerative diseases such as AD compared to primates. Here, we analyzed 131 AD-related genes in the Chinese tree shrew brain tissues based on protein sequence identity, positive selection, mRNA, and protein expression by comparing with those of human, rhesus monkey, and mouse. In particular, we focused on the Aβ and neurofibrillary tangles formation pathways, which are crucial to AD pathogenesis. The Chinese tree shrew had a generally higher sequence identity with human than that of mouse versus human for the AD pathway genes. There was no apparent selection on the tree shrew lineage for the AD-related genes. Moreover, expression pattern of the Aβ and neurofibrillary tangle formation pathway genes in tree shrew brain tissues resembled that of human brain tissues, with a similar aging-dependent effect. Our results provided an essential genetic basis for future AD research using the tree shrew as a viable model.
Keywords: Alzheimer Disease; Amino Acid Sequence; Animals; Biomedical Research; Disease Models, Animal; Gene Expression Profiling; Humans; Male; Mice; Tupaia

Drugs for Dementia and Excess of Hospitalization: A Longitudinal French Study. - François, Mathilde; Sicsic, Jonathan; Pelletier Fleury, Nathalie (J Alzheimers Dis, 2018)
BACKGROUND: The impact of adverse effects of drugs for dementia on the risk of hospitalization has not been much studied despite the impact of hospitalizations on cognitive decline. OBJECTIVE: To determine if the main adverse effects of cholinesterase inhibitors and memantine may be associated with excess of hospitalization and to quantify the subsequent impact on healthcare expenditures. METHODS: A representative sample of the French national health insurance beneficiaries aged 65 and older and suffering from dementia were included and followed from 2007 to 2014. Binary logit models for longitudinal data (GEE estimation technique) were used to estimate the excess of hospitalization events related to the adverse effects of anti-dementia drugs and then to derive the additional costs of hospitalizations for the public health insurance fund. RESULTS: In total, 7,668 patients were followed, generating 111,133 individual observations over the 8-year period. Treated patients were hospitalized significantly more than non-treated patients (adjusted Odd Ratio (OR) = 1.08, 95% confidence interval (95% CI) = [1.02 to 1.13], p = 0.004), mainly with cholinesterase inhibitors for cardiac (OR = 1.21, 95% CI = [1.01 to 1.46], p = 0.034) and gastrointestinal events (OR = 1.43, 95% CI = [1.01-2.05], p = 0.045), especially with rivastigmine. When extrapolated to the entire population, this corresponded to an annual additional cost of € 55,000. CONCLUSION: Prescription of antidementia drugs, more specifically rivastigmine, increases the risk of hospitalizations via their cardiac and gastrointestinal adverse effects and lead to additional health care expenditures. Even though these results must be confirmed, they may encourage cautious consideration of the balance between benefits and harms before a prescription is given.
Keywords: Aged; Aged, 80 and over; Cholinesterase Inhibitors; Dementia; Female; France; Health Expenditures; Hospitalization; Humans; Longitudinal Studies; Male; Rivastigmine

Dysregulation and Dislocation of SFPQ Disturbed DNA Organization in Alzheimer's Disease and Frontotemporal Dementia. - Lu, Jing; Shu, Runzhe; Zhu, Yan (J Alzheimers Dis, 2018)
SFPQ (Splicing factor proline- and glutamine-rich) is a DNA and RNA binding protein involved in transcription, pre-mRNA splicing, and DNA damage repair. SFPQ was found dysregulated in a few tauopathies such as Alzheimer's disease (AD) and frontotemporal dementia (FTD). In addition, knock-down of SFPQ induced FTD-like behavior in mouse. To confirm the role of SFPQ in AD and FTD, we analyzed the brain sections from the AD and FTD brain samples with SFPQ upregulation and dislocation. Specifically, we observed SFPQ dislocated to the cytoplasm and nuclear envelopes, and DNA structures and organizations were associated with these dislocation phenotypes in AD and FTD brains. Consistently, we also found decreased DAPI intensities and smaller chromocenters associated with SFPQ dislocation in nerural-2a (N2a) cells. As the upregulation and hyperphosphorylation of tau protein is a hallmark of AD and FTD, our study sought to investigate potential interactions between tau and SFPQ by co-transfection and co-immunoprecipitation assays in N2a cells. SFPQ dislocation was found enhanced with tau co-transfection and tau co-transfection further resulted in extended DNA disorganization in N2a cells. Overall, our results indicate that dysregulation and dislocation of SFPQ and subsequent DNA disorganization might be a novel pathway in the progression of AD and FTD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Animals; Brain; Cell Line, Tumor; DNA Damage; Female; Frontotemporal Dementia; Gene Expression Regulation; Humans; Male; Mice; PTB-Associated Splicing Factor; tau Proteins; Translocation, Genetic

Early and Persistent O-GlcNAc Protein Modification in the Streptozotocin Model of Alzheimer's Disease. - Dos Santos, João Paulo Almeida; Vizuete, Adriana; Hansen, Fernanda; Biasibetti, Regina; Gonçalves, Carlos-Alberto (J Alzheimers Dis, 2018)
O-GlcNAc transferase (OGT), an enzyme highly expressed in brain tissue, catalyzes the addition of N-acetyl-glucosamine (GlcNAc) to hydroxyl residues of serine and threonine of proteins. Brain protein O-GlcNAcylation is diminished in Alzheimer's disease (AD), and OGT targets include proteins of the insulin-signaling pathway (e.g., insulin receptor susbtrate-1, IRS-1). We hypothesized that ICV streptozotocin (STZ) also affects O-GlcNAc protein modification. We investigated hippocampal metabolic changes in Wistar rats, particularly OGT levels and insulin resistance, as well as related astroglial activities, immediately after ICV STZ administration (first week) and later on (fourth week). We found an early (at one week) and persistent (at fourth week) decrease in OGT in the ICV STZ model of AD, characterized by a spatial cognitive deficit. Consistent with this observation, we observed a decrease in protein O-GlnNAc modification at both times. Increased phosphorylation at serine-307 of IRS-1, which is related to insulin resistance, was observed on the fourth week. The decrease in OGT and consequent protein O-GlnNAc modifications appear to precede the decrease in glucose uptake and increment of the glyoxalase system observed in the hippocampus. Changes in glial fibrillary acidic protein and S100B in the hippocampus, as well as the alterations in cerebrospinal fluid S100B, confirm the astrogliosis. Moreover, decreases in glutamine synthetase and glutathione content suggest astroglial dysfunction, which are likely implicated in the neurodegenerative cascade triggered in this model. Together, these data contribute to the understanding of neurochemical changes in the ICV STZ model of sporadic AD, and may explain the decreases in protein O-GlcNAc levels and insulin resistance observed in AD.
Keywords: Alzheimer Disease; Analysis of Variance; Animals; Antibiotics, Antineoplastic; Brain; Disease Models, Animal; Glial Fibrillary Acidic Protein; Glucose; Glutathione; Insulin Receptor Substrate Proteins; Lactoylglutathione Lyase; Male; Maze Learning; N-Acetylglucosaminyltransferases; Rats; Rats, Wistar; S100 Calcium Binding Protein beta Subunit; Streptozocin; Time Factors

Early Stage Alterations in CA1 Extracellular Region Proteins Indicate Dysregulation of IL6 and Iron Homeostasis in the 5XFAD Alzheimer's Disease Mouse Model. - Gurel, Busra; Cansev, Mehmet; Sevinc, Cansu; Kelestemur, Seda; Ocalan, Busra; Cakir, Aysen; Aydin, Sami; Kahveci, Nevzat; Ozansoy, Mehmet; Taskapilioglu, Ozlem; Ulus, Ismail Hakki; Başar, Merve Karayel; et al. (J Alzheimers Dis, 2018)
In recent years, an increasing number of research papers revealed that the compositional and volumetric alterations in the extracellular matrix are the consequences of aging and may be related to Alzheimer's disease (AD). In this study, we aimed to demonstrate the alterations in hippocampal extracellular fluid proteins in vivo using the 5XFAD mouse model. Samples were obtained from hippocampi of 5XFAD mice (n = 6) and their non-transgenic littermates by intracerebral push-pull perfusion technique at 3 months of age, representing the pre-pathological stage of the AD. Proteins in the hippocampal perfusates were analyzed by Ultra Performance Liquid Chromatography-Electrospray Ionization Quadrupole Time-of-Flight Mass Spectrometry (UPLC-ESI-qTOF-MS/MS). 178 proteins were identified and 19 proteins of them were found to be statistically significantly altered (p≤0.05, fold change ≥40%, unique peptide count ≥3) in the hippocampal CA1 extracellular fluid of the 5XFAD mouse model. Ingenuity pathway analysis of the protein expression results identified IL6 as an upstream regulator. The upregulation of IL6 was validated by immunohistochemical staining of the hippocampus and cortex of the 5XFAD mice prior to Aβ plaque formation. Furthermore, the iron level in the hippocampus was measured by inductively coupled plasma-mass spectrometry as IL6 is mentioned in several studies to take part in iron homeostasis and inflammation and found to be increased in 5XFAD mice hippocampus. Alterations in extracellular matrix proteins in addition to increasing amount of hippocampal IL6 and iron in the early stages of AD may reveal inflammation-mediated iron dyshomeostasis in the early stages of neurodegeneration.
Keywords: Alzheimer Disease; Animals; CA1 Region, Hippocampal; Chromatography, Liquid; Disease Models, Animal; Female; Homeostasis; Interleukin-6; Iron; Mice; Mice, Transgenic; Proteomics; Tandem Mass Spectrometry

Endogenous Murine Amyloid-β Peptide Assembles into Aggregates in the Aged C57BL/6J Mouse Suggesting These Animals as a Model to Study Pathogenesis of Amyloid-β Plaque Formation. - Ahlemeyer, Barbara; Halupczok, Sascha; Rodenberg-Frank, Elke; Valerius, Klaus-Peter; Baumgart-Vogt, Eveline (J Alzheimers Dis, 2018)
Amyloid-β peptide (Aβ), paired helical filament-tau (PHF-tau), and α-synuclein are in the focus of neuroscience research because they aggregate in brains of patients with Alzheimer's and Parkinson's diseases. For this purpose, transgenic mouse models were used containing the human genes for AβPP/presenilin/tau or α-synuclein with the most frequent mutations. This is not ideal because most patients develop sporadic forms of the diseases with no causative single gene defect and furthermore the aggregation of human proteins in man is not necessarily the same in rodents. We hypothesized that for such cases the aged mouse could be an alternative model and analyzed the distribution of endogenous Aβ, PHF-tau, and α-synuclein in mouse brains at different ages. Whereas Aβ was below detectable levels at birth, it was present at high levels in the 15-month-old mouse. Aβ was found in the cytosol and lysosomes of neurons of the temporal cortex, cingulate area, pons, and cerebellum as well as extracellularly in the periventricular zone. Contrary to Aβ, mouse brain was devoid of PHF-tau-positive neurofibrillary tangles. α-Synuclein was detectable in the newborn mouse with highest levels in the marginal zone of the lateral cortex and average levels in the hippocampus, pons, and cerebellum. Brain-area specific differences in the α-synuclein level persisted up to 15 months of age, but increased 3-fold in all areas over time. α-Synuclein resided in the neuropil, but not in intracellular aggregates even in the aged mouse. We suggest the aged mouse as a model to study Aβ plaque formation.
Keywords: Age Factors; Aged; Aged, 80 and over; alpha-Synuclein; Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Female; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Neurofibrillary Tangles; Neurons; Plaque, Amyloid; tau Proteins

Epigenetic Drug Repositioning for Alzheimer's Disease Based on Epigenetic Targets in Human Interactome. - Chatterjee, Paulami; Roy, Debjani; Rathi, Nitin (J Alzheimers Dis, 2018)
BACKGROUND: Epigenetics has emerged as an important field in drug discovery. Alzheimer's disease (AD), the leading neurodegenerative disorder throughout the world, is shown to have an epigenetic basis. Currently, there are very few effective epigenetic drugs available for AD. OBJECTIVE: In this work, for the first time we have proposed 14 AD repositioning epigenetic drugs and identified their targets from extensive human interactome. METHODS: Interacting partners of the AD epigenetic proteins were identified from the extensive human interactome to construct Epigenetic Protein-Protein Interaction Network (EP-PPIN). Epigenetic Drug-Target Network (EP-DTN) was constructed with the drugs associated with the proteins of EP-PPIN. Regulation of non-coding RNAs associated with the target proteins of these drugs was also studied. AD related target proteins, epigenetic targets, enriched pathways, and functional categories of the proposed repositioning drugs were also studied. RESULTS: The proposed 14 AD epigenetic repositioning drugs have overlapping targets and miRs with known AD epigenetic targets and miRs. Furthermore, several shared functional categories and enriched pathways were obtained for these drugs with FDA approved epigenetic drugs and known AD drugs. CONCLUSIONS: The findings of our work might provide insight into future AD epigenetic-therapeutics.
Keywords: Alzheimer Disease; Antipsychotic Agents; Computational Biology; Drug Repositioning; Epigenesis, Genetic; Epigenomics; Humans; MicroRNAs; Protein Interaction Maps; PubMed

Erythromyeloid-Derived TREM2: A Major Determinant of Alzheimer's Disease Pathology in Down Syndrome. - Raha-Chowdhury, Ruma; Henderson, James W; Raha, Animesh Alexander; Stott, Simon R W; Vuono, Romina; Foscarin, Simona; Wilson, Liam; Annus, Tiina; Fincham, Robert; Allinson, Kieren; Devalia, Vinod; Friedland, Robert P; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Down syndrome (DS; trisomy 21) individuals have a spectrum of hematopoietic and neuronal dysfunctions and by the time they reach the age of 40 years, almost all develop Alzheimer's disease (AD) neuropathology which includes senile plaques and neurofibrillary tangles. Inflammation and innate immunity are key players in AD and DS. Triggering receptor expressed in myeloid cells-2 (TREM2) variants have been identified as risk factors for AD and other neurodegenerative diseases. OBJECTIVE: To investigate the effects of TREM2 and the AD-associated R47H mutation on brain pathology and hematopoietic state in AD and DS. METHODS: We analyzed peripheral blood, bone marrow, and brain tissue from DS, AD, and age-matched control subjects by immunohistochemistry and western blotting. TREM2-related phagocytosis was investigated using a human myeloid cell line. RESULTS: TREM2 protein levels in brain and sera declined with age and disease progression in DS. We observed soluble TREM2 in brain parenchyma that may be carried by a subset of microglia, macrophages, or exosomes. Two DS cases had the AD-associated TREM2-R47H mutation, which manifested a morphologically extreme phenotype of megakaryocytes and erythrocytes in addition to impaired trafficking of TREM2 to the erythroid membrane. TREM2 was shown to be involved in phagocytosis of red blood cells. TREM2 was seen in early and late endosomes. Silencing TREM2 using siRNA in THP1 cells resulted in significant cell death. CONCLUSION: We provide evidence that peripheral TREM2 originating from erythromyeloid cells significantly determines AD neuropathology in DS subjects. Understanding the molecular signaling pathways mediated by TREM2 may reveal novel therapeutic targets.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Cell Line; Disease Progression; Down Syndrome; Exosomes; Female; Humans; Immunity, Innate; Macrophages; Male; Membrane Glycoproteins; Microglia; Middle Aged; Phagocytosis; Polymorphism, Single Nucleotide; Receptors, Immunologic

Establishing a New Screening System for Mild Cognitive Impairment and Alzheimer's Disease with Mental Rotation Tasks that Evaluate Visuospatial Function. - Suzuki, Ayuko; Shinozaki, Jun; Yazawa, Shogo; Ueki, Yoshino; Matsukawa, Noriyuki; Shimohama, Shun; Nagamine, Takashi (J Alzheimers Dis, 2018)
BACKGROUND: The mental rotation task is well-known for the assessment of visuospatial function; however, it has not been used for screening of dementia patients. OBJECTIVE: The aim of this study was to create a simple screening test for patients with mild cognitive impairment (MCI) and Alzheimer's disease (AD) by focusing on non-amnestic symptoms. METHODS: Age-matched healthy controls (age 75.3±6.8), patients with MCI (76.5±5.5), and AD (78.2±5.0) participated in this study. They carried out mental rotation tasks targeting geometric graphics or alphabetical characters with three rotating angles (0°, 90°, and 180°) and indicated the correct answer. Response accuracy and reaction time were recorded along with their eye movements using an eye tracker. To quantify their visual processing strategy, the run count ratio (RC ratio) was calculated by dividing the mean number of fixations in incorrect answers by that in correct answers. RESULTS: AD patients showed lower accuracy and longer reaction time than controls. They also showed a significantly greater number of fixation and smaller saccade amplitude than controls, while fixation duration did not differ significantly. The RC ratio was higher for AD, followed by MCI and control groups. By setting the cut-off value to 0.47 in the 180° rotating angle task, we could differentiate MCI patients from controls with a probability of 80.0%. CONCLUSIONS: We established a new screening system for dementia patients by evaluating visuospatial function. The RC ratio during a mental rotation task is useful for discriminating MCI patients from controls.
Keywords: Aged; Aged, 80 and over; Agnosia; Alzheimer Disease; Case-Control Studies; Cognition; Cognitive Dysfunction; Disease Progression; Early Diagnosis; Eye Movements; Female; Humans; Male; Mental Status Schedule; Reaction Time; ROC Curve

Examining the Relationship between Trace Lithium in Drinking Water and the Rising Rates of Age-Adjusted Alzheimer's Disease Mortality in Texas. - Fajardo, Val Andrew; Fajardo, Val Andrei; LeBlanc, Paul J; MacPherson, Rebecca E K (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) mortality rates have steadily increased over time. Lithium, the current gold standard treatment for bipolar disorder, can exert neuroprotective effects against AD. OBJECTIVE: We examined the relationship between trace levels of lithium in drinking water and changes in AD mortality across several Texas counties. METHODS: 6,180 water samples from public wells since 2007 were obtained and averaged for 234 of 254 Texas counties. Changes in AD mortality rates were calculated by subtracting aggregated age-adjusted mortality rates obtained between 2000-2006 from those obtained between 2009-2015. Using aggregated rates maximized the number of counties with reliable mortality data. Correlational analyses between average lithium concentrations and changes in AD mortality were performed while also adjusting for gender, race, education, rural living, air pollution, physical inactivity, obesity, and type 2 diabetes. RESULTS: Age-adjusted AD mortality rate was significantly increased over time (+27%, p < 0.001). Changes in AD mortality were negatively correlated with trace lithium levels (p = 0.01, r = -0.20), and statistical significance was maintained after controlling for most risk factors except for physical inactivity, obesity, and type 2 diabetes. Furthermore, the prevalence of obesity and type 2 diabetes positively correlated with changes in AD mortality (p = 0.01 and 0.03, respectively), but also negatively correlated with trace lithium in drinking water (p = 0.05 and <0.0001, respectively). CONCLUSION: Trace lithium in water is negatively linked with changes in AD mortality, as well as obesity and type 2 diabetes, which are important risk factors for AD.
Keywords: Adult; Age Factors; Alzheimer Disease; Drinking Water; Female; Humans; Lithium; Longitudinal Studies; Male; Obesity; Prevalence; Risk Factors; Statistics as Topic; Texas; Young Adult

Executive Dysfunction Detected with the Frontal Assessment Battery in Alzheimer's Disease Versus Vascular Dementia. - D'Onofrio, Grazia; Panza, Francesco; Sancarlo, Daniele; Addante, Filomena; Solfrizzi, Vincenzo; Cantarini, Chiara; Mangiacotti, Antonio; Lauriola, Michele; Cascavilla, Leandro; Paris, Francesco; Lozupone, Madia; Daniele, Antonio; et al. (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) and vascular dementia (VaD) lead to progressive decline in executive function. We estimated the prevalence of executive dysfunction in AD and VaD patients, investigating cognitive, functional, and clinical correlates and also using a multidimensional approach based on a standardized comprehensive geriatric assessment (CGA). We included 215 patients (115 AD patients and 100 VaD patients) consecutively evaluated with a complete cognitive and affective assessment, a CGA, and the Frontal Assessment Battery (FAB) with six subtests investigating conceptualization, mental flexibility, motor programming, sensitivity to interference, inhibitory control, and environmental autonomy. The prevalence of dysexecutive syndrome screened with a FAB score <12 points was high in both AD (97 patients) and VaD (77 patients) (84.3% versus 77.0%, p = 0.171). AD patients were significantly younger, with higher grade of cognitive impairment and less severe comorbidity and polypharmacy than VaD patients. AD patients showed a significantly higher impairment in FAB total score and five FAB subtests (conceptualization, motor programming, sensitivity to interference, inhibitory control, and environmental autonomy) than VaD patients. These findings were largely confirmed in a sub-analysis conducted subdividing the sample in mild and moderate-to-severe demented patients and suggesting that in moderate-to-severe AD there was higher impairment in FAB total score and four FAB subtests (conceptualization, sensitivity to interference, inhibitory control, and environmental autonomy). Executive dysfunction could be greater in AD patients with moderate-to-severe dementia compared to VaD patients, although our groups were also not matched for age, comorbidity or polypharmacy, which could also exert an effect.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Comorbidity; Dementia, Vascular; Executive Function; Female; Frontal Lobe; Geriatric Assessment; Humans; Logistic Models; Male; Polypharmacy; Severity of Illness Index

The First Historically Reported Italian Family with FTD/ALS Teaches a Lesson on C9orf72 RE: Clinical Heterogeneity and Oligogenic Inheritance. - Giannoccaro, Maria Pia; Bartoletti-Stella, Anna; Piras, Silvia; Casalena, Alfonsina; Oppi, Federico; Ambrosetto, Giovanni; Montagna, Pasquale; Liguori, Rocco; Parchi, Piero; Capellari, Sabina (J Alzheimers Dis, 2018)
BACKGROUND: In 1969, Dazzi and Finizio reported the second observation of frontotemporal dementia (FTD) - amyotrophic lateral sclerosis (ALS) association in a large Italian kindred affected by an autosomal dominant form of ALS with high penetrance, frequent bulbar onset, and frequent cognitive decline. OBJECTIVE: To expand the original characterization of this family and report the link with the C9orf72 repeat expansion (RE). METHODS: We followed or reviewed the medical records of thirteen patients belonging to the original family and performed genetic analyses in four individuals. RESULTS: Eight patients presented with ALS, four with FTD, and one with schizophrenia. The C9orf72 RE was found in three patients but not in the healthy survivor. Additionally, we found a novel possible pathogenic variant in the ITM2B gene in one patient with a complex phenotype, associating movement disorders, psychiatric and cognitive features, deafness, and optic atrophy. The neuropathological examination of this patient did not show the classical features of ITM2B mutation related dementias suggesting that the putative pathogenic mechanism does not involve cellular mislocalization of the protein or the formation of amyloid plaques. CONCLUSION: We showed that the original Italian pedigree described with FTD/ALS carries the C9orf72 RE. Moreover, the finding of an additional mutation in another dementia causing gene in a patient with a more complex phenotype suggests a possible role of genetic modifiers in the disease. Together with other reports showing the coexistence of mutations in multiple ALS/FTD causative genes in the same family, our study supports an oligogenic etiology of ALS/FTD.
Keywords: Adult; Amyotrophic Lateral Sclerosis; C9orf72 Protein; Cerebral Cortex; DNA Repeat Expansion; Female; Frontotemporal Dementia; Genetic Testing; Humans; Male; Membrane Glycoproteins; Middle Aged; Multifactorial Inheritance; Mutation; Pedigree

Free Heme and Amyloid-β: A Fatal Liaison in Alzheimer's Disease. - Chiziane, Elisabeth; Telemann, Henriette; Krueger, Martin; Adler, Juliane; Arnhold, Jürgen; Alia, A; Flemmig, Jörg (J Alzheimers Dis, 2018)
While the etiology of Alzheimer's disease (AD) is still unknown, an increased formation of amyloid-β (Aβ) peptide and oxidative processes are major pathological mechanism of the disease. The interaction of Aβ with free heme leads to the formation of peroxidase-active Aβ-heme complexes. However, enzyme-kinetic data and systematic mutational studies are still missing. These aspects were addressed in this study to evaluate the role of Aβ-heme complexes in AD. The enzyme-kinetic measurements showed peroxidase-specific pH- and H2O2-dependencies. In addition, the enzymatic activity of Aβ-heme complexes constantly increased at higher peptide excess. Moreover, the role of the Aβ sequence for the named enzymatic activity was tested, depicting human-specific R5, Y10, and H13 as essential amino acids. Also by studying Y10 as an endogenous peroxidase substrate for Aβ-heme complexes, ratio-specific effects were observed, showing an optimal dityrosine formation at an about 40-fold peptide excess. As dityrosine formation promotes Aβ fibrillation while free heme disturbs protein aggregation, we also investigated the effect of Aβ-heme complex-derived peroxidase activity on the formation of Aβ fibrils. The fluorescence measurements showed a different fibrillation behavior at strong peroxidase activity, leading also to altered fibril morphologies. The latter was detected by electron microscopy. As illustrated by selected in vivo measurements on a mouse model of AD, the disease is also characterized by Aβ-derived microvessel destructions and hemolytic processes. Thus, thrombo-hemorrhagic events are discussed as a source for free heme in brain tissue. In summary, we suggest the formation and enzymatic activity of Aβ-heme complexes as pathological key features of AD.
Keywords: Alzheimer Disease; Amino Acid Sequence; Amyloid; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Heme; Humans; Hydrogen Peroxide; Mice; Mice, Transgenic; Oxidation-Reduction; Peptide Fragments; Peroxidases

Frequency of Cardiovascular Genetic Risk Factors in a Calabrian Population and Their Effects on Dementia. - Maletta, Raffaele; Smirne, Nicoletta; Bernardi, Livia; Anfossi, Maria; Gallo, Maura; Conidi, Maria Elena; Colao, Rosanna; Puccio, Gianfranco; Curcio, Sabrina A M; Laganà, Valentina; Frangipane, Francesca; Cupidi, Chiara; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Several genetic variants playing a key role in cholesterol levels, blood pressure, and vascular dysfunction influence the risk of Alzheimer's disease (AD) and vascular dementia (VaD). The many meta-analysis studies carried out on large numbers of samples in different populations have not provided clear results to date, because a trans-ethnic shift of risk genotypes in different populations is often observed. OBJECTIVES: To determine genotypes allele frequencies of the polymorphisms most frequently identified to be correlated with cardio-cerebrovascular disease and AD in a Southern Italy population and to investigate their possible association with dementia. METHODS: The genotype and allele frequencies of 13 cardio-cerebrovascular risk polymorphisms were assessed and their possible association with dementia was investigated in a case-control study, including 221 consecutive unrelated subjects diagnosed with dementia (120 subjects affected by AD, 55 by frontotemporal dementia, and 33 by vascular dementia) and 218 matched controls of Calabrian origin. RESULTS: Carriers of at least one APOEɛ4 allele resulted to be at higher risk of AD [OR(95% CI) = 2.721(1.477-5.011)] and VaD [OR(95% CI) = 6.205(2.356-16.342)] compared to non-carriers. Individuals with the IV genotype of the CETP polymorphism were more likely to have AD [OR(95% CI) = 2.427(1.364-4.319)] and VaD [OR(95% CI) = 3.649(1.455-9.152)] compared to subjects with the II-VV genotypes. CONCLUSION: CETP I405V polymorphism is likely a risk factor for AD and VaD in our cohort, independent of APOEɛ4 status. Unmodifiable genetic risk factors should be taken into account to promote a healthy lifestyle to prevent dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Case-Control Studies; Cholesterol Ester Transfer Proteins; Cohort Studies; Dementia, Vascular; Female; Frontotemporal Dementia; Gene Frequency; Humans; Italy; Male; Middle Aged; Polymorphism, Genetic; Risk Factors

GDF11 Rejuvenates Cerebrovascular Structure and Function in an Animal Model of Alzheimer's Disease. - Zhang, Wei; Guo, Yi; Li, Bo; Zhang, Qi; Liu, Jian-Hui; Gu, Guo-Jun; Wang, Jin-Hong; Bao, Rui-Kang; Chen, Yu-Jie; Xu, Jian-Rong (J Alzheimers Dis, 2018)
Cerebral amyloid angiopathy (CAA) is present in up to 90% of patients with Alzheimer's disease (AD), and may interact with classical neuropathology to exacerbate cognitive decline. Since growth differentiation factor 11 (GDF11) can activate vascular remodeling, we tested its effects on cognitive function and neuroinflammatory changes of AD model mice. We intravenously administered GDF11 or vehicle daily to 12-month-old transgenic mice overexpressing the amyloid-β protein precursor (AβPP)/PS1). Cognitive function was monitored using the Morris water maze, and after conclusion of the treatment, we assessed the morphology and presence of inflammatory markers in the cerebral vasculature. Subchronic treatment of adult AβPP/PS1 mice with GDF11 rescued cognitive function and ameliorated cerebrovascular function. In particular, the de novo genesis of small blood vessels and the expression of vascular-related proteins were significantly higher than in the vehicle-treated AβPP/PS1 mice, whereas the expressions of the inflammatory markers Iba-1 and GFAP significantly decreased in proportion to the lower ratio of two forms of amyloid-β (Aβ40/42). Daily intravenous treatment with GDF11-injection can rejuvenate respects of cognition and cerebrovascular changes in AD mice.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Behavior, Animal; Cerebral Amyloid Angiopathy; Disease Models, Animal; Growth Differentiation Factors; Maze Learning; Mice; Mice, Transgenic; Prefrontal Cortex; Presenilin-1

General Practice Clinical Data Help Identify Dementia Hotspots: A Novel Geospatial Analysis Approach. - Bagheri, Nasser; Wangdi, Kinley; Cherbuin, Nicolas; Anstey, Kaarin J (J Alzheimers Dis, 2018)
We have a poor understanding of whether dementia clusters geographically, how this occurs, and how dementia may relate to socio-demographic factors. To shed light on these important questions, this study aimed to compute a dementia risk score for individuals to assess spatial variation of dementia risk, identify significant clusters (hotspots), and explore their association with socioeconomic status. We used clinical records from 16 general practices (468 Statistical Area level 1 s, N = 14,746) from the city of west Adelaide, Australia for the duration of 1 January 2012 to 31 December 2014. Dementia risk was estimated using The Australian National University-Alzheimer's Disease Risk Index. Hotspot analyses were applied to examine potential clusters in dementia risk at small area level. Significant hotspots were observed in eastern and southern areas while coldspots were observed in the western area within the study perimeter. Additionally, significant hotspots were observed in low socio-economic communities. We found dementia risk scores increased with age, sex (female), high cholesterol, no physical activity, living alone (widow, divorced, separated, or never married), and co-morbidities such as diabetes and depression. Similarly, smoking was associated with a lower dementia risk score. The identification of dementia risk clusters may provide insight into possible geographical variations in risk factors for dementia and quantify these risks at the community level. As such, this research may enable policy makers to tailor early prevention strategies to the correct individuals within their precise locations.
Keywords: Age Factors; Aged; Aged, 80 and over; Australia; Dementia; Demography; Epidemiological Monitoring; Female; General Practice; Humans; Male; Retrospective Studies; Sex Factors; Topography, Medical

Geographical Distribution and Diversity of Gut Microbial NADH:Ubiquinone Oxidoreductase Sequence Associated with Alzheimer's Disease. - Paley, Elena L; Merkulova-Rainon, Tatiana; Faynboym, Aleksandr; Shestopalov, Valery I; Aksenoff, Igor (J Alzheimers Dis, 2018)
Earlier we reported induction of neurotoxicity and neurodegeneration by tryptophan metabolites that link the metabolic alterations to Alzheimer's disease (AD). Tryptophan is a product of Shikimate pathway (SP). Human cells lack SP, which is found in human gut bacteria exclusively using SP to produce aromatic amino acids (AAA). This study is a first attempt toward gene-targeted analysis of human gut microbiota in AD fecal samples. The oligonucleotide primers newly-designed for this work target SP-AAA in environmental bacteria associated with human activity. Using polymerase chain reaction (PCR), we found unique gut bacterial sequence in most AD patients (18 of 20), albeit rarely in controls (1 of 13). Cloning and sequencing AD-associated PCR products (ADPP) enables identification of Na(+)-transporting NADH: Ubiquinone reductase (NQR) in Clostridium sp. The ADPP of unrelated AD patients possess near identical sequences. NQR substrate, ubiquinone is a SP product and human neuroprotectant. A deficit in ubiquinone has been determined in a number of neuromuscular and neurodegenerative disorders. Antibacterial therapy prompted an ADPP reduction in an ADPP-positive control person who was later diagnosed with AD-dementia. We explored the gut microbiome databases and uncovered a sequence similarity (up to 97%) between ADPP and some healthy individuals from different geographical locations. Importantly, our main finding of the significant difference in the gut microbial genotypes between the AD and control human populations is a breakthrough.
Keywords: Adult; Aged; Aged, 80 and over; Alzheimer Disease; Anti-Bacterial Agents; Biological Transport; DNA Primers; Electron Transport Complex I; Feces; Female; Gastrointestinal Microbiome; Geography; Host-Pathogen Interactions; Humans; Male; Middle Aged; Sequence Analysis, DNA; Young Adult

Gradual Cerebral Hypoperfusion Impairs Fear Conditioning and Object Recognition Learning and Memory in Mice: Potential Roles of Neurodegeneration and Cholinergic Dysfunction. - Mehla, Jogender; Lacoursiere, Sean; Stuart, Emily; McDonald, Robert J; Mohajerani, Majid H (J Alzheimers Dis, 2018)
In the present study, male C57BL/6J mice were subjected to gradual cerebral hypoperfusion by implanting an ameroid constrictor (AC) on the left common carotid artery (CCA) and a stenosis on the right CCA. In the sham group, all surgical procedures were kept the same except no AC was implanted and stenosis was not performed. One month following the surgical procedures, fear conditioning and object recognition tests were conducted to evaluate learning and memory functions and motor functions were assessed using a balance beam test. At the experimental endpoint, mice were perfused and brains were collected for immunostaining and histology. Learning and memory as well as motor functions were significantly impaired in the hypoperfusion group. The immunoreactivity to choline acetyltransferase was decreased in dorsal striatum and basal forebrain of the hypoperfusion group indicating that cholinergic tone in these brain regions was compromised. In addition, an increased number of Fluoro-Jade positive neurons was also found in cerebral cortex, dorsal striatum and hippocampus indicating neurodegeneration in these brain regions. Based on this pattern of data, we argued that this mouse model would be a useful tool to investigate the therapeutic interventions for the treatment of vascular dementia. Additionally, this model could be employed to exploit the effect of microvascular occlusions on cognitive impairment in the absence and presence of Alzheimer's disease pathology.
Keywords: Animals; Brain; Carotid Stenosis; Cerebrovascular Circulation; Choline O-Acetyltransferase; Conditioning (Psychology); Disease Models, Animal; Fear; Fluoresceins; Learning Disorders; Male; Mice; Mice, Inbred C57BL; Phosphopyruvate Hydratase; Postural Balance; Recognition (Psychology)

High Caregiver Burden in Young Onset Dementia: What Factors Need Attention? - Lim, Linda; Zhang, Angeline; Lim, Levinia; Choong, Tanya-Marie; Silva, Eveline; Ng, Adeline; Kandiah, Nagaendran (J Alzheimers Dis, 2018)
BACKGROUND: There is an increase in prevalence of young onset dementia (YOD). The specific problems among YOD patients and levels of caregiver burden (CB) in this group warrants further evaluation. OBJECTIVE: To evaluate and compare level of CB in YOD and late onset dementia (LOD). Also, we sought to understand the specific factors, such as neuropsychiatric symptoms, that may affect the levels of caregiver burden in the YOD group. METHODS: Patient-caregiver dyads with YOD and LOD were recruited from a tertiary neurology center. Levels of CB between YOD and LOD were compared among 183 patient-caregiver dyads. CB was quantified using the Zarit Burden Inventory (ZBI). Neuropsychological evaluations as well as the Neuropsychiatric Inventory were performed. Factors that influenced level of CB in YOD group was investigated with regression analyses. RESULTS: There were 57 YOD and 126 LOD dyads. Caregivers of YOD subjects reported significantly higher levels of burden compared to caregivers of LOD subjects (ZBI: 17.3 versus 13.94; p = 0.015). 52.6% of YOD caregivers reported a high caregiver burden. When compared to caregivers of LOD, the odds of a caregiver of YOD reporting high caregiver burden was 2.34 (95% CI: 1.22-4.49: p = 0.010). YOD dyads with a high caregiver burden had significantly higher neuropsychiatric inventory scores. Risk factors for high caregiver burden in YOD included family history of dementia and behavioral symptoms including disinhibited behavior, delusions, and apathy. CONCLUSION: Targeted support for caregivers of patients with YOD is needed to address the higher CB in this group.
Keywords: Adaptation, Psychological; Age of Onset; Aged; Aged, 80 and over; Behavioral Symptoms; Caregivers; Cost of Illness; Cross-Sectional Studies; Dementia; Female; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Stress, Psychological; Surveys and Questionnaires

Hippocampal Stratum Radiatum, Lacunosum, and Moleculare Sparing in Mild Cognitive Impairment. - Su, Li; Hayes, Lawrence; Soteriades, Soteris; Williams, Guy; Brain, Susannah A E; Firbank, Michael J; Longoni, Giulia; Arnold, Robert J; Rowe, James B; O'Brien, John T (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is associated with atrophy in entorhinal cortex (ERC), the hippocampus, and its subfields Cornu Ammonis 1 (CA1) and subiculum, which predict conversion from mild cognitive impairment (MCI) to clinical AD. The stratum radiatum, lacunosum, and moleculare (SRLM) are also important gateways involving ERC and CA1, which are affected by early AD pathology. OBJECTIVE: To assess whether the SRLM is affected in MCI and AD. METHODS: In this proof-of-concept study, 27 controls, 13 subjects with AD, and 22 with MCI underwent 3T MRI. T1 maps were used for whole-hippocampal volumetry, T2 maps were segmented for hippocampal subfield areas, entorhinal cortex and subiculum thickness, and evaluated for SRLM integrity. RESULTS: Significant CA1 atrophy and subiculum thinning were found in both AD and MCI compared to similarly aged controls. However, SRLM integrity was only significantly reduced in AD but not in MCI compared to controls. There were no significant differences in other hippocampal subfields (CA2, CA3/dentate gyrus) or ERC thickness between the groups. Finally, CA1 and CA3/DG areas and SRLM clarity were correlated with clinical and cognitive measurements of disease severity. CONCLUSION: Although this study was cross sectional, it suggests a progression of specific subfield changes from MCI to established AD that is associated with the reduced integrity of SRLM, which may reflect more widespread hippocampal involvement as the disease progresses and the relative preservation of SRLM in MCI. These results provide new MRI biomarkers for disease staging and understanding of the neurobiology in AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Atrophy; Cognitive Dysfunction; Disease Progression; Entorhinal Cortex; Female; Hippocampus; Humans; Imaging, Three-Dimensional; Magnetic Resonance Imaging; Male; Middle Aged; Reproducibility of Results

Homocysteine and Cerebral Atrophy: The Epidemiology of Dementia in Singapore Study. - Tan, Bryce; Venketasubramanian, Narayanaswamy; Vrooman, Henri; Cheng, Ching-Yu; Wong, Tien Yin; Ikram, Mohammad Kamran; Chen, Christopher; Hilal, Saima (J Alzheimers Dis, 2018)
BACKGROUND: Plasma homocysteine levels are increasingly studied as a potential risk factor for dementia. Elevated homocysteine levels have been linked with gray and white matter volume reduction among individuals with mild cognitive impairment and Alzheimer's disease. However, the effects of homocysteine on brain changes in preclinical stages of dementia remain unexplored. OBJECTIVE: To examine the association of elevated homocysteine levels with markers of neurodegeneration, i.e., white and gray matter volume in an elderly population. METHODS: The study included 768 participants (mean age: 69.6±6.5 years, 51.3% women) from the Epidemiology of Dementia In Singapore study. Participants underwent a brain MRI scan and blood tests. Serum homocysteine was measured using competitive immunoassay. Cortical thickness and subcortical structural volume were quantified using FreeSurfer whereas white matter volume was quantified using a previous validated method. RESULTS: Higher homocysteine levels were significantly associated with decreased global white matter volume [mean difference (β) in volume (ml) per micromole per liter (μmol/l) increase in homocysteine levels: - 0.555, 95% Confidence Interval (CI): - 0.873; - 0.237], decreased parietal cortical thickness [β in thickness (μm) per μmol/l increase in homocysteine levels:- 1.429, 95% CI: - 2.781; - 0.077], and smaller volumes of the thalamus [β: - 0.017, 95% CI: - 0.026; - 0.008], brainstem [β: - 0.037, 95% CI: - 0.058; - 0.016], and accumbens [β: - 0.004, 95% CI: - 0.006; - 0.002]. CONCLUSION: Higher homocysteine levels were associated with cerebral atrophy. Further studies are required to assess whether lowering plasma homocysteine levels may prevent neurodegenerative changes or delay progression of clinical symptoms before the development of dementia.
Keywords: Aged; Atrophy; Biomarkers; Dementia; Female; Homocysteine; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Organ Size; Risk Factors; Singapore; White Matter

Homocysteine and Dementia: An International Consensus Statement. - Smith, A David; Refsum, Helga; Bottiglieri, Teodoro; Fenech, Michael; Hooshmand, Babak; McCaddon, Andrew; Miller, Joshua W; Rosenberg, Irwin H; Obeid, Rima (J Alzheimers Dis, 2018)
Identification of modifiable risk factors provides a crucial approach to the prevention of dementia. Nutritional or nutrient-dependent risk factors are especially important because dietary modifications or use of dietary supplements may lower the risk factor level. One such risk factor is a raised concentration of the biomarker plasma total homocysteine, which reflects the functional status of three B vitamins (folate, vitamins B12, B6). A group of experts reviewed literature evidence from the last 20 years. We here present a Consensus Statement, based on the Bradford Hill criteria, and conclude that elevated plasma total homocysteine is a modifiable risk factor for development of cognitive decline, dementia, and Alzheimer's disease in older persons. In a variety of clinical studies, the relative risk of dementia in elderly people for moderately raised homocysteine (within the normal range) ranges from 1.15 to 2.5, and the Population Attributable risk ranges from 4.3 to 31%. Intervention trials in elderly with cognitive impairment show that homocysteine-lowering treatment with B vitamins markedly slows the rate of whole and regional brain atrophy and also slows cognitive decline. The findings are consistent with moderately raised plasma total homocysteine (>11 μmol/L), which is common in the elderly, being one of the causes of age-related cognitive decline and dementia. Thus, the public health significance of raised tHcy in the elderly should not be underestimated, since it is easy, inexpensive, and safe to treat with B vitamins. Further trials are needed to see whether B vitamin treatment will slow, or prevent, conversion to dementia in people at risk of cognitive decline or dementia.
Keywords: Cognition; Cognitive Dysfunction; Consensus; Dementia; Dietary Supplements; Homocysteine; Humans; Meta-Analysis as Topic; Review Literature as Topic; Risk Factors; Vitamin B Complex

Human Gut Microbiota in Health and Alzheimer's Disease. - Szablewski, Leszek (J Alzheimers Dis, 2018)
Gut microbiota plays a crucial role in human health and disease. The alterations in the composition of gut microbiota may cause the onset of certain human pathologies. One of these is Alzheimer's disease (AD). High-fat diets, administration of antibiotics, lack of probiotics and/or prebiotics in diet increase the risk of AD. On the other hand, modulation of the composition of gut microbiota may decrease the risk of AD and be able to slow down the progression of AD.
Keywords: Alzheimer Disease; Diet, High-Fat; Dysbiosis; Gastrointestinal Microbiome; Gastrointestinal Tract; Humans; Risk Factors

Impact of a Virtual Dementia Experience on Medical and Pharmacy Students' Knowledge and Attitudes Toward People with Dementia: A Controlled Study. - Gilmartin-Thomas, Julia F-M; McNeil, John; Powell, Anne; Malone, Daniel T; Wolfe, Rory; Larson, Ian C; O'Reilly, Claire L; Kirkpatrick, Carl M; Kipen, Eva; Petrovich, Tanya; Bell, J Simon (J Alzheimers Dis, 2018)
BACKGROUND: Clinical practice guidelines for dementia highlight the importance of providing patient-centered care. This can be achieved by improving health professionals' attitudes and knowledge toward people with dementia. OBJECTIVE: Quantitatively evaluate the impact of a virtual dementia experience on medical and pharmacy students' knowledge and attitudes toward people with dementia. METHODS: A non-randomized controlled study from September-October 2016. The intervention group received a 1.5-hour multisensory, virtual simulation of light, sound, color, and visual content to experience the cognitive and perceptual difficulties faced by people with dementia. Controls participated in the standard curriculum only. All students were invited to complete the 20-item Dementia Attitudes Scale (DAS) pre- and post-intervention. RESULTS: A total of 278 students (n = 64 medical, n = 214 pharmacy) were analyzed (n = 80 intervention, n = 198 control). The majority of students were female (n = 184, 66.2%), with an average age of 22.5 years. The intervention improved the DAS total score and subdomains of comfort and knowledge (p < 0.001). CONCLUSION: The intervention had a positive impact on medical and pharmacy students' knowledge and attitudes toward people with dementia.
Keywords: Australia; Curriculum; Dementia; Female; Health Knowledge, Attitudes, Practice; Humans; Male; Students, Medical; Students, Pharmacy; Virtual Reality; Young Adult

The Impact of Music on the Self in Dementia. - Baird, Amee; Thompson, William Forde (J Alzheimers Dis, 2018)
In this review, we consider how the onset and progression of dementia can disrupt one's sense of self, and propose that music is an ideal tool for alleviating this distressing symptom. Various aspects of the self can be impaired in people with dementia, depending on how the self is defined. There are anecdotal reports that music can 'bring people back to themselves' in the face of dementia, but there have been scarce empirical investigations of this topic. Motivated by a consideration of the existing literature, we outline a novel theoretical framework that accounts for the relationship between music and the self in people with dementia. We propose that music has a number of 'design features' that make it uniquely equipped to engage multiple aspects of the self. We suggest that each design feature interacts with different aspects of the self to varying degrees, promoting overall wellbeing. We discuss how existing research on music and dementia fits within this framework, and describe two case studies in which music was an ideal stimulus for reaffirming their sense of self. Our framework may be useful for the diagnosis and treatment of impairments of self in people with dementia, and highlights how music, given its ability to engage all aspects of the self simultaneously, can result in an overall enhanced sense of self.
Keywords: Consciousness; Dementia; Humans; Music; Music Therapy; Personality

Impaired IL-17 Production in Gut-Residing Immune Cells of 5xFAD Mice with Alzheimer's Disease Pathology. - Saksida, Tamara; Koprivica, Ivan; Vujičić, Milica; Stošić-Grujičić, Stanislava; Perović, Milka; Kanazir, Selma; Stojanović, Ivana (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by accumulation of amyloid-β plaques that further promotes microglia-mediated neuroinflammatory responses and inflammation in the brain. Emerging data are revealing the relation between gut-associated lymphoid tissue (GALT) cells and CNS, as effector cells primed in the gut might home to the brain. This study aimed to determine cell composition of GALT in 5xFAD mice, an established model for AD. Immune cells isolated from Peyer's patches (PP) and mesenteric lymph nodes (MLN) were stained with surface and intracellular markers for T helper (Th) subpopulations, B lymphocytes and macrophages and analyzed cytofluorimetrically, while cytokine expression and production were determined by qPCR and ELISA, respectively. Inflammation was detected in GALT of 5xFAD mice with established AD pathology. Although the production of IFN-γ, IL-4, and IL-10 was comparable between the strains, lower IL-17 production was observed in PP and MLN cells. This phenomenon could not be attributed to a lower abundance of Th17 cells, or cytokines that initiate their formation or propagation (TGF-β, IL-6, and IL-23). Also, reduced IL-17 production was not a consequence of altered Il-17 mRNA transcription or deficiency of Rorγt, a key transcription factor for IL-17. However, the expression of miR-155 (a non-coding micro RNA that promotes the development of Th17 cells), was significantly lower in MLN cells of 5xFAD mice. In contrast, mice without AD neuropathology did not have inflammation in GALT or altered Th17 numbers, nor decreased IL-17 production. In conclusion, the observed changes in GALT of 5xFAD mice mirror the disease progression and might reflect inadequate immune surveillance in the gut and lead to enhanced AD pathology.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; B-Lymphocytes; Disease Models, Animal; Female; Interleukin-17; Lymph Nodes; Male; Mice; Mice, Transgenic; MicroRNAs; Peyer's Patches; Th17 Cells

In Vivo Visualization of Tau Accumulation, Microglial Activation, and Brain Atrophy in a Mouse Model of Tauopathy rTg4510. - Ishikawa, Ai; Tokunaga, Masaki; Maeda, Jun; Minamihisamatsu, Takeharu; Shimojo, Masafumi; Takuwa, Hiroyuki; Ono, Maiko; Ni, Ruiqing; Hirano, Shigeki; Kuwabara, Satoshi; Ji, Bin; Zhang, Ming-Rong; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Tau imaging using PET is a promising tool for the diagnosis and evaluation of tau-related neurodegenerative disorders, but the relationship among PET-detectable tau, neuroinflammation, and neurodegeneration is not yet fully understood. OBJECTIVE: We aimed to elucidate sequential changes in tau accumulation, neuroinflammation, and brain atrophy by PET and MRI in a tauopathy mouse model. METHODS: rTg4510 transgenic (tg) mice expressing P301L mutated tau and non-tg mice were examined with brain MRI and PET imaging (analyzed numbers: tg = 17, non-tg = 13; age 2.5∼14 months). As PET probes, [11C]PBB3 (Pyridinyl-Butadienyl-Benzothiazole 3) and [11C]AC-5216 were used to visualize tau pathology and 18-kDa translocator protein (TSPO) neuroinflammation. Tau pathology and microglia activation were subsequently analyzed by histochemistry. RESULTS: PET studies revealed age-dependent increases in [11C]PBB3 and [11C]AC-5216 signals, which were correlated with age-dependent volume reduction in the forebrain on MRI. However, the increase in [11C]PBB3 signals reached a plateau at age 7 months, and therefore its significant correlation with [11C]AC-5216 disappeared after age 7 months. In contrast, [11C]AC-5216 showed a strong correlation with both age and volume reduction until age 14 months. Histochemical analyses confirmed the relevance of pathological tau accumulation and elevated TSPO immunoreactivity in putative microglia. CONCLUSION: Our results showed that tau accumulation is associated with neuroinflammation and brain atrophy in a tauopathy mouse model. The time-course of the [11C]PBB3- and TSPO-PET finding suggests that tau deposition triggers progressive neuroinflammation, and the sequential changes can be evaluated in vivo in mouse brains.
Keywords: Animals; Atrophy; Benzothiazoles; Brain; Disease Models, Animal; Female; Magnetic Resonance Imaging; Male; Mice; Mice, Transgenic; Microglia; Positron-Emission Tomography; Receptors, GABA; tau Proteins; Tauopathies

Increased Foxo3a Nuclear Translocation and Activity is an Early Neuronal Response to βγ-Secretase-Mediated Processing of the Amyloid-β Protein Precursor: Utility of an AβPP-GAL4 Reporter Assay. - Law, Bernard M; Guest, Amy L; Pullen, Matthew W J; Perkinton, Michael S; Williams, Robert J (J Alzheimers Dis, 2018)
Sequential cleavage of the amyloid-β protein precursor (AβPP) by BACE1 (β-secretase) followed by theγ-secretase complex, is strongly implicated in Alzheimer's disease (AD) but the initial cellular responses to these cleavage events are not fully defined. β-secretase-mediated AβPP processing yields an extracellular domain (sAβPPβ) and a C-terminal fragment of AβPP of 99 amino acids (C99). Subsequent cleavage by γ-secretase produces amyloid-β (Aβ) and an AβPP intracellular domain (AICD). A cellular screen based on the generation of AICD from an AβPP-Gal4 fusion protein was adapted by introducing familial AD (FAD) mutations into the AβPP sequence and linking the assay to Gal4-UAS driven luciferase and GFP expression, to identify responses immediately downstream of AβPP processing in neurons with a focus on the transcription factor Foxo3a which has been implicated in neurodegeneration. The K670N/M671L, E682K, E693G, and V717I FAD mutations and the A673T protective mutation, were introduced into the AβPP sequence by site directed mutagenesis. When expressed in mouse cortical neurons, AβPP-Gal4-UAS driven luciferase and GFP expression was substantially reduced by γ-secretase inhibitors, lowered by β-secretase inhibitors, and enhanced by α-secretase inhibitors suggesting that AICD is a product of the βγ-secretase pathway. AβPP-Gal4-UAS driven GFP expression was exploited to identify individual neurons undergoing amyloidogenic AβPP processing, revealing increased nuclear localization of Foxo3a and enhanced Foxo3a-mediated transcription downstream of AICD production. Foxo3a translocation was not driven by AICD directly but correlated with reduced Akt phosphorylation. Collectively this suggests that βγ-secretase-mediated AβPP processing couples to Foxo3a which could be an early neuronal signaling response in AD.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Disease Models, Animal; Forkhead Box Protein O3; Mice; Mutagenesis, Site-Directed; Mutation; Neurons; Phosphorylation; Protein Transport; Signal Transduction

Increased Vulnerability of the Hippocampus in Transgenic Mice Overexpressing APP and Triple Repeat Tau. - Arner, Andrew; Rockenstein, Edward; Mante, Michael; Florio, Jazmin; Masliah, Deborah; Salehi, Bahar; Adame, Anthony; Overk, Cassia; Masliah, Eliezer; Rissman, Robert A (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is the most common tauopathy, characterized by progressive accumulation of amyloid-β (Aβ) and hyperphosphorylated tau. While pathology associated with the 4-repeat (4R) tau isoform is more abundant in corticobasal degeneration and progressive supranuclear palsy, both 3R and 4R tau isoforms accumulate in AD. Many studies have investigated interactions between Aβ and 4R tau in double transgenic mice, but few, if any, have examined the effects of Aβ with 3R tau. To examine this relationship, we crossed our APP751 mutant line with our recently characterized 3R tau mutant model to create a bigenic line (hAPP-3RTau) to model AD neuropathology. Mice were analyzed at 3 and 6 months of age for pathological and behavioral endpoints. While both the 3RTau and the hAPP-3RTau mice showed neuronal loss, increased tau aggregation, Aβ plaques and exhibited more behavioral deficits compared to the non-tg control, the bigenic mice often displaying relatively worsening levels. We found that even in young animals we found that the presence of APP/Aβ increased the accumulation of 3R tau in the neocortex and hippocampus. This observation was accompanied by activation of GSK3 and neurodegeneration in the neocortex and CA1 region. These results suggest that in addition to 4R tau, APP/Aβ may also enhance accumulation of 3R tau, a process which may be directly relevant to pathogenic pathways in AD. Our results demonstrate that this bigenic model closely parallels the pathological course of AD and may serve as a valuable model for testing new pharmacological interventions.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Disease Models, Animal; Female; Glycogen Synthase Kinase 3; Hippocampus; Humans; Male; Mice; Mice, Transgenic; Neocortex; tau Proteins; Tauopathies

Influence of Butyrylcholinesterase in Progression of Mild Cognitive Impairment to Alzheimer's Disease. - Gabriel, António José; Almeida, Maria Rosário; Ribeiro, Maria Helena; Carneiro, Diogo; Valério, Daniela; Pinheiro, Ana Cristina; Pascoal, Rui; Santana, Isabel; Baldeiras, Ines (J Alzheimers Dis, 2018)
BACKGROUND: Several demographic and genetic prognostic factors of conversion from mild cognitive impairment (MCI) to Alzheimer's disease (AD) have been recognized so far. The most frequent polymorphism of butyrylcholinesterase (BuChE), the K-variant, has been proposed as a risk factor for AD, but data regarding its influence on early disease progression is still limited. OBJECTIVE: To investigate the influence of the BuChE-K variant in MCI progression to AD. METHODS: 96 MCI patients were included in the study and were genotyped for BuChE-K variant and Apolipoprotein E (ApoE). Cerebrospinal fluid (CSF) BuChE activity, as well as the levels of AD biomarkers amyloid-β 42 (Aβ42), total and hyperphosphorylated tau (t-tau and p-tau) were also determined. RESULTS: No significant differences were found in either BuChE-K variant or BuChE activity between MCI patients that progressed to AD (MCI-AD) and patients that remained stable during clinical follow-up (MCI-St). As expected, baseline CSF levels of Aβ42 were significantly lower and t-Tau, p-Tau, and ApoE ɛ4 allele frequency were significantly higher in MCI-AD patients. An association between the ApoE ɛ4 allele and the BuChE-K variant in MCI-AD, but not in MCI-St patients, was found with patients carrying both alleles presenting the highest incidence of progression and the lowest estimated time of progression to AD. CONCLUSION: Although BuChE-K alone does not seem to play a major role in progression to AD in MCI patients, a synergistic effect with the ApoE ɛ4 allele was found, highlighting the importance of assessing these combined genotypes for evaluating risk progression in MCI patients.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Biomarkers; Butyrylcholinesterase; Cognitive Dysfunction; Disease Progression; Female; Genetic Predisposition to Disease; Humans; Kaplan-Meier Estimate; Male; Middle Aged; Risk Factors; tau Proteins

Interactions between Atrial Fibrillation, Cardiovascular Risk Factors, and ApoE Genotype in Promoting Cognitive Decline in Patients with Alzheimer's Disease: A Prospective Cohort Study. - Falsetti, Lorenzo; Viticchi, Giovanna; Buratti, Laura; Grigioni, Francesco; Capucci, Alessandro; Silvestrini, Mauro (J Alzheimers Dis, 2018)
BACKGROUND: An association between non-valvular atrial fibrillation (NVAF) and cognitive impairment has been hypothesized. OBJECTIVE: We sought to evaluate whether and how permanent NVAF (pNVAF) is associated with progression of cognitive impairment in patients with Alzheimer's disease (AD) in the presence of vascular or genetic risk factors. METHODS: 310 consecutive patients affected by mild-moderate AD were included and followed for a 24-month period. At the end of the follow-up, based on the results of the neuropsychological evaluation patients were classified as stable or deteriorated to severe AD. Clinical history, therapy, time in therapeutic range for anticoagulation, Framingham cardiovascular risk profile (FCRP), CHA2DS2-VASc score, Mini-Mental State Examination (MMSE), ApoE genotype, brain CT-scan, carotid ultrasound, and ECG were collected. Binary logistic and path analysis were adopted to assess relationships between pNVAF, ApoE, and cognitive outcome. RESULTS: Despite anticoagulant therapy, pNVAF was associated with lower entry MMSE, higher mean intima-media thickness (mIMT) and higher FCRP. Among patients carrying ApoE ɛ4 allele and affected by pNVAF, the lowest MMSE (14.90±7.62) and the highest mIMT (1.16±0.17 mm) and FCRP (26.24±3.96) values were detected. In this group, the risk of cognitive deterioration reached the highest probability. pNVAF was associated with an increased cognitive deterioration in subjects with high FCRP, CHA2DS2-VASc, or mIMT. CONCLUSIONS: pNVAF seems to identify AD patients with a significant atherosclerotic burden and reduced cognitive performances. The interaction between pNVAF and ApoE ɛ4 genotype, especially with aggregated risk factors and an advanced stage of vascular damage is associated with higher risk of fast cognitive deterioration.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Atherosclerosis; Atrial Fibrillation; Carotid Intima-Media Thickness; Cognitive Dysfunction; Disease Progression; Female; Humans; Logistic Models; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Prospective Studies; Risk Factors; Tomography, X-Ray Computed

Lentivirus-Mediated HDAC3 Inhibition Attenuates Oxidative Stress in APPswe/PS1dE9 Mice. - Yu, Linjie; Liu, Yi; Jin, Yuexinzi; Cao, Xiang; Chen, Jian; Jin, Jiali; Gu, Yue; Bao, Xinyu; Ren, Zhuoying; Xu, Yun; Zhu, Xiaolei (J Alzheimers Dis, 2018)
Amyloid-β (Aβ) induces a burst of oxidative stress and plays a critical role in the pathogenesis of Alzheimer's disease (AD). Our previous results have shown that histone deacetylase 3 (HDAC3) inhibition ameliorates spatial memory deficits and decreases the Aβ burden in the brains of 9-month-old APPswe/PS1dE9 (APP/PS1) mice. In this study, we investigated the role of HDAC3 inhibition in oxidative stress in vivo and in vitro models of AD. HDAC3 was detected mainly in the neurons, and HDAC3 inhibition significantly decreased reactive oxygen species generation and improved primary cortical neuron viability. In addition, HDAC3 inhibition attenuated spatial memory dysfunction in 6-month-old APP/PS1 mice, and decreased the apoptotic rate in the hippocampi as demonstrated by TUNEL staining. HDAC3 inhibition also reduced markers of lipid peroxidation, protein oxidation, and DNA/RNA oxidation in the hippocampi of APP/PS1 mice. Moreover, HDAC3 inhibition inactivated the c-Abl/MST1/YAP signaling pathway in the hippocampi of APP/PS1 mice. In conclusion, our data show that HDAC3 inhibition can attenuate spatial memory deficits and inhibit oxidative stress in APP/PS1 mice; these results indicate a potential strategy for AD treatment.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Disease Models, Animal; Hippocampus; Histone Deacetylases; Lentivirus; Male; Maze Learning; Mice; Mice, Inbred C57BL; Mice, Transgenic; Neurons; Oxidative Stress; Plaque, Amyloid; Primary Cell Culture; Reactive Oxygen Species; Spatial Memory; tau Proteins

A Longitudinal Study of Total and Phosphorylated α-Synuclein with Other Biomarkers in Cerebrospinal Fluid of Alzheimer's Disease and Mild Cognitive Impairment. - Wang, Hua; Stewart, Tessandra; Toledo, Jon B; Ginghina, Carmen; Tang, Lu; Atik, Anzari; Aro, Patrick; Shaw, Leslie M; Trojanowski, John Q; Galasko, Douglas R; Edland, Steven; Jensen, Poul H; et al. (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) features a dynamic sequence of amyloid deposition, neurodegeneration, and cognitive impairment. A significant fraction of AD brains also displays Lewy body pathology, suggesting that addition of classically Parkinson's disease-related proteins to the AD biomarker panel may be of value. To determine whether addition of cerebrospinal fluid (CSF) total α-synuclein and its form phosphorylated at S129 (pS129) to the AD biomarker panel [Amyloid-β1-42 (Aβ42), tau, and phosphorylated tau (p-tau181)] improves its performance, we examined CSF samples collected longitudinally up to 7 years as part of the Alzheimer's Disease Neuroimaging Initiative. From 87 AD, 177 mild cognitive impairment (MCI), and 104 age-matched healthy controls, 792 baseline and longitudinal CSF samples were tested for total α-synuclein, pS129, Aβ42, tau, and p-tau181. pS129, but not total α-synuclein, was weakly associated with diagnosis at baseline when t-tau/Aβ42 was included in the statistical model (β= 0.0026, p = 0.041, 95% CI [(0.0001)-(0.005)]). CSF α-synuclein predicted Alzheimer's Disease Assessment Scale-Cognitive (β= -0.59, p = 0.0015, 95% CI [(-0.96)-(-0.23)]), memory (β= 0.4, p = 0.00025, 95% CI [(0.16)-(0.59)]), and executive (0.62,<0.0001, 95% CI [(0.31)-(0.93)]) function composite scores, and progression from MCI to AD (β= 0.019, p = 0.0011, 95% CI [(0.002)-(0.20)]). pS129 was associated with executive function (β= -2.55, p = 0.0085, 95% CI [(-4.45)-(-0.66)]). Lower values in the mismatch between α-synuclein and p-tau181 predicted faster cognitive decline (β= 0.64, p = 0.0012, 95% CI [(0.48)-(0.84)]). Longitudinal biomarker changes did not differ between groups, and may not reflect AD progression. The α-synuclein-p-tau181-Mismatch could better predict longitudinal cognitive changes than classical AD markers alone, and its pathological correlates should be investigated further.
Keywords: Aged; Aged, 80 and over; alpha-Synuclein; Alzheimer Disease; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Disease Progression; Executive Function; Female; Humans; Linear Models; Longitudinal Studies; Male; Memory Disorders; Multivariate Analysis; Neuropsychological Tests; Phosphorylation; tau Proteins

Low Prevalence of Cancer in Patients with Frontotemporal Lobar Degeneration. - Katisko, Kasper; Haapasalo, Annakaisa; Koivisto, Anne; Krüger, Johanna; Hartikainen, Päivi; Korhonen, Ville; Helisalmi, Seppo; Herukka, Sanna-Kaisa; Remes, Anne M; Solje, Eino (J Alzheimers Dis, 2018)
Several studies have reported reduced risk of cancer in patients with Alzheimer's disease (AD) or Parkinson's disease. The relationship between cancer and frontotemporal lobar degeneration (FTLD) has not been previously reported. Here, our aim was to evaluate the occurrence of cancer in Finnish FTLD patients with a high proportion of C9ORF72 repeat expansion carriers in comparison to age- and sex-matched group of AD patients and control subjects classified as not cognitively impaired (NCI). The prevalence of cancer was 9.7% in FTLD, 18.7% in AD, and 17.4% in NCI (FTLD versus AD p = 0.012, FTLD versus NCI p = 0.029) groups. No differences were observed between C9ORF72 repeat expansion carriers and non-carriers inside the FTLD group. To our knowledge, this is the first study showing significantly lower prevalence of cancer in FTLD patients compared to patients with AD or NCI subjects. Our data suggest an inverse association between neurodegeneration and cancer and that FTLD-specific mechanisms may underlie the especially strong inverse association observed in this study.
Keywords: Aged; Alzheimer Disease; C9orf72 Protein; DNA Repeat Expansion; Female; Finland; Frontotemporal Lobar Degeneration; Heterozygote; Humans; Male; Middle Aged; Neoplasms; Prevalence

Mesenchymal Stem Cell-Derived Extracellular Vesicles Suppresses iNOS Expression and Ameliorates Neural Impairment in Alzheimer's Disease Mice. - Wang, Shan-Shan; Jia, Jianjun; Wang, Zhenfu (J Alzheimers Dis, 2018)
BACKGROUND: Mesenchymal stem cells (MSCs)-derived extracellular vesicles (EVs) have been reported to exhibit therapeutic effects in various animal models of neurological diseases, such as stroke and hypoxic-ischemic brain injury. OBJECTIVE: The present study investigated the potential beneficial effect of MSC-derived EVs in an animal model of Alzheimer's disease (AD). METHODS: APP/PS1 mice and their non-transgenic littermates (WT) received intracerebroventricle injection of MSC-derived EVs once per two days for two weeks. Then novel object recognition and water maze tasks were carried out to measure the cognitive behaviors. Electrophysiological tests were carried out to measure hippocampal synaptic plasticity. Inducible nitric oxide synthase (iNOS) mRNA and protein levels were measured by qRT-PCR and western blotting in primary cultured neurons treated with amyloid-β peptide (Aβ) or prepared from APP/PS1 mice. RESULTS: Treatment with MSC-derived EVs alleviates exogenous Aβ-induced iNOS mRNA and protein expression. In cultured primary neurons prepared from APP/PS1 pups, iNOS mRNA and protein levels were significantly reduced when treated with MSC-derived EVs. MSC-derived EVs improved cognitive behavior, rescued impairment of CA1 synaptic transmission, and long-term potentiation in APP/PS1 mice. CONCLUSION: MSC-derived EVs possessed beneficial effects in a mouse model of AD, probably by suppressing Aβ induced iNOS expression.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Cells, Cultured; Disease Models, Animal; Extracellular Vesicles; Humans; Male; Mesenchymal Stem Cells; Mice; Mice, Transgenic; Neuronal Plasticity; Neurons; Nitric Oxide Synthase Type II; Synaptic Transmission

microRNA 221 Targets ADAM10 mRNA and is Downregulated in Alzheimer's Disease. - Manzine, Patricia R; Pelucchi, Silvia; Horst, Maria A; Vale, Francisco A C; Pavarini, Sofia C I; Audano, Matteo; Mitro, Nico; Di Luca, Monica; Marcello, Elena; Cominetti, Márcia R (J Alzheimers Dis, 2018)
ADAM10 is the α-secretase that cleaves amyloid-β protein precursor in the non-amyloidogenic pathway in Alzheimer's disease (AD) and is known to be regulated by different microRNAs (miRNAs), which are post-transcriptional regulators related to several biological and pathological processes, including AD. Here we proposed to explore and validate miRNAs that have direct or indirect relations to the AD pathophysiology and ADAM10 gene. Approximately 700 miRNAs were analyzed and 21 differentially expressed miRNAs were validated in a sample of 21 AD subjects and 17 cognitively healthy matched controls. SH-SY5Y cells were transfected with miR-144-5p, miR-221, and miR-374 mimics and inhibitors, and ADAM10 protein levels were evaluated. miR-144-5p, miR-221, and miR-374 were downregulated in AD. The overexpression of miR-221 in SH-SY5Y cells resulted in ADAM10 reduction and its inhibition in ADAM10 increased. These findings show that miR-221 can be a new potential therapeutic target for increasing ADAM10 levels in AD. In addition, these results can contribute to the better understanding of ADAM10 post-transcriptional regulation.
Keywords: ADAM10 Protein; Aged; Aged, 80 and over; Alzheimer Disease; Cell Line, Tumor; Cohort Studies; Down-Regulation; Female; Humans; Male; MicroRNAs; Middle Aged; Neuroblastoma; Psychiatric Status Rating Scales; RNA, Messenger; ROC Curve; Transfection

The Need to Separate Chronic Traumatic Encephalopathy Neuropathology from Clinical Features. - Iverson, Grant L; Keene, C Dirk; Perry, George; Castellani, Rudolph J (J Alzheimers Dis, 2018)
There is tremendous recent interest in chronic traumatic encephalopathy (CTE) in former collision sport athletes, civilians, and military veterans. This critical review places important recent research results into a historical context. In 2015, preliminary consensus criteria were developed for defining the neuropathology of CTE, which substantially narrowed the pathology previously reported to be characteristic. There are no agreed upon clinical criteria for diagnosis, although sets of criteria have been proposed for research purposes. A prevailing theory is that CTE is an inexorably progressive neurodegenerative disease within the molecular classification of the tauopathies. However, historical and recent evidence suggests that CTE, as it is presented in the literature, might not be pathologically or clinically progressive in a substantial percentage of people. At present, it is not known whether the emergence, course, or severity of clinical symptoms can be predicted by specific combinations of neuropathologies, thresholds for accumulation of pathology, or regional distributions of pathologies. More research is needed to determine the extent to which the neuropathology ascribed to long-term effects of neurotrauma is static, progressive, or both. Disambiguating the pathology from the broad array of clinical features that have been reported in recent studies might facilitate and accelerate research- and improve understanding of CTE.
Keywords: Chronic Traumatic Encephalopathy; Cognition Disorders; Disease Progression; Gait Disorders, Neurologic; Humans; Neurodegenerative Diseases; Neuropathology; Tremor

Neuropsychiatric and Cognitive Subtypes among Community-Dwelling Older Persons and the Association with DSM-5 Mild Neurocognitive Disorder: Latent Class Analysis. - Liew, Tau Ming; Yu, Junhong; Mahendran, Rathi; Ng, Tze-Pin; Kua, Ee-Heok; Feng, Lei (J Alzheimers Dis, 2018)
BACKGROUND: Neuropsychiatric symptoms (NPS) have been shown to increase the risk of neurocognitive disorders (NCD), leading to the recently-published criteria of mild behavioral impairment (MBI) to identify pre-dementia using NPS alone. However, MBI drew concerns about over-diagnosing subclinical psychiatric disorders. OBJECTIVE: We hypothesized that the specificity of NPS in predicting NCD may be improved by considering NPS together with various domains of cognitive deficits. We tested this hypothesis by identifying subtypes based on the combination of NPS and cognitive deficits among community-dwelling older persons, and evaluating how the identified subtypes were associated with mild NCD. METHODS: Our participants were from a community-based cohort study. They completed assessments such as Geriatric Depression Scale (GDS), Geriatric Anxiety Inventory (GAI), and Montreal Cognitive Assessment (MoCA). Those with possible cognitive impairment underwent further evaluations for mild NCD. Latent class analysis was conducted using GDS, GAI, and MoCA domains. Logistic regression was performed to investigate the association between the latent-classes and mild NCD. RESULTS: We included 825 participants, and identified four distinct subtypes: Subtype 1 (no NPS or cognitive deficits), Subtype 2 (NPS alone), Subtype 3 (cognitive deficits alone), and Subtype 4 (both NPS and cognitive deficits). Subtype 1 and 2 had low risk of prevalent mild NCD (OR 0.92- 1.00), while Subtype 3 conferred a moderate risk (OR 4.47- 4.85) and Subtype 4 had the highest risk (OR 7.95- 8.63). CONCLUSION: We demonstrated the benefits of combining NPS and cognitive deficits to predict those at highest risk of prevalent mild NCD. Our findings highlighted the relevance of subclinical psychiatric symptoms in predicting NCD, and indirectly supported the need for longer durations of NPS to improve its specificity.
Keywords: Aged; Cognition; Cognitive Dysfunction; Diagnostic and Statistical Manual of Mental Disorders; Female; Humans; Latent Class Analysis; Logistic Models; Longitudinal Studies; Male; Middle Aged; Neuropsychological Tests; Sensitivity and Specificity

A Novel Antibody Targeting Tau Phosphorylated at Serine 235 Detects Neurofibrillary Tangles. - Brici, David; Götz, Jürgen; Nisbet, Rebecca M (J Alzheimers Dis, 2018)
Alzheimer's disease is characterized by two main pathological hallmarks in the human brain: the extracellular deposition of amyloid-β as plaques and the intracellular accumulation of the hyperphosphorylated protein tau as neurofibrillary tangles (NFTs). Phosphorylated tau (p-tau) specific-antibodies and silver staining have been used to reveal three morphological stages of NFT formation: pre-NFTs, intraneuronal NFTs (iNFTs), and extraneuronal NFTs (eNFTs). Here we characterize a novel monoclonal antibody, RN235, which is specific for tau phosphorylated at serine 235, and detects iNFTs and eNFTs in brain tissue, suggesting that phosphorylation at this site is indicative of late stage changes in tau.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Animals; Antibodies, Monoclonal; Antibody Specificity; Brain; Disease Models, Animal; Humans; Mice; Neurofibrillary Tangles; Phosphorylation; Plaque, Amyloid; tau Proteins

Nutrition: Review on the Possible Treatment for Alzheimer's Disease. - Botchway, Benson O A; Moore, Masania K; Akinleye, Faith O; Iyer, Ishwari C; Fang, Marong (J Alzheimers Dis, 2018)
Since its discovery some hundred years ago, Alzheimer's disease (AD), a neurodegenerative disease and an eminent cause of most dementia, continues to pose problems for affected families and society, especially in developed countries. With the approved medications by the Food and Drugs Administration in the United States, effectual treatment of AD apropos to the complete eradication of the disease continues to be elusive due to complexities relating to the pathophysiology of the disease. Nutrition has and continues to play a salient role in the survival of living organisms with no exception for human beings. Herein, we report the connection between nutrition and AD with particular attention to vitamins, curcumin, and the Mediterranean diet.
Keywords: Alzheimer Disease; Curcumin; Diet, Mediterranean; Dietary Supplements; Humans; Nutritional Status; Risk Factors; Vitamins

Patient Characteristics and Outcomes Associated with Receiving an Earlier Versus Later Diagnosis of Probable Alzheimer's Disease. - Kirson, Noam Y; Scott Andrews, J; Desai, Urvi; King, Sarah B; Schonfeld, Sophie; Birnbaum, Howard G; Ball, Daniel E; Kahle-Wrobleski, Kristin (J Alzheimers Dis, 2018)
BACKGROUND: Effectiveness of Alzheimer's disease (AD) treatments may depend critically on the timeliness of intervention. OBJECTIVE: To compare characteristics and outcomes of patients diagnosed with probable AD (prAD) based on time elapsed from first onset of cognitive decline. METHODS: Patients with ≥1 prAD diagnosis and ≥1 follow-up visit were selected from the National Alzheimer's Coordinating Center (NACC) Uniform Data Set (UDS; 9/2005-6/2015) and stratified based on the time between the perceived onset of cognitive decline at baseline and first prAD diagnosis (i.e., earlier versus later diagnosis). Characteristics at baseline and prAD diagnosis, clinically meaningful progression, and medication use following prAD diagnosis were compared. RESULTS: Median time from perceived onset of cognitive decline to prAD diagnosis was 4.5 years (earlier diagnosis: ≤3.46; later diagnosis: >5.71). Earlier-diagnosed patients (n = 1,476) were younger at baseline (74.3 versus 76.3 years) and had better cognitive and functional scores than later-diagnosed patients (n = 1,474). At first prAD diagnosis, earlier-diagnosed patients had lower mean global Clinical Dementia Rating (CDR) score (0.8 versus 1.1), higher mean Mini-Mental State Examination (MMSE) (22.6 versus 20.0), and lower mean Functional Activities Questionnaire (11.6 versus 17.3). Earlier- and later-diagnosed patients experienced similar time to a decrease of ≥3 points in MMSE (median 23.2 versus 23.1 months, p = 0.83), but earlier-diagnosed patients had longer time to a CDR score of ≥2 points, and longer times to initiation of AD medication and antipsychotic agents (all p < 0.01). CONCLUSION: Earlier prAD diagnosis in NACC data is associated with higher cognitive function and lower functional impairment at diagnosis.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Cognition Disorders; Cohort Studies; Datasets as Topic; Disease Progression; Female; Humans; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Statistics, Nonparametric; Time Factors

Perspectives on Communicating Biomarker-Based Assessments of Alzheimer's Disease to Cognitively Healthy Individuals. - Milne, Richard; Bunnik, Eline; Diaz, Ana; Richard, Edo; Badger, Shirlene; Gove, Dianne; Georges, Jean; Fauria, Karine; Molinuevo, Jose-Luis; Wells, Katie; Ritchie, Craig; Brayne, Carol (J Alzheimers Dis, 2018)
In clinical trials which target pathophysiological mechanisms associated with Alzheimer's disease, research participants who are recruited based on biomarker test results should be informed about their increased risk of developing Alzheimer's dementia. This paper presents the results of a qualitative focus group study of attitudes and concerns toward learning information about biomarker-based risk status among healthy research participants in the United Kingdom and Spain and people with dementia and their supporters/caregivers from countries represented in the European Working Group of People with Dementia of Alzheimer Europe. The study identified expectations related to learning risk status and preferences related to the content, quality, and follow-up of the disclosure process. The latter emphasize distinctions between risk and diagnoses, the importance of clear information about risk, and suggestions for risk reduction, as well as expectations for follow up and support. The implications of these preferences for practice are discussed. Providing details of research participants' experience and views may serve as a guide for the development of processes for the responsible disclosure of Alzheimer's disease biomarkers.
Keywords: Adult; Aged; Alzheimer Disease; Biomarkers; Caregivers; Disclosure; Female; Focus Groups; Humans; Male; Middle Aged; Qualitative Research; Risk Factors; Spain; United Kingdom

Potential of Low Dose Leuco-Methylthioninium Bis(Hydromethanesulphonate) (LMTM) Monotherapy for Treatment of Mild Alzheimer's Disease: Cohort Analysis as Modified Primary Outcome in a Phase III Clinical Trial. - Wilcock, Gordon K; Gauthier, Serge; Frisoni, Giovanni B; Jia, Jianping; Hardlund, Jiri H; Moebius, Hans J; Bentham, Peter; Kook, Karin A; Schelter, Bjoern O; Wischik, Damon J; Davis, Charles S; Staff, Roger T; et al. (J Alzheimers Dis, 2018)
BACKGROUND: LMTM is being developed as a treatment for AD based on inhibition of tau aggregation. OBJECTIVES: To examine the efficacy of LMTM as monotherapy in non-randomized cohort analyses as modified primary outcomes in an 18-month Phase III trial in mild AD. METHODS: Mild AD patients (n = 800) were randomly assigned to 100 mg twice a day or 4 mg twice a day. Prior to unblinding, the Statistical Analysis Plan was revised to compare the 100 mg twice a day as monotherapy subgroup (n = 79) versus 4 mg twice a day as randomized (n = 396), and 4 mg twice a day as monotherapy (n = 76) versus 4 mg twice a day as add-on therapy (n = 297), with strong control of family-wise type I error. RESULTS: The revised analyses were statistically significant at the required threshold of p < 0.025 in both comparisons for change in ADAS-cog, ADCS-ADL, MRI atrophy, and glucose uptake. The brain atrophy rate was initially typical of mild AD in both add-on and monotherapy groups, but after 9 months of treatment, the rate in monotherapy patients declined significantly to that reported for normal elderly controls. Differences in severity or diagnosis at baseline between monotherapy and add-on patients did not account for significant differences in favor of monotherapy. CONCLUSIONS: The results are consistent with earlier studies in supporting the hypothesis that LMTM might be effective as monotherapy and that 4 mg twice a day may serve as well as higher doses. A further suitably randomized trial is required to test this hypothesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Antipsychotic Agents; Cohort Studies; Double-Blind Method; Female; Humans; International Cooperation; Male; Mental Status and Dementia Tests; Methylene Blue; Middle Aged; Treatment Outcome

Predictors of Age of Diagnosis and Survival of Alzheimer's Disease in Down Syndrome. - Sinai, Amanda; Mokrysz, Claire; Bernal, Jane; Bohnen, Ingrid; Bonell, Simon; Courtenay, Ken; Dodd, Karen; Gazizova, Dina; Hassiotis, Angela; Hillier, Richard; McBrien, Judith; McCarthy, Jane; et al. (J Alzheimers Dis, 2018)
BACKGROUND: People with Down syndrome (DS) are an ultra-high risk population for Alzheimer's disease (AD). Understanding the factors associated with age of onset and survival in this population could highlight factors associated with modulation of the amyloid cascade. OBJECTIVE: This study aimed to establish the typical age at diagnosis and survival associated with AD in DS and the risk factors associated with these. METHODS: Data was obtained from the Aging with Down Syndrome and Intellectual Disabilities (ADSID) research database, consisting of data extracted from clinical records of patients seen by Community Intellectual Disability Services (CIDS) in England. Survival times when considering different risk factors were calculated. RESULTS: The mean age of diagnosis was 55.80 years, SD 6.29. Median survival time after diagnosis was 3.78 years, and median age at death was approximately 60 years. Survival time was associated with age of diagnosis, severity of intellectual disability, living status, anti-dementia medication status, and history of epilepsy. Age at diagnosis and treatment status remained predictive of survival time following adjustment. CONCLUSION: This study provides the best estimate of survival in dementia within the DS population to date, and is in keeping with previous estimates from smaller studies in the DS population. This study provides important estimates and insights into possible predictors of survival and age of diagnosis of AD in adults with DS, which will inform selection of participants for treatment trials in the future.
Keywords: Age of Onset; Alzheimer Disease; Down Syndrome; England; Female; Humans; Male; Middle Aged; Risk Factors; Survival Analysis

Prevalence of Delirium in a Population of Elderly Outpatients with Dementia: A Retrospective Study. - Addesi, Desirée; Maio, Raffaele; Smirne, Nicoletta; Laganà, Valentina; Altomari, Natalia; Puccio, Gianfranco; Colao, Rosanna; Cupidi, Chiara; Perticone, Francesco; Bruni, Amalia Cecilia (J Alzheimers Dis, 2018)
BACKGROUND: Delirium is a multifactorial geriatric syndrome and often occurs in patients with cognitive impairment. It also remains under-recognized, specifically in elderly outpatients, because signs of delirium might overlap with symptoms of dementia. OBJECTIVE: The aim of the present study is to retrospectively apply the chart-based delirium instrument on a cohort of elderly outpatients with dementia, to assess prevalence and features of delirium in this population. METHODS: We randomly selected 650 medical records of outpatients referred to the "Neurogenetic Regional Centre" (CRN) of Lamezia Terme. Each evaluation included demographics, medical history, drugs, type and severity of dementia, and cognitive and functional status. Delirium was identified by the application of the chart-based delirium instrument. RESULTS: The prevalence of delirium was 13.3%. The study population was divided, according to the presence of delirium, into two subgroups. Compared to the no delirium group, the delirium group was significantly older and had greater cognitive impairment with lower MMSE scores both at baseline and at the end of the follow up. They also had a significant lower score on the ADL and IADL. In this group, a higher intake of antihypertensive and antipsychotic drugs, together with a lower intake of cholinesterase inhibitors and memantine, was observed. CONCLUSIONS: In this study, the chart-based delirium instrument was applied to an outpatient population affected by dementia and followed for a long time. Our data confirm the importance that age and frailty play on the genesis of delirium and suggest attention should be paid to the pharmacological treatment of these patients.
Keywords: Aged; Aged, 80 and over; Antipsychotic Agents; Cohort Studies; Delirium; Dementia; Female; Geriatric Assessment; Humans; Male; Outpatients; Prevalence; Severity of Illness Index

Prevalence of Potentially Inappropriate Medication Use in Older Inpatients with and without Cognitive Impairment: A Systematic Review. - Redston, Mitchell R; Hilmer, Sarah N; McLachlan, Andrew J; Clough, Alexander J; Gnjidic, Danijela (J Alzheimers Dis, 2018)
BACKGROUND: Older people with cognitive impairment, including dementia and delirium, are high users of acute care services internationally. Potentially inappropriate medication (PIM) use may be associated with adverse outcomes, including hospital re-admission, functional disability, and mortality. OBJECTIVE: This systematic review aimed to quantify and compare the prevalence of PIMs in older inpatients with and without cognitive impairment. METHODS: A systematic search of observational studies was performed independently assessed by two reviewers in Embase, Medline, PsycINFO, International Pharmaceutical Abstracts, Scopus, and Informit. Articles published in English during the period January 2007-June 2017 that reported PIM prevalence in hospital inpatients ≥ 65 years were included. PIMs were defined as the presence of polypharmacy (multiple medication use) and using implicit or explicit tools, such as the Beers criteria, and 'Screening Tool of Older Person's Prescriptions' (STOPP). RESULTS: 47 articles were included. In studies measuring polypharmacy (n = 15), the prevalence of PIMs ranged from 53.2% to 89.8% and 30.4% to 97.1% for inpatients with and without cognitive impairment, respectively, and 24.0% to 80.0% when cognitive status was unreported. In studies employing explicit and implicit tools (n = 35), the prevalence of PIMs when cognitive impairment was reported ranged from 20.6% to 80.5% using the Beers criteria, and 39.3% to 88.5% using STOPP. When cognitive status was unreported, the prevalence of PIMs ranged from 7.0% to 79.2% using the Beers criteria, and 20.0% to 63.4% using STOPP. CONCLUSION: Our findings suggest a high prevalence of PIMs in older inpatients with and without cognitive impairment. Future studies should investigate the impact of PIM use on patient-centered outcomes, such as functional status and quality of life, to inform enhanced acute care services.
Keywords: Aged; Cognitive Dysfunction; Dementia; Humans; Inpatients; Polypharmacy; Potentially Inappropriate Medication List; Prevalence; Quality of Life

Progression of Alzheimer's Disease: A Longitudinal Study in Norwegian Memory Clinics. - Eldholm, Rannveig Sakshaug; Barca, Maria Lage; Persson, Karin; Knapskog, Anne-Brita; Kersten, Hege; Engedal, Knut; Selbæk, Geir; Brækhus, Anne; Skovlund, Eva; Saltvedt, Ingvild (J Alzheimers Dis, 2018)
BACKGROUND: The course of Alzheimer's disease (AD) varies considerably between individuals. There is limited evidence on factors important for disease progression. OBJECTIVE: The primary aim was to study the progression of AD, as measured by the Clinical Dementia Rating Scale Sum of Boxes (CDR-SB). Secondary aims were to investigate whether baseline characteristics are important for differences in progression, and to examine the correlation between progression assessed using three different instruments: CDR-SB (0-18), the cognitive test Mini-Mental State Examination (MMSE, 0-30), and the functional measure Instrumental Activities of Daily Living (IADL, 0-1). METHODS: The Progression of AD and Resource use (PADR) study is a longitudinal observational study in three Norwegian memory clinics. RESULTS: In total, 282 AD patients (mean age 73.3 years, 54% female) were followed for mean 24 (16-37) months. The mean annual increase in CDR-SB was 1.6 (SD 1.8), the mean decrease in MMSE score 1.9 (SD 2.6), and the mean decrease in IADL score 0.13 (SD 0.14). Of the 282 patients, 132 (46.8%) progressed slowly, with less than 1 point yearly increase in CDR-SB. Cognitive test results at baseline predicted progression rate, and together with age, ApoE, history of hypertension, and drug use could explain 17% of the variance in progression rate. The strongest correlation of change was found between CDR-SB and IADL scores, the weakest between MMSE and IADL scores. CONCLUSION: Progression rate varied considerably among AD patients; about half of the patients progressed slowly. Cognitive test results at baseline were predictors of progression rate.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Disease Progression; Female; Humans; Linear Models; Longitudinal Studies; Male; Memory; Neuropsychological Tests; Norway

Progression of Alzheimer's Disease-Related Pathology and Cell Counts in a Patient with Idiopathic Normal Pressure Hydrocephalus. - Libard, Sylwia; Laurell, Katarina; Cesarini, Kristina Giuliana; Alafuzoff, Irina (J Alzheimers Dis, 2018)
We had an opportunity to assess the change observed in the brain regarding Alzheimer's disease (AD)-related alterations, cell count, and inflammation that took place during a period of 21 months in a subject with a definite diagnosis of AD and idiopathic Normal Pressure Hydrocephalus (iNPH). Four neuronal markers, i.e., synaptophysin, microtubule associated protein 2, non-phosphorylated neurofilament H (SMI32), and embryonic lethal abnormal visual system proteins 3/4 HuC/HuD (HuC/HuD); three microglial markers CD68, Human Leucocytic Antigen DR, ionized calcium-binding adaptor molecule 1, glial fibrillary acidic protein (GFAP); and AD-related markers, hyperphosphorylated τ (HPτ) and amyloid-β (Aβ, Aβ40, Aβ42) were assessed. Morphometrically assessed immunoreactivity of all neuronal and all microglial markers and Aβ42 decreased parallel with an increase in the HPτ in the frontal cortex. The expression of GFAP was stable with time. The first sample was obtained during the therapeutic shunting procedure for iNPH, and the second sample was obtained postmortem. Negligible reactive changes were observed surrounding the shunt channel. In conclusion, in the late stage of AD with time, a neuronal loss, increase in the HPτ, and decrease in Aβ42 and microglia was observed, whereas the expression of GFAP was rather stable. The observations described here suggest that when a brain biopsy has been obtained from an adult subject with iNPH, the assessment of postmortem brain is of major significance.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Biopsy; Brain; Cell Count; Disease Progression; Female; Glial Fibrillary Acidic Protein; Humans; Hydrocephalus, Normal Pressure; Microglia; tau Proteins

The Progression of Neuropsychiatric Symptoms in Alzheimer's Disease During a Five-Year Follow-Up: Kuopio ALSOVA Study. - Hallikainen, Ilona; Hongisto, Kristiina; Välimäki, Tarja; Hänninen, Tuomo; Martikainen, Janne; Koivisto, Anne M (J Alzheimers Dis, 2018)
BACKGROUND: An improved understanding of the role of neuropsychiatric symptoms (NPS) in the course of Alzheimer's disease (AD) has recently emerged. NPS lead to hospitalization and caregiver stress, but are more variable during the course of the disease than other symptoms. Knowledge about the role of specific NPS in disease progression and prognosis is especially limited. OBJECTIVES: To examine the relationship between specific NPS and AD severity during a 5-year follow-up period, and to determine which baseline NPS predict AD progression. METHODS: 236 persons with very mild (CDR 0.5) or mild (CDR 1) AD at baseline and their caregivers were followed up for five years as part of the ALSOVA study. The Neuropsychiatric Inventory was used to assess NPS, and AD severity progression was measured with the Clinical Dementia Rating Sum of Boxes. Data was analyzed with Generalized Estimated Equations and Linear Mixed Models. RESULTS: The baseline NPS that best predicted AD progression were delusions, agitation, and aberrant motor behavior, while AD severity during follow-up was associated with hallucinations, delusions, agitation, apathy, aberrant motor behavior, and sleep and appetite disturbances. CONCLUSIONS: Persons with mild AD presenting delusions, agitation, and aberrant motor behavior at the time of diagnosis could have a more rapidly progressing disease, and some NPS are associated with AD severity. These results highlight the importance of evaluating NPS at the time of AD diagnosis, and the need to offer additional support to persons presenting delusions, agitation and aberrant motor behavior, and their caregivers.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Anxiety; Caregivers; Delusions; Disease Progression; Female; Finland; Hallucinations; Humans; Linear Models; Male; Motor Activity; Multivariate Analysis; Neuropsychological Tests; Severity of Illness Index

Protective Effects of Indian Spice Curcumin Against Amyloid-β in Alzheimer's Disease. - Reddy, P Hemachandra; Manczak, Maria; Yin, XiangLing; Grady, Mary Catherine; Mitchell, Andrew; Tonk, Sahil; Kuruva, Chandra Sekhar; Bhatti, Jasvinder Singh; Kandimalla, Ramesh; Vijayan, Murali; Kumar, Subodh; Wang, Rui; et al. (J Alzheimers Dis, 2018)
The purpose of our article is to assess the current understanding of Indian spice, curcumin, against amyloid-β (Aβ)-induced toxicity in Alzheimer's disease (AD) pathogenesis. Natural products, such as ginger, curcumin, and gingko biloba have been used as diets and dietary supplements to treat human diseases, including cancer, cardiovascular, respiratory, infectious, diabetes, obesity, metabolic syndromes, and neurological disorders. Products derived from plants are known to have protective effects, including anti-inflammatory, antioxidant, anti-arthritis, pro-healing, and boosting memory cognitive functions. In the last decade, several groups have designed and synthesized curcumin and its derivatives and extensively tested using cell and mouse models of AD. Recent research on Aβ and curcumin has revealed that curcumin prevents Aβ aggregation and crosses the blood-brain barrier, reach brain cells, and protect neurons from various toxic insults of aging and Aβ in humans. Recent research has also reported that curcumin ameliorates cognitive decline and improves synaptic functions in mouse models of AD. Further, recent groups have initiated studies on elderly individuals and patients with AD and the outcome of these studies is currently being assessed. This article highlights the beneficial effects of curcumin on AD. This article also critically assesses the current limitations of curcumin's bioavailability and urgent need for new formulations to increase its brain levels to treat patients with AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Blood-Brain Barrier; Curcumin; Disease Models, Animal; Humans; Mice; Neuroprotective Agents; Randomized Controlled Trials as Topic; Spices

Putative Dementia Cases Fluctuate as a Function of Mini-Mental State Examination Cut-Off Points. - Rosa, Ilka M; Henriques, Ana G; Wiltfang, Jens; da Cruz E Silva, Odete A B (J Alzheimers Dis, 2018)
As the population ages, there is a growing need to quickly and accurately identify putative dementia cases. Many cognitive tests are available; among those commonly used are the Cognitive Dementia Rating (CDR) and the Mini-Mental Status Examination (MMSE). The aim of this work was to compare the validity and reliability of these cognitive tests in a primary care based cohort (pcb-Cohort). The MMSE and the CDR were applied to 568 volunteers in the pcb-Cohort. Distinct cut-off points for the MMSE were considered, namely MMSE 27, MMSE 24, and MMSE PT (adapted for the Portuguese population). The MMSE 27 identified the greatest number of putative dementia cases, and, as determined by the ROC curve, it was the most sensitive and specific of the MMSE cut-offs considered. Putative predictive or risk factors identified included age, literacy, depression, and diabetes mellitus (DM). DM has previously been indicated as a risk factor for dementia and Alzheimer's disease. Comparatively, the MMSE 27 cut-off has the greatest sensibility (94.9%) and specificity (66.3%) when compared to MMSE PT and MMSE 24. Upon comparing MMSE and CDR scores, the latter identified a further 146 putative dementia cases, thus permitting one to propose that in an ideal situation, both tests should be employed. This increases the likelihood of identifying putative dementia cases for subsequent follow up work, thus these cognitive tests represent important tools in patient care. Further, this is a significant study for Portuguese populations, where few of these studies have been carried out.
Keywords: Age Factors; Aged; Aged, 80 and over; Cohort Studies; Community Health Planning; Cross-Sectional Studies; Dementia; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Neuropsychological Tests; ROC Curve

The Rationale and Design of the Reducing Pathology in Alzheimer's Disease through Angiotensin TaRgeting (RADAR) Trial. - Kehoe, Patrick G; Blair, Peter S; Howden, Beth; Thomas, David L; Malone, Ian B; Horwood, Jeremy; Clement, Clare; Selman, Lucy E; Baber, Hannah; Lane, Athene; Coulthard, Elizabeth; Passmore, Anthony Peter; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Anti-hypertensives that modify the renin angiotensin system may reduce Alzheimer's disease (AD) pathology and reduce the rate of disease progression. OBJECTIVE: To conduct a phase II, two arm, double-blind, placebo-controlled, randomized trial of losartan to test the efficacy of Reducing pathology in Alzheimer's Disease through Angiotensin TaRgeting (RADAR). METHODS: Men and women aged at least 55 years with mild-to-moderate AD will be randomly allocated 100 mg encapsulated generic losartan or placebo once daily for 12 months after successful completion of a 2-week open-label phase and 2-week placebo washout to establish drug tolerability. 228 participants will provide at least 182 subjects with final assessments to provide 84% power to detect a 25% difference in atrophy rate (therapeutic benefit) change over 12 months at an alpha level of 0.05. We will use intention-to-treat analysis, estimating between-group differences in outcomes derived from appropriate (linear or logistic) multivariable regression models adjusting for minimization variables. RESULTS: The primary outcome will be rate of whole brain atrophy as a surrogate measure of disease progression. Secondary outcomes will include changes to 1) white matter hyperintensity volume and cerebral blood flow; 2) performance on a standard series of assessments of memory, cognitive function, activities of daily living, and quality of life. Major assessments (for all outcomes) and relevant safety monitoring of blood pressure and bloods will be at baseline and 12 months. Additional cognitive assessment will also be conducted at 6 months along with safety blood pressure and blood monitoring. Monitoring of blood pressure, bloods, and self-reported side effects will occur during the open-label phase and during the majority of the post-randomization dispensing visits. CONCLUSION: This study will identify whether losartan is efficacious in the treatment of AD and whether definitive Phase III trials are warranted.
Keywords: Activities of Daily Living; Alzheimer Disease; Antihypertensive Agents; Atrophy; Blood Pressure Monitors; Brain; Clinical Trials, Phase II as Topic; Disease Progression; Double-Blind Method; Female; Humans; Losartan; Magnetic Resonance Imaging; Male; Multivariate Analysis; Quality of Life; Randomized Controlled Trials as Topic; Regression Analysis; Renin-Angiotensin System

Relationships Between Lower Olfaction and Brain White Matter Lesions in Elderly Subjects with Mild Cognitive Impairment. - Heinrich, Juliette; Vidal, Jean-Sébastien; Simon, Axelle; Rigaud, Anne-Sophie; Hanon, Olivier; Epelbaum, Jacques; Viollet, Cécile; Duron, Emmanuelle (J Alzheimers Dis, 2018)
BACKGROUND: Olfactory impairment is reported in mild cognitive impairment (MCI) and Alzheimer's disease (AD) and is associated with hippocampal atrophy. In elderly people, dementia with AD neuropathology and white matter lesions (WML) is common. In this context, olfactory impairment could also depend on the presence of WML. OBJECTIVE: To assess the cross-sectional relationship between olfaction and WML in elderly subjects with MCI. METHODS: Consecutive subjects, >65 years old, diagnosed as MCI after a comprehensive neuropsychological assessment in an expert memory center, with a brain MRI performed within a year and without major depressive state, were included. Olfaction was assessed by the Brief Smell Identification Test (BSIT). Two trained neuroradiologists, blind to cognitive and olfaction status, visually assessed hippocampal atrophy according to Scheltens' scale and WML according to Fazekas criteria. RESULTS: Seventy-five MCI subjects (mean age (SD) = 77.1 (6.2) years, 74.7% of women) were included. After adjustment for age and sex, factors associated with low BSIT scores were older age (p = 0.007), lower BMI (p = 0.08), lower MMSE score (p = 0.05), lower FCRST (p = 0.008), hippocampal atrophy (p = 0.04), periventricular WML (p = 0.007), and deep WML burden (p = 0.005). In multivariate analysis, severe deep WML (OR (95% CI) = 6.29 (1.4-35.13), p = 0.02) remained associated with low BSIT score independently from hippocampal atrophy. CONCLUSION: In elderly MCI subjects, low olfactory performances are associated with WML, whose progression may be slowed by vascular treatments. A longitudinal study to evaluate whether the progression of WML, hippocampal atrophy and low olfactory function, can predict accurately conversion from MCI to dementia is ongoing.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Atrophy; Cognitive Dysfunction; Cross-Sectional Studies; Disease Progression; Female; Humans; Logistic Models; Longitudinal Studies; Magnetic Resonance Imaging; Male; Multivariate Analysis; Neuropsychological Tests; Olfaction Disorders; Severity of Illness Index; White Matter

Role of ASK1/p38 Cascade in a Mouse Model of Alzheimer's Disease and Brain Aging. - Hasegawa, Yu; Toyama, Kensuke; Uekawa, Ken; Ichijo, Hidenori; Kim-Mitsuyama, Shokei (J Alzheimers Dis, 2018)
To examine the role of ASK1 in Alzheimer's disease (AD), we generated 5XFAD mice deficient in ASK1 and investigated the characteristics of old 5XFAD and wild-type mice with ASK1 deficiency. ASK1 deficiency improved cognitive function in 24-month-old 5XFAD mice, which was associated with the reduction of phosphorylated p38. Thus, ASK1/p38 cascade seems to play some role in the pathogenesis of AD in mice. In 24-month-old wild-type mice, ASK1 deficiency increased cerebral vasoreactivity to acetazolamide and significantly reduced brain soluble Aβ, which were also associated with the reduction of phosphorylated p38. Thus, ASK1/p38 cascade may contribute to brain aging of wild-type mice. Collectively, our present results provided the evidence suggesting the involvement of ASK1/p38 cascade in AD and brain aging.
Keywords: Aging; Alzheimer Disease; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Aspartic Acid Endopeptidases; Avoidance Learning; Disease Models, Animal; Gene Expression Regulation; MAP Kinase Kinase Kinase 5; MAP Kinase Signaling System; Mice; Mice, Inbred C57BL; Mice, Transgenic; Presenilin-1; Reaction Time

Sally-Anne Test in Patients with Alzheimer's Disease Dementia. - Takenoshita, Shintaro; Terada, Seishi; Yokota, Osamu; Kutoku, Yumiko; Wakutani, Yosuke; Nakashima, Makoto; Maki, Yohko; Hattori, Hideyuki; Yamada, Norihito (J Alzheimers Dis, 2018)
Social cognition has recently been recognized as one of the essential cognitive domains. Some reports suggested that patients with Alzheimer's disease dementia (ADD) presented significant theory of mind deficits even in the mild condition. However, most previous studies included only small numbers of patients with ADD. The present study administered the first-order false belief (Sally-Anne) test to 116 consecutive patients with ADD from the outpatient units of the Memory Clinic and compared the characteristics of the two groups with correct and incorrect answers on the test. Then various clinical characteristics were evaluated. Only 37.1% of patients with ADD correctly answered the Sally-Anne test with the right explanation. Comparison between the two groups of correct and incorrect answers revealed a significant association between the frontal assessment battery score and the result of the Sally-Anne test in the multiple logistic regression analyses. Thus, patients with ADD presented a significant deficit in social cognition even in the mild condition. Frontal dysfunction was thought to be related to the deficits in mild ADD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition Disorders; Disease Progression; Female; Humans; Logistic Models; Male; Neuropsychological Tests; Social Behavior Disorders; Theory of Mind

Structural Connectivity Alterations Along the Alzheimer's Disease Continuum: Reproducibility Across Two Independent Samples and Correlation with Cerebrospinal Fluid Amyloid-β and Tau. - Tucholka, Alan; Grau-Rivera, Oriol; Falcon, Carles; Rami, Lorena; Sánchez-Valle, Raquel; Lladó, Albert; Gispert, Juan Domingo; Molinuevo, José Luis (J Alzheimers Dis, 2018)
BACKGROUND: Gray matter changes associated with the progression of Alzheimer's disease (AD) have been thoroughly studied. However, alterations in white matter tracts have received less attention, particularly during early or preclinical stages of the disease. OBJECTIVE: To identify the structural connectivity changes across the AD continuum. METHODS: We performed probabilistic tractography in a total of 183 subjects on two independent samples that include control (n = 68) and preclinical AD individuals (n = 28), patients diagnosed with mild cognitive impairment (MCI) due to AD (n = 44), and AD patients (n = 43). We compared the connectivity between groups, and with CSF Aβ42 and tau biomarkers. RESULTS: We observed disconnections in preclinical individuals, mainly located in the temporal lobe. This pattern of disconnection spread to the parietal and frontal lobes at the MCI stage and involved almost all the brain in AD. These findings were not driven by gray matter atrophy. DISCUSSION: Using tractography, we were able to identify white matter changes between subsequent disease stages and, notably, also in preclinical AD. Therefore, this method may be useful for detecting early and specific brain structural changes during preclinical AD stage.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Atrophy; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Cohort Studies; Disease Progression; Female; Gray Matter; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Reproducibility of Results; Spain; tau Proteins; White Matter

Supplemental Retinal Carotenoids Enhance Memory in Healthy Individuals with Low Levels of Macular Pigment in A Randomized, Double-Blind, Placebo-Controlled Clinical Trial. - Power, Rebecca; Coen, Robert F; Beatty, Stephen; Mulcahy, Riona; Moran, Rachel; Stack, Jim; Howard, Alan N; Nolan, John M (J Alzheimers Dis, 2018)
BACKGROUND: There is a biologically plausible rationale whereby the dietary carotenoids lutein (L), zeaxanthin (Z), and meso-zeaxanthin (MZ), which are collectively referred to as macular pigment (MP) in the central retina (macula), support the maintenance of cognition via their antioxidant and anti-inflammatory properties. OBJECTIVE: To investigate the impact of supplemental L, Z, and MZ on memory, executive function, and verbal fluency among healthy individuals with low MP levels. METHODS: In this double-blind, placebo-controlled, randomized clinical trial, subjects (n = 91; mean±SD age = 45.42±12.40; % male = 51.6) consumed a daily formulation of 10 mg L, 10 mg MZ, and 2 mg Z (n = 45) or placebo (n = 46) for 12 months. Cognitive domains assessed included verbal and visual learning, immediate and delayed memory, executive function, and verbal fluency. MP and serum carotenoid concentrations of L, Z, and MZ were also measured. RESULTS: Following 12-month supplementation, individuals in the active group exhibited statistically significant improvements in memory when compared to the placebo group (paired associated learning [PAL] memory score [rANOVA, p = 0.009]; PAL errors [rANOVA, p = 0.017]). Furthermore, the observed reduction in the number of errors made in the PAL task among those in the intervention group was positively and significantly related to observed increases in MP volume (p = 0.005) and observed increases in serum concentrations of L (p = 0.009). CONCLUSION: This randomized, double-blind, placebo-controlled clinical trial demonstrates a memory-enhancing effect of daily supplementation with L, Z, and MZ in healthy subjects with low MP at baseline. The implications of these findings for intellectual performance throughout life, and for risk of cognitive decline in later life, warrant further study.
Keywords: Adult; Cognition; Dietary Supplements; Double-Blind Method; Executive Function; Female; Healthy Volunteers; Humans; Lutein; Macular Pigment; Male; Memory, Episodic; Middle Aged; Retina; Vision Tests; Zeaxanthins

Synthetic Fragment of Receptor for Advanced Glycation End Products Prevents Memory Loss and Protects Brain Neurons in Olfactory Bulbectomized Mice. - Volpina, Olga M; Samokhin, Alexandr N; Koroev, Dmitriy O; Nesterova, Inna V; Volkova, Tatyana D; Medvinskaya, Natalia I; Nekrasov, Pavel V; Tatarnikova, Olga G; Kamynina, Anna V; Balasanyants, Samson M; Voronina, Tamara A; Kulikov, Alexey M; et al. (J Alzheimers Dis, 2018)
Activation of receptor for advanced glycation end products (RAGE) plays an essential role in the development of Alzheimer's disease (AD). It is known that the soluble isoform of the receptor binds to ligands and prevents negative effects of the receptor activation. We proposed that peptide fragments from RAGE prevent negative effects of the receptor activation during AD neurodegeneration. We have synthesized peptide fragments from surface-exposed regions of RAGE. Peptides were intranasally administrated into olfactory bulbectomized (OBX) mice, which developed some characteristics similar to AD neurodegeneration. We have found that only insertion of fragment (60-76) prevents the memory of OBX mice. Immunization of OBX mice with peptides showed that again only (60-76) peptide protected the memory of animals. Both intranasal insertion and immunization decreased the amyloid-β (Aβ) level in the brain. Activity of shortened fragments of (60-76) peptide was tested and showed only the (60-70) peptide is responsible for manifestation of activity. Intranasal administration of (60-76) peptide shows most protective effect on morpho-functional characteristics of neurons in the cortex and hippocampal areas. Using Flu-(60-76) peptide, we revealed its penetration in the brain of OBX mice as well as colocalization of Flu-labeled peptide with Aβ in the brain regions in transgenic mice. Flu-(60-76) peptide complex with trimer of Aβ was detected by SDS-PAGE. These data indicate that Aβ can be one of the molecular target of (60-70) peptide. These findings provide a new peptide molecule for design of anti-AD drug and for investigation of RAGE activation ways in progression of AD neurodegeneration.
Keywords: Administration, Intranasal; Animals; Behavior, Animal; Brain; Disease Models, Animal; Male; Maze Learning; Memory Disorders; Mice; Mice, Transgenic; Neurons; Olfactory Bulb; Peptide Fragments; Receptor for Advanced Glycation End Products

Tauopathies: Mechanisms and Therapeutic Strategies. - Tan, Chen-Chen; Zhang, Xiao-Yan; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2018)
Tauopathies are morphologically, biochemically, and clinically heterogeneous neurodegenerative diseases defined by the accumulation of abnormal tau proteins in the brain. There is no effective method to prevent and reverse the tauopathies, but this gloomy picture has been changed by recent research advances. Evidences from genetic studies, experimental animal models, and molecular and cell biology have shed light on the main mechanisms of the diseases. The development of radiology and biochemistry, especially the development of PET imaging, will provide important biomarkers for the clinical diagnosis and treatment. Given the central role of tau in tauopathies, many treatments have constantly emerged, including targeting phosphorylation, targeting aggregation, increasing microtubule stabilization, tau immunization, clearance of tau, anti-inflammatory treatment, and other therapeutics. There is still a long way to go before we obtain drug therapy targeted at multifactor mechanisms.
Keywords: Animals; Biomarkers; Brain; Disease Models, Animal; Humans; Neuroimaging; Phosphorylation; Positron-Emission Tomography; tau Proteins; Tauopathies

Testamentary Capacity Assessment Tool (TCAT): A Brief Instrument for Patients with Dementia. - Papageorgiou, Sokratis G; Voskou, Panagiota; Economou, Alexandra; Beratis, Ion; Douzenis, Athanasios (J Alzheimers Dis, 2018)
BACKGROUND: In current practice, it is common for the medical practitioner to assess a person's testamentary capacity (TC) and give evidence to the Courts about a potential will contest. TC is an advanced cognitive activity that is both situation- and task-specific. OBJECTIVE: The aim of the present study was the development of a brief, specialized instrument for TC assessment in patients with dementia. METHOD: We developed a short tool consisting of four subtests, assessing the person's core functions which are required for TC: memory (orientation, autobiographical memory and realistic perception of beneficiaries), absence of serious psychopathology, knowledge of financial parameters (value of assets, everyday life products, bills), and intention (vignettes, theory of mind). For its validation, we examined 64 outpatients from the Cognitive Disorders/Dementia Unit, 2nd Department of Behavioral Neurology, University of Athens. The decision of the expert served as the gold standard for the evaluation of TC. RESULTS: Of the 64 participants, 39 were judged by the expert as capable of TC and the remaining 25 as incapable. For the total scale (maximum score of 48), the best combination of sensitivity (82.6%) and specificity (100%) was obtained for a cut-off score of 32/33. Cronbach's alpha showed high levels of internal reliability for the scale (α= 0.86) and the point-biserial correlation coefficients showed high levels of criterion-related validity (rbp = 0.797, p < 0.001). CONCLUSION: The new instrument appears to be a reliable screening tool for the evaluation of TC in dementia, which can be used by both the expert and the non-expert. Further research is needed to confirm these promising findings.
Keywords: Adult; Aged; Cognition Disorders; Dementia; Female; Humans; Male; Memory; Mental Competency; Middle Aged; Neuropsychological Tests; Reproducibility of Results; Sensitivity and Specificity; Wills

Treatment of Atrial Fibrillation in Patients with Dementia: A Cohort Study from the Swedish Dementia Registry. - Subic, Ana; Cermakova, Pavla; Religa, Dorota; Han, Shuang; von Euler, Mia; Kåreholt, Ingemar; Johnell, Kristina; Fastbom, Johan; Bognandi, Liselia; Winblad, Bengt; Kramberger, Milica G; Eriksdotter, Maria; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Patients with dementia might have higher risk for hemorrhagic complications with anticoagulant therapy prescribed for atrial fibrillation (AF). OBJECTIVE: This study assesses the risks and benefits of warfarin, antiplatelets, and no treatment in patients with dementia and AF. METHODS: Of 49,792 patients registered in the Swedish Dementia Registry 2007-2014, 8,096 (16%) had a previous diagnosis of AF. Cox proportional hazards models were used to calculate the risk for ischemic stroke (IS), nontraumatic intracranial hemorrhage, any-cause hemorrhage, and death. RESULTS: Out of the 8,096 dementia patients with AF, 2,143 (26%) received warfarin treatment, 2,975 (37%) antiplatelet treatment, and 2,978 (37%) had no antithrombotic treatment at the time of dementia diagnosis. Patients on warfarin had fewer IS than those without treatment (5.2% versus 8.7%; p < 0.001) with no differences compared to antiplatelets. In adjusted analyses, warfarin was associated with a lower risk for IS (HR 0.76, CI 0.59-0.98), while antiplatelets were associated with increased risk (HR 1.25, CI 1.01-1.54) compared to no treatment. For any-cause hemorrhage, there was a higher risk with warfarin (HR 1.28, CI 1.03-1.59) compared to antiplatelets. Warfarin and antiplatelets were associated with a lower risk for death compared to no treatment. CONCLUSIONS: Warfarin treatment in Swedish patients with dementia is associated with lower risk of IS and mortality, and a small increase in any-cause hemorrhage. This study supports the use of warfarin in appropriate cases in patients with dementia. The low percentage of patients on warfarin treatment indicates that further gains in stroke prevention are possible.
Keywords: Aged; Aged, 80 and over; Anticoagulants; Atrial Fibrillation; Dementia; Female; Hemorrhage; Humans; Longitudinal Studies; Male; Registries; Risk Factors; Stroke; Survival Analysis; Sweden; Warfarin

Ubisol-Q10 (a Nanomicellar Water-Soluble Formulation of CoQ10) Treatment Inhibits Alzheimer-Type Behavioral and Pathological Symptoms in a Double Transgenic Mouse (TgAPEswe, PSEN1dE9) Model of Alzheimer's Disease. - Muthukumaran, Krithika; Kanwar, Annie; Vegh, Caleb; Marginean, Alexandra; Elliott, Austin; Guilbeault, Nicholas; Badour, Alexander; Sikorska, Marianna; Cohen, Jerome; Pandey, Siyaram (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is one of the most common neurodegenerative pathologies for which there are no effective therapies to halt disease progression. Given the increase in the incidence of this disorder, there is an urgent need for pharmacological intervention. Unfortunately, recent clinical trials produced disappointing results. Molecular mechanisms of AD are converging on the notion that mitochondrial dysfunction, oxidative stress, and accumulation of dysfunctional proteins are involved in AD pathology. Previously, we have shown that a water-soluble formulation of Coenzyme Q10 (Ubisol-Q10), an integral part of the electron transport chain, stabilizes mitochondria and prevents neuronal cell death caused by neurotoxins or oxidative stress both in vitro and in vivo. In this study, we evaluated the neuroprotective effects of Ubisol-Q10 treatment in double transgenic AD mice. In the present study, we report that providing Ubisol-Q10 in drinking water (at a dose of ∼6 mg/kg/day) reduced circulating amyloid-β (Aβ) peptide, improved long term memory, preserved working spatial memory, and drastically inhibited Aβ plaque formation in 18-month-old transgenic mice compared to an untreated transgenic group. Thus Ubisol-Q10 supplementation has the potential to inhibit the progression of neurodegeneration, leading to a better quality of life for humans suffering with AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Disease Models, Animal; Male; Maze Learning; Memory; Memory Disorders; Mice; Mice, Transgenic; Microglia; Mutation; Nerve Tissue Proteins; Peptide Fragments; Presenilin-1; Ubiquinone; Vitamins

Update on Vascular Cognitive Impairment Associated with Subcortical Small-Vessel Disease. - Wallin, Anders; Román, Gustavo C; Esiri, Margaret; Kettunen, Petronella; Svensson, Johan; Paraskevas, George P; Kapaki, Elisabeth (J Alzheimers Dis, 2018)
Subcortical small-vessel disease (SSVD) is a disorder well characterized from the clinical, imaging, and neuropathological viewpoints. SSVD is considered the most prevalent ischemic brain disorder, increasing in frequency with age. Vascular risk factors include hypertension, diabetes, hyperlipidemia, elevated homocysteine, and obstructive sleep apnea. Ischemic white matter lesions are the hallmark of SSVD; other pathological lesions include arteriolosclerosis, dilatation of perivascular spaces, venous collagenosis, cerebral amyloid angiopathy, microbleeds, microinfarcts, lacunes, and large infarcts. The pathogenesis of SSVD is incompletely understood but includes endothelial changes and blood-brain barrier alterations involving metalloproteinases, vascular endothelial growth factors, angiotensin II, mindin/spondin, and the mammalian target of rapamycin pathway. Metabolic and genetic conditions may also play a role but hitherto there are few conclusive studies. Clinical diagnosis of SSVD includes early executive dysfunction manifested by impaired capacity to use complex information, to formulate strategies, and to exercise self-control. In comparison with Alzheimer's disease (AD), patients with SSVD show less pronounced episodic memory deficits. Brain imaging has advanced substantially the diagnostic tools for SSVD. With the exception of cortical microinfarcts, all other lesions are well visualized with MRI. Diagnostic biomarkers that separate AD from SSVD include reduction of cerebrospinal fluid amyloid-β (Aβ)42 and of the ratio Aβ42/Aβ40 often with increased total tau levels. However, better markers of small-vessel function of intracerebral blood vessels are needed. The treatment of SSVD remains unsatisfactory other than control of vascular risk factors. There is an urgent need of finding targets to slow down and potentially halt the progression of this prevalent, but often unrecognized, disorder.
Keywords: Animals; Cerebrovascular Disorders; Dementia; Humans

Visit-To-Visit Blood Pressure Variability and the Risk of Dementia in Older People. - van Middelaar, Tessa; van Dalen, Jan W; van Gool, Willem A; van den Born, Bert-Jan H; van Vught, Lonneke A; Moll van Charante, Eric P; Richard, Edo (J Alzheimers Dis, 2018)
BACKGROUND: High visit-to-visit variability (VVV) in blood pressure (BP) is associated with cerebrovascular lesions on neuroimaging. OBJECTIVE: Our primary objective was to investigate whether VVV is associated with incident all-cause dementia. As a secondary objective, we studied the association of VVV with cognitive decline and cardiovascular disease (CVD). METHODS: We included community-dwelling people (age 70-78 year) from the 'Prevention of Dementia by Intensive Vascular Care' (preDIVA) trial with three to five 2-yearly BP measurements during 6-8 years follow-up. VVV was defined using coefficient of variation (CV; SD/mean×100). Cognitive decline was assessed using the Mini-Mental State Examination (MMSE). Incident CVD was defined as myocardial infarction or stroke. We used a Cox proportional hazard regression and mixed-effects model adjusted for sociodemographic factors and cardiovascular risk factors. RESULTS: In 2,305 participants (aged 74.2±2.5), mean systolic BP over all available visits was 150.1 mmHg (SD 13.6), yielding a CV of 9.0. After 6.4 years (SD 0.8) follow-up, 110 (4.8%) participants developed dementia and 140 (6.1%) CVD. Higher VVV was not associated with increased risk of dementia (hazard ratio [HR] 1.00 per point CV increase; 95% confidence interval [CI] 0.96-1.05), although the highest quartile of VVV was associated with stronger decline in MMSE (β -0.09, 95% CI -0.17 to -0.01). Higher VVV was associated with incident CVD (HR 1.07; 95% CI 1.04-1.11). CONCLUSION: In our study among older people, high VVV is not associated with incident all-cause dementia. It is associated with decline in MMSE and incident CVD.
Keywords: Aged; Antihypertensive Agents; Blood Pressure; Cardiovascular Diseases; Dementia; Female; Humans; Hypertension; Incidence; Male; Netherlands; Proportional Hazards Models; Risk Factors

Amyloid-β Deposition and Long-Term Progression in Mild Cognitive Impairment due to Alzheimer's Disease Defined with Amyloid PET Imaging. - Hatashita, Shizuo; Wakebe, Daichi (J Alzheimers Dis, 2017)
The aim was to evaluate brain amyloid-β (Aβ) deposition in patients with mild cognitive impairment (MCI) due to Alzheimer's disease (AD) using amyloid PET imaging and clarify the relationship between the annual change in Aβ deposition and disease progression. Forty-eight MCI patients underwent neuropsychological assessment and amyloid PET imaging using [11C]-PIB over a follow-up of 5.7±1.5 years. Thirty-nine MCI patients who had an amyloid-positive scan were defined as MCI due to AD, and 9 MCI patients who had an amyloid-negative scan were included. Regions of interest were defined on co-registered MRI, and the PIB standardized uptake value ratio (SUVR) on the same regions was used over follow-up. Annual change in PIB SUVR was calculated. Patients with MCI due to AD had higher baseline PIB SUVR (1.81±0.32, n = 39, p < 0.01) and a greater annual rate of change in PIB SUVR (0.044±0.027, n = 39, p < 0.01) compared to amyloid-negative MCI patients. Twenty-eight (71.8%) progressed to AD. In patients who progressed during a short duration of 1.7±0.8 years, the annual rate of increase in PIB SUVR was 0.101±0.094 (n = 16, p < 0.05), which was greater compared to patients with long conversion or stable patients. There was a negative correlation between the annual rate of increase in PIB SUVR and duration of progression to AD among individual MCI converters (r = -0.47, n = 28, p < 0.05). The patients defined as MCI due to AD could progress to AD with a shorter period if they have a greater increased annual rate in brain Aβ deposition.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Aniline Compounds; Cognitive Dysfunction; Disease Progression; Female; Follow-Up Studies; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Positron-Emission Tomography; Thiazoles

Cholinesterase Inhibitor Therapy in Alzheimer's Disease: The Limits and Tolerability of Irreversible CNS-Selective Acetylcholinesterase Inhibition in Primates. - Moss, Donald E; Perez, Ruth G; Kobayashi, Haruo (J Alzheimers Dis, 2017)
Irreversible acetylcholinesterase (AChE) inhibition accumulates to high levels in the central nervous system (CNS) because AChE turnover in the brain is much slower than in peripheral tissues. As expected from this CNS selectivity, the irreversible AChE inhibitor methanesulfonyl fluoride (MSF) produces significant cognitive improvement in Alzheimer's disease patients without the gastrointestinal toxicity that plagues other AChE inhibitors. However, without dose-limiting gastrointestinal toxicity, one shortcoming of the prior human studies of MSF is that the upper limits of CNS AChE inhibition that might be tolerated could not be tested. Therefore, in this study, monkeys were treated with escalating intramuscular (IM) doses of MSF that culminated with several weeks of 1.5 mg/kg dosing, more than eight times the prior human clinical dose, still without signs of toxicity. Brain biopsies showed that ∼80% AChE inhibition had been produced and that the new synthesis of cortical AChE had a half-time (t1/2) of ∼12 days. A single IM dose of 1.5 mg/kg MSF produced ∼59% inhibition in cerebrospinal fluid (CSF) AChE as measured one day later. This corresponds to a peak of ∼80% inhibition in CSF AChE at the time of the injection, recovering with a t1/2 of 2.4 days. Computational analyses suggest that MSF at clinically relevant doses could theoretically produce a steady-state AChE inhibition between 65% and 85% in the CNS. These data suggest that the full therapeutic advantage of AChE inhibition therapy can be realized without interference from dose-limiting gastrointestinal toxicity if an irreversible inhibitor is employed.
Keywords: Acetylcholinesterase; Alzheimer Disease; Animals; Brain; Cholinesterase Inhibitors; Dose-Response Relationship, Drug; Drug Evaluation, Preclinical; Erythrocytes; Injections, Intramuscular; Macaca fascicularis; Male; Nootropic Agents; Time Factors

Coordinate-Based Meta-Analysis of the Default Mode and Salience Network for Target Identification in Non-Invasive Brain Stimulation of Alzheimer's Disease and Behavioral Variant Frontotemporal Dementia Networks. - Pievani, Michela; Pini, Lorenzo; Ferrari, Clarissa; Pizzini, Francesca B; Boscolo Galazzo, Ilaria; Cobelli, Chiara; Cotelli, Maria; Manenti, Rosa; Frisoni, Giovanni B (J Alzheimers Dis, 2017)
BACKGROUND: The accurate choice of the site of non-invasive brain stimulation (NIBS) is an important factor in trial design. OBJECTIVE: Based on the observation that Alzheimer's disease (AD) and behavioral frontotemporal dementia (bvFTD) affect specific large-scale networks, i.e., the default mode network (DMN) and the salience network (SN), respectively, we aimed to identify population-average coordinates of these networks that could be used as potential targets in NIBS trials aiming to modulate these circuits. METHODS: A systematic literature search of resting-state functional MRI studies reporting DMN and SN stereotactic coordinates was performed according to PRISMA guidelines. Coordinate-based meta-analyses were conducted to identify consistent nodes of the DMN and SN using GingerALE BrainMap software and the activation likelihood estimation method. RESULTS: DMN coordinates mapped primarily to mesial areas (posterior cingulate cortex/precuneus [Brodmann Area - BA 23/31] and medial prefrontal cortex [BA 9/10/32]). More superficial areas mapped to the bilateral parietal (angular gyrus [BA 39]), temporal (middle gyrus [BA 21]) and dorsolateral prefrontal (superior gyrus [BA 8]) cortex. SN coordinates mapped primarily to mesial and deep frontal areas (anterior insula, anterior cingulate cortex [BA 24/32]), but more superficial areas mapped to the bilateral parietal (supramarginal gyrus [BA 40]) and the right dorsolateral prefrontal (middle gyrus [BA 9/10]) cortex. CONCLUSIONS: NIBS should target the bilateral angular, the middle temporal cortex, or superior frontal gyri in AD for DMN modulation, and the right middle frontal or supramarginal gyri in bvFTD for SN modulation.
Keywords: Alzheimer Disease; Brain; Databases, Bibliographic; Deep Brain Stimulation; Electroencephalography; Frontotemporal Dementia; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Models, Neurological

The Efficacy of Emotion Recognition Rehabilitation for People with Alzheimer's Disease. - García-Casal, J Antonio; Goñi-Imizcoz, Miguel; Perea-Bartolomé, M Victoria; Soto-Pérez, Felipe; Smith, Sarah Jane; Calvo-Simal, Sara; Franco-Martín, Manuel (J Alzheimers Dis, 2017)
BACKGROUND: The ability to recognize emotional expression is essential for social interactions, adapting to the environment, and quality of life. Emotion recognition is impaired in people with Alzheimer's disease (AD), thus rehabilitation of these skills has the potential to elicit significant benefits. OBJECTIVE: This study sought to establish whether emotion recognition capacity could be rehabilitated in people with AD. METHODS: Thirty-six participants with AD were assigned to one of three conditions: an experimental group (EG) that received 20 sessions of rehabilitation of emotion recognition and 20 sessions of cognitive stimulation therapy (CST), a control group (CG) that received 40 sessions of CST, and a treatment as usual group (TAU). RESULTS: A positive treatment effect favoring the EG was found; participants were better able to correctly identify emotions (p = 0.021), made fewer errors of commission (p = 0.002), had greater precision of processing (p = 0.021), and faster processing speed (p = 0.001). Specifically, the EG were better able to identify sadness (p = 0.016), disgust (p = 0.005), and the neutral expression (p = 0.014), with quicker processing speed for disgust (p = 0.002). These gains were maintained at one month follow-up with the exception of processing speed for surprise, which improved. CONCLUSION: Capacity to recognize facial expressions of emotions can be improved through specific rehabilitation in people with AD, and gains are still present at a one month follow up. These findings have implications for the design of rehabilitation techniques for people with AD that may lead to improved quality of life and social interactions for this population.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Therapy; Depression; Emotions; Female; Follow-Up Studies; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Outcome Assessment (Health Care); Recognition (Psychology); Single-Blind Method; Statistics, Nonparametric

Family History of Alzheimer's Disease is Associated with Impaired Perceptual Discrimination of Novel Objects. - Mason, Emily J; Hussey, Erin P; Molitor, Robert J; Ko, Philip C; Donahue, Manus J; Ally, Brandon A (J Alzheimers Dis, 2017)
Early detection may be the key to developing therapies that will combat Alzheimer's disease (AD). It has been consistently demonstrated that one of the main pathologies of AD, tau, is present in the brain decades before a clinical diagnosis. Tau pathology follows a stereotypical route through the medial temporal lobe beginning in the entorhinal and perirhinal cortices. If early pathology leads to very subtle changes in behavior, it may be possible to detect these changes in subjects years before a clinical diagnosis can currently be made. We aimed to discover if cognitively normal middle-aged adults (40-60 years old) at increased risk for AD due to family history would have impaired performance on a cognitive task known to challenge the perirhinal cortex. Using an oddity detection task, we found that subjects with a family history of AD had lowered accuracy without demonstrating differences in rate of acquisition. There were no differences between subjects' medial temporal lobe volume or cortical thickness, indicating that the changes in behavior were not due to significant atrophy. These results demonstrate that subtle changes in perceptual processing are detectable years before a typical diagnosis even when there are no differences detectable in structural imaging data. Anatomically-targeted cognitive testing may be useful in identifying subjects in the earliest stages of AD.
Keywords: Adult; Alzheimer Disease; Cerebral Cortex; Discrimination (Psychology); Family Health; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Perceptual Disorders; Photic Stimulation; Recognition (Psychology); Signal Detection, Psychological

Humanin Specifically Interacts with Amyloid-β Oligomers and Counteracts Their in vivo Toxicity. - Romeo, Margherita; Stravalaci, Matteo; Beeg, Marten; Rossi, Alessandro; Fiordaliso, Fabio; Corbelli, Alessandro; Salmona, Mario; Gobbi, Marco; Cagnotto, Alfredo; Diomede, Luisa (J Alzheimers Dis, 2017)
The 24-residue peptide humanin (HN) has been proposed as a peptide-based inhibitor able to interact directly with amyloid-β (Aβ) oligomers and interfere with the formation and/or biological properties of toxic Aβ species. When administered exogenously, HN, or its synthetic S14G-derivative (HNG), exerted multiple cytoprotective effects, counteracting the Aβ-induced toxicity. Whether these peptides interact directly with Aβ, particularly with the soluble oligomeric assemblies, remains largely unknown. We here investigated the ability of HN and HNG to interact directly with highly aggregating Aβ42, and interfere with the formation and toxicity of its oligomers. Experiments were run in cell-free conditions and in vivo in a transgenic C. elegans strain in which the Aβ toxicity was specifically due to oligomeric species. Thioflavin-T assay indicated that both HN and HNG delay the formation and reduce the final amount of Aβ42 fibrils. In vitro surface plasmon resonance studies indicated that they interact with Aβ42 oligomers favoring the formation of amorphous larger assemblies, observed with turbidity and electron microscopy. In vivo studies indicated that both HN and HNG decrease the relative abundance of A11-positive prefibrillar oligomers as well as OC-positive fibrillar oligomers and had similar protective effects. However, while HN possibly decreased the oligomers by promoting their assembly into larger aggregates, the reduction of oligomers caused by HNG can be ascribed to a marked decrease of the total Aβ levels, likely the consequence of the HNG-induced overexpression of the Aβ-degrading enzyme neprilysin. These findings provide information on the mechanisms underlying the anti-oligomeric effects of HN and HNG and illustrate the role of S14G substitution in regulating the in vivo mechanism of action.
Keywords: Amyloid beta-Peptides; Animals; Animals, Genetically Modified; Caenorhabditis elegans; Caenorhabditis elegans Proteins; Circular Dichroism; Disease Models, Animal; Dose-Response Relationship, Drug; Gene Expression Regulation; Humans; Intracellular Signaling Peptides and Proteins; Microscopy, Atomic Force; Microscopy, Electron, Transmission; Neprilysin; Paralysis; Peptide Fragments; Surface Plasmon Resonance

Information and Communication Technologies for the Activities of Daily Living in Older Patients with Dementia: A Systematic Review. - D'Onofrio, Grazia; Sancarlo, Daniele; Ricciardi, Francesco; Panza, Francesco; Seripa, Davide; Cavallo, Filippo; Giuliani, Francesco; Greco, Antonio (J Alzheimers Dis, 2017)
BACKGROUND: Significant innovations have been introduced in recent years in the application of information and communication technologies (ICTs) to support healthcare for patients with dementia. OBJECTIVE: In the present systematic review, our goal is to keep track of ICT concepts and approaches to support the range of activities of daily living for people with dementia and to provide a snapshot of the effect that technology is having on patients' self-reliance. METHODS: We reviewed the literature and identified systematic reviews of cohort studies and other authoritative reports. Our selection criteria included: (1) activities of daily living, (2) ICT, and (3) dementia. RESULTS: We identified 56 studies published between 2000 and 2015, of which 26 met inclusion criteria. The present systematic review revealed many ICT systems that could purportedly support the range of activities of daily living for patients with dementia. The results showed five research bodies: 1) technologies used by patients with dementia, 2) technologies used by caregivers, 3) monitoring systems, 4) ambient assistive living with ICTs, and 5) tracking and wayfinding. CONCLUSIONS: There is a potential for ICTs to support dementia care at home and to improve quality of life for caregivers, reducing healthcare costs and premature institutional care for these patients.
Keywords: Activities of Daily Living; Aging; Databases, Bibliographic; Dementia; Humans; Medical Informatics; Self-Help Devices

Modeling the Relationships Among Late-Life Body Mass Index, Cerebrovascular Disease, and Alzheimer's Disease Neuropathology in an Autopsy Sample of 1,421 Subjects from the National Alzheimer's Coordinating Center Data Set. - Alosco, Michael L; Duskin, Jonathan; Besser, Lilah M; Martin, Brett; Chaisson, Christine E; Gunstad, John; Kowall, Neil W; McKee, Ann C; Stern, Robert A; Tripodis, Yorghos (J Alzheimers Dis, 2017)
The relationship between late-life body mass index (BMI) and Alzheimer's disease (AD) is poorly understood due to the lack of research in samples with autopsy-confirmed AD neuropathology (ADNP). The role of cerebrovascular disease (CVD) in the interplay between late-life BMI and ADNP is unclear. We conducted a retrospective longitudinal investigation and used joint modeling of linear mixed effects to investigate causal relationships among repeated antemortem BMI measurements, CVD (quantified neuropathologically), and ADNP in an autopsy sample of subjects across the AD clinical continuum. The sample included 1,421 subjects from the National Alzheimer's Coordinating Center's Uniform Data Set and Neuropathology Data Set with diagnoses of normal cognition (NC; n = 234), mild cognitive impairment (MCI; n = 201), or AD dementia (n = 986). ADNP was defined as moderate to frequent neuritic plaques and Braak stageIII-VI. Ischemic Injury Scale (IIS) operationalized CVD. Joint modeling examined relationships among BMI, IIS, and ADNP in the overall sample and stratified by initial visit Clinical Dementia Rating score. Subject-specific random intercept for BMI was the predictor for ADNP due to minimal BMI change (p = 0.3028). Analyses controlling for demographic variables and APOE ɛ4 showed lower late-life BMI predicted increased odds of ADNP in the overall sample (p < 0.001), and in subjects with CDR of 0 (p = 0.0021) and 0.5 (p = 0.0012), but not ≥1.0 (p = 0.2012). Although higher IIS predicted greater odds of ADNP (p < 0.0001), BMI did not predict IIS (p = 0.2814). The current findings confirm lower late-life BMI confers increased odds for ADNP. Lower late-life BMI may be a preclinical indicator of underlying ADNP.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Autopsy; Body Mass Index; Cerebrovascular Disorders; Datasets as Topic; Female; Humans; Male; National Institute on Aging (U.S.); Neuropathology; Neuropsychological Tests; Retrospective Studies; United States

Modulating the Balance of Synaptic and Extrasynaptic NMDA Receptors Shows Positive Effects against Amyloid-β-Induced Neurotoxicity. - Huang, Yan; Shen, Wei; Su, Jie; Cheng, Bin; Li, Dong; Liu, Gang; Zhou, Wen-Xia; Zhang, Yong-Xiang (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) patients suffer a disturbance in the balance between synaptic (GluN2A, mediating the protective pathway) and extrasynaptic NMDA receptors (NMDARs) (GluN2B, mediating the excitotoxic pathway), and, therefore, restoring the balance of GluN2A and GluN2B should be beneficial for AD. In this study, the GluN2B-selective antagonist, ifenprodil, and the non-selective NMDAR agonist, NMDA, had little effect on amyloid-β (Aβ)-induced long-term potentiation deficits. Enhancing the activity of GluN2A had a protective effect against Aβ, and specific activation of GluN2A and inhibition of GluN2B showed a better protective effect. In Aβ ICV-injected animals, the combination of ifenprodil and D-cycloserine (a co-activator of NMDRs similar to D-serine) led to greater improvement in behavior tests (nest building, novel object recognition, and Morris water maze) than ifenprodil (Morris water maze) or D-cycloserine (nest building) alone. Signal pathway analysis showed that Aβ disturbed the GluN2A/GluN2B-related pathway. The ratio of GluN2A to GluN2B decreased in Aβ-treated animals, and TORC dephosphorylation and ERK1/2 activation, which could be initiated by GluN2A, also decreased in the hippocampal tissues of Aβ-treated animals. As a result, the activation of CREB and the content of brain-derived BDNF decreased. The combination of ifenprodil and D-cycloserine reversed the signal pathway more significantly than ifenprodil or D-cycloserine alone, indicating that Aβ-induced toxicology was mediated both by functionally inhibiting GluN2A and enhancing GluN2B. These results indicate that enhancing synaptic NMDARs and inhibiting extrasynaptic NMDARs concurrently showed protective effects against Aβ-induced neurotoxicity, suggesting that modulation of the balance between GluN2A and GluN2B could be a potential strategy for AD drug development and therapy.
Keywords: Amyloid beta-Peptides; Animals; Antimetabolites; Cycloserine; Disease Models, Animal; Excitatory Amino Acid Antagonists; Excitatory Postsynaptic Potentials; Hippocampus; Locomotion; Male; Maze Learning; N-Methylaspartate; Nesting Behavior; Neurotoxicity Syndromes; Peptide Fragments; Piperidines; Rats; Rats, Wistar; Receptors, N-Methyl-D-Aspartate; Recognition (Psychology); Signal Transduction; Synapses

Palmitate Increases β-site AβPP-Cleavage Enzyme 1 Activity and Amyloid-β Genesis by Evoking Endoplasmic Reticulum Stress and Subsequent C/EBP Homologous Protein Activation. - Marwarha, Gurdeep; Rostad, Stephen; Lilek, Jaclyn; Kleinjan, Mason; Schommer, Jared; Ghribi, Othman (J Alzheimers Dis, 2017)
Epidemiological studies implicate diets rich in saturated free fatty acids (sFFA) as a potential risk factor for developing Alzheimer's disease (AD). In particular, high plasma levels of the sFFA palmitic acid (palmitate) were shown to inversely correlate with cognitive function. However, the cellular mechanisms by which sFFA may increase the risk for AD are not well known. Endoplasmic reticulum (ER) stress has emerged as one of the signaling pathways initiating and fostering the neurodegenerative changes in AD by increasing the aspartyl protease β-site AβPP cleaving enzyme 1 (BACE1) and amyloid-β (Aβ) genesis. In this study, we determined the extent to which palmitate increases BACE1 and Aβ levels in vitro and in vivo as well as the potential role of ER stress as cellular mechanism underlying palmitate effects. We demonstrate, in palmitate-treated SH-SY5Y neuroblastoma cells and in the hippocampi of palmitate-enriched diet-fed mice, that palmitate evokes the activation of the C/EBP Homologous Protein (CHOP), a transcription factor that is specifically responsive to ER stress. Induction of CHOP expression is associated with increased BACE1 mRNA, protein and activity levels, and subsequent enhanced amyloidogenic processing of amyloid-β protein precursor (AβPP) that culminates in a substantial increase in Aβ genesis. We further show that CHOP is an indispensable molecular mediator of palmitate-induced upregulation in BACE1 activity and Aβ genesis. Indeed, we show that Chop-/- mice and CHOP knocked-down SH-SY5Y neuroblastoma cells do not exhibit the same commensurate degree of palmitate-induced increase in BACE1 expression levels and Aβ genesis.
Keywords: Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Aspartic Acid Endopeptidases; Cell Line, Tumor; Dose-Response Relationship, Drug; Endoplasmic Reticulum Stress; Gene Expression Regulation; Hippocampus; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Neuroblastoma; Palmitates; RNA, Messenger; Signal Transduction; Transcription Factor CHOP; Transcription Factors; Transfection

PCSK9 Promotes oxLDL-Induced PC12 Cell Apoptosis Through the Bcl-2/Bax-Caspase 9/3 Signaling Pathway. - Liu, Lu-Shan; Bai, Xue-Qin; Gao, Ya; Wu, Qi; Ren, Zhong; Li, Qing; Pan, Li-Hong; He, Ni-Ya; Peng, Juan; Tang, Zhi-Han (J Alzheimers Dis, 2017)
BACKGROUND: Hyperlipidemia is a risk factor for neurodegenerative diseases. Proprotein convertase subtilisin / Kexin type 9 (PCSK9) degrades hepatic low-density lipoprotein receptor (LDLR) to regulate lipid metabolism. It is unclear if PCSK9 plays a role in neurodegenerative diseases. OBJECTIVE: This study was designed to determine whether PCSK9 is crucial between hyperlipidemia and Alzheimer's disease. The interrelationship between PCSK9 and neuronal apoptosis was explored in PC12 cells in response to treatment with oxidized low-density lipoprotein (oxLDL). METHODS: Cultured PC12 cells were serum-starved and incubated with different concentrations of oxLDL for 24 h. Intracytoplasmic lipid droplets were observed by oil red O staining. Morphological assessment of apoptotic cells was performed using Hoechst 33258 staining and flow cytometry analysis. The expression of mRNA and protein was detected by reverse-transcription polymerase chain reaction (RT-PCR) and western blot analyses, respectively. Transfection of small interfering RNA (siRNA) into PC12 cells was conducted using HiperFect Transfection Reagent. Concentrations of Aβ40 and Aβ42 were detected by enzyme-linked immunosorbent assay (ELISA) kit. RESULTS: Intracellular lipid content, the number of apoptotic cells, and PCSK9 expression were increased in PC12 cells after oxLDL treatment. Transfection with PCSK9 siRNA reduced the oxLDL-induced apoptosis of PC12 cells. We further confirmed the involvement of Bcl-2/Bax-Caspase (9, 3) signaling pathway in the regulation of PC12 cells apoptosis.β-Secretase 1, another target gene of PCSK9, was downregulated in PC12 cells in response to oxLDL treatment. Aβ40 and Aβ42 contents were also decreased. CONCLUSION: PCSK9 promotes oxLDL-induced PC12 cell apoptosis through the Bcl-2/Bax-Caspase 9/3 signaling pathway.
Keywords: Amyloid beta-Peptides; Analysis of Variance; Animals; Apoptosis; bcl-2-Associated X Protein; Caspases; Culture Media, Serum-Free; Dose-Response Relationship, Drug; Flow Cytometry; Lipid Metabolism; Lipoproteins, LDL; PC12 Cells; Peptide Fragments; Proprotein Convertase 9; Proto-Oncogene Proteins c-bcl-2; Rats; RNA, Messenger; RNA, Small Interfering; Signal Transduction; Transfection

The Progression of Alzheimer's Disease: Are Fast Decliners Really Fast? A Four-Year Follow-Up. - Barocco, Federica; Spallazzi, Marco; Concari, Letizia; Gardini, Simona; Pelosi, Annalisa; Caffarra, Paolo (J Alzheimers Dis, 2017)
BACKGROUND: The rate of cognitive and functional decline in Alzheimer's disease (AD) changes across individuals. OBJECTIVES: Our purpose was to assess whether the concept of "fast decline" really fits its definition and whether cognitive and functional variables at onset can predict the progression of AD. METHODS: 324 AD patients were included. We retrospectively examined their Mini-Mental State Examination (MMSE) total score and sub-items, Activities of Daily Living (ADL), and Instrumental Activities of Daily Living (IADL) at baseline and every six months for a 4-year follow-up. Patients were divided into "fast decliners" (n = 62), defined by a loss ≥5 points on the MMSE score within the first year from the baseline; "intermediate decliners" (n = 37), by a loss ≥5 points after the first year and before the 18th month; or "slow decliners" (n = 225), composed of the remaining patients. RESULTS: At baseline, the groups did not differ on demographic, clinical, and cognitive variables. The decline at the end of the 4-year follow-up period seems to be similar among the different decline clusters. Predictors of disease progression have not been identified; only the MMSE total score at 12 months <14/30 was indicative of a poor prognosis. CONCLUSIONS: Even with the limitation due to the small sample size, the lack of differences in the disease progression in time in the different clusters suggest the inconsistency of the so-called "fast decliners". This study was unable to show any significant difference among clusters of AD progression within a 4-year time interval. Further studies should better clarify whether a more consistent distinction exists between slow and fast decliners.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Cognition Disorders; Disease Progression; Female; Humans; Longitudinal Studies; Male; Psychiatric Status Rating Scales; ROC Curve; Time Factors

Role of Suppressor of Cytokine Signaling 3 (SOCS3) in Altering Activated Microglia Phenotype in APPswe/PS1dE9 Mice. - Iwahara, Naotoshi; Hisahara, Shin; Kawamata, Jun; Matsumura, Akihiro; Yokokawa, Kazuki; Saito, Taro; Fujikura, Mai; Manabe, Tatsuo; Suzuki, Hiromi; Matsushita, Takashi; Suzuki, Syuuichirou; Shimohama, Shun (J Alzheimers Dis, 2017)
In response to changes of the central nervous system environment, microglia are capable of acquiring diverse phenotypes for cytotoxic or immune regulation and resolution of injury. Alzheimer's disease (AD) pathology also induces several microglial activations, resulting in production of pro-inflammatory cytokines and reactive oxygen species or clearance of amyloid-β (Aβ) through phagocytosis. We previously demonstrated that microglial activation and increase in oxidative stress started from the middle age in APPswe/PS1dE9 mice, and hypothesized that M1 activation occurs in middle-aged AD mice by Aβ stimulation. In the present study, we analyzed in vivo expressions of pro-inflammatory cytokines (M1 microglial markers), M2 microglial markers, and suppressor of cytokine signaling (SOCS) family, and examined the microglial phenotypic profile in APPswe/PS1dE9 mice. Then we compared the in vitro gene expression patterns of Aβ- and lipopolysaccharide (LPS)-stimulated primary-cultured microglia. Microglia in APPswe/PS1dE9 mice exhibited an M1-like phenotype, expressing tumor necrosis factor α (TNFα) but not interleukin 6 (IL6). Aβ-stimulated primary-cultured microglia also expressed TNFα but not IL6, whereas LPS-stimulated primary-cultured microglia expressed both pro-inflammatory cytokines. Furthermore, both microglia in APPswe/PS1dE9 mice and Aβ-stimulated primary-cultured microglia expressed SOCS3. Reduction of SOCS3 expression in Aβ-challenged primary-cultured microglia resulted in upregulation of IL6 expression. Our findings indicate that SOCS3 suppresses complete polarization to M1 phenotype through blocking IL6 production, and Aβ-challenged primary-cultured microglia replicate the in vivo gene expression pattern of microglia in APPswe/PS1dE9 mice. Aβ may induce the M1-like phenotype through blocking of IL6 by SOCS3.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Brain; Cells, Cultured; Disease Models, Animal; Female; Humans; Interleukin-6; Lipopolysaccharides; Male; Mice, Inbred C57BL; Mice, Transgenic; Microglia; Neurons; Presenilin-1; Suppressor of Cytokine Signaling 3 Protein; Tumor Necrosis Factor-alpha

Triceps and Subscapular Skinfold in Men Aged 40-65 and Dementia Prevalence 36 Years Later. - Ravona-Springer, Ramit; Schnaider-Beeri, Michal; Goldbourt, Uri (J Alzheimers Dis, 2017)
BACKGROUND: The relationship of obesity with risk for dementia is complex and may change with age. OBJECTIVE: To analyze the relationship between measures of obesity at age 40-65 and dementia prevalence in survivors 36 years later. METHODS: Obesity-related measures of triceps and subscapular skinfold thickness were assessed in 1963 in n = 9,760 men aged 40-65 participating in the Israel Ischemic Heart Disease study. Cognitive evaluation and assessment of dementia prevalence were performed in n = 1,643 participants of the original cohort who survived until 1999/2000 (age ≥76 years) and had anthropometric measures in 1963. RESULTS: Age-adjusted prevalence of dementia in survivors in 1999/2000 by baseline triceps skinfold quintile was 20.5%, 21.2%, 17.6%, 15.6%, and 14.5%, respectively, from lowest to highest (p = 0.006 in trend test). Using logistic regression, a 6-mm increment of triceps skinfold was associated with an age and BMI-adjusted odds ratio of 0.81 (95% CI, 0.70-0.94) for dementia prevalence among survivors. Age-adjusted risk for dementia by subscapular skinfold quintile demonstrated 20.5%, 17.1%, 15.7%, 19.4%, and 18.1%, respectively, in groups of subjects by subscapular skinfold quintile from lowest to highest (p = 0.6 in trend test). CONCLUSIONS: Lower triceps skinfold at age 40-65, reflecting diminished peripheral fat, was associated with higher dementia prevalence in late life, potentially suggesting a protective role of peripheral fat to brain health.
Keywords: Adipose Tissue; Aged; Anthropometry; Arm; Body Mass Index; Dementia; Exercise; Humans; Israel; Leisure Activities; Longitudinal Studies; Male; Middle Aged; Muscle, Skeletal; Obesity; Odds Ratio; Prevalence; Shoulder; Skinfold Thickness; Social Class

What is the Relationship of Traumatic Brain Injury to Dementia? - Mendez, Mario F (J Alzheimers Dis, 2017)
There is a long history linking traumatic brain injury (TBI) with the development of dementia. Despite significant reservations, such as recall bias or concluding causality for TBI, a summary of recent research points to several conclusions on the TBI-dementia relationship. 1) Increasing severity of a single moderate-to-severe TBI increases the risk of subsequent Alzheimer's disease (AD), the most common type of dementia. 2) Repetitive, often subconcussive, mild TBIs increases the risk for chronic traumatic encephalopathy (CTE), a degenerative neuropathology. 3) TBI may be a risk factor for other neurodegenerative disorders that can be associated with dementia. 4) TBI appears to lower the age of onset of TBI-related neurocognitive syndromes, potentially adding "TBI cognitive-behavioral features". The literature further indicates several specific risk factors for TBI-associated dementia: 5) any blast or blunt physical force to the head as long as there is violent head displacement; 6) decreased cognitive and/or neuronal reserve and the related variable of older age at TBI; and 7) the presence of apolipoprotein E ɛ4 alleles, a genetic risk factor for AD. Finally, there are neuropathological features relating TBI with neurocognitive syndromes: 8) acute TBI results in amyloid pathology and other neurodegenerative proteinopathies; 9) CTE shares features with neurodegenerative dementias; and 10) TBI results in white matter tract and neural network disruptions. Although further research is needed, these ten findings suggest that dose-dependent effects of violent head displacement in vulnerable brains predispose to dementia; among several potential mechanisms is the propagation of abnormal proteins along damaged white matter networks.
Keywords: Apolipoprotein E4; Brain; Brain Injuries, Traumatic; Databases, Bibliographic; Dementia; Disease Progression; Humans; Neurodegenerative Diseases; Risk Factors

Accurate Prediction of Conversion to Alzheimer's Disease using Imaging, Genetic, and Neuropsychological Biomarkers. - Dukart, Juergen; Sambataro, Fabio; Bertolino, Alessandro (J Alzheimers Dis, 2016)
A variety of imaging, neuropsychological, and genetic biomarkers have been suggested as potential biomarkers for the identification of mild cognitive impairment (MCI) in patients who later develop Alzheimer's disease (AD). Here, we systematically evaluated the most promising combinations of these biomarkers regarding discrimination between stable and converter MCI and reflection of disease staging. Alzheimer's Disease Neuroimaging Initiative data of AD (n = 144), controls (n = 112), stable (n = 265) and converter (n = 177) MCI, for which apolipoprotein E status, neuropsychological evaluation, and structural, glucose, and amyloid imaging were available, were included in this study. Naïve Bayes classifiers were built on AD and controls data for all possible combinations of these biomarkers, with and without stratification by amyloid status. All classifiers were then applied to the MCI cohorts. We obtained an accuracy of 76% for discrimination between converter and stable MCI with glucose positron emission tomography as a single biomarker. This accuracy increased to about 87% when including further imaging modalities and genetic information. We also identified several biomarker combinations as strong predictors of time to conversion. Use of amyloid validated training data resulted in increased sensitivities and decreased specificities for differentiation between stable and converter MCI when amyloid was included as a biomarker but not for other classifier combinations. Our results indicate that fully independent classifiers built only on AD and controls data and combining imaging, genetic, and/or neuropsychological biomarkers can more reliably discriminate between stable and converter MCI than single modality classifiers. Several biomarker combinations are identified as strongly predictive for the time to conversion to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoproteins E; Area Under Curve; Brain; Cognitive Dysfunction; Disease Progression; Female; Fluorodeoxyglucose F18; Follow-Up Studies; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Prognosis; Radiopharmaceuticals; ROC Curve; Sensitivity and Specificity

Activation of p53 in Down Syndrome and in the Ts65Dn Mouse Brain is Associated with a Pro-Apoptotic Phenotype. - Tramutola, Antonella; Pupo, Gilda; Di Domenico, Fabio; Barone, Eugenio; Arena, Andrea; Lanzillotta, Chiara; Broekaart, Diede; Blarzino, Carla; Head, Elizabeth; Butterfield, D Allan; Perluigi, Marzia (J Alzheimers Dis, 2016)
Down syndrome (DS) is the most common genetic cause of intellectual disability, resulting from trisomy of chromosome 21. The main feature of DS neuropathology includes early onset of Alzheimer's disease (AD), with deposition of senile plaques and tangles. We hypothesized that apoptosis may be activated in the presence of AD neuropathology in DS, thus we measured proteins associated with upstream and downstream pathways of p53 in the frontal cortex from DS cases with and without AD pathology and from Ts65Dn mice, at different ages. We observed increased acetylation and phosphorylation of p53, coupled to reduced MDM2/p53 complex level and lower levels of SIRT1. Activation of p53 was associated with a number of targets (BAX, PARP1, caspase-3, p21, heat shock proteins, and PGC1α) that were modulated in both DS and DS/AD compared with age-matched controls. In particular, the most relevant changes (increased p-p53 and acetyl-p53 and reduced formation of MDM2/p53 complex) were found to be modified only in the presence of AD pathology in DS. In addition, a similar pattern of alterations in the p53 pathway was found in Ts65Dn mice. These results suggest that p53 may integrate different signals, which can result in a pro-apoptotic-phenotype contributing to AD neuropathology in people with DS.
Keywords: Acetylation; Alzheimer Disease; Animals; Apoptosis; Blotting, Western; Disease Models, Animal; Down Syndrome; Female; Frontal Lobe; Humans; Immunoprecipitation; Male; Mice, Inbred C3H; Mice, Inbred C57BL; Mice, Transgenic; Middle Aged; Phenotype; Phosphorylation; Tumor Suppressor Protein p53; Young Adult

Activities of Daily Living and Depressive Symptoms in Patients with Subjective Cognitive Decline, Mild Cognitive Impairment, and Alzheimer's Disease. - Stogmann, Elisabeth; Moser, Doris; Klug, Stefanie; Gleiss, Andreas; Auff, Eduard; Dal-Bianco, Peter; Pusswald, Gisela; Lehrner, Johann (J Alzheimers Dis, 2016)
BACKGROUND: Subjective cognitive decline (SCD) may be an early indicator for an increased risk of dementia. The exact definition of SCD remains unclear and has recently become a major research interest. OBJECTIVES: To determine impairments in activities of daily living (ADL) and depressive symptoms in elderly individuals with SCD, mild cognitive impairment (MCI), and Alzheimer's disease (AD). METHODS: We included 752 consecutive patients suffering from SCD, non-amnestic (naMCI) or amnestic MCI (aMCI), AD, and 343 healthy controls into this prospective cohort study. A neuropsychological test battery, B-ADL and BDI-II was performed. RESULTS: SCD patients showed a decreased performance in ADL compared to controls. Performance in ADL declined concurrently with cognitive abilities along the controls-SCD-naMCI-aMCI-AD continuum. Individuals with cognitive complains, no matter if SCD, MCI, or AD patients, reported more often depressive symptoms compared to healthy controls without complaints. Within all five cognitive subgroups, patients with depressive symptoms reported more difficulties in ADL in comparison to patients without depressive symptoms. Adjusting for depressive symptoms, there was no significant group difference between the control versus the SCD group (OR 1.1, CI 0.6-1.7). CONCLUSIONS: SCD is a heterogeneous clinical condition. Specific features such as slightly impaired ADL and depressive symptoms are associated with SCD. Clinical markers may serve as an indicator for preclinical AD and in combination with biomarkers guide to an early diagnosis of a progressive neurodegenerative disease.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Cognitive Dysfunction; Depression; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Odds Ratio; Perception; Prospective Studies

Age-Dependent Regulation of the Blood-Brain Barrier Influx/Efflux Equilibrium of Amyloid-β Peptide in a Mouse Model of Alzheimer's Disease (3xTg-AD). - Do, Tuan Minh; Dodacki, Agnès; Alata, Wael; Calon, Frederic; Nicolic, Sophie; Scherrmann, Jean-Michel; Farinotti, Robert; Bourasset, Fanchon (J Alzheimers Dis, 2016)
The involvement of transporters located at the blood-brain barrier (BBB) has been suggested in the control of cerebral Aβ levels, and thereby in Alzheimer's disease (AD). However, little is known about the regulation of these transporters at the BBB in animal models of AD. In this study, we investigated the BBB expression of Aβ influx (Rage) and efflux (Abcb1-Abcg2-Abcg4-Lrp-1) transporters and cholesterol transporter (Abca1) in 3-18-month-old 3xTg-AD and control mice. The age-dependent effect of BBB transporters regulation on the brain uptake clearance (Clup) of [3H]cholesterol and [3H]Aβ1 - 40 was then evaluated in these mice, using the in situ brain perfusion technique. Our data suggest that transgenes expression led to the BBB increase in Aβ influx receptor (Rage) and decrease in efflux receptor (Lrp-1). Our data also indicate that mice have mechanisms counteracting this increased net influx. Indeed, Abcg4 and Abca1 are up regulated in 3- and 3/6-month-old 3xTg-AD mice, respectively. Our data show that the balance between the BBB influx and efflux of Aβ is maintained in 3 and 6-month-old 3xTg-AD mice, suggesting that Abcg4 and Abca1 control the efflux of Aβ through the BBB by a direct (Abcg4) or indirect (Abca1) mechanism. At 18 months, the BBB Aβ efflux is significantly increased in 3xTg-AD mice compared to controls. This could result from the significant up-regulation of both Abcg2 and Abcb1 in 3xTg-AD mice compared to control mice. Thus, age-dependent regulation of several Aβ and cholesterol transporters at the BBB could ultimately limit the brain accumulation of Aβ.
Keywords: Aging; Alzheimer Disease; Amyloid beta-Peptides; Animals; ATP Binding Cassette Transporter, Sub-Family G, Member 1; ATP Binding Cassette Transporter, Sub-Family G, Member 2; ATP-Binding Cassette Transporters; Biological Transport; Blood-Brain Barrier; Brain; Carbon Isotopes; Cholesterol; Disease Models, Animal; Humans; Lipoproteins; Mice; Mice, Transgenic; P-Glycoproteins; Peptide Fragments; Receptors, LDL; Sucrose; Tritium; Tumor Suppressor Proteins

Aging as a Precipitating Factor in Chronic Restraint Stress-Induced Tau Aggregation Pathology, and the Protective Effects of Rosmarinic Acid. - Shan, Ye; Wang, Dan-Dan; Xu, Yu-Xia; Wang, Chu; Cao, Lan; Liu, Yun-Sheng; Zhu, Cui-Qing (J Alzheimers Dis, 2016)
Stress is an important risk factor of Alzheimer's disease (AD). It has been evidenced that stress could induce tau phosphorylation and increase tau insolubility in brain; however, little is known about the interactional effect of stress with aging on tauopathy. Therefore, we explored the effects of aging on stress-induced tauopathy and the potential mechanism in mouse model of chronic restraint stress (CRS). Here we found that in general, the level of phosphorylated tau (P-tau) was higher in brain of middle-aged mice than that in adult mice under physiological conditions. CRS-induced tau phosphorylation and its insolubility were more prominent in middle-aged mice. The increase of AT8-labeled insoluble P-tau was dramatic in middle-aged mice, which was highly ubiquitinated but did not form PHF structures. The levels of chaperones were relatively lower in middle-aged mice brain; CRS further reduced the expression, especially for HDJ2/HSP40. CRS also suppressed the expression of Pin1, the peptidylprolyl cis/trans isomerase, in middle-aged mice but not in adult mice. Downregulation of HSP40 or Pin1 caused an increase of transfected extraneous tau in 293 cells. Rosmarinic acid (RA) could effectively suppress the elevation of P-tau and insoluble P-tau formation induced by CRS, and reversed the abnormal changes of chaperones and Pin1 particularly in middle-aged mice. Taken together, our findings provided evidence that aging could be a promoting factor in stress-induced tauopathy, which was relevant with malregulation of chaperones and Pin1, and RA might be a promising beneficial agent for stress-induced tauopathy.
Keywords: Aging; Animals; Antioxidants; Brain; Cinnamates; Corticotropin-Releasing Hormone; Depsides; Disease Models, Animal; HEK293 Cells; HSP90 Heat-Shock Proteins; Humans; Male; Mice; Mice, Inbred C57BL; Microscopy, Immunoelectron; NIMA-Interacting Peptidylprolyl Isomerase; Peptidylprolyl Isomerase; Phosphorylation; Precipitating Factors; Receptors, Corticotropin; Restraint, Physical; Stress, Psychological; tau Proteins; Transfection

Analysis of the MIRIAD Data Shows Sex Differences in Hippocampal Atrophy Progression. - Ardekani, Babak A; Convit, Antonio; Bachman, Alvin H (J Alzheimers Dis, 2016)
BACKGROUND: Hippocampus (HC) atrophy is a hallmark of early Alzheimer's disease (AD). Atrophy rates can be measured by high-resolution structural MRI. Longitudinal studies have previously shown sex differences in the progression of functional and cognitive deficits and rates of brain atrophy in early AD dementia. It is important to corroborate these findings on independent datasets. OBJECTIVE: To study temporal rates of HC atrophy over a one-year period in probable AD patients and cognitively normal (CN) subjects by longitudinal MRI scans obtained from the Minimal Interval Resonance Imaging in AD (MIRIAD) database. METHODS: We used a novel algorithm to compute an index of hippocampal (volumetric) integrity (HI) at baseline and one-year follow-up in 43 mild-moderate probable AD patients and 22 CN subjects in MIRIAD. The diagnostic power of longitudinal HI measurement was assessed using a support vector machines (SVM) classifier. RESULTS: The HI was significantly reduced in the AD group (p <  10(-20)). In addition, the annualized percentage rate of reduction in HI was significantly greater in the AD group (p <  10(-13)). Within the AD group, the annual reduction of HI in women was significantly greater than in men (p = 0.008). The accuracy of SVM classification between AD and CN subjects was estimated to be 97% by 10-fold cross-validation. CONCLUSION: In the MIRIAD patients with probable AD, the HC atrophies at a significantly faster rate in women as compared to men. Female sex is a risk factor for faster descent into AD. The HI measure has potential for AD diagnosis, as a biomarker of AD progression and a therapeutic target in clinical trials.
Keywords: Alzheimer Disease; Atrophy; Disease Progression; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Longitudinal Studies; Magnetic Resonance Imaging; Male

Anthocyanins Protect SK-N-SH Cells Against Acrolein-Induced Toxicity by Preserving the Cellular Redox State. - Belkacemi, Abdenour; Ramassamy, Charles (J Alzheimers Dis, 2016)
In Alzheimer's disease (AD) and in mild cognitive impairment (MCI) patients, by-products of lipid peroxidation such as acrolein accumulated in vulnerable regions of the brain. We have previously shown that acrolein is a highly reactive and neurotoxic aldehyde and its toxicity involves the alteration of several redox-sensitive pathways. Recently, protein-conjugated acrolein in cerebrospinal fluid has been proposed as a biomarker to distinguish between MCI and AD. With growing evidence of the early involvement of oxidative stress in AD etiology, one would expect that a successful therapy should prevent brain oxidative damage. In this regard, several studies have demonstrated that polyphenol-rich extracts exert beneficial effect on cognitive impairment and oxidative stress. We have recently demonstrated the efficacy of an anthocyanin formulation (MAF14001) against amyloid-β-induced oxidative stress. The aim of this study is to investigate the neuroprotective effect of MAF14001 as a mixture of anthocyanins, a particular class of polyphenols, against acrolein-induced oxidative damage in SK-N-SH neuronal cells. Our results demonstrated that MAF14001, from 5μM, was able to efficiently protect SK-N-SH cells against acrolein-induced cell death. MAF14001 was able to lower reactive oxygen species and protein carbonyl levels induced by acrolein. Moreover, MAF1401 prevented glutathione depletion and positively modulated, in the presence of acrolein, some oxidative stress-sensitive pathways including the transcription factors NF-κB and Nrf2, the proteins γ-GCS and GSK3β, and the protein adaptator p66Shc. Along with its proven protective effect against amyloid-β toxicity, these results demonstrate that MAF14001 could target multiple mechanisms and could be a promising agent for AD prevention.
Keywords: Acrolein; Anthocyanins; Antioxidants; Cell Death; Cell Line, Tumor; Dose-Response Relationship, Drug; Glutathione; Humans; Neuroprotective Agents; NF-kappa B; Oxidation-Reduction; Oxidative Stress; Reactive Oxygen Species; Src Homology 2 Domain-Containing, Transforming Protein 1

Anti-Correlated Cerebrospinal Fluid Biomarker Trajectories in Preclinical Alzheimer's Disease. - Gomar, Jesus J; Conejero-Goldberg, Concepcion; Davies, Peter; Goldberg, Terry E (J Alzheimers Dis, 2016)
BACKGROUND: The earliest stage of preclinical Alzheimer's disease (AD) is defined by low levels of cerebrospinal fluid (CSF) amyloid-β (Aβ42). However, covariance in longitudinal dynamic change of Aβ42 and tau in incipient preclinical AD is poorly understood. OBJECTIVE: To examine dynamic interrelationships between Aβ42 and tau in preclinical AD. METHODS: We followed 47 cognitively intact participants (CI) with available CSF data over four years in ADNI. Based on longitudinal Aβ42 levels in CSF, CI were classified into three groups: 1) Aβ42 stable with normal levels of Aβ42 over time (n = 15); 2) Aβ42 declining with normal Aβ42 levels at baseline but showing decline over time (n = 14); and 3) Aβ42 levels consistently abnormal (n = 18). RESULTS: In the Aβ42 declining group, suggestive of incipient preclinical AD, CSF phosphorylated tau (p-tau) showed a similar longitudinal pattern of increasing abnormality over time (p = 0.0001). Correlation between longitudinal slopes of Aβ42 and p-tau confirmed that both trajectories were anti-correlated (rho = -0.60; p = 0.02). Regression analysis showed that Aβ42 slope (decreasing Aβ42) predicted p-tau slope (increasing p-tau) (R2 = 0.47, p = 0.03). Atrophy in the hippocampus was predicted by the interaction of Aβ42 and p-tau slopes (p <  0.0001) only in this incipient preclinical AD group. In all groups combined, memory decline was predicted by p-tau. CONCLUSIONS: The evolution of Aβ42 and p-tau CSF biomarkers in CI subjects follows an anti-correlated trajectory, i.e., as Aβ42 declined, p-tau increased, and thus was suggestive of strong temporal coincidence. Rapid pathogenic cross-talk between Aβ42 and p-tau thus may be evident in very early stages of preclinical AD.
Keywords: Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Atrophy; Brain; Disease Progression; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Peptide Fragments; Prodromal Symptoms; Regression Analysis; Statistics, Nonparametric; tau Proteins

Apolipoprotein E Related Co-Morbidities and Alzheimer's Disease. - Singhrao, Sim K; Harding, Alice; Chukkapalli, Sasanka; Olsen, Ingar; Kesavalu, Lakshmyya; Crean, StJohn (J Alzheimers Dis, 2016)
The primary goal of advancement in clinical services is to provide a health care system that enhances an individual's quality of life. Incidence of diabetes mellitus, cardiovascular disease, and associated dementia coupled with the advancing age of the population, have led to an increase in the worldwide challenge to the healthcare system. In order to overcome these challenges, prior knowledge of common, reliable risk factors and their effectors is essential. Oral health constitutes one such relatively unexplored but indispensable risk factor for aforementioned co-morbidities, in the form of poor oral hygiene and tooth loss during aging. Behavioral traits such as low education, smoking, poor diet, neglect of oral health, lack of exercise, and hypertension are few of the risk factors that are shared commonly among these conditions. In addition, common genetic susceptibility traits such as the apolipoprotein E gene, together with an individual's lifestyle can also influence the development of co-morbidities such as periodontitis, atherosclerosis/stroke, diabetes, and Alzheimer's disease. This review specifically addresses the susceptibility of apolipoprotein E gene allele 4 as the plausible commonality for the etiology of co-morbidities that eventually result from periodontal diseases and ultimately progress to dementia.
Keywords: Aging; Alzheimer Disease; Animals; Apolipoprotein E4; Cardiovascular Diseases; Comorbidity; Diabetes Mellitus, Type 2; Humans; Mice; Periodontal Diseases

Apolipoprotein ɛ4 is Associated with Dementia and Cognitive Impairment Predominantly Due to Alzheimer's Disease and Not with Vascular Cognitive Impairment: A Singapore-Based Cohort. - Chai, Yuek Ling; Yeo, Hazel Kai-Hui; Wang, Jiehao; Hilal, Saima; Ikram, Mohammad Kamran; Venketasubramanian, Narayanaswamy; Wong, Boon-Seng; Chen, Christopher Li-Hsian (J Alzheimers Dis, 2016)
BACKGROUND AND OBJECTIVE: While the association for apolipoprotein ɛ4 allele (APOE4) with Alzheimer's disease (AD) has been consistently confirmed, the association with vascular cognitive impairment (VCI) is unclear. We therefore explored the relationship of APOE with both AD and cerebrovascular disease (CeVD) by examining the prevalence of APOE4 in AD, AD with CeVD and vascular dementia (VaD), as well as in cognitive impairment no dementia (CIND) with and without CeVD. METHODS: We performed a case-control study with subjects recruited from memory clinics and the community. All subjects underwent standardized brain neuroimaging, clinical and neuropsychological assessments, following which they were classified using research criteria. RESULTS: A total of 411 subjects; 92 controls with no cognitive impairment (NCI), 77 CIND without CeVD, 87 CIND with CeVD, 55 AD without CeVD, 68 AD with CeVD, and 32 VaD patients were recruited. Compared to NCI (16.3%), the prevalence of APOE4 carriers was significantly higher only in CIND (37.7%) and AD in the absence of CeVD (45.5%), but not in the three subgroups of VCI, namely CIND with CeVD (20.7%), AD with CeVD (27.9%) and VaD (25.0%). Logistic regression analyses also showed that APOE4 carriers were more likely to have CIND without CeVD (Odds Ratio [OR]: 3.34; 95% Confidence Interval [CI]: 1.59-7.03) and AD without CeVD (OR: 7.21; 95% CI: 2.74-18.98), but no such association was observed in the VCI subgroups. CONCLUSION: APOE4 is significantly associated with dementia and CIND due to AD pathology, but not with VCI.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Apolipoprotein E4; Cognition Disorders; Cohort Studies; Dementia; Female; Genetic Association Studies; Genotype; Humans; Male; Middle Aged; Neuroimaging; Neuropsychological Tests; Psychiatric Status Rating Scales; Singapore; Vascular Diseases

Application of the IWG-2 Diagnostic Criteria for Alzheimer's Disease to the ADNI. - Wang, Hui-Fu; Tan, Lan; Cao, Lei; Zhu, Xi-Chen; Jiang, Teng; Tan, Meng-Shan; Liu, Ying; Wang, Chong; Tsai, Richard M; Jia, Jian-Ping; Yu, Jin-Tai (J Alzheimers Dis, 2016)
BACKGROUND: The International Working Group (IWG) recently proposed the revised diagnostic criteria for Alzheimer's disease (AD) to define and refine several types of AD, and to reclassify AD-related biomarkers into diagnostic and progression markers, but its performance is not known. OBJECTIVE: This study was designed to describe the application of the revised IWG criteria in the Alzheimer's Disease Neuroimaging Initiative (ADNI) dataset, and to ascertain whether diagnostic and progression markers show significant differences in their relationships to AD severity and progression. METHODS: Based on the requirements of the refined criteria, 857 ADNI subjects with memory evaluation and at least one pathophysiological marker (CSF or amyloid imaging biomarkers) were eligible and reclassified in this study, and we calculated the associations of diagnostic (CSF and amyloid PET) and progression markers (MRI and fluorodeoxyglucose-PET) with AD severity and progression respectively. RESULTS: The majority (84.2% ) of ADNI AD group (n = 117) and 173 MCI (37.4% ) subjects in ADNI met the definition of typical AD; and 105 cognitively normal (41.0% ) individuals were diagnosed as asymptomatic AD. Furthermore, diagnostic and progression markers showed significant differences when correlated to AD severity and progression. CONCLUSION: A large proportion of AD dementia subjects were categorized as typical AD, and the revised criteria could identify typical AD from MCI status as well as asymptomatic AD at the asymptomatic stage. Moreover, the significant differences between diagnostic and progression markers further supported the new biomarkers categorization in the refined criteria.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid Precursor Protein Secretases; Aspartic Acid Endopeptidases; Cognitive Dysfunction; Databases, Factual; Disease Progression; Female; Humans; Longitudinal Studies; Male; Multicenter Studies as Topic; Neuroimaging; Psychiatric Status Rating Scales; tau Proteins

Association between Coffee Consumption and Incident Risk of Disabling Dementia in Elderly Japanese: The Ohsaki Cohort 2006 Study. - Sugiyama, Kemmyo; Tomata, Yasutake; Kaiho, Yu; Honkura, Kenji; Sugawara, Yumi; Tsuji, Ichiro (J Alzheimers Dis, 2016)
Epidemiological studies of the association between coffee consumption and dementia have yielded inconsistent results. Therefore, we investigated the association between coffee consumption and incident risk of dementia in an elderly Japanese population. 23,091 subjects aged ≥65 y living in Ohsaki City, northeastern Japan, responded to the baseline survey in 2006. Of these, we analyzed 13,137 subjects who gave informed consent and were not disabled at baseline. The outcome was the incidence of disabling dementia defined by usage of the Long-term Care Insurance database. We used the Cox proportional hazards regression model for multivariate analysis. During 5.7 y of follow-up period, we identified 1,107 cases of incident dementia. Overall, coffee consumption was significantly associated with a lower risk of incident dementia. The multivariate-adjusted HRs for the incidence of dementia according to coffee consumption categories (never, occasionally, 1-2 cups/d, and ≥3 cups/d) were 1.00, 0.73 (95% CI, 0.62-0.86), 0.72 (95% CI, 0.61-0.84), and 0.82 (95% CI, 0.65-1.02; p for trend = 0.009), respectively. In addition, this significant inverse association was more remarkable among women, non-smokers, and non-drinkers. Coffee consumption is significantly associated with a lower risk of incident dementia.
Keywords: Aged; Aged, 80 and over; Coffee; Dementia; Female; Health Surveys; Humans; Incidence; Japan; Male; Prospective Studies; Risk Factors

Association of Butyrylcholinesterase-K Allele and Apolipoprotein E ɛ4 Allele with Cognitive Decline in Dementia with Lewy Bodies and Alzheimer's Disease. - Vijayaraghavan, Swetha; Darreh-Shori, Taher; Rongve, Arvid; Berge, Guro; Sando, Sigrid B; White, Linda R; Auestad, Bjørn H; Witoelar, Aree; Andreassen, Ole A; Ulstein, Ingun D; Aarsland, Dag (J Alzheimers Dis, 2016)
BACKGROUND: A common polymorphism of the butyrylcholinesterase gene, the K-variant (BCHE-K) is associated with reduced butyrylcholinesterase (BuChE) activity. Insufficient studies exist regarding the frequency and role of BCHE-K in dementias. OBJECTIVE: To determine the association of BCHE-K and APOEɛ4 with diagnosis and rate of cognitive decline in dementia with Lewy bodies (DLB) and Alzheimer's disease (AD) patients. METHODS: Genomic DNA from 368 subjects (108 AD, 174 DLB, and 86 controls) from two routine clinical cohort studies in Norway; DemVest and TrønderBrain, were genotyped for BCHE-K and APOEɛ4. The mild dementia DemVest subjects received annual Mini-Mental State Examination assessments for five years. RESULTS: BCHE-K frequency was lower in DLB (33.9% ; p <  0.01) than in control subjects (51.2%), and was numerically lower in AD as well (38.9% ; p = 0.11). More rapid cognitive decline was associated with the APOEɛ4 genotype, but not with the BCHE-K genotype. In an exploratory analysis of patients who completed all five follow-up visits, there was greater cognitive decline in BCHE-K carriers in the presence of the APOEɛ4 allele than in the absence of these polymorphisms. CONCLUSION: BCHE-K is associated with a reduced risk for AD and DLB whereas APOEɛ4 is associated with more rapid cognitive decline. The greater cognitive decline in individuals with both APOEɛ4 and BCHE-K alleles require prospective confirmation in well-controlled trials.
Keywords: Aged; Aged, 80 and over; Alleles; Alzheimer Disease; Apolipoprotein E4; Butyrylcholinesterase; Cognition; Disease Progression; Female; Gene Frequency; Genotype; Humans; Lewy Body Disease; Male; Neuropsychological Tests

Association of Serum Vitamin D with the Risk of Incident Dementia and Subclinical Indices of Brain Aging: The Framingham Heart Study. - Karakis, Ioannis; Pase, Matthew P; Beiser, Alexa; Booth, Sarah L; Jacques, Paul F; Rogers, Gail; DeCarli, Charles; Vasan, Ramachandran S; Wang, Thomas J; Himali, Jayandra J; Annweiler, Cedric; Seshadri, Sudha (J Alzheimers Dis, 2016)
BACKGROUND: Identifying nutrition- and lifestyle-based risk factors for cognitive impairment and dementia may aid future primary prevention efforts. OBJECTIVE: We aimed to examine the association of serum vitamin D levels with incident all-cause dementia, clinically characterized Alzheimer's disease (AD), MRI markers of brain aging, and neuropsychological function. METHODS: Framingham Heart Study participants had baseline serum 25-hydroxyvitamin D (25(OH)D) concentrations measured between 1986 and 2001. Vitamin D status was considered both as a continuous variable and dichotomized as deficient (<10 ng/mL), or at the cohort-specific 20th and 80th percentiles. Vitamin D was related to the 9-year risk of incident dementia (n = 1663), multiple neuropsychological tests (n = 1291) and MRI markers of brain volume, white matter hyperintensities and silent cerebral infarcts (n = 1139). RESULTS: In adjusted models, participants with vitamin D deficiency (n = 104, 8% of the cognitive sample) displayed poorer performance on Trail Making B-A (β= -0.03 to -0.05±0.02) and the Hooper Visual Organization Test (β= -0.09 to -0.12±0.05), indicating poorer executive function, processing speed, and visuo-perceptual skills. These associations remained when vitamin D was examined as a continuous variable or dichotomized at the cohort specific 20th percentile. Vitamin D deficiency was also associated with lower hippocampal volumes (β= -0.01±0.01) but not total brain volume, white matter hyperintensities, or silent brain infarcts. No association was found between vitamin D deficiency and incident all-cause dementia or clinically characterized AD. CONCLUSIONS: In this large community-based sample, low 25(OH)D concentrations were associated with smaller hippocampal volume and poorer neuropsychological function.
Keywords: Adult; Aging; Brain; Cohort Studies; Dementia; Female; Humans; Incidence; Magnetic Resonance Imaging; Male; Middle Aged; Multivariate Analysis; Neuropsychological Tests; Regression Analysis; Risk; Sensitivity and Specificity; Vitamin D

AZD3293: A Novel, Orally Active BACE1 Inhibitor with High Potency and Permeability and Markedly Slow Off-Rate Kinetics. - Eketjäll, Susanna; Janson, Juliette; Kaspersson, Karin; Bogstedt, Anna; Jeppsson, Fredrik; Fälting, Johanna; Haeberlein, Samantha Budd; Kugler, Alan R; Alexander, Robert C; Cebers, Gvido (J Alzheimers Dis, 2016)
A growing body of pathological, biomarker, genetic, and mechanistic data suggests that amyloid accumulation, as a result of changes in production, processing, and/or clearance of brain amyloid-β peptide (Aβ) concentrations, plays a key role in the pathogenesis of Alzheimer's disease (AD). Beta-secretase 1 (BACE1) mediates the first step in the processing of amyloid-β protein precursor (AβPP) to Aβ peptides, with the soluble N terminal fragment of AβPP (sAβPPβ) as a direct product, and BACE1 inhibition is an attractive target for therapeutic intervention to reduce the production of Aβ. Here, we report the in vitro and in vivo pharmacological profile of AZD3293, a potent, highly permeable, orally active, blood-brain barrier (BBB) penetrating, BACE1 inhibitor with unique slow off-rate kinetics. The in vitro potency of AZD3293 was demonstrated in several cellular models, including primary cortical neurons. In vivo in mice, guinea pigs, and dogs, AZD3293 displayed significant dose- and time-dependent reductions in plasma, cerebrospinal fluid, and brain concentrations of Aβ40, Aβ42, and sAβPPβ. The in vitro potency of AZD3293 in mouse and guinea pig primary cortical neuronal cells was correlated to the in vivo potency expressed as free AZD3293 concentrations in mouse and guinea pig brains. In mice and dogs, the slow off-rate from BACE1 may have translated into a prolongation of the observed effect beyond the turnover rate of Aβ. The preclinical data strongly support the clinical development of AZD3293, and patients with AD are currently being recruited into a combined Phase 2/3 study to test the disease-modifying properties of AZD3293.
Keywords: Administration, Oral; Amyloid beta-Peptides; Amyloid Precursor Protein Secretases; Animals; Blood Chemical Analysis; Blood-Brain Barrier; Brain; Dogs; Dose-Response Relationship, Drug; Drug Evaluation, Preclinical; Enzyme Inhibitors; Female; Guinea Pigs; Humans; Imidazoles; Kinetics; Male; Mice, Inbred C57BL; Peptide Fragments; Spiro Compounds

Beneficial Effects of an Integrated Psychostimulation Program in Patients with Alzheimer's Disease. - Ibarria, Marta; Alegret, Montserrat; Valero, Sergi; Morera, Amèrica; Guitart, Marina; Cañabate, Pilar; Moreno, Mariola; Lara, Susana; Diego, Susana; Hernández, Joan; Tantinyá, Natàlia; Vera, Maribel; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The existing pharmacological treatments for Alzheimer's disease (AD) can only slow the progression of symptoms or delay admission to long-term care facilities. The beneficial effects of non-drug treatments are poorly studied. OBJECTIVE: To describe the effects of an Integrated Psychostimulation Program (IPP) in patients with mild-moderate AD treated with acetylcholinesterase inhibitors; and to identify factors related to greater benefit of the IPP. METHODS: 206 patients (mean age = 75.9 years; MMSE = 19.6) were evaluated before starting the IPP and 3, 6, 9, and 12 months later. Measures included: Mini-Mental State Examination (MMSE), Cognitive Subscale of Alzheimer's Disease Assessment Scale (ADAS-Cog), Rapid Disability Rating Scale (RDRS-2), and Neuropsychiatric Inventory Questionnaire (NPI-Q). RESULTS: Patients remained cognitively stable (MMSE/ADAS-Cog) for more than 6 months and significantly worsened at 9-month and 12-month follow-ups, without clinically significant functional changes (RDRS-2) or psychiatric symptoms(NPI-Q). The mean annual change on MMSE and ADAS-Cog were 2.06 and 3.56 points, respectively, lower than the annual decline demonstrated previously in similar patients (2.4 and 4.5, respectively). 42.7% of patients maintained or improved global cognitive scores between baseline and 12-month follow-up. The patients who maintained cognitive functions were older than those who did not (77.5 versus 74.7 years). CONCLUSIONS: The IPP may be an effective treatment to maintain cognition, functionality, and psychiatric symptoms in AD patients pharmacologically treated, and older age seems to increase beneficial effects of IPP.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cholinesterase Inhibitors; Cognition; Combined Modality Therapy; Disease Progression; Female; Humans; Male; Neuropsychological Tests; Psychotherapy; Severity of Illness Index; Treatment Outcome

Biochemical and Radiological Markers of Alzheimer's Disease Progression. - Dziedzic, Tomasz; Pera, Joanna; Klimkowicz-Mrowiec, Aleksandra; Mroczko, Barbara; Slowik, Agnieszka (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a neurodegenerative, inevitably progressive disease with a rate of cognitive, functional, and behavioral decline that varies highly from patient to patient. Although several clinical predictors of AD progression have been identified, to our mind in clinical practice there is a lack of a reliable biomarker that enables one to stratify the risk of deterioration. Identification of biomarkers that allow the monitoring of AD progression could change the way physicians and caregivers make treatment decisions. This review summarizes the results of studies on potential biochemical and radiological markers related to AD progression.
Keywords: Alzheimer Disease; Biomarkers; Disease Progression; Humans; Neuroimaging; Radionuclide Imaging

Biomarkers Differentiating Dementia with Lewy Bodies from Other Dementias: A Meta-Analysis. - Mishima, Aki; Nihashi, Takashi; Ando, Yoshio; Kawai, Hisashi; Kato, Takashi; Ito, Kengo; Terasawa, Teruhiko (J Alzheimers Dis, 2016)
BACKGROUND: Several nuclear imaging and cerebrospinal fluid (CSF) biomarkers are under investigation, aimed at facilitating the differential diagnosis of dementias. OBJECTIVE: To quantitatively synthesize data on test performance in differentiating dementia with Lewy bodies (DLB) from other dementias. METHODS: We searched PubMed (January 2000- March 2015) for English-language publications that assessed a selected set of five imaging and three CSF biomarkers for this purpose. We meta-analyzed measures of agreement between biomarker results and clinical diagnosis. RESULTS: Forty-five publications were eligible. The majority of evidence was based on studies that enrolled representative disease populations. For differentiating between DLB and Alzheimer's disease (AD) or other dementias, metaiodobenzylguanidine scintigraphy and dopamine transporter (DAT) single photon emission computed tomography (SPECT) showed, respectively, excellent (summary kappa = 0.85; 95% confidence interval [95% CI], 0.74-0.96) and good (summary kappa = 0.71; 95% CI, 0.43-0.99) agreement. Metaiodobenzylguanidine scintigraphy appeared superior to fluorodeoxyglucose- positron emission tomography (summary kappa = 0.53; 95% CI, 0.36-0.69) and cerebral blood flow SPECT (summary kappa = 0.40; 95% CI, 0.33-0.47). For differentiating DLB from AD, CSF t-tau levels (summary kappa = 0.68; 95% CI, 0.55-0.82) performed comparably to metaiodobenzylguanidine scintigraphy and DAT SPECT. Sparse direct comparative evidence failed to corroborate these indirect comparisons. CONCLUSION: Metaiodobenzylguanidine scintigraphy and DAT SPECT are highly concordant with clinical diagnosis in differentiating DLB from other dementias. However, given the limitations in the study design, the applicability of these results to real-world differential diagnosis remains unclear. Prospective studies targeting patients with atypical presentations that adopt gold standard tests would reliably estimate the true test performance of these promising biomarkers.
Keywords: Biomarkers; Dementia; Diagnosis, Differential; Humans; Lewy Bodies; PubMed; Radionuclide Imaging; Retrospective Studies

Brain-Specific Basal and Novelty-Induced Alternations in PI3K-Akt and MAPK/ERK Signaling in a Middle-Aged AβPP/PS1 Mouse Model of Alzheimer's Disease. - Guillot, Florence; Kemppainen, Susanna; Lavasseur, Gregoire; Miettinen, Pasi O; Laroche, Serge; Tanila, Heikki; Davis, Sabrina (J Alzheimers Dis, 2016)
Although it is well established that insulin/IGF and BDNF signaling are dysfunctionally regulated in Alzheimer's disease, there are very few studies documenting changes in major target proteins in different murine models of the disease. We investigated a panel of proteins in the PI3K-Akt and MAPK/ERK cascades in parietal cortex, dentate gyrus and CA1 in 13-month-old AβPP/PS1 transgenic mice to determine whether amyloid pathology is associated with basal dysregulation of these proteins or following exposure to novelty. The most striking effect we found was that there was little common regulation of proteins either by pathology alone or exposure to novelty across the three structures, suggesting dysfunctional mechanisms that occur simultaneously have important structure specificity. CA1 shared certain dysfunctional regulation of proteins in the MAPK/ERK cascade, but shared dysfunctional regulation of the PI3K/Akt cascade with the dentate gyrus. Changes in ERK/CREB in transgenic mice did not result in coordinated dysfunction of the downstream transcription factor, Egr1, as it was overexpressed in a normal manner following exposure to novelty. In the PI3K-Akt cascade, there was a flagrant increase in the levels of proteins associated with inflammation, such as NFκB, and structure specific regulation of proteins associated with autophagy, such as mTOR and FOXO1 and lack of regulation of Beclin-1. Finally, Beclin-1 was increased by novelty in wild-type mice but deficient in transgenic mice. Results are interpreted in terms of structure-specific dysfunctional regulation of signaling mechanisms associated with Alzheimer's disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Gene Expression Regulation; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mitogen-Activated Protein Kinase Kinases; Mutation; Oncogene Protein v-akt; Phosphatidylinositol 3-Kinases; Presenilin-1; Signal Transduction

Bridging Integrator 1 (BIN1) Genotypes Mediate Alzheimer's Disease Risk by Altering Neuronal Degeneration. - Wang, Hui-Fu; Wan, Yu; Hao, Xiao-Ke; Cao, Lei; Zhu, Xi-Chen; Jiang, Teng; Tan, Meng-Shan; Tan, Lin; Zhang, Dao-Qiang; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2016)
BACKGROUND: Bridging integrator 1 (BIN1) has been identified as one of the most associated loci for Alzheimer's disease (AD), and recently was reported to modulate tau pathology to mediate AD in vitro. However, the effects of BIN1 on the AD related biomarkers in AD continuum were not specifically assessed. OBJECTIVE: We explored the effects of BIN1 loci on AD specific biomarkers (CSF proteins, brain structures, glucose and amyloid-β (Aβ) metabolisms) to investigate the role BIN1 in AD pathogenesis. METHODS: We calculated the associations of BIN1 loci with these markers at baseline and follow-up in multiple linear models in 812 ADNI subjects. RESULTS: BIN1 loci were significantly associated with the levels of T-tau (rs744373: pc = 0.047, rs13031703: pc = 0.042) and P-tau (rs744373: pc = 0.044, rs13031703: pc = 0.019), but not with Aβ in CSF test. BIN1 genotypes were strongly related to atrophy of hippocampus (rs7561528: pc = 0.011), CA1 (rs1469980: pc = 0.029) and parahippocampus (rs72838284, pc = 0.017) on MRI, and to glucose metabolism on FDG-PET, but not to Aβ deposition on AV45-PET imaging. Furthermore, haplotype and subgroup analysis confirmed these significant findings. In addition, the loci associated with these markers were also identified to influence the risk for AD in the meta-analysis of 74 046 European individuals. CONCLUSION: This study supported that BIN1 contributes to the risk of AD by altering neural degeneration (abnormal tau, brain atrophy and glucose metabolism) but not Aβ pathology.
Keywords: Adaptor Proteins, Signal Transducing; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Brain; Databases, Factual; European Continental Ancestry Group; Female; Follow-Up Studies; Genetic Predisposition to Disease; Glucose; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Nerve Degeneration; Nuclear Proteins; Polymorphism, Single Nucleotide; Positron-Emission Tomography; Risk; tau Proteins; Tumor Suppressor Proteins

Cannabinoid Receptor 2 Participates in Amyloid-β Processing in a Mouse Model of Alzheimer's Disease but Plays a Minor Role in the Therapeutic Properties of a Cannabis-Based Medicine. - Aso, Ester; Andrés-Benito, Pol; Carmona, Margarita; Maldonado, Rafael; Ferrer, Isidre (J Alzheimers Dis, 2016)
The endogenous cannabinoid system represents a promising therapeutic target to modify neurodegenerative pathways linked to Alzheimer's disease (AD). The aim of the present study was to evaluate the specific contribution of CB2 receptor to the progression of AD-like pathology and its role in the positive effect of a cannabis-based medicine (1:1 combination of Δ9-tetrahidrocannabinol and cannabidiol) previously demonstrated to be beneficial in the AβPP/PS1 transgenic model of the disease. A new mouse strain was generated by crossing AβPP/PS1 transgenic mice with CB2 knockout mice. Results show that lack of CB2 exacerbates cortical Aβ deposition and increases the levels of soluble Aβ40. However, CB2 receptor deficiency does not affect the viability of AβPP/PS1 mice, does not accelerate their memory impairment, does not modify tau hyperphosphorylation in dystrophic neurites associated to Aβ plaques, and does not attenuate the positive cognitive effect induced by the cannabis-based medicine in these animals. These findings suggest a minor role for the CB2 receptor in the therapeutic effect of the cannabis-based medicine in AβPP/PS1 mice, but also constitute evidence of a link between CB2 receptor and Aβ processing.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Cannabidiol; Cognition; Disease Models, Animal; Dronabinol; Humans; Male; Medical Marijuana; Memory; Mice, Inbred C57BL; Mice, Transgenic; Nootropic Agents; Presenilin-1; Random Allocation; Receptor, Cannabinoid, CB2; tau Proteins; Treatment Outcome

Cerebrospinal Fluid Fatty Acid-Binding Protein 3 is Related to Dementia Development in a Population-Based Sample of Older Adult Women Followed for 8 Years. - Bjerke, Maria; Kern, Silke; Blennow, Kaj; Zetterberg, Henrik; Waern, Margda; Börjesson-Hanson, Anne; Östling, Svante; Kern, Jürgen; Skoog, Ingmar (J Alzheimers Dis, 2016)
BACKGROUND: Increased fatty acid-binding protein 3 (FABP-3) levels have been reported in neurodegenerative diseases, including Alzheimer's disease (AD). Cerebrospinal fluid (CSF) FABP-3 has therefore been proposed as a putative marker for dementia. Population-based studies examining whether CSF FABP-3 predicts later development of dementia are lacking. OBJECTIVE: The aim of this study was to examine CSF levels of FABP-3 in relation to later development of dementia in elderly women and in relation to Aβ42, T-tau, P-tau181, and CSF: serum albumin ratio. METHODS: 86 non-demented women aged 70-84 years who participated in the Prospective Population Study of Women in Gothenburg, Sweden took part in a lumbar puncture in 1992-93. CSF-FABP-3, Aβ42, T-tau, P-tau181, and the CSF: serum albumin ratio were measured at baseline. Participants were examined with a neuropsychiatric exam at baseline and at follow-up in 2000. Dementia was diagnosed in accordance with DSM-III-R criteria. RESULTS: Between 1992 and 2000, 8 women developed dementia (4 AD, 3 vascular dementia, 1 mixed vascular dementia and AD). Higher levels of CSF-FABP-3 at baseline were related to development of dementia (OR 1.36 CI [1.05-1.76] p = 0.022) and the subtype AD (OR 1.38 CI [1.06-1.82), p = 0.019) during follow-up. FABP-3 correlated with CSF T-tau (r = 0.88, p <  0.001), P-tau181 (r = 0.619, p <  0.001), and CSF:serum albumin ratio (r = 0.233, p = 0.031), but not with Aβ42 (r = -0.08, p = 0.444)CONCLUSION:CSF FABP-3 may be an early marker for later development of dementia, probably related to neuronal degeneration, but independent of Aβ metabolism.
Keywords: Aged; Aged, 80 and over; Albumins; Amyloid beta-Peptides; Community Health Planning; Dementia; Fatty Acid-Binding Proteins; Female; Humans; Longitudinal Studies; Peptide Fragments; Sweden; tau Proteins

Cerebrospinal Fluid Markers of Alzheimer's Disease Pathology and Microglial Activation are Associated with Altered White Matter Microstructure in Asymptomatic Adults at Risk for Alzheimer's Disease. - Melah, Kelsey E; Lu, Sharon Yuan-Fu; Hoscheidt, Siobhan M; Alexander, Andrew L; Adluru, Nagesh; Destiche, Daniel J; Carlsson, Cynthia M; Zetterberg, Henrik; Blennow, Kaj; Okonkwo, Ozioma C; Gleason, Carey E; Dowling, N Maritza; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The immune response in Alzheimer's disease (AD) involves activation of microglia which may remove amyloid-β (Aβ). However, overproduction of inflammatory compounds may exacerbate neural damage in AD. AD pathology accumulates years before diagnosis, yet the extent to which neuroinflammation is involved in the earliest disease stages is unknown. OBJECTIVE: To determine whether neuroinflammation exacerbates neural damage in preclinical AD. METHODS: We utilized cerebrospinal fluid (CSF) and magnetic resonance imaging collected in 192 asymptomatic late-middle-aged adults (mean age = 60.98 years). Neuroinflammatory markers chitinase-3-like protein 1 (YKL-40) and monocyte chemoattractant protein-1 (MCP-1) in CSF were utilized as markers of neuroinflammation. Neural cell damage was assessed using CSF neurofilament light chain protein (NFL), CSF total tau (T-Tau), and neural microstructure assessed with diffusion tensor imaging (DTI). With regard to AD pathology, CSF Aβ42 and tau phosphorylated at threonine 181 (P-Tau181) were used as markers of amyloid and tau pathology, respectively. We hypothesized that higher YKL-40 and MCP-1 in the presence of AD pathology would be associated with higher NFL, T-Tau, and altered microstructure on DTI. RESULTS: Neuroinflammation was associated with markers of neural damage. Higher CSF YKL-40 was associated with both higher CSF NFL and T-Tau. Inflammation interacted with AD pathology, such that greater MCP-1 and lower Aβ42 was associated with altered microstructure in bilateral frontal and right temporal lobe and that greater MCP-1 and greater P-Tau181 was associated with altered microstructure in precuneus. CONCLUSION: Inflammation may play a role in neural damage in preclinical AD.
Keywords: Adipokines; Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Chemokine CCL2; Chitinase-3-Like Protein 1; Diffusion Tensor Imaging; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Lectins; Male; Microglia; Middle Aged; Peptide Fragments; tau Proteins; White Matter

Changes in Brain Volume with Bapineuzumab in Mild to Moderate Alzheimer's Disease. - Novak, Gerald; Fox, Nick; Clegg, Shona; Nielsen, Casper; Einstein, Steven; Lu, Yuan; Tudor, Iulia Cristina; Gregg, Keith; Di, Jianing; Collins, Peter; Wyman, Bradley T; Yuen, Eric; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Bapineuzumab, an anti-amyloid-β monoclonal antibody, was evaluated in two placebo-controlled trials in APOE*ɛ4 carriers and noncarriers, respectively, with Alzheimer's disease. OBJECTIVES: A volumetric magnetic resonance imaging substudy was performed to determine if bapineuzumab altered brain volume rate of change. METHODS: Bapineuzumab dosages included 0.5 mg/kg in carriers and 0.5 or 1.0 mg/kg in noncarriers, every 13 weeks for 78 weeks. Volumetric outcomes included annualized brain, ventricular, and mean hippocampal boundary shift integrals (BBSI; VBSI; HBSI) up to Week 71. Treatment differences were estimated using mixed models for repeated measures. RESULTS: For BBSI and HBSI, there were no significant treatment-related differences within either study, but, compared to pooled carriers and noncarriers receiving placebo, noncarriers receiving1.0 mg/kg bapineuzumab had greater increases in these measures. Bapineuzumab-treated patients showed significantly greater VBSI rates compared with placebo for 0.5 mg/kg in carriers and 1.0 mg/kg (but not 0.5 mg/kg) in noncarriers. CONCLUSIONS: Bapineuzumab produced an increase in ventricular volume compared with placebo. Etiology for this increase is unclear but may be related to amyloid-β clearance or its consequences.
Keywords: Aged; Alzheimer Disease; Antibodies, Monoclonal, Humanized; Apolipoprotein E4; Brain; Double-Blind Method; Female; Heterozygote; Humans; Least-Squares Analysis; Magnetic Resonance Imaging; Male; Nootropic Agents; Organ Size; Severity of Illness Index; Treatment Outcome

Characterizing Aging, Mild Cognitive Impairment, and Dementia with Blood-Based Biomarkers and Neuropsychology. - Kleinschmidt, Martin; Schoenfeld, Robby; Göttlich, Claudia; Bittner, Daniel; Metzner, Jürgen Erich; Leplow, Bernd; Demuth, Hans-Ulrich (J Alzheimers Dis, 2016)
BACKGROUND: Current treatment in Alzheimer's disease (AD) is initiated at a stage where the brain already has irreversible structural deteriorations. Therefore, the concept of treatment prior to obvious cognitive deficits has become widely accepted, and simple biochemical tests to discriminate normal aging from prodromal or demented stages are now common practice. OBJECTIVE: The objective of the study was the differentiation of controls, mild cognitive impairment (MCI) and AD patients by novel blood-based assays in combination with neuropsychological tests. METHODS: In a cross-sectional study, 143 subjects aged 18 to 85 years were recruited. All participants were classified by a comprehensive neuropsychological assessment. Blood samples were analyzed for several amyloid-β (Aβ) species, pro-inflammatory markers, anti-Aβ autoantibodies, and ApoE allele status, respectively. RESULTS: Plasma Aβ1-42 was significantly decreased in MCI and AD compared to age-matched controls, whereas Aβ1-40 did not differ, but increases with age in healthy controls. The Aβ1-42 to Aβ1-40 ratio was stepwise decreased from age-matched controls via MCI to AD, and shows a clear correlation with memory scores. Reduced Aβ1-42 and Aβ1-42 to Aβ1-40 ratio have strongly correlated with carrying ApoE ɛ4 allele. Autoantibodies against pyroglutamate-modified Aβ, but only a certain subclass, were significantly decreased in AD compared to MCI and age-matched controls, whereas autoantibodies against the unmodified N-terminus of Aβ did not differ. CONCLUSION: Comprehensive sample preparation and assay standardization enable reliable usage of plasma Aβ for diagnosis of MCI and AD. Anti-pGlu-Aβ autoantibodies correlate with cognition, but not with ApoE, supporting the associated plasma Aβ analysis with additional and independent information.
Keywords: Activities of Daily Living; Adolescent; Adult; Aged; Aged, 80 and over; Aging; Amyloid beta-Peptides; Analysis of Variance; Apolipoproteins E; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Cross-Sectional Studies; Cytokines; Dementia; Female; Humans; Male; Memory Disorders; Middle Aged; Neuropsychological Tests; Young Adult

Characterizing White Matter Tract Degeneration in Syndromic Variants of Alzheimer's Disease: A Diffusion Tensor Imaging Study. - Madhavan, Ajay; Schwarz, Christopher G; Duffy, Joseph R; Strand, Edythe A; Machulda, Mary M; Drubach, Daniel A; Kantarci, Kejal; Przybelski, Scott A; Reid, Robert I; Senjem, Matthew L; Gunter, Jeffrey L; Apostolova, Liana G; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Different clinical syndromes can arise from Alzheimer's disease (AD) neuropathology, including dementia of the Alzheimer's type (DAT), logopenic primary progressive aphasia (lvPPA), and posterior cortical atrophy (PCA). OBJECTIVE: To assess similarities and differences in patterns of white matter tract degeneration across these syndromic variants of AD. METHODS: Sixty-four subjects (22 DAT, 24 lvPPA, and 18 PCA) that had diffusion tensor imaging and showed amyloid-β deposition on PET were assessed in this case-control study. A whole-brain voxel-based analysis was performed to assess differences in fractional anisotropy, mean diffusivity, axial diffusivity, and radial diffusivity across groups. RESULTS: All three groups showed overlapping diffusion abnormalities in a network of tracts, including fornix, corpus callosum, posterior thalamic radiations, superior longitudinal fasciculus, inferior longitudinal fasciculus, inferior fronto-occipital fasciculus, and uncinate fasciculus. Subtle regional differences were also observed across groups, with DAT particularly associated with degeneration of fornix and cingulum, lvPPA with left inferior fronto-occipital fasciculus and uncinate fasciculus, and PCA with posterior thalamic radiations, superior longitudinal fasciculus, posterior cingulate, and splenium of the corpus callosum. CONCLUSION: These findings show that while each AD phenotype is associated with degeneration of a specific structural network of white matter tracts, striking spatial overlap exists among the three network patterns that may be related to AD pathology.
Keywords: Aged; Alzheimer Disease; Aniline Compounds; Anisotropy; Aphasia, Primary Progressive; Case-Control Studies; Diffusion Tensor Imaging; Female; Humans; Image Processing, Computer-Assisted; Male; Middle Aged; Nerve Fibers, Myelinated; Neurodegenerative Diseases; Neuropsychological Tests; Positron-Emission Tomography; Psychiatric Status Rating Scales; Retrospective Studies; Thiazoles; White Matter

Cholesterol, 24-Hydroxycholesterol, and 27-Hydroxycholesterol as Surrogate Biomarkers in Cerebrospinal Fluid in Mild Cognitive Impairment and Alzheimer's Disease: A Meta-Analysis. - Wang, Hua-Long; Wang, Yan-Yong; Liu, Xin-Gang; Kuo, Sheng-Han; Liu, Na; Song, Qiao-Yun; Wang, Ming-Wei (J Alzheimers Dis, 2016)
Abnormal cholesterol metabolism is an established feature of Alzheimer's disease (AD). Cerebrospinal fluid (CSF) is the fluid surrounding the central nervous system, and the protein and lipid content alterations in the CSF could be biomarkers for degenerative changes in the brain. The laboratory diagnosis of AD is limited to the analysis of three biomarkers in CSF: Aβ42, total tau, and phospho-tau. The purpose of this analysis is to systematically analyze the available data describing the biomarkers of cholesterol and its metabolites in the CSF of subjects with AD. MEDLINE, EMBASE, and the Cochrane Central database were systematically queried to collect studies that have evaluated the markers of cholesterol and its metabolites in the CSF of subjects with mild cognitive impairment (MCI) or AD and age-matched controls. Analysis of the published data shows that the levels of cholesterol are increased in MCI subjects; 24-hydroxycholesterol and 27-hydroxycholesterol are elevated in AD and MCI subjects compared to controls. There is a significant dysfunction of cholesterol metabolism in the CSF of AD subjects. This analysis indicates that in addition to the available biomarkers in the CSF, such as Aβ42, total tau, and phospho-tau, 24-hydroxycholesterol, 27-hydroxycholesterol, and cholesterol appear to be sensitive biomarkers for the evaluation of MCI and AD.
Keywords: Alzheimer Disease; Cholesterol; Cognitive Dysfunction; Databases, Bibliographic; Humans; Hydroxycholesterols

Chronic Sleep Deprivation Exacerbates Learning-Memory Disability and Alzheimer's Disease-Like Pathologies in AβPP(swe)/PS1(ΔE9) Mice. - Qiu, Hongyan; Zhong, Rujia; Liu, Hui; Zhang, Feng; Li, Song; Le, Weidong (J Alzheimers Dis, 2016)
Recently, there is an increasing concern over the association between sleep disorders and Alzheimer's disease (AD). Clinical observations have reported that chronic sleep deprivation (SD) may serve as a risk factor for AD. However, the pathological evidence for this assumption is still lacking. In the present study, we examined the potential impacts of chronic SD on learning-memory and AD-related pathologies in AβPP(swe)/PS1(ΔE9) transgenic (TG) mice and their wild-type (WT) littermates. Results indicated that mice (both TG and WT) exposed to 2-month SD showed an altered amyloid-β protein precursor processing, an elevated level of phosphorylated tau protein, and impaired cognitive performance as compared to non-sleep deprivation (NSD) controls. Moreover, the SD-treated TG mice exhibited more amyloid-β(1-42) production and developed more senile plaques in the cortex and hippocampus than NSD-treated TG mice. In addition, SD caused a striking neuronal mitochondrial damage, caspase cascade activation, and neuronal apoptosis in the hippocampus of both TG and WT mice. More importantly, all these behavioral, neuropathological, and biochemical changes induced by chronic SD were long lasting and were irreversible during a 3-month normal housing condition. Collectively, these results indicate that chronic SD impairs learning and memory, exacerbates AD pathologies, and aggravates the mitochondria-mediated neuronal apoptosis in a long-lasting manner. Our findings provide important experimental evidence to prove that chronic SD is a risk factor for AD.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Apoptosis; Brain; Cognition Disorders; Disease Models, Animal; Humans; In Situ Nick-End Labeling; Learning Disorders; Mice; Mice, Transgenic; Mitochondrial Diseases; Mutation; Phosphorylation; Plaque, Amyloid; Presenilin-1; Reversal Learning; Sleep Deprivation; tau Proteins

Cigarette Smoke-Induced Alterations in Frontal White Matter Lipid Profiles Demonstrated by MALDI-Imaging Mass Spectrometry: Relevance to Alzheimer's Disease. - Nunez, Kavin; Kay, Jared; Krotow, Alexander; Tong, Ming; Agarwal, Amit R; Cadenas, Enrique; de la Monte, Suzanne M (J Alzheimers Dis, 2016)
BACKGROUND: Meta-analysis has shown that smokers have significantly increased risks for Alzheimer's disease (AD), and neuroimaging studies showed that smoking alters white matter (WM) structural integrity. OBJECTIVE: Herein, we characterize the effects of cigarette smoke (CS) exposures and withdrawal on WM myelin lipid composition using matrix assisted laser desorption and ionization-imaging mass spectrometry (MALDI-IMS). METHODS: Young adult male A/J mice were exposed to air (8 weeks; A8), CS (4 or 8 weeks; CS4, CS8), or CS8 followed by 2 weeks recovery (CS8 + R). Frontal lobe WM was examined for indices of lipid and protein oxidation and lipid profile alterations by MALDI-IMS. Lipid ions were identified by MS/MS with the LIPID MAPS prediction tools database. Inter-group comparisons were made using principal component analysis and R-generated heatmap. RESULTS: CS increased lipid and protein adducts such that higher levels were present in CS8 compared with CS4 samples. CS8 + R reversed CS8 effects and normalized the levels of oxidative stress. MALDI-IMS demonstrated striking CS-associated alterations in WM lipid profiles characterized by either reductions or increases in phospholipids (phosphatidylinositol, phosphatidylserine, phosphatidylcholine, or phosphatidylethanolamine) and sphingolipids (sulfatides), and partial reversal of CS's inhibitory effects with recovery. The heatmap hierarchical dendrogram and PCA distinguished CS exposure, duration, and withdrawal effects on WM lipid profiles. CONCLUSION: CS-mediated WM degeneration is associated with lipid peroxidation, protein oxidative injury, and alterations in myelin lipid composition, including shifts in phospholipids and sphingolipids needed for membrane integrity, plasticity, and intracellular signaling. Future goals are to delineate WM abnormalities in AD using MALDI-IMS, and couple the findings with MRI-mass spectroscopy to improve in vivo diagnostics and early detection of brain biochemical responses to treatment.
Keywords: Aldehydes; Analysis of Variance; Animals; Dinoprost; Disease Models, Animal; Enzyme-Linked Immunosorbent Assay; Frontal Lobe; Lipid Metabolism; Male; Mice; Phospholipids; Principal Component Analysis; Protein Carbonylation; Smoking; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Substance Withdrawal Syndrome; White Matter

Circadian Disruption Reveals a Correlation of an Oxidative GSH/GSSG Redox Shift with Learning and Impaired Memory in an Alzheimer's Disease Mouse Model. - LeVault, Kelsey R; Tischkau, Shelley A; Brewer, Gregory J (J Alzheimers Dis, 2016)
It is unclear whether pre-symptomatic Alzheimer's disease (AD) causes circadian disruption or whether circadian disruption accelerates AD pathogenesis. In order to examine the sensitivity of learning and memory to circadian disruption, we altered normal lighting phases by an 8 h shortening of the dark period every 3 days (jet lag) in the APPSwDI NOS2-/- model of AD (AD-Tg) at a young age (4-5 months), when memory is not yet affected compared to non-transgenic (non-Tg) mice. Analysis of activity in 12-12 h lighting or constant darkness showed only minor differences between AD-Tg and non-Tg mice. Jet lag greatly reduced activity in both genotypes during the normal dark time. Learning on the Morris water maze was significantly impaired only in the AD-Tg mice exposed to jet lag. However, memory 3 days after training was impaired in both genotypes. Jet lag caused a decrease of glutathione (GSH) levels that tended to be more pronounced in AD-Tg than in non-Tg brains and an associated increase in NADH levels in both genotypes. Lower brain GSH levels after jet lag correlated with poor performance on the maze. These data indicate that the combination of the environmental stress of circadian disruption together with latent stress of the mutant amyloid and NOS2 knockout contributes to cognitive deficits that correlate with lower GSH levels.
Keywords: Age Factors; Alzheimer Disease; Amyloid beta-Protein Precursor; Analysis of Variance; Animals; Brain; Chromatography, High Pressure Liquid; Chronobiology Disorders; Disease Models, Animal; Gene Expression Regulation; Glutathione; Glutathione Disulfide; Humans; Memory Disorders; Mice; Mice, Transgenic; Mutation; NADP; Nitric Oxide Synthase Type II; Oxidation-Reduction

Circulating microRNAs as Biomarkers of Alzheimer's Disease: A Systematic Review. - Wu, Helen Zong Ying; Ong, Kwok Leung; Seeher, Katrin; Armstrong, Nicola J; Thalamuthu, Anbupalam; Brodaty, Henry; Sachdev, Perminder; Mather, Karen (J Alzheimers Dis, 2016)
BACKGROUND: In recent years, microRNAs (miRNA), a class of non-coding RNA known to regulate protein expression post-transcriptionally, have been recognized as novel biomarkers of diseases. OBJECTIVE: In this systematic review, we identify miRNAs that are differentially expressed in Alzheimer's disease (AD) and/or mild cognitive impairment (MCI) and evaluate their accuracy as potential blood biomarkers. METHODS: Eligible studies of miRNAs in peripheral blood distinguishing patients with AD or MCI from cognitively normal controls were identified through standardized search strategies in Medline, PubMed, and Embase. MiRNAs that were differentially expressed were identified and where available their sensitivity and specificity for AD or MCI extracted from the retrieved studies. RESULTS: Eighteen studies investigated the diagnostic value of miRNAs as peripheral biomarkers of AD/MCI. Twenty miRNAs were significantly upregulated and 32 miRNAs downregulated in AD compared to controls in ten AD studies. Nine miRNAs were consistently dysregulated in more than one study. Of the 8 MCI studies, only one miRNA, miR-132, was consistently upregulated in three independent studies. Of the studies that reported diagnostic accuracy data, the majority of miRNA panels and individual miRNAs had a sensitivity and specificity greater than 0.75. CONCLUSION: Individual studies suggest that miRNAs can differentiate patients with AD/MCI from cognitively normal controls with modest accuracy. However, the literature is constrained by methodological differences between studies, with few studies assessing the same miRNAs. To become potential biomarkers for AD, further studies with standardized study designs for replication and validation are required. Results from this review may help researchers select candidate miRNAs for further investigation.
Keywords: Alzheimer Disease; Biomarkers; Databases, Bibliographic; Humans; MicroRNAs

Clearing Amyloid-β through PPARγ/ApoE Activation by Genistein is a Treatment of Experimental Alzheimer's Disease. - Bonet-Costa, Vicent; Herranz-Pérez, Vicente; Blanco-Gandía, MariCarmen; Mas-Bargues, Cristina; Inglés, Marta; Garcia-Tarraga, Patricia; Rodriguez-Arias, Marta; Miñarro, Jose; Borras, Consuelo; Garcia-Verdugo, Jose Manuel; Viña, Jose (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) clearance from brain, which is decreased in Alzheimer's disease, is facilitated by apolipoprotein E (ApoE). ApoE is upregulated by activation of the retinoid X receptor moiety of the RXR/PPARγ dimeric receptor. Genistein, a non-toxic, well-tested, and inexpensive drug activates the other moiety of the receptor PPARγ. Treatment of an Alzheimer's disease mouse model with genistein results in a remarkable and rapid improvement in various parameters of cognition, such as hippocampal learning, recognition memory, implicit memory, and odor discrimination. This is associated with a lowering of Aβ levels in brain, in the number and the area of amyloid plaques (confirmed in vivo by positron emission tomography) as well as in microglial reactivity. Finally, incubation of primary astrocytes with genistein results in a PPARγ-mediated increased release of ApoE. Our results strongly suggest that controlled clinical trials should be performed to test the effect of genistein as treatment of human Alzheimer's disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Apolipoproteins E; Astrocytes; Avoidance Learning; Brain; Cells, Cultured; Disease Models, Animal; Female; Genistein; Habituation, Psychophysiologic; Maze Learning; Mice, Inbred C57BL; Mice, Transgenic; Neuroprotective Agents; Nootropic Agents; Olfactory Perception; Plaque, Amyloid; PPAR gamma; Recognition (Psychology); Tetrahydronaphthalenes

Clinical and Demographic Factors Associated with the Cognitive and Emotional Efficacy of Regular Musical Activities in Dementia. - Särkämö, Teppo; Laitinen, Sari; Numminen, Ava; Kurki, Merja; Johnson, Julene K; Rantanen, Pekka (J Alzheimers Dis, 2016)
Recent evidence suggests that music-based interventions can be beneficial in maintaining cognitive, emotional, and social functioning in persons with dementia (PWDs). Our aim was to determine how clinical, demographic, and musical background factors influence the cognitive and emotional efficacy of caregiver-implemented musical activities in PWDs. In a randomized controlled trial, 89 PWD-caregiver dyads received a 10-week music coaching intervention involving either singing or music listening or standard care. Extensive neuropsychological testing and mood and quality of life (QoL) measures were performed before and after the intervention (n = 84) and six months later (n = 74). The potential effects of six key background variables (dementia etiology and severity, age, care situation, singing/instrument playing background) on the outcome of the intervention were assessed. Singing was beneficial especially in improving working memory in PWDs with mild dementia and in maintaining executive function and orientation in younger PWDs. Music listening was beneficial in supporting general cognition, working memory, and QoL especially in PWDs with moderate dementia not caused by Alzheimer's disease (AD) who were in institutional care. Both music interventions alleviated depression especially in PWDs with mild dementia and AD. The musical background of the PWD did not influence the efficacy of the music interventions. Our findings suggest that clinical and demographic factors can influence the cognitive and emotional efficacy of caregiver-implemented musical activities and are, therefore, recommended to take into account when applying and developing the intervention to achieve the greatest benefit.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Caregivers; Case-Control Studies; Cognition Disorders; Dementia; Executive Function; Female; Follow-Up Studies; Humans; Male; Memory, Short-Term; Middle Aged; Mood Disorders; Music Therapy; Neuropsychological Tests; Orientation; Outcome Assessment (Health Care); Psychiatric Status Rating Scales; Quality of Life

Clinical Impact of a Second FDG-PET in Atypical/Unclear Dementia Syndromes. - Bergeron, David; Beauregard, Jean-Mathieu; Guimond, Jean; Fortin, Marie-Pierre; Houde, Michèle; Poulin, Stéphane; Verret, Louis; Bouchard, Rémi W; Laforce, Robert (J Alzheimers Dis, 2016)
Diagnosis of atypical/unclear dementia is often difficult and this delays treatment initiation. Several authors have shown that beyond standard dementia workup, 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) reduces the number of unclear diagnoses, leads to earlier treatment, and has a beneficial impact on families. However, it is not uncommon that the FDG-PET findings are equivocal in this setting. For those cases, a repeat FDG-PET may clarify the diagnosis and prevent treatment delay. We retrospectively assessed the clinical impact of a repeat FDG-PET in 59 patients with atypical/unclear dementia syndromes and inconclusive initial FDG-PET. Changes in primary diagnosis, diagnostic confidence, and management following the second FDG-PET were examined. Conducting a second FDG-PET reduced the number of unclear diagnoses from 80% to 34% , led to diagnostic change in 24% of cases, and treatment modification in 22% of patients. Overall, the clinical impact was higher when initial diagnostic confidence was low and the second FDG-PET repeated ≥12 months after the first one. In tertiary care memory clinic settings, when diagnostic incertitude persists despite extensive evaluation and an equivocal FDG-PET, repeating the FDG-PET 12 months later can greatly clarify the diagnosis and improve management.
Keywords: Adult; Brain; Dementia; Diagnosis, Differential; Female; Fluorodeoxyglucose F18; Humans; Male; Middle Aged; Positron-Emission Tomography; Radiopharmaceuticals; Retrospective Studies

Clinical utility of the informant AD8 as a dementia case finding instrument in primary healthcare. - Chan, Qun Lin; Xu, Xin; Shaik, Muhammad Amin; Chong, Steven Shih Tsze; Hui, Richard Jor Yeong; Chen, Christopher Li-Hsian; Dong, YanHong (J Alzheimers Dis, 2016)
The informant AD8 has excellent discriminant ability for dementia case finding in tertiary healthcare settings. However, its clinical utility for dementia case finding at the forefront of dementia management, primary healthcare, is unknown. Therefore, we recruited participants from two primary healthcare centers in Singapore and measured their performance on the Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), Clinical Dementia Rating (CDR), and a local formal neuropsychological battery, in addition to the AD8. Logistic regression was conducted to examine the associations between demographic factors and dementia. Area under the receiver operating characteristics (ROC) curve analysis was used to establish the optimal cut-off points for dementia case finding. Of the 309 participants recruited, 243 (78.7%) had CDR = 0, 22 (7.1%) CDR = 0.5, and 44 (14.2%) CDR ≥1. Age was strongly associated with dementia, and the optimal age for dementia case finding in primary healthcare settings was ≥75 years. In this age group, the AD8 has excellent dementia case finding capability and was superior to the MMSE and equivalent to the MoCA [AD8 AUC (95% CI): 0.95 (0.91-0.99), cut-off: ≥3, sensitivity: 0.90, specificity: 0.88, PPV: 0.79 and NPV: 0.94; MMSE AUC (95% CI): 0.87 (0.79-0.94), p = 0.04; MoCA AUC (95% CI): 0.88 (0.82-0.95), p = 0.06]. In conclusion, the AD8 is well suited for dementia case finding in primary healthcare settings.
Keywords: Aged; Aged, 80 and over; Dementia; Female; Humans; Language; Logistic Models; Male; Mass Screening; Middle Aged; Neuropsychological Tests; Primary Health Care; Reproducibility of Results; ROC Curve; Sensitivity and Specificity; Singapore; Surveys and Questionnaires

The Cognitive Change Index as a Measure of Self and Informant Perception of Cognitive Decline: Relation to Neuropsychological Tests. - Rattanabannakit, Chatchawan; Risacher, Shannon L; Gao, Sujuan; Lane, Kathleen A; Brown, Steven A; McDonald, Brenna C; Unverzagt, Frederick W; Apostolova, Liana G; Saykin, Andrew J; Farlow, Martin R (J Alzheimers Dis, 2016)
BACKGROUND: The perception of cognitive decline by individuals and those who know them well ("informants") has been inconsistently associated with objective cognitive performance, but strongly associated with depressive symptoms. OBJECTIVE: We investigated associations of self-report, informant-report, and discrepancy between self- and informant-report of cognitive decline obtained from the Cognitive Change Index (CCI) with cognitive test performance and self-reported depressive symptoms. METHODS: 267 participants with normal cognition, mild cognitive impairment (MCI), or mild dementia were included from a cohort study and memory clinic. Association of test performance and self-rated depression (Geriatric Depression Scale, GDS) with CCI scores obtained from subjects (CCI-S), their informants (CCI-I), and discrepancy scores between subjects and informants (CCI-D; CCI-S minus CCI-I) were analyzed using correlation and analysis of covariance (ANCOVA) models. RESULTS: CCI-S and CCI-I scores showed high internal consistency (Cronbach alpha 0.96 and 0.98, respectively). Higher scores on CCI-S and CCI-I, and lower scores on the CCI-D, were associated with lower performance on various cognitive tests in both univariate and in ANCOVA models adjusted for age, gender, and education. Adjustment for GDS slightly weakened the relationships between CCI and test performance but most remained significant. CONCLUSION: Self- and informant-report of cognitive decline, as measured by the CCI, show moderately strong relationships with objective test performance independent of age, gender, education, and depressive symptoms. The CCI appears to be a valid cross-sectional measure of self and informant perception of cognitive decline across the continuum of functioning. Studies are needed to address the relationship of CCI scores to longitudinal outcome.
Keywords: Adult; Aged; Aged, 80 and over; Analysis of Variance; Cognitive Dysfunction; Cross-Sectional Studies; Dementia; Female; Humans; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Perception; Self Report

Cohort Effects in the Prevalence and Survival of People with Dementia in a Rural Area in Northern Sweden. - Wimo, Anders; Sjölund, Britt-Marie; Sköldunger, Anders; Qiu, Chengxuan; Klarin, Inga; Nordberg, Gunilla; von Strauss, Eva (J Alzheimers Dis, 2016)
BACKGROUND: Recent studies suggest that trends in cardiovascular risk may result in a decrease in age-specific prevalence of dementia. Studies in rural areas are rare. OBJECTIVES: To study cohort effects in dementia prevalence and survival of people with dementia in a Swedish rural area. METHODS: Participants were from the 1995-1998 Nordanstig Project (NP) (n = 303) and the 2001-2003 Swedish National study on Aging and Care in Nordanstig (SNAC-N) (n = 384). Overall 6-year dementia prevalence and mortality in NP and SNAC-N were compared for people 78 years and older. Logistic regression analyses were used to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for dementia occurrence using the NP study population as the reference group. Cox regression models were used to analyze time to death. RESULTS: The crude prevalence of dementia was 21.8% in NP and 17.4% in SNAC-N. When the NP cohort was used as the reference group, the age- and gender-adjusted OR of dementia was 0.71 (95% CI 0.48-1.04) in SNAC-N; the OR was 0.47 (0.24-0.90) for men and 0.88 (0.54-1.44) for women. In the extended model, the OR of dementia was significantly lower in SNAC-N than in the NP cohort as a whole (0.63; 0.39-0.99) and in men (0.34; 0.15-0.79), but not in women (0.81; 0.46-1.44). The Cox regression models indicated that the hazard ratio of dying was lower in the SNAC-N than NP population. CONCLUSIONS: Trends toward a lower prevalence of dementia in high-income countries seem to be evident in this Swedish rural area, at least in men.
Keywords: Aged; Aged, 80 and over; Aging; Cohort Effect; Dementia; Female; Humans; Male; Prevalence; Risk Factors; Rural Population; Sex Factors; Survival Rate; Sweden

Comparing the Effects of Multisensory Stimulation and Individualized Music Sessions on Elderly People with Severe Dementia: A Randomized Controlled Trial. - Sánchez, Alba; Maseda, Ana; Marante-Moar, M Pilar; de Labra, Carmen; Lorenzo-López, Laura; Millán-Calenti, José Carlos (J Alzheimers Dis, 2016)
The objective of this study was to compare the effects of a multisensory stimulation environment (MSSE) and individualized music sessions on agitation, emotional and cognitive status, and dementia severity in a sample of institutionalized patients with severe dementia. Twenty-two participants with a diagnosis of severe or very severe dementia were randomly assigned to two groups: MSSE and individualized music sessions. Both groups participated in two 30-min weekly sessions over 16 weeks. Outcomes were agitation (Cohen-Mansfield Agitation Inventory, CMAI), mood (Cornell Scale for Depression in Dementia, CSDD), anxiety (Rating Anxiety in Dementia, RAID), cognitive function (Severe Mini-Mental State Examination, SMMSE), and the overall severity of dementia (Bedford Alzheimer Nursing Severity Scale, BANS-S). They were assessed at baseline (pre-trial), in the middle (mid-trial), at the end of the intervention (post-trial), and 8 weeks after the intervention (follow-up). Patients in the MSSE group showed significant improvement in their RAID and BANS-S scores compared with the individualized music group post- versus pre-trial. With regard to agitation, there was improvement during the intervention in both the MSSE and individualized music groups in the CMAI total score after 16 weeks of intervention, with no significant differences between the groups. The results suggest that MSSE could have better effects on anxiety symptoms and dementia severity in comparison with individualized music sessions in elderly patients with severe dementia.
Keywords: Affect; Aged; Aged, 80 and over; Anxiety; Cognition; Dementia; Environment; Female; Follow-Up Studies; Humans; Male; Mental Status Schedule; Music Therapy; Precision Medicine; Sensory Art Therapies; Severity of Illness Index; Treatment Outcome

Comparison of Different Matrices as Potential Quality Control Samples for Neurochemical Dementia Diagnostics. - Lelental, Natalia; Brandner, Sebastian; Kofanova, Olga; Blennow, Kaj; Zetterberg, Henrik; Andreasson, Ulf; Engelborghs, Sebastiaan; Mroczko, Barbara; Gabryelewicz, Tomasz; Teunissen, Charlotte; Mollenhauer, Brit; Parnetti, Lucilla; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Assay-vendor independent quality control (QC) samples for neurochemical dementia diagnostics (NDD) biomarkers are so far commercially unavailable. This requires that NDD laboratories prepare their own QC samples, for example by pooling leftover cerebrospinal fluid (CSF) samples. OBJECTIVE: To prepare and test alternative matrices for QC samples that could facilitate intra- and inter-laboratory QC of the NDD biomarkers. METHODS: Three matrices were validated in this study: (A) human pooled CSF, (B) Aβ peptides spiked into human prediluted plasma, and (C) Aβ peptides spiked into solution of bovine serum albumin in phosphate-buffered saline. All matrices were tested also after supplementation with an antibacterial agent (sodium azide). We analyzed short- and long-term stability of the biomarkers with ELISA and chemiluminescence (Fujirebio Europe, MSD, IBL International), and performed an inter-laboratory variability study. RESULTS: NDD biomarkers turned out to be stable in almost all samples stored at the tested conditions for up to 14 days as well as in samples stored deep-frozen (at - 80°C) for up to one year. Sodium azide did not influence biomarker stability. Inter-center variability of the samples sent at room temperature (pooled CSF, freeze-dried CSF, and four artificial matrices) was comparable to the results obtained on deep-frozen samples in other large-scale projects. CONCLUSION: Our results suggest that it is possible to replace self-made, CSF-based QC samples with large-scale volumes of QC materials prepared with artificial peptides and matrices. This would greatly facilitate intra- and inter-laboratory QC schedules for NDD measurements.
Keywords: Amyloid beta-Peptides; Animals; Anti-Bacterial Agents; Biomarkers; Cattle; Clinical Chemistry Tests; Dementia; Humans; Peptide Fragments; Quality Control; Reference Standards; Serum Albumin, Bovine; Sodium Azide; tau Proteins; Time Factors; Tissue Preservation

Comparison of Prefrontal Atrophy and Episodic Memory Performance in Dysexecutive Alzheimer's Disease and Behavioral-Variant Frontotemporal Dementia. - Wong, Stephanie; Bertoux, Maxime; Savage, Greg; Hodges, John R; Piguet, Olivier; Hornberger, Michael (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) sometimes presents with prominent executive dysfunction and associated prefrontal cortex atrophy. The impact of such executive deficits on episodic memory performance as well as their neural correlates in AD, however, remains unclear. The aim of the current study was to investigate episodic memory and brain atrophy in AD patients with relatively spared executive functioning (SEF-AD; n = 12) and AD patients with relatively impaired executive functioning (IEF-AD; n = 23). We also compared the AD subgroups with a group of behavioral-variant frontotemporal dementia patients (bvFTD; n = 22), who typically exhibit significant executive deficits, and age-matched healthy controls (n = 38). On cognitive testing, the three patient groups showed comparable memory profiles on standard episodic memory tests, with significant impairment relative to controls. Voxel-based morphometry analyses revealed extensive prefrontal and medial temporal lobe atrophy in IEF-AD and bvFTD, whereas this was limited to the middle frontal gyrus and hippocampus in SEF-AD. Moreover, the additional prefrontal atrophy in IEF-AD and bvFTD correlated with memory performance, whereas this was not the case for SEF-AD. These findings indicate that IEF-AD patients show prefrontal atrophy in regions similar to bvFTD, and suggest that this contributes to episodic memory performance. This has implications for the differential diagnosis of bvFTD and subtypes of AD.
Keywords: Aged; Alzheimer Disease; Atrophy; Databases, Factual; Diagnosis, Differential; Executive Function; Female; Frontotemporal Dementia; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Memory, Episodic; Middle Aged; Neuropsychological Tests; Prefrontal Cortex

Cost Related to Dementia in the Young and the Impact of Etiological Subtype on Cost. - Kandiah, Nagaendran; Wang, Vivian; Lin, Xuling; Nyu, Mei Mei; Lim, Linda; Ng, Adeline; Hameed, Shahul; Wee, Hwee Lin (J Alzheimers Dis, 2016)
BACKGROUND: Young onset dementia (YOD) presents in individuals who are economically productive and socially active. While the cost related to dementia in the elderly has been widely studied, the cost related to YOD is largely unknown. OBJECTIVE: To study the economic burden of community dwelling YOD in relation to late onset dementia (LOD) and cost of YOD based on etiology. METHODS: In this prospective cross-sectional study of 255 patients attending a tertiary neurology center, data on economic burden, clinical features, and caregiver burden were collected using structured financial questionnaire, standard cognitive and neuropsychiatric measures, and Zarit caregiver burden scale. Cost components were grouped into those relating to direct medical costs, direct non-medical costs, and those related to indirect costs. Cost was also categorized based on etiology of YOD. RESULTS: The mean age at symptom onset in the YOD and LOD cohort was 57.0 (SD 5.1) and 75.0 (SD 5.9) years, respectively. The median annual cost for patients with YOD was almost twice that of LOD (USD 15,815 versus USD 8,396). Indirect cost contributed heavily to cost related to YOD. Even when grouped by dementia etiology, YOD patients with Alzheimer's disease, frontotemporal dementia (FTD), and vascular dementia had higher cost compared to their elderly counterparts. Young onset FTD had the highest cost. 43.2% of YOD reported loss of employment due to dementia, which was significantly higher than that in LOD (2.4%). CONCLUSION: Patients with YOD have a high economic burden. Young patients with FTD have the highest cost followed by vascular dementia and Alzheimer's disease.
Keywords: Age of Onset; Aged; Cohort Studies; Costs and Cost Analysis; Cross-Sectional Studies; Dementia; Female; Humans; Independent Living; Male; Mental Disorders; Middle Aged; Perceptual Disorders; Prospective Studies; Psychiatric Status Rating Scales; Severity of Illness Index; Surveys and Questionnaires; Young Adult

Course and Determinants of Anosognosia in Alzheimer's Disease: A 12-Month Follow-up. - Turró-Garriga, Oriol; Garre-Olmo, Josep; Calvó-Perxas, Laia; Reñé-Ramírez, Ramón; Gascón-Bayarri, Jordi; Conde-Sala, Josep Lluís (J Alzheimers Dis, 2016)
Anosognosia in Alzheimer's disease (AD) has been associated with greater cognitive impairment and more behavioural and psychological symptoms of dementia (BPSD). This study examines the incidence, persistence, and remission rates of anosognosia over a 12-month period, as well as the related risk factors. This was an observational 12-month prospective study. The longitudinal sample comprised 177 patients with mild or moderate AD, and their respective caregivers. Anosognosia was assessed using the Anosognosia Questionnaire in Dementia, and we also evaluated cognitive status (Mini-Mental State Examination), functional disability (Disability Assessment in Dementia), and the presence of BPSD (Neuropsychiatric Inventory). Multinomial logistic regression was used to determine the variables associated with the incidence, persistence and remission of anosognosia. The prevalence of anosognosia was 39.5% (95% CI = 32.1-47.1) at baseline. At 12 months, incidence was 38.3% (95% CI = 28.6-48.0), persistence was 80.0% (95% CI = 69.9-90.1) and remission was 20.0% (95% CI = 9.9-30.1). The regression model identified lower age, more education, and the presence of delusions as variables associated with incidence, and more education, lower instrumental DAD score, and disinhibition as variables associated with persistence. No variables were associated with remission (n = 14). The presence of anosognosia in AD patients is high. Education and certain neuropsychiatric symptoms may explain a greater and earlier incidence of anosognosia. However, anosognosia also increases with greater cognitive impairment and disease severity.
Keywords: Age Factors; Aged; Agnosia; Alzheimer Disease; Disability Evaluation; Disease Progression; Educational Status; Female; Follow-Up Studies; Humans; Incidence; Logistic Models; Longitudinal Studies; Male; Mental Status Schedule; Neuropsychological Tests; Prevalence; Prospective Studies; Risk Factors; Severity of Illness Index

Cycloheximide Treatment Causes a ZVAD-Sensitive Protease-Dependent Cleavage of Human Tau in Drosophila Cells. - Geng, Junhua; Xia, Lu; Li, Wanjie; Zhao, Changqi; Dou, Fei (J Alzheimers Dis, 2016)
Neurofibrillary tangles are the main pathological feature of Alzheimer's disease. Insoluble tau protein is the major component of neurofibrillary tangles. Defects in the tau protein degradation pathway in neurons can lead to the accumulation of tau and its subsequent aggregation. Currently, contradictory results on the tau degradation pathway have been reported by different groups. This discrepancy is most likely due to different cell lines and methods used in those studies. In this study, we found that cycloheximide treatment induced mild activation of a ZVAD-sensitive protease in Drosophila Kc cells, resulting in cleavage of tau at its C-terminus; this cleavage could generate misleading tau protein degradation pattern results depending on the antibodies used in the assay. Because cycloheximide is a broadly used chemical reagent for the study of protein degradation, the unexpected artificial effect we observed here indicates that cycloheximide is not suitable for the study of tau degradation. Other methods, such as inducible expression systems and pulse-chase assays, may be more appropriate for studying tau degradation under physiological conditions.
Keywords: Animals; Apoptosis; Caspase 3; Cell Line; Cycloheximide; Drosophila; Drosophila Proteins; Drug Evaluation, Preclinical; Humans; Oligopeptides; Peptide Hydrolases; Protease Inhibitors; Protein Synthesis Inhibitors; tau Proteins; Time

The Cytome Assay as a Tool to Investigate the Possible Association Between Exposure to Extremely Low Frequency Magnetic Fields and an Increased Risk for Alzheimer's Disease. - Maes, Annemarie; Anthonissen, Roel; Wambacq, Sheleen; Simons, Koen; Verschaeve, Luc (J Alzheimers Dis, 2016)
Exposure to extremely low frequency magnetic fields (ELF-MF) has been identified as one of the potential environmental risk factors for Alzheimer's disease (AD). However, this is far from being established. So far there is no experimental evidence supporting this alleged association. We have performed an in vitro cytogenetic laboratory investigation to explore the plausibility of such association. Our investigation was based on possible similarities found in cells from AD patients and in cells exposed to ELF-MF. We especially found that 50  Hz ELF-MF increase the frequency of cells with (large) micronuclei and nuclear buds indicating that fields above 50 μT may induce chromosome instabilities as those found in AD patients. It should be stressed yet that results from the few published experimental studies on ELF-MF and AD are rather reassuring. Thus, our findings certainly do not prove anything. They only suggest that further investigations might be necessary.
Keywords: Apoptosis; Carcinoma; Cell Line, Tumor; Chromosome Aberrations; Cytokinesis; Dose-Response Relationship, Radiation; Humans; Magnetic Fields; Risk Factors

Decreased Levels of VAMP2 and Monomeric Alpha-Synuclein Correlate with Duration of Dementia. - Vallortigara, Julie; Whitfield, David; Quelch, William; Alghamdi, Amani; Howlett, David; Hortobágyi, Tibor; Johnson, Mary; Attems, Johannes; O'Brien, John T; Thomas, Alan; Ballard, Clive G; Aarsland, Dag; et al. (J Alzheimers Dis, 2016)
Alpha-synuclein (α-syn) aggregations are the key pathological hallmark of dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD), but are also frequently present in Alzheimer's disease (AD). Much remains unknown about the role of α-syn in the synapse and the wider role of synaptic dysfunction in these dementias. Changes in concentrations of key 'SNAP (Soluble N-ethylmaleimide Sensitive Factor Attachment Protein) Receptor' (SNARE) proteins as a consequence of alterations in the aggregation state of α-syn may contribute to synaptic dysfunction in patients with DLB, PDD, and AD and result in impaired cognition. We have studied a large cohort (n = 130) of autopsy confirmed DLB, PDD, AD, and control brains. Using semi-quantitative western blotting, we have demonstrated significant changes across the diagnostic groups of DLB, PDD, and AD in the SNARE and vesicle proteins syntaxin, Munc18, VAMP2, and monomeric α-syn in the prefrontal cortex, with a significant reduction of Munc18 in AD patients (p <  0.001). This correlated to the final MMSE score before death (p = 0.016). We also identified a significant negative correlation between the duration of dementia and the levels of the binding partners VAMP2 (p = 0.0004) and monomeric α-syn (p = 0.0002). Our findings may indicate that an upregulation of SNARE complex related proteins occurs in the early stages of disease as an attempt at compensating for failing synapses, prior to widespread deposition of pathological α-syn.
Keywords: Aged; Aged, 80 and over; alpha-Synuclein; Amyloid beta-Peptides; Analysis of Variance; Cognition Disorders; Dementia; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Regression Analysis; Synaptophysin; tau Proteins; Vesicle-Associated Membrane Protein 2

Delusions in Patients with Alzheimer's Disease: A Multidimensional Approach. - D'Onofrio, Grazia; Panza, Francesco; Sancarlo, Daniele; Paris, Francesco F; Cascavilla, Leandro; Mangiacotti, Antonio; Lauriola, Michele; Paroni, Giulia H; Seripa, Davide; Greco, Antonio (J Alzheimers Dis, 2016)
In Alzheimer's disease (AD) patients with delusions, clinical outcomes and mortality result from a combination of psychological, biological, functional, and environmental factors. We determined the effect of delusions on mortality risk, clinical outcomes linked to comprehensive geriatric assessment (CGA), cognitive, depressive, and neuropsychiatric symptoms (NPS) in 380 consecutive AD patients with Mini-Mental State Examination, Clinical Dementia Rating scale, 15-item Geriatric Depression Scale, and Neuropsychiatric Inventory (NPI), assessing one-year mortality risk using the Multidimensional Prognostic Index (MPI). We included 121 AD patients with delusions (AD-D) and 259 AD patients without delusions (AD-noD). AD-D patients were significantly older, with higher age at onset and cognitive impairment, a more severe stage of dementia, and more depressive symptoms than AD-noD patients. Disease duration was slightly higher in AD-D patients than in those without delusions, although this difference was not statistically significant. At CGA, AD-D patients showed a higher grade of disability in basic and instrumental activities of daily living, and an increased risk of malnutrition and bedsores. The two groups of patients significantly differed in MPI score (AD-D: 0.65 versus AD-noD: 0.51, p <  0.0001) and MPI grade. AD-D patients showed also a significant higher score in NPI of the following NPS than AD-noD patients: hallucinations, agitation/aggression, depression mood, apathy, irritability/lability, aberrant motor activity, sleep disturbances, and eating disorders. Therefore, AD-D patients showed higher dementia severity, and higher impairment in cognitive and depressive symptoms, and several neuropsychiatric domains than AD-noD patients, and this appeared to be associated with higher multidimensional impairment and increased risk of mortality.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Delusions; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Prognosis; Risk; Severity of Illness Index; Time Factors

Dementia Apraxia Test (DATE): A Brief Tool to Differentiate Behavioral Variant Frontotemporal Dementia from Alzheimer's Dementia Based on Apraxia Profiles. - Johnen, Andreas; Frommeyer, Jana; Modes, Fenja; Wiendl, Heinz; Duning, Thomas; Lohmann, Hubertus (J Alzheimers Dis, 2016)
BACKGROUND: Standardized praxis assessments with modern, empirically validated screening tests have substantially improved clinical evaluation of apraxia in patients with stroke. Although apraxia may contribute to early differential diagnosis of Alzheimer's dementia (AD) and behavioral variant frontotemporal dementia (bvFTD), no comparable test is readily available to clinicians for this purpose to date. OBJECTIVE: To design a clinically useful apraxia test for the differentiation of AD and bvFTD. METHODS: 84 test items pertaining to twelve praxis subdomains were evaluated for their efficacy to discriminate between patients with bvFTD (n = 24), AD (n = 28), and elderly healthy controls (HC; n = 35). Items were then selected based on discriminative value and psychometric properties. RESULTS: Items indicative of mild AD comprised spatially complex imitation of hand and finger postures and to a lesser degree, pantomime of common object-use. Buccofacial apraxia including imitation of face postures, emblematic face postures, and repetition of multisyllabic pseudowords differentiated bvFTD from HC and AD. The final test version consisting of 20 items proved highly efficient for the discrimination of biologically confirmed dementia patients from HC (sensitivity 91% , specificity 71%) but also for differential diagnosis of bvFTD and AD (sensitivity 74% , specificity 93%). CONCLUSIONS: Assessment of praxis profiles effectively contributes to diagnosis and differential diagnosis of AD and bvFTD. The Dementia Apraxia Test (DATE) is a brief and easy to administer cognitive tool for dementia assessment, has a high inter-rater reliability (Cohen's κ= 0.885) and demonstrates content validity.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Apraxias; Diagnosis, Differential; Female; Frontotemporal Dementia; Humans; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Psychometrics; Reference Values

Depressive Symptoms and Small Hippocampal Volume Accelerate the Progression to Dementia from Mild Cognitive Impairment. - Chung, Jun Ku; Plitman, Eric; Nakajima, Shinichiro; Chakravarty, M Mallar; Caravaggio, Fernando; Takeuchi, Hiroyoshi; Gerretsen, Philip; Iwata, Yusuke; Patel, Raihaan; Mulsant, Benoit H; Graff-Guerrero, Ariel (J Alzheimers Dis, 2016)
Previous studies have highlighted that decreased hippocampal volume, an early neural correlate of dementia, is commonly observed in patients with mild cognitive impairment (MCI). However, it is unclear whether neurodegenerative and resultant clinical trajectories are accelerated in MCI patients with concomitant depressive symptoms, leading to a faster conversion to dementia stages than those who are not depressed. No longitudinal study has investigated whether depressed amnestic MCI (DEP+aMCI) patients show an earlier onset of progression to dementia than non-depressed amnestic MCI (DEP-aMCI) patients and whether progressive hippocampal volume reductions are related in the conversion process. Using data from Alzheimer's Disease Neuroimaging Initiative, we examined 2-year follow-up data from 38 DEP+aMCI patients and 38 matched DEP-aMCI patients and compared their ages of conversion from aMCI to AD and trajectories of progressive hippocampal volume changes. DEP+ and DEP- patients were defined as having baseline Geriatric Depression Scale scores of 5 or above and 0, respectively. DEP+ converters showed earlier ages of conversion to dementia (p = 0.009) and greater left hippocampal volume loss than both DEP- converters and DEP+ non-converters over the 2-year period (p = 0.003, p = 0.001, respectively). These findings could not be explained by changes in total brain volume, differences in their clinical symptoms of dementia, daily functioning, or apolipoprotein E4 genotypes. No difference in conversion rate to dementia or progressive hippocampal volume change was found between DEP+ patients and DEP-patients, which suggested depressive symptoms themselves may not lead to progression of dementia from MCI. In conclusion, there is a synergistic effect of depressive symptoms and smaller left hippocampal volume in MCI patients that accelerates conversion to dementia.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Dementia; Depression; Disease Progression; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Psychiatric Status Rating Scales

Detection of Alzheimer's Disease by Three-Dimensional Displacement Field Estimation in Structural Magnetic Resonance Imaging. - Wang, Shuihua; Zhang, Yudong; Liu, Ge; Phillips, Preetha; Yuan, Ti-Fei (J Alzheimers Dis, 2016)
BACKGROUND: Within the past decade, computer scientists have developed many methods using computer vision and machine learning techniques to detect Alzheimer's disease (AD) in its early stages. OBJECTIVE: However, some of these methods are unable to achieve excellent detection accuracy, and several other methods are unable to locate AD-related regions. Hence, our goal was to develop a novel AD brain detection method. METHODS: In this study, our method was based on the three-dimensional (3D) displacement-field (DF) estimation between subjects in the healthy elder control group and AD group. The 3D-DF was treated with AD-related features. The three feature selection measures were used in the Bhattacharyya distance, Student's t-test, and Welch's t-test (WTT). Two non-parallel support vector machines, i.e., generalized eigenvalue proximal support vector machine and twin support vector machine (TSVM), were then used for classification. A 50 × 10-fold cross validation was implemented for statistical analysis. RESULTS: The results showed that "3D-DF+WTT+TSVM" achieved the best performance, with an accuracy of 93.05 ± 2.18, a sensitivity of 92.57 ± 3.80, a specificity of 93.18 ± 3.35, and a precision of 79.51 ± 2.86. This method also exceled in 13 state-of-the-art approaches. Additionally, we were able to detect 17 regions related to AD by using the pure computer-vision technique. These regions include sub-gyral, inferior parietal lobule, precuneus, angular gyrus, lingual gyrus, supramarginal gyrus, postcentral gyrus, third ventricle, superior parietal lobule, thalamus, middle temporal gyrus, precentral gyrus, superior temporal gyrus, superior occipital gyrus, cingulate gyrus, culmen, and insula. These regions were reported in recent publications. CONCLUSIONS: The 3D-DF is effective in AD subject and related region detection.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Brain Mapping; Datasets as Topic; Female; Humans; Imaging, Three-Dimensional; Machine Learning; Magnetic Resonance Imaging; Male

Development and Validation of the RxDx-Dementia Risk Index to Predict Dementia in Patients with Type 2 Diabetes and Hypertension. - Mehta, Hemalkumar B; Mehta, Vinay; Tsai, Chu-Lin; Chen, Hua; Aparasu, Rajender R; Johnson, Michael L (J Alzheimers Dis, 2016)
BACKGROUND: Elderly patients with type 2 diabetes mellitus and hypertension are at high risk for developing dementia. In addition to comorbid disease conditions (Dx), prescription drugs (Rx) are important risk factors for dementia. OBJECTIVE: Develop and validate the RxDx-Dementia risk index by combining diagnosis and prescription information in a single risk index to predict incident dementia, and compare its performance with diagnosis-based Charlson comorbidity score (CCS) and prescription-based chronic disease score (CDS). METHODS: Elderly patients diagnosed with type 2 diabetes mellitus and hypertension, and without prior dementia were identified from the Clinical Practice Research Datalink (2003-2012). A Cox proportional hazard model was constructed to model the time to dementia by incorporating age, gender, and 31 RxDx disease conditions as independent variables. Points were assigned to risk factors to obtain summary risk score. Discrimination and calibration of the risk index were evaluated. Different risk indices were compared against RxDx-Dementia risk index using c-statistic, net reclassification improvement (NRI) and integrated discrimination improvement (IDI). RESULTS: Of 133,176 patients with type 2 diabetes mellitus and hypertension, 3.42% patients developed dementia.The c-statistics value for RxDx-Dementia risk index was 0.806 (95% CI, 0.799-0.812). Based on the c-statistics, NRI and IDI values, the RxDx-Dementia risk index performed better compared to CCS, CDS, and their combinations. CONCLUSION: The RxDx-Dementia risk index can be a useful tool to identify hypertensive and diabetic patients who are at high risk of developing dementia. This has implications for clinical management of patients with multiple comorbid conditions as well as risk adjustment for database studies.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Dementia; Diabetes Mellitus, Type 2; Female; Humans; Hypertension; Male; Middle Aged; Predictive Value of Tests; Prescription Drugs; Proportional Hazards Models; Reproducibility of Results; Risk Assessment; Risk Factors

Development of a Standardized Approach to Disclosing Amyloid Imaging Research Results in Mild Cognitive Impairment. - Lingler, Jennifer H; Butters, Meryl A; Gentry, Amanda L; Hu, Lu; Hunsaker, Amanda E; Klunk, William E; Mattos, Meghan K; Parker, Lisa A; Roberts, J Scott; Schulz, Richard (J Alzheimers Dis, 2016)
The increased use of PET amyloid imaging in clinical research has sparked numerous concerns about whether and how to return such research test results to study participants. Chief among these is the question of how best to disclose amyloid imaging research results to individuals who have cognitive symptoms that could impede comprehension of the information conveyed. We systematically developed and evaluated informational materials for use in pre-test counseling and post-test disclosures of amyloid imaging research results in mild cognitive impairment (MCI). Using simulated sessions, persons with MCI and their family care partners (N = 10 dyads) received fictitious but realistic information regarding brain amyloid status, followed by an explanation of how results impact Alzheimer's disease risk. Satisfaction surveys, comprehension assessments, and focus group data were analyzed to evaluate the materials developed. The majority of persons with MCI and their care partners comprehended and were highly satisfied with the information presented. Focus group data reinforced findings of high satisfaction and included 6 recommendations for practice: 1) offer pre-test counseling, 2) use clear graphics, 3) review participants' own brain images during disclosures, 4) offer take-home materials, 5) call participants post-disclosure to address emerging questions, and 6) communicate seamlessly with primary care providers. Further analysis of focus group data revealed that participants understood the limitations of amyloid imaging, but nevertheless viewed the prospect of learning one's amyloid status as valuable and empowering.
Keywords: Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Brain; Brain Chemistry; Cognitive Dysfunction; Disclosure; Family; Female; Focus Groups; Health Communication; Humans; Male; Middle Aged; Patient Satisfaction; Pilot Projects; Positron-Emission Tomography

Diagnostic Assessment and Management of Dysphagia in Patients with Alzheimer's Disease. - Boccardi, Virginia; Ruggiero, Carmelinda; Patriti, Alberto; Marano, Luigi (J Alzheimers Dis, 2016)
A growing concern in patients affected by Alzheimer's disease (AD) is dysphagia, or swallowing impairment, which leads to malnutrition, dehydration, weight loss, functional decline and fear of eating and drinking, as well as a decrease in the quality of life. Thus the diagnostic assessment of dysphagia in patients with AD is imperative to ensure that they receive effective management, avoiding complications, and reducing comorbidity and mortality in such a growing population. Dysphagia management requires a multidisciplinary approach considering that no single strategy is appropriate for all patients. However, evidence for clinical diagnostic assessment, interventions, and medical management of dysphagia in these patients are still limited: few studies are reporting the evaluation and the management among this group of patients. Here we analyzed the most recent findings in diagnostic assessment and management of swallowing impairment in patients affected by AD.
Keywords: Alzheimer Disease; Deglutition Disorders; Humans

Diet and Inflammation in Alzheimer's Disease and Related Chronic Diseases: A Review. - Gardener, Samantha L; Rainey-Smith, Stephanie R; Martins, Ralph N (J Alzheimers Dis, 2016)
Inflammation is one of the pathological features of the neurodegenerative disease, Alzheimer's disease (AD). A number of additional disorders are likewise associated with a state of chronic inflammation, including obesity, cardiovascular disease, and type-2 diabetes, which are themselves risk factors for AD. Dietary components have been shown to modify the inflammatory process at several steps of the inflammatory pathway. This review aims to evaluate the published literature on the effect of consumption of pro- or anti-inflammatory dietary constituents on the severity of both AD pathology and related chronic diseases, concentrating on the dietary constituents of flavonoids, spices, and fats. Diet-based anti-inflammatory components could lead to the development of potent novel anti-inflammatory compounds for a range of diseases. However, further work is required to fully characterize the therapeutic potential of such compounds, including gaining an understanding of dose-dependent relationships and limiting factors to effectiveness. Nutritional interventions utilizing anti-inflammatory foods may prove to be a valuable asset in not only delaying or preventing the development of age-related neurodegenerative diseases such as AD, but also treating pre-existing conditions including type-2 diabetes, cardiovascular disease, and obesity.
Keywords: Alzheimer Disease; Cardiovascular Diseases; Chronic Disease; Diet; Humans; Inflammation; Neurodegenerative Diseases

Dietary high cholesterol and trace metals in the drinking water increase levels of ABCA1 in the rabbit hippocampus and temporal cortex. - Schreurs, Bernard G; Sparks, D Larry (J Alzheimers Dis, 2016)
BACKGROUND: Cholesterol-fed rabbits have been documented to show increased amyloid-β (Aβ) deposits in the brain that can be exacerbated by the quality of drinking water especially if rabbits drink tap water or distilled water containing copper. One mechanism of cholesterol and Aβ clearance may be through the ATP-binding cassette transporter A1 (ABCA1). OBJECTIVE AND METHODS: Using an ABCA1 antibody, we determined the number of ABCA1-immunopositive neurons in three areas of rabbit brain as a function of feeding 2% cholesterol and providing tap water, distilled water, or distilled water to which aluminum, copper, or zinc was added. RESULTS: The number of neurons with ABCA1 immunoreactivity was increased significantly as a result of dietary cholesterol in the rabbit hippocampus and inferior and superior temporal cortex. The number of neurons with ABCA1 immunoreactivity was further increased in all three areas as a result of cholesterol-fed rabbits drinking tap water or distilled water with copper. Finally, cholesterol-fed rabbits that drank distilled water with aluminum also showed an increased number of ABCA1-immunopositive neurons in inferior and superior temporal cortex. CONCLUSIONS: These data suggest that ABCA1 levels increase in parallel with previously documented increases in Aβ levels as a result of high dietary cholesterol and copper in the drinking water. Addition of aluminum to distilled water may have a similar effect in the temporal cortex. ABCA1 has been proposed as a means of clearing Aβ from the brain and manipulations that increase Aβ also result in an increase of clearance machinery.
Keywords: Aluminum; Alzheimer Disease; Animals; ATP-Binding Cassette Transporters; Brain Chemistry; Cholesterol, Dietary; Copper; Drinking Water; Hippocampus; Male; Neurons; Rabbits; Temporal Lobe; Zinc

Different Expression Patterns of Amyloid-β Protein Precursor Secretases in Human and Mouse Hippocampal Neurons: A Potential Contribution to Species Differences in Neuronal Susceptibility to Amyloid-β Pathogenesis. - Xu, Zhi-Qiang; Huang, Huang; Chen, Ya-Li; Gao, Yun-Ying; Xu, Jun; Marshall, Charles; Cai, Zhi-You; Xiao, Ming (J Alzheimers Dis, 2016)
Extensive loss of hippocampal neurons serves a pathological basis for irreversible cognitive impairment in patients with Alzheimer's disease (AD). However, this characteristic cannot be replicated by transgenic mouse models, and its underlying mechanisms are unclear. Here, we present evidence that different expression patterns of amyloid-β protein precursor (AβPP) secretases in human and mouse hippocampal neurons are a decisive cause of species difference in the susceptibility to Aβ pathogenesis. Cell bodies of both pyramidal and granular neurons did not appear to undergo Aβ deposits in the 10-month-old transgenic mutant human AβPP/presenilin-1 (PS1) mice. They expressed high levels of non-amyloidogenic α-secretase, and its neuroprotective products soluble AβPPα, but low levels of amyloidogenic β-secretase and γ-secretase, and a neurotoxic product, Aβ42 peptide. Unlike those found in the mouse, human hippocampal neuronal cell bodies expressed β-secretase and γ-secretase, but not α-secretase, which could increase Aβ generation, thus undergoing death in response to various pathological conditions. Increased hippocampal neuronal apoptosis at 48 h following local microinjection of α-secretase antibody ADAM10 into the hippocampus of AβPP/PS1 mice further suggests that high α-secretase expression in mouse neuronal cell bodies is a factor in the paucity of neuronal loss in AD-like pathology. Therefore, selective down-regulation of brain α-secretase in transgenic AD models will better replicate the disease spectrum, including decreased brain soluble AβPPα levels and massive neuronal loss in AD patients, and be beneficial for preclinical therapeutic evaluation of AD.
Keywords: ADAM10 Protein; Amyloid beta-Peptides; Amyloid Precursor Protein Secretases; Animals; Antibodies; Aspartic Acid Endopeptidases; Cell Count; Dose-Response Relationship, Drug; Female; Gene Expression Regulation; Hippocampus; Humans; Low Density Lipoprotein Receptor-Related Protein-1; Male; Mice; Mice, Transgenic; Middle Aged; Mutation; Neurons; Peptide Fragments; Presenilin-1; Species Specificity; Time Factors

Different Patterns of Correlation between Grey and White Matter Integrity Account for Behavioral and Psychological Symptoms in Alzheimer's Disease. - Makovac, Elena; Serra, Laura; Spanò, Barbara; Giulietti, Giovanni; Torso, Mario; Cercignani, Mara; Caltagirone, Carlo; Bozzali, Marco (J Alzheimers Dis, 2016)
Behavioral disorders and psychological symptoms (BPSD) in Alzheimer's disease (AD) are known to correlate with grey matter (GM) atrophy and, as shown recently, also with white matter (WM) damage. WM damage and its relationship with GM atrophy are reported in AD, reinforcing the interpretation of the AD pathology in light of a disconnection syndrome. It remains uncertain whether this disconnection might account also for different BPSD observable in AD. Here, we tested the hypothesis of different patterns of association between WM damage of the corpus callosum (CC) and GM atrophy in AD patients exhibiting one of the following BPSD clusters: Mood (i.e., anxiety and depression; ADmood), Frontal (i.e., dishinibition and elation; ADfrontal), and Psychotic (delusions and hallucinations; ADpsychotic) related symptoms, as well as AD patients without BPSD. Overall, this study brings to light the strict relationship between WM alterations in different parts of the CC and GM atrophy in AD patients exhibiting BPSD, supporting the hypothesis that such symptoms are likely to be caused by characteristic patterns of neurodegeneration of WM and GM, rather than being a reactive response to accumulation of cognitive disabilities, and should therefore be regarded as potential markers of diagnostic and prognostic value in AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Atrophy; Brain; Depression; Female; Gray Matter; Hallucinations; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; White Matter

Differential Diagnosis of Dementia with High Levels of Cerebrospinal Fluid Tau Protein. - Grangeon, Lou; Paquet, Claire; Bombois, Stephanie; Quillard-Muraine, Muriel; Martinaud, Olivier; Bourre, Bertrand; Lefaucheur, Romain; Nicolas, Gaël; Dumurgier, Julien; Gerardin, Emmanuel; Jan, Mary; Laplanche, Jean-Louis; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Total Tau concentration in cerebrospinal fluid (CSF) is widely used as a biomarker in the diagnosis of neurodegenerative process primarily in Alzheimer's disease (AD). A particularly high Tau level may indicate AD but may also be associated with Creutzfeldt-Jakob disease (CJD). In such situations little is known about the distribution of differential diagnoses. OBJECTIVE: Our study aimed to describe the different diagnoses encountered in clinical practice for patients with dementia and CSF Tau levels over 1000 pg/ml. We studied the p-Tau/Tau ratio to specify its ability to distinguish AD from CJD. METHODS: Patients (n = 202) with CSF Tau levels over 1000 pg/ml were recruited in three memory clinics in France. All diagnoses were made using the same diagnostic procedure and criteria. RESULTS: Patients were diagnosed with AD (n = 148, 73.2%), mixed dementia (n = 38, 18.8%), CJD, vascular dementia (n = 4, 2.0% for each), Lewy body dementia, and frontotemporal dementia (n = 3, 1.5% for each). Dispersion of CSF Tau levels clearly showed an overlap between all diagnoses. Using the p-Tau/Tau ratio suggestive of CJD (<0.075), all CJD patients were correctly categorized and only two AD patients were miscategorized. This ratio was highly associated with CJD compared to AD (p < 0.0001). CONCLUSION: Our study showed that in clinical practice, extremely high CSF Tau levels are mainly related to diagnosis of AD. CJD patients represent a minority. Our results support a sequential interpretation algorithm for CSF biomarkers in dementia. High CSF Tau levels should alert clinicians to check the p-Tau/Tau ratio to consider a probable diagnosis of CJD.
Keywords: Adult; Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Creutzfeldt-Jakob Syndrome; Dementia, Vascular; Diagnosis, Differential; Female; France; Frontotemporal Dementia; Humans; Lewy Body Disease; Male; Mental Status Schedule; Middle Aged; Phosphorylation; Retrospective Studies; Sex Factors; tau Proteins

Differential Regulation of N-Methyl-D-Aspartate Receptor Subunits is an Early Event in the Actions of Soluble Amyloid-β(1-40) Oligomers on Hippocampal Neurons. - Chang, Lirong; Zhang, Yali; Liu, Jinping; Song, Yizhi; Lv, Angchu; Li, Yan; Zhou, Wei; Yan, Zhen; Almeida, Osborne F X; Wu, Yan (J Alzheimers Dis, 2016)
Synaptic dysfunction during early stages of Alzheimer's disease (AD) is triggered by soluble amyloid-β (Aβ) oligomers that interact with NMDA receptors (NMDARs). We previously showed that Aβ induces synaptic protein loss through NMDARs, albeit through undefined mechanisms. Accordingly, we here examined the contribution of individual NMDAR subunits to synaptotoxicity and demonstrate that Aβ exerts differential effects on the levels and distribution of GluN2A and GluN2B subunits of NMDAR in dendrites. Treatment of cultured hippocampal neurons with Aβ1-40 (10 μM, 1 h) induced a significant increase of dendritic and synaptic GluN2B puncta densities with parallel decreases in the puncta densities of denritic and synaptic pTyr1472-GluN2B. Conversely, Aβ significantly decreased dendritic and synaptic GluN2A and dendritic pTyr1325-GluN2A puncta densities and increased synaptic pTyr1325-GluN2A puncta densities. Unexpectedly, Aβ treatment resulted in a significant reduction of GluN2B and pTyr1472-GluN2B protein levels but did not influence GluN2A and pTyr1325-GluN2A levels. These results show that Aβ exerts complex and distinct regulatory effects on the trafficking and phosphorylation of GluN2A and GluN2B, as well as on their localization within synaptic and non-synaptic sites. Increased understanding of these early events in Aβ-induced synaptic dysfunction is likely to be important for the development of timely preventive and therapeutic interventions.
Keywords: Amyloid beta-Peptides; Animals; Animals, Newborn; Cells, Cultured; Dendrites; Gene Expression Regulation; Hippocampus; Male; Neurons; Peptide Fragments; Phosphorylation; Rats; Rats, Wistar; Receptors, N-Methyl-D-Aspartate

Diminished CRE-Induced Plasticity is Linked to Memory Deficits in Familial Alzheimer's Disease Mice. - Bartolotti, Nancy; Segura, Laura; Lazarov, Orly (J Alzheimers Dis, 2016)
The mechanism underlying impaired learning and memory in Alzheimer's disease is not fully elucidated. The phosphorylation of cyclic-AMP response element binding protein (pCREB) in the hippocampus is thought to be a critical initiating step in the formation of long-term memories. Here, we tested CRE-driven gene expression following learning in mice harboring the familial Alzheimer's disease-linked APPswe/PS1ΔE9 mutations using CRE-β galactosidase reporter. We show that young adult APPswe/PS1ΔE9 mice exhibit impaired recognition memory and reduced levels of pCREB, and its cofactors CREB binding protein (CBP) and p-300 following a learning task, compared to their wild type littermate counterparts. Impairments in learning-induced activation of CREB in these mice are manifested by reduced CRE-driven gene transcription. Importantly, expression of the CRE-driven immediate early gene, Egr-1 (Zif268) is decreased in the CA1 region of the hippocampus. These studies implicate defective CREB-dependent plasticity in the mechanism underlying learning and memory deficits in Alzheimer's disease.
Keywords: Alzheimer Disease; Animals; Cyclic AMP Response Element-Binding Protein; Disease Models, Animal; Hippocampus; Maze Learning; Memory Disorders; Mice; Neuronal Plasticity; Neurons; Phosphorylation

The Disconnection Hypothesis in Alzheimer's Disease Studied Through Multimodal Magnetic Resonance Imaging: Structural, Perfusion, and Diffusion Tensor Imaging. - Lacalle-Aurioles, María; Navas-Sánchez, Francisco Javier; Alemán-Gómez, Yasser; Olazarán, Javier; Guzmán-De-Villoria, Juan Adán; Cruz-Orduña, Isabel; Mateos-Pérez, José María; Desco, Manuel (J Alzheimers Dis, 2016)
According to the so-called disconnection hypothesis, the loss of synaptic inputs from the medial temporal lobes (MTL) in Alzheimer's disease (AD) may lead to reduced activity of target neurons in cortical areas and, consequently, to decreased cerebral blood flow (CBF) in those areas. The aim of this study was to assess whether hypoperfusion in parietotemporal and frontal cortices of patients with mild cognitive impairment who converted to AD (MCI-c) and patients with mild AD is associated with atrophy in the MTL and/or microstructural changes in the white matter (WM) tracts connecting these areas. We assessed these relationships by investigating correlations between CBF in hypoperfused areas, mean cortical thickness in atrophied regions of the MTL, and fractional anisotropy (FA) in WM tracts. In the MCI-c group, a strong correlation was observed between CBF of the superior parietal gyri and FA in the parahippocampal tracts (left: r = 0.90, p <  0.0001; right: r = 0.597, p = 0.024), and between FA in the right parahippocampal tract and the right precuneus (r = 0.551, p = 0.041). No significant correlations between CBF in hypoperfused regions and FA in the WM tract were observed in the AD group. These results suggest an association between perfusion deficits and altered WM tracts in prodromal AD, while microvasculature impairments may have a greater influence in more advanced stages. We did not find correlations between cortical thinning in the medial temporal lobes and decreased FA in the WM tracts of the limbic system in either group.
Keywords: Aged; Alzheimer Disease; Brain; Brain Mapping; Cerebral Angiography; Cerebrovascular Circulation; Cognitive Dysfunction; Diffusion Tensor Imaging; Female; Functional Laterality; Humans; Magnetic Resonance Imaging; Male; Mental Status Schedule; Models, Neurological; Multimodal Imaging; Organ Size; Prospective Studies

Discrepancy in Expression of β-Secretase and Amyloid-β Protein Precursor in Alzheimer-Related Genes in the Rat Medial Temporal Lobe Cortex Following Transient Global Brain Ischemia. - Pluta, Ryszard; Kocki, Janusz; Ułamek-Kozioł, Marzena; Petniak, Alicja; Gil-Kulik, Paulina; Januszewski, Sławomir; Bogucki, Jacek; Jabłoński, Mirosław; Brzozowska, Judyta; Furmaga-Jabłońska, Wanda; Bogucka-Kocka, Anna; Czuczwar, Stanisław J (J Alzheimers Dis, 2016)
Brain ischemia may be causally related with Alzheimer's disease. Presumably, β-secretase and amyloid-β protein precursor gene expression changes may be associated with Alzheimer's disease neuropathology. Consequently, we have examined quantitative changes in both β-secretase and amyloid-β protein precursor genes in the medial temporal lobe cortex with the use of quantitative rtPCR analysis following 10-min global brain ischemia in rats with survival of 2, 7, and 30 days. The greatest significant overexpression of β-secretase gene was noted on the 2nd day, while on days 7-30 the expression of this gene was only modestly downregulated. Amyloid-β protein precursor gene was downregulated on the 2nd day, but on days 7-30 postischemia, there was a significant reverse tendency. Thus, the demonstrated alterations indicate that the considerable changes of expression of β-secretase and amyloid-β protein precursor genes may be connected with a response of neurons in medial temporal lobe cortex to transient global brain ischemia. Finally, the ischemia-induced gene changes may play a key role in a late and slow onset of Alzheimer-type pathology.
Keywords: Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Brain Ischemia; Disease Models, Animal; Down-Regulation; Female; Rats; Rats, Wistar; Temporal Lobe; Time Factors

Distinctive Resting State Network Disruptions Among Alzheimer's Disease, Subcortical Vascular Dementia, and Mixed Dementia Patients. - Kim, Hee Jin; Cha, Jungho; Lee, Jong-Min; Shin, Ji Soo; Jung, Na-Yeon; Kim, Yeo Jin; Choe, Yearn Seong; Lee, Kyung Han; Kim, Sung Tae; Kim, Jae Seung; Lee, Jae Hong; Na, Duk L; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Recent advances in resting-state functional MRI have revealed altered functional networks in Alzheimer's disease (AD), especially those of the default mode network (DMN) and central executive network (CEN). However, few studies have evaluated whether small vessel disease (SVD) or combined amyloid and SVD burdens affect the DMN or CEN. OBJECTIVE: The aim of this study was to evaluate whether SVD or combined amyloid and SVD burdens affect the DMN or CEN. METHODS: In this cross-sectional study, we investigated the resting-state functional connectivity within DMN and CEN in 37 Pittsburgh compound-B (PiB)(+) AD, 37 PiB(-) subcortical vascular dementia (SVaD), 13 mixed dementia patients, and 65 normal controls. RESULTS: When the resting-state DMN of PiB(+) AD and PiB(-) SVaD patients were compared, the PiB(+) AD patients displayed lower functional connectivity in the inferior parietal lobule while the PiB(-) SVaD patients displayed lower functional connectivity in the medial frontal and superior frontal gyri. Compared to the PiB(-) SVaD or PiB(+) AD, the mixed dementia patients displayed lower functional connectivity within the DMN in the posterior cingulate gyrus. When the resting-state CEN connectivity of PiB(+) AD and PiB(-) SVaD patients were compared, the PiB(-) SVaD patients displayed lower functional connectivity in the anterior insular region. Compared to the PiB(-) SVaD or PiB(+) AD, the mixed dementia patients displayed lower functional connectivity within the CEN in the inferior frontal gyrus. CONCLUSIONS: Our findings suggest that in PiB(+) AD and PiB(-) SVaD, there is divergent disruptions in resting-state DMN and CEN. Furthermore, patients with combined amyloid and SVD burdens exhibited more disrupted resting-state DMN and CEN than patients with only amyloid or SVD burden.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Aniline Compounds; Cerebral Cortex; Cross-Sectional Studies; Dementia; Dementia, Vascular; Female; Humans; Image Processing, Computer-Assisted; Male; Middle Aged; Models, Neurological; Neural Pathways; Neuropsychological Tests; Oxygen; Psychiatric Status Rating Scales; Radionuclide Imaging; Rest; Thiazoles

Divergent Longitudinal Propagation of White Matter Degradation in Logopenic and Semantic Variants of Primary Progressive Aphasia. - Tu, Sicong; Leyton, Cristian E; Hodges, John R; Piguet, Olivier; Hornberger, Michael (J Alzheimers Dis, 2016)
BACKGROUND: Clinico-pathological distinction of primary progressive aphasia (PPA) can be challenging at clinic presentation. In particular, cross-sectional neuroimaging signatures across the logopenic (lvPPA) and semantic (svPPA) variants are difficult to establish, with longitudinal profiles showing greater divergence. OBJECTIVE: Assess longitudinal propagation of white matter degradation in lvPPA and svPPA to determine disease progression over time, and whether this reflects distinct underlying pathology. METHOD: A cohort of 27 patients with dementia (12 lvPPA; 15 svPPA) and 12 healthy controls were assessed at baseline and 1-year follow-up on the Addenbrooke's Cognitive Examination-Revised and Sydney Language Battery. Diffusion weighted images were collected at both time-points and analyzed for longitudinal white matter change using DTI-TK and TBSS. RESULTS: LvPPA patients showed a significant decline in naming and repetition, over 1 year, while svPPA patients declined in naming and comprehension. Longitudinal imaging revealed widespread bilateral degradation of white matter tracts in lvPPA over a 1-year period with early involvement of the left posterior inferior longitudinal fasciculus (ILF). SvPPA demonstrated focal left lateralized white matter degradation involving the uncinate fasciculus (UF) and anterior ILF, propagating to the right UF with disease progression. CONCLUSIONS: LvPPA and svPPA cohorts showed distinct longitudinal cognitive and white matter profiles. We propose differences in multi-centric and focal white matter dysfunction in lvPPA and svPPA, respectively, reflect underlying pathological differences. The clinical relevance of white matter degradation and mechanisms underlying disease propagation are discussed.
Keywords: Aged; Analysis of Variance; Aphasia, Primary Progressive; Brain; Cohort Studies; Cross-Sectional Studies; Disease Progression; Female; Humans; Image Processing, Computer-Assisted; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Middle Aged; Names; Neuropsychological Tests; Semantics

Diversity of Cognitive Phenotypes Associated with C9ORF72 Hexanucleotide Expansion. - Gómez-Tortosa, Estrella; Prieto-Jurczynska, Cristina; Serrano, Soledad; Franco-Macías, Emilio; Olivié, Laura; Gallego, Jesús; Guerrero-López, Rosa; Trujillo-Tiebas, María José; Ayuso, Carmen; García Ruiz, Pedro; Pérez-Pérez, Julián; Sainz, María José (J Alzheimers Dis, 2016)
For diagnostic purposes, we screened for the C9ORF72 mutation in a) 162 FTLD cases, and b) 145 cases with other diagnoses but with some frontotemporal features or manifestations previously reported in C9 carriers. Ten cases (onset 50 to 75 years) harbored the expansion: seven had FTLD syndromes (4.3% of total, 11% of familial cases), and three (2%) had a different diagnosis. All positive cases had family history of dementia, psychiatric disease, or ALS, but only 20% of families with mixed FTLD/ALS phenotypes carried the expansion. Language impairment was the most common symptom, followed by behavioral changes, memory deficits, and parkinsonism. C9ORF72 mutation has a low frequency in our dementia series and very diverse clinical manifestations.
Keywords: Adult; Age of Onset; Apolipoprotein E4; Cognition; DNA Repeat Expansion; Family; Female; Follow-Up Studies; Frontotemporal Lobar Degeneration; Genetic Association Studies; Genetic Predisposition to Disease; Genotyping Techniques; Humans; Male; Middle Aged; Prevalence; Proteins; Spain

Dogs with Cognitive Dysfunction as a Spontaneous Model for Early Alzheimer's Disease: A Translational Study of Neuropathological and Inflammatory Markers. - Schütt, Trine; Helboe, Lone; Pedersen, Lars Østergaard; Waldemar, Gunhild; Berendt, Mette; Pedersen, Jan Torleif (J Alzheimers Dis, 2016)
Aged companion dogs with canine cognitive dysfunction (CCD) spontaneously develop varying degrees of progressive cognitive decline and particular neuropathological features correspondent to the changes associated with Alzheimer's disease (AD) in humans. The aim of the present study was to characterize certain aspects of neuropathology and inflammatory markers related to aging and CCD in dogs in comparison with human AD. Fifteen brains from aged dogs with normal cognitive function, mild cognitive impairment, or CCD were investigated and compared with two control brains from young dogs and brain sections from human AD subjects. The neuropathological investigations included evaluation of amyloid-β (Aβ) plaque deposition (N-terminally truncated and pyroglutamyl-modified Aβ included), tau pathology, and inflammatory markers in prefrontal cortex. Cortical Aβ deposition was found to be only of the diffuse subtype as no dense-core or neuritic plaques were found. The Aβ deposition followed a progressive pattern in four maturation stages. Accumulation of the Aβ peptide was also observed in the vessel walls. Both immunohistochemically and biochemically measured levels of Aβ pathology in prefrontal cortex showed a consistent positive correlation to age but not to cognitive deficit severity. No evidence of neurofibrillary tau pathology was found. The level of pro-inflammatory cytokines was generally low and showed no significant association to cognitive status. The findings of the present study support the senescent dog with spontaneous cognitive dysfunction as a valuable non-transgenic model for further investigations of the molecular events involved in the neurodegenerative processes associated with aging and early stage AD, especially the Aβ-related pathology.
Keywords: Aging; Alzheimer Disease; Animals; Brain; Cognitive Dysfunction; Cytokines; Denmark; Disease Models, Animal; Disease Progression; Dog Diseases; Dogs; Female; Humans; Immunohistochemistry; Longitudinal Studies; Male; Plaque, Amyloid; Severity of Illness Index; Species Specificity; tau Proteins; Translational Medical Research

Dose-Dependent Neuroprotection and Neurotoxicity of Simvastatin through Reduction of Farnesyl Pyrophosphate in Mice Treated with Intracerebroventricular Injection of Aβ 1-42. - Jin, Huafeng; Chen, Tingting; Li, Guoxi; Wang, Conghui; Zhang, Baofeng; Cao, Xinyuan; Sha, Sha; Wan, Qi; Chen, Ling (J Alzheimers Dis, 2016)
BACKGROUND: Simvastatin (SV) has been reported to improve dementia and slow progression of Alzheimer's disease (AD), however there are conflicting reports. OBJECTIVE & METHODS: Intracerebroventricular injection of aggregated Aβ1-42 in mice (Aβ1-42-mice) caused spatial cognitive deficits, long-term potentiation (LTP) impairment, and death of hippocampal pyramidal cells. The present study focused on exploring the dose-dependent effects of SV (10-80 mg/kg) on Aβ1-42-impaired spatial memory and the underlying mechanisms. RESULTS: The treatment of Aβ1-42-mice with SV for continuous 15 days could attenuate the spatial cognitive deficits and recover the LTP induction in a "U" type dose-dependent manner. The death of pyramidal cells in Aβ1-42-mice was significantly reduced by the SV-treatment at 20 mg/kg, but not at a dose of 10 or 40 mg/kg, even was aggravated at a dose of 80 mg/kg. Hippocampal NMDA receptor (NMDAr) NR2B phosphorylation (phospho-NR2B) was elevated in Aβ1-42-mice, which was further dose-dependently increased by SV-treatment. Replenishment of isoprenoid farnesyl pyrophosphate (FPP) by applying farnesol (FOH) could abolish the SV-increased phospho-NR2B in Aβ1-42-mice, but had no effect on the Aβ1-42-enhanced phospho-NR2B. NMDAr antagonist blocked the neurotoxicity of Aβ1-42 and SV (80 mg/kg) in Aβ1-42-mice, whereas FOH only inhibited SV (80 mg/kg)-neurotoxicity. The SV-treatment in Aβ1-42-mice corrected the decrease in hippocampal Akt phosphorylation. The PI3K inhibitor abolished the SV (20 mg/kg)-neuroprotection in Aβ1-42-mice. CONCLUSION: SV-treatment in Aβ1-42-mice exerts dose-dependent neuroprotection and neurotoxicity by reducing FPP to enhance the phosphorylation of NR2B and Akt.
Keywords: Amyloid beta-Peptides; Animals; Dose-Response Relationship, Drug; Hippocampus; Injections, Intraventricular; Male; Maze Learning; Mice; Neuroprotective Agents; Peptide Fragments; Phosphorylation; Polyisoprenyl Phosphates; Receptors, N-Methyl-D-Aspartate; Sesquiterpenes; Simvastatin; Spatial Memory

Dysregulation and diagnostic potential of microRNA in Alzheimer's disease. - Pan, Yaoqian; Liu, Ruizhu; Terpstra, Erin; Wang, Yanqing; Qiao, Fangfang; Wang, Jin; Tong, Yigang; Pan, Bo (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is one of the most common neurodegenerative diseases and is considered to be the main cause of cognitive impairment in elderly people. The major symptom of AD is progressive dementia that eventually results in dysfunction of daily life. Due to the fact that AD has a long period of incubation before clinical symptoms emerge, the available therapeutic treatments can only improve the symptoms but not delay the progression of AD. Therefore, there is an urgent need to explore effective diagnostic approaches to catch and better treat the disease before clinical symptoms appear. Recent research revealed that abnormal expression of certain miRNA could have a crucial role in the pathological process of neurodegenerative disease including AD. Furthermore, given that AD patients show increased level of miRNAs in the blood and cerebrospinal fluid, miRNAs are considered promising non-invasive candidates for AD diagnosis and prognosis. Here, we reviewed the current research related to implications of miRNAs during the development of AD, summarized of actively used approaches to identifying potential miRNA biomarkers in body fluids, and discussed the diagnostic potential of microRNAs as biomarkers for AD.
Keywords: Aged; Alzheimer Disease; Biomarkers; Disease Progression; Humans; MicroRNAs; Prognosis

Early in vivo Effects of the Human Mutant Amyloid-β Protein Precursor (hAβPPSwInd) on the Mouse Olfactory Bulb. - Rusznák, Zoltán; Kim, Woojin Scott; Hsiao, Jen-Hsiang T; Halliday, Glenda M; Paxinos, George; Fu, YuHong (J Alzheimers Dis, 2016)
The amyloid-β protein precursor (AβPP) has long been linked to Alzheimer's disease (AD). Using J20 mice, which express human AβPP with Swedish and Indiana mutations, we studied early pathological changes in the olfactory bulb. The presence of AβPP/amyloid-β (Aβ) was examined in mice aged 3 months (before the onset of hippocampal Aβ deposition) and over 5 months (when hippocampal Aβ deposits are present). The number of neurons, non-neurons, and proliferating cells was assessed using the isotropic fractionator method. Our results demonstrate that although AβPP is overexpressed in some of the mitral cells, widespread Aβ deposition and microglia aggregates are not prevalent in the olfactory bulb. The olfactory bulbs of the younger J20 group harbored significantly fewer neurons than those of the age-matched wild-type mice (5.57±0.13 million versus 6.59±0.36 million neurons; p = 0.011). In contrast, the number of proliferating cells was higher in the young J20 than in the wild-type group (i.e., 6617±425 versus 4455±623 cells; p = 0.011). A significant increase in neurogenic activity was also observed in the younger J20 olfactory bulb. In conclusion, our results indicate that (1) neurons participating in the mouse olfactory function overexpress AβPP; (2) the cellular composition of the young J20 olfactory bulb is different from that of wild-type littermates; (3) these differences may reflect altered neurogenic activity and/or delayed development of the J20 olfactory system; and (4) AβPP/Aβ-associated pathological changes that take place in the J20 hippocampus and olfactory bulb are not identical.
Keywords: Age Factors; Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cell Proliferation; Disease Models, Animal; Gene Expression Regulation; Humans; Ki-67 Antigen; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Nerve Tissue Proteins; Neurogenesis; Neurons; Olfactory Bulb; Piriform Cortex

Early-Life Exposure to Lead (Pb) Alters the Expression of microRNA that Target Proteins Associated with Alzheimer's Disease. - Masoud, Anwar M; Bihaqi, Syed W; Machan, Jason T; Zawia, Nasser H; Renehan, William E (J Alzheimers Dis, 2016)
There is a growing recognition of the impact of environmental toxins on the epigenetic regulation of gene expression, including the genes that play a critical role in neural development, neural function, and neurodegeneration. We have shown previously that exposure to the heavy metal lead (Pb) in early life results in a latent over-expression of AD-related proteins in rodents and primates. The present study provides evidence that early postnatal exposure to Pb also alters the expression of select miRNA. Mice were exposed to 0.2% Pb acetate from Postnatal Day 1 (PND 1, first 24 h after birth) to PND 20 via their mother's milk. Brain tissue was harvested at PND 20, 180, or 700, and miRNA were isolated and quantified by qPCR. This exposure produced a transient increase (relative to control) in the expression of miR-106b (binds to AβPP mRNA), miR-29b (targets the mRNA for the transcription factor SP1) and two miRNAs (miR-29b and miR-132) that have the ability to inhibit translation of proteins involved in promoter methylation. The expression of miR-106b decreased over time in the Pb-exposed animals and was significantly less than the levels exhibited by the control animals at PND700. The level of miR-124, which binds to SP1 mRNA, was also reduced (relative to controls) at PND700. In summary, we show that exposure to the heavy metal Pb in early life has a significant impact on the short- and long-term expression of miRNA that target epigenetic mediators and neurotoxic proteins.
Keywords: Age Factors; Amyloid beta-Protein Precursor; Animals; Animals, Newborn; Disease Models, Animal; Dose-Response Relationship, Drug; Female; Gene Expression Regulation, Developmental; Lead; Male; Mice; Mice, Inbred C57BL; MicroRNAs; Pregnancy; RNA, Messenger; Sp1 Transcription Factor

Economic Analysis of Formal Care, Informal Care, and Productivity Losses in Primary Care Patients who Screened Positive for Dementia in Germany. - Michalowsky, Bernhard; Thyrian, Jochen René; Eichler, Tilly; Hertel, Johannes; Wucherer, Diana; Flessa, Steffen; Hoffmann, Wolfgang (J Alzheimers Dis, 2016)
BACKGROUND: The majority of people with dementia (PwD) live at home and require professional formal care and informal care that is generally provided by close relatives. OBJECTIVE: To determine the utilization and costs of formal and informal care for PwD, indirect costs because of productivity losses of caregivers, and the associations between cost, socio-demographic and clinical variables. METHODS: The analysis includes the data of 262 community-dwelling PwD and their caregivers. Socio-demographics, clinical variables, and the utilization of formal care were assessed within the baseline assessment. To evaluate informal care costs, the Resource Utilization in Dementia (RUD) questionnaire was used. Costs were calculated from a social perspective. Associations were evaluated using multiple linear and logistic regression models. RESULTS: Formal care services were utilized less (26.3%) than informal care (85.1%), resulting in a cost ratio of one to ten(1,646 €; 16,473 €, respectively). In total, 29% of caregivers were employed, and every seventh (14.3%) experienced productivity losses, which corresponded to 1,258 € annually. Whereas increasing deficits in daily living activities were associated with higher formal and higher informal costs, living alone was significantly associated with higher formal care costs and the employment of a caregiver was associated with lower informal care costs. CONCLUSION: Informal care contributes the most to total care costs. Living alone is a major cost driver for formal costs because of the lower availability of potential informal care. The availability of informal care is limited and productivity losses are increased when a caregiver is employed.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Caregivers; Cost of Illness; Cross-Sectional Studies; Dementia; Female; Germany; Health Care Costs; Home Care Services; Humans; Male; Patient Care; Sensitivity and Specificity; Surveys and Questionnaires

Effect of Anserine/Carnosine Supplementation on Verbal Episodic Memory in Elderly People. - Hisatsune, Tatsuhiro; Kaneko, Jun; Kurashige, Hiroki; Cao, Yuan; Satsu, Hideo; Totsuka, Mamoru; Katakura, Yoshinori; Imabayashi, Etsuko; Matsuda, Hiroshi (J Alzheimers Dis, 2016)
Our goal in this study was to determine whether or not anserine/carnosine supplementation (ACS) is capable of preserving cognitive function of elderly people. In a double-blind randomized controlled trial, volunteers were randomly assigned to an ACS or placebo group at a 1:1 ratio. The ACS group took 1.0 g of an anserine/carnosine (3:1) formula daily for 3 months. Participants were evaluated by psychological tests before and after the 3-month supplementation period. Thirty-nine healthy elderly volunteers (60-78 years old) completed the follow-up tests. Among the tests, delayed recall verbal memory assessed by the Wechsler Memory Scale-Logical Memory showed significant preservation in the ACS group, compared to the placebo group (p = 0.0128). Blood analysis revealed a decreased secretion of inflammatory cytokines, including CCL-2 and IL-8, in the ACS group. MRI analysis using arterial spin labeling showed a suppression in the age-related decline in brain blood flow in the posterior cingulate cortex area in the ACS group, compared to the placebo group (p = 0.0248). In another randomized controlled trial, delayed recall verbal memory showed significant preservation in the ACS group, compared to the placebo group (p = 0.0202). These results collectively suggest that ACS may preserve verbal episodic memory and brain perfusion in elderly people, although further study is needed.
Keywords: Adult; Aged; Aging; Anserine; Brain; Carnosine; Cytokines; Dietary Supplements; Double-Blind Method; Female; Gene Expression Regulation; Humans; Image Processing, Computer-Assisted; Male; Memory, Episodic; Middle Aged; Neuropsychological Tests; Oligonucleotide Array Sequence Analysis; Verbal Learning

Effect of Early Referral to Specialist in Dementia on Institutionalization and Functional Decline: Findings from a Population-Based Study. - Pimouguet, Clément; Le-Goff, Mélanie; Rizzuto, Debora; Berr, Claudine; Leffondré, Karen; Pérès, Karine; Dartigues, Jean François; Helmer, Catherine (J Alzheimers Dis, 2016)
BACKGROUND: Although early diagnosis has been hypothesized to benefit both patients and caregivers, until now studies evaluating the effect of early dementia diagnosis are lacking. OBJECTIVE: To investigate the influence of early specialist referral for dementia on the risk of institutionalization and functional decline in Activity of Daily Living (ADL). METHODS: Incident dementia cases were screened in a prospective population-based cohort, the Three-City Study, and initial specialist consultation for cognitive complaint was assessed at dementia diagnosis. Proportional hazard regression and illness-death models were used to test the association between specialist referral and, respectively, institutionalization and functional decline. RESULTS: Only one third of the incident individuals with dementia had consulted a specialist for cognitive problems early (36%). After adjustment on potential confounders (including cognitive and functional decline) and competing risk of death, participants who had consulted a specialist early in the disease course presented a higher rate of being institutionalized than those who did not (Hazard Ratio = 2.00, 95% Confidence Interval (CI): 1.09- 3.64). But early specialist referral was not associated with further functional decline (HR = 1.09, 95% CI: 0.71- 1.67). CONCLUSIONS: Early specialist referral in dementia is associated with increased risk of institutionalization but not with functional decline in ADL. These findings suggest that early care referral in dementia may be a marker of concern for patients and/or caregivers; subsequent medical and social care could be suboptimal or inappropriate to allow patients to stay longer at home.
Keywords: Activities of Daily Living; Cognition Disorders; Community Health Planning; Dementia; Disability Evaluation; Female; Finland; Follow-Up Studies; Humans; Institutionalization; Male; Psychiatric Status Rating Scales; Referral and Consultation; Specialization

The Effects of Latrepirdine on Amyloid-β Aggregation and Toxicity. - Porter, Tenielle; Bharadwaj, Prashant; Groth, David; Paxman, Adrian; Laws, Simon M; Martins, Ralph N; Verdile, Giuseppe (J Alzheimers Dis, 2016)
Latrepirdine (Dimebon) has been demonstrated to be a neuroprotective and cognition improving agent in neurodegenerative diseases that feature protein aggregation and deposition, such as Alzheimer's disease (AD). The accumulation of amyloid-β (Aβ) protein aggregates is a key event in the neurodegenerative process in AD. This study explores if latrepirdine modulation of protein aggregation contributes to its neuroprotective mechanism of action. Assessment of neuronal cell death showed that there was a significant reduction in lactate dehydrogenase release at an equimolar ratio of Aβ:latrepirdine and with lower concentrations of latrepirdine. The ability of latrepirdine to alter the formation of Aβ42 aggregates was assessed by thioflavin-T fluorescence, western immunoblotting and atomic force microscopy (AFM). Despite showing a reduction in thioflavin-T fluorescence with latrepirdine treatment, indicating a decrease in aggregation, immunoblotting and AFM showed a modest increase in both the formation and size of Aβ aggregates. The discrepancies between thioflavin-T and the other assays are consistent with previous evidence that cyclic molecules can interfere with thioflavin-T binding of amyloid protein preparations. The ability of latrepirdine to modulate Aβ aggregation appears to be independent of its neuroprotective effects, and is unlikely to be a mechanism by which latrepirdine offers protection. This study investigates the effect of latrepirdine on Aβ aggregation, and presents evidence suggesting that caution should be applied in the use of thioflavin-T fluorescence based assays as a method for screening compounds for protein aggregation altering properties.
Keywords: Amyloid beta-Peptides; Analysis of Variance; Antipsychotic Agents; Cell Line, Tumor; Dose-Response Relationship, Drug; Drug Interactions; Humans; Indoles; L-Lactate Dehydrogenase; Microscopy, Atomic Force; Neuroblastoma; Peptide Fragments; Protein Aggregates

Efficacy and Safety of ABT-126 in Subjects with Mild-to-Moderate Alzheimer's Disease on Stable Doses of Acetylcholinesterase Inhibitors: A Randomized, Double-Blind, Placebo-Controlled Study. - Florian, Hana; Meier, Andreas; Gauthier, Serge; Lipschitz, Stanley; Lin, Yunzhi; Tang, Qi; Othman, Ahmed A; Robieson, Weining Z; Gault, Laura M (J Alzheimers Dis, 2016)
BACKGROUND: ABT-126 is a potent, selective α7 nicotinic acetylcholine receptor agonist with putative procognitive effects as a monotherapy in treating Alzheimer's disease (AD). OBJECTIVE: This randomized, double-blind, placebo-controlled multicenter study (NCT01549834) investigated the efficacy and safety of ABT-126 in subjects with mild-to-moderate AD who were taking stable doses of acetylcholinesterase inhibitors (AChEIs). METHODS: Subjects received 25 mg ABT-126 (n = 143), 75 mg ABT-126 (n = 145), or placebo (n = 146) once daily for 24 weeks. Subjects who completed the 24-week double-blind study were eligible to enroll in a 28-week open-label extension study (NCT01690195) and received 75 mg ABT-126 daily. The primary efficacy endpoint was the change from baseline to week 24 in the 11-item total score of the Alzheimer's Disease Assessment Scale- Cognitive Subscale (ADAS-Cog). RESULTS: Neither dose of ABT-126 demonstrated significant improvement compared with placebo in the primary efficacy endpoint. However, 25 mg ABT-126 demonstrated significant improvement compared with placebo in ADAS-Cog scores at week 4 (least squares mean difference, -1.21; standard error, 0.51; p <  0.010, one-sided); 75 mg ABT-126 did not demonstrate significant improvements in ADAS-Cog scores compared with placebo at any time point. A treatment effect was not observed for any secondary efficacy measures of cognition, function, or global improvement. ABT-126 was generally well tolerated; the most common adverse events were agitation, constipation, diarrhea, fall, and headache. CONCLUSIONS: Overall, the efficacy profile of ABT-126 did not warrant further development as add-on therapy to AChEIs to treat mild-to-moderate AD.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cholinesterase Inhibitors; Disease Progression; Dose-Response Relationship, Drug; Double-Blind Method; Female; Humans; Indans; International Cooperation; Male; Medication Adherence; Middle Aged; Piperidines; Psychiatric Status Rating Scales; Treatment Outcome

Efficacy and Safety of MMFS-01, a Synapse Density Enhancer, for Treating Cognitive Impairment in Older Adults: A Randomized, Double-Blind, Placebo-Controlled Trial. - Liu, Guosong; Weinger, Jason G; Lu, Zhong-Lin; Xue, Feng; Sadeghpour, Safa (J Alzheimers Dis, 2016)
BACKGROUND: Cognitive impairment is a major problem in elderly, affecting quality of life. Pre-clinical studies show that MMFS-01, a synapse density enhancer, is effective at reversing cognitive decline in aging rodents. OBJECTIVE: Since brain atrophy during aging is strongly associated with both cognitive decline and sleep disorder, we evaluated the efficacy of MMFS-01 in its ability to reverse cognitive impairment and improve sleep. METHODS: We conducted a randomized, double-blind, placebo-controlled, parallel-designed trial in older adult subjects (age 50-70) with cognitive impairment. Subjects were treated with MMFS-01 (n = 23) or placebo (n = 21) for 12 weeks and cognitive ability, sleep quality, and emotion were evaluated. Overall cognitive ability was determined by a composite score of tests in four major cognitive domains. RESULTS: With MMFS-01 treatment, overall cognitive ability improved significantly relative to placebo (p = 0.003; Cohen's d = 0.91). Cognitive fluctuation was also reduced. The study population had more severe executive function deficits than age-matched controls from normative data and MMFS-01 treatment nearly restored their impaired executive function, demonstrating that MMFS-01 may be clinically significant. Due to the strong placebo effects on sleep and anxiety, the effects of MMFS-01 on sleep and anxiety could not be determined. CONCLUSIONS: The current study demonstrates the potential of MMFS-01 for treating cognitive impairment in older adults.
Keywords: Aged; Anxiety; Butyrates; Cognition; Cognition Disorders; Double-Blind Method; Emotions; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Nootropic Agents; Sleep; Synapses; Treatment Outcome

Efficacy and Safety of Sustained Release Donepezil High Dose versus Immediate Release Donepezil Standard Dose in Japanese Patients with Severe Alzheimer's Disease: A Randomized, Double-Blind Trial. - Homma, Akira; Atarashi, Hirotsugu; Kubota, Naoki; Nakai, Kenya; Takase, Takao (J Alzheimers Dis, 2016)
BACKGROUND: Donepezil is an established treatment for mild, moderate, and severe Alzheimer's disease (AD). An international study demonstrated superior efficacy of sustained release (SR) 23 mg/day donepezil over immediate release (IR) 10 mg/day donepezil for cognitive function, but not global function in moderate-to-severe AD. OBJECTIVE: To demonstrate the superiority of SR 23 mg/day donepezil over IR 10 mg/day donepezil in Japanese patients with severe AD (SAD). METHODS: In this multicenter, randomized, double-blind, parallel-group study, Japanese outpatients with SAD were randomly assigned to continue IR 10 mg/day or switch to SR 23 mg/day for 24 weeks. Endpoints included the Severe Impairment Battery (SIB), Clinician's Interview-Based Impression of Change Plus Caregiver Input (CIBIC-plus), and safety. RESULTS: Overall, 166 and 185 patients were randomized to receive IR 10 mg/day and SR 23 mg/day, respectively. SR 23 mg/day was not statistically superior to IR 10 mg/day by SIB (least squares mean difference [LSMD]: 0.0; 95% confidence interval [CI]: -1.7, 1.8; p = 0.981) or CIBIC-plus (LSMD: 0.2; 95% CI: 0.0, 0.4; p = 0.080). Common adverse events in the SR 23 mg group were decreased appetite, vomiting, diarrhea, and contusion. Safety findings were consistent with known safety profiles of donepezil. CONCLUSION: SR 23 mg/day donepezil was not superior to IR 10 mg/day donepezil regarding the efficacy endpoints for Japanese SAD. Considering that a 10 mg/day dose is approved for SAD in Japan, the present findings suggest that IR 10 mg/day donepezil is the optimal dosage for Japanese patients with SAD.
Keywords: Aged; Alzheimer Disease; Cholinesterase Inhibitors; Delayed-Action Preparations; Double-Blind Method; Female; Humans; Indans; Japan; Male; Mental Status Schedule; Nootropic Agents; Outpatients; Piperidines; Psychiatric Status Rating Scales; Severity of Illness Index; Treatment Outcome

Empirically Defining Trajectories of Late-Life Cognitive and Functional Decline. - Hochstetler, Helen; Trzepacz, Paula T; Wang, Shufang; Yu, Peng; Case, Michael; Henley, David B; Degenhardt, Elisabeth; Leoutsakos, Jeannie-Marie; Lyketsos, Constantine G (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) is associated with variable cognitive and functional decline, and it is difficult to predict who will develop the disease and how they will progress. OBJECTIVE: This exploratory study aimed to define latent classes from participants in the Alzheimer's Disease Neuroimaging Initiative (ADNI) database who had similar growth patterns of both cognitive and functional change using Growth Mixture Modeling (GMM), identify characteristics associated with those trajectories, and develop a decision tree using clinical predictors to determine which trajectory, as determined by GMM, individuals will most likely follow. METHODS: We used ADNI early mild cognitive impairment (EMCI), late MCI (LMCI), AD dementia, and healthy control (HC) participants with known amyloid-β status and follow-up assessments on the Alzheimer's Disease Assessment Scale - Cognitive Subscale or the Functional Activities Questionnaire (FAQ) up to 24 months postbaseline. GMM defined trajectories. Classification and Regression Tree (CART) used certain baseline variables to predict likely trajectory path. RESULTS: GMM identified three trajectory classes (C): C1 (n = 162, 13.6%) highest baseline impairment and steepest pattern of cognitive/functional decline; C3 (n = 819, 68.7%) lowest baseline impairment and minimal change on both; C2 (n = 211, 17.7%) intermediate pattern, worsening on both, but less steep than C1. C3 had fewer amyloid- or apolipoprotein-E ɛ4 (APOE4) positive and more healthy controls (HC) or EMCI cases. CART analysis identified two decision nodes using the FAQ to predict likely class with 82.3% estimated accuracy. CONCLUSIONS: Cognitive/functional change followed three trajectories with greater baseline impairment and amyloid and APOE4 positivity associated with greater progression. FAQ may predict trajectory class.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Apolipoprotein E4; Cognition Disorders; Databases, Factual; Dementia; Disease Progression; Female; Follow-Up Studies; Humans; Male; Middle Aged; Neuroimaging; Neuropsychological Tests; Surveys and Questionnaires

Enalapril Alone or Co-Administered with Losartan Rescues Cerebrovascular Dysfunction, but not Mnemonic Deficits or Amyloidosis in a Mouse Model of Alzheimer's Disease. - Ongali, Brice; Nicolakakis, Nektaria; Tong, Xing-Kang; Aboulkassim, Tahar; Imboden, Hans; Hamel, Edith (J Alzheimers Dis, 2016)
The co-administration of angiotensin converting enzyme inhibitors (ACEi) and angiotensin II (AngII) receptor blockers (ARB) that bind angiotensin type 1 receptors (AT1R) may protect from Alzheimer's disease (AD) better than each treatment taken alone. We tested the curative potential of the non brain-penetrant ACEi enalapril (3 mg/kg/day) administered for 3 months either alone or in combination with the brain penetrant ARB losartan (10 mg/kg/day) in aged (∼15 months) transgenic mice overexpressing a mutated form of the human amyloid-β protein precursor (AβPP, thereafter APP mice). We studied cerebrovascular function, protein levels of oxidative stress markers (superoxide dismutases SOD1, SOD2 and the NADPH oxidase subunit p67phox), amyloid-β (Aβ) pathology, astrogliosis, cholinergic innervation, AT1R and angiotensin IV receptor (AT4R) levels, together with cognitive performance. Both treatments normalized cerebrovascular reactivity and p67phox protein levels, but they did not reduce the cerebrovascular levels of SOD1. Combined treatment normalized cerebrovascular SOD2 levels, significantly attenuated astrogliosis, but did not reduce the increased levels of cerebrovascular AT1R. Yet, combined therapy enhanced thioflavin-S labeled Aβ plaque burden, a tendency not significant when Aβ1 - 42 plaque load was considered. None of the treatments rescued cognitive deficits, cortical AT4R or cholinergic innervation. We conclude that both treatments normalized cerebrovascular function by inhibiting the AngII-induced oxidative stress cascade, and that the positive effects of the combined therapy on astrogliosis were likely due to the ability of losartan to enter brain parenchyma. However, enalapril did not potentiate, and may even dampen, the reported cognitive benefits of losartan, raising caution when selecting the most appropriate antihypertensive therapy in AD patients.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloidosis; Analysis of Variance; Animals; Antihypertensive Agents; Cerebrovascular Disorders; Cholinesterases; Disease Models, Animal; Drug Combinations; Enalapril; Female; Glial Fibrillary Acidic Protein; Humans; Losartan; Male; Maze Learning; Memory Disorders; Mice; Mice, Transgenic; Mutation

Evaluation of Cerebrospinal Fluid Assay Variability in Alzheimer's Disease. - White, Matthew T; Shaw, Leslie M; Xie, Sharon X (J Alzheimers Dis, 2016)
Studies of cerebrospinal fluid (CSF) biomarkers in Alzheimer's disease (AD) have indicated that much of the variability observed in the biomarkers may be due to measurement error. Biomarkers are often obtained with measurement error, which may make the diagnostic biomarker appear less effective than it truly is. In the Alzheimer's Disease Neuroimaging Initiative (ADNI) database, technical replicates of CSF biomarkers are available; the National Alzheimer's Coordinating Center database contains longitudinal replicates of CSF biomarkers. We focus on the area under the receiver operating characteristic curve (AUC) as the measure of diagnostic effectiveness for differentiating AD from normal cognition using CSF biomarkers and compare AUC estimates obtained by a more standard, naïve method (which uses a single observation per subject and ignores measurement error) to a maximum likelihood (ML) based method (which uses all replicates per subject and adjusts for measurement error). The choice of analysis method depends upon the noise to signal ratio (i.e., the magnitude of the measurement error variability relative to the true biomarker variability); moderate to high ratios may significantly bias the naïve AUC estimate, and the ML-based method would be preferred. The noise to signal ratios were low for the ADNI biomarkers but high for the tTau and pTau biomarkers in NACC. Correspondingly, the naïve and ML-based AUC estimates were nearly identical in the ADNI data but dissimilar for the tTau and pTau biomarkers in the NACC data. Therefore, using the naïve method is adequate for analysis of CSF biomarkers in the ADNI study, but the ML method is recommended for the NACC data.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Area Under Curve; Biomarkers; Databases, Factual; Female; Humans; Likelihood Functions; Male; Peptide Fragments; Phosphorylation; ROC Curve; tau Proteins

The Evolution of Caregiver Burden in Frontotemporal Dementia with and without Amyotrophic Lateral Sclerosis. - Hsieh, Sharpley; Leyton, Cristian E; Caga, Jashelle; Flanagan, Emma; Kaizik, Cassandra; O'Connor, Claire M; Kiernan, Matthew C; Hodges, John R; Piguet, Olivier; Mioshi, Eneida (J Alzheimers Dis, 2016)
BACKGROUND AND AIMS: Frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) represent a disease spectrum. Caregiver burden in subtypes of FTD has not yet been directly compared with those patients who have co-existent FTD and ALS (ALSFTD). METHOD: Perceived caregiver burden was evaluated using the short Zarit Burden Interview (ZBI) in patients with behavioral-variant FTD (bvFTD, n = 21), semantic dementia (SD, n = 18), and ALSFTD (n = 15) at the initial clinical presentation and follow-up assessments. The Mini-Addenbrooke's Cognitive Examination (M-ACE) and the Motor Neuron Disease Behaviour Scale (MiND-B) were also used. Linear mixed effects models examined longitudinal changes on the ZBI, M-ACE, and MiND-B across groups. RESULTS: Burden at baseline was highest for the bvFTD group. Longitudinally, perceived burden increased for the SD and ALSFTD groups whereas in bvFTD, the level of burden which was high at baseline and remained high with disease progression. The severity of abnormal behaviors at baseline, as assessed by the MiND-B, correlated with baseline levels of caregiver burden and further accounted for 23% of the variance in caregiver burden at clinical follow-up. CONCLUSIONS: The trajectory of perceived burden differs across the FTD-ALS spectrum, with SD and ALSFTD caregivers demonstrating an increased burden that develops over time, compared to a persistently high level for bvFTD caregivers, evident throughout the disease course. The evolution of burden in these three syndromes likely reflects the initial presentation and clinical characterization that develops with time. Psycho-education programs for caregivers, which provide better coping strategies for challenging behaviors, may reduce levels of burden experienced with disease progression.
Keywords: Adaptation, Psychological; Aged; Amyotrophic Lateral Sclerosis; Analysis of Variance; Caregivers; Case-Control Studies; Cost of Illness; Disease Progression; Female; Frontotemporal Dementia; Humans; Interviews as Topic; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Surveys and Questionnaires

Fibrillar Amyloid-β Accumulation Triggers an Inflammatory Mechanism Leading to Hyperphosphorylation of the Carboxyl-Terminal End of Tau Polypeptide in the Hippocampal Formation of the 3×Tg-AD Transgenic Mouse. - Ontiveros-Torres, Miguel Ángel; Labra-Barrios, María Luisa; Díaz-Cintra, Sofía; Aguilar-Vázquez, Azucena Ruth; Moreno-Campuzano, Samadhi; Flores-Rodríguez, Paola; Luna-Herrera, Claudia; Mena, Raúl; Perry, George; Florán-Garduño, Benjamín; Luna-Muñoz, José; Luna-Arias, Juan Pedro (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a degenerative and irreversible disorder whose progressiveness is dependent on age. It is histopathologically characterized by the massive accumulation of insoluble forms of tau and amyloid-β (Aβ) asneurofibrillary tangles and neuritic plaques, respectively. Many studies have documented that these two polypeptides suffer several posttranslational modifications employing postmortem tissue sections from brains of patients with AD. In order to elucidate the molecular mechanisms underlying the posttranslational modifications of key players in this disease, including Aβ and tau, several transgenic mouse models have been developed. One of these models is the 3×Tg-AD transgenic mouse, carrying three transgenes encoding APPSWE, S1M146V, and TauP301L proteins. To further characterize this transgenicmouse, we determined the accumulation of fibrillar Aβ as a function of age in relation to the hyperphosphorylation patterns of TauP301L at both its N- and C-terminus in the hippocampal formation by immunofluorescence and confocal microscopy. Moreover, we searched for the expression of activated protein kinases and mediators of inflammation by western blot of wholeprotein extracts from hippocampal tissue sections since 3 to 28 months as well. Our results indicate that the presence of fibrillar Aβ deposits correlates with a significant activation of astrocytes and microglia in subiculum and CA1 regions of hippocampus. Accordingly, we also observed a significant increase in the expression of TNF-α associated to neuritic plaques and glial cells. Importantly, there is an overexpression of the stress activated protein kinases SAPK/JNK and Cdk-5 in pyramidal neurons, which might phosphorylate several residues at the C-terminus of TauP301L. Therefore, the accumulation of Aβ oligomers results in an inflammatory environment that upregulates kinases involved in hyperphosphorylation of TauP301L polypeptide.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid beta-Peptides; Animals; Disease Models, Animal; Female; Hippocampus; Humans; Male; Mice, Inbred C57BL; Mice, Transgenic; Neuroglia; Phosphorylation; Plaque, Amyloid; Presenilin-1; Pyramidal Cells; tau Proteins

Fluoxetine Treatment Induces Seizure Behavior and Premature Death in APPswe/PS1dE9 Mice. - Sierksma, Annerieke S R; de Nijs, Laurence; Hoogland, Govert; Vanmierlo, Tim; van Leeuwen, Fred W; Rutten, Bart P F; Steinbusch, Harry W M; Prickaerts, Jos; van den Hove, Daniel L A (J Alzheimers Dis, 2016)
Treatment of Alzheimer's disease (AD) patients with the antidepressant fluoxetine is known to improve memory and cognitive function. However, the mechanisms underlying these effects are largely unknown. To unravel these mechanisms, we aimed to treat APPswe/PS1dE9 mice with fluoxetine. Unexpectedly, with time, an increased number of animals displayed seizure behavior and died. Although spontaneous behavioral seizures have been reported previously in this mouse model, the observation of seizures and death consequential to fluoxetine treatment is new. Our results warrant further research on the underlying mechanisms as this may refine the treatment of AD patients.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Anticonvulsants; Body Weight; Disease Models, Animal; Fluoxetine; Humans; Logistic Models; Male; Mice, Inbred C57BL; Mice, Transgenic; Neuroprotective Agents; Presenilin-1; Seizures

Formal Psychiatric Disorders are not Overrepresented in Behavioral Variant Frontotemporal Dementia. - Gossink, Flora T; Dols, Annemieke; Krudop, Welmoed A; Sikkes, Sietske A; Kerssens, Cora J; Prins, Niels D; Scheltens, Philip; Stek, Max L; Pijnenburg, Yolande A L (J Alzheimers Dis, 2016)
While psychiatric misdiagnosis is well-known in behavioral variant frontotemporal dementia (bvFTD), a systematic evaluation of standardized criteria for psychiatric disorders in bvFTD is still missing. Our aim was to define frequency and character of DSM-IV psychiatric disorders among patients with probable and definite bvFTD compared to possible bvFTD, other neurodegenerative diseases, and psychiatric diagnoses, using MINI-International Neuropsychiatric Interview. We additionally compared psychiatric prodromes between these groups. Subjects were participants of the late-onset frontal lobe (LOF) study, a longitudinal multicenter study. In each patient, after baseline diagnostic procedure, a neurologist and geriatric psychiatrist made a joint clinical diagnosis. Independently, a structured diagnostic interview according to DSM-IV and ICD-10 criteria (MINI-Plus) was performed by a trained professional blinded to clinical diagnosis. Out of 91 patients, 23 with probable and definite bvFTD, 3 with possible bvFTD, 25 with a non bvFTD neurodegenerative disease, and 40 with a clinical psychiatric diagnosis were included. Overall frequency of formal current and past psychiatric disorders in probable and definite bvFTD (21.7% current, 8.7% past) did not differ from other neurodegenerative diseases (12.0% current, 16.0% past) or possible bvFTD (66.7% current, 66.7% past), but was less than in patients with a clinical psychiatric diagnosis (57.5% current, 62.5% past; p <  0.01). In probable and definite bvFTD unipolar mood disorders were most common. Formally diagnosed psychiatric disorders are not overrepresented in probable bvFTD, suggesting that psychiatric misdiagnosis in bvFTD can be reduced by strictly applying diagnostic criteria. In suspected bvFTD close collaboration between neurologists and psychiatrists will advance diagnostics and subsequent treatment.
Keywords: Aged; Cohort Studies; Diagnostic and Statistical Manual of Mental Disorders; Female; Frontotemporal Dementia; Humans; Male; Mental Disorders; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales

Gene Expression Profiling in the APP/PS1KI Mouse Model of Familial Alzheimer's Disease. - Weissmann, Robert; Hüttenrauch, Melanie; Kacprowski, Tim; Bouter, Yvonne; Pradier, Laurent; Bayer, Thomas A; Kuss, Andreas W; Wirths, Oliver (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a devastating neurodegenerative disorder characterized by early intraneuronal amyloid-β (Aβ) accumulation, extracellular deposition of Aβ peptides, and intracellular hyperphosphorylated tau aggregates. These lesions cause dendritic and synaptic alterations and induce an inflammatory response in the diseased brain. Although the neuropathological characteristics of AD have been known for decades, the molecular mechanisms causing the disease are still under investigation. Studying gene expression changes in postmortem AD brain tissue can yield new insights into the molecular disease mechanisms. To that end, one can employ transgenic AD mouse models and the next-generation sequencing technology. In this study, a whole-brain transcriptome analysis was carried out using the well-characterized APP/PS1KI mouse model for AD. These mice display a robust phenotype reflected by working memory deficits at 6 months of age, a significant neuron loss in a variety of brain areas including the CA1 region of the hippocampus and a severe amyloid pathology. Based on deep sequencing, differentially expressed genes (DEGs) between 6-month-old WT or PS1KI and APP/PS1KI were identified and verified by qRT-PCR. Compared to WT mice, 250 DEGs were found in APP/PS1KI mice, while 186 DEGs could be found compared to PS1KI control mice. Most of the DEGs were upregulated in APP/PS1KI mice and belong to either inflammation-associated pathways or lysosomal activation, which is likely due to the robust intraneuronal accumulation of Aβ in this mouse model. Our comprehensive brain transcriptome study further highlights APP/PS1KI mice as a valuable model for AD, covering molecular inflammatory and immune responses.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Brain; Disease Models, Animal; Gene Expression Profiling; Male; Mice; Mice, Transgenic; Nerve Degeneration; Presenilin-1; Transcriptome

GSK-3β is Dephosphorylated by PP2A in a Leu309 Methylation-Independent Manner. - Chu, Dandan; Tan, Jianxin; Xie, Shutao; Jin, Nana; Yin, Xiaomin; Gong, Cheng-Xin; Iqbal, Khalid; Liu, Fei (J Alzheimers Dis, 2016)
Hyperphosphorylation of tau is pivotally involved in the pathogenesis of Alzheimer's disease (AD) and related tauopathies. Glycogen synthase kinase-3β (GSK-3β) and protein phosphate 2A (PP2A) are crucial enzymes to regulate tau phosphorylation. GSK-3β activity is regulated by its inhibitory phosphorylation at Ser9. We previously reported the cross-talk between GSK-3β and PP2A signaling and showed that PP2A could dephosphorylate GSK-3β at Ser9. Here, we investigated the dephosphorylation of GSK-3β in brain extracts in the presence of phosphatase inhibitors and found that a PP2A-like phosphatase activity was required for dephosphorylation of GSK-3β at Ser9. PP2A interacted with GSK-3β and suppressed its Ser9 phosphorylation in vitro and in HEK-293FT cells. Activity of PP2A negatively correlated to the level of phosphorylated GSK-3β in kainic acid-induced excitotoxic mouse brain. Alteration of methylation of the catalytic subunit of PP2A (PP2Ac) at Leu309 did not affect GSK-3β phosphorylation. These findings suggest that Leu309 methylation is not required for PP2A to dephosphorylate GSK-3β at Ser9.
Keywords: Animals; Brain; Carboxylic Ester Hydrolases; Cell Line, Transformed; Dose-Response Relationship, Drug; Enzyme Inhibitors; Excitatory Amino Acid Agonists; Glycogen Synthase Kinase 3; Glycogen Synthase Kinase 3 beta; Humans; Kainic Acid; Leucine; Luminescent Proteins; Male; Methylation; Mice; Phosphorylation; Protein O-Methyltransferase; Protein Phosphatase 2; RNA, Small Interfering; Serine; tau Proteins

Health-Related Quality of Life in Patients with Alzheimer's Disease in Different German Health Care Settings. - Heßmann, Philipp; Seeberg, Greta; Reese, Jens Peter; Dams, Judith; Baum, Erika; Müller, Matthias J; Dodel, Richard; Balzer-Geldsetzer, Monika (J Alzheimers Dis, 2016)
The purpose of this study is to evaluate the health-related quality of life (HrQoL) of patients with Alzheimer's disease (AD) in different care settings (institutionalized versus community-dwelling) across all severity stages of dementia. Patients were consecutively recruited with their primary caregivers (123 inpatients and 272 outpatients), and the impact of patient-related parameters such as behavioral and psychological symptoms of dementia (BPSD) (Geriatric Depression Scale [GDS] and Neuropsychiatric Inventory [NPI]) and functional capacity (Alzheimer's Disease Cooperative Study-Activities of Daily Living [ADCS-ADL]) on HrQoL was analyzed. Patients' HrQoL was assessed using self-reported and caregiver-rated generic (EuroQoL Instrument) and dementia-specific (Quality of Life-Alzheimer's Disease [Qol-AD]) scales. Patients reported a considerably higher HrQoL than their caregivers on the QoL-AD, EQ-5D, and EQ VAS (p <  0.001). Different dementia severity groups showed significantly worse results in HrQoL for patients with lower MMSE scores. The mean self-reported QoL-AD decreased from 32.3±5.7 in the group with the highest MMSE scores to 27.1±5.5 in patients with the lowest MMSE scores (p <  0.001). A considerably lower HrQoL was shown for institutionalized patients versus participants in outpatient settings (proxy-rated QoL-AD 19.7±4.6 versus 26.0±7.1, p <  0.001). Depressive symptoms (GDS), BPSD (NPI), and reduced functional capacity (ADCS-ADL) were evaluated for their impact on patients' HrQoL. Multivariate models explained between 22% and 54% of the variance in patients' HrQoL. To analyze the causative direction of the reported associations, further longitudinal studies should be conducted.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Caregivers; Depression; Female; Germany; Humans; Inpatients; Male; Multivariate Analysis; Neuropsychological Tests; Outpatients; Psychiatric Status Rating Scales; Quality of Life; Residential Facilities; Self Report; Severity of Illness Index

Hemisphere Asymmetry of Response to Pharmacologic Treatment in an Alzheimer's Disease Mouse Model. - Manousopoulou, Antigoni; Saito, Satoshi; Yamamoto, Yumi; Al-Daghri, Nasser M; Ihara, Masafumi; Carare, Roxana O; Garbis, Spiros D (J Alzheimers Dis, 2016)
The aim of this study was to examine hemisphere asymmetry of response to pharmacologic treatment in an Alzheimer's disease mouse model using cilostazol as a chemical stimulus. Eight-month-old mice were assigned to vehicle or cilostazol treatment for three months and hemispheres were analyzed using quantitative proteomics. Bioinformatics interpretation showed that following treatment, aggregation of blood platelets significantly decreased in the right hemisphere whereas neurodegeneration significantly decreased and synaptic transmission increased in the left hemisphere only. Our study provides novel evidence on cerebral laterality of pharmacologic activity, with important implications in deciphering regional pharmacodynamic effects of existing drugs thus uncovering novel hemisphere-specific therapeutic targets.
Keywords: Alzheimer Disease; Animals; Brain; Disease Models, Animal; Functional Laterality; Male; Mice, Transgenic; Nootropic Agents; Proteome; Tetrazoles

Heterogeneity of Cognitive Anosognosia and its Variation with the Severity of Dementia in Patients with Alzheimer's Disease. - Avondino, Emilie; Antoine, Pascal (J Alzheimers Dis, 2016)
Currently, the lack of awareness of deficits, i.e., anosognosia, is a major obstacle in the healthcare circuit that delays the diagnosis of Alzheimer's disease (AD). However, a clear framework is lacking in the literature related to this phenomenon in terms of its definition, mechanisms, and objects. The aim of this study is to assess the different levels of cognitive anosognosia using a prediction-performance procedure and to identify the potential correlates of these levels. A sample of patients with probable AD was divided into three groups according to the severity of dementia (mild (MiD), moderate (MoD), and moderately severe (MSD) dementia), ranked according to the results of the Mini-Mental State Examination. We observed the following three scores: the real score, the prediction score, and the anosognosia score. These scores were calculated based on the prediction-performance task MISAwareness from the Dementia Rating Scale for cognitive processes (i.e., Attention, Initiation, Conceptualization, Construction, and Memory). We obtained a strong plateau effect between the MiD and MoD groups for anosognosia scores for actual performance or prediction for both the level of overall functioning and for specific processes. The sole exception was the result for memory processes. Moreover, the profiles of the patients' responses on the Memory subscale were substantially different and, indeed, opposite from those for the other processes. The main results confirm the multidimensionality of anosognosia and its variability with the stage of dementia and specifically implicate memory processes that indicate a cleavage between memory and other cognitive functions.
Keywords: Agnosia; Alzheimer Disease; Attention; Chi-Square Distribution; Cognition Disorders; Dementia; Female; Humans; Male; Memory; Neuropsychological Tests; Predictive Value of Tests; Prospective Studies; Psychiatric Status Rating Scales; Severity of Illness Index

Higher Fasting Plasma Glucose Levels, within the Normal Range, are Associated with Decreased Processing Speed in High Functioning Young Elderly. - Raizes, Meytal; Elkana, Odelia; Franko, Motty; Ravona Springer, Ramit; Segev, Shlomo; Beeri, Michal Schnaider (J Alzheimers Dis, 2016)
We explored the association of plasma glucose levels within the normal range with processing speed in high functioning young elderly, free of type 2 diabetes mellitus (T2DM). A sample of 41 participants (mean age = 64.7, SD = 10; glucose 94.5 mg/dL, SD = 9.3), were examined with a computerized cognitive battery. Hierarchical linear regression analysis showed that higher plasma glucose levels, albeit within the normal range (<110 mg/dL), were associated with longer reaction times (p <  0.01). These findings suggest that even in the subclinical range and in the absence of T2DM, monitoring plasma glucose levels may have an impact on cognitive function.
Keywords: Aged; Blood Glucose; Cognition; Diabetes Mellitus, Type 2; Fasting; Female; Humans; Linear Models; Male; Middle Aged; Neuropsychological Tests; Psychomotor Performance; Reaction Time; Reference Values

Hippocampal Lipid Homeostasis in APP/PS1 Mice is Modulated by a Complex Interplay Between Dietary DHA and Estrogens: Relevance for Alzheimer's Disease. - Díaz, Mario; Fabelo, Noemí; Casañas-Sánchez, Verónica; Marin, Raquel; Gómez, Tomás; Quinto-Alemany, David; Pérez, José A (J Alzheimers Dis, 2016)
Current evidence suggests that lipid homeostasis in the hippocampus is affected by different genetic, dietary, and hormonal factors, and that its deregulation may be associated with the onset and progression of Alzheimer's disease (AD). However, the precise levels of influence of each of these factors and their potential interactions remain largely unknown, particularly during neurodegenerative processes. In the present study, we have performed multifactorial analyses of the combined effects of diets containing different doses of docosahexaenoic acid (DHA), estrogen status (ovariectomized animals receiving vehicle or 17β-estradiol), and genotype (wild-type or transgenic APP/PS1 mice) in hippocampal lipid profiles. We have observed that the three factors affect lipid classes and fatty acid composition to different extents, and that strong interactions between these factors exist. The most aberrant lipid profiles were observed in APP/PS1 animals receiving DHA-poor diets and deprived of estrogens. Conversely, wild-type animals under a high-DHA diet and receiving estradiol exhibited a lipid profile that closely resembled that of the hippocampus of control animals. Interestingly, though the lipid signatures of APP/PS1 hippocampi markedly differed from wild-type, administration of a high-DHA diet in the presence of estrogens gave rise to a lipid profile that approached that of control animals. Paralleling changes in lipid composition, patterns of gene expression of enzymes involved in lipid biosynthesis were also altered and affected by combination of experimental factors. Overall, these results indicate that hippocampal lipid homeostasis is strongly affected by hormonal and dietary conditions, and that manipulation of these factors might be incorporated in AD therapeutics.
Keywords: Acyl Coenzyme A; Alzheimer Disease; Amyloid beta-Protein Precursor; Analysis of Variance; Animals; Disease Models, Animal; Docosahexaenoic Acids; Dose-Response Relationship, Drug; Estrogens; Gene Expression Regulation; Hippocampus; Homeostasis; Humans; Lipid Metabolism; Mice; Mice, Transgenic; Mutation; Presenilin-1; RNA, Messenger

Hyperactivity with Agitative-Like Behavior in a Mouse Tauopathy Model. - Jul, Pia; Volbracht, Christiane; de Jong, Inge E M; Helboe, Lone; Elvang, Anders Brandt; Pedersen, Jan Torleif (J Alzheimers Dis, 2016)
Tauopathies, such as Alzheimer's disease (AD) and frontotemporal dementia (FTD), are characterized by formation of neurofibrillary tangles consisting of hyperphosphorylated tau. In addition to memory loss, patients experience behavioral symptoms such as agitation, aggression, depression, and insomnia. We explored the behavioral phenotype of a mouse model (rTg4510) carrying the human tau P301L mutation found in a familial form of FTD. We tested these mice in locomotor activity assays as well as in the Morris water maze to access spatial memory. In addition to cognitive impairments, rTg4510 mice exhibited a hyperactivity phenotype which correlated with progression of tau pathology and was dependent on P301L tau transgene expression. The hyperactive phenotype was characterized by significantly increased locomotor activity in a novel and in a simulated home cage environment together with a disturbed day/night cycle. The P301L-tau-dependent hyperactivity and agitative-like phenotype suggests that these mice may form a correlate to some of the behavioral disturbances observed in advanced AD and FTD.
Keywords: Age Factors; Analysis of Variance; Animals; Brain; Cognition Disorders; Disease Models, Animal; Doxycycline; Exploratory Behavior; Humans; Hyperkinesis; Male; Maze Learning; Mice; Mice, Transgenic; Motor Activity; Mutation; Psychomotor Agitation; tau Proteins; Tauopathies; Time Factors

"I Don't Think Of It As An Illness": Illness Representations in Mild to Moderate Dementia. - Clare, Linda; Quinn, Catherine; Jones, Ian Rees; Woods, Robert T (J Alzheimers Dis, 2016)
The self-regulatory model proposes that illness representations influence adjustment and coping in chronic conditions. Better understanding of the illness representations held by people with dementia could help with targeting information and support so as to optimize adjustment and coping. In this mixed-methods study of illness representations among people with mild to moderate Alzheimer's, vascular, or mixed dementia we aimed to clarify the nature of the representations held, to determine whether specific profiles can be identified based on perceptions of the identity and cause of the condition, and to examine associations between these profiles and other participant characteristics. Data were collected in the second wave of the Memory Impairment and Dementia Awareness Study (MIDAS). Sixty-four people with dementia, who had been told their diagnosis at a memory clinic, completed interviews and responded to questionnaires. In each case a carer was also interviewed. Cluster analysis based on responses about identity and cause identified three profiles. 'Illness' cluster participants saw themselves as living with an illness and used diagnostic labels, 'ageing' cluster participants did not use diagnostic labels and viewed their difficulties as related to ageing, and 'no problem' cluster participants considered that they did not have any difficulties. 'Illness' cluster participants had better cognition and better awareness, but lower mood, and perceived more practical consequences, than 'ageing' cluster participants. Holding an 'illness' model may not be advantageous. Rather than encouraging adoption of such a model, it may be preferable to target information and select interventions in line with the person's representation profile.
Keywords: Adaptation, Psychological; Aged; Aged, 80 and over; Aging; Awareness; Caregivers; Dementia; Female; Follow-Up Studies; Humans; Male; Middle Aged; Psychiatric Status Rating Scales; Residence Characteristics; Self Concept; Statistics, Nonparametric; Surveys and Questionnaires

Impact of Depressive Symptoms on Conversion from Mild Cognitive Impairment Subtypes to Alzheimer's Disease: A Community-Based Longitudinal Study. - Kida, Jiro; Nemoto, Kiyotaka; Ikejima, Chiaki; Bun, Shogyoku; Kakuma, Tatsuyuki; Mizukami, Katsuyoshi; Asada, Takashi (J Alzheimers Dis, 2016)
BACKGROUND: While longitudinal studies have investigated the relationships between mild cognitive impairment (MCI) subtypes and dementia subtypes, the results have been contradictory. In addition, some research shows that depression accompanied by MCI might increase the risk of Alzheimer's disease (AD). OBJECTIVE: The aim of this study is to longitudinally investigate the relationships between MCI subtypes and dementia subtypes, with special attention to the effect of comorbid depressive symptoms in a Japanese rural community. METHODS: Non-demented participants (n = 802) completed a baseline and follow-up study. Outcomes were conversion to dementia especially AD, MCI, or no conversion. A complementary log-log analysis was conducted to investigate the risk of dementia and AD in amnestic MCI (aMCI) compared to nonamnestic MCI (naMCI) groups. The impact of depressive symptoms on the transition from MCI to AD and from cognitively normal to MCI or AD was also analyzed. RESULTS: The risk of developing dementia, in particular AD, for the aMCI group was significantly higher than that for the naMCI group. In the aMCI group, the presence of depressive symptoms increased the risk of developing AD, but depressive symptoms in the naMCI group did not. In the cognitively normal group, the presence of depressive symptoms increased the risk of aMCI but not naMCI or AD. CONCLUSION: MCI subtyping could be useful in finding a prodrome for dementia and in particular for AD. The differing impacts of depressive symptoms on the development of AD suggest that the relationship between depressive symptoms and cognitive impairment could differ in aMCI and naMCI patients.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Cognitive Dysfunction; Depression; Disease Progression; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Prodromal Symptoms; Prognosis; Risk

Impact of Omega-3 Fatty Acid Supplementation on Memory Functions in Healthy Older Adults. - Külzow, Nadine; Witte, A Veronica; Kerti, Lucia; Grittner, Ulrike; Schuchardt, Jan Philipp; Hahn, Andreas; Flöel, Agnes (J Alzheimers Dis, 2016)
As the process of Alzheimer's disease (AD) begins years before disease onset, searching for prevention strategies is of major medical and economic importance. Nutritional supplementation with long-chain polyunsaturated omega-3 fatty acids (LC-n3-FA) may exert beneficial effects on brain structure and function. However, experimental evidence in older adults without clinical dementia is inconsistent, possibly due to low sensitivity of previously employed test batteries for detecting subtle improvements in cognition in healthy individuals. Here we used LOCATO, recently described as a robust and sensitive tool for assessing object-location memory (OLM) in older adults, to evaluate the impact of LC-n3-FA supplementation on learning and memory formation. In a double-blind placebo-controlled proof-of-concept study, 44 (20 female) cognitively healthy individuals aged 50-75 years received either LC-n3-FA (2,200 mg/day, n = 22) or placebo (n = 22) for 26 weeks. Before and after intervention, memory performance in the OLM-task (primary) was tested. As secondary outcome parameters, performance in Rey Auditory Verbal Learning Test (AVLT), dietary habits, omega-3-index, and other blood-derived parameters were assessed. Omega-3 index increased significantly in the LC-n3-FA group compared with the placebo group. Moreover, recall of object locations was significantly better after LC-n3-FA supplementation compared with placebo. Performance in the AVLT was not significantly affected by LC-n3-FA. This double-blind placebo-controlled proof-of-concept study provides further experimental evidence that LC-n3-FA exert positive effects on memory functions in healthy older adults. Our findings suggest novel strategies to maintain cognitive functions into old age.
Keywords: Aged; Apolipoproteins E; Auditory Perception; Blood Chemical Analysis; Cognitive Aging; Dietary Supplements; Double-Blind Method; Fatty Acids, Omega-3; Feeding Behavior; Female; Humans; Learning; Male; Memory; Middle Aged; Neuropsychological Tests; Nootropic Agents; Treatment Outcome

Impaired Autophagy in APOE4 Astrocytes. - Simonovitch, Shira; Schmukler, Eran; Bespalko, Alina; Iram, Tal; Frenkel, Dan; Holtzman, David M; Masliah, Eliezer; Michaelson, Danny M; Pinkas-Kramarski, Ronit (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is the most prevalent form of dementia in elderly. Genetic studies revealed allelic segregation of the apolipoprotein E (ApoE) gene in sporadic AD and in families with higher risk of AD. The mechanisms underlying the pathological effects of ApoE4 are not yet entirely clear. Several studies indicate that autophagy, which plays an important role in degradation pathways of proteins, organelles and protein aggregates, may be impaired in AD. In the present study, we investigated the effects of ApoE4 versus the ApoE3 isoform on the process of autophagy in mouse-derived astrocytes. The results obtained reveal that under several autophagy-inducing conditions, astrocytes expressing ApoE4 exhibit lower autophagic flux compared to astrocytes expressing ApoE3. Using an in situ model, we examined the role of autophagy and the effects thereon of ApoE4 in the elimination of Aβ plaques from isolated brain sections of transgenic 5xFAD mice. This revealed that ApoE4 astrocytes eliminate Aβ plaques less effectively than the corresponding ApoE3 astrocytes. Additional experiments showed that the autophagy inducer, rapamycin, enhances Aβ plaque degradation by ApoE4 astrocytes whereas the autophagy inhibitor, chloroquine, blocks Aβ plaque degradation by ApoE3 astrocytes. Taken together, these findings show that ApoE4 impairs autophagy in astrocyte cultures and that this effect is associated with reduced capacity to clear Aβ plaques. This suggests that impaired autophagy may play a role in mediating the pathological effects of ApoE4 in AD.
Keywords: Amyloid beta-Peptides; Animals; Apolipoprotein E3; Apolipoprotein E4; Astrocytes; Autophagy; Brain; Cells, Cultured; Central Nervous System Agents; Chloroquine; Disease Models, Animal; Humans; Mice, Transgenic; Plaque, Amyloid; Sirolimus; Time Factors

Increased Electron Paramagnetic Resonance Signal Correlates with Mitochondrial Dysfunction and Oxidative Stress in an Alzheimer's disease Mouse Brain. - Fang, Du; Zhang, Zhihua; Li, Hang; Yu, Qing; Douglas, Justin T; Bratasz, Anna; Kuppusamy, Periannan; Yan, Shirley ShiDu (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a progressive neurodegenerative disease characterized clinically by cognitive decline and memory loss. The pathological features are amyloid-β peptide (Aβ) plaques and intracellular neurofibrillary tangles. Many studies have suggested that oxidative damage induced by reactive oxygen species (ROS) is an important mechanism for AD progression. Our recent study demonstrated that oxidative stress could further impair mitochondrial function. In the present study, we adopted a transgenic mouse model of AD (mAPP, overexpressing AβPP/Aβ in neurons) and performed redox measurements using in vivo electron paramagnetic resonance (EPR) imaging with methoxycarbamyl-proxyl (MCP) as a redox-sensitive probe for studying oxidative stress in an early stage of pathology in a transgenic AD mouse model. Through assessing oxidative stress, mitochondrial function and cognitive behaviors of mAPP mice at the age of 8-9 months, we found that oxidative stress and mitochondrial dysfunction appeared in the early onset of AD. Increased ROS levels were associated with defects of mitochondrial and cognitive dysfunction. Notably, the in vivo EPR method offers a unique way of assessing tissue oxidative stress in living animals under noninvasive conditions, and thus holds a potential for early diagnosis and monitoring the progression of AD.
Keywords: Adenosine Triphosphate; Age of Onset; Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Brain; Cognition; Disease Models, Animal; Electron Spin Resonance Spectroscopy; Electron Transport Complex IV; Female; Humans; Male; Maze Learning; Mice, Transgenic; Mitochondria; Oxidative Stress; Reactive Oxygen Species; Spatial Memory

Increased Total Homocysteine Levels Predict the Risk of Incident Dementia Independent of Cerebral Small-Vessel Diseases and Vascular Risk Factors. - Miwa, Kaori; Tanaka, Makiko; Okazaki, Shuhei; Yagita, Yoshiki; Sakaguchi, Manabu; Mochizuki, Hideki; Kitagawa, Kazuo (J Alzheimers Dis, 2016)
BACKGROUND: Homocysteine has been identified as a potential risk factor for stroke, cerebral small-vessel diseases (SVD), and dementia. OBJECTIVE: The present study aimed to investigate the predictive value of homocysteine levels on incident dementia while simultaneously controlling for MRI findings and vascular risk factors. METHODS: Within a Japanese cohort of participants with vascular risk factors in an observational study, we evaluated the association between baseline total homocysteine (tHcy) levels (per 1 μmol/L and the tertile of tHcy), the prevalence of MRI-findings at baseline, and incident all-cause dementia. Baseline brain MRI was used to determine SVD (lacunas, white matter hyperintensities, and cerebral microbleeds [CMBs]) and atrophy (medial-temporal lobe atrophy and bicaudate ratio). Logistic regression analyses were used to estimate the cross-sectional association between tHcy and each of MRI findings. Cox proportional hazards analyses were performed to estimate the longitudinal association between tHcy and dementia. RESULTS: In the 643 subjects (age: 67.2 ± 8.4 years, male: 59% ; education: 12.9 ± 2.6 years), multivariable analyses adjusted for several potential confounders, including estimated glomerular filtration rate (eGFR) and intima-media thickness, showed that highest tHcy tertile was associated with lacunas, CMBs, and strictly deep CMBs. During the mean 7.3-year follow-up (range: 2-13), 47 patients were diagnosed with dementia (Alzheimer's disease: 24; vascular dementia: 18; mixed-type: 3; other: 2). After adjusting for age, gender, APOE ɛ4, education, BMI, MMSE, hypertension, cerebrovascular events, eGFR, and MRI-findings, tHcy level (hazard ratios [HR]: 1.08, p = 0.043) and the highest tertile of tHcy (HR: 2.50, p = 0.047) for all-cause dementia remained significant. CONCLUSIONS: Our results provide additional evidence of tHcy that contributes to increased susceptibility to dementia risk.
Keywords: Aged; Carotid Intima-Media Thickness; Cerebral Small Vessel Diseases; Dementia; Female; Homocysteine; Humans; Incidence; Longitudinal Studies; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Predictive Value of Tests; Proportional Hazards Models; Risk Factors; Statistics, Nonparametric

Influence of Incipient Dementia on Hospitalization for Primary Care Sensitive Conditions: A Population-Based Cohort Study. - Pimouguet, Clément; Rizzuto, Debora; Fastbom, Johan; Lagergren, Mårten; Fratiglioni, Laura; Xu, Weili (J Alzheimers Dis, 2016)
BACKGROUND: Studies have reported that moderate/severe stages of dementia are linked to increased hospitalization rates, but little is known about the influence of incipient dementia on hospitalizations for primary care sensitive conditions (PCSCs). OBJECTIVE: To examine the associations between incipient dementia and hospitalization outcomes, including all-cause and PCSC hospitalization. METHODS: A total of 2,268 dementia-free participants in the Swedish National study on Aging and Care-Kungsholmen were interviewed and clinically examined at baseline. Participants aged ≥78 years were followed for 3 years, and those aged 60-72 years, for 6 years. Number of hospitalizations was retrieved from the National Patient Register. Dementia was diagnosed in accordance with Diagnostic and Statistical Manual of Mental Disorders-IV criteria. Hospitalization outcomes were compared in participants who did and did not develop dementia. Zero-inflated Poisson regressions and logistic regressions were used in data analysis. RESULTS: During the follow-up, 175 participants developed dementia. The unadjusted PCSC admission rate was 88.2 per 1000 person-years in those who developed dementia and 25.6 per 1000 person-years in those who did not. In the fully adjusted logistic regression model, incipient dementia was associated with an increased risk of hospitalization for PCSCs (OR = 2.3, 95% CI 1.3-3.9) but not with the number of hospitalizations or with all-cause hospitalization. Risks for hospitalization for diabetes, congestive heart failure, and pyelonephritis were higher in those who developed dementia than in those who did not. About 10% participants had a PCSC hospitalization attributable to incipient dementia. CONCLUSION: People with incipient dementia are more prone to hospitalization for PCSCs but not to all-cause hospitalization.
Keywords: Acute Disease; Age Factors; Aged; Aged, 80 and over; Chronic Disease; Dementia; Female; Follow-Up Studies; Hospitalization; Humans; Logistic Models; Longitudinal Studies; Male; Primary Health Care; Registries; Risk; Sensitivity and Specificity; Socioeconomic Factors; Sweden

Inhibition of Cholesterol Biosynthesis Reduces γ-Secretase Activity and Amyloid-β Generation. - Kim, Yoonhee; Kim, Chaeyoung; Jang, Hye Young; Mook-Jung, Inhee (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) is one of major molecules contributing to the pathogenesis of Alzheimer's disease (AD). Aβ is derived from amyloid-β protein precursor (AβPP) through sequential cleavages by β- and γ-secretases. Regulation of these components is thought to be an important factor in Aβ generation during the pathogenesis of AD. AβPP, β-secretase, and γ-secretase reside in lipid rafts, where cholesterol regulates the integrity and flexibility of membrane proteins and Aβ is generated. However, the relationship between cholesterol and Aβ generation is controversial. In this study, we aimed to elucidate the direct effects of cholesterol depletion on AβPP processing using AY9944, which blocks the last step of cholesterol biosynthesis and thus minimizes the unknown side effects of upstream inhibitors, such as HMG-CoA reductase inhibitors. Treatment with AY9944 decreased γ-secretase activity and Aβ generation. These results suggested that changes in membrane composition by lowering cholesterol with AY9944 affected γ-secretase activity and Aβ generation, which is associated with AD pathogenesis.
Keywords: Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Analysis of Variance; Animals; Anticholesteremic Agents; Cell Line; Cholesterol; Cricetinae; Down-Regulation; Humans; In Situ Nick-End Labeling; Luminescent Proteins; Membrane Glycoproteins; Membrane Microdomains; Mutation; Presenilin-1; Protein Transport; trans-1,4-Bis(2-chlorobenzaminomethyl)cyclohexane Dihydrochloride; Transfection

Integrated Analysis of Alzheimer's Disease and Schizophrenia Dataset Revealed Different Expression Pattern in Learning and Memory. - Li, Wen-Xing; Dai, Shao-Xing; Liu, Jia-Qian; Wang, Qian; Li, Gong-Hua; Huang, Jing-Fei (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) and schizophrenia (SZ) are both accompanied by impaired learning and memory functions. This study aims to explore the expression profiles of learning or memory genes between AD and SZ. We downloaded 10 AD and 10 SZ datasets from GEO-NCBI for integrated analysis. These datasets were processed using RMA algorithm and a global renormalization for all studies. Then Empirical Bayes algorithm was used to find the differentially expressed genes between patients and controls. The results showed that most of the differentially expressed genes were related to AD whereas the gene expression profile was little affected in the SZ. Furthermore, in the aspects of the number of differentially expressed genes, the fold change and the brain region, there was a great difference in the expression of learning or memory related genes between AD and SZ. In AD, the CALB1, GABRA5, and TAC1 were significantly downregulated in whole brain, frontal lobe, temporal lobe, and hippocampus. However, in SZ, only two genes CRHBP and CX3CR1 were downregulated in hippocampus, and other brain regions were not affected. The effect of these genes on learning or memory impairment has been widely studied. It was suggested that these genes may play a crucial role in AD or SZ pathogenesis. The different gene expression patterns between AD and SZ on learning and memory functions in different brain regions revealed in our study may help to understand the different mechanism between two diseases.
Keywords: Adult; Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Bayes Theorem; Brain; Datasets as Topic; Gene Expression Profiling; Humans; Learning; Memory; Microarray Analysis; Middle Aged; Schizophrenia; Schizophrenic Psychology; Young Adult

Integrating Biomarkers for Underlying Alzheimer's Disease in Mild Cognitive Impairment in Daily Practice: Comparison of a Clinical Decision Support System with Individual Biomarkers. - Rhodius-Meester, Hanneke F M; Koikkalainen, Juha; Mattila, Jussi; Teunissen, Charlotte E; Barkhof, Frederik; Lemstra, Afina W; Scheltens, Philip; Lötjönen, Jyrki; van der Flier, Wiesje M (J Alzheimers Dis, 2016)
BACKGROUND: Recent criteria allow biomarkers to provide evidence of Alzheimer's disease (AD) pathophysiology. How they should be implemented in daily practice remains unclear, especially in mild cognitive impairment (MCI) patients. OBJECTIVE: We evaluated how a clinical decision support system such as the PredictAD tool can aid clinicians to integrate biomarker evidence to support AD diagnosis. METHODS: With available data on demographics, cerebrospinal fluid (CSF), and MRI, we trained the PredictAD tool on a reference population of 246 controls and 491 AD patients. We then applied the identified algorithm to 211 MCI patients. For comparison, we also classified patients based on individual biomarkers (MRI; CSF) and the NIA-AA criteria. Progression to dementia was used as outcome measure. RESULTS: After a median follow up of 3 years, 72 (34%) MCI patients remained stable and 139 (66%) progressed to AD. The PredictAD tool assigned a likelihood of underlying AD to each patient (AUC 0.82). Excluding patients with missing data resulted in an AUC of 0.87. According to the NIA-AA criteria, half of the MCI patients had uninformative biomarkers, precluding an assignment of AD likelihood. A minority (41%) was assigned to high or low AD likelihood with good predictive value. The individual biomarkers showed best value for CSF total tau (AUC 0.86). CONCLUSION: The ability of the PredictAD tool to identify AD pathophysiology was comparable to individual biomarkers. The PredictAD tool has the advantage that it assigns likelihood to all patients, regardless of missing or conflicting data, allowing clinicians to integrate biomarker data in daily practice.
Keywords: Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Area Under Curve; Biomarkers; Cognitive Dysfunction; Cohort Studies; Decision Support Systems, Clinical; Disease Progression; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Outcome Assessment (Health Care); Predictive Value of Tests

Intranasal TAT-haFGF Improves Cognition and Amyloid-β Pathology in an AβPP/PS1 Mouse Model of Alzheimer's Disease. - Lou, Guofeng; Zhang, Qihao; Xiao, Fei; Xiang, Qi; Su, Zhijian; Huang, Yadong (J Alzheimers Dis, 2016)
Neurotoxic amyloid-β (Aβ) peptide causing cognitive function disabilities is one of the most characteristic pathological features in Alzheimer's disease (AD). A novel fusion protein, TAT-haFGF, was administrated to AβPP/PS1 transgenic mice by intravenous (IV) injection and intranasal (IN) delivery, respectively, for 5 weeks to compare the pharmacodynamics between the two routes of administration. Our results showed that IN administration of TAT-haFGF improved cognition and reduced Aβ plaques more significantly in AβPP/PS1 mice, when compared with IV injection. Our new findings suggest that TAT-haFGF might be a promising new therapy to attenuate AD pathological process.
Keywords: Administration, Intranasal; Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Brain; Cognition Disorders; Disease Models, Animal; Fibroblast Growth Factors; Gene Products, tat; Humans; Injections, Intraventricular; Maze Learning; Mice; Mice, Inbred C57BL; Mice, Transgenic; Movement; Mutation; Peptide Fragments; Plaque, Amyloid; Presenilin-1

Japanese Care Location and Medical Procedures for People with Dementia in the Last Month of Life. - Nakanishi, Miharu; Nakashima, Taeko; Shindo, Yumi; Niimura, Junko; Nishida, Atsushi (J Alzheimers Dis, 2016)
BACKGROUND: Dementia-related societies worldwide have called for palliative end-of-life care for those suffering dementia; meanwhile, the Japanese dementia plan was revised on January 2015 to introduce into its objectives the support for end-of-life care via increased social and health care collaboration. OBJECTIVE: The study focus was the use of medical procedures in the last month of life among dementia patients in different care locations in Japan. METHODS: This study was conducted using a retrospective study design. Data from the Survey of Institutions and Establishments for Long-Term Care, which is a nationally representative cross-sectional survey of the public long-term care insurance services, were used. The 6,148 patients who received end-of-life care in their own home, nursing homes, or hospitals in September 2007, 2010, and 2013 were included for analysis. The primary disease of each patient was based on the ICD-10 code; a diagnosis of dementia included F00 (Alzheimer's), F01 (vascular), F02 (other), and F03 (unspecified). RESULTS: Of 6,148 patients, 886 (14.4%) had dementia as a primary disease; most received care in the last month of life in nursing homes (48.0%) or hospitals (44.8%) rather than in their own home (7.2%). Patients were less likely to undergo pain management when their primary disease was dementia (adjusted odds ratio, 0.44; 95% confidence interval, 0.21-0.91). CONCLUSION: Education and policy efforts are required to provide palliative end-of-life care to people with dementia at home. The national dementia plan should also explore possible approaches regarding pain management for dying people who have dementia.
Keywords: Aged, 80 and over; Cross-Sectional Studies; Dementia; Female; Hospitals; Housing; Humans; Japan; Male; Nursing Homes; Pain Management; Retrospective Studies; Terminal Care; Time Factors

JNK: A Putative Link Between Insulin Signaling and VGLUT1 in Alzheimer's Disease. - Rodriguez-Perdigon, Manuel; Solas, Maite; Ramirez, Maria Javier (J Alzheimers Dis, 2016)
In the present work, the involvement of JNK in insulin signaling alterations and its role in glutamatergic deficits in Alzheimer's disease (AD) has been studied. In postmortem cortical tissues, pJNK levels were increased, while insulin signaling and the expression of VGLUT1 were decreased. A significant correlation was found between reduced expression of insulin receptor and VGLUT1. The administration of a JNK inhibitor reversed the decrease in VGLUT1 expression found in a mice model of insulin resistance. It is suggested that activation of JNK in AD inhibits insulin signaling which could lead to a decreased expression of VGLUT1, therefore contributing to the glutamatergic deficit in AD.
Keywords: Aged; Alzheimer Disease; Animals; Brain; Corticosterone; Disease Models, Animal; Female; Humans; Insulin; Insulin Resistance; Male; MAP Kinase Kinase 4; Mice, Inbred C57BL; Mitogen-Activated Protein Kinase 1; Neuroprotective Agents; RNA, Messenger; Vesicular Glutamate Transport Protein 1

The Korean Size/Weight Attribute Test: A Semantic Knowledge Test for Korean Older Adults and Brain-Imaging Evidence. - Yoo, Yongjoon; Shin, Seong A; Park, Soowon; Lee, Ji-Hye; Youn, Jung-Hae; Kim, Yu Kyeong; Lee, Jun-Young (J Alzheimers Dis, 2016)
BACKGROUND: A standardized tool for evaluating semantic knowledge of the Korean population is needed. OBJECTIVE: The purpose of this study was to develop a neuropsychological test for the evaluation of semantic knowledge in the Korean elderly population. METHODS: The Korean version of the Size/Weight Attribute Test (SWAT-K) was developed in reference to the original version. The diagnostic validity of SWAT-K was evaluated with 95 elderly outpatients [67 normal controls; 18 with Alzheimer's disease (AD); 10 with semantic-variant progressive aphasia (SV-PPA)]. Voxel-based morphometry (VBM) was employed to examine associations between SWAT-K scores and morphological changes of the brain. RESULTS: SWAT-K could discriminate the three subject groups (normal >AD, p <  0.001; AD >SV-PPA, p = 0.040), whereas Boston Naming Test could not distinguish SV-PPA from AD. ROC curve analysis confirmed high levels of sensitivity (0.90) and specificity (0.93) for SWAT-K. The test's inter-rater reliability (ICC = 0.827) and test-retest reliability (ICC = 0.666) were assessed as well. VBM found a significant positive correlation (uncorrected p <  0.005, k >  100) between SWAT-K scores and gray matter volume in right inferior frontal cortex (T = 4.08, k = 191) and bilateral temporal cortices (left, T = 4.42, k = 135; right, T = 3.55, k = 253), the areas the most affected in SV-PPA. CONCLUSIONS: SWAT-K is a sensitive and reliable test for evaluating semantic knowledge in the Korean elderly population. Strong positive correlations between SWAT-K scores and the brain areas responsible for semantic processing further corroborate the validity of SWAT-K.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Analysis of Variance; Brain; Dementia; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Psychiatric Status Rating Scales; Republic of Korea; ROC Curve; Semantics

The Latent Dementia Phenotype δ is Associated with Cerebrospinal Fluid Biomarkers of Alzheimer's Disease and Predicts Conversion to Dementia in Subjects with Mild Cognitive Impairment. - Koppara, Alexander; Wolfsgruber, Steffen; Kleineidam, Luca; Schmidtke, Klaus; Frölich, Lutz; Kurz, Alexander; Schulz, Stefanie; Hampel, Harald; Heuser, Isabella; Peters, Oliver; Reischies, Friedel M; Jahn, Holger; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The recently proposed latent variable δ is a new tool for dementia case finding. It is built in a structural equation modeling framework of cognitive and functional data and constitutes a novel endophenotype for Alzheimer's disease (AD) research and clinical trials. OBJECTIVE: To investigate the association of δ with AD biomarkers and to compare the prediction of δ with established scales for conversion to dementia in patients with mild cognitive impairment (MCI). METHODS: Using data from a multicenter memory clinic study, we examined the external associations of the latent variable δ and compared δ with well-established cognitive and functional scales and cognitive-functional composite scores. For that purpose, logistic regressions with cerebrospinal fluid (CSF) biomarkers and conversion to dementia as dependent variables were performed with the investigated scores. The models were tested for significant differences. RESULTS: In patients with MCI, δ based on a broad range of cognitive scales (including the ADAS-cog, the MMSE, and the CERAD neuropsychological battery) predicted an abnormal CSF Aβ42/tau ratio indicative of AD (n = 340, AUC = 0.78, p <  0.001), and predicted incident dementia within 1-3 years of follow-up (n = 525, AUC = 0.84, p <  0.001). These associations were generally stronger than for any other scale or cognitive-functional composite examined. Homologs of δ based on reduced test batteries yielded somewhat lower effects. CONCLUSION: These findings support the interpretation of δ as a construct capturing the disease-related "essence" of cognitive and functional impairments in patients with MCI and dementia, and suggest that δ might become an analytical tool for dementia research.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Dementia; Disease Progression; Female; Humans; Logistic Models; Longitudinal Studies; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptide Fragments; Phenotype; Predictive Value of Tests; Retrospective Studies; tau Proteins

Late-Onset Metachromatic Leukodystrophy with Early Onset Dementia Associated with a Novel Missense Mutation in the Arylsulfatase A Gene. - Stoeck, Katharina; Psychogios, Marios Nikos; Ohlenbusch, Andreas; Steinfeld, Robert; Schmidt, Jens (J Alzheimers Dis, 2016)
A 48-year-old male patient presented with personality changes and progressive memory loss over 2 years with initially suspected Hashimoto's encephalopathy. Strategy of diagnostic workup of early onset dementia included dementia from neurodegenerative, neuroinflammatory, metabolic/toxic, and psychiatric origin. The patient's neurological exam was normal. MRI revealed a leukencephalopathy, predominantly in the frontal periventricular white matter, without notable changes over 2 years. On neurophysiological examination, prolonged central conduction times and a sensorimotor polyneuropathy were noted. Neuropsychological impairment included disorientation in place and a reduced short time memory. Behavioral alterations were predominated by sudden mood changes and disinhibition. Cerebrospinal fluid was normal. Despite presence of thyroid autoantibodies, glucocorticosteroid treatment did not improve the dementia. A metachromatic leukodystrophy was diagnosed by decreased arylsulfatase-A activity in leucocytes/fibroblasts and identification of a compound heterozygous mutation in the ARSA gene: c.542T>G (exon 3) and the novel mutation c.1013T>C (exon 6). Pathogenic function was suggested by bioinformatic mutation search. In a patient with early onset dementia, strategic diagnostic workup including genetic assessment revealed an adult-onset metachromatic leukodystrophy with a novel mutation in the arylsulfatase A gene.
Keywords: Age of Onset; Brain; Cerebroside-Sulfatase; Dementia; Diagnosis, Differential; DNA Mutational Analysis; Exons; Humans; Leukodystrophy, Metachromatic; Male; Middle Aged; Mutation, Missense; Neuropsychological Tests

Lewy Bodies, Vascular Risk Factors, and Subcortical Arteriosclerotic Leukoencephalopathy, but not Alzheimer Pathology, are Associated with Development of Psychosis in Alzheimer's Disease. - Fischer, Corinne E; Qian, Winnie; Schweizer, Tom A; Millikin, Colleen P; Ismail, Zahinoor; Smith, Eric E; Lix, Lisa M; Shelton, Paul; Munoz, David G (J Alzheimers Dis, 2016)
BACKGROUND: The neuropathological correlates of psychosis in Alzheimer's disease (AD) is unclear, with some studies reporting a correlation between psychosis and increased AD pathology while others have found no association. OBJECTIVE: To determine the demographic, clinical, and neuropathological features associated with psychotic symptoms in clinically attributed and neuropathologically proven AD. METHOD: We separately reviewed two overlapping groups of clinically diagnosed (cAD) AD patients with neuropathology data and neuropathologically definite (npAD) cases (regardless of clinical diagnosis) from the NACC database, and explored the relationships between psychosis and clinical variables, neuropathologic correlates, and vascular risk factors. Delusions and hallucinations, defined according to the NPI-Q, were analyzed separately. RESULTS: 1,073 subjects in the database fulfilled our criteria (890 cAD and 728 npAD patients). 34% of cAD and 37% of npAD had psychotic symptoms during their illness. Hallucinations were associated with greater cognitive and functional impairments on the MMSE and CDR, while delusional patients showed less impairment on CDR, consistent across cAD and npAD groups. Burden of AD pathology appears to relate to presence of psychotic symptoms in the clinical AD group, but this result is not confirmed in the neuropathologically confirmed group suggesting the findings in the clinical group were due to misdiagnosis of AD. Lewy body pathology, subcortical arteriosclerotic leukoencephalopathy, and vascular risk factors, including a history of hypertension and diabetes, were associated with the development of psychosis. METHOD: Vascular and Lewy body pathologies and vascular risk factors are important modifiers of the risk of psychosis in AD.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cognition Disorders; Databases, Factual; Dementia, Vascular; Female; Hemorrhage; Humans; Lewy Bodies; Male; Middle Aged; Psychiatric Status Rating Scales; Psychotic Disorders; Retrospective Studies; Risk Factors; Severity of Illness Index; Surveys and Questionnaires

Lifelong Reading Disorder and Mild Cognitive Impairment: Implications for Diagnosis. - Lebowitz, Brian K; Weinstein, Cheryl; Beiser, Alexa; Seshadri, Sudha; Wolf, Philip A; Auerbach, Sandford; Au, Rhoda (J Alzheimers Dis, 2016)
Although neuropsychological tests are commonly used in the evaluation of possible mild cognitive impairment (MCI), poor test scores may be indicative of factors other than neurological compromise. The current study assessed the role of lifelong reading disorder on MCI classification. Community dwelling older adults with a suspected developmental reading disorder were identified by inference based on reading test performance. Individuals with a suspected reading disorder were significantly more likely to perform at a level consistent with MCI on several commonly used neuropsychological tests. The findings suggest a relationship between a history of reading disorder and MCI classification.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Dyslexia; Female; Humans; Independent Living; Longitudinal Studies; Male; Neuropsychological Tests; Psychometrics; Retrospective Studies

Linguistic Features Identify Alzheimer's Disease in Narrative Speech. - Fraser, Kathleen C; Meltzer, Jed A; Rudzicz, Frank (J Alzheimers Dis, 2016)
BACKGROUND: Although memory impairment is the main symptom of Alzheimer's disease (AD), language impairment can be an important marker. Relatively few studies of language in AD quantify the impairments in connected speech using computational techniques. OBJECTIVE: We aim to demonstrate state-of-the-art accuracy in automatically identifying Alzheimer's disease from short narrative samples elicited with a picture description task, and to uncover the salient linguistic factors with a statistical factor analysis. METHODS: Data are derived from the DementiaBank corpus, from which 167 patients diagnosed with "possible" or "probable" AD provide 240 narrative samples, and 97 controls provide an additional 233. We compute a number of linguistic variables from the transcripts, and acoustic variables from the associated audio files, and use these variables to train a machine learning classifier to distinguish between participants with AD and healthy controls. To examine the degree of heterogeneity of linguistic impairments in AD, we follow an exploratory factor analysis on these measures of speech and language with an oblique promax rotation, and provide interpretation for the resulting factors. RESULTS: We obtain state-of-the-art classification accuracies of over 81% in distinguishing individuals with AD from those without based on short samples of their language on a picture description task. Four clear factors emerge: semantic impairment, acoustic abnormality, syntactic impairment, and information impairment. CONCLUSION: Modern machine learning and linguistic analysis will be increasingly useful in assessment and clustering of suspected AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Diagnosis, Computer-Assisted; Factor Analysis, Statistical; Female; Humans; Language Disorders; Linguistics; Logistic Models; Machine Learning; Male; Mental Status Schedule; Middle Aged; Narration; Photic Stimulation; Speech; Verbal Behavior

Longitudinal Changes in Functional Brain Connectivity Predicts Conversion to Alzheimer's Disease. - Serra, Laura; Cercignani, Mara; Mastropasqua, Chiara; Torso, Mario; Spanò, Barbara; Makovac, Elena; Viola, Vanda; Giulietti, Giovanni; Marra, Camillo; Caltagirone, Carlo; Bozzali, Marco (J Alzheimers Dis, 2016)
This longitudinal study investigates the modifications in structure and function occurring to typical Alzheimer's disease (AD) brains over a 2-year follow-up, from pre-dementia stages of disease, with the aim of identifying biomarkers of prognostic value. Thirty-one patients with amnestic mild cognitive impairment were recruited and followed-up with clinical, neuropsychological, and MRI assessments. Patients were retrospectively classified as AD Converters or Non-Converters, and the data compared between groups. Cross-sectional MRI data at baseline, assessing volume and functional connectivity abnormalities, confirmed previous findings, showing a more severe pattern of regional grey matter atrophy and default-mode network disconnection in Converters than in Non-Converters. Longitudinally, Converters showed more grey matter atrophy in the frontotemporal areas, accompanied by increased connectivity in the precuneus. Discriminant analysis revealed that functional connectivity of the precuneus within the default mode network at baseline is the parameter able to correctly classify patients in Converters and Non-Converters with high sensitivity, specificity, and accuracy.
Keywords: Aged; Alzheimer Disease; Atrophy; Brain; Brain Mapping; Cognitive Dysfunction; Cross-Sectional Studies; Discriminant Analysis; Disease Progression; Female; Follow-Up Studies; Gray Matter; Humans; Image Processing, Computer-Assisted; Longitudinal Studies; Magnetic Resonance Imaging; Male; Neural Pathways; Neuropsychological Tests; Prognosis; Rest

Longitudinal Memory Profiles in Behavioral-Variant Frontotemporal Dementia and Alzheimer's Disease. - Schubert, Samantha; Leyton, Cristian E; Hodges, John R; Piguet, Olivier (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) and behavioral-variant of frontotemporal dementia (bvFTD) can present with an overlapping neuropsychological profile, which often hinders their clinical differentiation. OBJECTIVE: To compare changes over time in memory, general cognition tasks, and functional scales between bvFTD and AD. METHODS: Consecutive cases diagnosed with probable bvFTD (n = 22) and typical AD (n = 31) with at least two clinical visits were selected. Of these, 13 (9 AD, 4 bvFTD) underwent Pittsburgh compound B PET scan, which supported the clinical diagnosis in all cases. Mixed-model regressions were used to estimate the differential rate of decline on selected tasks between cohorts. RESULTS: Analyses demonstrated that, despite equivalent baseline performance, bvFTD patients experienced a more rapid functional deterioration and a steeper decline in global cognition than AD patients. At baseline, both groups were impaired on executive function and memory tasks compared to controls, but these deficits were more marked in the bvFTD group. In addition, performance on these domains continued to decline more rapidly in this group. CONCLUSIONS: Neither the initial neuropsychological assessment nor projected performances can reliably distinguish the totality of bvFTD and AD individuals. Nevertheless, annual rates of progression on cognitive tasks provide valuable information and will potentially help establish the impact of future therapeutic treatments in these dementia syndromes.
Keywords: Alzheimer Disease; Aniline Compounds; Brain; Diagnosis, Differential; Disease Progression; Executive Function; Female; Follow-Up Studies; Frontotemporal Dementia; Humans; Longitudinal Studies; Male; Memory; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Radiopharmaceuticals; Thiazoles

Longitudinal Protein Changes in Blood Plasma Associated with the Rate of Cognitive Decline in Alzheimer's Disease. - Sattlecker, Martina; Khondoker, Mizanur; Proitsi, Petroula; Williams, Stephen; Soininen, Hilkka; Kłoszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Lovestone, Simon; Dobson, Richard Jb (J Alzheimers Dis, 2016)
Biomarkers of Alzheimer's disease (AD) progression are needed to support the development of urgently needed disease modifying drugs. We employed a SOMAscan assay for quantifying 1,001 proteins in blood samples from 90 AD subjects, 37 stable mild cognitive impaired (MCI) subjects, 39 MCI subjects converting to AD within a year and 69 controls at baseline and one year follow up. We used linear mixed effects models to identify proteins changing significantly over one year with the rate of cognitive decline, which was quantified as the reduction in Mini Mental State Examination (MMSE) scores. Additionally, we investigated proteins changing differently across disease groups and during the conversion from MCI to AD. We found that levels of proteins belonging to the complement cascade increase significantly in fast declining AD patients. Longitudinal changes in the complement cascade might be a surrogate biomarker for disease progression. We also found that members of the cytokine-cytokine receptor interaction pathway change during AD when compared to healthy aging subjects.
Keywords: Aged; Alzheimer Disease; Biomarkers; Cognition; Cognitive Dysfunction; Disease Progression; Female; Follow-Up Studies; Humans; Linear Models; Longitudinal Studies; Male; Mental Status Schedule; Neuropsychological Tests

Low Prevalence of Mixed Dementia in a Cohort of 2,000 Elderly Patients in a Memory Clinic Setting. - Claus, Jules J; Staekenborg, Salka S; Roorda, Jelmen J; Stevens, Martijn; Herderschee, Dirk; van Maarschalkerweerd, Willy; Schuurmans, Lilly; Tielkes, Caroline E M; Koster, Pieter; Bavinck, Chris; Scheltens, Philip (J Alzheimers Dis, 2016)
BACKGROUND: It is generally assumed that with increasing age, pathology in clinically diagnosed Alzheimer's disease (AD) becomes more mixed, i.e., co-existence of amyloid plaques and cerebrovascular pathology. OBJECTIVE: To test the hypothesis of increasing prevalence of mixed dementia in late-onset clinically diagnosed Alzheimer's disease (AD) in a single-center memory clinic population. METHODS: Patients included had diagnoses of AD (n = 832), subjective cognitive impairment (SCI, n = 333), mild cognitive impairment (MCI, n = 492), vascular dementia (VaD, n = 57), other dementia (n = 53), or other diagnosis (n = 233). Prevalence of severe white matter lesions (WML) was defined as a score of 2 or higher on the Fazekas-scale on brain computed tomography to classify AD patients as having mixed dementia. We examined the effect of age on WML using multiple linear regression analysis, and AD patients were compared to SCI to determine the effect of disease on WML. RESULTS: Prevalence of severe WML was 33.6% in AD patients (mixed dementia), 11.4% in SCI, 22.7% in MCI, 75.4% in VaD, 3.8% in other dementia, and 15.5% in other diagnosis. With increasing age there was a significant and similar increase of WML scores in SCI, MCI, AD, other dementia, and other diagnosis, indicating no effect modification by AD. The difference between AD patients and SCI averaged 0.16 on the WML score and difference in percentage severe WML between AD and SCI patients was 15% across all ages. CONCLUSION: We found a low prevalence of mixed dementia. Furthermore, severe WML in AD was largely explained by age rather than effect of disease.
Keywords: Age Factors; Aged; Aged, 80 and over; Analysis of Variance; Cognitive Dysfunction; Cohort Studies; Dementia; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Prevalence; Regression Analysis; Risk Factors; Tomography Scanners, X-Ray Computed

Maintenance of Cognitive Performance and Mood for Individuals with Alzheimer's Disease Following Consumption of a Nutraceutical Formulation: A One-Year, Open-Label Study. - Remington, Ruth; Bechtel, Cynthia; Larsen, David; Samar, Annemarie; Page, Robert; Morrell, Christopher; Shea, Thomas B (J Alzheimers Dis, 2016)
Nutritional interventions have shown varied efficacy on cognitive performance during Alzheimer's disease (AD). Twenty-four individuals diagnosed with AD received a nutraceutical formulation (NF: folate, alpha-tocopherol, B12, S-adenosyl methioinine, N-acetyl cysteine, acetyl-L-carnitine) under open-label conditions (ClinicalTrials.gov NCT01320527). Primary outcome was cognitive performance. Secondary outcomes were behavioral and psychological symptoms of dementia (BPSD) and activities of daily living. Participants maintained their baseline cognitive performance and BPSD over 12 months. These findings are consistent with improvement in cognitive performance and BPSD in prior placebo-controlled studies with NF, and contrast with the routine decline for participants receiving placebo.
Keywords: Aged; Aged, 80 and over; alpha-Tocopherol; Alzheimer Disease; Cognition Disorders; Dietary Supplements; Disease Progression; Female; Folic Acid; Follow-Up Studies; Humans; Male; Mood Disorders; Neuropsychological Tests; Psychiatric Status Rating Scales; Time Factors; Vitamin B 12

Matrix Metalloproteinase in Blood-Brain Barrier Breakdown in Dementia. - Weekman, Erica M; Wilcock, Donna M (J Alzheimers Dis, 2016)
The neurovascular unit, which consists of astrocytic end-feet, neurons, pericytes, and endothelial cells, plays a key role in maintaining brain homeostasis by forming the blood-brain barrier and carefully controlling local cerebral blood flow. When the blood-brain barrier is disrupted, blood components can leak into the brain, damage the surrounding tissue and lead to cognitive impairment. This disruption in the blood-brain barrier and subsequent impairment in cognition are common after stroke and during cerebral amyloid angiopathy and Alzheimer's disease. Matrix metalloproteinases are proteases that degrade the extracellular matrix as well as tight junctions between endothelial cells and have been implicated in blood-brain barrier breakdown in neurodegenerative diseases. This review will focus on the roles of MMP2 and MMP9 in dementia, primarily post-stroke events that lead to dementia, cerebral amyloid angiopathy, and Alzheimer's disease.
Keywords: Animals; Blood-Brain Barrier; Dementia; Humans; Matrix Metalloproteinase 2; Matrix Metalloproteinase 9

A Mercaptoacetamide-Based Class II Histone Deacetylase Inhibitor Increases Dendritic Spine Density via RasGRF1/ERK Pathway. - Song, Jung Min; Sung, You Me; Nam, Jin Han; Yoon, Hyejin; Chung, Andrew; Moffat, Emily; Jung, Mira; Pak, Daniel T S; Kim, Jungsu; Hoe, Hyang-Sook (J Alzheimers Dis, 2016)
BACKGROUND: The accumulation of amyloid-β (Aβ) leads to the loss of dendritic spines and synapses, which is hypothesized to cause cognitive impairments in Alzheimer's disease (AD) patients. In our previous study, we demonstrated that a novel mercaptoacetamide-based class II histone deacetylase inhibitor (HDACI), known as W2, decreased Aβ levels and improved learning and memory in mice. However, the underlying mechanism of this effect is unknown. OBJECTIVE: Because dendritic spine formation is associated with cognitive performance, here we investigated whether HDACI W2 regulates dendritic spine density and its molecular mechanism of action. METHODS: To examine the effect of HDACI W2 on dendritic spine density, we conducted morphological analysis of dendritic spines using GFP transfection and Golgi staining. In addition, to determine the molecular mechanism of W2 effects on spines, we measured the levels of mRNAs and proteins involved in the Ras signaling pathway using quantitative real-time PCR, immunocytochemistry, and western analysis. RESULTS: We found that HDACI W2 altered dendritic spine density and morphology in vitro and in vivo. Additionally, W2 increased the mRNA or protein levels of Ras GRF1 and phospho-ERK. Moreover, knockdown of RasGRF1 and inhibition of ERK activity prevented the W2-mediated spinogenesis in primary hippocampal neurons. CONCLUSION: Our Class II-selective HDACI W2 promotes the formation and growth of dendritic spines in a RasGRF1 and ERK dependent manner in primary hippocampal neurons.
Keywords: Acetamides; Animals; Blotting, Western; Cells, Cultured; Cerebral Cortex; Dendritic Spines; Gene Knockdown Techniques; Green Fluorescent Proteins; Hippocampus; Histone Deacetylase Inhibitors; Immunohistochemistry; MAP Kinase Signaling System; Mice, Inbred C57BL; ras-GRF1; Rats, Sprague-Dawley; Real-Time Polymerase Chain Reaction; Receptors, AMPA; Receptors, N-Methyl-D-Aspartate; RNA, Messenger; Thioglycolates; Transfection

Metformin Facilitates Amyloid-β Generation by β- and γ-Secretases via Autophagy Activation. - Son, Sung Min; Shin, Hong-Joon; Byun, Jayoung; Kook, Sun Young; Moon, Minho; Chang, Yu Jin; Mook-Jung, Inhee (J Alzheimers Dis, 2016)
The evidence of strong pathological associations between type 2 diabetes and Alzheimer's disease (AD) has increased in recent years. Contrary to suggestions that anti-diabetes drugs may have potential for treating AD, we demonstrate here that the insulin sensitizing anti-diabetes drug metformin (Glucophage®) increased the generation of amyloid-β (Aβ), one of the major pathological hallmarks of AD, by promoting β- and γ-secretase-mediated cleavage of amyloid-β protein precursor (AβPP) in SH-SY5Y cells. In addition, we show that metformin caused autophagosome accumulation in Tg6799 AD model mice. Extremely high γ-secretase activity was also detected in autophagic vacuoles, apparently a novel site of Aβ peptide generation. Together, these data suggest that metformin-induced accumulation of autophagosomes resulted in increased γ-secretase activity and Aβ generation. Additional experiments indicated that metformin increased phosphorylation of AMP-activated protein kinase, which activates autophagy by suppressing mammalian target of rapamycin (mTOR). The suppression of mTOR then induces the abnormal accumulation of autophagosomes. We conclude that metformin, an anti-diabetes drug, may exacerbate AD pathogenesis by promoting amyloidogenic AβPP processing in autophagosomes.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Autophagy; Cell Line, Tumor; Disease Models, Animal; Female; Humans; Hypoglycemic Agents; Lysosomes; Metformin; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microscopy, Electron; Mutation; Neuroblastoma; Signal Transduction

Metformin in Amnestic Mild Cognitive Impairment: Results of a Pilot Randomized Placebo Controlled Clinical Trial. - Luchsinger, Jose A; Perez, Thania; Chang, Helena; Mehta, Pankaj; Steffener, Jason; Pradabhan, Gnanavalli; Ichise, Masanori; Manly, Jennifer; Devanand, Davangere P; Bagiella, Emilia (J Alzheimers Dis, 2016)
Diabetes and hyperinsulinemia may be risk factors for Alzheimer's disease (AD). We conducted a pilot study of metformin, a medication efficacious in treating and preventing diabetes while reducing hyperinsulinemia, among persons with amnestic mild cognitive impairment (aMCI) with the goal of collecting preliminary data on feasibility, safety, and efficacy. Participants were 80 men and women aged 55 to 90 years with aMCI, overweight or obese, without treated diabetes. We randomized participants to metformin 1000 mg twice a day or matching placebo for 12 months. The co-primary clinical outcomes were changes from baseline to 12 months in total recall of the Selective Reminding Test (SRT) and the score of the Alzheimer's Disease Assessment Scale-cognitive subscale (ADAS-cog). The secondary outcome was change in relative glucose uptake in the posterior cingulate-precuneus in brain fluorodeoxyglucose positron emission tomography. Change in plasma Aβ42 was an exploratory outcome. The mean age of participants was 65 years. Fifty percent of participants were women. The only baseline variable that was different between the arms was the ADAS-Cog. Metformin could not be tolerated by 7.5% of participants; 15% tolerated 500 mg/day, 35% tolerated 1000 mg/day, 32.5% tolerated 1500 mg/day, and only 10% tolerated the maximum dose. There were no serious adverse events related to metformin. The 7.5% of persons who did not tolerate metformin reported gastrointestinal symptoms. After adjusting for baseline ADAS-cog, changes in total recall of the SRT favored the metformin group (9.7±8.5 versus 5.3±8.5; p = 0.02). Differences for other outcomes were not significant. A larger trial seems warranted to evaluate the efficacy and cognitive safety of metformin in prodromal AD.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Brain; Cognitive Dysfunction; Double-Blind Method; Female; Follow-Up Studies; Glucose; Humans; Male; Metformin; Middle Aged; Nootropic Agents; Overweight; Peptide Fragments; Pilot Projects; Positron-Emission Tomography; Psychological Tests; Severity of Illness Index; Treatment Outcome

Mild Cognitive Impairment and Susceptibility to Scams in Old Age. - Han, S Duke; Boyle, Patricia A; James, Bryan D; Yu, Lei; Bennett, David A (J Alzheimers Dis, 2016)
BACKGROUND: Falling victim to financial scams can have a significant impact upon social and financial wellbeing and independence. A large proportion of scam victims are older adults, but whether older victims with mild cognitive impairment (MCI) are at higher risk remains unknown. OBJECTIVE: We tested the hypothesis that older persons with MCI exhibit greater susceptibility to scams compared to those without cognitive impairment. METHODS: Seven hundred and thirty older adults without dementia were recruited from the Rush Memory and Aging Project, a community-based epidemiologic study of aging. Participants completed a five-item self-report measure of susceptibility to scams, a battery of cognitive measures, and clinical diagnostic evaluations. RESULTS: In models adjusted for age, education, and gender, the presence of MCI was associated with greater susceptibility to scams (B = 0.125, SE = 0.063, p-value = 0.047). Further, in analyses of the role of specific cognitive systems in susceptibility to scams among persons with MCI (n = 144), the level of performance in two systems, episodic memory and perceptual speed abilities, were associated with susceptibility. CONCLUSIONS: Adults with MCI may be more susceptible to scams in old age than older persons with normal cognition. Lower abilities in specific cognitive systems, particularly perceptual speed and episodic memory, may contribute to greater susceptibility to scams in those with MCI.
Keywords: Aged; Aged, 80 and over; Aging; Cognitive Dysfunction; Crime Victims; Disease Susceptibility; Female; Humans; Male; Memory, Episodic; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Residence Characteristics; Self Report

Mindfulness in the Maintenance of Cognitive Capacities in Alzheimer's Disease: A Randomized Clinical Trial. - Quintana-Hernández, Domingo J; Miró-Barrachina, María T; Ibáñez-Fernández, Ignacio J; Pino, Angelo Santana-Del; Quintana-Montesdeoca, María P; Rodríguez-de Vera, Bienvenida; Morales-Casanova, David; Pérez-Vieitez, María Del Carmen; Rodríguez-García, Javier; Bravo-Caraduje, Noelia (J Alzheimers Dis, 2016)
BACKGROUND: The Canary Islands longitudinal study on non-pharmacological treatments showed the overall effectiveness of mindfulness in Alzheimer's disease (AD). However, no specific data on the maintenance of cognitive capacities were presented. OBJECTIVE: To determine whether the practice of mindfulness modifies the course of cognitive impairment in AD. METHODS: DESIGN: Longitudinal, non-inferiority and equivalence, randomized clinical trial, repeated-measures design, with three experimental groups and one control group. PARTICIPANTS: Patients with AD who voluntarily attended the Lidia García Foundation (n = 502). Only those who were treated with donepezil and MMSE ≥18 were included (n = 120). INTERVENTION: Over a two-year period, each group carried out three weekly sessions of stimulation based on mindfulness, cognitive stimulation therapy, and progressive muscle relaxation. MEASURES: Cognitive assessment CAMDEX-R (MMSE and CAMCOG). STATISTICAL ANALYSIS: Repeated-measures ANOVA (p <  0.05) and the effect size Cohen's d were performed. RESULTS: The mindfulness group showed significant scores compared with the control and muscle relaxation groups (p <  0.05), while mindfulness and cognitive stimulation therapy were equivalent (p≥0.05). Group cognitive stimulation evolved better than the control (p <  0.05) group but not better than the muscle relaxation group (p≥0.05). The effect size compared over two years was large for the mindfulness group (p≥0.80), moderate for the relaxation group (p≥0.50), and low for the cognitive stimulation group (p≥0.20). CONCLUSION: The practice of mindfulness maintained cognitive function over a period of two years. This longitudinal study suggests that mindfulness can be used as a non-pharmacological treatment to slow cognitive impairment in AD.
Keywords: Age Factors; Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Cognition Disorders; Double-Blind Method; Female; Humans; Longitudinal Studies; Male; Mental Status Schedule; Mindfulness; Neuropsychological Tests; Treatment Outcome

Moderate-to-High Intensity Physical Exercise in Patients with Alzheimer's Disease: A Randomized Controlled Trial. - Hoffmann, Kristine; Sobol, Nanna A; Frederiksen, Kristian S; Beyer, Nina; Vogel, Asmus; Vestergaard, Karsten; Brændgaard, Hans; Gottrup, Hanne; Lolk, Annette; Wermuth, Lene; Jacobsen, Søren; Laugesen, Lars P; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Studies of physical exercise in patients with Alzheimer's disease (AD) are few and results have been inconsistent. OBJECTIVE: To assess the effects of a moderate-to-high intensity aerobic exercise program in patients with mild AD. METHODS: In a randomized controlled trial, we recruited 200 patients with mild AD to a supervised exercise group (60-min sessions three times a week for 16 weeks) or to a control group. Primary outcome was changed from baseline in cognitive performance estimated by Symbol Digit Modalities Test (SDMT) in the intention-to-treat (ITT) group. Secondary outcomes included changes in quality of life, ability to perform activities of daily living, and in neuropsychiatric and depressive symptoms. RESULTS: The ITT analysis showed no significant differences between intervention and control groups in change from baseline of SDMT, other cognitive tests, quality of life, or activities of daily living. The change from baseline in Neuropsychiatric Inventory differed significantly in favor of the intervention group (mean: -3.5, 95% confidence interval (CI) -5.8 to -1.3, p = 0.002). In subjects who adhered to the protocol, we found a significant effect on change from baseline in SDMT as compared with the control group (mean: 4.2, 95% CI 0.5 to 7.9, p = 0.028), suggesting a dose-response relationship between exercise and cognition. CONCLUSIONS: This is the first randomized controlled trial with supervised moderate-to-high intensity exercise in patients with mild AD. Exercise reduced neuropsychiatric symptoms in patients with mild AD, with possible additional benefits of preserved cognition in a subgroup of patients exercising with high attendance and intensity.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Depression; Exercise; Exercise Therapy; Female; Humans; Male; Middle Aged; Quality of Life; Treatment Outcome

Modulation of miR-19 in Aluminum-Induced Neural Cell Apoptosis. - Zhu, Mingming; Huang, Cong; Ma, Xiao; Wu, Rui; Zhu, Weiwei; Li, Xiaoting; Liang, Zhaofeng; Deng, Feifei; Zhu, Jianyun; Xie, Wei; Yang, Xue; Jiang, Ye; et al. (J Alzheimers Dis, 2016)
Neuronal cell death is an important feature of neurodegeneration. Aluminum is associated with neurodegenerative disorders, particularly Alzheimer's disease. However, the underlying mechanisms by which aluminum induces neuronal apoptosis remain to be elucidated. miR-19 is a key miRNA implicated in regulating cell survival process, while the role of miR-19 in Alzheimer's disease has not been investigated. In the present study, we showed that Aluminum maltolate (Al-malt), a lipophilic Al complex which is a common component of human diet with the ability to facilitate the entry of Al into the brain, induced apoptosis in human neuroblastoma SH-SY5Y cells, along with downregulation of miR-19a/miR-19b, upregulation of miR-19-targeted PTEN, and alterations of its downstream apoptosis related proteins including AKT, p53, Bax, and Bcl-2. miR-19 overexpression attenuated Al-malt-induced apoptosis as well as changes in the expression of apoptosis related proteins in SH-SY5Y cells. We further revealed that exposure of rats to Al-malt for 12 weeks at doses relevant to human exposure significantly elevated Al concentrations in serum and brain tissues. Al-malt dose-dependently induced apoptosis in rat brain, as evidenced by increased caspase activation and increased TUNEL staining. Consistent with in vitro results, Al-malt reduced miR-19 expression and altered the expression of apoptotic related proteins in rat brain. Taken together, our data suggest for the first time that miR-19 modulation is critically involved in Al-induced neural cell apoptosis. Findings from this study could provide new insight into the molecular mechanisms of Al-associated neurodegenerative pathogenesis.
Keywords: Aluminum; Animals; Apoptosis; Brain; Cell Line, Tumor; Dose-Response Relationship, Drug; Humans; Male; MicroRNAs; Neurons; Proto-Oncogene Proteins c-akt; PTEN Phosphohydrolase; Rats, Sprague-Dawley; Tumor Suppressor Protein p53

Multifunctional Effect of Human Serum Albumin Reduces Alzheimer's Disease Related Pathologies in the 3xTg Mouse Model. - Ezra, Assaf; Rabinovich-Nikitin, Inna; Rabinovich-Toidman, Polina; Solomon, Beka (J Alzheimers Dis, 2016)
Alzheimer's disease (AD), the prevalent dementia in the elderly, involves many related and interdependent pathologies that manifests simultaneously, eventually leading to cognitive impairment and death. No treatment is currently available; however, an agent addressing several key pathologies simultaneously has a better therapeutic potential. Human serum albumin (HSA) is a highly versatile protein, harboring multifunctional properties that are relevant to key pathologies underlying AD. This study provides insight into the mechanism for HSA's therapeutic effect. In vivo, a myriad of beneficial effects were observed by pumps infusing HSA intracerebroventricularly, for the first time in an AD 3xTg mice model. A significant effect on amyloid-β (Aβ) pathology was observed. Aβ1-42, soluble oligomers, and total plaque area were reduced. Neuroblastoma SHSY5Y cell line confirmed that the reduction in Aβ1-42 toxicity was due to direct binding rather than other properties of HSA. Total and hyperphosphorylated tau were reduced along with an increase in tubulin, suggesting increased microtubule stability. HSA treatment also reduced brain inflammation, affecting both astrocytes and microglia markers. Finally, evidence for blood-brain barrier and myelin integrity repair was observed. These multidimensional beneficial effects of intracranial administrated HSA, together or individually, contributed to an improvement in cognitive tests, suggesting a non-immune or Aβ efflux dependent means for treating AD.
Keywords: Albumins; Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Blood-Brain Barrier; Brain; Calcium; Cell Line, Tumor; Cognition Disorders; Disease Models, Animal; Drug Delivery Systems; Encephalitis; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Neuroblastoma; Neuropsychological Tests; Peptide Fragments; Presenilin-1; tau Proteins

Multimodal Magnetic Resonance Imaging in Alzheimer's Disease Patients at Prodromal Stage. - Eustache, Pierre; Nemmi, Federico; Saint-Aubert, Laure; Pariente, Jérémie; Péran, Patrice (J Alzheimers Dis, 2016)
One objective of modern neuroimaging is to identify markers that can aid in diagnosis, monitor disease progression, and impact long-term drug analysis. In this study, physiopathological modifications in seven subcortical structures of patients with mild cognitive impairment (MCI) due to Alzheimer's disease (AD) were characterized by simultaneously measuring quantitative magnetic resonance parameters that are sensitive to complementary tissue characteristics (e.g., volume atrophy, shape changes, microstructural damage, and iron deposition). Fourteen MCI patients and fourteen matched, healthy subjects underwent 3T-magnetic resonance imaging with whole-brain, T1-weighted, T2*-weighted, and diffusion-tensor imaging scans. Volume, shape, mean R2*, mean diffusivity (MD), and mean fractional anisotropy (FA) in the thalamus, hippocampus, putamen, amygdala, caudate nucleus, pallidum, and accumbens were compared between MCI patients and healthy subjects. Comparisons were then performed using voxel-based analyses of R2*, MD, FA maps, and voxel-based morphometry to determine which subregions showed the greatest difference for each parameter. With respect to the micro- and macro-structural patterns of damage, our results suggest that different and distinct physiopathological processes are present in the prodromal phase of AD. MCI patients had significant atrophy and microstructural changes within their hippocampi and amygdalae, which are known to be affected in the prodromal stage of AD. This suggests that the amygdala is affected in the same, direct physiopathological process as the hippocampus. Conversely, atrophy alone was observed within the thalamus and putamen, which are not directly involved in AD pathogenesis. This latter result may reflect another mechanism, whereby atrophy is linked to indirect physiopathological processes.
Keywords: Aged; Alzheimer Disease; Biomarkers; Brain; Cognitive Dysfunction; Diffusion Tensor Imaging; Female; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Mental Status Schedule; Multimodal Imaging; Neuropsychological Tests; Organ Size; Positron-Emission Tomography; Prodromal Symptoms; Radiopharmaceuticals

Music and Memory in Alzheimer's Disease and The Potential Underlying Mechanisms. - Peck, Katlyn J; Girard, Todd A; Russo, Frank A; Fiocco, Alexandra J (J Alzheimers Dis, 2016)
With population aging and a projected exponential expansion of persons diagnosed with Alzheimer's disease (AD), the development of treatment and prevention programs has become a fervent area of research and discovery. A growing body of evidence suggests that music exposure can enhance memory and emotional function in persons with AD. However, there is a paucity of research that aims to identify specific underlying neural mechanisms associated with music's beneficial effects in this particular population. As such, this paper reviews existing anecdotal and empirical evidence related to the enhancing effects of music exposure on cognitive function and further provides a discussion on the potential underlying mechanisms that may explain music's beneficial effect. Specifically, this paper will outline the potential role of the dopaminergic system, the autonomic nervous system, and the default network in explaining how music may enhance memory function in persons with AD.
Keywords: Alzheimer Disease; Auditory Perception; Autonomic Nervous System; Dopamine; Humans; Memory Disorders; Music Therapy

Naphthoquinone-Tryptophan Hybrid Inhibits Aggregation of the Tau-Derived Peptide PHF6 and Reduces Neurotoxicity. - Frenkel-Pinter, Moran; Tal, Sharon; Scherzer-Attali, Roni; Abu-Hussien, Malak; Alyagor, Idan; Eisenbaum, Tal; Gazit, Ehud; Segal, Daniel (J Alzheimers Dis, 2016)
Tauopathies, such as Alzheimer's disease (AD), are a group of disorders characterized neuropathologically by intracellular toxic accumulations of abnormal protein aggregates formed by misfolding of the microtubule-associated protein tau. Since protein self-assembly appears to be an initial key step in the pathology of this group of diseases, intervening in this process can be both a prophylactic measure and a means for modifying the course of the disease for therapeutic purposes. We and others have shown that aromatic small molecules can be effective inhibitors of aggregation of various protein assemblies, by binding to the aromatic core in aggregation-prone motifs and preventing their self-assembly. Specifically, we have designed a series of small aromatic naphthoquinone-tryptophan hybrid molecules as candidate aggregation inhibitors of β -sheet based assembly and demonstrated their efficacy toward inhibiting aggregation of the amyloid-β peptide, another culprit of AD, as well as of various other aggregative proteins involved in other protein misfolding diseases. Here we tested whether a leading naphthoquinone-tryptophan hybrid molecule, namely NQTrp, can be repurposed as an inhibitor of the aggregation of the tau protein in vitro and in vivo. We show that the molecule inhibits the in vitro assembly of PHF6, the aggregation-prone fragment of tau protein, reduces hyperphosphorylated tau deposits and ameliorates tauopathy-related behavioral defect in an established transgenic Drosophila model expressing human tau. We suggest that NQTrp, or optimized versions of it, could act as novel disease modifying drugs for AD and other tauopathies.
Keywords: Animals; Carrier Proteins; Disease Models, Animal; Drosophila; Drosophila Proteins; Eye; Female; Humans; Immunoprecipitation; In Vitro Techniques; Larva; Locomotion; Mice, Transgenic; Microscopy, Electron, Scanning; Naphthoquinones; Neurotoxicity Syndromes; Protein Aggregates; Retinal Pigments; tau Proteins; Tryptophan

Neuronal activity and amyloid plaque pathology: an update. - Ovsepian, Saak V; O'Leary, Valerie B (J Alzheimers Dis, 2016)
A breakthrough in Alzheimer's disease (AD) research came with the discovery of the link between activity-dependent release of amyloid-β (Aβ) from neurons and formation of amyloid plaques. Along with elucidating the cellular basis of behavioral-dependent fluctuations in Aβ levels in the brain, insights have been gained toward understanding the mechanisms that warrant selective vulnerability of various forebrain circuits to amyloid pathology. The notion of elevated activity as a source of excessive Aβ production and plaque formation is, however, in conflict with ample electrophysiological data, which demonstrate exceedingly intense activity (both intrinsic and synaptic) of neurons in several brain regions that are spared or marginally affected by amyloid plaques of AD. Thus, the link between the functional load of brain circuits and their vulnerability to amyloidosis, while evident, is also complex and remains poorly understood. Here, we discuss emerging data suggestive of a major role for super-intense synchronous activity of cortical and limbic networks in excessive Aβ production and plaque formation. It is proposed that dense recurrent wiring of associative areas prone to epileptic seizures might be of critical relevance to their higher susceptibility to plaque pathology and related functional impairments.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid Precursor Protein Secretases; Amyloidosis; Animals; Disease Models, Animal; Humans; Mice; Mice, Transgenic; Neurons; Plaque, Amyloid; Prosencephalon; Seizures

Non-Verbal Episodic Memory Deficits in Primary Progressive Aphasias are Highly Predictive of Underlying Amyloid Pathology. - Ramanan, Siddharth; Flanagan, Emma; Leyton, Cristian E; Villemagne, Victor L; Rowe, Christopher C; Hodges, John R; Hornberger, Michael (J Alzheimers Dis, 2016)
Diagnostic distinction of primary progressive aphasias (PPA) remains challenging, in particular for the logopenic (lvPPA) and nonfluent/agrammatic (naPPA) variants. Recent findings highlight that episodic memory deficits appear to discriminate these PPA variants from each other, as only lvPPA perform poorly on these tasks while having underlying amyloid pathology similar to that seen in amnestic dementias like Alzheimer's disease (AD). Most memory tests are, however, language based and thus potentially confounded by the prevalent language deficits in PPA. The current study investigated this issue across PPA variants by contrasting verbal and non-verbal episodic memory measures while controlling for their performance on a language subtest of a general cognitive screen. A total of 203 participants were included (25 lvPPA; 29 naPPA; 59 AD; 90 controls) and underwent extensive verbal and non-verbal episodic memory testing, with a subset of patients (n = 45) with confirmed amyloid profiles as assessed by Pittsburgh Compound B and PET. The most powerful discriminator between naPPA and lvPPA patients was a non-verbal recall measure (Rey Complex Figure delayed recall), with 81% of PPA patients classified correctly at presentation. Importantly, AD and lvPPA patients performed comparably on this measure, further highlighting the importance of underlying amyloid pathology in episodic memory profiles. The findings demonstrate that non-verbal recall emerges as the best discriminator of lvPPA and naPPA when controlling for language deficits in high load amyloid PPA cases.
Keywords: Aged; Alzheimer Disease; Amyloid; Aniline Compounds; Aphasia, Primary Progressive; Brain; Diagnosis, Differential; Female; Humans; Logistic Models; Male; Memory, Episodic; Neuropsychological Tests; Positron-Emission Tomography; Radiopharmaceuticals; Speech Perception; Thiazoles

Normal Amplitude of Electroretinography and Visual Evoked Potential Responses in AβPP/PS1 Mice. - Leinonen, Henri; Lipponen, Arto; Gurevicius, Kestutis; Tanila, Heikki (J Alzheimers Dis, 2016)
Alzheimer's disease has been shown to affect vision in human patients and animal models. This may pose the risk of bias in behavior studies and therefore requires comprehensive investigation. We recorded electroretinography (ERG) under isoflurane anesthesia and visual evoked potentials (VEP) in awake amyloid expressing AβPPswe/PS1dE9 (AβPP/PS1) and wild-type littermate mice at a symptomatic age. The VEPs in response to patterned stimuli were normal in AβPP/PS1 mice. They also showed normal ERG amplitude but slightly shortened ERG latency in dark-adapted conditions. Our results indicate subtle changes in visual processing in aged male AβPP/PS1 mice specifically at a retinal level.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Contrast Sensitivity; Disease Models, Animal; Electroencephalography; Electroretinography; Evoked Potentials, Visual; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Photic Stimulation; Presenilin-1; Reaction Time

Novel Selective Calpain 1 Inhibitors as Potential Therapeutics in Alzheimer's Disease. - Fà, Mauro; Zhang, Hong; Staniszewski, Agnieszka; Saeed, Faisal; Shen, Li W; Schiefer, Isaac T; Siklos, Marton I; Tapadar, Subhasish; Litosh, Vladislav A; Libien, Jenny; Petukhov, Pavel A; Teich, Andrew F; et al. (J Alzheimers Dis, 2016)
Alzheimer's disease, one of the most important brain pathologies associated with neurodegenerative processes, is related to overactivation of calpain-mediated proteolysis. Previous data showed a compelling efficacy of calpain inhibition against abnormal synaptic plasticity and memory produced by the excess of amyloid-β, a distinctive marker of the disease. Moreover, a beneficial effect of calpain inhibitors in Alzheimer's disease is predictable by the occurrence of calpain hyperactivation leading to impairment of memory-related pathways following abnormal calcium influxes that might ensue independently of amyloid-β elevation. However, molecules currently available as effective calpain inhibitors lack adequate selectivity. This work is aimed at characterizing the efficacy of a novel class of epoxide-based inhibitors, synthesized to display improved selectivity and potency towards calpain 1 compared to the prototype epoxide-based generic calpain inhibitor E64. Both functional and preliminary toxicological investigations proved the efficacy, potency, and safety of the novel and selective calpain inhibitors NYC438 and NYC488 as possible therapeutics against the disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cysteine Proteinase Inhibitors; Disease Models, Animal; Dose-Response Relationship, Drug; Fear; Glycoproteins; Hippocampus; Humans; In Vitro Techniques; Long-Term Potentiation; Maze Learning; Memory; Mice; Mice, Inbred ICR; Mice, Transgenic; Mutation; Patch-Clamp Techniques; Peptide Fragments; Presenilin-1; Spectrin

N-truncated Aβ2-X starting with position two in sporadic Alzheimer's disease cases and two Alzheimer mouse models. - Savastano, Adriana; Klafki, Hans; Haußmann, Ute; Oberstein, Timo Jan; Muller, Petr; Wirths, Oliver; Wiltfang, Jens; Bayer, Thomas A (J Alzheimers Dis, 2016)
According to the modified amyloid hypothesis, the key event in the pathogenesis of Alzheimer's disease (AD) is the deposition of neurotoxic amyloid β-peptides (Aβs) in plaques and cerebral blood vessels. Additionally to full-length peptides, a great diversity of N-truncated Aβ variants is derived from the larger amyloid-β protein precursor (AβPP). Vast evidence suggests that Aβx-42 isoforms play an important role in triggering neurodegeneration due to their high abundance, amyloidogenic propensity and toxicity. Although N-truncated Aβ peptides and Aβx-42 species appear to be the crucial players in AD etiology, the Aβ2-X isoforms did not receive much attention yet. The present study is the first to show immunohistochemical evidence of Aβ2-X in cases of AD and its distribution in AβPP/PS1KI and 5XFAD transgenic mouse models using a novel antibody pAB77 that has been developed using Aβ2-14 as antigen. Positive plaques and congophilic amyloid angiopathy (CAA) were observed in AD cases and in both mouse models. While in AD cases, abundant CAA and less pronounced plaque pathology was evident, the two mouse models showed predominantly extracellular Aβ deposits and minor CAA staining. Western blotting and a capillary isoelectric focusing immunoassay demonstrated the high specificity of the antibody pAb77 against Aβ-variants starting with the N-terminal Alanine-2.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Animals; Blotting, Western; Brain; Cerebral Amyloid Angiopathy; Disease Models, Animal; Female; Humans; Male; Mice; Mice, Transgenic; Plaque, Amyloid

Nutritional Status is Associated with Faster Cognitive Decline and Worse Functional Impairment in the Progression of Dementia: The Cache County Dementia Progression Study1. - Sanders, Chelsea; Behrens, Stephanie; Schwartz, Sarah; Wengreen, Heidi; Corcoran, Chris D; Lyketsos, Constantine G; Tschanz, JoAnn T (J Alzheimers Dis, 2016)
Nutritional status may be a modifiable factor in the progression of dementia. We examined the association of nutritional status and rate of cognitive and functional decline in a U.S. population-based sample. Study design was an observational longitudinal study with annual follow-ups up to 6 years of 292 persons with dementia (72% Alzheimer's disease, 56% female) in Cache County, UT using the Mini-Mental State Exam (MMSE), Clinical Dementia Rating Sum of Boxes (CDR-sb), and modified Mini Nutritional Assessment (mMNA). mMNA scores declined by approximately 0.50 points/year, suggesting increasing risk for malnutrition. Lower mMNA score predicted faster rate of decline on the MMSE at earlier follow-up times, but slower decline at later follow-up times, whereas higher mMNA scores had the opposite pattern (mMNA by time β= 0.22, p = 0.017; mMNA by time2 β= -0.04, p = 0.04). Lower mMNA score was associated with greater impairment on the CDR-sb over the course of dementia (β= 0.35, p <  0.001). Assessment of malnutrition may be useful in predicting rates of progression in dementia and may provide a target for clinical intervention.
Keywords: Age of Onset; Aged, 80 and over; Alzheimer Disease; Dementia, Vascular; Disease Progression; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Mental Status Schedule; Nutritional Status; Severity of Illness Index; Sex Factors; Utah

Oculodentodigital dysplasia with massive brain calcification and a new mutation of GJA1 gene. - Tumminelli, Gemma; Di Donato, Ilaria; Guida, Valentina; Rufa, Alessandra; De Luca, Alessandro; Federico, Antonio (J Alzheimers Dis, 2016)
Oculodentodigital dysplasia (ODDD) [MIM 164200] is a rare disorder caused by mutations in the gap junction alpha 1 (GJA1) gene encoding for connexin 43 (Cx43). Typical signs include type III syndactyly, microphtalmia, microdontia, and neurological disturbances. We report a 59-year-old man having clinical symptoms and signs suggestive of ODDD, with some rarely reported features, that is the presence of gross calcifications of basal ganglia and cerebellar nuclei. Mutation analysis of GJA1 gene identified an unreported heterozygous missense mutation [NM_000165.3:c.124 G>C;p.(Glu42Gln)], which may be thought to alter the brain microvessels leading to massive calcifications, as in primary familial brain calcification.
Keywords: Basal Ganglia; Calcinosis; Connexin 43; Craniofacial Abnormalities; DNA Mutational Analysis; Eye Abnormalities; Fingers; Foot Deformities, Congenital; Humans; Male; Middle Aged; Mutation, Missense; Syndactyly; Tomography, X-Ray Computed; Tooth Abnormalities

Older Adults Taking AT1-Receptor Blockers Exhibit Reduced Cerebral Amyloid Retention. - Nation, Daniel A; Ho, Jean; Yew, Belinda (J Alzheimers Dis, 2016)
BACKGROUND: Evidence suggests that angiotensin II AT1-receptor blockers (ARBs) may be protective against dementia, and studies in transgenic animals indicate that this may be due to improved amyloid-β (Aβ) clearance. OBJECTIVE: We investigated whether taking ARBs was associated with an attenuation of age-related increases in cerebral Aβ retention, and reduced progression to dementia. METHODS: Eight hundred seventy-one stroke-free and dementia-free older adults from the Alzheimer's Disease Neuroimaging Initiative (ADNI) study underwent baseline lumbar puncture, and a subgroup (n = 124) underwent 12 and 24 month follow-up lumbar puncture. Participants were followed at variable intervals for clinical progression to dementia. Linear mixed models and ANCOVA compared ARBs users with those taking other antihypertensives (O-antiHTN) or no antihypertensives (No-antiHTN) on cerebrospinal fluid (CSF) Aβ and phosphorylated tau (P-tau) levels. Cox regression and chi-square analyses compared groups on progression to dementia. RESULTS: ARBs users exhibited greater vascular risk and lower educational attainment than the No-antiHTN group. Longitudinal analyses indicated higher CSF Aβ and lower P-tau in ARBs users versus other groups. Cross-sectional analyses revealed age-related decreases in CSF Aβ in other groups but not ARBs users. ARBs users were less likely to progress to dementia and showed reduced rate of progression relative to the No-antiHTN group. DISCUSSION: Patients taking ARBs showed an attenuation of age-related decreases in CSF Aβ, a finding that is consistent with studies done in transgenic animals. These findings may partly explain why ARBs users show reduced progression to dementia despite their lower educational attainment and greater vascular risk burden.
Keywords: Aged; Aged, 80 and over; Aging; Amyloid beta-Peptides; Angiotensin Receptor Antagonists; Antihypertensive Agents; Chi-Square Distribution; Cross-Sectional Studies; Dementia; Female; Humans; Longitudinal Studies; Male; Middle Aged; Peptide Fragments; Psychiatric Status Rating Scales; Regression Analysis; tau Proteins; Time Factors

Omega-3 Fatty Acid Status Enhances the Prevention of Cognitive Decline by B Vitamins in Mild Cognitive Impairment. - Oulhaj, Abderrahim; Jernerén, Fredrik; Refsum, Helga; Smith, A David; de Jager, Celeste A (J Alzheimers Dis, 2016)
A randomized trial (VITACOG) in people with mild cognitive impairment (MCI) found that B vitamin treatment to lower homocysteine slowed the rate of cognitive and clinical decline. We have used data from this trial to see whether baseline omega-3 fatty acid status interacts with the effects of B vitamin treatment. 266 participants with MCI aged ≥70 years were randomized to B vitamins (folic acid, vitamins B6 and B12) or placebo for 2 years. Baseline cognitive test performance, clinical dementia rating (CDR) scale, and plasma concentrations of total homocysteine, total docosahexaenoic and eicosapentaenoic acids (omega-3 fatty acids) were measured. Final scores for verbal delayed recall, global cognition, and CDR sum-of-boxes were better in the B vitamin-treated group according to increasing baseline concentrations of omega-3 fatty acids, whereas scores in the placebo group were similar across these concentrations. Among those with good omega-3 status, 33% of those on B vitamin treatment had global CDR scores >0 compared with 59% among those on placebo. For all three outcome measures, higher concentrations of docosahexaenoic acid alone significantly enhanced the cognitive effects of B vitamins, while eicosapentaenoic acid appeared less effective. When omega-3 fatty acid concentrations are low, B vitamin treatment has no effect on cognitive decline in MCI, but when omega-3 levels are in the upper normal range, B vitamins interact to slow cognitive decline. A clinical trial of B vitamins combined with omega-3 fatty acids is needed to see whether it is possible to slow the conversion from MCI to AD.
Keywords: Aged; Aged, 80 and over; Cognition; Cognitive Dysfunction; Disease Progression; Fatty Acids, Omega-3; Female; Humans; Male; Neuropsychological Tests; Treatment Outcome; Vitamin B Complex

Optimization of Statistical Single Subject Analysis of Brain FDG PET for the Prognosis of Mild Cognitive Impairment-to-Alzheimer's Disease Conversion. - Lange, Catharina; Suppa, Per; Frings, Lars; Brenner, Winfried; Spies, Lothar; Buchert, Ralph (J Alzheimers Dis, 2016)
BACKGROUND: Positron emission tomography (PET) with the glucose analog F-18-fluorodeoxyglucose (FDG) is widely used in the diagnosis of neurodegenerative diseases. Guidelines recommend voxel-based statistical testing to support visual evaluation of the PET images. However, the performance of voxel-based testing strongly depends on each single preprocessing step involved. OBJECTIVE: To optimize the processing pipeline of voxel-based testing for the prognosis of dementia in subjects with amnestic mild cognitive impairment (MCI). METHODS: The study included 108 ADNI MCI subjects grouped as 'stable MCI' (n = 77) or 'MCI-to-AD converter' according to their diagnostic trajectory over 3 years. Thirty-two ADNI normals served as controls. Voxel-based testing was performed with the statistical parametric mapping software (SPM8) starting with default settings. The following modifications were added step-by-step: (i) motion correction, (ii) custom-made FDG template, (iii) different reference regions for intensity scaling, and (iv) smoothing was varied between 8 and 18 mm. The t-sum score for hypometabolism within a predefined AD mask was compared between the different settings using receiver operating characteristic (ROC) analysis with respect to differentiation between 'stable MCI' and 'MCI-to-AD converter'. The area (AUC) under the ROC curve was used as performance measure. RESULTS: The default setting provided an AUC of 0.728. The modifications of the processing pipeline improved the AUC up to 0.832 (p = 0.046). Improvement of the AUC was confirmed in an independent validation sample of 241 ADNI MCI subjects (p = 0.048). CONCLUSION: The prognostic value of voxel-based single subject analysis of brain FDG PET in MCI subjects can be improved considerably by optimizing the processing pipeline.
Keywords: Aged; Alzheimer Disease; Area Under Curve; Brain; Cognitive Dysfunction; Disease Progression; Female; Fluorodeoxyglucose F18; Follow-Up Studies; Glucose; Humans; Image Interpretation, Computer-Assisted; Male; Positron-Emission Tomography; Prognosis; Radiopharmaceuticals; ROC Curve

An Optimized Combination of Ginger and Peony Root Effectively Inhibits Amyloid-β Accumulation and Amyloid-β-Mediated Pathology in AβPP/PS1 Double-Transgenic Mice. - Lim, Soonmin; Choi, Jin Gyu; Moon, Minho; Kim, Hyo Geun; Lee, Wonil; Bak, Hyoung-Rok; Sung, Hachang; Park, Chi Hye; Kim, Sun Yeou; Oh, Myung Sook (J Alzheimers Dis, 2016)
The progressive aggregation of amyloid-β protein (Aβ) into senile plaques is a major pathological factor of Alzheimer's disease (AD) and is believed to result in memory impairment. We aimed to investigate the effect of an optimized combination of ginger and peony root (OCGP), a standardized herbal mixture of ginger and peony root, on Aβ accumulation and memory impairment in amyloid-β protein precursor (AβPP)/presenilin 1 (PS1) double-transgenic mice. In an in vitro thioflavin T fluorescence assay, 100 μg/ml OCGP inhibited Aβ accumulation to the same extent as did 10 μM curcumin. Furthermore, AβPP/PS1 double-transgenic mice treated with OCGP (50 or 100 mg/kg/day given orally for 14 weeks) exhibited reduced Aβ plaque accumulation in the hippocampus and lower levels of glial fibrillary acid protein and cyclooxygease-2 expression compared with vehicle-treated controls. These results suggest that OCGP may prevent memory impairment in AD by inhibiting Aβ accumulation and inflammation in the brain.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Analysis of Variance; Animals; Cyclooxygenase 2; Disease Models, Animal; Dose-Response Relationship, Drug; Ginger; Glial Fibrillary Acidic Protein; Humans; Male; Mice; Mice, Transgenic; Mutation; Paeonia; Phytotherapy; Plant Preparations; Plaque, Amyloid; Presenilin-1

Overexpression of Metallothionein-1 Modulates the Phenotype of the Tg2576 Mouse Model of Alzheimer's Disease. - Manso, Yasmina; Comes, Gemma; López-Ramos, Juan C; Belfiore, Mónica; Molinero, Amalia; Giralt, Mercedes; Carrasco, Javier; Adlard, Paul A; Bush, Ashley I; Delgado-García, José María; Hidalgo, Juan (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is the most commonly diagnosed dementia, where signs of neuroinflammation and oxidative stress are prominent. In this study we intend to further characterize the roles of the antioxidant, anti-inflammatory, and heavy metal binding protein, metallothionein-1 (MT-1), by crossing Mt1 overexpressing mice with a well-known mouse model of AD, Tg2576 mice, which express the human amyloid-β protein precursor (hAβPP) with the Swedish K670N/M671L mutations. Mt1 overexpression increased overall perinatal survival, but did not affect significantly hAβPP-induced mortality and weight loss in adult mice. Amyloid plaque burden in ∼14-month-old mice was increased by Mt1 overexpression in the hippocampus but not the cortex. Despite full length hAβPP levels and amyloid plaques being increased by Mt1 overexpression in the hippocampus of both sexes, oligomeric and monomeric forms of Aβ, which may contribute more to toxicity, were decreased in the hippocampus of females and increased in males. Several behavioral traits such as exploration, anxiety, and learning were altered in Tg2576 mice to various degrees depending on the age and the sex. Mt1 overexpression ameliorated the effects of hAβPP on exploration in young females, and potentiated those on anxiety in old males, and seemed to improve the rate of spatial learning (Morris water maze) and the learning elicited by a classical conditioning procedure (eye-blink test). These results clearly suggest that MT-1 may be involved in AD pathogenesis.
Keywords: Age Factors; Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Anxiety; Disease Models, Animal; Exploratory Behavior; Female; Gene Expression Regulation; Humans; Male; Matrix Metalloproteinase 16; Maze Learning; Metallothionein; Mice; Mice, Inbred C57BL; Mice, Transgenic; Motor Activity; Mutation; Phenotype; Psychomotor Disorders

Pain Assessment in Elderly with Behavioral and Psychological Symptoms of Dementia. - Malara, Alba; De Biase, Giuseppe Andrea; Bettarini, Francesco; Ceravolo, Francesco; Di Cello, Serena; Garo, Michele; Praino, Francesco; Settembrini, Vincenzo; Sgrò, Giovanni; Spadea, Fausto; Rispoli, Vincenzo (J Alzheimers Dis, 2016)
BACKGROUND: Pain is under-detected and undertreated in people with dementia. The present study investigates the prevalence of pain in people with dementia hospitalized in nursing homes that are members of National Association of Third Age Residences (ANASTE) Calabria, and evaluates the association among pain, mood, and behavioral and psychological symptoms of dementia (BPSD). OBJECTIVE: The aim of this study is to define the prevalence of pain in people with dementia in long term care facilities using scales of self-reporting and observational tools and, particularly, to study the relationship between pain and BPSD. METHODS: A prospective observational study was carried out on 233 patients. Pain assessment was performed using self-reporting tools such as the Numeric Rating Scale (NRS) for patients with slight cognitive impairment or no cognitive impairment and observational tools such as Pain Assessment In Advanced Dementia Scale (PAINAD) for patients with moderate or severe cognitive impairment. Mood was evaluated through the Cornell Scale for Depression in Dementia (CSDD) while behavioral problems were assessed through the Cohen-Mansfield Agitation Inventory (CMAI) and Neuropsychiatric Inventory (NPI). RESULTS: Only 42.5% of patients evaluated by NRS provided a reliable answer; of these, 20.4% reported no pain. The percentage of pain evaluated by PAINAD was 51.8% . Analysis of data showed a statistically significant correlation between diagnosis of pain and depressive symptoms, assessed with CSDD (p = 0.0113), as well as by single items of NPI, such as anxiety (p = 0.0362) and irritability (p = 0.0034), and F1 profile (Aggression) of CMAI (p = 0.01). CONCLUSION: This study confirms that self-report alone is not sufficient to assess pain in elderly people with dementia; the observational tool is a necessary and suitable way of assessing pain in patients with cognitive impairment. If not adequately treated, chronic pain can cause depression, agitation, and aggression in patients with dementia.
Keywords: Affect; Aged, 80 and over; Analgesics; Anxiety; Dementia; Depression; Female; Humans; Italy; Logistic Models; Long-Term Care; Male; Multivariate Analysis; Nursing Homes; Pain; Pain Measurement; Prevalence; Prospective Studies; Psychiatric Status Rating Scales; Self Report; Severity of Illness Index

A Pathway Based Classification Method for Analyzing Gene Expression for Alzheimer's Disease Diagnosis. - Voyle, Nicola; Keohane, Aoife; Newhouse, Stephen; Lunnon, Katie; Johnston, Caroline; Soininen, Hilkka; Kloszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Lovestone, Simon; Hodges, Angela; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Recent studies indicate that gene expression levels in blood may be able to differentiate subjects with Alzheimer's disease (AD) from normal elderly controls and mild cognitively impaired (MCI) subjects. However, there is limited replicability at the single marker level. A pathway-based interpretation of gene expression may prove more robust. OBJECTIVES: This study aimed to investigate whether a case/control classification model built on pathway level data was more robust than a gene level model and may consequently perform better in test data. The study used two batches of gene expression data from the AddNeuroMed (ANM) and Dementia Case Registry (DCR) cohorts. METHODS: Our study used Illumina Human HT-12 Expression BeadChips to collect gene expression from blood samples. Random forest modeling with recursive feature elimination was used to predict case/control status. Age and APOE ɛ4 status were used as covariates for all analysis. RESULTS: Gene and pathway level models performed similarly to each other and to a model based on demographic information only. CONCLUSIONS: Any potential increase in concordance from the novel pathway level approach used here has not lead to a greater predictive ability in these datasets. However, we have only tested one method for creating pathway level scores. Further, we have been able to benchmark pathways against genes in datasets that had been extensively harmonized. Further work should focus on the use of alternative methods for creating pathway level scores, in particular those that incorporate pathway topology, and the use of an endophenotype based approach.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoproteins E; Cohort Studies; Datasets as Topic; Female; Gene Expression; Gene Expression Profiling; Humans; Male; Models, Genetic; Oligonucleotide Array Sequence Analysis; Signal Transduction

Patterns of Brain Iron Accumulation in Vascular Dementia and Alzheimer's Dementia Using Quantitative Susceptibility Mapping Imaging. - Moon, Yeonsil; Han, Seol-Heui; Moon, Won-Jin (J Alzheimers Dis, 2016)
BACKGROUND: Emerging evidence suggests that the excessive accumulation of iron in subcortical and deep gray matter has been related to dementia. However, the presence and pattern of iron accumulation in vascular dementia (VaD) and Alzheimer's disease (AD) are rarely investigated. OBJECTIVE: To examine and compare the pattern and presence of brain iron accumulation of VaD and AD using quantitative susceptibility mapping (QSM). MATERIALS AND METHODS: Twelve patients with VaD, 27 patients with AD, and 18 control subjects were recruited in this institutional review-board approved study. Susceptibility maps were reconstructed from a three-dimensional multiecho spoiled gradient-echo sequence. Four regions of interest were drawn manually on QSM images, namely the globus pallidus, putamen, caudate nucleus, and pulvinar nucleus of the thalamus. Comparisons of patient demographics, and iron concentrations among the VaD, AD, and control subjects were assessed using analysis of variance and post-hoc analyses. The relationships of age and cognitive state with susceptibility values were assessed using partial correlation analysis. RESULTS: In VaD and AD, overall susceptibility values were higher than those of control subjects. A significant difference in susceptibility values was found in the putamen and caudate nucleus (p <  0.001 and p = 0.002, respectively). However, susceptibility values did not differ between VaD and AD. Age and cognitive deficit severity were not related to susceptibility values in the VaD and AD groups. CONCLUSION: Increased iron deposition in the putamen and caudate nucleus in VaD and AD patients was not associated with age or the severity of cognitive deficits. Further evaluations are needed to determine the temporal changes in iron load and their diagnostic role in dementia pathology.
Keywords: Aged; Aging; Alzheimer Disease; Brain; Brain Mapping; Cognition; Dementia, Vascular; Female; Humans; Imaging, Three-Dimensional; Iron; Magnetic Resonance Imaging; Male; Mental Status Schedule; Retrospective Studies; Severity of Illness Index

PDE5 Exists in Human Neurons and is a Viable Therapeutic Target for Neurologic Disease. - Teich, Andrew F; Sakurai, Mikako; Patel, Mitesh; Holman, Cameron; Saeed, Faisal; Fiorito, Jole; Arancio, Ottavio (J Alzheimers Dis, 2016)
Phosphodiesterase 5 (PDE5) is a critical component of the cGMP-PKG axis of cellular signaling in neurons, and inhibition of PDE5 has been shown to be therapeutic in a wide range of neurologic conditions in animal models. However, enthusiasm for PDE5 inhibitors in humans is limited by data suggesting that PDE5 may not exist in human neurons. Here, we first show that past attempts to quantify PDE5 mRNA were flawed due to the use of incorrect primers, and that when correct primers are used, PDE5 mRNA is detectable in human brain tissue. We then show that PDE5 protein exists in human brain by western blot and ELISA. Most importantly, we performed immunohistochemistry and demonstrate that PDE5 is present in human neurons. We hope that this work will trigger a renewed interest in the development of PDE5 inhibitors for neurologic disease.
Keywords: Blotting, Western; Brain; Cyclic Nucleotide Phosphodiesterases, Type 5; DNA Primers; Enzyme-Linked Immunosorbent Assay; Humans; Immunohistochemistry; Nervous System Diseases; Neurons; Phosphodiesterase 5 Inhibitors; Polymerase Chain Reaction; RNA, Messenger

Performance of Hippocampus Volumetry with FSL-FIRST for Prediction of Alzheimer's Disease Dementia in at Risk Subjects with Amnestic Mild Cognitive Impairment. - Suppa, Per; Hampel, Harald; Kepp, Timo; Lange, Catharina; Spies, Lothar; Fiebach, Jochen B; Dubois, Bruno; Buchert, Ralph (J Alzheimers Dis, 2016)
MRI-based hippocampus volume, a core feasible biomarker of Alzheimer's disease (AD), is not yet widely used in clinical patient care, partly due to lack of validation of software tools for hippocampal volumetry that are compatible with routine workflow. Here, we evaluate fully-automated and computationally efficient hippocampal volumetry with FSL-FIRST for prediction of AD dementia (ADD) in subjects with amnestic mild cognitive impairment (aMCI) from phase 1 of the Alzheimer's Disease Neuroimaging Initiative. Receiver operating characteristic analysis of FSL-FIRST hippocampal volume (corrected for head size and age) revealed an area under the curve of 0.79, 0.70, and 0.70 for prediction of aMCI-to-ADD conversion within 12, 24, or 36 months, respectively. Thus, FSL-FIRST provides about the same power for prediction of progression to ADD in aMCI as other volumetry methods.
Keywords: Aged; Aging; Alzheimer Disease; Area Under Curve; Cognitive Dysfunction; Databases, Factual; Disease Progression; Hippocampus; Humans; Image Interpretation, Computer-Assisted; Magnetic Resonance Imaging; Neuropsychological Tests; Organ Size; Pattern Recognition, Automated; Prognosis; Reproducibility of Results; Risk; ROC Curve; Sensitivity and Specificity; Time Factors

Performance on Specific Cognitive Domains and Cause of Death: A Prospective Population-Based Study in Non-Demented Older Adults (NEDICES). - Benito-León, Julián; Contador, Israel; Mitchell, Alex J; Domingo-Santos, Ángela; Bermejo-Pareja, Félix (J Alzheimers Dis, 2016)
Evidence regarding the relationship between performance on specific cognitive domains and cause of death is scarce. We assessed whether specific cognitive domains predicted mortality and the presence of any association with specific causes of death in a population-dwelling sample of non-demented older adults. In this population-based, prospective study (NEDICES), 2,390 non-demented subjects ≥65 years completed a brief neuropsychological battery. Cox's proportional hazards models, adjusted by sociodemographic and comorbidity factors, global cognitive performance, educational level, and premorbid intelligence were used to assess the risk of death. Participants were followed for a median of 9.2 years (range 0.01-10.7), after which the death certificates of those who died were examined. 880 (36.8%) of 2,390 participants died over a median follow-up of 5.5 years (range 0.01-10.5). Using adjusted Cox regression models, we found that hazard ratios for mortality in participants within the lowest tertiles (worse performance) were 1.31 (speed of cognitive processing, p = 0.03); 1.22 (semantic fluency, p = 0.04), 1.32 (delayed free recall, p = 0.003), and 1.23 (delayed logical memory, p = 0.03). Poor performance on delayed recall and speed of cognitive processing tests were associated with dementia and cerebrovascular disease mortality, respectively. Further, poor performance on semantic fluency was associated with decreased cancer mortality. In this study of community dwelling non-demented older adults, worse neuropsychological performance was associated with increased risk of mortality. Performance on specific cognitive domains were related to different causes of death. Of particular note there appears to be an inverse association between poor semantic fluency and cancer mortality.
Keywords: Aged; Cause of Death; Cerebrovascular Disorders; Cognitive Aging; Dementia; Educational Status; Female; Follow-Up Studies; Humans; Intelligence; Longitudinal Studies; Male; Neuropsychological Tests; Prospective Studies; Risk; Spain

Platelet Membrane β-Secretase Activity in Mild Cognitive Impairment and Conversion to Dementia: a Longitudinal Study. - McGuinness, Bernadette; Fuchs, Marc; Barrett, Suzanne L; Passmore, A Peter; Johnston, Janet A (J Alzheimers Dis, 2016)
A blood-based biomarker to complement the clinical and neuropsychological assessments used to evaluate the risk of individuals with mild cognitive impairment (MCI) developing Alzheimer's disease (AD) would be invaluable. Previous pilot studies by our group identified elevated platelet membrane β-secretase activity in patients with AD and MCI, as compared to controls, and this activity was influenced by membrane cholesterol levels. The present study investigated baseline platelet membrane β-secretase activity and cholesterol levels in 97 MCI participants and 85 controls and explored whether these parameters differed in individuals with stable MCI, as compared to those who subsequently developed AD. To evaluate signal specificity, β-secretase activity assays were conducted in the presence and absence of beta-site amyloid-β protein precursor-cleaving enzyme (BACE) inhibitors. Baseline platelet membrane β-secretase activity did not differ significantly in MCI participants, as compared to controls, and platelet membrane cholesterol levels were significantly lower in the MCI group. The longitudinal study indicated that the activities inhibited by two different BACE inhibitors did not predict conversion to AD; however, the activity that was not affected by BACE inhibitors was significantly (40%) higher in individuals with stable MCI, as compared with those who subsequently developed AD. These findings indicated that further research into the source of this activity could contribute to a measure facilitating prediction of the risk of conversion from MCI to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid Precursor Protein Secretases; Biomarkers; Blood Platelets; Cholesterol; Cognitive Dysfunction; Cross-Sectional Studies; Disease Progression; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Middle Aged; Neuropsychological Tests; Sensitivity and Specificity

Post Hoc Analyses of ApoE Genotype-Defined Subgroups in Clinical Trials. - Kennedy, Richard E; Cutter, Gary R; Wang, Guoqiao; Schneider, Lon S (J Alzheimers Dis, 2016)
BACKGROUND: Many post hoc analyses of clinical trials in Alzheimer's disease (AD) and mild cognitive impairment (MCI) are in small Phase 2 trials. Subject heterogeneity may lead to statistically significant post hoc results that cannot be replicated in larger follow-up studies. OBJECTIVE: We investigated the extent of this problem using simulation studies mimicking current trial methods with post hoc analyses based on ApoE4 carrier status. METHODS: We used a meta-database of 24 studies, including 3,574 subjects with mild AD and 1,171 subjects with MCI/prodromal AD, to simulate clinical trial scenarios. Post hoc analyses examined if rates of progression on the Alzheimer's Disease Assessment Scale-cognitive (ADAS-cog) differed between ApoE4 carriers and non-carriers. RESULTS: Across studies, ApoE4 carriers were younger and had lower baseline scores, greater rates of progression, and greater variability on the ADAS-cog. Up to 18% of post hoc analyses for 18-month trials in AD showed greater rates of progression for ApoE4 non-carriers that were statistically significant but unlikely to be confirmed in follow-up studies. The frequency of erroneous conclusions dropped below 3% with trials of 100 subjects per arm. In MCI, rates of statistically significant differences with greater progression in ApoE4 non-carriers remained below 3% unless sample sizes were below 25 subjects per arm. CONCLUSIONS: Statistically significant differences for ApoE4 in post hoc analyses often reflect heterogeneity among small samples rather than true differential effect among ApoE4 subtypes. Such analyses must be viewed cautiously. ApoE genotype should be incorporated into the design stage to minimize erroneous conclusions.
Keywords: Alzheimer Disease; Apolipoprotein E4; Clinical Trials as Topic; Cognitive Dysfunction; Data Interpretation, Statistical; Humans; Research Design

Prediction of Progressive Mild Cognitive Impairment by Multi-Modal Neuroimaging Biomarkers. - Xu, Lele; Wu, Xia; Li, Rui; Chen, Kewei; Long, Zhiying; Zhang, Jiacai; Guo, Xiaojuan; Yao, Li (J Alzheimers Dis, 2016)
For patients with mild cognitive impairment (MCI), the likelihood of progression to probable Alzheimer's disease (AD) is important not only for individual patient care, but also for the identification of participants in clinical trial, so as to provide early interventions. Biomarkers based on various neuroimaging modalities could offer complementary information regarding different aspects of disease progression. The current study adopted a weighted multi-modality sparse representation-based classification method to combine data from the Alzheimer's Disease Neuroimaging Initiative (ADNI) database, from three imaging modalities: Volumetric magnetic resonance imaging (MRI), fluorodeoxyglucose (FDG) positron emission tomography (PET), and florbetapir PET. We included 117 normal controls (NC) and 110 MCI patients, 27 of whom progressed to AD within 36 months (pMCI), while the remaining 83 remained stable (sMCI) over the same time period. Modality-specific biomarkers were identified to distinguish MCI from NC and to predict pMCI among MCI. These included the hippocampus, amygdala, middle temporal and inferior temporal regions for MRI, the posterior cingulum, precentral, and postcentral regions for FDG-PET, and the hippocampus, amygdala, and putamen for florbetapir PET. Results indicated that FDG-PET may be a more effective modality in discriminating MCI from NC and in predicting pMCI than florbetapir PET and MRI. Combining modality-specific sensitive biomarkers from the three modalities boosted the discrimination accuracy of MCI from NC (76.7%) and the prediction accuracy of pMCI (82.5%) when compared with the best single-modality results (73.6% for MCI and 75.6% for pMCI with FDG-PET).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Aniline Compounds; Biomarkers; Brain; Cognitive Dysfunction; Disease Progression; Ethylene Glycols; Female; Fluorodeoxyglucose F18; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Positron-Emission Tomography; Predictive Value of Tests; Psychiatric Status Rating Scales; Sensitivity and Specificity

Predictive factors for disease progression in patients with early-onset Alzheimer's disease. - Yoon, Bora; Shim, Yong S; Park, Hee-Kyung; Park, Sun Ah; Choi, Seong Hye; Yang, Dong Won (J Alzheimers Dis, 2016)
BACKGROUND: Only a few studies have investigated disease progression in patients with early-onset Alzheimer's disease (EOAD). Therefore, the aim of this study was to investigate disease progression in patients with EOAD and the influence of various factors, such as gender, education, and apolipoprotein E (APOE) genotype on disease progression. METHODS: A total of 288 EOAD patients were enrolled in the study. Linear mixed models were used to investigate the rate of cognitive and functional decline in terms of age at onset, gender, education, follow-up period, and APOE genotype. RESULTS: EOAD patients showed an annual decline of -1.54 points/years in the Korean version mini-mental examination score, an annual increase of 3.46 points/year in the Seoul instrumental activities of daily living (SIADL) score, and an annual increase of 1.15 points/year in the clinical dementia rating scale-sum of boxes score. After stratification, higher educated patients showed faster disease progression in all three parameters, and female patients demonstrated faster disease progression as assessed by the SIADL score. Age at onset and APOE genotype had no influence on disease progression. CONCLUSION: We confirmed the rate of disease progression in Korean patients with EOAD in real-life hospital-based clinical practice. The results of this study suggest that education and female gender, not APOE genotype, may be important as independent strong predictive factors for disease progression in patients with EOAD.
Keywords: Activities of Daily Living; Adult; Age Factors; Aged; Alleles; Alzheimer Disease; Apolipoproteins E; Disease Progression; Female; Genotype; Humans; Linear Models; Longitudinal Studies; Male; Middle Aged; Neuropsychological Tests; Risk Factors; Sex Factors

Predictive Value of Cerebrospinal Fluid Visinin-Like Protein-1 Levels for Alzheimer's Disease Early Detection and Differential Diagnosis in Patients with Mild Cognitive Impairment. - Babić Leko, Mirjana; Borovečki, Fran; Dejanović, Nenad; Hof, Patrick R; Šimić, Goran (J Alzheimers Dis, 2016)
Visinin-like protein 1 (VILIP-1) recently emerged as a potential biomarker of Alzheimer's disease (AD). This neuronal calcium sensor protein previously used as a marker of acute ischemic stroke is elevated in the cerebrospinal fluid (CSF) of AD patients. The goal of this study was to assess CSF VILIP-1 potential in early AD diagnosis and in differentiating mild cognitive impairment (MCI) patients with and without risk of AD. Additionally, we tested VILIP-1 ability to differentiate AD from other primary causes of dementia, and predict the progression of AD-related cognitive decline. VILIP-1 levels were compared with five CSF AD biomarkers (t-tau, Aβ1-42, p-tau181, p-tau199, and p-tau231). VILIP-1 successfully differentiated two MCI patient groups characterized by absence or presence of pathological levels of these CSF biomarkers, except for t-tau. VILIP-1/Aβ(1-42) and VILIP-1/p-tau181 ratios also differentiated MCI patients with pathological CSF biomarker levels. However, there was no difference in VILIP-1 levels between AD and MCI patients. VILIP-1/Aβ(1-42) and VILIP-1/p-tau231 ratios reached high sensitivities (above 70%) and very high specificities (above 85%) in differentiating AD patients from HC. Additionally, VILIP-1 differentiated AD from patients with Lewy body disease with 77.1% sensitivity and 100% specificity. VILIP-1 potential as a prognostic biomarker of cognitive decline in AD was also proved since VILIP-1/t-tau, VILIP-1/p-tau181, and VILIP-1/p-tau231 ratios correlated with MMSE scores. These data indicate that VILIP-1 alone or in combination with other AD CSF biomarkers represent a valuable marker for the early diagnosis of AD, recognition of MCI patients at higher risk to develop dementia, and in differentiating AD from LBD.
Keywords: Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Diagnosis, Differential; Disease Progression; Female; Humans; Male; Mental Status Schedule; Middle Aged; Neurocalcin; Peptide Fragments; Predictive Value of Tests; ROC Curve; Statistics as Topic; tau Proteins

Prognostic Significance of Mild Cognitive Impairment Subtypes for Dementia and Mortality: Data from the NEDICES Cohort. - Bermejo-Pareja, Félix; Contador, Israel; Trincado, Rocío; Lora, David; Sánchez-Ferro, Álvaro; Mitchell, Alex J; Boycheva, Elina; Herrero, Alejandro; Hernández-Gallego, Jesús; Llamas, Sara; Villarejo Galende, Alberto; Benito-León, Julián (J Alzheimers Dis, 2016)
BACKGROUND: The predictive value of diverse subtypes of mild cognitive impairment (MCI) for dementia and death is highly variable. OBJECTIVE: To compare the predictive value of several MCI subtypes in progression to dementia and/or mortality in the NEDICES (Neurological Disorders in Central Spain) elderly cohort. METHODS: Retrospect algorithmic MCI subgroups were established in a non-dementia baseline NEDICES cohort using Spanish adaptations of the original Mini-Mental State Examination (MMSE-37) and Pfeffer's Functional Activities Questionnaire (Pfeffer-11). The presence of MCI was defined according two cognitive criteria: using two cut-offs points on the total MMSE-37 score. Five cognitive domains were used to establish the MCI subtypes. Functional capacity (Pfeffer-11) was preserved or minimally impaired in all MCI participants. The incident dementia diagnoses were established by specialists and the mortality data obtained from Spanish official registries. RESULTS: 3,411 participants without dementia were assessed in 1994-5. The baseline prevalence of MCI varied according to the MCI definition (4.3%-31.8%). The follow-up was a mean of 3.2 years (1997-8). The dementia incidence varied between 14.9 and 71.8 per 1,000/person-years. The dementia conversion rate was increased in almost all MCI subgroups (p >  0.01), and mortality rate was raised only in four MCI subtypes. The amnestic-multi-domain MCI (aMd-MCI) had the best dementia predictive accuracy (highest positive likelihood ratio and highest clinical utility when negative). CONCLUSIONS: Those with aMd-MCI were at greatest risk of progression to dementia, as in other surveys and might be explored with increased attention in MCI research and in dementia preventive trials.
Keywords: Aged; Aged, 80 and over; Algorithms; Cognitive Dysfunction; Cohort Studies; Dementia; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Spain

Progranulin Protein Levels in Cerebrospinal Fluid in Primary Neurodegenerative Dementias. - Morenas-Rodriguez, Estrella; Cervera-Carles, Laura; Vilaplana, Eduard; Alcolea, Daniel; Carmona-Iragui, María; Dols-Icardo, Oriol; Ribosa-Nogué, Roser; Muñoz-Llahuna, Laia; Sala, Isabel; Belén Sánchez-Saudinós, M; Blesa, Rafael; Clarimón, Jordi; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Progranulin is implicated in frontotemporal dementia (FTD), but its role in other neurodegenerative disorders is unknown. OBJECTIVE: To investigate the levels of progranulin (PGRN) in cerebrospinal fluid (CSF) in different neurodegenerative dementias and their correlation with levels in plasma in cognitively normal subjects. METHODS: We measured PGRN in CSF in 229 patients with amnestic mild cognitive impairment, Alzheimer's disease dementia, sporadic FTD, dementia with Lewy bodies, corticobasal syndrome, or progressive supranuclear palsy. We also measured PGRN in CSF and plasma in 74 cognitively normal individuals. We examined the correlation between PGRN levels in CSF and diagnosis, cortical thickness, genetic factors and other CSF biomarkers. We also investigated the correlation between plasma and CSF levels of PGRN in cognitively normal individuals. RESULTS: CSF levels did not differ across diagnoses or correlate with cortical thickness. Polymorphism rs5848 in GRN influenced CSF PGRN levels, but APOEɛ4 allele did not. Amyloid-β42, t-tau, p-tau, and YKL-40 levels correlated weakly with PGRN in CSF. We found a weak correlation (r = 0.362) between plasma and CSF PGRN levels in cognitively normal individuals. CONCLUSIONS: Our findings do not support a diagnostic value of CSF PGRN in neurodegenerative diseases. Our data confirm that levels of PGRN in plasma do not reflect accurately levels in CSF in cognitively normal controls. These data should be considered in clinical trials aiming to increase PGRN.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Biomarkers; Dementia; Female; Humans; Intercellular Signaling Peptides and Proteins; Male; Middle Aged; Neurodegenerative Diseases; Polymorphism, Single Nucleotide; tau Proteins

Progression of Extrapyramidal Signs in Alzheimer's Disease: Clinical and Neuropathological Correlates. - Tosto, Giuseppe; Monsell, Sarah E; Hawes, Stephen E; Bruno, Giuseppe; Mayeux, Richard (J Alzheimers Dis, 2016)
BACKGROUND: Extrapyramidal signs (EPS) are frequent in Alzheimer's disease (AD) and core manifestation of related diseases, i.e., dementia with Lewy bodies and Parkinson's disease; furthermore, Lewy bodies and AD-type pathology occur in all three conditions. OBJECTIVE: To identify clusters of EPS progression over time and their clinical and neuropathological correlates. METHODS: 3,502 AD patients with longitudinal assessment from the National Alzheimer's Coordinating Center database were included; 394 provided neuropathological data. k-means algorithm was employed to identify clusters of EPS progression and those were compared in terms of cognitive profile, neuropsychiatric features and neuropathological findings. RESULTS: Three clusters of EPS progression were identified: no/low (n = 1,583), medium (n = 1,259), and high (n = 660) EPS burden. Compared to those with no/low and medium EPS, those with high EPS had greater cognitive and neuropsychiatric impairment, specifically hallucinations. Despite similar AD-pathology across the three clusters, the high EPS cluster had a significantly number of subjects diagnosed with dementia with Lewy bodies. CONCLUSIONS: Cluster analysis of EPS progression over time identified different subgroups of AD patients with distinct clinical and neuropathological features.
Keywords: Aged; Algorithms; Alzheimer Disease; Cluster Analysis; Databases, Factual; Disease Progression; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Severity of Illness Index

Psychotropic Drug Prescription in Patients with Dementia: Nursing Home Residents Versus Patients Living at Home. - Jacquin-Piques, Agnès; Sacco, Guillaume; Tavassoli, Neda; Rouaud, Olivier; Bejot, Yannick; Giroud, Maurice; Robert, Philippe; Vellas, Bruno; Bonin-Guillaume, Sylvie (J Alzheimers Dis, 2016)
BACKGROUND: Psychotropic drugs are frequently prescribed in nursing homes (NH). Nonetheless, we hoped that institutionalization decreases the number of psychotropic drug classes prescribed, because NH residents may have more psychosocial interventions than patients living at home. OBJECTIVE: The aim was to compare the type and number of psychotropic drugs prescribed in elderly NH residents with dementia with those in community-living patients. METHODS: This cross-sectional study included elderly patients (at least 75 years old) with dementia recorded in the National Alzheimer's data Bank ("Banque Nationale Alzheimer") during the year 2012 and who were taking at least one psychotropic drug. Psychotropic drugs were classified as follows: antidepressant, anxiolytic, hypnotic, and antipsychotic drugs. Patients were classified into three categories of dementia severity according to the MMSE score. RESULTS: Among the 50,932 patients with dementia recorded in the BNA, 40.1% had at least one psychotropic drug prescribed. Most of the patients who were treated by at least one psychotropic drug class had antidepressant therapy (69.0%), whatever their residence type, and 16.1% were treated with antipsychotics. Among the study population, 51.9% of the NH residents and 67.4% of the patients living at home had only one psychotropic drug class prescribed. Living in a NH was significantly associated with the more frequent prescription of anxiolytic, hypnotic, and antipsychotic drugs, and with a greater number of psychotropic drug classes prescribed, whatever the severity of the dementia. CONCLUSION: We underlined the more frequent prescription of psychotropic drugs in NH residents regardless of MMSE scores.
Keywords: Aged; Aged, 80 and over; Chi-Square Distribution; Cross-Sectional Studies; Databases, Factual; Dementia; Drug Prescriptions; Female; Humans; Male; Nursing Homes; Psychotropic Drugs; Residence Characteristics

Puerarin Ameliorates D-Galactose Induced Enhanced Hippocampal Neurogenesis and Tau Hyperphosphorylation in Rat Brain. - Hong, Xiao-Ping; Chen, Tao; Yin, Ni-Na; Han, Yong-Ming; Yuan, Fang; Duan, Yan-Jun; Shen, Feng; Zhang, Yan-Hong; Chen, Ze-Bin (J Alzheimers Dis, 2016)
Enhanced neurogenesis has been reported in the hippocampus of patients with Alzheimer's disease (AD), the most common neurodegenerative disorder characterized with amyloid-β (Aβ) aggregation, tau hyperphosphorylation, and progressive neuronal loss. Previously we reported that tau phosphorylation played an essential role in adult hippocampal neurogenesis, and activation of glycogen synthase kinase (GSK-3), a crucial tau kinase, could induce increased hippocampal neurogenesis. In the present study, we found that treatment of D-galactose rats with Puerarin could significantly improve behavioral performance and ameliorate the enhanced neurogenesis and microtubule-associated protein tau hyperphosphorylation in the hippocampus of D-galactose rat brains. FGF-2/GSK-3 signaling pathway might be involved in the effects of Puerarin on hippocampal neurogenesis and tau hyperphosphorylation. Our finding provides primary in vivo evidence that Puerarin can attenuate AD-like enhanced hippocampal neurogenesis and tau hyperphosphorylation. Our finding also suggests Puerarin can be served as a treatment for age-related neurodegenerative disorders, such as AD.
Keywords: Animals; Cognition Disorders; Disease Models, Animal; Fibroblast Growth Factor 2; Galactose; Glycogen Synthase Kinase 3; Hippocampus; Isoflavones; Male; Maze Learning; Neurogenesis; Neurons; Neuroprotective Agents; Phosphorylation; Random Allocation; Rats, Sprague-Dawley; Signal Transduction; Spatial Memory; tau Proteins

Quantitative phosphoproteomic analyses of the inferior parietal lobule from three different pathological stages of Alzheimer's disease. - Triplett, Judy C; Swomley, Aaron M; Cai, Jian; Klein, Jon B; Butterfield, D Allan (J Alzheimers Dis, 2016)
Alzheimer's disease (AD), the most common age-related neurodegenerative disorder, is clinically characterized by progressive neuronal loss resulting in loss of memory and dementia. AD is histopathologically characterized by the extensive distribution of senile plaques and neurofibrillary tangles, and synapse loss. Amnestic mild cognitive impairment (MCI) is generally accepted to be an early stage of AD. MCI subjects have pathology and symptoms that fall on the scale intermediately between 'normal' cognition with little or no pathology and AD. A rare number of individuals, who exhibit normal cognition on psychometric tests but whose brains show widespread postmortem AD pathology, are classified as 'asymptomatic' or 'preclinical' AD (PCAD). In this study, we evaluated changes in protein phosphorylation states in the inferior parietal lobule of subjects with AD, MCI, PCAD, and control brain using a 2-D PAGE proteomics approach in conjunction with Pro-Q Diamond phosphoprotein staining. Statistically significant changes in phosphorylation levels were found in 19 proteins involved in energy metabolism, neuronal plasticity, signal transduction, and oxidative stress response. Changes in the disease state phosphoproteome may provide insights into underlying mechanisms for the preservation of memory with expansive AD pathology in PCAD and the progressive memory loss in amnestic MCI that escalates to the dementia and the characteristic pathology of AD brain.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Disease Progression; Female; Humans; Male; Memory; Neurofibrillary Tangles; Oxidative Stress; Parietal Lobe; Phosphorylation; Plaque, Amyloid; Proteome

Region-Specific Vulnerability to Oxidative Stress, Neuroinflammation, and Tau Hyperphosphorylation in Experimental Diabetes Mellitus Mice. - Elahi, Montasir; Hasan, Zafrul; Motoi, Yumiko; Matsumoto, Shin-Ei; Ishiguro, Koichi; Hattori, Nobutaka (J Alzheimers Dis, 2016)
Recent epidemiological evidence suggests that diabetes mellitus (DM) is a risk factor for Alzheimer's disease (AD). One of the pathological hallmarks of AD is hyperphosphorylated tau protein, which forms neurofibrillary tangles. Oxidative stress and the activation of inflammatory pathways are features that are associated with both DM and AD. However, the brain region specificity of AD-related neurodegeneration, which mainly occurs in the hippocampus while the cerebellum is relatively unaffected, has not yet been clarified. Therefore, we used experimental DM mice (caused by an intraperitoneal injection of streptozotocin [STZ]) to determine whether these neurodegeneration-associated mechanisms were associated with region-specific selective vulnerability or tau phosphorylation. The hippocampus, midbrain, and cerebellum of aged (14 to 18 months old) non-transgenic (NTg) and transgenic mice overexpressing wild-type human tau (Tg601 mice) were evaluated after a treatment with STZ. The STZ injection increased reactive oxygen species, lipid peroxidation markers such as 4-hydroxynonenal and malondialdehyde in the hippocampus, but not in the midbrain or cerebellum. The STZ treatment also increased the number of Iba-1-positive and CD68-positive microglial cells, astrocytes, and IL-1β, IL-6, IL-10, and IL-18 levels in the hippocampus, but not in the midbrain or cerebellum. Tau hyperphosphorylation was also enhanced in the hippocampus, but not in the midbrain or cerebellum. When the effects of STZ were compared between Tg601 and NTg mice, microglial proliferation and elevations in IL-6 and phosphorylated tau were higher in Tg601 mice. These results suggest that neuroinflammation and oxidative stress in STZ-treated mice are associated with tau hyperphosphorylation, which may contribute to selective neurodegeneration in human AD.
Keywords: Adaptor Proteins, Signal Transducing; Animals; Antibiotics, Antineoplastic; Brain; Calcium-Binding Proteins; Calcium-Calmodulin-Dependent Protein Kinase Type 2; Cell Proliferation; Diabetes Mellitus, Experimental; Disease Models, Animal; Encephalitis; Female; Humans; Lipid Peroxidation; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microfilament Proteins; Neuroglia; Oxidative Stress; Reactive Oxygen Species; Streptozocin; tau Proteins

Resting-State Cardiac Workload is Related to Both Increased Neocortical Aggregation of Amyloid-β and Relative Impairments in Spatial Working Memory in Pre-Clinical Alzheimer's Disease. - Santos, Cláudia Yang; Lim, Yen Ying; Wu, Wen-Chih; Machan, Jason Timothy; Polynice, Shahena; Schindler, Rachel; Maruff, Paul; Snyder, Peter Jeffrey (J Alzheimers Dis, 2016)
We sought to determine whether there is any association between a cardiac workload marker, rate pressure product (RPP), working memory, and cortical amyloid-β (Aβ) burden in 63 cognitively normal midlife adults (Mage = 62.8 years; range = 55 to 75 years) at risk for Alzheimer's disease (AD). The results show a small-to-moderate relationship between increasing cardiac workload (at rest) and neocortical amyloidosis in individuals at the preclinical stage of AD. Moreover, increasing RPP was linearly related to increasing relative impairments on a spatial working memory task (R2 = 0.30), but only for those individuals with neuroimaging evidence suggestive of preclinical AD. These results support a relationship between the aggregation of Aβ protein plaques in the neocortex, increased cognitive impairment, and more inefficient myocardial oxygen use in the absence of significant metabolic demands.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Blood Pressure; Disease Progression; Female; Heart Rate; Humans; Male; Maze Learning; Memory Disorders; Middle Aged; Neocortex; Neuropsychological Tests; Positron-Emission Tomography; Protein Aggregation, Pathological; Workload

Reversal of LTP-Like Cortical Plasticity in Alzheimer's Disease Patients with Tau-Related Faster Clinical Progression. - Koch, Giacomo; Di Lorenzo, Francesco; Del Olmo, Miguel Fernandez; Bonní, Sonia; Ponzo, Viviana; Caltagirone, Carlo; Bozzali, Marco; Martorana, Alessandro (J Alzheimers Dis, 2016)
Cerebrospinal fluid (CSF) concentrations of amyloid-β (Aβ), total tau (t-tau), and phosphorylated tau proteins are associated with different clinical progression in Alzheimer's disease (AD). We enrolled forty newly diagnosed AD patients, who underwent lumbar puncture, and carried out a K-means cluster analysis based on CSF biomarkers levels, resulting in two AD patient groups: Cluster 1 showed relatively high levels of Aβ and low levels of tau; Cluster 2 showed relatively low levels of Aβ and high levels of tau. Cortical plasticity was tested using the intermittent and continuous theta burst stimulation (iTBS and cTBS) protocols evoking respectively long-term potentiation (LTP) and depression (LTD). Cholinergic transmission was tested by the short-latency afferent inhibition protocol. Neurophysiological evaluation showed that the two AD groups differed in terms of cortical plasticity: after iTBS, Cluster 2 patients showed a remarkable reversal of LTP toward LTD that was not observed in Cluster 1. LTD and central cholinergic transmission did not differ between groups. Patients were assessed longitudinally with Mini-Mental State Examination at 6, 12, and 18 month follow-ups. Cluster 2 AD had a faster cognitive decline already evident at the 12 month follow-up. High tau CSF levels were associated with LTD-like cortical plasticity and faster clinical progression. These results suggest that more aggressive tau pathology is associated with prominent LTD-like mechanisms of cortical plasticity and faster cognitive decline.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Cognition; Disease Progression; Evoked Potentials, Motor; Female; Humans; Male; Motor Cortex; Neuronal Plasticity; Neuropsychological Tests; Phosphorylation; tau Proteins; Transcranial Magnetic Stimulation

Risk of dementia in patients with celiac disease: a population-based cohort study. - Lebwohl, Benjamin; Luchsinger, Jose A; Freedberg, Daniel E; Green, Peter H R; Ludvigsson, Jonas F (J Alzheimers Dis, 2016)
BACKGROUND: Patients with celiac disease (CD) frequently report cognitive symptoms when they are exposed to gluten, and cognitive deficits have been quantified in patients with newly diagnosed CD. OBJECTIVE: To determine whether patients with CD have an increased risk of dementia. METHODS: Using a population-based database of older adults (age ≥50 years) with histologically proven CD (duodenal/jejunal villous atrophy) from all 28 pathology departments in Sweden, we compared the incidence of a subsequent dementia diagnosis to those of age- and gender-matched controls. RESULTS: Among patients with CD (n = 8,846) and controls (n = 43,474), the median age was 63 years and 56% were female. During a median follow-up time of 8.4 years, dementia was diagnosed in 4.3% of CD patients and 4.4% of controls (HR 1.07; 95% CI 0.95-1.20). Although there was an increased risk of dementia in the first year following a diagnosis of CD (HR 1.73; 95% CI 1.15-2.61), this risk was not present in the whole observation period. Among those subjects with a dementia subtype specified, the increased risk was restricted to vascular dementia (HR 1.28; 95% CI 1.00-1.64) and was not present for Alzheimer's dementia (HR 1.12; 95% CI 0.91-1.37). CONCLUSIONS: Patients with CD are not at increased risk for dementia overall, though subgroup analysis suggests that they may be at increased risk for vascular dementia.
Keywords: Aged; Celiac Disease; Cohort Studies; Databases, Factual; Dementia; Female; Humans; Incidence; Logistic Models; Male; Middle Aged; Proportional Hazards Models; Risk Factors; Sweden

The Role of Alzheimer's and Cerebrovascular Pathology in Mediating the Effects of Age, Race, and Apolipoprotein E Genotype on Dementia Severity in Pathologically-Confirmed Alzheimer's Disease. - Gavett, Brandon E; John, Samantha E; Gurnani, Ashita S; Bussell, Cara A; Saurman, Jessica L (J Alzheimers Dis, 2016)
BACKGROUND: Dementia severity can be modeled as the construct δ, representing the "cognitive correlates of functional status." OBJECTIVE: We recently validated a model for estimating δ in the National Alzheimer's Coordinating Center's Uniform Data Set; however, the association of δ with neuropathology remains untested. METHODS: We used data from 727 decedents evaluated at Alzheimer's Disease (AD) Centers nationwide. Participants spoke English, had no genetic abnormalities, and were pathologically diagnosed with AD as a primary or contributing etiology. Clinical data from participants' last visit prior to death were used to estimate dementia severity (δ). RESULTS: A structural equation model using age, education, race, and apolipoprotein E (APOE) genotype (number of ɛ2 and ɛ4 alleles) as predictors and latent AD pathology and cerebrovascular disease (CVD) pathology as mediators fit the data well (RMSEA = 0.031; CFI = 0.957). AD pathology mediated the effects of age and APOE genotype on dementia severity. An older age at death and more ɛ2 alleles were associated with less AD pathology and, in turn, with less severe dementia. In contrast, more ɛ4 alleles were associated with more pathology and more severe dementia. Although age and race contributed to differences in CVD pathology, CVD pathology was not related to dementia severity in this sample of decedents with pathologically-confirmed AD. CONCLUSIONS: Using δ as an estimate of dementia severity fits well within a structural model in which AD pathology directly affects dementia severity and mediates the relationship between age and APOE genotype on dementia severity.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Apolipoproteins E; Cerebrovascular Disorders; Continental Population Groups; Dementia; Educational Status; Female; Genotype; Humans; Male; Mental Status Schedule; Middle Aged; Models, Theoretical

The Role of Ethnicity in Alzheimer's Disease: Findings From The C-PATH Online Data Repository. - Chen, Huei-Yang; Panegyres, Peter K (J Alzheimers Dis, 2016)
BACKGROUND: Ethnic minorities seem to be at an increased risk of Alzheimer's disease (AD). However, little is known about ethnic differences and the risks of early onset AD (EOAD). OBJECTIVE: Cognitive function changes over time and odds of EOAD by ethnicity were analyzed by the mixed model and the logistic regression. METHODS: Information on demographics, self-reported co-morbidities, cognitive functions (MMSE and ADAS-COG), and ApoE genotypes were collected for 6,500 subjects with AD obtained from the placebo arm of clinical trials; this data was examined by ethnicities: Caucasian, Asian, African American, Hispanic, and other minorities--including Native Alaskans, Americans, and Hawaiians. RESULTS: Of the total subjects, Caucasians accounted for 89.0% , followed by 4.7% Asians, 2.7% African Americans, 2.4% Hispanics, and 1.2% Native Americans, Alaskans, and Hawaiians. Age, gender, EOAD status, co-morbidities, family history of AD, and ApoE genotypes were significantly different by ethnicity. ApoE ɛ2 allele is possibly overrepresented in the Native Americans, Africans, Hawaiians, and African Americans. A significant interaction with time, ethnicity, and cognitive performance was found, indicating more cognitive deterioration in other minorities than Caucasians for mini-mental state (p <  0.01). After adjusting for co-morbidities and gender, the odds of EOAD among African Americans (OR: 1.6, 95% CI: 1.1-2.4) and Native Alaskans, Americans, and Hispanics (OR: 2.1, 95% CI: 1.2-3.5) were significantly higher, compared with Caucasians. CONCLUSIONS: Ethnicity may impact AD through age of onset, co-morbidities, family history, ApoE gene status, and cognitive change over time. The greater odds of EOAD among African Americans, Alaskans, and Hawaiians suggest that some ethnicities may be at risk of AD at a younger age.
Keywords: African Americans; Age Factors; Aged; Alaska Natives; Alzheimer Disease; Apolipoproteins E; Asian Continental Ancestry Group; Clinical Trials as Topic; Comorbidity; Databases, Factual; European Continental Ancestry Group; Female; Hispanic Americans; Humans; Indians, North American; Internet; Logistic Models; Male; Oceanic Ancestry Group; Risk; Sex Factors

Safety and Efficacy of Medical Cannabis Oil for Behavioral and Psychological Symptoms of Dementia: An-Open Label, Add-On, Pilot Study. - Shelef, Assaf; Barak, Yoram; Berger, Uri; Paleacu, Diana; Tadger, Shelly; Plopsky, Igor; Baruch, Yehuda (J Alzheimers Dis, 2016)
BACKGROUND: Tetrahydrocannabinol (THC) is a potential treatment for Alzheimer's disease (AD). OBJECTIVE: To measure efficacy and safety of medical cannabis oil (MCO) containing THC as an add-on to pharmacotherapy, in relieving behavioral and psychological symptoms of dementia (BPSD). METHODS: Eleven AD patients were recruited to an open label, 4 weeks, prospective trial. RESULTS: Ten patients completed the trial. Significant reduction in CGI severity score (6.5 to 5.7; p <  0.01) and NPI score were recorded (44.4 to 12.8; p <  0.01). NPI domains of significant decrease were: Delusions, agitation/aggression, irritability, apathy, sleep and caregiver distress. CONCLUSION: Adding MCO to AD patients' pharmacotherapy is safe and a promising treatment option.
Keywords: Aged; Aged, 80 and over; Antipsychotic Agents; Behavioral Symptoms; Cognition Disorders; Dementia; Female; Humans; Male; Medical Marijuana; Neuropsychological Tests; Outcome Assessment (Health Care); Physical Examination; Pilot Projects; Prospective Studies; Psychiatric Status Rating Scales

Salidroside, a Bioactive Compound of Rhodiola Rosea, Ameliorates Memory and Emotional Behavior in Adult Mice. - Palmeri, Agostino; Mammana, Leonardo; Tropea, Maria Rosaria; Gulisano, Walter; Puzzo, Daniela (J Alzheimers Dis, 2016)
Rhodiola Rosea (R. Rosea) is a plant used in traditional popular medicine to enhance cognition and physical performance. R. Rosea medicinal properties have been related to its capability to act as an adaptogen, i.e., a substance able to increase the organism's resistance to a variety of chemical, biological, and physical stressors in a non-specific way. These adaptogen properties have been mainly attributed to the glycoside salidroside, one of the bioactive compounds present in the standardized extracts of R. Rosea. Here, we aimed to investigate whether a single dose of salidroside is able to affect memory and emotional behavior in wild type adult mice. We performed fear conditioning to assess cued and contextual memory, elevated plus maze and open field to evaluate anxiety, and tail suspension test to evaluate depression. Our results showed that a single i.p. administration of salidroside was able to enhance fear memory and exerted an anxiolytic and antidepressant effect. These data confirmed the adaptogenic effect of R. Rosea bioactive compounds in animal models and suggest that salidroside might represent an interesting pharmacological tool to ameliorate cognition and counteract mood disorders.
Keywords: Animals; Anti-Anxiety Agents; Antidepressive Agents; Anxiety Disorders; Conditioning (Psychology); Depressive Disorder; Disease Models, Animal; Drug Evaluation, Preclinical; Exploratory Behavior; Fear; Female; Freezing Reaction, Cataleptic; Glucosides; Male; Maze Learning; Memory; Mice, Inbred C57BL; Motor Activity; Nootropic Agents; Phenols; Phytotherapy; Plant Extracts; Rhodiola

Screening for Mild Cognitive Impairment: Comparison of "MCI Specific" Screening Instruments. - O'Caoimh, Rónán; Timmons, Suzanne; Molloy, D William (J Alzheimers Dis, 2016)
BACKGROUND: Sensitive and specific instruments are required to screen for cognitive impairment (CI) in busy clinical practice. The Montreal Cognitive Assessment (MoCA) is widely validated but few studies compare it to tests designed specifically to detect mild cognitive impairment (MCI). OBJECTIVE: Comparison of two "MCI specific" screens: the Quick Mild Cognitive Impairment screen (Qmci) and MoCA. METHODS: Patients with subjective memory complaints (SMC; n = 73), MCI (n = 103), or dementia (n = 274), were referred to a university hospital memory clinic and underwent comprehensive assessment. Caregivers, without cognitive symptoms, were recruited as normal controls (n = 101). RESULTS: The Qmci was more accurate than the MoCA in differentiating MCI from controls, area under the curve (AUC) of 0.90 versus 0.80, p = 0.009. The Qmci had greater (AUC 0.81), albeit non-significant, accuracy than the MoCA (AUC 0.73) in separating MCI from SMC, p = 0.09. At its recommended cut-off (<62/100), the Qmci had a sensitivity of 90% and specificity of 87% for CI (MCI/dementia). Raising the cut-off to <65 optimized sensitivity (94%), reducing specificity (80%). At <26/30 the MoCA had better sensitivity (96%) but poor specificity (58%). A MoCA cut-off of <24 provided the optimal balance. Median Qmci administration time was 4.5 (±1.3) minutes compared with 9.5 (±2.8) for the MoCA. CONCLUSIONS: Although both tests distinguish MCI from dementia, the Qmci is particularly accurate in separating MCI from normal cognition and has shorter administration times, suggesting it is more useful in busy hospital clinics. This study reaffirms the high sensitivity of the MoCA but suggests a lower cut-off (<24) in this setting.
Keywords: Aged; Aged, 80 and over; Area Under Curve; Cognitive Dysfunction; Dementia; Diagnosis, Differential; Female; Humans; Male; Neuropsychological Tests; Perception; ROC Curve; Sensitivity and Specificity; Time Factors

Self-Reported Traumatic Brain Injury and Mild Cognitive Impairment: Increased Risk and Earlier Age of Diagnosis. - LoBue, Christian; Denney, David; Hynan, Linda S; Rossetti, Heidi C; Lacritz, Laura H; Hart, John; Womack, Kyle B; Woon, Fu L; Cullum, C Munro (J Alzheimers Dis, 2016)
This study examined whether history of traumatic brain injury (TBI) is associated with increased risk and earlier onset of mild cognitive impairment (MCI). Subjects with MCI (n = 3,187) and normal cognition (n = 3,244) were obtained from the National Alzheimer's Coordinating Center database. TBI was categorized based on lifetime reported TBI with loss of consciousness (LOC) without chronic deficit. Logistic regression was used to examine TBI history as a predictor of MCI, adjusted for demographics, apolipoprotein E-ɛ4 (ApoE4), a composite vascular risk score, and history of psychiatric factors. ANCOVA was used to examine whether age at MCI diagnosis and estimated age of onset differed between those with (TBI+) and without (TBI-) a history of TBI. TBI history was a significant predictor (p <  0.01) and associated with increased odds of MCI diagnosis in unadjusted (OR = 1.25; 95% CI = 1.05-1.49) and adjusted models, accounting for age, education, ApoE4, and a composite vascular score (OR = 1.32; 95% CI = 1.10-1.58). This association, however, was largely attenuated (OR = 1.14; 95% CI = 0.94-1.37; p = 0.18) after adjustment for reported history of depression. MCI was diagnosed a mean of 2.3 years earlier (p <  0.001) in the TBI+ group, and although TBI+ subjects had an estimated mean of decline 1.7 years earlier, clinician-estimated age of onset failed to differ (p = 0.13) when gender and psychiatric factors were controlled. This is the first report of a possible role for TBI as a risk factor in MCI, but its association may be related to other factors such as gender and depression and requires further investigation.
Keywords: Age of Onset; Aged; Apolipoproteins E; Brain Injuries, Traumatic; Cognitive Dysfunction; Cohort Studies; Databases, Factual; Depression; Educational Status; Female; Humans; Logistic Models; Male; Risk Factors; Self Report; United States

Shared Genetic Etiology between Type 2 Diabetes and Alzheimer's Disease Identified by Bioinformatics Analysis. - Gao, Lei; Cui, Zhen; Shen, Liang; Ji, Hong-Fang (J Alzheimers Dis, 2016)
Type 2 diabetes (T2D) and Alzheimer's disease (AD) are two major health issues, and increasing evidence in recent years supports the close connection between these two diseases. The present study aimed to explore the shared genetic etiology underlying T2D and AD based on the available genome wide association studies (GWAS) data collected through August 2014. We performed bioinformatics analyses based on GWAS data of T2D and AD on single nucleotide polymorphisms (SNPs), gene, and pathway levels, respectively. Six SNPs (rs111789331, rs12721046, rs12721051, rs4420638, rs56131196, and rs66626994) were identified for the first time to be shared genetic factors between T2D and AD. Further functional enrichment analysis found lipid metabolism related pathways to be common between these two disorders. The findings may have important implications for future mechanistic and interventional studies for T2D and AD.
Keywords: Alzheimer Disease; Apolipoprotein C-I; Computational Biology; Databases, Factual; Diabetes Mellitus, Type 2; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Lipid Metabolism; Male; Polymorphism, Single Nucleotide

Shared Genetic Risk Factors for Late-Life Depression and Alzheimer's Disease. - Ye, Qing; Bai, Feng; Zhang, Zhijun (J Alzheimers Dis, 2016)
BACKGROUND: Considerable evidence has been reported for the comorbidity between late-life depression (LLD) and Alzheimer's disease (AD), both of which are very common in the general elderly population and represent a large burden on the health of the elderly. The pathophysiological mechanisms underlying the link between LLD and AD are poorly understood. Because both LLD and AD can be heritable and are influenced by multiple risk genes, shared genetic risk factors between LLD and AD may exist. OBJECTIVE: The objective is to review the existing evidence for genetic risk factors that are common to LLD and AD and to outline the biological substrates proposed to mediate this association. METHODS: A literature review was performed. RESULTS: Genetic polymorphisms of brain-derived neurotrophic factor, apolipoprotein E, interleukin 1-beta, and methylenetetrahydrofolate reductase have been demonstrated to confer increased risk to both LLD and AD by studies examining either LLD or AD patients. These results contribute to the understanding of pathophysiological mechanisms that are common to both of these disorders, including deficits in nerve growth factors, inflammatory changes, and dysregulation mechanisms involving lipoprotein and folate. Other conflicting results have also been reviewed, and few studies have investigated the effects of the described polymorphisms on both LLD and AD. CONCLUSION: The findings suggest that common genetic pathways may underlie LLD and AD comorbidity. Studies to evaluate the genetic relationship between LLD and AD may provide insights into the molecular mechanisms that trigger disease progression as the population ages.
Keywords: Age of Onset; Alzheimer Disease; Animals; Depressive Disorder; Genetic Predisposition to Disease; Humans; Polymorphism, Single Nucleotide; Risk Factors

Social Cognition Deficits: The Key to Discriminate Behavioral Variant Frontotemporal Dementia from Alzheimer's Disease Regardless of Amnesia? - Bertoux, Maxime; de Souza, Leonardo Cruz; O'Callaghan, Claire; Greve, Andrea; Sarazin, Marie; Dubois, Bruno; Hornberger, Michael (J Alzheimers Dis, 2016)
Relative sparing of episodic memory is a diagnostic criterion of behavioral variant frontotemporal dementia (bvFTD). However, increasing evidence suggests that bvFTD patients can show episodic memory deficits at a similar level as Alzheimer's disease (AD). Social cognition tasks have been proposed to distinguish bvFTD, but no study to date has explored the utility of such tasks for the diagnosis of amnestic bvFTD. Here, we contrasted social cognition performance of amnestic and non-amnestic bvFTD from AD, with a subgroup having confirmed in vivo pathology markers. Ninety-six participants (38 bvFTD and 28 AD patients as well as 30 controls) performed the short Social-cognition and Emotional Assessment (mini-SEA). BvFTD patients were divided into amnestic versus non-amnestic presentation using the validated Free and Cued Selective Reminding Test (FCSRT) assessing episodic memory. As expected, the accuracy of the FCSRT to distinguish the overall bvFTD group from AD was low (69.7% ) with ∼50% of bvFTD patients being amnestic. By contrast, the diagnostic accuracy of the mini-SEA was high (87.9% ). When bvFTD patients were split on the level of amnesia, mini-SEA diagnostic accuracy remained high (85.1% ) for amnestic bvFTD versus AD and increased to very high (93.9% ) for non-amnestic bvFTD versus AD. Social cognition deficits can distinguish bvFTD and AD regardless of amnesia to a high degree and provide a simple way to distinguish both diseases at presentation. These findings have clear implications for the diagnostic criteria of bvFTD. They suggest that the emphasis should be on social cognition deficits with episodic memory deficits not being a helpful diagnostic criterion in bvFTD.
Keywords: Aged; Alzheimer Disease; Amnesia; Cognition; Diagnosis, Differential; Emotions; Female; Frontotemporal Dementia; Humans; Male; Memory, Episodic; Neuropsychological Tests; Social Perception

The Societal Cost of Dementia in Singapore: Results from the WiSE Study. - Abdin, Edimansyah; Subramaniam, Mythily; Achilla, Evanthia; Chong, Siow Ann; Vaingankar, Janhavi Ajit; Picco, Louisa; Sambasivam, Rajeswari; Pang, Shirlene; Chua, Boon Yiang; Ng, Li Ling; Chua, Hong Choon; Heng, Derrick; et al. (J Alzheimers Dis, 2016)
BACKGROUND: There is currently limited evidence on the economic burden that dementia exerts on multi-ethnic Asian populations. OBJECTIVE: The present study aimed to estimate the economic cost of dementia in Singapore. METHODS: We used data from the Well-being of the Singapore Elderly study, a nationally representative survey of the older Singapore Resident population aged 60 years and above. Generalized linear modeling was used to estimate factors associated with costs. RESULTS: The total cost of dementia in 2013 was estimated at S$532 million (95% CI, S$361 million to S$701 million) while the annual cost per person was estimated at S$10,245 per year (95% CI, S$6,954 to S$12,495). Apart from dementia, higher total societal cost were also significantly associated with older age, Indian ethnicity, and those who were diagnosed with heart problems, stroke, diabetes or depression, whereas being divorced/separated, lower education, and those who were diagnosed with hypertension were significantly associated with lower total societal cost. CONCLUSION: The study provides a rich body of information on healthcare utilization and cost of dementia, which is essential for future planning of services for the elderly population.
Keywords: Adult; Aged, 80 and over; Cost of Illness; Dementia; Female; Humans; Linear Models; Male; Middle Aged; Singapore

Spatial Memory Impairment is Associated with Intraneural Amyloid-β Immunoreactivity and Dysfunctional Arc Expression in the Hippocampal-CA3 Region of a Transgenic Mouse Model of Alzheimer's Disease. - Morin, Jean-Pascal; Cerón-Solano, Giovanni; Velázquez-Campos, Giovanna; Pacheco-López, Gustavo; Bermúdez-Rattoni, Federico; Díaz-Cintra, Sofía (J Alzheimers Dis, 2016)
Dysfunction of synaptic communication in cortical and hippocampal networks has been suggested as one of the neuropathological hallmarks of the early stages of Alzheimer's disease (AD). Also, several lines of evidence have linked disrupted levels of activity-regulated cytoskeletal associated protein (Arc), an immediate early gene product that plays a central role in synaptic plasticity, with AD "synaptopathy". The mapping of Arc expression patterns in brain networks has been extensively used as a marker of memory-relevant neuronal activity history. Here we evaluated basal and behavior-induced Arc expression in hippocampal networks of the 3xTg-AD mouse model of AD. The basal percentage of Arc-expressing cells in 10-month-old 3xTg-AD mice was higher than wild type in CA3 (4.88% versus 1.77% , respectively) but similar in CA1 (1.75% versus 2.75% ). Noteworthy, this difference was not observed at 3 months of age. Furthermore, although a Morris water maze test probe induced a steep (∼4-fold) increment in the percentage of Arc+ cells in the CA3 region of the 10-month-old wild-type group, no such increment was observed in age-matched 3xTg-AD, whereas the amount of Arc+ cells in CA1 increased in both groups. Further, we detected that CA3 neurons with amyloid-β were much more likely to express Arc protein under basal conditions. We propose that in 3xTg-AD mice, intraneuronal amyloid-β expression in CA3 could increase unspecific neuronal activation and subsequent Arc protein expression, which might impair further memory-stabilizing processes.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Benzeneacetamides; CA3 Region, Hippocampal; Cytoskeletal Proteins; Disease Models, Animal; Gene Expression Regulation; Humans; Maze Learning; Memory Disorders; Mice; Mice, Transgenic; Mutation; Nerve Tissue Proteins; Neurons; Presenilin-1; Pyridines; tau Proteins

Specific Features of Subjective Cognitive Decline Predict Faster Conversion to Mild Cognitive Impairment. - Fernández-Blázquez, Miguel A; Ávila-Villanueva, Marina; Maestú, Fernando; Medina, Miguel (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) is a silent disorder that needs the earliest possible intervention in order to reduce its high economic and social impact. It has been recently suggested that subjective cognitive decline (SCD) appears at preclinical stages many years before the onset of AD. Therefore, SCD could become an ideal target for early therapeutic intervention. OBJECTIVE: The goal of this study was to evaluate the clinical significance of SCD on the conversion from a cognitively healthy stage to a mild cognitive impairment (MCI) in one-year follow-up. METHODS: A total of 608 cognitively intact individuals from the Vallecas Project's cohort, a community-based prospective study to identify early markers of AD, were enrolled in this study. Participants were classified in three groups: i) No Complaints (NCg), ii) Subjects with complaints in one or more cognitive domains (SCDg), and iii) Subjects who, besides complaints, fulfilled the features of SCD Plus proposed by the International Working Group of SCD (SCD-Pg). RESULTS: Individuals were followed up for a mean of 13.1 months (range 10.7-22.4). During this time, 41 volunteers developed MCI (6.7% of total sample). The conversion rate for SCD-Pg (18.9%) was significantly higher than SCDg (5.6%) and NCg (4.9%). CONCLUSION: Specific features associated with SCD may help to identify individuals at high risk of fast conversion to MCI. These results highlight the importance of a close follow-up of subjects with SCD-P and include them in early intervention programs because of their increased risk for the development of MCI.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Cognitive Dysfunction; Disease Progression; Female; Follow-Up Studies; Genotyping Techniques; Humans; Kaplan-Meier Estimate; Male; Neuropsychological Tests; Perception; Prodromal Symptoms; Prognosis; Prospective Studies; Time Factors

STX, a Novel Membrane Estrogen Receptor Ligand, Protects Against Amyloid-β Toxicity. - Gray, Nora E; Zweig, Jonathan A; Kawamoto, Colleen; Quinn, Joseph F; Copenhaver, Philip F (J Alzheimers Dis, 2016)
Because STX is a selective ligand for membrane estrogen receptors, it may be able to confer the beneficial effects of estrogen without eliciting the deleterious side effects associated with activation of the nuclear estrogen receptors. This study evaluates the neuroprotective properties of STX in the context of amyloid-β (Aβ) exposure. MC65 and SH-SY5Y neuroblastoma cell lines, as well as primary hippocampal neurons from wild type (WT) and Tg2576 mice, were used to investigate the ability of STX to attenuate cell death, mitochondrial dysfunction, dendritic simplification, and synaptic loss induced by Aβ. STX prevented Aβ-induced cell death in both neuroblastoma cell lines; it also normalized the decrease in ATP and mitochondrial gene expression caused by Aβ in these cells. Notably, STX also increased ATP content and mitochondrial gene expression in control neuroblastoma cells (in the absence of Aβ). Likewise in primary neurons, STX increased ATP levels and mitochondrial gene expression in both genotypes. In addition, STX treatment enhanced dendritic arborization and spine densities in WT neurons and prevented the diminished outgrowth of dendrites caused by Aβ exposure in Tg2576 neurons. These data suggest that STX can act as an effective neuroprotective agent in the context of Aβ toxicity, improving mitochondrial function as well as dendritic growth and synaptic differentiation. In addition, since STX also improved these endpoints in the absence of Aβ, this compound may have broader therapeutic value beyond Alzheimer's disease.
Keywords: Acrylamides; Adenosine Triphosphate; Amyloid beta-Peptides; Animals; Cell Death; Cell Line, Tumor; Drug Evaluation, Preclinical; Estrogen Receptor Modulators; Genes, Mitochondrial; Hippocampus; Humans; Mice, Transgenic; Mitochondria; Neurons; Neuroprotective Agents

T3D-959: A Multi-Faceted Disease Remedial Drug Candidate for the Treatment of Alzheimer's Disease. - Tong, Ming; Deochand, Chetram; Didsbury, John; de la Monte, Suzanne M (J Alzheimers Dis, 2016)
BACKGROUND: T3D-959, a dual PPAR-δ/PPAR γ nuclear receptor agonist and former diabetes drug candidate, has been repositioned as an Alzheimer's disease (AD)-modifying therapy. OBJECTIVE: This study examines the effectiveness and mechanisms of T3D-959's therapeutic effects using in vivo and ex vivo rat models of sporadic AD. METHODS: A sporadic AD model was generated by intracerebral (i.c.) administration of streptozotocin (STZ). Control and i.c. STZ treated rats were gavaged with saline or T3D-959 (0.3 to 3.0 mg/kg/day) for 28 days. Spatial learning and memory were evaluated using the Morris water maze test. Frontal lobe slice cultures generated 24 hours after i.c. STZ or vehicle were used to study early effects of T3D-959 (0.5-1.0 μM) on viability and molecular markers of AD. RESULTS: T3D-959 significantly improved spatial learning and memory in i.c STZ-treated rats. Mechanistically, T3D-959 significantly improved culture viability and brain morphology, reduced levels of oxidative stress and Aβ, and normalized expression of phospho-tau, choline acetyltransferase, and myelin-associated glycoprotein. Protective effects occurred even at the lowest tested dose of T3D-959. CONCLUSIONS: Pre-clinical proof of concept has been demonstrated that T3D-959 can improve multiple pathologies of AD resulting in significant improvements in cognitive function and molecular and biochemical indices of neurodegeneration. These results support the theses that (1) effective disease modification in AD can be achieved by targeting relevant nuclear receptors, and (2) treating AD as a metabolic disease has the potential to be disease remedial. A Phase 2a trial of T3D-959 in mild-to-moderate AD patients has been initiated (ClinicalTrials.gov identifier NCT02560753).
Keywords: Alzheimer Disease; Analysis of Variance; Animals; Animals, Newborn; Antibiotics, Antineoplastic; Antipsychotic Agents; Blood Glucose; Body Weight; Brain; Choline O-Acetyltransferase; Disease Models, Animal; Dose-Response Relationship, Drug; Glial Fibrillary Acidic Protein; Glucosephosphate Dehydrogenase; In Vitro Techniques; Maze Learning; Myelin Basic Protein; Neurotoxicity Syndromes; Organ Culture Techniques; PPAR delta; PPAR gamma; Rats; Rats, Long-Evans; Spatial Learning; Streptozocin

A TgCRND8 Mouse Model of Alzheimer's Disease Exhibits Sexual Dimorphisms in Behavioral Indices of Cognitive Reserve. - Granger, Matthew W; Franko, Bettina; Taylor, Matthew W; Messier, Claude; George-Hyslop, Peter St; Bennett, Steffany A L (J Alzheimers Dis, 2016)
Cognitive decline is sexually dimorphic in Alzheimer's disease (AD). Men show higher incidences of amnestic mild cognitive impairment yet women disproportionally phenoconvert to AD. It is hypothesized that men maintain greater cognitive reserve than women under comparable amyloid-β (Aβ) challenge. One behavioral aspect of cognitive reserve in mice is the capacity to cope with Aβ-associated stereotypies by switching to increasingly effective navigational search strategies in the Morris water maze. To explore inherent sex differences in this paradigm, however, we require an AβPP mouse model wherein behavioral flexibility is impaired earlier in females than males despite equivalent Aβ load. Here, we show that when F1 C57Bl/6×C3H/HeJ TgCRND8 mice are placed on C57Bl/6 background, N5 Tg males and females exhibit equivalent Aβ pathologies at 2, 4, 6, and 8 months of age yet females display learning and memory deficits earlier than males. We further show that this N5 line does not carry the autosomal recessive pde6brd1 mutation that impairs visual acuity and that the estrous cycle is not disrupted on this genetic background. At 5.5 months of age, Tg males, but not females, compensate for Aβ-associated stereotypic behaviors (i.e., hyperactive tight circling) by alternating navigational search strategies and adopting increasingly productive spatial search strategies. Females fail to overcome Aβ-associated stereotypies and do not efficiently switch from systematic to spatial learning strategies. Together, these data identify a novel AβPP mouse model that can be used for preclinical testing of interventions targeting sexual dimorphisms in behavioral indices of cognitive reserve.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Brain; Cognitive Reserve; Cyclic Nucleotide Phosphodiesterases, Type 6; Disease Models, Animal; Female; Humans; Male; Maze Learning; Mice, Inbred C3H; Mice, Inbred C57BL; Mice, Transgenic; Plaque, Amyloid; Psychomotor Performance; Sex Characteristics; Spatial Memory; Spatial Navigation; Survival Analysis

Three-Dimensional Eigenbrain for the Detection of Subjects and Brain Regions Related with Alzheimer's Disease. - Zhang, Yudong; Wang, Shuihua; Phillips, Preetha; Yang, Jiquan; Yuan, Ti-Fei (J Alzheimers Dis, 2016)
BACKGROUND: Considering that Alzheimer's disease (AD) is untreatable, early diagnosis of AD from the healthy elderly controls (HC) is pivotal. However, computer-aided diagnosis (CAD) systems were not widely used due to its poor performance. OBJECTIVE: Inspired from the eigenface approach for face recognition problems, we proposed an eigenbrain to detect AD brains. Eigenface is only for 2D image processing and is not suitable for volumetric image processing since faces are usually obtained as 2D images. METHODS: We extended the eigenbrain to 3D. This 3D eigenbrain (3D-EB) inherits the fundamental strategies in either eigenface or 2D eigenbrain (2D-EB). All the 3D brains were transferred to a feature space, which encoded the variation among known 3D brain images. The feature space was named as the 3D-EB, and defined as eigenvectors on the set of 3D brains. We compared four different classifiers: feed-forward neural network, support vector machine (SVM) with linear kernel, polynomial (Pol) kernel, and radial basis function kernel. RESULTS: The 50x10-fold stratified cross validation experiments showed that the proposed 3D-EB is better than the 2D-EB. SVM with Pol kernel performed the best among all classifiers. Our "3D-EB + Pol-SVM" achieved an accuracy of 92.81% ± 1.99% , a sensitivity of 92.07% ± 2.48% , a specificity of 93.02% ± 2.22% , and a precision of 79.03% ± 2.37% . Based on the most important 3D-EB U1, we detected 34 brain regions related with AD. The results corresponded to recent literature. CONCLUSIONS: We validated the effectiveness of the proposed 3D-EB by detecting subjects and brain regions related to AD.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alzheimer Disease; Brain; Datasets as Topic; Early Diagnosis; Female; Humans; Image Interpretation, Computer-Assisted; Imaging, Three-Dimensional; Magnetic Resonance Imaging; Male; Middle Aged; Sensitivity and Specificity; Young Adult

Time trends in antipsychotic drug use in patients with dementia: a nationwide study. - Nørgaard, Ane; Jensen-Dahm, Christina; Gasse, Christiane; Hansen, Hanne Vibe; Waldemar, Gunhild (J Alzheimers Dis, 2016)
BACKGROUND: Antipsychotics are often used to treat neuropsychiatric symptoms in dementia, but the evidence for effect is limited. Antipsychotics have been associated with increased risk of adverse events and mortality in patients with dementia, leading to safety regulations worldwide. OBJECTIVE: To investigate time trends in use of antipsychotics and other psychotropic drugs in dementia care. METHODS: The study included longitudinal data on all Danish residents ≥65 years. The study population was defined on January 1 of each year from 2000-2012. Data included prescriptions, discharge diagnoses, and somatic and psychiatric comorbidities. Multivariate time trend analyses of psychotropic drug use in patients with dementia within 4-year age bands were performed. RESULTS: Overall, among patients with dementia the prevalence of antipsychotic drug use decreased from 31.3% in 2000 to 20.4% in 2012. The decreasing use of antipsychotics was accompanied by decreasing use of anxiolytics and hypnotics/sedatives, but an increase in the use of antidepressants from 43.3% in 2000 to 53.8% in 2012. These changes were significant across almost all age groups. Treatment intensity among patients using antipsychotics increased as the annual median number of defined daily doses (DDD) increased from 33.3 to 42.0 DDD. CONCLUSIONS: The changing patterns of psychotropic drug use may be caused by warnings against use of antipsychotics. Further research is needed to explore the implications for patient safety.
Keywords: Aged; Aged, 80 and over; Anti-Anxiety Agents; Antidepressive Agents; Antipsychotic Agents; Dementia; Denmark; Drug Prescriptions; Female; Homes for the Aged; Humans; Hypnotics and Sedatives; Longitudinal Studies; Male; Multivariate Analysis; Nursing Homes; Registries

Timely Diagnosis for Alzheimer's Disease: A Literature Review on Benefits and Challenges. - Dubois, Bruno; Padovani, Alessandro; Scheltens, Philip; Rossi, Andrea; Dell'Agnello, Grazia (J Alzheimers Dis, 2016)
BACKGROUND: Timely diagnosis of Alzheimer's disease (AD) refers to a diagnosis at the stage when patients come to the attention of clinicians because of concerns about changes in cognition, behavior, or functioning and can be still free of dementia and functionally independent. OBJECTIVES: To comprehensively review existing scientific evidence on the benefits and potential challenges of making a timely diagnosis of AD. METHODS: Relevant studies were identified by searching electronic databases (Medline, Embase) and bibliographies for studies published in English between 1 January 2000 and 2 June 2014 on the consequences of a timely diagnosis of AD. RESULTS: Nine studies were identified that investigated the consequences of diagnosing AD at the initial stages; none were specifically focused on prodromal AD. A timely diagnosis potentially offers the opportunities of early intervention, implementation of coordinated care plans, better management of symptoms, patient safety, cost savings, and postponement of institutionalization. Barriers to making a timely diagnosis include stigma, suicide risk, lack of training, diagnostic uncertainty, shortage of specialized diagnostic services, and the reluctance of healthcare providers to make a diagnosis when no effective disease-modifying options are available. CONCLUSIONS: Despite its potential benefits, few published studies have explored the advantages or risks of a timely diagnosis of AD. In light of the cultural shift toward diagnosis at the initial stage of the disease continuum, when the patient does not yet have dementia, more investigations are needed to evaluate the benefits and address the barriers that may impede making a timely AD diagnosis.
Keywords: Alzheimer Disease; Databases, Bibliographic; Humans; Time Factors

Tobacco Smoke-Induced Brain White Matter Myelin Dysfunction: Potential Co-Factor Role of Smoking in Neurodegeneration. - Yu, Rosa; Deochand, Chetram; Krotow, Alexander; Leão, Raiane; Tong, Ming; Agarwal, Amit R; Cadenas, Enrique; de la Monte, Suzanne M (J Alzheimers Dis, 2016)
BACKGROUND: Meta-analysis studies showed that smokers have increased risk for developing Alzheimer's disease (AD) compared with non-smokers, and neuroimaging studies revealed that smoking damages white matter structural integrity. OBJECTIVE: The present study characterizes the effects of side-stream (second hand) cigarette smoke (CS) exposures on the expression of genes that regulate oligodendrocyte myelin-synthesis, maturation, and maintenance and neuroglial functions. METHODS: Adult male A/J mice were exposed to air (8 weeks; A8), CS (4 or 8 weeks; CS4, CS8), or CS8 followed by 2 weeks recovery (CS8 + R). The frontal lobes were used for histology and qRT-PCR analysis. RESULTS: Luxol fast blue, Hematoxylin and Eosin stained histological sections revealed CS-associated reductions in myelin staining intensity and narrowing of the corpus callosum. CS exposures broadly decreased mRNA levels of immature and mature oligodendrocyte myelin-associated, neuroglial, and oligodendrocyte-related transcription factors. These effects were more prominent in the CS8 compared with CS4 group, suggesting that molecular abnormalities linked to white matter atrophy and myelin loss worsen with duration of CS exposure. Recovery normalized or upregulated less than 25% of the suppressed genes; in most cases, inhibition of gene expression was either sustained or exacerbated. CONCLUSION: CS exposures broadly inhibit expression of genes needed for myelin synthesis and maintenance. These adverse effects often were not reversed by short-term CS withdrawal. The results support the hypothesis that smoking contributes to white matter degeneration, and therefore could be a key risk factor for a number of neurodegenerative diseases, including AD.
Keywords: 2',3'-Cyclic-Nucleotide Phosphodiesterases; AC133 Antigen; Animals; Antigens, CD; Brain; Disease Models, Animal; Galactosylceramides; Gene Expression Regulation; Glycoproteins; Leukoencephalopathies; Male; Mice; Nerve Degeneration; Nerve Tissue Proteins; Neuroglia; Neurons; Oligodendroglia; Papain; Peptides; Smoking; Tobacco; Transcription Factors

Tract-Specific Correlates of Neuropsychological Deficits in Patients with Subcortical Vascular Cognitive Impairment. - Jung, Na-Yeon; Han, Cheol E; Kim, Hee Jin; Yoo, Sang Wook; Kim, Hee-Jong; Kim, Eun-Joo; Na, Duk L; Lockhart, Samuel N; Jagust, William J; Seong, Joon-Kyung; Seo, Sang Won (J Alzheimers Dis, 2016)
The white matter tract-specific correlates of neuropsychological deficits are not fully established in patients with subcortical vascular cognitive impairment (SVCI), where white matter tract damage may be a critical factor in cognitive impairment. The purpose of this study is to investigate the tract-specific correlates of neuropsychological deficits in SVCI patients using tract-specific statistical analysis (TSSA). We prospectively recruited 114 SVCI patients, and 55 age-, gender-, and education-matched individuals with normal cognition (NC). All participants underwent diffusion weighted imaging and neuropsychological testing. We classified tractography results into fourteen major fiber tracts and analyzed group comparison and correlation with cognitive impairments. Relative to NC subjects, SVCI patients showed decreased fractional anisotropy values in bilateral anterior-thalamic radiation, cingulum, superior-longitudinal fasciculus, uncinate fasciculus, corticospinal tract, and left inferior-longitudinal fasciculus. Focal disruptions in specific tracts were associated with specific cognitive impairments. Our findings suggest that disconnection of specific white matter tracts, especially those neighboring and providing connections between gray matter regions important to certain cognitive functions, may contribute to specific cognitive impairments in SVCI.
Keywords: Aged; Brain; Cerebrovascular Disorders; Cognitive Dysfunction; Diffusion Magnetic Resonance Imaging; Diffusion Tensor Imaging; Female; Gray Matter; Humans; Male; Neural Pathways; Neuropsychological Tests; White Matter

Transferring cut-off values between assays for cerebrospinal fluid Alzheimer's disease biomarkers. - García Barrado, Leandro; Coart, Els; Vanderstichele, Hugo M J; Burzykowski, Tomasz (J Alzheimers Dis, 2016)
Current technologies quantifying cerebrospinal fluid biomarkers to identify subjects with Alzheimer's disease pathology report different concentrations in function of technology and suffer from between-laboratory variability. Hence, lab- and technology-specific cut-off values are required. It is common practice to establish cut-off values on small datasets and, in the absence of well-characterized samples, to transfer the cut-offs to another assay format using 'side-by-side' testing of samples with both assays. We evaluated the uncertainty in cut-off estimation and the performance of two methods of cut-off transfer by using two clinical datasets and simulated data. The cut-off for the new assay was transferred by applying the commonly-used linear regression approach and a new Bayesian method, which consists of using prior information about the current assay for estimation of the biomarker's distributions for the new assay. Simulations show that cut-offs established with current sample sizes are insufficiently precise and also show the effect of increasing sample sizes on the cut-offs' precision. The Bayesian method results in unbiased and less variable cut-offs with substantially narrower 95% confidence intervals compared to the linear-regression transfer. For the BIODEM datasets, the transferred cut-offs for INNO-BIA Aβ1-42 are 167.5 pg/mL (95% credible interval [156.1, 178.0] and 172.8 pg/mL (95% CI [147.6, 179.6]) with Bayesian and linear regression methods, respectively. For the EUROIMMUN assay, the estimated cut-offs are 402.8 pg/mL (95% credible interval [348.0, 473.9]) and 364.4 pg/mL (95% CI [269.7, 426.8]). Sample sizes and statistical methods used to establish and transfer cut-off values have to be carefully considered to guarantee optimal diagnostic performance of biomarkers.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Bayes Theorem; Biomarkers; Cognitive Dysfunction; Datasets as Topic; Humans; Linear Models; Multivariate Analysis; Peptide Fragments; tau Proteins

Two Phase 2 Multiple Ascending-Dose Studies of Vanutide Cridificar (ACC-001) and QS-21 Adjuvant in Mild-to-Moderate Alzheimer's Disease. - Pasquier, Florence; Sadowsky, Carl; Holstein, Ann; Leterme, Ghislaine Le Prince; Peng, Yahong; Jackson, Nicholas; Fox, Nick C; Ketter, Nzeera; Liu, Enchi; Ryan, J Michael (J Alzheimers Dis, 2016)
Vanutide cridificar (ACC-001), an immunotherapeutic vaccine, is a potentially disease-modifying therapy that aims to reduce brain amyloid-β (Aβ) plaques in patients with Alzheimer's disease (AD). ACC-001 was evaluated in two phase 2a, multicenter, randomized, third party-unblinded, placebo-controlled, multiple ascending-dose studies of ACC-001 (3μg, 10μg, 30μg) with and without QS-21 adjuvant that enrolled patients with mild-to-moderate AD (n = 245). Patients were treated with up to five doses of study vaccine or placebo and followed for safety and tolerability (primary objective) and anti-Aβ IgG immunogenicity (secondary objective) up to 12 months after the last vaccination. Exploratory assessments included cognitive/functional measures, brain magnetic resonance imaging (MRI) volumetry, and pharmacodynamic markers in plasma and cerebrospinal fluid (CSF). The most frequent treatment-emergent adverse events (≥10%) were local injection reactions and headache. Amyloid-related imaging abnormalities with vasogenic edema occurred in two (0.8%) patients (ACC-001 30μg + QS-21; ACC-001 10μg). ACC-001 + QS-21 elicited consistently higher peak and sustained anti-Aβ IgG titers compared with ACC-001 alone. Plasma Aβx-40 was significantly higher in all ACC-001 + QS-21 groups versus placebo (weeks 16-56), with no evidence of dose response. Exploratory cognitive evaluations, volumetric brain MRI, and CSF biomarkers did not show differences or trends between treatment groups and placebo. ACC-001 with or without QS-21 adjuvant has an acceptable safety profile in patients with mild-to-moderate AD.
Keywords: Adjuvants, Immunologic; Aged; Alzheimer Disease; Amyloid beta-Peptides; Antipsychotic Agents; Dose-Response Relationship, Drug; Female; Follow-Up Studies; Humans; Interferon-gamma; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Peptide Fragments; Recombinant Fusion Proteins; Saponins; Single-Blind Method; Treatment Outcome

UCH-L1 Inhibition Decreases the Microtubule-Binding Function of Tau Protein. - Xie, Min; Han, Yun; Yu, Quntao; Wang, Xia; Wang, Shaohui; Liao, Xiaomei (J Alzheimers Dis, 2016)
Ubiquitin C-terminal hydrolase L1 (UCH-L1) is critical for protein degradation and free ubiquitin recycling. In Alzheimer's disease brains, UCH-L1 is negatively related to neurofibrillary tangles whose major component is hyperphosphorylated tau protein, but the direct action of UCH-L1 on tau has not been reported. In the current study, mouse neuroblastoma Neuro2a (N2a) cells were treated by the different concentrations of UCH-L1 inhibitor LDN (2.5, 5 and 10 μM) to inhibit the hydrolase activity of UCH-L1. In addition, we also used UCH-L1 siRNA to treat the HEK293/tau441 cells to decrease the expression of UCH-L1. After LDN and UCH-L1 siRNA treatment, we used immunofluorescence, immunoprecipitation, and tau-microtubule binding assay to measure the microtubule-binding ability and post-translational modifications of tau protein. All the results presented that both inhibition of the activity and expression of UCH-L1 induced the decreased microtubule-binding ability and increased phosphorylation of tau protein. Abnormal aggregation and ubiquitination of tau protein was also observed after UCH-L1 inhibition. The above results suggested that aggregation of tau protein might be devoted to the abnormal post-translational modifications of tau protein. Our study first indicates that dysfunction of UCH-L1 most likely affected normal biological function of tau protein through decreasing degradation of ubiquitinated and hyperphosphorylated tau.
Keywords: Animals; Cell Line, Tumor; Dose-Response Relationship, Drug; HEK293 Cells; Humans; Immunoprecipitation; Indoles; Mice; Microtubules; Neuroblastoma; Oximes; Protein Binding; Proteolysis; RNA, Small Interfering; tau Proteins; Ubiquitin Thiolesterase; Ubiquitination

Unmet Needs of Community-Dwelling Primary Care Patients with Dementia in Germany: Prevalence and Correlates. - Eichler, Tilly; Thyrian, Jochen René; Hertel, Johannes; Richter, Steffen; Wucherer, Diana; Michalowsky, Bernhard; Teipel, Stefan; Kilimann, Ingo; Dreier, Adina; Hoffmann, Wolfgang (J Alzheimers Dis, 2016)
BACKGROUND: To provide an optimal care for persons with dementia (PWD), their individual unmet needs have to be identified and comprehensively addressed. OBJECTIVES: Present analyses aim to describe the number and types of unmet needs of German primary care patients screened positive for dementia and factors associated with the number of unmet needs. METHODS: DelpHi-MV (Dementia: life- and person-centered help in Mecklenburg-Western Pomerania) is a general practitioner-based, cluster-randomized controlled intervention trial. Analyses are based on the baseline data of 227 PWD (≥70 years, living at home) of the intervention group who had screened positive for dementia (DemTect<9) and received a standardized computer-assisted needs assessment. RESULTS: PWD had on average 8.77±5.04 unmet needs (Range = 0-31). More than 90% of the PWD had three or more unmet needs. Unmet needs were identified across all predefined 26 subcategories. The majority of unmet needs occurred in the domains "nursing treatment and care" (38%), "social counseling and legal support" (20%), and "pharmacological treatment and care" (15%). More impairment in the activities of daily living was the only factor that was significantly associated with a higher number of unmet needs, independent of age, gender, living situation, presence of an informal caregiver, cognitive impairment, and depression. CONCLUSIONS: Present results demonstrate that community-dwelling PWD had a broad range of varying unmet needs. These findings emphasize the importance of a comprehensive needs assessment that allows the identification of individual needs as the basis for a tailored intervention- such as Dementia Care Management- that can address these needs.
Keywords: Aged, 80 and over; Caregivers; Cross-Sectional Studies; Dementia; Depression; Female; Germany; Health Services Needs and Demand; Humans; Male; Needs Assessment; Prevalence

Unraveling Alzheimer's: Making Sense of the Relationship between Diabetes and Alzheimer's Disease1. - Schilling, Melissa A (J Alzheimers Dis, 2016)
Numerous studies have documented a strong association between diabetes and Alzheimer's disease (AD). The nature of the relationship, however, has remained a puzzle, in part because of seemingly incongruent findings. For example, some studies have concluded that insulin deficiency is primarily at fault, suggesting that intranasal insulin or inhibiting the insulin-degrading enzyme (IDE) could be beneficial. Other research has concluded that hyperinsulinemia is to blame, which implies that intranasal insulin or the inhibition of IDE would exacerbate the disease. Such antithetical conclusions pose a serious obstacle to making progress on treatments. However, careful integration of multiple strands of research, with attention to the methods used in different studies, makes it possible to disentangle the research on AD. This integration suggests that there is an important relationship between insulin, IDE, and AD that yields multiple pathways to AD depending on the where deficiency or excess in the cycle occurs. I review evidence for each of these pathways here. The results suggest that avoiding excess insulin, and supporting robust IDE levels, could be important ways of preventing and lessening the impact of AD. I also describe what further tests need to be conducted to verify the arguments made in the paper, and their implications for treating AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amylose; Diabetes Mellitus; Humans; Insulin; Insulysin

Unstable Body Mass Index and Progression to Probable Alzheimer's Disease Dementia in Patients with Amnestic Mild Cognitive Impairment. - Ye, Byoung Seok; Jang, Eun Young; Kim, Seong Yoon; Kim, Eun-Joo; Park, Sun Ah; Lee, Yunhwan; Hong, Chang Hyung; Choi, Seong Hye; Yoon, Bora; Yoon, Soo Jin; Na, Hae Ri; Lee, Jae-Hong; et al. (J Alzheimers Dis, 2016)
BACKGROUND AND OBJECTIVE: We investigated the influence of body mass index (BMI) status at baseline and changes in BMI over a follow-up period on the development of dementia in amnestic mild cognitive impairment (aMCI) patients. METHODS: The longitudinal data of 747 aMCI patients were used to investigate the relationships among baseline BMI status, subsequent changes in BMI (median follow-up duration: 1.6 years, interquartile range: 1.0-2.3 years), and risk of progression to probable Alzheimer's disease dementia (pADD). The aMCI patients were classified into underweight, normal weight, overweight, and obese subgroups, and further categorized into increased BMI, stable BMI, and decreased BMI subgroups during follow-up using a 4% mean annual change in BMI cut-off value. RESULTS: Compared to the normal weight group, the underweight group had a higher risk of pADD (hazard ratio [HR]: 1.89, 95% confidence interval [CI]: 1.07-3.37) while the obese group had a lower risk (HR: 0.70, 95% CI: 0.49-0.999). After controllingfor baseline BMI status, the decreased BMI (HR: 2.29, 95% CI: 1.41-3.72) and increased BMI (HR: 3.96, 95% CI: 2.62-6.00) groups were at increased risk of progression to pADD. CONCLUSIONS: Our findings suggested that underweight at baseline was associated with a higher risk of progression to pADD, while obesity at baseline predicted a lower risk. Furthermore, significant changes in BMI during the follow-up period reflected an increased risk of progression to pADD, regardless of BMI status at baseline.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Body Mass Index; Body Weight; Cognitive Dysfunction; Dementia; Disease Progression; Female; Humans; Kaplan-Meier Estimate; Longitudinal Studies; Male; Neuropsychological Tests; Registries

Upregulation of Connexin 43 Expression Via C-Jun N-Terminal Kinase Signaling in Prion Disease. - Lee, Geon-Hwi; Jang, Byungki; Choi, Hong-Seok; Kim, Hee-Jun; Park, Jeong-Ho; Jeon, Yong-Chul; Carp, Richard I; Kim, Yong-Sun; Choi, Eun-Kyoung (J Alzheimers Dis, 2016)
Prion infection leads to neuronal cell death, glial cell activation, and the accumulation of misfolded prion proteins. However, the altered cellular environments in animals with prion diseases are poorly understood. In the central nervous system, cells connect the cytoplasm of adjacent cells via connexin (Cx)-assembled gap junction channels to allow the direct exchange of small molecules, including ions, neurotransmitters, and signaling molecules, which regulate the activities of the connected cells. Here, we investigate the role of Cx43 in the pathogenesis of prion diseases. Upregulated Cx43 expression, which was dependent on c-Jun N-Terminal Kinase (JNK)/c-Jun signaling cascades, was found in prion-affected brain tissues and hippocampal neuronal cells. Scrapie infection-induced Cx43 formed aggregated plaques within the cytoplasmic compartments at the cell-cell interfaces. The ethidium bromide (EtBr) uptake assay and scrape-loading dye transfer assay demonstrated that increased Cx43 has functional consequences for the activity of Cx43 hemichannels. Interestingly, blockade of PrPSc accumulation reduced Cx43 expression through the inhibition of JNK signaling, indicating that PrPSc accumulation may be directly involved in JNK activation-mediated Cx43 upregulation. Overall, our findings describe a scrapie infection-mediated novel regulatory signaling pathway of Cx43 expression and may suggest a role for Cx43 in the pathogenesis of prion diseases.
Keywords: Animals; Brain; Cell Membrane; Cells, Cultured; Connexin 43; Disease Models, Animal; JNK Mitogen-Activated Protein Kinases; MAP Kinase Signaling System; Mesocricetus; Mice, Inbred C57BL; Mice, Knockout; PrPSc Proteins; RNA, Messenger; Scrapie; Up-Regulation

Usefulness of an Integrated Analysis of Different Memory Tasks to Predict the Progression from Mild Cognitive Impairment to Alzheimer's Disease: The Episodic Memory Score (EMS). - Marra, Camillo; Gainotti, Guido; Fadda, Lucia; Perri, Roberta; Lacidogna, Giordano; Scaricamazza, Eugenia; Piccininni, Chiara; Quaranta, Davide (J Alzheimers Dis, 2016)
Taking into the account both the severity and the consistency of performances obtained on memory tests by patients with amnestic mild cognitive impairment (aMCI) could improve the power to predict their progression to Alzheimer's disease. For this purpose, we constructed the Episodic Memory Score (EMS), which is obtained by subdividing in tertiles performances obtained at baseline in verbal (RAVLT) and visual episodic memory (Rey-Osterrieth Figure-delayed recall) and giving a score ranging from 1 (worst result) to 3 (best result) to results falling within each tertile. The EMS was computed for each patient by summing the tertile score obtained on each memory task, so that the total score ranged from 4 (worst performance) to 12 (best performance). The aMCI sample consisted of 198 subjects who completed the two-year follow-up, at the end of which 55 subjects had converted to dementia. The mean EMS score obtained by aMCI converters was significantly lower than that of aMCI-stable patients. In detecting conversion to dementia, the comparison between EMS and individual memory scores obtained at baseline was made by computing ROC curves, and estimating the respective area under the curve (AUC). The EMS had a larger AUC than the individual memory scores. At baseline aMCI converters performed worse than non-converters not only on memory tasks, but also on executive functions tasks. However, in a multiple variables logistic regression analysis in which all scores showing statistically significant differences between aMCI-converters and aMCI-stable were entered, the EMS was the only reliable predictor of progression from aMCI to dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Disease Progression; Female; Humans; Logistic Models; Longitudinal Studies; Male; Memory, Episodic; Mental Recall; Neuropsychological Tests; ROC Curve

Vascular Risk Factors and Cognition in Parkinson's Disease. - Pilotto, Andrea; Turrone, Rosanna; Liepelt-Scarfone, Inga; Bianchi, Marta; Poli, Loris; Borroni, Barbara; Alberici, Antonella; Premi, Enrico; Formenti, Anna; Bigni, Barbara; Cosseddu, Maura; Cottini, Elisabetta; et al. (J Alzheimers Dis, 2016)
Vascular risk factors have been associated with cognitive deficits and incident dementia in the general population, but their role on cognitive dysfunction in Parkinson's disease (PD) is still unclear. The present study addresses the single and cumulative effect of vascular risk factors on cognition in PD patients, taking clinical confounders into account. Standardized neuropsychological assessment was performed in 238 consecutive PD patients. We evaluated the association of single and cumulative vascular risk factors (smoking, diabetes, hypercholesterolemia, hypertension, and heart disease), with the diagnosis of PD normal cognition (PDNC, n = 94), mild cognitive impairment (PD-MCI, n = 111), and dementia (PDD, n = 33). The association between single neuropsychological tests and vascular risk factors was evaluated with covariance analyses adjusted for age at onset, educational levels, gender, disease duration, and motor performance. Age, educational levels, disease duration, and motor function were significantly different between PDNC, PD-MCI, and PDD. Heart disease was the only vascular factor significantly more prevalent in PDD compared with PDNC in adjusted analyses. Performance of tests assessing executive and attention functions were significantly worse in patients with hypertension, heart disease, and/or diabetes (p <  0.05). Heart disease is associated with dementia in PD, suggesting a potential window of intervention. Vascular risk factors act especially on attention and executive functions in PD. Vascular risk stratification may be useful in order to identify PD patients with a greater risk of developing dementia. These findings need to be verified in longitudinal studies.
Keywords: Age of Onset; Aged; Attention; Disability Evaluation; Educational Status; Executive Function; Female; Humans; Male; Motor Activity; Neuropsychological Tests; Parkinson Disease; Prevalence; Risk Factors; Sex Factors; Time Factors; Vascular Diseases

Ventilatory Response to Hypercapnia Predicts Dementia with Lewy Bodies in Late-Onset Major Depressive Disorder. - Takahashi, Sho; Mizukami, Katsuyoshi; Arai, Tetsuaki; Ogawa, Ryoko; Kikuchi, Norihiro; Hattori, Satoshi; Darby, David; Asada, Takashi (J Alzheimers Dis, 2016)
BACKGROUND: Studies have shown that developing major depressive disorder (MDD) at 50 years of age or older can predict dementia. Depression is particularly common in dementia with Lewy bodies (DLB), and occasionally occurs before the onset of extrapyramidal symptoms. Moreover, systemic autonomic dysfunction, including an abnormal ventilatory response to hypercapnia (VRH), is common in patients with DLB. OBJECTIVE: Here, we aimed to determine whether the VRH is useful for distinguishing depression that is predictive of DLB from other types of MDD. METHODS: Participants were 35 consecutive patients with first onset MDD at 50 years or older with bradykinesia. After diagnosing the clinical subtype of MDD according to DSM-IV criteria, each subject underwent a battery of psychological tests, autonomic examinations including VRH, brain magnetic resonance imaging, and 123I-meta-iodobenzylguanidine scintigraphy. RESULTS: Longitudinal follow-up showed that all 18 patients with abnormal VRH results developed DLB, whereas none of the 17 patients with normal VRH results converted to DLB within the study period (sensitivity: 100% , specificity: 100%). Additionally, over half of the DLB converters showed abnormalities on other autonomic examinations. For converters, the most common MDD subtype had psychotic and melancholic features simultaneously. The frequency of hypersensitivity to psychotropics was higher in converters than it was in non-converters. CONCLUSION: In the present study, patients with abnormal VRH results were very likely to develop DLB. Thus, for patients with late-onset MDD accompanied by bradykinesia, the VRH in combination with the clinical subtype of MDD or hypersensitivity to psychotropics may be useful for diagnosing prodromal DLB.
Keywords: 3-Iodobenzylguanidine; Aged; Aged, 80 and over; Depressive Disorder, Major; Follow-Up Studies; Heart Rate; Humans; Hypercapnia; Hypotension, Orthostatic; Kaplan-Meier Estimate; Lewy Body Disease; Middle Aged; Partial Pressure; Psychiatric Status Rating Scales; Retrospective Studies; Ventilators, Mechanical

What are the Most Frequently Impaired Markers of Neurodegeneration in ADNI Subjects? - Andriuta, Daniela; Moullart, Véronique; Schraen, Susanna; Devendeville, Agnes; Meyer, Marc-Etienne; Godefroy, Olivier (J Alzheimers Dis, 2016)
The aim of this study was to examine the relationship between cerebrospinal fluid (CSF) levels of biomarkers for Alzheimer's disease (AD) (Aβ1-42, t-tau, and p-tau) and 18Fluorodeoxyglucose positron emission tomography (FDG-PET) hypometabolism in subjects from the Alzheimer's Disease Neuroimaging Initiative, and specifically to determine which index of neurodegeneration was most frequently affected. The secondary objective was to determine the most frequently hypometabolic region in patients with a CSF AD signature (abnormal Aβ1-42 and abnormal p-tau). We included the 372 subjects (85 normal subjects, 212 patients with mild cognitive impairment, and 75 patients with AD) with a CSF biomarker dosage (Aβ1-42, t-tau, and p-tau) and brain FDG-PET. The relationship between FDG-PET metabolism (in five regions of interest (ROI) known to be damaged in AD) and CSF t-tau and p-tau levels was studied as a function of CSF Aβ1-42 status. FDG-PET hypometabolism and CSF t-tau and p-tau levels were correlated only in patients with an abnormal CSF Aβ1-42 level (t-tau: R2 = 0.044, p = 0.001; p-tau: R2 = 0.02, p = 0.03). In the latter patients, CSF p-tau was the most frequently (p = 0.0001) abnormal neurodegeneration marker (p-tau: 92.8%; FDG-PET: 56.5%; CSF t-tau: 59.1%). Within the five ROI of FDG PET, the angular gyrus metabolism (R2 = 0.149; p = 0.0001) was selected as the most tightly associated with CSF AD signature. The relation between CSF markers of neurodegeneration (p-tau and t-tau) and brain hypometabolism (in FDG-PET) is conditioned by presence of amyloid abnormality. This finding supports the current physiopathological model of AD. P-tau is the most frequently impaired biomarker. Using FDG PET angular gyrus hypometabolism is the most sensitive to CSF-biomarker-defined AD.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Brain; Cognitive Dysfunction; Databases, Factual; Female; Fluorodeoxyglucose F18; Humans; Male; Peptide Fragments; Phosphorylation; Positron-Emission Tomography; Radiopharmaceuticals; tau Proteins

White Matter Abnormalities Track Disease Progression in PSEN1 Autosomal Dominant Alzheimer's Disease. - Sánchez-Valle, Raquel; Monté, Gemma C; Sala-Llonch, Roser; Bosch, Beatriz; Fortea, Juan; Lladó, Albert; Antonell, Anna; Balasa, Mircea; Bargalló, Nuria; Molinuevo, José Luis (J Alzheimers Dis, 2016)
PSEN1 mutations are the most frequent cause of autosomal dominant Alzheimer's disease (ADAD), and show nearly full penetrance. There is presently increasing interest in the study of biomarkers that track disease progression in order to test therapeutic interventions in ADAD. We used white mater (WM) volumetric characteristics and diffusion tensor imaging (DTI) metrics to investigate correlations with the normalized time to expected symptoms onset (relative age ratio) and group differences in a cohort of 36 subjects from PSEN1 ADAD families: 22 mutation carriers, 10 symptomatic (SMC) and 12 asymptomatic (AMC), and 14 non-carriers (NC). Subjects underwent a 3T MRI. WM morphometric data and DTI metrics were analyzed. We found that PSEN1 MC showed significant negative correlation between fractional anisotropy (FA) and the relative age ratio in the genus and body of corpus callosum and corona radiate (p <  0.05 Family-wise error correction (FWE) at cluster level) and positive correlation with mean diffusivity (MD), axial diffusivity (AxD), and radial diffusivity (RD) in the splenium of corpus callosum. SMC presented WM volume loss, reduced FA and increased MD, AxD, and RD in the anterior and posterior corona radiate, corpus callosum (p <  0.05 FWE) compared with NC. No significant differences were observed between AMC and NC in WM volume or DTI measures. These findings suggest that the integrity of the WM deteriorates linearly in PSEN1 ADAD from the early phases of the disease; thus DTI metrics might be useful to monitor the disease progression. However, the lack of significant alterations at the preclinical stages suggests that these indexes might not be good candidates for early markers of the disease.
Keywords: Adult; Aging; Alzheimer Disease; Brain; Cohort Studies; Diffusion Tensor Imaging; Disease Progression; Family; Female; Heterozygote; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Mutation; Neuropsychological Tests; Organ Size; Presenilin-1; White Matter

White Matter and Hippocampal Volume Predict the Risk of Dementia in Patients with Cerebral Small Vessel Disease: The RUN DMC Study. - van Uden, Ingeborg W M; van der Holst, Helena M; Tuladhar, Anil M; van Norden, Anouk G W; de Laat, Karlijn F; Rutten-Jacobs, Loes C A; Norris, David G; Claassen, Jurgen A H R; van Dijk, Ewoud J; Kessels, Roy P C; de Leeuw, Frank-Erik (J Alzheimers Dis, 2016)
BACKGROUND: The relationship between cerebral small vessel disease (SVD) and dementia has been studied without considering white matter (WM) volume, the microstructural integrity of the WM surrounding the SVD, and grey matter (GM). OBJECTIVE: We prospectively investigated the relationship between these structures and the risk of dementia, and formed a prediction model to investigate which characteristics (macro- or microstructural) explained most of the variance. METHODS: The RUN DMC study is a prospective cohort study among 503 non-demented participants with an age between 50 and 85 years at baseline, with baseline assessment in 2006 and follow-up assessment in 2012. Two were lost to follow-up (yielding a 99.6% response-rate). Cox regression analysis was used, to calculate hazard ratios for dementia, of baseline MRI characteristics. Tract-Based Spatial Statistics (TBSS) analysis was used to assess the added value of microstructural integrity of the WM. RESULTS: Mean age at baseline was 65.6 years (SD 8.8) and 56.8% was male. 43 participants developed dementia (8.6%), resulting in a 5.5-year cumulative risk of 11.1% (95% CI 7.7-14.6). Low WM and hippocampal volume are significant predictors for dementia. WM, WM hyperintensities, and hippocampal volume explained most of the variance. TBSS analyses showed no additional value of diffusion parameters. CONCLUSIONS: WM and hippocampal volume were the main predictors for the development of incident dementia at 5-year follow-up in elderly with SVD. There was no additional diagnostic value of the diffusion tensor imaging parameters on top of the macrostructural characteristics.
Keywords: Aged; Cerebral Small Vessel Diseases; Cohort Studies; Dementia; Diffusion Tensor Imaging; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Statistics, Nonparametric; White Matter

White Matter Changes are Associated with Ventricular Expansion in Aging, Mild Cognitive Impairment, and Alzheimer's Disease. - Coutu, Jean-Philippe; Goldblatt, Alison; Rosas, H Diana; Salat, David H (J Alzheimers Dis, 2016)
White matter lesions are highly prevalent in individuals with Alzheimer's disease (AD). Although these lesions are presumed to be of vascular origin and linked to small vessel disease in older adults, little information exists about their relationship to markers of classical AD neurodegeneration. Thus, we examined the link between these white matter changes (WMC) segmented on T1-weighted MRI and imaging markers presumed to be altered due to primary AD neurodegenerative processes. Tissue microstructure of WMC was quantified using diffusion tensor imaging and the relationship of WMC properties and volume to neuroimaging markers was examined in 219 cognitively healthy older adults and individuals with mild cognitive impairment and AD using data from the Alzheimer's Disease Neuroimaging Initiative. No significant group differences in WMC properties were found. However, there were strong associations between diffusivity of WMC and ventricular volume, volume of WMC and total WM volume. In comparison, group differences in parahippocampal white matter microstructure were found for all diffusion metrics and were largely explained by hippocampal volume. Factor analysis on neuroimaging markers suggested two independent sets of covarying degenerative changes, with potentially age- and vascular-mediated tissue damage contributing to one factor and classical neurodegenerative changes associated with AD contributing to a second factor. These data demonstrate two potentially distinct classes of degenerative change in AD, with one factor strongly linked to aging, ventricular expansion, and both volume and tissue properties of white matter lesions, while the other factor related to classical patterns of cortical and hippocampal neurodegeneration in AD.
Keywords: Aged; Aging; Alzheimer Disease; Cognitive Dysfunction; Diffusion Tensor Imaging; Factor Analysis, Statistical; Female; Hippocampus; Humans; Imaging, Three-Dimensional; Male; Mental Status Schedule; Neuropsychological Tests; White Matter

C9orf72 nucleotide repeat structures initiate molecular cascades of disease. - Haeusler, Aaron R; Donnelly, Christopher J; Periz, Goran; Simko, Eric A J; Shaw, Patrick G; Kim, Min-Sik; Maragakis, Nicholas J; Troncoso, Juan C; Pandey, Akhilesh; Sattler, Rita; Rothstein, Jeffrey D; Wang, Jiou (Nature, 2014)
A hexanucleotide repeat expansion (HRE), (GGGGCC)n, in C9orf72 is the most common genetic cause of the neurodegenerative diseases amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Here we identify a molecular mechanism by which structural polymorphism of the HRE leads to ALS/FTD pathology and defects. The HRE forms DNA and RNA G-quadruplexes with distinct structures and promotes RNA•DNA hybrids (R-loops). The structural polymorphism causes a repeat-length-dependent accumulation of transcripts aborted in the HRE region. These transcribed repeats bind to ribonucleoproteins in a conformation-dependent manner. Specifically, nucleolin, an essential nucleolar protein, preferentially binds the HRE G-quadruplex, and patient cells show evidence of nucleolar stress. Our results demonstrate that distinct C9orf72 HRE structural polymorphism at both DNA and RNA levels initiates molecular cascades leading to ALS/FTD pathologies, and provide the basis for a mechanistic model for repeat-associated neurodegenerative diseases.
Keywords: Amyotrophic Lateral Sclerosis; B-Lymphocytes; Base Sequence; Cell Nucleolus; DNA; DNA Repeat Expansion; Frontotemporal Dementia; G-Quadruplexes; HEK293 Cells; Humans; Models, Molecular; Neurons; Open Reading Frames; Phosphoproteins; Ribonucleoproteins; RNA; RNA-Binding Proteins; Stress, Physiological; Transcription, Genetic

Phase 3 trials of solanezumab for mild-to-moderate Alzheimer's disease. - Doody, Rachelle S; Thomas, Ronald G; Farlow, Martin; Iwatsubo, Takeshi; Vellas, Bruno; Joffe, Steven; Kieburtz, Karl; Raman, Rema; Sun, Xiaoying; Aisen, Paul S; Siemers, Eric; Liu-Seifert, Hong; et al. (N Engl J Med, 2014)
BACKGROUND: Alzheimer's disease is characterized by amyloid-beta plaques, neurofibrillary tangles, gliosis, and neuronal loss. Solanezumab, a humanized monoclonal antibody, preferentially binds soluble forms of amyloid and in preclinical studies promoted its clearance from the brain. METHODS: In two phase 3, double-blind trials (EXPEDITION 1 and EXPEDITION 2), we randomly assigned 1012 and 1040 patients, respectively, with mild-to-moderate Alzheimer's disease to receive placebo or solanezumab (administered intravenously at a dose of 400 mg) every 4 weeks for 18 months. The primary outcomes were the changes from baseline to week 80 in scores on the 11-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog11; range, 0 to 70, with higher scores indicating greater cognitive impairment) and the Alzheimer's Disease Cooperative Study-Activities of Daily Living scale (ADCS-ADL; range, 0 to 78, with lower scores indicating worse functioning). After analysis of data from EXPEDITION 1, the primary outcome for EXPEDITION 2 was revised to the change in scores on the 14-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog14; range, 0 to 90, with higher scores indicating greater impairment), in patients with mild Alzheimer's disease. RESULTS: Neither study showed significant improvement in the primary outcomes. The modeled difference between groups (solanezumab group minus placebo group) in the change from baseline was -0.8 points for the ADAS-cog11 score (95% confidence interval [CI], -2.1 to 0.5; P=0.24) and -0.4 points for the ADCS-ADL score (95% CI, -2.3 to 1.4; P=0.64) in EXPEDITION 1 and -1.3 points (95% CI, -2.5 to 0.3; P=0.06) and 1.6 points (95% CI, -0.2 to 3.3; P=0.08), respectively, in EXPEDITION 2. Between-group differences in the changes in the ADAS-cog14 score were -1.7 points in patients with mild Alzheimer's disease (95% CI, -3.5 to 0.1; P=0.06) and -1.5 in patients with moderate Alzheimer's disease (95% CI, -4.1 to 1.1; P=0.26). In the combined safety data set, the incidence of amyloid-related imaging abnormalities with edema or hemorrhage was 0.9% with solanezumab and 0.4% with placebo for edema (P=0.27) and 4.9% and 5.6%, respectively, for hemorrhage (P=0.49). CONCLUSIONS: Solanezumab, a humanized monoclonal antibody that binds amyloid, failed to improve cognition or functional ability. (Funded by Eli Lilly; EXPEDITION 1 and 2 ClinicalTrials.gov numbers, NCT00905372 and NCT00904683.).
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Antibodies, Monoclonal, Humanized; Apolipoproteins E; Biomarkers; Cognition; Double-Blind Method; Female; Humans; Intention to Treat Analysis; Male; Neuropsychological Tests; Severity of Illness Index; tau Proteins; Treatment Failure

Plasma phospholipids identify antecedent memory impairment in older adults. - Mapstone, Mark; Cheema, Amrita K; Fiandaca, Massimo S; Zhong, Xiaogang; Mhyre, Timothy R; MacArthur, Linda H; Hall, William J; Fisher, Susan G; Peterson, Derick R; Haley, James M; Nazar, Michael D; Rich, Steven A; et al. (Nat Med, 2014)
Alzheimer's disease causes a progressive dementia that currently affects over 35 million individuals worldwide and is expected to affect 115 million by 2050 (ref. 1). There are no cures or disease-modifying therapies, and this may be due to our inability to detect the disease before it has progressed to produce evident memory loss and functional decline. Biomarkers of preclinical disease will be critical to the development of disease-modifying or even preventative therapies. Unfortunately, current biomarkers for early disease, including cerebrospinal fluid tau and amyloid-β levels, structural and functional magnetic resonance imaging and the recent use of brain amyloid imaging or inflammaging, are limited because they are either invasive, time-consuming or expensive. Blood-based biomarkers may be a more attractive option, but none can currently detect preclinical Alzheimer's disease with the required sensitivity and specificity. Herein, we describe our lipidomic approach to detecting preclinical Alzheimer's disease in a group of cognitively normal older adults. We discovered and validated a set of ten lipids from peripheral blood that predicted phenoconversion to either amnestic mild cognitive impairment or Alzheimer's disease within a 2-3 year timeframe with over 90% accuracy. This biomarker panel, reflecting cell membrane integrity, may be sensitive to early neurodegeneration of preclinical Alzheimer's disease.
Keywords: Aged; Alzheimer Disease; Asparagine; Biomarkers; Carnitine; Cohort Studies; Dipeptides; Female; Humans; Longitudinal Studies; Lysophosphatidylcholines; Malates; Male; Memory Disorders; Metabolome; Mild Cognitive Impairment; Neuropsychological Tests; Phosphatidylcholines; Phosphatidylinositols; Phospholipids; Proline; Prospective Studies; Sensitivity and Specificity; Sphingomyelins; Ursodeoxycholic Acid

REST and stress resistance in ageing and Alzheimer's disease. - Lu, Tao; Aron, Liviu; Zullo, Joseph; Pan, Ying; Kim, Haeyoung; Chen, Yiwen; Yang, Tun-Hsiang; Kim, Hyun-Min; Drake, Derek; Liu, X Shirley; Bennett, David A; Colaiácovo, Monica P; et al. (Nature, 2014)
Human neurons are functional over an entire lifetime, yet the mechanisms that preserve function and protect against neurodegeneration during ageing are unknown. Here we show that induction of the repressor element 1-silencing transcription factor (REST; also known as neuron-restrictive silencer factor, NRSF) is a universal feature of normal ageing in human cortical and hippocampal neurons. REST is lost, however, in mild cognitive impairment and Alzheimer's disease. Chromatin immunoprecipitation with deep sequencing and expression analysis show that REST represses genes that promote cell death and Alzheimer's disease pathology, and induces the expression of stress response genes. Moreover, REST potently protects neurons from oxidative stress and amyloid β-protein toxicity, and conditional deletion of REST in the mouse brain leads to age-related neurodegeneration. A functional orthologue of REST, Caenorhabditis elegans SPR-4, also protects against oxidative stress and amyloid β-protein toxicity. During normal ageing, REST is induced in part by cell non-autonomous Wnt signalling. However, in Alzheimer's disease, frontotemporal dementia and dementia with Lewy bodies, REST is lost from the nucleus and appears in autophagosomes together with pathological misfolded proteins. Finally, REST levels during ageing are closely correlated with cognitive preservation and longevity. Thus, the activation state of REST may distinguish neuroprotection from neurodegeneration in the ageing brain.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid beta-Peptides; Animals; Autophagy; Brain; Caenorhabditis elegans Proteins; Cell Death; Cell Nucleus; Chromatin Immunoprecipitation; Cognition; DNA-Binding Proteins; Down-Regulation; Frontotemporal Dementia; Gene Expression Regulation; Humans; Lewy Body Disease; Longevity; Mice; Mild Cognitive Impairment; Neurons; Neuroprotective Agents; Oxidative Stress; Phagosomes; Repressor Proteins; Transcription Factors; Up-Regulation; Wnt Signaling Pathway; Young Adult

A three-dimensional human neural cell culture model of Alzheimer's disease. - Choi, Se Hoon; Kim, Young Hye; Hebisch, Matthias; Sliwinski, Christopher; Lee, Seungkyu; D'Avanzo, Carla; Chen, Hechao; Hooli, Basavaraj; Asselin, Caroline; Muffat, Julien; Klee, Justin B; Zhang, Can; et al. (Nature, 2014)
Alzheimer's disease is the most common form of dementia, characterized by two pathological hallmarks: amyloid-β plaques and neurofibrillary tangles. The amyloid hypothesis of Alzheimer's disease posits that the excessive accumulation of amyloid-β peptide leads to neurofibrillary tangles composed of aggregated hyperphosphorylated tau. However, to date, no single disease model has serially linked these two pathological events using human neuronal cells. Mouse models with familial Alzheimer's disease (FAD) mutations exhibit amyloid-β-induced synaptic and memory deficits but they do not fully recapitulate other key pathological events of Alzheimer's disease, including distinct neurofibrillary tangle pathology. Human neurons derived from Alzheimer's disease patients have shown elevated levels of toxic amyloid-β species and phosphorylated tau but did not demonstrate amyloid-β plaques or neurofibrillary tangles. Here we report that FAD mutations in β-amyloid precursor protein and presenilin 1 are able to induce robust extracellular deposition of amyloid-β, including amyloid-β plaques, in a human neural stem-cell-derived three-dimensional (3D) culture system. More importantly, the 3D-differentiated neuronal cells expressing FAD mutations exhibited high levels of detergent-resistant, silver-positive aggregates of phosphorylated tau in the soma and neurites, as well as filamentous tau, as detected by immunoelectron microscopy. Inhibition of amyloid-β generation with β- or γ-secretase inhibitors not only decreased amyloid-β pathology, but also attenuated tauopathy. We also found that glycogen synthase kinase 3 (GSK3) regulated amyloid-β-mediated tau phosphorylation. We have successfully recapitulated amyloid-β and tau pathology in a single 3D human neural cell culture system. Our unique strategy for recapitulating Alzheimer's disease pathology in a 3D neural cell culture model should also serve to facilitate the development of more precise human neural cell models of other neurodegenerative disorders.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cell Culture Techniques; Cell Differentiation; Drug Evaluation, Preclinical; Extracellular Space; Glycogen Synthase Kinase 3; Humans; Microtubule-Associated Proteins; Models, Biological; Neural Stem Cells; Neurites; Phosphorylation; Presenilin-1; Protein Aggregation, Pathological; Reproducibility of Results; tau Proteins

Two phase 3 trials of bapineuzumab in mild-to-moderate Alzheimer's disease. - Salloway, Stephen; Sperling, Reisa; Fox, Nick C; Blennow, Kaj; Klunk, William; Raskind, Murray; Sabbagh, Marwan; Honig, Lawrence S; Porsteinsson, Anton P; Ferris, Steven; Reichert, Marcel; Ketter, Nzeera; et al. (N Engl J Med, 2014)
BACKGROUND: Bapineuzumab, a humanized anti-amyloid-beta monoclonal antibody, is in clinical development for the treatment of Alzheimer's disease. METHODS: We conducted two double-blind, randomized, placebo-controlled, phase 3 trials involving patients with mild-to-moderate Alzheimer's disease--one involving 1121 carriers of the apolipoprotein E (APOE) ε4 allele and the other involving 1331 noncarriers. Bapineuzumab or placebo, with doses varying by study, was administered by intravenous infusion every 13 weeks for 78 weeks. The primary outcome measures were scores on the 11-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog11, with scores ranging from 0 to 70 and higher scores indicating greater impairment) and the Disability Assessment for Dementia (DAD, with scores ranging from 0 to 100 and higher scores indicating less impairment). A total of 1090 carriers and 1114 noncarriers were included in the efficacy analysis. Secondary outcome measures included findings on positron-emission tomographic amyloid imaging with the use of Pittsburgh compound B (PIB-PET) and cerebrospinal fluid phosphorylated tau (phospho-tau) concentrations. RESULTS: There were no significant between-group differences in the primary outcomes. At week 78, the between-group differences in the change from baseline in the ADAS-cog11 and DAD scores (bapineuzumab group minus placebo group) were -0.2 (P=0.80) and -1.2 (P=0.34), respectively, in the carrier study; the corresponding differences in the noncarrier study were -0.3 (P=0.64) and 2.8 (P=0.07) with the 0.5-mg-per-kilogram dose of bapineuzumab and 0.4 (P=0.62) and 0.9 (P=0.55) with the 1.0-mg-per-kilogram dose. The major safety finding was amyloid-related imaging abnormalities with edema among patients receiving bapineuzumab, which increased with bapineuzumab dose and APOE ε4 allele number and which led to discontinuation of the 2.0-mg-per-kilogram dose. Between-group differences were observed with respect to PIB-PET and cerebrospinal fluid phospho-tau concentrations in APOE ε4 allele carriers but not in noncarriers. CONCLUSIONS: Bapineuzumab did not improve clinical outcomes in patients with Alzheimer's disease, despite treatment differences in biomarkers observed in APOE ε4 carriers. (Funded by Janssen Alzheimer Immunotherapy and Pfizer; Bapineuzumab 301 and 302 ClinicalTrials.gov numbers, NCT00575055 and NCT00574132, and EudraCT number, 2009-012748-17.).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Antibodies, Monoclonal, Humanized; Apolipoproteins E; Biomarkers; Brain; Cognition; Double-Blind Method; Edema; Female; Humans; Intention to Treat Analysis; Male; Middle Aged; Neuropsychological Tests; Phosphorylation; Positron-Emission Tomography; Severity of Illness Index; tau Proteins; Treatment Failure

Young blood reverses age-related impairments in cognitive function and synaptic plasticity in mice. - Villeda, Saul A; Plambeck, Kristopher E; Middeldorp, Jinte; Castellano, Joseph M; Mosher, Kira I; Luo, Jian; Smith, Lucas K; Bieri, Gregor; Lin, Karin; Berdnik, Daniela; Wabl, Rafael; Udeochu, Joe; et al. (Nat Med, 2014)
As human lifespan increases, a greater fraction of the population is suffering from age-related cognitive impairments, making it important to elucidate a means to combat the effects of aging. Here we report that exposure of an aged animal to young blood can counteract and reverse pre-existing effects of brain aging at the molecular, structural, functional and cognitive level. Genome-wide microarray analysis of heterochronic parabionts--in which circulatory systems of young and aged animals are connected--identified synaptic plasticity-related transcriptional changes in the hippocampus of aged mice. Dendritic spine density of mature neurons increased and synaptic plasticity improved in the hippocampus of aged heterochronic parabionts. At the cognitive level, systemic administration of young blood plasma into aged mice improved age-related cognitive impairments in both contextual fear conditioning and spatial learning and memory. Structural and cognitive enhancements elicited by exposure to young blood are mediated, in part, by activation of the cyclic AMP response element binding protein (Creb) in the aged hippocampus. Our data indicate that exposure of aged mice to young blood late in life is capable of rejuvenating synaptic plasticity and improving cognitive function.
Keywords: Age Factors; Aging; Animals; Blood Transfusion; Blotting, Western; Cell Line; Cognition Disorders; Cyclic AMP Response Element-Binding Protein; DNA Primers; Hippocampus; Immunohistochemistry; Mice; Mice, Inbred C57BL; Microarray Analysis; Neuronal Plasticity; Parabiosis; Polymerase Chain Reaction

Alzheimer's disease risk gene CD33 inhibits microglial uptake of amyloid beta. - Griciuc, Ana; Serrano-Pozo, Alberto; Parrado, Antonio R; Lesinski, Andrea N; Asselin, Caroline N; Mullin, Kristina; Hooli, Basavaraj; Choi, Se Hoon; Hyman, Bradley T; Tanzi, Rudolph E (Neuron, 2013)
The transmembrane protein CD33 is a sialic acid-binding immunoglobulin-like lectin that regulates innate immunity but has no known functions in the brain. We have previously shown that the CD33 gene is a risk factor for Alzheimer's disease (AD). Here, we observed increased expression of CD33 in microglial cells in AD brain. The minor allele of the CD33 SNP rs3865444, which confers protection against AD, was associated with reductions in both CD33 expression and insoluble amyloid beta 42 (Aβ42) levels in AD brain. Furthermore, the numbers of CD33-immunoreactive microglia were positively correlated with insoluble Aβ42 levels and plaque burden in AD brain. CD33 inhibited uptake and clearance of Aβ42 in microglial cell cultures. Finally, brain levels of insoluble Aβ42 as well as amyloid plaque burden were markedly reduced in APP(Swe)/PS1(ΔE9)/CD33(-/-) mice. Therefore, CD33 inactivation mitigates Aβ pathology and CD33 inhibition could represent a novel therapy for AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Case-Control Studies; Disease Models, Animal; Genetic Predisposition to Disease; Humans; Matched-Pair Analysis; Mice; Mice, Inbred C57BL; Mice, Knockout; Mice, Transgenic; Microglia; Polymorphism, Single Nucleotide; Reference Values; RNA, Messenger; Sialic Acid Binding Ig-like Lectin 3

Modeling Alzheimer's disease with iPSCs reveals stress phenotypes associated with intracellular Aβ and differential drug responsiveness. - Kondo, Takayuki; Asai, Masashi; Tsukita, Kayoko; Kutoku, Yumiko; Ohsawa, Yutaka; Sunada, Yoshihide; Imamura, Keiko; Egawa, Naohiro; Yahata, Naoki; Okita, Keisuke; Takahashi, Kazutoshi; Asaka, Isao; et al. (Cell Stem Cell, 2013)
Oligomeric forms of amyloid-β peptide (Aβ) are thought to play a pivotal role in the pathogenesis of Alzheimer's disease (AD), but the mechanism involved is still unclear. Here, we generated induced pluripotent stem cells (iPSCs) from familial and sporadic AD patients and differentiated them into neural cells. Aβ oligomers accumulated in iPSC-derived neurons and astrocytes in cells from patients with a familial amyloid precursor protein (APP)-E693Δ mutation and sporadic AD, leading to endoplasmic reticulum (ER) and oxidative stress. The accumulated Aβ oligomers were not proteolytically resistant, and docosahexaenoic acid (DHA) treatment alleviated the stress responses in the AD neural cells. Differential manifestation of ER stress and DHA responsiveness may help explain variable clinical results obtained with the use of DHA treatment and suggests that DHA may in fact be effective for a subset of patients. It also illustrates how patient-specific iPSCs can be useful for analyzing AD pathogenesis and evaluating drugs.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cell Differentiation; Cerebral Cortex; Docosahexaenoic Acids; Humans; Induced Pluripotent Stem Cells; Intracellular Space; Models, Biological; Mutant Proteins; Neurons; Oxidative Stress; Phenotype; Protein Structure, Quaternary

Demonstrated brain insulin resistance in Alzheimer's disease patients is associated with IGF-1 resistance, IRS-1 dysregulation, and cognitive decline. - Talbot, Konrad; Wang, Hoau-Yan; Kazi, Hala; Han, Li-Ying; Bakshi, Kalindi P; Stucky, Andres; Fuino, Robert L; Kawaguchi, Krista R; Samoyedny, Andrew J; Wilson, Robert S; Arvanitakis, Zoe; Schneider, Julie A; et al. (J Clin Invest, 2012)
While a potential causal factor in Alzheimer's disease (AD), brain insulin resistance has not been demonstrated directly in that disorder. We provide such a demonstration here by showing that the hippocampal formation (HF) and, to a lesser degree, the cerebellar cortex in AD cases without diabetes exhibit markedly reduced responses to insulin signaling in the IR→IRS-1→PI3K signaling pathway with greatly reduced responses to IGF-1 in the IGF-1R→IRS-2→PI3K signaling pathway. Reduced insulin responses were maximal at the level of IRS-1 and were consistently associated with basal elevations in IRS-1 phosphorylated at serine 616 (IRS-1 pS⁶¹⁶) and IRS-1 pS⁶³⁶/⁶³⁹. In the HF, these candidate biomarkers of brain insulin resistance increased commonly and progressively from normal cases to mild cognitively impaired cases to AD cases regardless of diabetes or APOE ε4 status. Levels of IRS-1 pS⁶¹⁶ and IRS-1 pS⁶³⁶/⁶³⁹ and their activated kinases correlated positively with those of oligomeric Aβ plaques and were negatively associated with episodic and working memory, even after adjusting for Aβ plaques, neurofibrillary tangles, and APOE ε4. Brain insulin resistance thus appears to be an early and common feature of AD, a phenomenon accompanied by IGF-1 resistance and closely associated with IRS-1 dysfunction potentially triggered by Aβ oligomers and yet promoting cognitive decline independent of classic AD pathology.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Brain; Cerebellar Cortex; Cognition Disorders; Diabetes Complications; Drug Resistance; Female; Glucose; Hippocampus; Humans; Insulin; Insulin Receptor Substrate Proteins; Insulin Resistance; Insulin-Like Growth Factor I; Male; Middle Aged; Phosphorylation; Phosphoserine; Protein Processing, Post-Translational; Recombinant Proteins; Signal Transduction

An epigenetic blockade of cognitive functions in the neurodegenerating brain. - Gräff, Johannes; Rei, Damien; Guan, Ji-Song; Wang, Wen-Yuan; Seo, Jinsoo; Hennig, Krista M; Nieland, Thomas J F; Fass, Daniel M; Kao, Patricia F; Kahn, Martin; Su, Susan C; Samiei, Alireza; et al. (Nature, 2012)
Cognitive decline is a debilitating feature of most neurodegenerative diseases of the central nervous system, including Alzheimer's disease. The causes leading to such impairment are only poorly understood and effective treatments are slow to emerge. Here we show that cognitive capacities in the neurodegenerating brain are constrained by an epigenetic blockade of gene transcription that is potentially reversible. This blockade is mediated by histone deacetylase 2, which is increased by Alzheimer's-disease-related neurotoxic insults in vitro, in two mouse models of neurodegeneration and in patients with Alzheimer's disease. Histone deacetylase 2 associates with and reduces the histone acetylation of genes important for learning and memory, which show a concomitant decrease in expression. Importantly, reversing the build-up of histone deacetylase 2 by short-hairpin-RNA-mediated knockdown unlocks the repression of these genes, reinstates structural and synaptic plasticity, and abolishes neurodegeneration-associated memory impairments. These findings advocate for the development of selective inhibitors of histone deacetylase 2 and suggest that cognitive capacities following neurodegeneration are not entirely lost, but merely impaired by this epigenetic blockade.
Keywords: Acetylation; Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Epigenesis, Genetic; Gene Expression Regulation; Gene Knockdown Techniques; Hippocampus; Histone Deacetylase 2; Histones; Humans; Hydrogen Peroxide; Memory Disorders; Mice; Neurodegenerative Diseases; Neuronal Plasticity; Peptide Fragments; Phosphorylation; Promoter Regions, Genetic; Receptors, Glucocorticoid; RNA Polymerase II

Neuroinflammation, hyperphosphorylated tau, diffuse amyloid plaques, and down-regulation of the cellular prion protein in air pollution exposed children and young adults. - Calderón-Garcidueñas, Lilian; Kavanaugh, Michael; Block, Michelle; D'Angiulli, Amedeo; Delgado-Chávez, Ricardo; Torres-Jardón, Ricardo; González-Maciel, Angelica; Reynoso-Robles, Rafael; Osnaya, Norma; Villarreal-Calderon, Rodolfo; Guo, Ruixin; Hua, Zhaowei; et al. (J Alzheimers Dis, 2012)
Air pollution exposures have been linked to neuroinflammation and neuropathology. Autopsy samples of the frontal cortex from control (n = 8) and pollution-exposed (n = 35) children and young adults were analyzed by RT-PCR (n = 43) and microarray analysis (n = 12) for gene expression changes in oxidative stress, DNA damage signaling, NFκB signaling, inflammation, and neurodegeneration pathways. The effect of apolipoprotein E (APOE) genotype on the presence of protein aggregates associated with Alzheimer's disease (AD) pathology was also explored. Exposed urbanites displayed differential (>2-fold) regulation of 134 genes. Forty percent exhibited tau hyperphosphorylation with pre-tangle material and 51% had amyloid-β (Aβ) diffuse plaques compared with 0% in controls. APOE4 carriers had greater hyperphosphorylated tau and diffuse Aβ plaques versus E3 carriers (Q = 7.82, p = 0.005). Upregulated gene network clusters included IL1, NFκB, TNF, IFN, and TLRs. A 15-fold frontal down-regulation of the prion-related protein (PrP(C)) was seen in highly exposed subjects. The down-regulation of the PrP(C) is critical given its important roles for neuroprotection, neurodegeneration, and mood disorder states. Elevation of indices of neuroinflammation and oxidative stress, down-regulation of the PrP(C) and AD-associated pathology are present in young megacity residents. The inducible regulation of gene expression suggests they are evolving different mechanisms in an attempt to cope with the constant state of inflammation and oxidative stress related to their environmental exposures. Together, these data support a role for air pollution in CNS damage and its impact upon the developing brain and the potential etiology of AD and mood disorders.
Keywords: Adolescent; Adult; Age Factors; Air Pollution; Child; Child, Preschool; Cohort Studies; Down-Regulation; Encephalitis; Female; Frontal Lobe; Gene Regulatory Networks; Humans; Infant; Male; Mexico; Phosphorylation; Plaque, Amyloid; Prions; tau Proteins; Young Adult

An operational approach to National Institute on Aging-Alzheimer's Association criteria for preclinical Alzheimer disease. - Jack, Clifford R; Knopman, David S; Weigand, Stephen D; Wiste, Heather J; Vemuri, Prashanthi; Lowe, Val; Kantarci, Kejal; Gunter, Jeffrey L; Senjem, Matthew L; Ivnik, Robert J; Roberts, Rosebud O; Rocca, Walter A; et al. (Ann Neurol, 2012)
OBJECTIVE: A workgroup commissioned by the Alzheimer's Association (AA) and the National Institute on Aging (NIA) recently published research criteria for preclinical Alzheimer disease (AD). We performed a preliminary assessment of these guidelines. METHODS: We employed Pittsburgh compound B positron emission tomography (PET) imaging as our biomarker of cerebral amyloidosis, and (18) fluorodeoxyglucose PET imaging and hippocampal volume as biomarkers of neurodegeneration. A group of 42 clinically diagnosed AD subjects was used to create imaging biomarker cutpoints. A group of 450 cognitively normal (CN) subjects from a population-based sample was used to develop cognitive cutpoints and to assess population frequencies of the different preclinical AD stages using different cutpoint criteria. RESULTS: The new criteria subdivide the preclinical phase of AD into stages 1 to 3. To classify our CN subjects, 2 additional categories were needed. Stage 0 denotes subjects with normal AD biomarkers and no evidence of subtle cognitive impairment. Suspected non-AD pathophysiology (SNAP) denotes subjects with normal amyloid PET imaging, but abnormal neurodegeneration biomarker studies. At fixed cutpoints corresponding to 90% sensitivity for diagnosing AD and the 10th percentile of CN cognitive scores, 43% of our sample was classified as stage 0, 16% stage 1, 12 % stage 2, 3% stage 3, and 23% SNAP. INTERPRETATION: This cross-sectional evaluation of the NIA-AA criteria for preclinical AD indicates that the 1-3 staging criteria coupled with stage 0 and SNAP categories classify 97% of CN subjects from a population-based sample, leaving only 3% unclassified. Future longitudinal validation of the criteria will be important.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Aniline Compounds; Biomarkers; Brain; Cognition Disorders; Disease Progression; Female; Fluorodeoxyglucose F18; Humans; Longitudinal Studies; Male; Mental Status Schedule; National Institute on Aging (U.S.); Neuropsychological Tests; Positron-Emission Tomography; Thiazoles; United States

Propagation of tau pathology in a model of early Alzheimer's disease. - de Calignon, Alix; Polydoro, Manuela; Suárez-Calvet, Marc; William, Christopher; Adamowicz, David H; Kopeikina, Kathy J; Pitstick, Rose; Sahara, Naruhiko; Ashe, Karen H; Carlson, George A; Spires-Jones, Tara L; Hyman, Bradley T (Neuron, 2012)
Neurofibrillary tangles advance from layer II of the entorhinal cortex (EC-II) toward limbic and association cortices as Alzheimer's disease evolves. However, the mechanism involved in this hierarchical pattern of disease progression is unknown. We describe a transgenic mouse model in which overexpression of human tau P301L is restricted to EC-II. Tau pathology progresses from EC transgene-expressing neurons to neurons without detectable transgene expression, first to EC neighboring cells, followed by propagation to neurons downstream in the synaptic circuit such as the dentate gyrus, CA fields of the hippocampus, and cingulate cortex. Human tau protein spreads to these regions and coaggregates with endogenous mouse tau. With age, synaptic degeneration occurs in the entorhinal target zone and EC neurons are lost. These data suggest that a sequence of progressive misfolding of tau proteins, circuit-based transfer to new cell populations, and deafferentation induced degeneration are part of a process of tau-induced neurodegeneration.
Keywords: Age Factors; Alzheimer Disease; Animals; Disease Models, Animal; Disease Progression; Entorhinal Cortex; Epitopes; Gene Expression Regulation; Glial Fibrillary Acidic Protein; Gliosis; Hippocampus; Humans; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Nerve Degeneration; Neurofibrillary Tangles; Neurons; RNA, Messenger; Serine; tau Proteins; Tauopathies

Reduction of hippocampal hyperactivity improves cognition in amnestic mild cognitive impairment. - Bakker, Arnold; Krauss, Gregory L; Albert, Marilyn S; Speck, Caroline L; Jones, Lauren R; Stark, Craig E; Yassa, Michael A; Bassett, Susan S; Shelton, Amy L; Gallagher, Michela (Neuron, 2012)
Elevated hippocampal activation is observed in conditions that confer risk for Alzheimer's disease, including amnestic mild cognitive impairment (aMCI). Studies in relevant animal models have indicated that overactivity in selective hippocampal circuits contributes to cognitive impairment. Here, we tested the effect of reducing hippocampal activation in aMCI. Under placebo treatment, hippocampal activation in the dentate gyrus/CA3 was elevated in aMCI patients compared to a healthy control group. By using a low dose of the antiepileptic levetiracetam hippocampal activation in aMCI was reduced to a level that did not differ from the control group. Compared to aMCI memory performance under placebo, performance in the scanning task was significantly improved under drug treatment. Contrary to the view that greater hippocampal activation might serve a beneficial function, these results support the view that increased hippocampal activation in aMCI is a dysfunctional condition and that targeting excess hippocampal activity has therapeutic potential.
Keywords: Aged; Aged, 80 and over; Amnesia; Brain Mapping; Case-Control Studies; Choice Behavior; Double-Blind Method; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Mild Cognitive Impairment; Neuropsychological Tests; Nootropic Agents; Oxygen; Photic Stimulation; Piracetam; Statistics as Topic

Anti-aβ therapeutics in Alzheimer's disease: the need for a paradigm shift. - Golde, Todd E; Schneider, Lon S; Koo, Edward H (Neuron, 2011)
Most current Alzheimer's disease (AD) therapies in advanced phases of development target amyloid β-peptide (Aβ) production, aggregation, or accumulation. Translational models suggest that anti-Aβ therapies may be highly effective if tested as agents to prevent or delay development of the disease or as therapies for asymptomatic patients with very early signs of AD pathology. However, anti-Aβ therapeutics are currently being tested in symptomatic patients where they are likely to be much less effective or ineffective. The lack of alignment between human clinical studies and preclinical studies, together with predictions about optimal trial design based on our understanding of the initiating role of Aβ aggregates in AD, has created a treatment versus prevention dilemma. In this perspective, we discuss why it is imperative to resolve this dilemma and suggest ways for moving forward in the hopes of enhancing the development of truly effective AD therapeutics.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Biomarkers; Clinical Trials as Topic; Disease Progression; Health Services Needs and Demand; Humans; Translational Medical Research

Caspase signalling controls microglia activation and neurotoxicity. - Burguillos, Miguel A; Deierborg, Tomas; Kavanagh, Edel; Persson, Annette; Hajji, Nabil; Garcia-Quintanilla, Albert; Cano, Josefina; Brundin, Patrik; Englund, Elisabet; Venero, Jose L; Joseph, Bertrand (Nature, 2011)
Activation of microglia and inflammation-mediated neurotoxicity are suggested to play a decisive role in the pathogenesis of several neurodegenerative disorders. Activated microglia release pro-inflammatory factors that may be neurotoxic. Here we show that the orderly activation of caspase-8 and caspase-3/7, known executioners of apoptotic cell death, regulate microglia activation through a protein kinase C (PKC)-δ-dependent pathway. We find that stimulation of microglia with various inflammogens activates caspase-8 and caspase-3/7 in microglia without triggering cell death in vitro and in vivo. Knockdown or chemical inhibition of each of these caspases hindered microglia activation and consequently reduced neurotoxicity. We observe that these caspases are activated in microglia in the ventral mesencephalon of Parkinson's disease (PD) and the frontal cortex of individuals with Alzheimer's disease (AD). Taken together, we show that caspase-8 and caspase-3/7 are involved in regulating microglia activation. We conclude that inhibition of these caspases could be neuroprotective by targeting the microglia rather than the neurons themselves.
Keywords: Alzheimer Disease; Animals; Caspase 3; Caspase 7; Caspase 8; Caspase Inhibitors; Caspases; Cell Death; Cells, Cultured; Dopamine; Enzyme Activation; Frontal Lobe; Gene Knockdown Techniques; Humans; Lipopolysaccharides; Mice; Microglia; Neostriatum; Neurotoxicity Syndromes; Parkinson Disease; Protein Kinase C-delta; Rats; Signal Transduction; Substantia Nigra; Toll-Like Receptor 4

The diagnosis of dementia due to Alzheimer's disease: recommendations from the National Institute on Aging-Alzheimer's Association workgroups on diagnostic guidelines for Alzheimer's disease. - McKhann, Guy M; Knopman, David S; Chertkow, Howard; Hyman, Bradley T; Jack, Clifford R; Kawas, Claudia H; Klunk, William E; Koroshetz, Walter J; Manly, Jennifer J; Mayeux, Richard; Mohs, Richard C; Morris, John C; et al. (Alzheimers Dement, 2011)
The National Institute on Aging and the Alzheimer's Association charged a workgroup with the task of revising the 1984 criteria for Alzheimer's disease (AD) dementia. The workgroup sought to ensure that the revised criteria would be flexible enough to be used by both general healthcare providers without access to neuropsychological testing, advanced imaging, and cerebrospinal fluid measures, and specialized investigators involved in research or in clinical trial studies who would have these tools available. We present criteria for all-cause dementia and for AD dementia. We retained the general framework of probable AD dementia from the 1984 criteria. On the basis of the past 27 years of experience, we made several changes in the clinical criteria for the diagnosis. We also retained the term possible AD dementia, but redefined it in a manner more focused than before. Biomarker evidence was also integrated into the diagnostic formulations for probable and possible AD dementia for use in research settings. The core clinical criteria for AD dementia will continue to be the cornerstone of the diagnosis in clinical practice, but biomarker evidence is expected to enhance the pathophysiological specificity of the diagnosis of AD dementia. Much work lies ahead for validating the biomarker diagnosis of AD dementia.
Keywords: Alzheimer Disease; Biomarkers; Diagnosis, Differential; Diagnostic Imaging; Disease Progression; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; Societies, Medical; United States

The diagnosis of mild cognitive impairment due to Alzheimer's disease: recommendations from the National Institute on Aging-Alzheimer's Association workgroups on diagnostic guidelines for Alzheimer's disease. - Albert, Marilyn S; DeKosky, Steven T; Dickson, Dennis; Dubois, Bruno; Feldman, Howard H; Fox, Nick C; Gamst, Anthony; Holtzman, David M; Jagust, William J; Petersen, Ronald C; Snyder, Peter J; Carrillo, Maria C; et al. (Alzheimers Dement, 2011)
The National Institute on Aging and the Alzheimer's Association charged a workgroup with the task of developing criteria for the symptomatic predementia phase of Alzheimer's disease (AD), referred to in this article as mild cognitive impairment due to AD. The workgroup developed the following two sets of criteria: (1) core clinical criteria that could be used by healthcare providers without access to advanced imaging techniques or cerebrospinal fluid analysis, and (2) research criteria that could be used in clinical research settings, including clinical trials. The second set of criteria incorporate the use of biomarkers based on imaging and cerebrospinal fluid measures. The final set of criteria for mild cognitive impairment due to AD has four levels of certainty, depending on the presence and nature of the biomarker findings. Considerable work is needed to validate the criteria that use biomarkers and to standardize biomarker analysis for use in community settings.
Keywords: Alzheimer Disease; Biomarkers; Cognition Disorders; Diagnosis, Differential; Diagnostic Imaging; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; Societies, Medical; United States

Neuronal activity regulates the regional vulnerability to amyloid-β deposition. - Bero, Adam W; Yan, Ping; Roh, Jee Hoon; Cirrito, John R; Stewart, Floy R; Raichle, Marcus E; Lee, Jin-Moo; Holtzman, David M (Nat Neurosci, 2011)
Amyloid-β (Aβ) plaque deposition in specific brain regions is a pathological hallmark of Alzheimer's disease. However, the mechanism underlying the regional vulnerability to Aβ deposition in Alzheimer's disease is unknown. Herein, we provide evidence that endogenous neuronal activity regulates the regional concentration of interstitial fluid (ISF) Aβ, which drives local Aβ aggregation. Using in vivo microdialysis, we show that ISF Aβ concentrations in several brain regions of APP transgenic mice before plaque deposition were commensurate with the degree of subsequent plaque deposition and with the concentration of lactate, a marker of neuronal activity. Furthermore, unilateral vibrissal stimulation increased ISF Aβ, and unilateral vibrissal deprivation decreased ISF Aβ and lactate, in contralateral barrel cortex. Long-term unilateral vibrissal deprivation decreased amyloid plaque formation and growth. Our results suggest a mechanism to account for the vulnerability of specific brain regions to Aβ deposition in Alzheimer's disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cerebral Cortex; Disease Models, Animal; Extracellular Fluid; Female; Lactic Acid; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microdialysis; Neurons; Plaque, Amyloid; Sensory Deprivation; Somatosensory Cortex

Pathogenic protein seeding in Alzheimer disease and other neurodegenerative disorders. - Jucker, Mathias; Walker, Lary C (Ann Neurol, 2011)
The misfolding and aggregation of specific proteins is a seminal occurrence in a remarkable variety of neurodegenerative disorders. In Alzheimer disease (the most prevalent cerebral proteopathy), the two principal aggregating proteins are β-amyloid (Aβ) and tau. The abnormal assemblies formed by conformational variants of these proteins range in size from small oligomers to the characteristic lesions that are visible by optical microscopy, such as senile plaques and neurofibrillary tangles. Pathologic similarities with prion disease suggest that the formation and spread of these proteinaceous lesions might involve a common molecular mechanism-corruptive protein templating. Experimentally, cerebral β-amyloidosis can be exogenously induced by exposure to dilute brain extracts containing aggregated Aβ seeds. The amyloid-inducing agent probably is Aβ itself, in a conformation generated most effectively in the living brain. Once initiated, Aβ lesions proliferate within and among brain regions. The induction process is governed by the structural and biochemical nature of the Aβ seed, as well as the attributes of the host, reminiscent of pathogenically variant prion strains. The concept of prionlike induction and spreading of pathogenic proteins recently has been expanded to include aggregates of tau, α-synuclein, huntingtin, superoxide dismutase-1, and TDP-43, which characterize such human neurodegenerative disorders as frontotemporal lobar degeneration, Parkinson/Lewy body disease, Huntington disease, and amyotrophic lateral sclerosis. Our recent finding that the most effective Aβ seeds are small and soluble intensifies the search in bodily fluids for misfolded protein seeds that are upstream in the proteopathic cascade, and thus could serve as predictive diagnostics and the targets of early, mechanism-based interventions. Establishing the clinical implications of corruptive protein templating will require further mechanistic and epidemiologic investigations. However, the theory that many chronic neurodegenerative diseases can originate and progress via the seeded corruption of misfolded proteins has the potential to unify experimental and translational approaches to these increasingly prevalent disorders.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; DNA-Binding Proteins; Humans; Neurodegenerative Diseases; Prions; Proteins; tau Proteins

Report of the task force on designing clinical trials in early (predementia) AD. - Aisen, P S; Andrieu, S; Sampaio, C; Carrillo, M; Khachaturian, Z S; Dubois, B; Feldman, H H; Petersen, R C; Siemers, E; Doody, R S; Hendrix, S B; Grundman, M; et al. (Neurology, 2011)
BACKGROUND: A large number of promising candidate disease-modifying treatments for Alzheimer disease (AD) continue to advance into phase II and phase III testing. However, most completed trials have failed to demonstrate efficacy, and there is growing concern that methodologic difficulties may contribute to these clinical trial failures. The optimal time to intervene with such treatments is probably in the years prior to the onset of dementia, before the neuropathology has progressed to the advanced stage corresponding to clinical dementia. METHOD: An international task force of individuals from academia, industry, nonprofit foundations, and regulatory agencies was convened to discuss optimal trial design in early (predementia) AD. RESULTS: General consensus was reached on key principles involving the scope of the AD diagnosis, the selection of subjects for trials, outcome measures, and analytical methods. CONCLUSION: A consensus has been achieved in support of the testing of candidate treatments in the early (predementia) AD population.
Keywords: Advisory Committees; Alzheimer Disease; Amyloidogenic Proteins; Biomarkers; Clinical Trials as Topic; Cognition; Consensus; Disease Progression; Drug Industry; Early Diagnosis; Europe; Humans; Indans; International Cooperation; Nootropic Agents; Outcome Assessment (Health Care); Patient Selection; Piperidines; Positron-Emission Tomography; Research Design; Treatment Outcome; United States; United States Food and Drug Administration; Vitamin E

Soluble amyloid beta-protein dimers isolated from Alzheimer cortex directly induce Tau hyperphosphorylation and neuritic degeneration. - Jin, Ming; Shepardson, Nina; Yang, Ting; Chen, Gang; Walsh, Dominic; Selkoe, Dennis J (Proc Natl Acad Sci U S A, 2011)
Alzheimer disease is a major cause of cognitive failure, and a pathogenically related but more subtle process accounts for many cases of mild memory symptoms in older humans. Insoluble fibrillar plaques of amyloid β-proteins (Aβ) and neurofibrillary deposits of hyperphosphorylated tau proteins are the diagnostic lesions of AD, but their temporal mechanistic relationship has long been debated. The recent recognition that small, diffusible oligomers may be the principal bioactive form of Aβ raises the key question of whether these are sufficient to initiate cytoskeletal change and neurite degeneration. A few studies have examined the effects of oligomers of synthetic Aβ peptides of one defined length at supraphysiological concentrations, but the existence of such assemblies in the AD brain is not established. Here, we isolated Aβ dimers, the most abundant form of soluble oligomer detectable in the human brain, from the cortices of typical AD subjects and found that at subnanomolar concentrations, they first induced hyperphosphorylation of tau at AD-relevant epitopes in hippocampal neurons and then disrupted the microtubule cytoskeleton and caused neuritic degeneration, all in the absence of amyloid fibrils. Application of pure, synthetic dimers confirmed the effects of the natural AD dimers, although the former were far less potent. Knocking down endogenous tau fully prevented the neuritic changes, whereas overexpressing human tau accelerated them. Coadministering Aβ N-terminal antibodies neutralized the cytoskeletal disruption. We conclude that natural dimers isolated from the AD brain are sufficient to potently induce AD-type tau phosphorylation and then neuritic dystrophy, but passive immunotherapy mitigates this.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Blotting, Western; Chromatography, Gel; Dimerization; Genetic Vectors; Hippocampus; Humans; Immunohistochemistry; Immunoprecipitation; In Situ Nick-End Labeling; Lentivirus; Microscopy, Confocal; Microtubules; Neurites; Phosphorylation; Rats; Rats, Sprague-Dawley; tau Proteins

Stages of the pathologic process in Alzheimer disease: age categories from 1 to 100 years. - Braak, Heiko; Thal, Dietmar R; Ghebremedhin, Estifanos; Del Tredici, Kelly (J Neuropathol Exp Neurol, 2011)
Two thousand three hundred and thirty two nonselected brains from 1- to 100-year-old individuals were examined using immunocytochemistry (AT8) and Gallyas silver staining for abnormal tau; immunocytochemistry (4G8) and Campbell-Switzer staining were used for the detection ofβ-amyloid. A total of 342 cases was negative in the Gallyas stain but when restaged for AT8 only 10 were immunonegative. Fifty-eight cases had subcortical tau predominantly in the locus coeruleus, but there was no abnormal cortical tau (subcortical Stages a-c). Cortical involvement (abnormal tau in neurites) was identified first in the transentorhinal region (Stage 1a, 38 cases). Transentorhinal pyramidal cells displayed pretangle material (Stage 1b, 236 cases). Pretangles gradually became argyrophilic neurofibrillary tangles (NFTs) that progressed in parallel with NFT Stages I to VI. Pretangles restricted to subcortical sites were seen chiefly at younger ages. Of the total cases, 1,031 (44.2%) had β-amyloid plaques. The first plaques occurred in the neocortex after the onset of tauopathy in the brainstem. Plaques generally developed in the 40s in 4% of all cases, culminating in their tenth decade (75%). β-amyloid plaques and NFTs were significantly correlated (p < 0.0001). These data suggest that tauopathy associated with sporadic Alzheimer disease may begin earlier than previously thought and possibly in the lower brainstem rather than in the transentorhinal region.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Brain; Child; Child, Preschool; Cohort Studies; Disease Progression; Female; Humans; Infant; Male; Middle Aged; Neurofibrillary Tangles; Neurons; Silver Staining; Statistics, Nonparametric; tau Proteins; Young Adult

Vascular risk factors promote conversion from mild cognitive impairment to Alzheimer disease. - Li, J; Wang, Y J; Zhang, M; Xu, Z Q; Gao, C Y; Fang, C Q; Yan, J C; Zhou, H D (Neurology, 2011)
OBJECTIVE: Growing evidence suggests that vascular risk factors (VRF) contribute to cognitive decline. The aim of this study was to investigate the impact of VRF on the conversion from mild cognitive impairment (MCI) to Alzheimer disease (AD) dementia. METHODS: A total of 837 subjects with MCI were enrolled at baseline and followed up annually for 5 years. The incidence of AD dementia was investigated. A mixed random effects regression model was used to analyze the association between VRF and the progression of MCI assessed with Mini-Mental State Examination and instrumental Activities of Daily Living. Cox proportional hazard models were used to identify the association between VRF and dementia conversion, and to examine whether treatment of VRF can prevent dementia conversion. RESULTS: At the end of the follow-up, 298 subjects converted to AD dementia, while 352 remained MCI. Subjects with VRF had a faster progression in cognition and function relative to subjects without. VRF including hypertension, diabetes, cerebrovascular diseases, and hypercholesterolemia increased the risk of dementia conversion. Those subjects with MCI in whom all VRF were treated had a lower risk of dementia than those who had some VRF treated. Treatment of individual VRF including hypertension, diabetes, and hypercholesterolemia was associated with the reduced risk of AD conversion. CONCLUSION: VRF increased the risk of incident AD dementia. Treatment of VRF was associated with a reduced risk of incident AD dementia. Although our findings are observational, they suggest active intervention for VRF might reduce progression in MCI to AD dementia.
Keywords: Aged; Alzheimer Disease; Cerebrovascular Disorders; Cognition Disorders; Disease Progression; Female; Humans; Incidence; Longitudinal Studies; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptides; Regression Analysis; Residence Characteristics; Retrospective Studies; Risk Factors; Statistics, Nonparametric

Alzheimer's Disease Neuroimaging Initiative (ADNI): clinical characterization. - Petersen, R C; Aisen, P S; Beckett, L A; Donohue, M C; Gamst, A C; Harvey, D J; Jack, C R; Jagust, W J; Shaw, L M; Toga, A W; Trojanowski, J Q; Weiner, M W (Neurology, 2010)
BACKGROUND: Neuroimaging measures and chemical biomarkers may be important indices of clinical progression in normal aging and mild cognitive impairment (MCI) and need to be evaluated longitudinally. OBJECTIVE: To characterize cross-sectionally and longitudinally clinical measures in normal controls, subjects with MCI, and subjects with mild Alzheimer disease (AD) to enable the assessment of the utility of neuroimaging and chemical biomarker measures. METHODS: A total of 819 subjects (229 cognitively normal, 398 with MCI, and 192 with AD) were enrolled at baseline and followed for 12 months using standard cognitive and functional measures typical of clinical trials. RESULTS: The subjects with MCI were more memory impaired than the cognitively normal subjects but not as impaired as the subjects with AD. Nonmemory cognitive measures were only minimally impaired in the subjects with MCI. The subjects with MCI progressed to dementia in 12 months at a rate of 16.5% per year. Approximately 50% of the subjects with MCI were on antidementia therapies. There was minimal movement on the Alzheimer's Disease Assessment Scale-Cognitive Subscale for the normal control subjects, slight movement for the subjects with MCI of 1.1, and a modest change for the subjects with AD of 4.3. Baseline CSF measures of Abeta-42 separated the 3 groups as expected and successfully predicted the 12-month change in cognitive measures. CONCLUSION: The Alzheimer's Disease Neuroimaging Initiative has successfully recruited cohorts of cognitively normal subjects, subjects with mild cognitive impairment (MCI), and subjects with Alzheimer disease with anticipated baseline characteristics. The 12-month progression rate of MCI was as predicted, and the CSF measures heralded progression of clinical measures over 12 months.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Cross-Sectional Studies; Diagnostic Imaging; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Middle Aged

Gamma-secretase activating protein is a therapeutic target for Alzheimer's disease. - He, Gen; Luo, Wenjie; Li, Peng; Remmers, Christine; Netzer, William J; Hendrick, Joseph; Bettayeb, Karima; Flajolet, Marc; Gorelick, Fred; Wennogle, Lawrence P; Greengard, Paul (Nature, 2010)
Accumulation of neurotoxic amyloid-beta is a major hallmark of Alzheimer's disease. Formation of amyloid-beta is catalysed by gamma-secretase, a protease with numerous substrates. Little is known about the molecular mechanisms that confer substrate specificity on this potentially promiscuous enzyme. Knowledge of the mechanisms underlying its selectivity is critical for the development of clinically effective gamma-secretase inhibitors that can reduce amyloid-beta formation without impairing cleavage of other gamma-secretase substrates, especially Notch, which is essential for normal biological functions. Here we report the discovery of a novel gamma-secretase activating protein (GSAP) that drastically and selectively increases amyloid-beta production through a mechanism involving its interactions with both gamma-secretase and its substrate, the amyloid precursor protein carboxy-terminal fragment (APP-CTF). GSAP does not interact with Notch, nor does it affect its cleavage. Recombinant GSAP stimulates amyloid-beta production in vitro. Reducing GSAP concentrations in cell lines decreases amyloid-beta concentrations. Knockdown of GSAP in a mouse model of Alzheimer's disease reduces levels of amyloid-beta and plaque development. GSAP represents a type of gamma-secretase regulator that directs enzyme specificity by interacting with a specific substrate. We demonstrate that imatinib, an anticancer drug previously found to inhibit amyloid-beta formation without affecting Notch cleavage, achieves its amyloid-beta-lowering effect by preventing GSAP interaction with the gamma-secretase substrate, APP-CTF. Thus, GSAP can serve as an amyloid-beta-lowering therapeutic target without affecting other key functions of gamma-secretase.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Benzamides; Cell Line; Disease Models, Animal; Gene Knockdown Techniques; Humans; Imatinib Mesylate; Mice; Peptide Fragments; Piperazines; Proteins; Pyrimidines; Receptor, Notch1; RNA Interference

Memory impairment in transgenic Alzheimer mice requires cellular prion protein. - Gimbel, David A; Nygaard, Haakon B; Coffey, Erin E; Gunther, Erik C; Laurén, Juha; Gimbel, Zachary A; Strittmatter, Stephen M (J Neurosci, 2010)
Soluble oligomers of the amyloid-beta (Abeta) peptide are thought to play a key role in the pathophysiology of Alzheimer's disease (AD). Recently, we reported that synthetic Abeta oligomers bind to cellular prion protein (PrP(C)) and that this interaction is required for suppression of synaptic plasticity in hippocampal slices by oligomeric Abeta peptide. We hypothesized that PrP(C) is essential for the ability of brain-derived Abeta to suppress cognitive function. Here, we crossed familial AD transgenes encoding APPswe and PSen1DeltaE9 into Prnp-/- mice to examine the necessity of PrP(C) for AD-related phenotypes. Neither APP expression nor Abeta level is altered by PrP(C) absence in this transgenic AD model, and astrogliosis is unchanged. However, deletion of PrP(C) expression rescues 5-HT axonal degeneration, loss of synaptic markers, and early death in APPswe/PSen1DeltaE9 transgenic mice. The AD transgenic mice with intact PrP(C) expression exhibit deficits in spatial learning and memory. Mice lacking PrP(C), but containing Abeta plaque derived from APPswe/PSen1DeltaE9 transgenes, show no detectable impairment of spatial learning and memory. Thus, deletion of PrP(C) expression dissociates Abeta accumulation from behavioral impairment in these AD mice, with the cognitive deficits selectively requiring PrP(C).
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Avoidance Learning; Brain; Disease Models, Animal; Maze Learning; Memory; Mice; Mice, Inbred C57BL; Mice, Transgenic; Nerve Degeneration; Presenilin-1; PrPC Proteins; Random Allocation; Serotonin; Survival Analysis